Alzheimer's disease-related cortical proteins modify the association of brain insulin signaling with cognitive decline. - Tong, Han; Petyuk, Vladislav A; Sendtner, Michael; Sood, Ajay; Bennett, David A; Capuano, Ana W; Arvanitakis, Zoe (J Alzheimers Dis, 2025)
BackgroundBrain insulin signaling has been associated with both Alzheimer's disease (AD) pathology and cognitive decline, but the mechanisms remain unclear.ObjectiveTo examine whether AD-related cortically-expressed proteins modify the association of brain insulin signaling and cognitive decline.MethodsParticipants included 116 autopsied members of the Religious Orders Study (58 with diabetes matched to 58 without, by age at death, sex, and education) who had both postmortem brain (prefrontal cortex) insulin signaling (by ELISA and immunohistochemistry, including RAC-alpha serine/threonine-protein kinase or AKT1) and AD-related cortical protein measurements. Levels of five AD-related proteins including insulin-like growth factor-binding protein-5 (IGFBP-5) and inositol-tetrakisphosphate 1-kinase (ITPK1) were measured using quantitative proteomics. We conducted adjusted linear mixed model analyses to examine associations of insulin signaling measures and AD-related proteins with longitudinally assessed cognitive function.ResultsHigher levels of IGFBP-5 and lower levels of ITPK1 were each associated with higher levels of AKT1 phosphorylation (pTAKT1 /total AKT1). Additionally, higher levels of AKT1 phosphorylation were associated with faster decline in global cognition and most cognitive domains. IGFBP-5 partially mediated the association of AKT1 phosphorylation with the decline rate of global cognition and cognitive domains including perceptual speed and visuospatial abilities. Further, ITPK1 had an interaction with AKT1 phosphorylation on decline of global cognition and domains including episodic memory, perceptual speed, and visuospatial abilities.ConclusionsAD-related proteins IGFBP-5 and ITPK1 are each associated with insulin signaling AKT1 phosphorylation in the postmortem human brain. Moreover, IGFBP-5 mediates, while ITPK1 moderates, the association between AKT1 phosphorylation and late-life cognitive decline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cognitive Dysfunction; Female; Humans; Insulin; Insulin-Like Growth Factor Binding Protein 5; Male; Phosphorylation; Proto-Oncogene Proteins c-akt; Signal Transduction

Impact of obesity on neuropsychiatric symptoms in Alzheimer's disease: Insights from the ADNI cohort. - Wang, Shuoshi; Ni, Jingnian; Wei, Mingqing; Li, Ting; Shi, Jing; Tian, Jinzhou (J Alzheimers Dis, 2025)
BackgroundObesity is a major global health issue linked to increased risks of dementia, including Alzheimer's disease (AD). While the association between obesity and neuropsychiatric symptoms (NPS) in AD remains underexplored, identifying these links could aid in weight management in AD patients.ObjectiveThis study investigates the relationship between body mass index (BMI) and NPS in AD dementia patients, focusing on the potential mediating role of systemic inflammation.MethodsWe employed Generalized Additive Models (GAMs) to explore the relationship between BMI and NPS, as measured by the Neuropsychiatric Inventory Questionnaire (NPI-Q). Participants were classified into ideal, overweight, and obese groups based on WHO criteria. Longitudinal analyses assessed the trajectory of NPI-Q scores in different groups over a one-year follow-up.ResultsBMI significantly affects NPI-Q total scores and specific symptoms, including delusions, hallucinations, agitation/aggression, elation/euphoria, disinhibition, irritability/lability, aberrant motor behavior, nighttime disturbances, and appetite/eating disturbances. Obese patients exhibited higher NPI-Q total scores and greater severity in symptoms such as hallucinations, agitation/aggression, elation/euphoria, apathy/indifference, disinhibition, aberrant motor behavior, and nighttime disturbances. Additionally, CRP and complement C3 were identified as mediators in the relationship between obesity and NPS, highlighting the role of systemic inflammation.ConclusionsThis study demonstrates that obesity is associated with a heightened burden of NPS in AD dementia patients. The identification of CRP and complement C3 as mediators suggests inflammation plays a crucial role in the association between obesity and NPS. These findings underscore the importance of addressing obesity and its inflammatory consequences in managing NPS among this vulnerable population.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Body Mass Index; Cohort Studies; Female; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Obesity

Acute Hyperglycemia Induced by Hyperglycemic Clamp Affects Plasma Amyloid-β in Type 2 Diabetes. - Rolandsson, Olov; Tornevi, Andreas; Steneberg, Pär; Edlund, Helena; Olsson, Tommy; Andreasson, Ulf; Zetterberg, Henrik; Blennow, Kaj (J Alzheimers Dis, 2024)
BACKGROUND: Individuals with type 2 diabetes (T2D) have an increased risk of cognitive symptoms and Alzheimer's disease (AD). Mis-metabolism with aggregation of amyloid-β peptides (Aβ) play a key role in AD pathophysiology. Therefore, human studies on Aβ metabolism and T2D are warranted. OBJECTIVE: The objective of this study was to examine whether acute hyperglycemia affects plasma Aβ1-40 and Aβ1-42 concentrations in individuals with T2D and matched controls. METHODS: Ten participants with T2D and 11 controls (median age, 69 years; range, 66-72 years) underwent hyperglycemic clamp and placebo clamp (saline infusion) in a randomized order, each lasting 4 hours. Aβ1-40, Aβ1-42, and insulin-degrading enzyme (IDE) plasma concentrations were measured in blood samples taken at 0 and 4 hours of each clamp. Linear mixed-effect regression models were used to evaluate the 4-hour changes in Aβ1-40 and Aβ1-42 concentrations, adjusting for body mass index, estimated glomerular filtration rate, and 4-hour change in insulin concentration. RESULTS: At baseline, Aβ1-40 and Aβ1-42 concentrations did not differ between the two groups. During the hyperglycemic clamp, Aβ decreased in the control group, compared to the placebo clamp (Aβ1-40: p = 0.034, Aβ1-42: p = 0.020), IDE increased (p = 0.016) during the hyperglycemic clamp, whereas no significant changes in either Aβ or IDE was noted in the T2D group. CONCLUSIONS: Clamp-induced hyperglycemia was associated with increased IDE levels and enhanced Aβ40 and Aβ42 clearance in controls, but not in individuals with T2D. We hypothesize that insulin-degrading enzyme was inhibited during hyperglycemic conditions in people with T2D.
Keywords: Aged; Amyloid beta-Peptides; Blood Glucose; Diabetes Mellitus, Type 2; Female; Glucose Clamp Technique; Humans; Hyperglycemia; Insulysin; Male; Peptide Fragments

Amnestic Syndrome in Memory Clinics: Similar Morphological Brain Patterns in Older Adults with and without Alzheimer's Disease. - Lalive, Hadrien M; Griffa, Alessandra; Carlier, Sabrina; Nasuti, Mirco; Di Noto, Tommaso; Maréchal, Bénédicte; Rouaud, Olivier; Allali, Gilles (J Alzheimers Dis, 2024)
BACKGROUND: Amnestic syndrome of the hippocampal type (ASHT) in Memory Clinics is a presentation common to Alzheimer's disease (AD). However, ASHT can be found in other neurodegenerative disorders. OBJECTIVE: To compare brain morphometry including hippocampal volumes between amnestic older adults with and without AD pathology and investigate their relationship with memory performance and cerebrospinal fluid (CSF) biomarkers. METHODS: Brain morphometry of 92 consecutive patients (72.5±6.8 years old; 39% female) with Free and Cued Selective Recall Reminding Test (FCSRT) total recall < 40/48 was assessed with an automated algorithm and compared between AD and non-AD patients, as defined by CSF biomarkers. RESULTS: AD and non-AD patients presented comparable brain morphology. Total recall was associated to hippocampal volume irrespectively from AD pathology. CONCLUSIONS: Brain morphometry, including hippocampal volumes, is similar between AD and non-AD older adults with ASHT evaluated in a Memory Clinic, underlying the importance of using molecular biomarkers for the diagnosis of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amnesia; Amyloid beta-Peptides; Biomarkers; Brain; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Mental Recall; Neuropsychological Tests; Organ Size

The Association Between Distinct Delusional Ideations and Depressive Symptoms in Alzheimer's Disease: A Re-Analysis of CATIE-AD. - Nagata, Tomoyuki; Nakajima, Shinichiro; Kito, Shinsuke; Shinagawa, Shunichiro (J Alzheimers Dis, 2024)
BACKGROUND: Delusional ideations, one of neuropsychiatric symptoms (NPSs), are frequently shown in the long-term progression of Alzheimer's disease (AD), and comorbid with other NPSs including depression or agitation. Despite various types of delusional ideations, the comorbidity between each delusional ideation and depressive symptoms has not been discussed. OBJECTIVE: The present cross-sectional study is aimed at testing the hypothetical mechanism of comorbid pattern in AD. METHODS: Among 421 patients with AD, we analyzed the dataset of the Clinical Antipsychotic Trials of Intervention Effectiveness-Alzheimer's Disease to compare age, sex, racial type, Mini-Mental State Examination (MMSE) scores, and Neuropsychiatric Inventory (NPI) depression score of between the presence and absence of each delusional ideation (delusion of persecution, theft, jealousy, abandonment, phantom boarder, Capgras syndrome, misidentification of place, or television sign). Next, with the stratification based on MMSE score of < or > = 15 points, we further explored association between delusional ideation and depressive symptom that was found significances in the primary analysis. RESULTS: Among eight subtypes of delusional ideations, depression score was higher in those with persecution delusion or Capgras syndrome. Moreover, the Capgras syndrome was associated with presence of depression in severer global cognitive impairment status. CONCLUSIONS: As comorbid NPSs of delusional ideation in AD, depressive severity is associated with specific delusional subtype: persecution delusion and Capgras syndrome. Capgras syndrome may be attributable to severe cognitive impairment in addition to depressive symptom. The consideration of pathogenetic differences in the distinct delusional ideations may be helpful for clinicians to select the treatment strategy.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cross-Sectional Studies; Delusions; Depression; Female; Humans; Male; Mental Status and Dementia Tests

Association of Plastic Exposure with Cognitive Function Among Chinese Older Adults. - Zhu, Yongbin; Wu, Yueping; Shi, Liping; Yang, Yue; Wang, Yanrong; Pan, Degong; He, Shulan; Wang, Liqun; Li, Jiangping (J Alzheimers Dis, 2024)
BACKGROUND: The widespread exposure to plastic products and the increasing number of individuals with cognitive impairments have imposed a heavy burden on society. OBJECTIVE: This study aims to investigate the relationship between plastic product exposure in daily life and cognitive function in older Chinese individuals. METHODS: Data were obtained from the 2023 Ningxia Older Psychological Health Cohort, comprising 4045 participants aged 60 and above. Cognitive function was assessed using the Mini-Mental State Examination scale. A population-based plastic exposure questionnaire was used to calculate plastic exposure scores (PES). Binary logistic regression was employed to analyze the relationship between PES and cognitive function, while restricted cubic splines were used to examine the dose-response relationship between PES and cognitive function. Latent profile analysis (LPA) was employed to explore the potential patterns of plastic exposure, and logistic regression was used to investigate the relationship between different exposure patterns and cognitive function. A linear regression model was utilized to investigate the relationship between PES and different dimensions of cognitive function. RESULTS: Among the 4045 participants, 1915 individuals were assessed with mild cognitive impairment (MCI). After adjusting for all covariates, PES (OR = 1.04, 95% CI 1.02-1.06) was significantly associated with the risk of MCI and exhibited a dose-response relationship. LPA identified two potential categories of plastic exposure, with a higher risk of MCI observed in the group using plastic utensils. CONCLUSIONS: This study indicates a positive correlation between plastic exposure levels and MCI risk, particularly among individuals who frequently use plastic tableware.
Keywords: Aged; Aged, 80 and over; China; Cognition; Cognitive Dysfunction; Cohort Studies; East Asian People; Environmental Exposure; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Plastics; Surveys and Questionnaires

Association of Statin Use with Dementia Risk Among Older Adults in Japan: A Nested Case-Control Study Using the LIFE Study. - Ge, Sanyu; Kitamura, Tetsuhisa; Zha, Ling; Komatsu, Masayo; Komukai, Sho; Murata, Fumiko; Maeda, Megumi; Gon, Yasufumi; Kimura, Yasuyoshi; Kiyohara, Kosuke; Sobue, Tomotaka; Fukuda, Haruhisa (J Alzheimers Dis, 2024)
BACKGROUND: Previous studies have shown a possible association between statin use and a decreased risk of dementia, but the association has not been sufficiently established, especially in the super-aging society of Japan. OBJECTIVE: This study aimed to determine the association between statin use and the risk of dementia among Japanese participants aged> =65 years old. METHODS: Data from the Longevity Improvement and Fair Evidence (LIFE) Study were utilized, including medical and long-term care (LTC) claim data from 17 municipalities between April 2014 and December 2020. A nested case-control study was conducted with one case matched to five controls based on age, sex, municipality, and year of cohort entry. We used a conditional logistic regression model to calculate the odds ratios (ORs) and 95% confidence intervals (95% CIs). RESULTS: This study included 57,302 cases and 283,525 controls, with 59.7% of the participants being woman. After adjusting for potential confounders, statin use was associated with a lower risk of dementia (OR, 0.70; 95% CI: 0.68-0.73) and Alzheimer's disease (OR: 0.66; 95% CI: 0.63-0.69). Compared with non-users, the ORs of dementia were as follows: 1.42 (1.34-1.50) for 1-30 total standardized daily dose (TSDD), 0.91 (0.85-0.98) for 31-90 TSDD, 0.63 (0.58-0.69) for 91-180 TSDD, and 0.33 (0.31-0.36) for >180 TSDD in dose-analysis. CONCLUSIONS: Statin use is associated with a reduced risk of dementia and Alzheimer's disease among older Japanese adults. A low cumulative statin dose is associated with an increased risk of dementia, whereas a high cumulative statin dose is a protective factor against dementia.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Dementia; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Japan; Male; Risk Factors

Characterizing Gut Microbiota in Older Chinese Adults with Cognitive Impairment: A Cross-Sectional Study. - Wang, Jing; Zhang, Gong; Lai, Hao; Li, Zengbin; Shen, Mingwang; Li, Chao; Kwan, Patrick; O'Brien, Terence J; Wu, Ting; Yang, Siyu; Zhang, Xueli; Zhang, Lei (J Alzheimers Dis, 2024)
BACKGROUND: Cognitive impairment is a clinical manifestation that occurs in the course of dementia like Alzheimer's disease. The association between cognitive impairment and gut microbiota is unclear. OBJECTIVE: We aimed to identify gut microbiota characteristics and key gut microbiota biomarkers associated with cognitive impairment in a relatively large cohort of older adults in China. METHODS: A total of 229 adults aged ≥60 years from Shenzhen, China were recruited into this cross-sectional study. Participants were divided into cognitive impairment (CI) and no cognitive impairment (NCI) groups according to the results of the Mini-Mental State Examination. Diversity analysis and network analysis were used to characterize the gut microbiota between the two groups. The linear discriminant analysis effect size method and machine learning approaches were sequentially performed to identify gut microbiota biomarkers. The relationship between biomarkers and lifestyle factors was explored using Transformation-based redundancy analysis (tb-RDA). RESULTS: A total of 74 CI participants and 131 NCI participants were included in the analysis. The CI group demonstrated lower α-diversity compared to the NCI group (Shannon: 2.798 versus 3.152, p < 0.001). The density of the gut microbiota interaction network was lower in the CI group (0.074) compared to the NCI group (0.081). Megamonas, Blautia, Pseudomonas, Stenotrophomonas, and Veillonella were key biomarkers for CI. The tb-RDA revealed that increased fruit intake and exercise contribute to a higher abundance of Megamonas, Blautia, and Veillonella. CONCLUSIONS: We identified a significantly reduced abundance of certain beneficial gut microbiota in older Chinese adults with cognitive impairment.
Keywords: Aged; Aged, 80 and over; Biomarkers; China; Cognitive Dysfunction; Cross-Sectional Studies; East Asian People; Female; Gastrointestinal Microbiome; Humans; Machine Learning; Male; Middle Aged

Circulating adipokines and MRI markers of brain aging in middle-aged adults from the community. - Satizabal, Claudia L; Himali, Jayandra Jung; Conner, Sarah C; Beiser, Alexa S; Maillard, Pauline; Vasan, Ramachandran S; DeCarli, Charles; Seshadri, Sudha (J Alzheimers Dis, 2024)
BACKGROUND: Midlife obesity is related to late-onset dementia. Studying adipose tissue-secreted adipokines in the context of brain aging may help us understand this association. OBJECTIVE: To investigate associations between adipokines and brain MRI markers in middle-aged adults from the Third-Generation cohort of the Framingham Heart Study. METHODS: Serum adiponectin, retinol-binding protein 4 (RBP4), fetuin-A, and Fatty Acid-Binding Protein 4 (FABP4) concentrations were measured by enzymatic immunoassays. MRI measures included total brain, cortical gray matter, hippocampal (total and anterior), lateral ventricular, and white matter hyperintensity volumes. We used linear regression models to separately relate adipokine concentrations to MRI measures, adjusting for potential confounders. RESULTS: We included 1882 participants (mean age of 48 ± 8 years, 54% women). Higher RBP4 concentrations were related to markers of brain atrophy, including smaller total (Beta ± standard error, -0.05 ± 0.02; p = 0.014) and cortical gray brain volumes (-0.06 ± 0.02; p = 0.004), and larger lateral ventricular volumes (0.06 ± 0.02; p = 0.006). Additionally, higher RBP4 (-0.06 ± 0.03; p = 0.042), Fetuin-A (-0.06 ± 0.03; p = 0.039), and FABP4 (-0.09 ± 0.03; p = 0.008) concentrations were associated with smaller anterior hippocampal volumes. Most associations remained after additional adjustment for vascular risk factors. In exploratory analyses, higher FABP4 was related to larger total brain in non-obese participants, and to smaller anterior hippocampal volumes in obese participants. Finally, higher adiponectin concentrations were related to smaller cortical gray, only in non-obese participants. CONCLUSIONS: Our results suggest that adipokines are associated with markers of brain atrophy during midlife. Further studies are needed to replicate these findings and elucidate any potential mechanisms contributing to abnormal brain aging.
Keywords: Adipokines; Adiponectin; Adult; Aging; alpha-2-HS-Glycoprotein; Atrophy; Biomarkers; Brain; Cohort Studies; Fatty Acid-Binding Proteins; Female; Gray Matter; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Retinol-Binding Proteins, Plasma

On the Clinimetrics of the Montreal Cognitive Assessment: Cutoff Analysis in Patients with Mild Cognitive Impairment due to Alzheimer's Disease. - Ilardi, Ciro Rosario; Menichelli, Alina; Michelutti, Marco; Cattaruzza, Tatiana; Federico, Giovanni; Salvatore, Marco; Iavarone, Alessandro; Manganotti, Paolo (J Alzheimers Dis, 2024)
BACKGROUND: In the era of disease-modifying therapies, empowering the clinical neuropsychologist's toolkit for timely identification of mild cognitive impairment (MCI) is crucial. OBJECTIVE: Here we examine the clinimetric properties of the Montreal Cognitive Assessment (MoCA) for the early diagnosis of MCI due to Alzheimer's disease (MCI-AD). METHODS: Data from 48 patients with MCI-AD and 47 healthy controls were retrospectively analyzed. Raw MoCA scores were corrected according to the conventional Nasreddine's 1-point correction and demographic adjustments derived from three normative studies. Optimal cutoffs were determined while previously established cutoffs were diagnostically reevaluated. RESULTS: The original Nasreddine's cutoff of 26 and normative cutoffs (non-parametric outer tolerance limit on the 5th percentile of demographically-adjusted score distributions) were overly imbalanced in terms of Sensitivity (Se) and Specificity (Sp). The optimal cutoff for Nasreddine's adjustment showed adequate clinimetric properties (≤23.50, Se = 0.75, Sp = 0.70). However, the optimal cutoff for Santangelo's adjustment (≤22.85, Se = 0.65, Sp = 0.87) proved to be the most effective for both screening and diagnostic purposes according to Larner's metrics. The results of post-probability analyses revealed that an individual testing positive using Santangelo's adjustment combined with a cutoff of 22.85 would have 84% post-test probability of receiving a diagnosis of MCI-AD (LR+ = 5.06). CONCLUSIONS: We found a common (mal)practice of bypassing the applicability of normative cutoffs in diagnosis-oriented clinical practice. In this study, we identified optimal cutoffs for MoCA to be allocated in secondary care settings for supporting MCI-AD diagnosis. Methodological and psychometric issues are discussed.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Neuropsychological Tests; Retrospective Studies; Sensitivity and Specificity

Comparative accuracy of Mini-Linguistic State Examination, Addenbrooke's Cognitive Examination, and Depistage Cognitif de Quebec for the diagnosis of primary progressive aphasia. - Fernández-Romero, Lucía; Morello-García, Florentina; Laforce, Robert; Delgado-Alonso, Cristina; Delgado-Álvarez, Alfonso; Gil-Moreno, María José; Lavoie, Monica; Matías-Guiu, Jorge; Cuetos, Fernando; Matías-Guiu, Jordi A (J Alzheimers Dis, 2024)
BACKGROUND: Clinical diagnosis in primary progressive aphasia (PPA) is challenging. Recently, emphasis has been placed on the importance of screening evaluation. Three different screening tests that use different strategies based on the assessment of language (Mini-Linguistic State Examination, MLSE) or different cognitive domains (Addenbrooke's Cognitive Examination, ACE-III and Dépistage Cognitif de Québec, DCQ) have been proposed and independently validated. These tests aim to detect PPA and classify into the three main variants (non-fluent (nfvPPA), semantic (svPPA) and logopenic (lvPPA)). OBJECTIVE: This study aims to evaluate and compare the diagnostic capacity of these three instruments in PPA. METHODS: A cross-sectional study including 43 patients with PPA (nfvPPA ( = 19), svPPA ( = 8), and lvPPA ( = 16)) and 21 cognitively unimpaired controls was conducted. Clinical diagnoses were established based on an extensive multidisciplinary assessment including neuropsychological assessment, fluorodeoxyglucose-positron emission tomography, MRI, and cerebrospinal fluid biomarkers. Both PPA patients and controls completed the three tests (MLSE, ACE-III, and DCQ). RESULTS: Internal consistency was excellent for the three tests. The area under the curve for the diagnosis of PPA was 0.950 for MLSE, 0.953 for ACE-III, and 0.933 for DCQ. Correlations between the three tests were high. The MLSE, ACE-III, and DCQ tests obtained adequate levels of discrimination between the variants of PPA, with accuracies between 76-79%. CONCLUSIONS: This study confirms the validity of ACE-III, MLSE, and DCQ for the diagnosis of PPA and its variants. This suggests that detailed assessment of linguistic characteristics (MLSE) and non-linguistic features (DCQ, ACE-III) are relevant for the diagnosis and classification of PPA.
Keywords: Aged; Aphasia, Primary Progressive; Cross-Sectional Studies; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Reproducibility of Results

Effect of Metformin on Plasma and Cerebrospinal Fluid Biomarkers in Non-Diabetic Older Adults with Mild Cognitive Impairment Related to Alzheimer's Disease. - Weinberg, Marc S; He, Yingnan; Kivisäkk, Pia; Arnold, Steven E; Das, Sudeshna (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is a complicated condition involving multiple metabolic and immunologic pathophysiological processes that can occur with the hallmark pathologies of amyloid-β, tau, and neurodegeneration. Metformin, an anti-diabetes drug, targets several of these disease processes in in vitro and animal studies. However, the effects of metformin on human cerebrospinal fluid (CSF) and plasma proteins as potential biomarkers of treatment remain unexplored. OBJECTIVE: Using proteomics data from a metformin clinical trial, identify the impact of metformin on plasma and CSF proteins. METHODS: We analyzed plasma and CSF proteomics data collected previously (ClinicalTrials.gov identifier: NCT01965756, conducted between 2013 and 2015), and conduced bioinformatics analyses to compare the plasma and CSF protein levels after 8 weeks of metformin or placebo use to their baseline levels in 20 non-diabetic patients with mild cognitive impairment (MCI) and positive AD biomarkers participants. RESULTS: 50 proteins were significantly (unadjusted p < 0.05) altered in plasma and 26 in CSF after 8 weeks of metformin use, with 7 proteins in common (AZU1, CASP-3, CCL11, CCL20, IL32, PRTN3, and REG1A). The correlation between changes in plasma and CSF levels of these 7 proteins after metformin use relative to baseline levels was high (r = 0.98). The proteins also demonstrated temporal stability. CONCLUSIONS: Our pilot study is the first to investigate the effect of metformin on plasma and CSF proteins in non-diabetic patients with MCI and positive AD biomarkers and identifies several candidate plasma biomarkers for future clinical trials after confirmatory studies.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Double-Blind Method; Female; Humans; Hypoglycemic Agents; Male; Metformin; Middle Aged; Proteomics

Epistatic Features and Machine Learning Improve Alzheimer's Disease Risk Prediction Over Polygenic Risk Scores. - Hermes, Stephen; Cady, Janet; Armentrout, Steven; O'Connor, James; Holdaway, Sarah Carlson; Cruchaga, Carlos; Wingo, Thomas; Greytak, Ellen McRae (J Alzheimers Dis, 2024)
BACKGROUND: Polygenic risk scores (PRS) are linear combinations of genetic markers weighted by effect size that are commonly used to predict disease risk. For complex heritable diseases such as late-onset Alzheimer's disease (LOAD), PRS models fail to capture much of the heritability. Additionally, PRS models are highly dependent on the population structure of the data on which effect sizes are assessed and have poor generalizability to new data. OBJECTIVE: The goal of this study is to construct a paragenic risk score that, in addition to single genetic marker data used in PRS, incorporates epistatic interaction features and machine learning methods to predict risk for LOAD. METHODS: We construct a new state-of-the-art genetic model for risk of Alzheimer's disease. Our approach innovates over PRS models in two ways: First, by directly incorporating epistatic interactions between SNP loci using an evolutionary algorithm guided by shared pathway information; and second, by estimating risk via an ensemble of non-linear machine learning models rather than a single linear model. We compare the paragenic model to several PRS models from the literature trained on the same dataset. RESULTS: The paragenic model is significantly more accurate than the PRS models under 10-fold cross-validation, obtaining an AUC of 83% and near-clinically significant matched sensitivity/specificity of 75%. It remains significantly more accurate when evaluated on an independent holdout dataset and maintains accuracy within APOE genotype strata. CONCLUSIONS: Paragenic models show potential for improving disease risk prediction for complex heritable diseases such as LOAD over PRS models.
Keywords: Aged; Alzheimer Disease; Apolipoproteins E; Epistasis, Genetic; Female; Genetic Predisposition to Disease; Genetic Risk Score; Genome-Wide Association Study; Humans; Machine Learning; Male; Models, Genetic; Multifactorial Inheritance; Polymorphism, Single Nucleotide

The Etiology of Rapidly Progressive Dementia: A 3-Year Retrospective Study in a Tertiary Hospital in China. - Shi, Qin; Liu, Wei-Shi; Liu, Fang; Zeng, Yi-Xuan; Chen, Shu-Fen; Chen, Ke-Liang; Yu, Jin-Tai; Huang, Yu-Yuan (J Alzheimers Dis, 2024)
BACKGROUND: Rapidly progressive dementia (RPD), characterized by a rapid cognitive decline leading to dementia, comprises a diverse range of disorders. Despite advancements in diagnosis and treatment, research on RPD primarily focuses on Western populations. OBJECTIVE: This study aims to explore the etiology and demographics of RPD in Chinese patients. METHODS: We retrospectively analyzed 323 RPD inpatients at Huashan Hospital from May 2019 to March 2023. Data on sociodemographic factors, epidemiology, clinical presentation, and etiology were collected and analyzed. RESULTS: The median onset age of RPD patients was 60.7 years. Two-thirds received a diagnosis within 6 months of symptom onset. Memory impairment was the most common initial symptom, followed by behavioral changes. Neurodegenerative diseases accounted for 47.4% of cases, with central nervous system inflammatory diseases at 30.96%. Autoimmune encephalitis was the leading cause (16.7%), followed by Alzheimer's disease (16.1%), neurosyphilis (11.8%), and Creutzfeldt-Jakob disease (9.0%). Alzheimer's disease, Creutzfeldt-Jakob disease, and frontotemporal dementia were the primary neurodegenerative causes, while autoimmune encephalitis, neurosyphilis, and vascular cognitive impairment were the main non-neurodegenerative causes. CONCLUSIONS: The etiology of RPD in Chinese patients is complex, with neurodegenerative and non-neurodegenerative diseases equally prevalent. Recognizing treatable conditions like autoimmune encephalitis and neurosyphilis requires careful consideration and differentiation.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; China; Cognitive Dysfunction; Creutzfeldt-Jakob Syndrome; Dementia; Disease Progression; Encephalitis; Female; Frontotemporal Dementia; Humans; Male; Middle Aged; Neurodegenerative Diseases; Neurosyphilis; Retrospective Studies; Tertiary Care Centers

First Biodistribution Study of [68Ga]Ga-NOTA-Insulin Following Intranasal Administration in Adult Vervet Monkeys. - Solingapuram Sai, Kiran Kumar; Erichsen, Jennifer M; Gollapelli, Krishna K; Krizan, Ivan; Miller, Mack; Bansode, Avinash; Jorgensen, Mathew J; Register, Thomas; Cazzola, Charles; Gandhi, Reenal; Suman, Julie; Craft, Suzanne (J Alzheimers Dis, 2024)
BACKGROUND: Intranasal insulin (INI) is being explored as a treatment for Alzheimer's disease (AD). Improved memory, functional ability, and cerebrospinal fluid (CSF) AD biomarker profiles have been observed following INI administration. However, the method of intranasal delivery may significantly affect outcomes. OBJECTIVE: To show reliable delivery of insulin to the brain using the Aptar Cartridge Pump System (CPS) intranasal delivery system. METHODS: To visualize INI biodistribution, we developed a novel PET radiotracer, Gallium 68-radiolabeled (NOTA-conjugated) insulin, [68Ga]Ga-NOTA-insulin. We used the Aptar CPS to administer [68Ga]Ga-NOTA-insulin to anesthetized healthy adult vervet monkeys and measured brain regional activity and whole-body dosimetry following PET/CT scans. RESULTS: We observed brain penetration of [68Ga]Ga-NOTA-insulin following intranasal administration with the Aptar CPS. Radioactive uptake was seen in multiple regions, including the amygdala, putamen, hypothalamus, hippocampus, and choroid plexus. A safety profile and whole-body dosimetry were also established in a second cohort of vervets. Safety was confirmed: vitals remained stable, blood glucose levels were unchanged, and no organ was exposed to more than 2.5 mSv of radioactivity. Extrapolations from vervet organ distribution allowed for estimation of the [68Ga]Ga-NOTA-insulin absorbed dose in humans, and the maximum dose of [68Ga]Ga-NOTA-insulin that can be safely administered to humans was determined to be 185 MBq. CONCLUSIONS: The use of [68Ga]Ga-NOTA-insulin as a PET radiotracer is safe and effective for observing brain uptake in vervet monkeys. Further, the Aptar CPS successfully targets [68Ga]Ga-NOTA-insulin to the brain. The data will be essential in guiding future studies of intranasal [68Ga]Ga-NOTA-insulin administration in humans.
Keywords: Administration, Intranasal; Animals; Brain; Chlorocebus aethiops; Female; Gallium Radioisotopes; Heterocyclic Compounds; Heterocyclic Compounds, 1-Ring; Insulin; Male; Positron Emission Tomography Computed Tomography; Positron-Emission Tomography; Radiopharmaceuticals; Tissue Distribution

Functional Connectivity Favors Aberrant Visual Network c-Fos Expression Accompanied by Cortical Synapse Loss in a Mouse Model of Alzheimer's Disease. - L'Esperance, Oliver J; McGhee, Joshua; Davidson, Garett; Niraula, Suraj; Smith, Adam S; Sosunov, Alexandre A; Yan, Shirley ShiDu; Subramanian, Jaichandar (J Alzheimers Dis, 2024)
BACKGROUND: While Alzheimer's disease (AD) has been extensively studied with a focus on cognitive networks, visual network dysfunction has received less attention despite compelling evidence of its significance in AD patients and mouse models. We recently reported c-Fos and synaptic dysregulation in the primary visual cortex of a pre-amyloid plaque AD-model. OBJECTIVE: We test whether c-Fos expression and presynaptic density/dynamics differ in cortical and subcortical visual areas in an AD-model. We also examine whether aberrant c-Fos expression is inherited through functional connectivity and shaped by light experience. METHODS: c-Fos+ cell density, functional connectivity, and their experience-dependent modulation were assessed for visual and whole-brain networks in both sexes of 4-6-month-old J20 (AD-model) and wildtype (WT) mice. Cortical and subcortical differences in presynaptic vulnerability in the AD-model were compared using ex vivo and in vivo imaging. RESULTS: Visual cortical, but not subcortical, networks show aberrant c-Fos expression and impaired experience-dependent modulation. The average functional connectivity of a brain region in WT mice significantly predicts aberrant c-Fos expression, which correlates with impaired experience-dependent modulation in the AD-model. We observed a subtle yet selective weakening of excitatory visual cortical synapses. The size distribution of cortical boutons in the AD-model is downscaled relative to those in WT mice, suggesting a synaptic scaling-like adaptation of bouton size. CONCLUSIONS: Visual network structural and functional disruptions are biased toward cortical regions in pre-plaque J20 mice, and the cellular and synaptic dysregulation in the AD-model represents a maladaptive modification of the baseline physiology seen in WT conditions.
Keywords: Alzheimer Disease; Animals; Disease Models, Animal; Female; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Proto-Oncogene Proteins c-fos; Synapses; Visual Cortex

The funnel effect of reserves prompted by leisure activities across the Alzheimer's disease continuum. - Serra, Laura; Bonarota, Sabrina; Di Domenico, Carlotta; Caruso, Giulia; Giulietti, Giovanni; Rizzuti, Martina; Assogna, Martina; Rodini, Marta; Mencarelli, Lucia; Di Lorenzo, Francesco; Koch, Giacomo; Fadda, Lucia; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Reserves' mechanisms explain inconsistencies between accumulation of neuropathological damage and clinical manifestations. Leisure activities are believed to promote reserves. OBJECTIVE: This study evaluates whether cognitive, social, and physical leisure activities performed over life-span predict current cognitive functioning in normal aging and Alzheimer's disease (AD) continuum. METHODS: 35 AD, 24 amnestic-Mild Cognitive Impairment (a-MCI) patients, 21 individuals with subjective cognitive complaint (SCD), and 25 controls underwent a questionnaire developed to quantify leisure activities in different life periods, the Addenbrooke's Cognitive Examination-Revised (ACE-R), and T1-weighted 3T-MRI scans for brain volumetrics and cortical thickness quantification. Partial/total leisure activities' scores and demographic and brain variables were entered as predictors, while ACE-R scores as dependent variables in linear regression analyses. RESULTS: Current level of cognition was predicted by (i) social and physical activities performed in middle age and current cognitive activity in AD; (ii) cognitive and social activities performed in middle age, current age and cortical thickness in a-MCI; (iii) recreational activities the set of lifetime, current age, and brain features in SCD; (iv) education and the set of lifetime leisure activities over lifespan in controls. CONCLUSIONS: This study shows a funnel effect due to gradual reduction of stimulatory activities in the transition from healthy aging to AD. Reserve indices taking into account different types of stimulatory activities allow to capture even smallest residual effects of reserves accumulated over lifespan, until their complete depletion at advanced AD stages. These results may help target tailored interventions during normal and pathological aging.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Brain; Cognition; Cognitive Dysfunction; Cognitive Reserve; Female; Humans; Leisure Activities; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Surveys and Questionnaires

Gene Co-Expression Analysis of Multiple Brain Tissues Reveals Correlation of FAM222A Expression with Multiple Alzheimer's Disease-Related Genes. - Liang, Jingjing; LaFleur, Bonnie; Hussainy, Sadiya; Perry, George (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is the most common form of dementia in the elderly marked by central nervous system (CNS) neuronal loss and amyloid plaques. FAM222A, encoding an amyloid plaque core protein, is an AD brain atrophy susceptibility gene that mediates amyloid-β aggregation. However, the expression interplay between FAM222A and other AD-related pathway genes is unclear. OBJECTIVE: Our goal was to study FAM222A's whole-genome co-expression profile in multiple tissues and investigate its interplay with other AD-related genes. METHODS: We analyzed gene expression correlations in Genotype-Tissue Expression (GTEx) tissues to identify FAM222A co-expressed genes and performed functional enrichment analysis on identified genes in CNS system. RESULTS: Genome-wide gene expression profiling identified 673 genes significantly correlated with FAM222A (p < 2.5×10-6) in 48 human tissues, including 298 from 13 CNS tissues. Functional enrichment analysis revealed that FAM222A co-expressed CNS genes were enriched in multiple AD-related pathways. Gene co-expression network analysis for identified genes in each brain region predicted other disease associated genes with similar biological function. Furthermore, co-expression of 25 out of 31 AD-related pathways genes with FAM222A was replicated in brain samples from 107 aged subjects from the Aging, Dementia and TBI Study. CONCLUSION: This gene co-expression study identified multiple AD-related genes that are associated with FAM222A, indicating that FAM222A and AD-associated genes can be active simultaneously in similar biological processes, providing evidence that supports the association of FAM222A with AD.
Keywords: Aged; Alzheimer Disease; Brain; Female; Gene Expression Profiling; Genome-Wide Association Study; Humans; Male

Influence of genotype on PCSK9-lipids association in cerebrospinal fluid and serum of patients in the Alzheimer's disease continuum. - Papotti, Bianca; Palumbo, Marcella; Adorni, Maria Pia; Elviri, Lisa; Chiari, Annalisa; Tondelli, Manuela; Bedin, Roberta; Baldelli, Enrica; Lancellotti, Giulia; Lupo, Maria Giovanna; Ferri, Nicola; Bertolotti, Marco; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Alterations in factors involved in cholesterol homeostasis are critical in Alzheimer's disease (AD), but the stage of occurrence, their specific association, and a possible relationship with the genotype are not clarified. OBJECTIVE: We aimed to quantify and correlate specific lipid factors in patients with different degrees of cognitive decline, namely patients with AD and patients with mild cognitive impairment due to AD (MCI-AD), carriers or non-carriers of the genotype. METHODS: We evaluated Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9), cholesterol and the oxidative metabolites 24-, 25-, 27-hydroxycholesterol (HC) in the cerebrospinal fluid (CSF) and serum of AD (n = 28) and MCI-AD (n = 27) patients. RESULTS: CSF and serum PCSK9 and lipids were similar, except for higher serum PCSK9 and triglycerides in MCI-AD compared to AD. In CSF, AD carriers showed higher PCSK9 and 24-HC (+61.3%,  = 0.027 and +32.7%,  = 0.037), compared to non-carriers. There was a negative association between CSF PCSK9 and 27-HC in AD (r = -0.444,  = 0.049) and, exclusively among AD carriers, a negative association between CSF PCSK9 and 24-HC (r = -0.786,  = 0.028). A positive correlation was observed between CSF and serum PCSK9 in AD (r = 0.520,  = 0.004), driven by carriers (r = 0.544,  = 0.038), suggesting PCSK9 exchange between brain and periphery. A positive correlation was detected between serum and CSF 27-HC (r = 0.465,  = 0.039) in AD. None of these results were found in MCI-AD patients. CONCLUSIONS: PCSK9 and 24-HC might be specific markers of ApoE4-associated lipid alterations in AD, possibly contributing to clinical progression in the AD continuum.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Cholesterol; Cognitive Dysfunction; Female; Genotype; Humans; Lipids; Male; Middle Aged; Proprotein Convertase 9

Interaction Between Arteriosclerosis and Amyloid-β on Cognitive Function. - Frentz, Ingeborg; van Arendonk, Joyce; Leeuwis, Anna E; Vernooij, Meike W; van der Flier, Wiesje M; Bos, Daniel; De Deyn, Peter Paul; Wolters, Frank J; Ikram, M Arfan (J Alzheimers Dis, 2024)
BACKGROUND: Dementia is a multifactorial disease, with Alzheimer's disease (AD) and vascular pathology often co-occurring in many individuals with dementia. Yet, the interplay between AD and vascular pathology in cognitive decline is largely undetermined. OBJECTIVE: The aim of the present study was to examine the joint effect of arteriosclerosis and AD pathology on cognition in the general population without dementia. METHODS: We determined the interaction between blood-based AD biomarkers and CT-defined arteriosclerosis on cognition in 2,229 dementia-free participants of the population-based Rotterdam Study (mean age: 68.9 years, 52% women) cross-sectionally. RESULTS: Amyloid-β (Aβ)42 and arterial calcification were associated with cognitive performance. After further adjustment for confounders in a model that combined all biomarkers, only arterial calcification remained independently associated with cognition. There was a significant interaction between arterial calcification and Aβ42 and between arterial calcification and the ratio of Aβ42/40. Yet, estimates attenuated, and interactions were no longer statistically significant after adjustment for cardio metabolic risk factors. CONCLUSIONS: Arteriosclerosis and AD display additive interaction-effects on cognition in the general population, that are due in part to cardio metabolic risk factors. These findings suggest that joint assessment of arteriosclerosis and AD pathology is important for understanding of disease etiology in individuals with cognitive impairment.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Arteriosclerosis; Biomarkers; Cognition; Cognitive Dysfunction; Female; Humans; Male; tau Proteins

Long-Term Safety of Gantenerumab in Participants with Alzheimer's Disease: A Phase III, Double-Blind, and Open-Label Extension Study (Marguerite RoAD). - Neve, Anuja; Das, Bibha; Wojtowicz, Jakub; Huang, Zhiyue; Bullain, Szofia; Watkin, Michelle; Lott, Dominik; Bittner, Tobias; Delmar, Paul; Klein, Gregory; Hofmann, Carsten; Kerchner, Geoffrey A; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Gantenerumab is an anti-amyloid-β immunoglobulin G1 monoclonal antibody for subcutaneous (SC) administration. The efficacy and safety of low-dose (105 mg or 225 mg) gantenerumab were investigated in Marguerite RoAD (MR; NCT02051608), a Phase III, double-blind (DB), placebo-controlled study in participants with mild Alzheimer's disease (AD) dementia. Following a preplanned futility analysis of the SCarlet RoAD study (NCT01224106), MR was converted into an open-label extension (OLE). OBJECTIVE: The DB study aimed to assess the efficacy of gantenerumab compared with placebo from baseline to Week 104 in participants with mild AD dementia. Following conversion to an OLE, this objective became exploratory, as the OLE assessed the long-term safety and tolerability of SC gantenerumab at doses of up to 1,200 mg every 4 weeks (Q4W) in OLE participants. METHODS: Eligible DB study participants were offered the opportunity to receive gantenerumab up-titrated to 1,200 mg Q4W. Safety and tolerability were assessed using magnetic resonance imaging (MRI), physical and neurologic examinations, and adverse event monitoring. RESULTS: Overall, 225 participants were rolled over from the DB part of MR and received ≥1 gantenerumab dose in the OLE. The median treatment duration was 123 weeks. Fifty-nine (26.2%) and 41 (18.2%) participants had amyloid-related imaging abnormality (ARIA)-edema and ARIA-hemorrhage MRI findings, respectively. ARIA findings were manageable with MRI monitoring and dose intervention; most were asymptomatic. There were no unexpected safety findings. CONCLUSIONS: SC gantenerumab at doses of up to 1,200 mg Q4W were well tolerated in participants with mild AD dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antibodies, Monoclonal, Humanized; Double-Blind Method; Female; Humans; Male; Middle Aged; Treatment Outcome

Memory consolidation, temporal and parietal atrophy, and metabolism in amyloid-β positive and negative mild cognitive impairment. - Keith, Cierra M; Haut, Marc W; Vieira Ligo Teixeira, Camila; Mehta, Rashi I; Phelps, Holly; Ward, Melanie; Miller, Mark; Navia, R Osvaldo; Coleman, Michelle M; Marano, Gary; Wang, Xiaofei; Pockl, Stephanie; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is classically characterized by alterations in memory consolidation. With the advent of diagnostic biomarkers, some patients clinically diagnosed with AD display biomarkers inconsistent with the diagnosis. OBJECTIVE: We aimed to explore differences in memory consolidation and neurodegeneration of the temporal and parietal lobes as a function of amyloid-β status in amnestic mild cognitive impairment (aMCI). METHODS: We examined differences in memory consolidation and neurodegeneration between patients diagnosed with amyloid-β positive aMCI (Aβ+ N = 78), amyloid-β negative aMCI (Aβ- N = 48), and healthy participants (HP; N = 41), within a well-characterized clinical cohort. RESULTS: Aβ+ exhibited more pronounced consolidation impairments compared to Aβ-, while Aβ- faced more consolidation challenges than HP. Both Aβ+ and Aβ- were similar in hippocampal volume and entorhinal thickness, but Aβ+ had thinner inferior parietal cortex than Aβ-. Using F-fluoro-deoxyglucose-positron emission tomography, metabolism in both temporal and parietal regions was lower in Aβ+ relative to Aβ-. CONCLUSIONS: These findings suggest pathologies other than AD likely contribute to memory consolidation difficulties in aMCI, and neurodegeneration of the parietal cortex in combination with hypometabolism may contribute to more pronounced consolidation problems in Aβ+.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Atrophy; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Memory Consolidation; Middle Aged; Neuropsychological Tests; Parietal Lobe; Positron-Emission Tomography; Temporal Lobe

A Metabolomics Analysis of a Novel Phenotype of Older Adults at Higher Risk of Dementia. - Sultana, Munira; Camicioli, Richard; Dixon, Roger A; Whitehead, Shawn; Pieruccini-Faria, Frederico; Petrotchenko, Evgeniy; Speechley, Mark; Borchers, Christoph H; Montero-Odasso, Manuel (J Alzheimers Dis, 2024)
BACKGROUND: Older adults presenting with dual-decline in cognition and walking speed face a 6-fold higher risk for dementia compared with those showing no decline. We hypothesized that the metabolomics profile of dual-decliners would be unique even before they show signs of decline in cognition and gait speed. OBJECTIVE: The objective of this study was to determine if plasma metabolomics signatures can discriminate dual-decliners from no decliners, purely cognitive decliners, and purely motor decliners prior to decline. METHODS: A retrospective cross-sectional study using baseline plasma for untargeted metabolomics analyses to investigate early signals of later dual-decline status in study participants (n = 76) with convenient sampling. Dual-decline was operationalized as decline in gait speed (>10 cm/s) and cognition (>2 points decline in Montreal Cognitive Assessment score) on at least two consecutive 6-monthly assessments. The participants' decliner status was evaluated 3 years after the blood sample was collected. Pair-wise comparison of detected compounds was completed using principal components and hierarchical clustering analyses. RESULTS: Analyses did not detect any cluster separation in untargeted metabolomes across baseline groups. However, follow-up analyses of specific molecules detected 4 compounds (17-Hydroxy-12-(hydroxymethyl)-10-oxo-8 oxapentacyclomethyl hexopyranoside, Fleroxacin, Oleic acid, and 5xi-11,12-Dihydroxyabieta-8(14),9(11),12-trien-20-oic acid) were at significantly higher concentration among the dual-decliners compared to non-decliners. The pure cognitive decliner group had significantly lower concentration of six compounds (1,3-nonanediol acetate, 4-(2-carboxyethyl)-2-methoxyphenyl beta-D-glucopyranosiduronic acid, oleic acid, 2E-3-[4-(sulfo-oxy)phenyl] acrylic acid, palmitelaidic acid, and myristoleic acid) compared to the non-decliner group. CONCLUSIONS: The unique metabolomics profile of dual-decliners warrants follow-up metabolomics analysis. Results may point to modifiable pathways.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cross-Sectional Studies; Dementia; Female; Humans; Male; Metabolomics; Phenotype; Retrospective Studies

Mitochondria-Related Candidate Genes and Diagnostic Model to Predict Late-Onset Alzheimer's Disease and Mild Cognitive Impairment. - Yan, Ran; Wang, Wenjing; Yang, Wen; Huang, Masha; Xu, Wei (J Alzheimers Dis, 2024)
BACKGROUND: Late-onset Alzheimer's disease (LOAD) is the most common type of dementia, but its pathogenesis remains unclear, and there is a lack of simple and convenient early diagnostic markers to predict the occurrence. OBJECTIVE: Our study aimed to identify diagnostic candidate genes to predict LOAD by machine learning methods. METHODS: Three publicly available datasets from the Gene Expression Omnibus (GEO) database containing peripheral blood gene expression data for LOAD, mild cognitive impairment (MCI), and controls (CN) were downloaded. Differential expression analysis, the least absolute shrinkage and selection operator (LASSO), and support vector machine recursive feature elimination (SVM-RFE) were used to identify LOAD diagnostic candidate genes. These candidate genes were then validated in the validation group and clinical samples, and a LOAD prediction model was established. RESULTS: LASSO and SVM-RFE analyses identified 3 mitochondria-related genes (MRGs) as candidate genes, including NDUFA1, NDUFS5, and NDUFB3. In the verification of 3 MRGs, the AUC values showed that NDUFA1, NDUFS5 had better predictability. We also verified the candidate MRGs in MCI groups, the AUC values showed good performance. We then used NDUFA1, NDUFS5 and age to build a LOAD diagnostic model and AUC was 0.723. Results of qRT-PCR experiments with clinical blood samples showed that the three candidate genes were expressed significantly lower in the LOAD and MCI groups when compared to CN. CONCLUSION: Two mitochondrial-related candidate genes, NDUFA1 and NDUFS5, were identified as diagnostic markers for LOAD and MCI. Combining these two candidate genes with age, a LOAD diagnostic prediction model was successfully constructed.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Male; Mitochondria; Support Vector Machine

Optimizing the Implementation of a Lifestyle Dementia Prevention Intervention for Older Patients in an Academic Healthcare System. - Mace, Ryan A; Lyons, Christopher; Cohen, Joshua E; Ritchie, Christine; Bartels, Stephen; Okereke, Olivia I; Hoeppner, Bettina B; Brewer, Judson A; Vranceanu, Ana-Maria (J Alzheimers Dis, 2024)
BACKGROUND: Interventions that promote healthy lifestyles are critical for the prevention of Alzheimer's disease and Alzheimer's disease related dementias (AD/ADRD). However, knowledge of the best practices for implementing AD/ADRD prevention in healthcare settings remains limited. OBJECTIVE: We aimed to qualitatively identify barriers and facilitators to implementing a clinical trial of a novel lifestyle intervention (My Healthy Brain) in our medical center for older patients with subjective cognitive decline who are at-risk for AD/ADRD. METHODS: We conducted focus groups with 26 healthcare professionals (e.g., physicians, psychology, nursing) from 5 clinics that treat older patients (e.g., memory care, psychiatry). Our qualitative analysis integrated two implementation frameworks to systematically capture barriers and facilitators to AD/ADRD prevention (Consolidated Framework for Implementation Science Research) that impact implementation outcomes of acceptability, appropriateness, and feasibility (Proctor's framework). RESULTS: We found widespread support for an RCT of My Healthy Brain and AD/ADRD prevention. Participants identified barriers related to patients (stigma, technological skills), providers (dismissiveness of "worried well," doubting capacity for behavior change), clinics (limited time and resources), and the larger healthcare system (underemphasis on prevention). Implementation strategies guided by Expert Recommendations for Implementing Change (ERIC) included: developing tailored materials, training staff, obtaining buy-in from leadership, addressing stigmatized language and practices, identifying "champions," and integrating with workflows and resources. CONCLUSIONS: The results will inform our recruitment, enrollment, and retention procedures to implement the first randomized clinical trial of My Healthy Brain. Our study provides a blueprint for addressing multi-level barriers to the implementation of AD/ADRD prevention for older patients in medical settings.
Keywords: Academic Medical Centers; Aged; Alzheimer Disease; Cognitive Dysfunction; Dementia; Female; Focus Groups; Health Personnel; Humans; Life Style; Male

Palliative Care in Nursing Home Residents with Young-Onset Dementia: Professional and Family Caregiver Perspectives. - Maters, Jasper; van der Steen, Jenny T; de Vugt, Marjolein E; Bakker, Christian; Koopmans, Raymond T C M (J Alzheimers Dis, 2024)
BACKGROUND: The evidence underpinning palliative care in dementia is mostly based on research in older populations. Little is known about the palliative care needs of people with young-onset dementia (YOD). OBJECTIVE: To describe palliative care practices including advance care planning (ACP) in people with YOD residing in Dutch nursing homes. METHODS: The study presents baseline questionnaire data from an observational cohort study. Physicians, family caregivers, and nursing staff completed questionnaires about 185 residents with YOD. The questionnaires included items on sociodemographics, quality of life measured with the quality of life in late-stage dementia (QUALID) scale, dementia-related somatic health problems, symptoms, pain medication, psychotropic drugs, and ACP. RESULTS: The mean age was 63.9 (SD 5.8) years. Half (50.3%) of them were female. Alzheimer's disease dementia (42.2%) was the most prevalent subtype. The mean QUALID score was 24.0 (SD 7.9) as assessed by family caregivers, and 25.3 (SD 8.6) as assessed by the nursing staff. Swallowing problems were the most prevalent dementia-related health problem (11.4%). Agitation was often reported by physicians (42.0%) and nursing staff (40.5%). Psychotropics were prescribed frequently (72.3%). A minority had written advance directives (5.4%) or documentation on treatment preferences by the former general practitioner (27.2%). Global care goals most often focused on comfort (73.9%). Proportions of do-not-treat orders were higher than do-treat orders for all interventions except for hospitalization and antibiotics. CONCLUSIONS: ACP must be initiated earlier, before nursing home admission. A palliative approach seems appropriate even though residents are relatively young and experience few dementia-related health problems.
Keywords: Aged; Alzheimer Disease; Caregivers; Dementia; Female; Humans; Male; Nursing Homes; Palliative Care; Quality of Life

Plasma BDNF/Irisin Ratio Associates with Cognitive Function in Older People. - Huang, Xiuxiu; Wang, Jiaxin; Zhang, Shifang; Zhao, Xiaoyan; An, Ran; Lan, Yue; Yi, Ming; Wan, Qiaoqin (J Alzheimers Dis, 2024)
BACKGROUND: Reliable blood biomarkers are crucial for early detection and treatment evaluation of cognitive impairment, including Alzheimer's disease and other dementias. OBJECTIVE: To examine whether plasma biomarkers and their combination are different between older people with mild cognitive impairment (MCI) and cognitively normal individuals, and to explore their relations with cognitive performance. METHODS: This cross-sectional study included 250 older adults, including 124 participants with MCI, and 126 cognitively normal participants. Plasma brain-derived neurotrophic factor (BDNF), irisin and clusterin were measured, and BDNF/irisin ratio was calculated. Global cognition was evaluated by the Montreal Cognitive Assessment. RESULTS: Plasma irisin levels, but not BDNF, were significantly different between MCI group and cognitively normal group. Higher irisin concentration was associated with an increased probability for MCI both before and after controlling covariates. By contrast, plasma BDNF concentration, but not irisin, was linearly correlated with cognitive performance after adjusting for covariates. Higher BDNF/irisin ratios were not only correlated with better cognitive performance, but also associated with lower risks of MCI, no matter whether we adjusted for covariates. Plasma BDNF and irisin concentrations increased with aging, whereas BDNF/irisin ratios remained stable. No significant results of clusterin were observed. CONCLUSIONS: Plasma BDNF/irisin ratio may be a reliable indicator which not only reflects the odds of the presence of MCI but also directly associates with cognitive performance.
Keywords: Aged; Aged, 80 and over; Aging; Biomarkers; Brain-Derived Neurotrophic Factor; Clusterin; Cognition; Cognitive Dysfunction; Cross-Sectional Studies; Female; Fibronectins; Humans; Male; Mental Status and Dementia Tests; Neuropsychological Tests

Potential Impact of Slowing Disease Progression in Early Symptomatic Alzheimer's Disease on Patient Quality of Life, Caregiver Time, and Total Societal Costs: Estimates Based on Findings from GERAS-US Study. - Chandler, Julie M; Ye, Wenyu; Mi, Xiaojuan; Doty, Erin G; Johnston, Joseph A (J Alzheimers Dis, 2024)
BACKGROUND: Impact of Alzheimer's disease (AD) progression on patient health-related quality of life (HRQoL), caregiver time, and societal costs is not well characterized in early AD. OBJECTIVE: To assess the association of change in cognition with HRQoL, caregiver time, and societal costs over 36 months, and estimate the impact of slowing disease progression on these outcomes. METHODS: This post-hoc analysis included patients with amyloid-positive mild cognitive impairment (MCI) and mild AD dementia (MILD AD) from the 36-month GERAS-US study. Disease progression was assessed using the Mini-Mental State Examination score. Change in outcomes associated with slowing AD progression was estimated using coefficients from generalized linear models. RESULTS: At baseline, 300 patients had MCI and 317 had MILD AD. Observed natural progression over 36 months was associated with: 5.1 point decline in the Bath Assessment of Subjective Quality of Life in Dementia (BASQID) score (for HRQoL), increase in 1,050 hours of total caregiver time, and $8,504 total societal costs for MCI; 6.6 point decline in the BASQID score, increase in 1,929 hours of total caregiver time, and $12,795 total societal costs for MILD AD per person. Slowing AD progression by 30% could result in per person savings in HRQoL decline, total caregiver time, and total societal costs: for MCI: 1.5 points, 315 hours, and $2,638; for MILD AD: 2.0 points, 579 hours, and $3,974. CONCLUSIONS: Slowing AD progression over 36 months could slow decline in HRQoL and save caregiver time and societal cost in patients with MCI and MILD AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Caregivers; Cognitive Dysfunction; Cost of Illness; Disease Progression; Female; Humans; Male; Mental Status and Dementia Tests; Quality of Life; United States

Pre-existing dementia is associated with 2-3 folds risk for in-hospital mortality and complications after intracerebral hemorrhage stroke. - Zuo, Lijun; Hu, Yang; Dong, YanHong; Seet, Raymond Cs; Li, Zixiao; Wang, Yongjun; Zhao, Xingquan (J Alzheimers Dis, 2024)
BACKGROUND: Pre-existing dementia was related to poor functional outcome after intracerebral hemorrhage (ICH), and its commonly underlying pathologies were considered as cerebral amyloid angiopathy. But the impact of pre-existing dementia on in-hospital mortality in Chinese ICH patients has not been well characterized. OBJECTIVE: To investigate the association between pre-existing dementia and in-hospital mortality after ICH. METHODS: Data were extracted from the China Stroke Center Alliance database. Information about the existence of prior to stroke dementia was obtained from next of kin informants and registered in clinical charts. Patients' characteristics, in-hospital mortality, home discharge and complications were compared between ICH patients with and without pre-existing dementia. RESULTS: Out of the 72,318 ICH patients, we identified 328 patients with pre-existing dementia. Patients with pre-existing dementia were more likely to experience greater stroke severity as measured by the National Institute of Health Stroke Scale and Glasgow Coma Scale. In the adjusted models, the presence of pre-existing dementia was associated with an increased risk of in-hospital mortality (OR 2.31, 95% CI 1.12-4.77), more frequent in-hospital complications of pulmonary embolism (OR 5.41, 95% CI 1.16-25.14), pneumonia (OR 1.58, 95% CI 1.08-2.33), urinary tract infection (OR 2.37, 95% CI 1.21-4.64), gastrointestinal bleeding (OR 2.39, 95% CI 1.27-4.49) and lower home discharge (OR 0.59, 95% CI 0.38∼0.93). CONCLUSIONS: ICH patients with pre-existing dementia are more likely to suffer from greater stroke severity, poorer outcomes and lower home discharge. Future studies should evaluate the value of intensive risk factor control among individuals with pre-existing dementia for stroke prevention.
Keywords: Aged; Aged, 80 and over; Cerebral Hemorrhage; China; Dementia; Female; Hemorrhagic Stroke; Hospital Mortality; Humans; Male; Middle Aged; Risk Factors; Stroke

Regional differences in glucose metabolic decline and tau deposition in the Alzheimer's continuum brain. - Ishii, Kazunari; Yamada, Takahiro; Hanaoka, Kohei; Kaida, Hayato; Kojita, Yasuyuki; Kono, Atsushi; Hanada, Kazushi; Saigoh, Kazumasa; Sakuta, Shizuka; Hashimoto, Mamoru; Kato, Takashi; Nakamura, Akinori (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is characterized by the accumulation of amyloid-β and tau proteins, leading to neurofibrillary tangles. A biomarker-based diagnostic method called the ATN system categorizes AD pathology into amyloid-β (A), tau (T), and neurodegeneration (N). The relationship between regional tau deposition and reduced glucose metabolism in the preclinical AD stage is not well understood. OBJECTIVE: We presented voxel-by-voxel metabolic/tau deposition ratio (MTR) images to investigate the effects of tau deposition on metabolism in AD brains on a stage-by-stage basis. METHODS: We selected 174 subjects who underwent 3D-MRI, FDG-PET, amyloid PET, and tau PET scans. MTR images were created by normalizing FDG-PET toMK6240 PET images. Voxel-wise comparisons among 63 cognitively normal amyloid-negative (CNA) subjects, 49 subjects with AD dementia (ADD), 23 subjects with mild cognitive impairment due to AD (MCA), and 39 preclinical AD (PRC) subjects were conducted. RESULTS: There was reduced glucose metabolism in ADD and MCA groups compared to CNA, predominantly in parietotemporal areas. Tau deposition was observed in wider areas in ADD and restricted to the medial temporal lobes in MCA. MTR exhibited significant reductions in broader regions in ADD and MCA, indicating simultaneous glucose metabolism decrease and tau deposition. At the MCA and PRC stages, glucose metabolism impairment and tau deposition were shown in separate regions by FDG PET and tau PET, respectively, while MTR images showed impairment in both regions. CONCLUSIONS: Our findings suggest that MTR imaging provides insights into AD pathophysiology by simultaneously assessing glucose metabolism and tau deposition. In the early stage of the AD continuum (MCA and PRC), metabolic decline and tau deposition occur independently in different brain regions.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Glucose; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Positron-Emission Tomography; tau Proteins

The RESIST Study: Examining Cognitive Change in Rheumatoid Arthritis Patients with Mild Cognitive Impairment Being Treated with a TNF-Inhibitor Compared to a Conventional Synthetic Disease-Modifying Anti-Rheumatic Drug. - Marr, Calum; McDowell, Bethany; Holmes, Clive; Edwards, Christopher J; Cardwell, Christopher; McHenry, Michelle; Meenagh, Gary; Teeling, Jessica L; McGuinness, Bernadette (J Alzheimers Dis, 2024)
BACKGROUND: Evidence suggests that TNF inhibitors (TNFi) used to treat rheumatoid arthritis (RA) may protect against Alzheimer's disease progression by reducing inflammation. OBJECTIVE: To investigate whether RA patients with mild cognitive impairment (MCI) being treated with a TNFi show slower cognitive decline than those being treated with a conventional synthetic disease-modifying anti-rheumatic drug (csDMARD). METHODS: 251 participants with RA and MCI taking either a csDMARD (N = 157) or a TNFi (N = 94) completed cognitive assessments at baseline and 6-month intervals for 18 months. It was hypothesized that those taking TNFis would show less decline on the primary outcome of Free and Cued Selective Reminding Test with Immediate Recall (FCSRT-IR) and the secondary outcome of Montreal Cognitive Assessment (MoCA). RESULTS: No significant changes in FCSRT-IR scores were observed in either treatment group. There was no significant difference in FCSRT-IR between treatment groups at 18 months after adjusting for baseline (mean difference = 0.5, 95% CI = -1.3, 2.3). There was also no difference in MoCA score (mean difference = 0.4, 95% CI = -0.4, 1.3). CONCLUSIONS: There was no cognitive decline in participants with MCI being treated with TNFis and csDMARDs, raising the possibility both classes of drug may be protective. Future studies should consider whether controlling inflammatory diseases using any approach is more important than a specific therapeutic intervention.
Keywords: Aged; Antirheumatic Agents; Arthritis, Rheumatoid; Cognitive Dysfunction; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Neuropsychological Tests; Tumor Necrosis Factor Inhibitors; Tumor Necrosis Factor-alpha

Sex and Sleep Disruption as Contributing Factors in Alzheimer's Disease. - Johnson, Carrie E; Duncan, Marilyn J; Murphy, M Paul (J Alzheimers Dis, 2024)
Alzheimer's disease (AD) affects more women than men, with women throughout the menopausal transition potentially being the most under researched and at-risk group. Sleep disruptions, which are an established risk factor for AD, increase in prevalence with normal aging and are exacerbated in women during menopause. Sex differences showing more disrupted sleep patterns and increased AD pathology in women and female animal models have been established in literature, with much emphasis placed on loss of circulating gonadal hormones with age. Interestingly, increases in gonadotropins such as follicle stimulating hormone are emerging to be a major contributor to AD pathogenesis and may also play a role in sleep disruption, perhaps in combination with other lesser studied hormones. Several sleep influencing regions of the brain appear to be affected early in AD progression and some may exhibit sexual dimorphisms that may contribute to increased sleep disruptions in women with age. Additionally, some of the most common sleep disorders, as well as multiple health conditions that impair sleep quality, are more prevalent and more severe in women. These conditions are often comorbid with AD and have bi-directional relationships that contribute synergistically to cognitive decline and neuropathology. The association during aging of increased sleep disruption and sleep disorders, dramatic hormonal changes during and after menopause, and increased AD pathology may be interacting and contributing factors that lead to the increased number of women living with AD.
Keywords: Alzheimer Disease; Animals; Cross-Sectional Studies; Female; Humans; Male; Multimorbidity; Sex Factors; Sleep; Sleep Wake Disorders

Short-Term Practice Effects on Cognitive Tests Across the Late Life Cognitive Spectrum and How They Compare to Biomarkers of Alzheimer's Disease. - Duff, Kevin; Hammers, Dustin B; Koppelmans, Vincent; King, Jace B; Hoffman, John M (J Alzheimers Dis, 2024)
BACKGROUND: Practice effects on cognitive testing in mild cognitive impairment (MCI) and Alzheimer's disease (AD) remain understudied, especially with how they compare to biomarkers of AD. OBJECTIVE: The current study sought to add to this growing literature. METHODS: Cognitively intact older adults (n = 68), those with amnestic MCI (n = 52), and those with mild AD (n = 45) completed a brief battery of cognitive tests at baseline and again after one week, and they also completed a baseline amyloid PET scan, a baseline MRI, and a baseline blood draw to obtain APOE ɛ4 status. RESULTS: The intact participants showed significantly larger baseline cognitive scores and practice effects than the other two groups on overall composite measures. Those with MCI showed significantly larger baseline scores and practice effects than AD participants on the composite. For amyloid deposition, the intact participants had significantly less tracer uptake, whereas MCI and AD participants were comparable. For total hippocampal volumes, all three groups were significantly different in the expected direction (intact > MCI > AD). For APOE ɛ4, the intact had significantly fewer copies of ɛ4 than MCI and AD. The effect sizes of the baseline cognitive scores and practice effects were comparable, and they were significantly larger than effect sizes of biomarkers in 7 of the 9 comparisons. CONCLUSION: Baseline cognition and short-term practice effects appear to be sensitive markers in late life cognitive disorders, as they separated groups better than commonly-used biomarkers in AD. Further development of baseline cognition and short-term practice effects as tools for clinical diagnosis, prognostic indication, and enrichment of clinical trials seems warranted.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Cognition; Cognitive Dysfunction; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Positron-Emission Tomography; Practice, Psychological

Small RNA Profiles of Brain Tissue-Derived Extracellular Vesicles in Alzheimer's Disease. - Huang, Yiyao; Driedonks, Tom A P; Cheng, Lesley; Turchinovich, Andrey; Pletniková, Olga; Redding-Ochoa, Javier; Troncoso, Juan C; Hill, Andrew F; Mahairaki, Vasiliki; Zheng, Lei; Witwer, Kenneth W (J Alzheimers Dis, 2024)
BACKGROUND: Extracellular vesicles (EVs) and non-coding RNAs (ncRNAs) are emerging contributors to Alzheimer's disease (AD) pathophysiology. Differential abundance of ncRNAs carried by EVs may provide valuable insights into underlying disease mechanisms. Brain tissue-derived EVs (bdEVs) are particularly relevant, as they may offer valuable insights about the tissue of origin. However, there is limited research on diverse ncRNA species in bdEVs in AD. OBJECTIVE: This study explored whether the non-coding RNA composition of EVs isolated from post-mortem brain tissue is related to AD pathogenesis. METHODS: bdEVs from age-matched late-stage AD patients (n = 23) and controls (n = 10) that had been separated and characterized in our previous study were used for RNA extraction, small RNA sequencing, and qPCR verification. RESULTS: Significant differences of non-coding RNAs between AD and controls were found, especially for miRNAs and tRNAs. AD pathology-related miRNA and tRNA differences of bdEVs partially matched expression differences in source brain tissues. AD pathology had a more prominent association than biological sex with bdEV miRNA and tRNA components in late-stage AD brains. CONCLUSIONS: Our study provides further evidence that EV non-coding RNAs from human brain tissue, including but not limited to miRNAs, may be altered and contribute to AD pathogenesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Extracellular Vesicles; Female; Humans; Male; MicroRNAs; RNA, Small Untranslated; RNA, Transfer; RNA, Untranslated

Voluntary wheel running decreases amyloidogenic pathway and rescues cognition and mitochondrial energy metabolism in middle-aged female 3xTg-AD mouse model of Alzheimer's disease. - Dos Santos, Jonathas Rodrigo; Catalão, Carlos Henrique Rocha; Vulczak, Anderson; Azzolini, Ana Elisa Caleiro Seixas; Alberici, Luciane Carla (J Alzheimers Dis, 2024)
BACKGROUND: Evidence supports the neuroprotective effects of physical activity, either in experimental animal models or humans. However, the biological mechanisms by which physical exercise modulates dementia and Alzheimer's disease (AD) progression are still unclear. OBJECTIVE: This study investigated whether long-term (6 months) of voluntary wheel running induces neuroprotective effects in the pathogenesis of AD in middle-aged (8 months) female mice, focusing on energy metabolism. METHODS: A genetic mice model of AD (3xTg-AD) that performed wheel running presented changes in body metabolism and muscle oxidative profile, as well as restored discriminative and non-associative retention memories, evaluated by novel object recognition and open field tasks, respectively. RESULTS: In the hippocampus, these mice exhibited reduced levels of amyloidogenic AβPPβ fragment, phospho-Tau protein and phospho-Akt (activated form), without changes in phospho-AMPK (activated form). In addition, hippocampal mitochondria presented a restored respiratory function, characterized by lower coupling degree and weak contribution from complex I found in 3xTg-AD mice. CONCLUSIONS: The results demonstrated that voluntary exercise improves cognitive parameters and biochemical hallmarks of AD, modulates Akt activation and enhances mitochondrial energy metabolism in hippocampus of middle-aged 3xTg-AD female mice, thereby reinforcing the neuroprotective role of physical exercise and the involvement of mitochondria in the etiology of the AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cognition; Disease Models, Animal; Energy Metabolism; Female; Hippocampus; Mice; Mice, Transgenic; Mitochondria; Physical Conditioning, Animal; tau Proteins

Association of Interleukin-6 and Interleukin-8 with Cognitive Decline in an Asian Memory Clinic Population. - Teoh, Nicole Shu Ning; Gyanwali, Bibek; Lai, Mitchell K P; Chai, Yuek Ling; Chong, Joyce R; Chong, Eddie Jun Yi; Chen, Christopher; Tan, Chuen Seng; Hilal, Saima (J Alzheimers Dis, 2023)
BACKGROUND: Neuroinflammation has been postulated to play an important role in cognitive impairment, cognitive decline, and dementia. Inflammatory biomarkers such as interleukin-6 (IL-6) and IL-8 are found to be associated with the neuro-inflammatory process and worse cognitive function. However, it is unknown whether these interleukins are associated with long-term cognitive function. OBJECTIVE: To investigate the association of baseline IL-6 and IL-8 with cognitive function at baseline as well as its association with cognitive decline over five-year follow-up. METHODS: 387 patients were recruited from an ongoing memory clinic-based study who underwent comprehensive physical, medical, neuropsychological and blood assessments together with brain MRI. IL-6 and IL-8 were measured using LUMINEX assays. The National Institute of Neurological Disorders and Stroke-Canadian Stroke Network neuropsychological battery was used to assess cognitive decline across multiple domains. RESULTS: Among the 387 (mean age = 72.9 years and 53.7% males) participants, 322 had at least two follow-up assessments and were included in the longitudinal analysis. Negative linear trend associations were found between tertiles of IL-8 with baseline global cognition (p-trend< 0.001), attention (p-trend = 0.005), executive function (p-trend< 0.001), and visuospatial function (p-trend = 0.002) domains. No association was found between baseline IL-8 and cognitive decline. IL-6 was not associated with both baseline and follow-up cognition. CONCLUSION: IL-8 was associated with worse cognition especially in attention, executive function, and visuospatial function, suggesting the role of neuroinflammation in cognitive impairment. Hence, blood inflammatory biomarkers may be useful indicators in identifying patients at risk of cognitive impairment and warrant consideration for inclusion in treatment trials.
Keywords: Aged; Biomarkers; Canada; Cognition; Cognitive Dysfunction; Female; Humans; Interleukin-6; Interleukin-8; Male; Neuroinflammatory Diseases; Neuropsychological Tests

Characterizing Performance Gaps of a Code-Based Dementia Algorithm in a Population-Based Cohort of Cognitive Aging. - Vassilaki, Maria; Fu, Sunyang; Christenson, Luke R; Garg, Muskan; Petersen, Ronald C; St Sauver, Jennifer; Sohn, Sunghwan (J Alzheimers Dis, 2023)
BACKGROUND: Multiple algorithms with variable performance have been developed to identify dementia using combinations of billing codes and medication data that are widely available from electronic health records (EHR). If the characteristics of misclassified patients are clearly identified, modifying existing algorithms to improve performance may be possible. OBJECTIVE: To examine the performance of a code-based algorithm to identify dementia cases in the population-based Mayo Clinic Study of Aging (MCSA) where dementia diagnosis (i.e., reference standard) is actively assessed through routine follow-up and describe the characteristics of persons incorrectly categorized. METHODS: There were 5,316 participants (age at baseline (mean (SD)): 73.3 (9.68) years; 50.7% male) without dementia at baseline and available EHR data. ICD-9/10 codes and prescription medications for dementia were extracted between baseline and one year after an MCSA dementia diagnosis or last follow-up. Fisher's exact or Kruskal-Wallis tests were used to compare characteristics between groups. RESULTS: Algorithm sensitivity and specificity were 0.70 (95% CI: 0.67, 0.74) and 0.95 (95% CI: 0.95, 0.96). False positives (i.e., participants falsely diagnosed with dementia by the algorithm) were older, with higher Charlson comorbidity index, more likely to have mild cognitive impairment (MCI), and longer follow-up (versus true negatives). False negatives (versus true positives) were older, more likely to have MCI, or have more functional limitations. CONCLUSIONS: We observed a moderate-high performance of the code-based diagnosis method against the population-based MCSA reference standard dementia diagnosis. Older participants and those with MCI at baseline were more likely to be misclassified.
Keywords: Alzheimer Disease; Cognitive Aging; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Male

Coexistence of Amyotrophic Lateral Sclerosis and Alzheimer's Disease: Case Report and Review of the Literature. - Verde, Federico; Aiello, Edoardo Nicolò; Adobbati, Laura; Poletti, Barbara; Solca, Federica; Tiloca, Cinzia; Sangalli, Davide; Maranzano, Alessio; Muscio, Cristina; Ratti, Antonia; Zago, Stefano; Ticozzi, Nicola; et al. (J Alzheimers Dis, 2023)
We describe a case of amyotrophic lateral sclerosis (ALS) associated with Alzheimer's disease (AD) and review the literature about the coexistence of the two entities, highlighting the following: mean age at onset is 63.8 years, with slight female predominance; ALS tends to manifest after cognitive impairment and often begins in the bulbar region; average disease duration is 3 years; cognitive phenotype is mostly amnestic; the pattern of brain involvement is, in most cases, consistent with AD. Our case and the reviewed ones suggest that patients with ALS and dementia lacking unequivocal features of FTD should undergo additional examinations in order to recognize AD.
Keywords: Alzheimer Disease; Amyotrophic Lateral Sclerosis; Brain; Cognitive Dysfunction; Female; Frontotemporal Dementia; Humans; Male

The Effect of Exercise on Falls in People Living with Dementia: A Systematic Review. - Jehu, Deborah A; Davis, Jennifer C; Gill, Jessica; Oke, Olabamibo; Liu-Ambrose, Teresa (J Alzheimers Dis, 2023)
BACKGROUND: People living with dementia (PWD) are at a heightened risk for falls. However, the effects of exercise on falls in PWD are unclear. OBJECTIVE: To conduct a systematic review of randomized controlled trials (RCTs) examining the efficacy of exercise to reduce falls, recurrent falls, and injurious falls relative to usual care among PWD. METHODS: We included peer-reviewed RCTs evaluating any exercise mode on falls and related injuries among medically diagnosed PWD aged ≥55years (international prospective register of systematic reviews (PROSPERO) ID:CRD42021254637). We excluded studies that did not solely involve PWD and were not the primary publication examining falls. We searched the Cochrane Dementia and Cognitive Improvement Group's Specialized Register and grey literature on 08/19/2020 and 04/11/2022; topical categories included dementia, exercise, RCTs, and falls. We evaluated the risk of bias (ROB) using the Cochrane ROB Tool-2 and study quality using the Consolidated Standards of Reporting Trials. RESULTS: Twelve studies were included (n = 1,827; age = 81.3±7.0 years; female = 59.3%; Mini-Mental State Examination = 20.1±4.3 points; intervention duration = 27.8±18.5 weeks; adherence = 75.5±16.2%; attrition = 21.0±12.4%). Exercise reduced falls in two studies [Incidence Rate Ratio (IRR) range = 0.16 to 0.66; fall rate range: intervention = 1.35-3.76 falls/year, control = 3.07-12.21 falls/year]; all other studies (n = 10) reported null findings. Exercise did not reduce recurrent falls (n = 0/2) or injurious falls (n = 0/5). The RoB assessment ranged from some concerns (n = 9) to high RoB (n = 3); no studies were powered for falls. The quality of reporting was good (78.8±11.4%). CONCLUSION: There was insufficient evidence to suggest that exercise reduces falls, recurrent falls, or injurious falls among PWD. Well-designed studies powered for falls are needed.
Keywords: Dementia; Exercise; Female; Humans; Independent Living

Effects of Striatal Amyloidosis on the Dopaminergic System and Behavior: A Comparative Study in Male and Female 5XFAD Mice. - Lansdell, Theresa A; Xu, Hui; Galligan, James J; Dorrance, Anne M (J Alzheimers Dis, 2023)
BACKGROUND: Nearly two-thirds of patients diagnosed with Alzheimer's disease (AD) are female. In addition, female patients with AD have more significant cognitive impairment than males at the same disease stage. This disparity suggests there are sex differences in AD progression. While females appear to be more affected by AD, most published behavioral studies utilize male mice. In humans, there is an association between antecedent attention-deficit/hyperactivity disorder and increased risk of dementia. Functional connectivity studies indicate that dysfunctional cortico-striatal networks contribute to hyperactivity in attention deficit hyperactivity disorder. Higher plaque density in the striatum accurately predicts the presence of clinical AD pathology. In addition, there is a link between AD-related memory dysfunction and dysfunctional dopamine signaling. OBJECTIVE: With the need to consider sex as a biological variable, we investigated the influence of sex on striatal plaque burden, dopaminergic signaling, and behavior in prodromal 5XFAD mice. METHODS: Six-month-old male and female 5XFAD and C57BL/6J mice were evaluated for striatal amyloid plaque burden, locomotive behavior, and changes in dopaminergic machinery in the striatum. RESULTS: 5XFAD female mice had a higher striatal amyloid plaque burden than male 5XFAD mice. 5XFAD females, but not males, were hyperactive. Hyperactivity in female 5XFAD mice was associated with increased striatal plaque burden and changes in dopamine signaling in the dorsal striatum. CONCLUSION: Our results indicate that the progression of amyloidosis involves the striatum in females to a greater extent than in males. These studies have significant implications for using male-only cohorts in the study of AD progression.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloidosis; Animals; Disease Models, Animal; Dopamine; Female; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Plaque, Amyloid

Mild Cognitive Impairment is Associated with Poorer Everyday Decision Making. - Fenton, Laura; Han, S Duke; DiGuiseppi, Carolyn G; Fowler, Nicole R; Hill, Linda; Johnson, Rachel L; Peterson, Ryan A; Knoepke, Christopher E; Matlock, Daniel D; Moran, Ryan; Karlawish, Jason; Betz, Marian E (J Alzheimers Dis, 2023)
BACKGROUND: Older adults are faced with many unique and highly consequential decisions such as those related to finances, healthcare, and everyday functioning (e.g., driving cessation). Given the significant impact of these decisions on independence, wellbeing, and safety, an understanding of how cognitive impairment may impact decision making in older age is important. OBJECTIVE: To examine the impact of mild cognitive impairment (MCI) on responses to a modified version of the Short Portable Assessment of Capacity for Everyday Decision making (SPACED). METHODS: Participants were community-dwelling, actively driving older adults (N = 301; M age = 77.1 years, SD = 5.1; 69.4% with a college degree or higher; 51.2% female; 95.3% White) enrolled in the Advancing Understanding of Transportation Options (AUTO) study. A generalized linear model adjusted for age, education, sex, randomization group, cognitive assessment method, and study site was used to examine the relationship between MCI status and decision making. RESULTS: MCI status was associated with poorer decision making; participants with MCI missed an average of 2.17 times more points on the SPACED than those without MCI (adjusted mean ratio: 2.17, 95% CI: 1.02, 4.61, p = 0.044). CONCLUSION: This finding supports the idea that older adults with MCI exhibit poorer decision-making abilities than cognitively normal older adults. It also suggests that older adults with MCI may exhibit poorer decision making across a wide range of decision contexts.
Keywords: Aged; Cognitive Dysfunction; Decision Making; Delivery of Health Care; Educational Status; Female; Humans; Independent Living; Male

Mortality Risks and Causes of Death by Dementia Types in a Japanese Cohort with Dementia: NCGG-STORIES. - Ono, Rei; Sakurai, Takashi; Sugimoto, Taiki; Uchida, Kazuaki; Nakagawa, Takeshi; Noguchi, Taiji; Komatsu, Ayane; Arai, Hidenori; Saito, Tami (J Alzheimers Dis, 2023)
BACKGROUND: Prognosis-related information regarding dementia needs to be updated, as changes in medical and long-term care environments for patients with dementia in recent decades may be improving the prognosis of the disease. OBJECTIVE: We aimed to investigate the mortality, cause of death, and prognostic factors by types of dementia in a Japanese clinic-based cohort. METHODS: The National Center for Geriatrics and Gerontology-Life Stories of People with Dementia consists of clinical records and prognostic data of patients who visited the Memory Clinic in Japan. Patients who attended the clinic between July 2010 and September 2018, or their close relatives, were asked about death information via a postal survey. A cohort of 3,229 patients (mean age, 76.9; female, 1,953) was classified into six groups: normal cognition (NC), mild cognitive impairment (MCI), Alzheimer's disease (AD), vascular dementia, dementia with Lewy bodies (DLB), and frontotemporal lobar degeneration. A Cox proportional hazards model was employed to compare the mortality of each type of dementia, MCI, and NC. RESULTS: Patients with all types of dementia and MCI had higher mortality rates than those with NC (hazard risks: 2.61-5.20). The most common cause of death was pneumonia, followed by cancer. In the MCI, AD, and DLB groups, older age, male sex, and low cognitive function were common prognostic factors but not presence of apolipoprotein E ɛ4 allele. CONCLUSION: Our findings suggest important differences in the mortality risk and cause of death among patients with dementia, which will be useful in advanced care planning and policymaking.
Keywords: Aged; Alzheimer Disease; Cause of Death; Cognitive Dysfunction; Dementia; East Asian People; Female; Humans; Lewy Body Disease; Male

Observed Improvement in Cognition During a Personalized Lifestyle Intervention in People with Cognitive Decline. - Sandison, Heather; Callan, Nini G L; Rao, Rammohan V; Phipps, John; Bradley, Ryan (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a chronic condition marked by progressive objective cognitive impairment (OCI). No monotherapy has substantially altered disease progression, suggesting the disease is multifactorial and may require a multimodal therapeutic approach. OBJECTIVE: We sought to determine if cognitive function in a sample with OCI would change in response to a multimodal, individualized care plan based on potential contributors to cognitive decline (e.g., nutritional status, infection, etc.). METHODS: Participants (n = 34) were recruited from the San Diego, CA area. The multimodal intervention included lifestyle changes (i.e., movement, diet, and stress management), nutraceutical support, and medications. It was delivered pragmatically over four clinical visits, and outcome measures were gathered at four study visits, occurring at baseline, one, three, and six months (primary endpoint). Study participants received weekly phone calls for nutrition support throughout study participation. Outcome measures included the Cambridge Brain Sciences (CBS) battery, and the Montreal Cognitive Assessment (MoCA). RESULTS: At 6 months, mean MoCA scores improved from 19.6±3.1 to 21.7±6.2 (p = 0.013). Significant improvement was observed in mean scores of the CBS memory domain [25.2 (SD 23.3) to 35.8 (SD 26.9); p < 0.01] and CBS overall composite cognition score [24.5 (SD 16.1) to 29.7 (SD 20.5); p = 0.02]. All CBS domains improved. CONCLUSION: Multiple measures of cognitive function improved after six months of intervention. Our results support the feasibility and impact of a multimodal, individualized treatment approach to OCI, warranting further research.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; California; Cognition; Cognitive Dysfunction; Diet, Healthy; Dietary Supplements; Disease Progression; Exercise; Feasibility Studies; Female; Healthy Lifestyle; Humans; Infections; Male; Memory; Middle Aged; Nutritional Status; Pragmatic Clinical Trials as Topic; Reproducibility of Results; Stress, Psychological; Time Factors; Treatment Outcome; Verbal Behavior

Psychopharmacological Medication Use in Frontotemporal Dementia at the Time of Diagnosis: Comparison with Alzheimer's Disease. - Katisko, Kasper; Krüger, Johanna; Soppela, Helmi; Hartikainen, Päivi; Haapasalo, Annakaisa; Remes, Anne M; Solje, Eino (J Alzheimers Dis, 2023)
BACKGROUND: Due to the significant presence of neuropsychiatric symptoms in patients with frontotemporal dementia (FTD) spectrum disorders, psychiatric misdiagnoses, diagnostic delay, and use of psychiatric treatments are common prior to the FTD diagnosis. Furthermore, treatment of diagnosed FTD patients mainly relies on off-label psychopharmacological approaches. Currently, limited real-world data are available regarding the actual use of psychopharmacological medications in FTD. OBJECTIVE: To evaluate psychopharmacological medication use at the time of FTD diagnosis. METHODS: Psychopharmacological medication use was evaluated in a Finnish FTD cohort containing 222 FTD patients, including the major clinical disease phenotypes (behavioral, language, and motor variants) and genetic patients carrying the C9orf72 repeat expansion. A cohort of 214 Alzheimer's disease (AD) patients was used as a neurodegenerative disease reference group. RESULTS: Active use of psychopharmacological medications at the time of diagnosis was significantly more common in FTD compared to AD, especially in the case of antidepressants (26.1% versus 15.0%, OR = 2.01, p = 0.008), antipsychotics (23.9% versus 9.3%, OR = 3.15, p < 0.001), and mood-stabilizers (6.3% versus 1.9%, OR = 2.93, p = 0.085; not statistically significant), whereas the use of cholinesterase inhibitors or memantine was nearly nonexistent in FTD patients. Female gender and behavioral variant of FTD phenotype alongside with depressive and psychotic symptoms were the most prominent factors associating with the use of these medications among the FTD spectrum patients. CONCLUSION: Use of off-label psychopharmacological medication and polypharmacy is substantially common at the time of FTD diagnosis. This likely reflects the challenges in using symptom-driven treatment approaches, especially prior to the eventual diagnosis.
Keywords: Alzheimer Disease; Delayed Diagnosis; Female; Frontotemporal Dementia; Humans; Memantine; Neurodegenerative Diseases

5-Hydroxymethylcytosine Signatures in Circulating Cell-Free DNA as Diagnostic Biomarkers for Late-Onset Alzheimer's Disease. - Chen, Lei; Shen, Qianqian; Xu, Shunliang; Yu, Hongzhuan; Pei, Shengjie; Zhang, Yangting; He, Xin; Wang, QiuZhen; Li, Duo (J Alzheimers Dis, 2022)
BACKGROUND: 5-Hydroxymethylcytosine (5hmC) is an epigenetic DNA modification that is highly abundant in central nervous system. It has been reported that DNA 5hmC dysregulation play a critical role in Alzheimer's disease (AD) pathology. Changes in 5hmC signatures can be detected in circulating cell-free DNA (cfDNA), which has shown potential as a non-invasive liquid biopsy material. OBJECTIVE: However, the genome-wide profiling of 5hmC in cfDNA and its potential for the diagnosis of AD has not been reported to date. METHODS: We carried out a case-control study and used a genome-wide chemical capture followed by high-throughput sequencing to detect the genome-wide profiles of 5hmC in human cfDNA and identified differentially hydroxymethylated regions (DhMRs) in late-onset AD patients and the control. RESULTS: We discovered significant differences of 5hmC enrichment in gene bodies which were linked to multiple AD pathogenesis-associated signaling pathways in AD patients compared with cognitively normal controls, indicating they can be well distinguished from normal controls by DhMRs in cfDNA. Specially, we identified 7 distinct genes (RABEP1, CPNE4, DNAJC15, REEP3, ROR1, CAMK1D, and RBFOX1) with predicting diagnostic potential based on their significant correlations with MMSE and MoCA scores of subjects. CONCLUSION: The present results suggest that 5hmC markers derived from plasma cfDNA can served as an effective, minimally invasive biomarkers for clinical auxiliary diagnosis of late-onset AD.
Keywords: 5-Methylcytosine; Aged; Alzheimer Disease; Biomarkers; Case-Control Studies; Cell-Free Nucleic Acids; DNA Methylation; DNA, Neoplasm; Epigenesis, Genetic; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged

Antihypertensive Medication Class and the Risk of Dementia and Cognitive Decline in Older Adults: A Secondary Analysis of the Prospective HELIAD Cohort. - Liampas, Ioannis; Hatzimanolis, Alex; Siokas, Vasileios; Yannakoulia, Mary; Kosmidis, Mary H; Sakka, Paraskevi; Hadjigeorgiou, Georgios M; Scarmeas, Nikolaos; Dardiotis, Efthimios (J Alzheimers Dis, 2022)
BACKGROUND: It is unclear whether the main antihypertensive medication classes (diuretics, calcium channel blockers, beta-blockers, angiotensin converting enzyme inhibitors, and angiotensin receptor blockers (ARBs)) are associated with different risks of cognitive decline. Published evidence is conflicting and stems mainly from observational studies. OBJECTIVE: To investigate the differential effects of antihypertensives on the risks of developing dementia and cognitive decline, with a specific focus on the vascular component of the mechanisms underlying these interactions. METHODS: Older adults with a history of hypertension and without dementia were drawn from the population-based HELIAD cohort. Age-, gender-, education-, and antihypertensive medication- (five dichotomous exposures) adjusted Cox proportional-hazards models and generalized estimating equations were performed to appraise the associations of baseline antihypertensive therapy with dementia incidence and cognitive decline (quantified using a comprehensive neuropsychological battery). Analyses were subsequently adjusted for clinical vascular risk (dyslipidemia, diabetes mellitus, smoking, cardiovascular, and cerebrovascular history) and genetic susceptibility to stroke (using polygenic risk scores generated according to the MEGASTROKE consortium GWAS findings). RESULTS: A total of 776 predominantly female participants (73.61±4.94 years) with hypertension and a mean follow-up of 3.02±0.82 years were analyzed. Baseline treatment was not associated with the risk of incident dementia. ARB users experienced a slower yearly global cognitive [2.5% of a SD, 95% CI = (0.1, 4.9)] and language [4.4% of a SD, 95% CI = (1.4, 7.4)] decline compared to non-users. The fully adjusted model reproduced similar associations for both global cognitive [β= 0.027, 95% CI =  (-0.003, 0.057)], and language decline [β= 0.063, 95% CI = (0.023, 0.104)]. CONCLUSION: ARBs may be superior to other antihypertensive agents in the preservation of cognition, an association probably mediated by vascular-independent mechanisms.
Keywords: Aged; Angiotensin Receptor Antagonists; Angiotensin-Converting Enzyme Inhibitors; Antihypertensive Agents; Calcium Channel Blockers; Cognitive Dysfunction; Dementia; Diuretics; Female; Humans; Hypertension; Male; Prospective Studies

Anti-Inflammatory Gene Therapy Improves Spatial Memory Performance in a Mouse Model of Alzheimer's Disease. - Yoo, Tai June (J Alzheimers Dis, 2022)
The immune system plays a critical role in neurodegenerative processes involved in Alzheimer's disease (AD). In this study, a gene-based immunotherapeutic method examined the effects of anti-inflammatory cellular immune response elements (CIREs) in the amyloid-β protein precursor (AβPP) mouse model. Bi-monthly intramuscular administration, beginning at either 4 or 6 months, and examined at 7.5 through 16 months, with plasmids encoding Interleukin (IL)-10, IL-4, TGF-β polynucleotides, or a combination thereof, into AβPP mice improved spatial memory performance. This work demonstrates an efficient gene therapy strategy to downregulate neuroinflammation, and possibly prevent or delay cognitive decline in AD.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Anti-Inflammatory Agents; Cognition; Disease Models, Animal; Female; Genetic Therapy; Immunity, Cellular; Immunotherapy; Injections, Intramuscular; Interleukin-10; Interleukin-4; Male; Mice; Mice, Transgenic; Spatial Memory

Association Between Serum Vitamins and the Risk of Alzheimer's Disease in Chinese Population. - Liu, Xi-Xi; Wu, Peng-Fei; Liu, Ying-Zi; Jiang, Ya-Ling; Wan, Mei-Dan; Xiao, Xue-Wen; Yang, Qi-Jie; Jiao, Bin; Liao, Xin-Xin; Wang, Jun-Ling; Liu, Shao-Hui; Zhang, Xuewei; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Alzheimer's disease (AD) is a chronic and fatal neurodegenerative disease; accumulating evidence suggests that vitamin deficiency is associated with the risk of AD. However, studies attempting to elucidate the relationship between vitamins and AD varied widely. OBJECTIVE: This study aimed to investigate the relationship between serum vitamin levels and AD in a cohort of the Chinese population. METHODS: A total of 368 AD patients and 574 healthy controls were recruited in this study; serum vitamin A, B1, B6, B9, B12, C, D, and E were measured in all participants. RESULTS: Compared with the controls, vitamin B2, B9, B12, D, and E were significantly reduced in AD patients. Lower levels of vitamin B2, B9, B12, D, and E were associated with the risk of AD. After adjusting for age and gender, low levels of vitamin B2, B9, and B12 were still related to the risk of AD. In addition, a negative correlation was determined between vitamin E concentration and Activity of Daily Living Scale score while no significant association was found between serum vitamins and age at onset, disease duration, Mini-Mental State Examination, and Neuropsychiatric Inventory Questionnaire score. CONCLUSION: We conclude that lower vitamin B2, B9, B12, D, and E might be associated with the risk of AD, especially vitamin B2, B9, and B12. And lower vitamin E might be related to severe ability impairment of daily activities.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Case-Control Studies; China; Female; Folic Acid; Humans; Logistic Models; Male; Mental Status and Dementia Tests; Middle Aged; Riboflavin; Risk; Vitamin B 12; Vitamin D; Vitamin E

Association of Cholinergic Basal Forebrain Volume and Functional Connectivity with Markers of Inflammatory Response in the Alzheimer's Disease Spectrum. - Teipel, Stefan J; Dyrba, Martin; Ballarini, Tommaso; Brosseron, Frederic; Bruno, Davide; Buerger, Katharina; Cosma, Nicoleta-Carmen; Dechent, Peter; Dobisch, Laura; Düzel, Emrah; Ewers, Michael; Fliessbach, Klaus; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Inflammation has been described as a key pathogenic event in Alzheimer's disease (AD), downstream of amyloid and tau pathology. Preclinical and clinical data suggest that the cholinergic basal forebrain may moderate inflammatory response to different pathologies. OBJECTIVE: To study the association of cholinergic basal forebrain volume and functional connectivity with measures of neuroinflammation in people from the AD spectrum. METHODS: We studied 261 cases from the DELCODE cohort, including people with subjective cognitive decline, mild cognitive impairment, AD dementia, first degree relatives, and healthy controls. Using Bayesian ANCOVA, we tested associations of MRI indices of cholinergic basal forebrain volume and functional connectivity with cerebrospinal fluid (CSF) levels of sTREM2 as a marker of microglia activation, and serum levels of complement C3. Using Bayesian elastic net regression, we determined associations between basal forebrain measures and a large inflammation marker panel from CSF and serum. RESULTS: We found anecdotal to moderate evidence in favor of the absence of an effect of basal forebrain volume and functional connectivity on CSF sTREM2 and serum C3 levels both in Aβ42/ptau-positive and negative cases. Bayesian elastic net regression identified several CSF and serum markers of inflammation that were associated with basal forebrain volume and functional connectivity. The effect sizes were moderate to small. CONCLUSION: Our data-driven analyses generate the hypothesis that cholinergic basal forebrain may be involved in the neuroinflammation response to Aβ42 and phospho-tau pathology in people from the AD spectrum. This hypothesis needs to be tested in independent samples.
Keywords: Aged; Alzheimer Disease; Basal Forebrain; Biomarkers; Cholinergic Agents; Cognitive Dysfunction; Cohort Studies; Female; Humans; Inflammation; Magnetic Resonance Imaging; Male

Association of COVID-19 with New-Onset Alzheimer's Disease. - Wang, Lindsey; Davis, Pamela B; Volkow, Nora D; Berger, Nathan A; Kaelber, David C; Xu, Rong (J Alzheimers Dis, 2022)
An infectious etiology of Alzheimer's disease has been postulated for decades. It remains unknown whether SARS-CoV-2 viral infection is associated with increased risk for Alzheimer's disease. In this retrospective cohort study of 6,245,282 older adults (age ≥65 years) who had medical encounters between 2/2020-5/2021, we show that people with COVID-19 were at significantly increased risk for new diagnosis of Alzheimer's disease within 360 days after the initial COVID-19 diagnosis (hazard ratio or HR:1.69, 95% CI: 1.53-1.72), especially in people age ≥85 years and in women. Our findings call for research to understand the underlying mechanisms and for continuous surveillance of long-term impacts of COVID-19 on Alzheimer's disease.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; COVID-19; COVID-19 Testing; Female; Humans; Retrospective Studies; SARS-CoV-2

"Captive by the Uncertainty"-Experiences with Anticipatory Guidance for People Living with Dementia and Their Caregivers at a Specialty Dementia Clinic. - Shafir, Adi; Ritchie, Christine S; Garrett, Sarah B; Bernstein Sideman, Alissa; Naasan, Georges; Merrilees, Jennifer; Widera, Eric; Flint, Lynn; Harrison, Krista L (J Alzheimers Dis, 2022)
BACKGROUND: After a diagnosis of Alzheimer's disease and related disorders, people living with dementia (PWD) and caregivers wonder what disease trajectory to expect and how to plan for functional and cognitive decline. This qualitative study aimed to identify patient and caregiver experiences receiving anticipatory guidance about dementia from a specialty dementia clinic. OBJECTIVE: To examine PWD and caregiver perspectives on receiving anticipatory guidance from a specialty dementia clinic. METHODS: We conducted semi-structured interviews with PWD, and active and bereaved family caregivers, recruited from a specialty dementia clinic. Interviews were recorded, transcribed, and systematically summarized. Thematic analysis identified anticipatory guidance received from clinical or non-clinical sources and areas where respondents wanted additional guidance. RESULTS: Of 40 participants, 9 were PWD, 16 were active caregivers, and 15 were bereaved caregivers. PWD had a mean age of 75 and were primarily male (n = 6/9); caregivers had a mean age of 67 and were primarily female (n = 21/31). Participants felt they received incomplete or "hesitant" guidance on prognosis and expected disease course via their clinicians and filled the gap with information they found via the internet, books, and support groups. They appreciated guidance on behavioral, safety, and communication issues from clinicians, but found more timely and advance guidance from other non-clinical sources. Guidance on legal and financial planning was primarily identified through non-clinical sources. CONCLUSION: PWD and caregivers want more information about expected disease course, prognosis, and help planning after diagnosis. Clinicians have an opportunity to improve anticipatory guidance communication and subsequent care provision.
Keywords: Aged; Alzheimer Disease; Caregivers; Dementia; Female; Humans; Male; Qualitative Research; Uncertainty

Caregiver Tele-Assistance for Reduction of Emotional Distress During the COVID-19 Pandemic. Psychological Support to Caregivers of People with Dementia: The Italian Experience. - Rotondo, Emanuela; Galimberti, Daniela; Mercurio, Matteo; Giardinieri, Giulia; Forti, Sara; Vimercati, Roberto; Borracci, Vittoria; Fumagalli, Giorgio G; Pietroboni, Anna M; Carandini, Tiziana; Nobili, Alessandro; Scarpini, Elio; et al. (J Alzheimers Dis, 2022)
BACKGROUND: COVID-19 pandemic worsened vulnerability of patients with dementia (PWD). This new reality associated with government restriction and isolation worsened stress burden and psychological frailties in PWD caregivers. OBJECTIVE: To give tele-psychological support to caregivers and evaluate the effect of this intervention by quantifying stress burden and quality of life during the first COVID-19 lockdown. METHODS: 50 caregivers were divided into two groups: "Caregiver-focused group" (Cg) and "Patient-focused group" (Pg). Both groups received telephone contact every 2 weeks over a 28-week period, but the content of the call was different: in Cg, caregivers answered questions about the state of the PWD but also explored their own emotional state, stress burden, and quality of life. In Pg instead, telephone contacts were focused only on the PWD, and no evaluation regarding the caregiver mood or state of stress was made. Psychometric scales were administered to evaluate COVID-19 impact, stress burden, and quality of life. RESULTS: Considering the time of intervention, from baseline (W0) to W28, Zarit Burden Interview and Quality of Life-caregiver questionnaires remained unchanged in Cg as compared with baseline (p > 0.05), whereas they worsened significantly in Pg (p < 0.01), showing increased stress over time and decreased quality of life in this group. Moreover, Impact on Event Scale values improved over the weeks in Cg (p = 0.015), while they remained unchanged in Pg (p = 0.483). CONCLUSION: Caregivers who received telephone support about their mood and stress burden did not worsen their psychological state during the time of intervention, as did instead those who did not get such support.
Keywords: Aged; Aged, 80 and over; Caregiver Burden; Caregivers; COVID-19; Dementia; Female; Humans; Italy; Male; Middle Aged; Psychological Distress; Psychosocial Support Systems; Quality of Life; Surveys and Questionnaires; Telephone

Cognitive Decline Risk Stratification in People with Late-Onset Epilepsy of Unknown Etiology: An Electroencephalographic Connectivity and Graph Theory Pilot Study. - Costa, Cinzia; Vecchio, Fabrizio; Romoli, Michele; Miraglia, Francesca; Nardi Cesarini, Elena; Alù, Francesca; Calabresi, Paolo; Rossini, Paolo Maria (J Alzheimers Dis, 2022)
BACKGROUND: Although people with late onset epilepsy of unknown etiology (LOEU) are at higher risk of cognitive decline compared to the general population, we still lack affordable tools to predict and stratify their risk of dementia. OBJECTIVE: This pilot-study investigates the potential application of electroencephalography (EEG) network small-world (SW) properties in predicting cognitive decline among patients with LOEU. METHODS: People diagnosed with LOEU and normal cognitive examination at the time of epilepsy diagnosis were included. Cerebrospinal fluid biomarkers, brain imaging, and neuropsychological assessment were performed at the time of epilepsy diagnosis. Baseline EEG was analyzed for SW properties. Patients were followed-up over time with neuropsychological testing to define the trajectory of cognitive decline. RESULTS: Over 5.1 years of follow-up, among 24 patients diagnosed with LOEU, 62.5% were female, mean age was 65.3 years, thirteen developed mild cognitive impairment (MCI), and four developed dementia. Patients with LOEU developing MCI had lower values of SW coefficients in the delta (p = 0.03) band and higher SW values in the alpha frequency bands (p = 0.02) compared to patients having normal cognition at last follow-up. The two separate ANOVAs, for low and alpha bands, confirmed an interaction between SW and cognitive decline at follow-up. A similar gradient was confirmed for patients developing dementia compared to those with normal cognitive function as well as to those developing MCI. CONCLUSION: Baseline EEG analysis through SW is worth investigating as an affordable, widely available tool to stratify LOEU patients for their risk of cognitive decline.
Keywords: Aged; Cognitive Dysfunction; Dementia; Electroencephalography; Epilepsy; Female; Humans; Male; Neuropsychological Tests; Pilot Projects; Risk Assessment

A Comparison of Behavioral and Psychological Symptoms of Dementia (BPSD) and BPSD Sub-Syndromes in Early-Onset and Late-Onset Alzheimer's Disease. - Altomari, Natalia; Bruno, Francesco; Laganà, Valentina; Smirne, Nicoletta; Colao, Rosanna; Curcio, Sabrina; Di Lorenzo, Raffaele; Frangipane, Francesca; Maletta, Raffaele; Puccio, Gianfranco; Bruni, Amalia Cecilia (J Alzheimers Dis, 2022)
BACKGROUND: Behavioral and psychological symptoms of dementia (BPSD) have a large impact on the quality of life of patients with Alzheimer's disease (AD). Few studies have compared BPSD between early-onset (EOAD) and late-onset (LOAD) patients, finding conflicting results. OBJECTIVE: The aims of this study were to: 1) characterize the presence, overall prevalence, and time of occurrence of BPSD in EOAD versus LOAD; 2) estimate the prevalence over time and severity of each BPSD in EOAD versus LOAD in three stages: pre-T0 (before the onset of the disease), T0 (from onset to 5 years), and T1 (from 5 years onwards); 3) track the manifestation of BPSD sub-syndromes (i.e., hyperactivity, psychosis, affective, and apathy) in EOAD versus LOAD at T0 and T1. METHODS: The sample includes 1,538 LOAD and 387 EOAD diagnosed from 1996 to 2018. Comprehensive assessment batteries, including the Neuropsychiatric Inventory (NPI), were administered at the first medical assessment and at different follow-up period. RESULTS: The overall prevalence for the most of BPSD was significantly higher in EOAD compared to LOAD whereas most BPSD appeared significantly later in EOAD patients. Between the two groups, from pre-T0 to T1 we recorded a different pattern of BPSD prevalence over time as well as for BPSD sub-syndromes at T0 and T1. Results on severity of BPSD did not show significant differences. CONCLUSION: EOAD and LOAD represent two different forms of a single entity not only from a neuropathological, cognitive, and functional level but also from a psychiatric point of view.
Keywords: Affective Symptoms; Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Apathy; Behavioral Symptoms; Dementia; Female; Humans; Italy; Male; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Psychomotor Agitation; Psychotic Disorders; Severity of Illness Index

The Correlation of Tau Levels with Blood Monocyte Count in Patients with Alzheimer's Disease. - Sun, Hao-Lun; Zhou, Fa-Ying; Chen, Dong-Wan; Tan, Cheng-Rong; Zeng, Gui-Hua; Liu, Yu-Hui; Wang, Jun; Bu, Xian-Le; Wang, Yan-Jiang; Li, Hui-Yun; Jin, Wang-Sheng (J Alzheimers Dis, 2022)
BACKGROUND: Recent studies have shown that monocytes can phagocytize the tau protein, which may ameliorate tau-type pathology in Alzheimer's disease (AD). However, there are few clinical studies on the relationship between monocytes and tau-type pathology in AD patients. OBJECTIVE: We aimed to explore changes in peripheral monocytes and their association with tau protein in AD patients. METHODS: A total of 127 clinically diagnosed AD patients and 100 age- and sex-matched cognitively normal controls were recruited for analysis of the correlation of plasma tau levels with the blood monocyte count. Cerebrospinal fluid (CSF) samples from 46 AD patients and 88 controls were further collected to analyze the correlation of CSF tau and amyloid-β (Aβ) levels with the blood monocyte count. 105 clinically diagnosed mild cognitive impairment (MCI) patients and 149 age- and sex-matched cognitively normal controls were recruited from another cohort for verification. RESULTS: Compared to normal controls, AD patients showed a significant reduction in the blood monocyte count. In addition, the monocyte count of AD patients was negatively correlated with CSF t-tau and p-tau levels but not with plasma tau levels. In normal people, monocyte count lack correlation with tau levels both in plasma and CSF. Monocyte count were not correlated with CSF Aβ levels in either group but were negatively correlated with CSF tau/Aβ42 levels in the AD group. We had further verified the correlations of monocyte count with CSF tau levels in another cohort. CONCLUSION: This study suggests that monocytes may play an important role in the clearance of tau protein in the brain.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Cohort Studies; Female; Humans; Male; Monocytes; tau Proteins

Impact of COVID-19 on 'Living Well' with Mild-to-Moderate Dementia in the Community: Findings from the IDEAL Cohort. - Clare, Linda; Martyr, Anthony; Gamble, Laura D; Pentecost, Claire; Collins, Rachel; Dawson, Eleanor; Hunt, Anna; Parker, Sophie; Allan, Louise; Burns, Alistair; Hillman, Alexandra; Litherland, Rachael; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Negative impacts of the COVID-19 pandemic on people with dementia have been widely-documented, but most studies have relied on carer reports and few have compared responses to information collected before the pandemic. OBJECTIVE: We aimed to explore the impact of the pandemic on community-dwelling individuals with mild-to-moderate dementia and compare responses with pre-pandemic data. METHODS: During the second wave of the pandemic, we conducted structured telephone interviews with 173 people with dementia and 242 carers acting as informants, all of whom had previously participated in the IDEAL cohort. Where possible, we benchmarked responses against pre-pandemic data. RESULTS: Significant perceived negative impacts were identified in cognitive and functional skills and ability to engage in self-care and manage everyday activities, along with increased levels of loneliness and discontinuity in sense of self and a decline in perceived capability to 'live well'. Compared to pre-pandemic data, there were lower levels of pain, depression, and anxiety, higher levels of optimism, and better satisfaction with family support. There was little impact on physical health, mood, social connections and relationships, or perceptions of neighborhood characteristics. CONCLUSION: Efforts to mitigate negative impacts of pandemic-related restrictions and restore quality of life could focus on reablement to address the effects on participation in everyday activities, creating opportunities for social contact to reduce loneliness, and personalized planning to reconnect people with their pre-COVID selves. Such efforts may build on the resilience demonstrated by people with dementia and carers in coping with the pandemic.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Caregivers; COVID-19; Dementia; Female; Humans; Male; Middle Aged; Neighborhood Characteristics; Quality of Life; SARS-CoV-2

Rheumatoid Arthritis, Cognitive Impairment, and Neuroimaging Biomarkers: Results from the Mayo Clinic Study of Aging. - Vassilaki, Maria; Crowson, Cynthia S; Davis Iii, John M; Duong, Stephanie Q; Jones, David T; Nguyen, Aivi; Mielke, Michelle M; Vemuri, Prashanthi; Myasoedova, Elena (J Alzheimers Dis, 2022)
BACKGROUND: Observational studies suggested that dementia risk in patients with rheumatoid arthritis (RA) is higher than in the general population. OBJECTIVE: To examine the associations of RA with cognitive decline and dementia, and neuroimaging biomarkers of aging, Alzheimer's disease, and vascular pathology in adult participants in the Mayo Clinic Study of Aging (MCSA). METHODS: Participants with RA were matched 1:3 on age, sex, education, and baseline cognitive diagnosis to participants without RA. RA cases with MRI were also matched with non-cases with available MRI. All available imaging studies (i.e., amyloid and FDG PET, sMRI, and FLAIR) were included. The study included 104 participants with RA and 312 without RA (mean age (standard deviation, SD) 75.0 (10.4) years, 33% male and average follow-up (SD) 4.2 (3.8) years). RESULTS: Groups were similar in cognitive decline and risk of incident dementia. Among participants with neuroimaging, participants with RA (n = 33) and without RA (n = 98) had similar amyloid burden and neurodegeneration measures, including regions sensitive to aging and dementia, but greater mean white matter hyperintensity volume relative to the total intracranial volume (mean (SD)% : 1.12 (0.57)% versus 0.76 (0.69)% of TIV, p = 0.01), and had higher mean (SD) number of cortical infarctions (0.24 (0.44) versus 0.05 (0.33), p = 0.02). CONCLUSION: Although cognitive decline and dementia risk were similar in participants with and without RA, participants with RA had more abnormal cerebrovascular pathology on neuroimaging. Future studies should examine the mechanisms underlying these changes and potential implications for prognostication and prevention of cognitive decline in RA.
Keywords: Aged; Aging; Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidosis; Arthritis, Rheumatoid; Biomarkers; Brain; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Neuroimaging; Positron-Emission Tomography

Risk of Alzheimer's Disease Following Influenza Vaccination: A Claims-Based Cohort Study Using Propensity Score Matching. - Bukhbinder, Avram S; Ling, Yaobin; Hasan, Omar; Jiang, Xiaoqian; Kim, Yejin; Phelps, Kamal N; Schmandt, Rosemarie E; Amran, Albert; Coburn, Ryan; Ramesh, Srivathsan; Xiao, Qian; Schulz, Paul E (J Alzheimers Dis, 2022)
BACKGROUND: Prior studies have found a reduced risk of dementia of any etiology following influenza vaccination in selected populations, including veterans and patients with serious chronic health conditions. However, the effect of influenza vaccination on Alzheimer's disease (AD) risk in a general cohort of older US adults has not been characterized. OBJECTIVE: To compare the risk of incident AD between patients with and without prior influenza vaccination in a large US claims database. METHODS: Deidentified claims data spanning September 1, 2009 through August 31, 2019 were used. Eligible patients were free of dementia during the 6-year look-back period and≥65 years old by the start of follow-up. Propensity-score matching (PSM) was used to create flu-vaccinated and flu-unvaccinated cohorts with similar baseline demographics, medication usage, and comorbidities. Relative risk (RR) and absolute risk reduction (ARR) were estimated to assess the effect of influenza vaccination on AD risk during the 4-year follow-up. RESULTS: From the unmatched sample of eligible patients (n = 2,356,479), PSM produced a sample of 935,887 flu-vaccinated-unvaccinated matched pairs. The matched sample was 73.7 (SD, 8.7) years of age and 56.9% female, with median follow-up of 46 (IQR, 29-48) months; 5.1% (n = 47,889) of the flu-vaccinated patients and 8.5% (n = 79,630) of the flu-unvaccinated patients developed AD during follow-up. The RR was 0.60 (95% CI, 0.59-0.61) and ARR was 0.034 (95% CI, 0.033-0.035), corresponding to a number needed to treat of 29.4. CONCLUSION: This study demonstrates that influenza vaccination is associated with reduced AD risk in a nationwide sample of US adults aged 65 and older.
Keywords: Adult; Aged; Alzheimer Disease; Chronic Disease; Cohort Studies; Female; Humans; Influenza, Human; Male; Middle Aged; Propensity Score; Vaccination

Sex Differences in Behavior and Molecular Pathology in the 5XFAD Model. - Sil, Annesha; Erfani, Arina; Lamb, Nicola; Copland, Rachel; Riedel, Gernot; Platt, Bettina (J Alzheimers Dis, 2022)
BACKGROUND: The prevalence of Alzheimer's disease (AD) is greater in women compared to men, but the reasons for this remain unknown. This sex difference has been widely neglected in experimental studies using transgenic mouse models of AD. OBJECTIVE: Here, we studied behavior and molecular pathology of 5-month-old 5XFAD mice, which express mutated human amyloid precursor protein and presenilin-1 on a C57BL/6J background, versus their wild-type littermate controls, to compare both sex- and genotype-dependent differences. METHODS: A novel behavioral paradigm was utilized (OF-NO-SI), comprising activity measures (Open Field, OF) arena, followed by Novel Object exploration (NO) and Social Interaction (SI) of a sex-matched conspecific. Each segment consisted of two repeated trials to assess between-trial habituation. Subsequently, brain pathology (amyloid load, stress response and inflammation markers, synaptic integrity, trophic support) was assessed using qPCR and western blotting. RESULTS: Female 5XFAD mice had higher levels of human APP and amyloid-β and heightened inflammation versus males. These markers correlated with hyperactivity observed in both sexes, yet only female 5XFAD mice presented with subtle deficits in object and social exploration. Male animals had higher expression of stress markers and neurotrophic factors irrespective of genotype, this correlated with cognitive performance. CONCLUSION: The impact of sex on AD-relevant phenotypes is in line with human data and emphasizes the necessity of appropriate study design and reporting. Differential molecular profiles observed in male versus female mice offer insights into possible protective mechanisms, and hence treatment strategies.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Disease Models, Animal; Female; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Pathology, Molecular; Presenilin-1; Sex Characteristics

ANMerge: A Comprehensive and Accessible Alzheimer's Disease Patient-Level Dataset. - Birkenbihl, Colin; Westwood, Sarah; Shi, Liu; Nevado-Holgado, Alejo; Westman, Eric; Lovestone, Simon; Hofmann-Apitius, Martin (J Alzheimers Dis, 2021)
BACKGROUND: Accessible datasets are of fundamental importance to the advancement of Alzheimer's disease (AD) research. The AddNeuroMed consortium conducted a longitudinal observational cohort study with the aim to discover AD biomarkers. During this study, a broad selection of data modalities was measured including clinical assessments, magnetic resonance imaging, genotyping, transcriptomic profiling, and blood plasma proteomics. Some of the collected data were shared with third-party researchers. However, this data was incomplete, erroneous, and lacking in interoperability. OBJECTIVE: To provide the research community with an accessible, multimodal, patient-level AD cohort dataset. METHODS: We systematically addressed several limitations of the originally shared resources and provided additional unreleased data to enhance the dataset. RESULTS: In this work, we publish and describe ANMerge, a new version of the AddNeuroMed dataset. ANMerge includes multimodal data from 1,702 study participants and is accessible to the research community via a centralized portal. CONCLUSION: ANMerge is an information rich patient-level data resource that can serve as a discovery and validation cohort for data-driven AD research, such as, for example, machine learning and artificial intelligence approaches.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Datasets as Topic; Female; Gene Expression Profiling; Genotype; Humans; Magnetic Resonance Imaging; Male; Proteomics

APOE4 Copy Number-Dependent Proteomic Changes in the Cerebrospinal Fluid. - Berger, Miles; Cooter, Mary; Roesler, Alexander S; Chung, Stacey; Park, John; Modliszewski, Jennifer L; VanDusen, Keith W; Thompson, J Will; Moseley, Arthur; Devinney, Michael J; Smani, Shayan; Hall, Ashley; et al. (J Alzheimers Dis, 2021)
BACKGROUND: APOE4 has been hypothesized to increase Alzheimer's disease risk by increasing neuroinflammation, though the specific neuroinflammatory pathways involved are unclear. OBJECTIVE: Characterize cerebrospinal fluid (CSF) proteomic changes related to APOE4 copy number. METHODS: We analyzed targeted proteomic data from ADNI CSF samples using a linear regression model adjusting for age, sex, and APOE4 copy number, and additional linear models also adjusting for AD clinical status or for CSF Aβ, tau, or p-tau levels. False discovery rate was used to correct for multiple comparisons correction. RESULTS: Increasing APOE4 copy number was associated with a significant decrease in a CRP peptide level across all five models (q < 0.05 for each), and with significant increases in ALDOA, CH3L1 (YKL-40), and FABPH peptide levels (q < 0.05 for each) except when controlling for AD clinical status or neurodegeneration biomarkers (i.e., CSF tau or p-tau). In all models except the one controlling for CSF Aβ levels, though not statistically significant, there was a consistent inverse direction of association between APOE4 copy number and the levels of all 24 peptides from all 8 different complement proteins measured. The odds of this happening by chance for 24 unrelated peptides would be less than 1 in 16 million. CONCLUSION: Increasing APOE4 copy number was associated with decreased CSF CRP levels across all models, and increased CSF ALDOA, CH3L1, and FABH levels when controlling for CSF Aβ levels. Increased APOE4 copy number may also be associated with decreased CSF complement pathway protein levels, a hypothesis for investigation in future studies.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Chitinase-3-Like Protein 1; DNA Copy Number Variations; Female; Fructose-Bisphosphate Aldolase; Humans; Male; Proteomics; Receptors, Immunologic

Automatic Subtyping of Individuals with Primary Progressive Aphasia. - Themistocleous, Charalambos; Ficek, Bronte; Webster, Kimberly; den Ouden, Dirk-Bart; Hillis, Argye E; Tsapkini, Kyrana (J Alzheimers Dis, 2021)
BACKGROUND: The classification of patients with primary progressive aphasia (PPA) into variants is time-consuming, costly, and requires combined expertise by clinical neurologists, neuropsychologists, speech pathologists, and radiologists. OBJECTIVE: The aim of the present study is to determine whether acoustic and linguistic variables provide accurate classification of PPA patients into one of three variants: nonfluent PPA, semantic PPA, and logopenic PPA. METHODS: In this paper, we present a machine learning model based on deep neural networks (DNN) for the subtyping of patients with PPA into three main variants, using combined acoustic and linguistic information elicited automatically via acoustic and linguistic analysis. The performance of the DNN was compared to the classification accuracy of Random Forests, Support Vector Machines, and Decision Trees, as well as to expert clinicians' classifications. RESULTS: The DNN model outperformed the other machine learning models as well as expert clinicians' classifications with 80% classification accuracy. Importantly, 90% of patients with nfvPPA and 95% of patients with lvPPA was identified correctly, providing reliable subtyping of these patients into their corresponding PPA variants. CONCLUSION: We show that the combined speech and language markers from connected speech productions can inform variant subtyping in patients with PPA. The end-to-end automated machine learning approach we present can enable clinicians and researchers to provide an easy, quick, and inexpensive classification of patients with PPA.
Keywords: Acoustics; Aged; Aphasia, Primary Progressive; Decision Trees; Female; Humans; Linguistics; Machine Learning; Male; Models, Theoretical; Neural Networks, Computer; Primary Progressive Nonfluent Aphasia; Reproducibility of Results; Support Vector Machine

The Behavioral and Psychological Symptoms of Dementia in Down Syndrome Scale (BPSD-DS II): Optimization and Further Validation. - Dekker, Alain D; Ulgiati, Aurora M; Groen, Henk; Boxelaar, Vincent A; Sacco, Silvia; Falquero, Ségolène; Carfi, Angelo; di Paola, Antonella; Benejam, Bessy; Valldeneu, Silvia; Fopma, Roelie; Oosterik, Marjo; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with Down syndrome (DS) are at high risk to develop Alzheimer's disease dementia (AD). Behavioral and psychological symptoms of dementia (BPSD) are common and may also serve as early signals for dementia. However, comprehensive evaluation scales for BPSD, adapted to DS, are lacking. Therefore, we previously developed the BPSD-DS scale to identify behavioral changes between the last six months and pre-existing life-long characteristic behavior. OBJECTIVE: To optimize and further study the scale (discriminative ability and reliability) in a large representative DS study population. METHODS: Optimization was based on item irrelevance and clinical experiences obtained in the initial study. Using the shortened and refined BPSD-DS II, informant interviews were conducted to evaluate 524 individuals with DS grouped according to dementia status: no dementia (DS, N = 292), questionable dementia (DS + Q, N = 119), and clinically diagnosed dementia (DS + AD, N = 113). RESULTS: Comparing item change scores between groups revealed prominent changes in frequency and severity for anxious, sleep-related, irritable, restless/stereotypic, apathetic, depressive, and eating/drinking behavior. For most items, the proportion of individuals displaying an increased frequency was highest in DS + AD, intermediate in DS + Q, and lowest in DS. For various items within sections about anxious, sleep-related, irritable, apathetic, and depressive behaviors, the proportion of individuals showing an increased frequency was already substantial in DS + Q, suggesting that these changes may serve as early signals of AD in DS. Reliability data were promising. CONCLUSION: The optimized scale yields largely similar results as obtained with the initial version. Systematically evaluating BPSD in DS may increase understanding of changes among caregivers and (timely) adaptation of care/treatment.
Keywords: Adult; Aged; Anxiety; Dementia; Down Syndrome; Female; Humans; Irritable Mood; Male; Middle Aged; Reproducibility of Results; Symptom Assessment

Cognition at Each Stage of Lewy Body Disease with Co-occurring Alzheimer's Disease Pathology. - Ryman, Sephira G; Yutsis, Maya; Tian, Lu; Henderson, Victor W; Montine, Thomas J; Salmon, David P; Galasko, Douglas; Poston, Kathleen L (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease neuropathologic change (ADNC) may contribute to dementia in patients with Lewy body disease (LBD) pathology. OBJECTIVE: To examine how co-occurring ADNC impacts domain specific cognitive impairments at each pathologic stage (brainstem, limbic, cerebral cortical) of LBD. METHODS: 2,433 participants with antemortem longitudinal neuropsychological assessment and postmortem neuropathological assessment from the National Alzheimer's Coordinating Center's Uniform Data Set were characterized based on the evaluation of ADNC and LBD. Longitudinal mixed-models were used to derive measures of cumulative cognitive deficit for each cognitive domain at each pathologic stage of LBD (brainstem, limbic, and cerebral cortical). RESULTS: 111 participants with a pathologic diagnosis of LBD, 741 participants with combined LBD and ADNC, 1,357 participants with ADNC only, and 224 with no pathology (healthy controls) were included in the analyses. In the executive/visuospatial domain, combined LBD and ADNC showed worse deficits than LBD only when Lewy bodies were confined to the brainstem, but no difference when Lewy bodies extended to the limbic or cerebral cortical regions. The cerebral cortical LBD only group exhibited greater executive/visuospatial deficits than the ADNC only group. By contrast, the ADNC only group and the combined pathology group both demonstrated significantly greater cumulative memory deficits relative to Lewy body disease only, regardless of stage. CONCLUSION: The impact of co-occurring ADNC on antemortem cumulative cognitive deficits varies not only by domain but also on the pathological stage of Lewy bodies. Our findings stress the cognitive impact of different patterns of neuropathological progression in Lewy body diseases.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cognitive Dysfunction; Female; Humans; Lewy Body Disease; Male

Cognitive Effects of the BET Protein Inhibitor Apabetalone: A Prespecified Montreal Cognitive Assessment Analysis Nested in the BETonMACE Randomized Controlled Trial. - Cummings, Jeffrey; Schwartz, Gregory G; Nicholls, Stephen J; Khan, Aziz; Halliday, Chris; Toth, Peter P; Sweeney, Michael; Johansson, Jan O; Wong, Norman C W; Kulikowski, Ewelina; Kalantar-Zadeh, Kamyar; Lebioda, Kenneth; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Epigenetic changes may contribute importantly to cognitive decline in late life including Alzheimer's disease (AD) and vascular dementia (VaD). Bromodomain and extra-terminal (BET) proteins are epigenetic "readers" that may distort normal gene expression and contribute to chronic disorders. OBJECTIVE: To assess the effects of apabetalone, a small molecule BET protein inhibitor, on cognitive performance of patients 70 years or older participating in a randomized trial of patients at high risk for major cardiovascular events (MACE). METHODS: The Montreal Cognitive Assessment (MoCA) was performed on all patients 70 years or older at the time of randomization. 464 participants were randomized to apabetalone or placebo in the cognition sub-study. In a prespecified analysis, participants were assigned to one of three groups: MoCA score≥26 (normal performance), MoCA score 25-22 (mild cognitive impairment), and MoCA score≤21 (dementia). Exposure to apabetalone was equivalent in the treatment groups in each MoCA-defined group. RESULTS: Apabetalone was associated with an increased total MoCA score in participants with baseline MoCA score of≤21 (p = 0.02). There was no significant difference in change from baseline in the treatment groups with higher MoCA scores. In the cognition study, more patients randomized to apabetalone discontinued study drug for adverse effects (11.3% versus 7.9%). CONCLUSION: In this randomized controlled study, apabetalone was associated with improved cognition as measured by MoCA scores in those with baseline scores of 21 or less. BET protein inhibitors warrant further investigation for late life cognitive disorders.
Keywords: Aged; Cardiovascular Diseases; Cognitive Dysfunction; Epigenesis, Genetic; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Quinazolinones

Combining Multimodal Behavioral Data of Gait, Speech, and Drawing for Classification of Alzheimer's Disease and Mild Cognitive Impairment. - Yamada, Yasunori; Shinkawa, Kaoru; Kobayashi, Masatomo; Caggiano, Vittorio; Nemoto, Miyuki; Nemoto, Kiyotaka; Arai, Tetsuaki (J Alzheimers Dis, 2021)
BACKGROUND: Gait, speech, and drawing behaviors have been shown to be sensitive to the diagnosis of Alzheimer's disease (AD) and mild cognitive impairment (MCI). However, previous studies focused on only analyzing individual behavioral modalities, although these studies suggested that each of these modalities may capture different profiles of cognitive impairments associated with AD. OBJECTIVE: We aimed to investigate if combining behavioral data of gait, speech, and drawing can improve classification performance compared with the use of individual modality and if each of these behavioral data can be associated with different cognitive and clinical measures for the diagnosis of AD and MCI. METHODS: Behavioral data of gait, speech, and drawing were acquired from 118 AD, MCI, and cognitively normal (CN) participants. RESULTS: Combining all three behavioral modalities achieved 93.0% accuracy for classifying AD, MCI, and CN, and only 81.9% when using the best individual behavioral modality. Each of these behavioral modalities was statistically significantly associated with different cognitive and clinical measures for diagnosing AD and MCI. CONCLUSION: Our findings indicate that these behaviors provide different and complementary information about cognitive impairments such that classification of AD and MCI is superior to using either in isolation.
Keywords: Aged; Alzheimer Disease; Cognitive Dysfunction; Female; Gait; Humans; Male; Neuropsychological Tests; Speech

Could Altered Evoked Pain Responsiveness Be a Phenotypic Biomarker for Alzheimer's Disease Risk? A Cross-Sectional Analysis of Cognitively Healthy Individuals. - Romano, Raymond R; Carter, Michael A; Dietrich, Mary S; Cowan, Ronald L; Bruehl, Stephen P; Monroe, Todd B (J Alzheimers Dis, 2021)
BACKGROUND: This study evaluated whether the apolipoprotein ɛ4 (APOE4) allele, a genetic marker associated with increased risk of developing late-onset Alzheimer's disease (AD), was associated with differences in evoked pain responsiveness in cognitively healthy subjects. OBJECTIVE: The aim was to determine whether individuals at increased risk of late-onset AD based on APOE allele genotype differ phenotypically in their response to experimentally-induced painful stimuli compared to those who do not have at least one copy of the ɛ4 allele. METHODS: Forty-nine cognitively healthy subjects aged 30-89 years old with the APOE4 allele (n = 12) and without (n = 37) were assessed for group differences in pain thresholds and affective (unpleasantness) responses to experimentally-induced thermal pain stimuli. RESULTS: Statistically significant main effects of APOE4 status were observed for both the temperature at which three different pain intensity percepts were reached (p = 0.040) and the level of unpleasantness associated with each (p = 0.014). APOE4 positive participants displayed lower overall pain sensitivity than those who were APOE4 negative and also greater overall levels of pain unpleasantness regardless of intensity level. CONCLUSION: Cognitively healthy APOE4 carriers at increased risk of late-onset AD demonstrated reduced thermal pain sensitivity but greater unpleasantness to thermal pain stimuli relative to individuals at lower risk of late-onset AD. These results suggest that altered evoked pain perception could potentially be used as a phenotypic biomarker of late-onset AD risk prior to disease onset. Additional studies of this issue may be warranted.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Cross-Sectional Studies; Female; Genetic Association Studies; Hot Temperature; Humans; Male; Middle Aged; Pain Perception; Phenotype; Risk Factors

COVID-19: Association Between Increase of Behavioral and Psychological Symptoms of Dementia During Lockdown and Caregivers' Poor Mental Health. - Pongan, Elodie; Dorey, Jean-Michel; Borg, Céline; Getenet, Jean Claude; Bachelet, Romain; Lourioux, Charles; Laurent, Bernard; Rey, Romain; Rouch, Isabelle (J Alzheimers Dis, 2021)
BACKGROUND: From March 2020, the support and care systems for caregivers and people with dementia (PWD) were suspended or dramatically changed due to the lockdown during the world pandemic of COVID-19. Thus, these changes in living conditions have had deleterious consequences on the behavior of PWD and subsequently on their caregivers' mental health, the two being linked. OBJECTIVE: Our study aimed to examine changes in behavior among PWD and to look for associations between the evolution of behavioral and psychological symptoms of dementia (BPSD) and caregivers' mental health in the context of COVID-19. METHODS: The study was conducted among caregivers of PWD living at home in France. Caregivers were interviewed via an anonymous cross-sectional online survey during the first lockdown between April 15 and June 15, 2020. RESULTS: Three hundred and eighty-nine caregivers accompanying a relative living at home participated in the study; 43.3%of the PWD presented a worsening of BPSD during the lockdown. With multivariate logistic regressions, a significant association was observed between "more BPSD" and burden, anxiety and depression, between "BPSD equivalent" and anxiety and depression, and between "emerging BPSD" and only depression. CONCLUSION: The lockdown seems to have an impact on behavioral disorders in PWD and these disorders are associated with poorer mental health of caregivers. Our findings suggest attention should be given to caregivers of PWD who have BPSD before lockdown and the need for continued consultations and professional help in case of new lockdowns.
Keywords: Aged; Aged, 80 and over; Caregivers; Communicable Disease Control; COVID-19; Cross-Sectional Studies; Dementia; Female; France; Humans; Male; Mental Disorders; Mental Health; Middle Aged; Surveys and Questionnaires

COVID-19 Crisis Effects on Caregiver Distress in Neurocognitive Disorder. - Alexopoulos, Panagiotis; Soldatos, Rigas; Kontogianni, Evangelia; Frouda, Maria; Loanna Aligianni, Souzana; Skondra, Maria; Passa, Maria; Konstantopoulou, Georgia; Stamouli, Evangelia; Katirtzoglou, Evgenia; Politis, Anastasios; Economou, Polychronis; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The outbreak of the COVID-19 pandemic seems to have mental health implications for both people with neurocognitive disorder and their caregivers. OBJECTIVE: The study aimed to shed light on relations between caregiver mental reaction to the pandemic and caregiver distress related to neuropsychiatric symptoms, memory impairment progression, and functional impairment of people with neurocognitive disorder during the period of confinement in Greece. METHODS: The study included caregivers of patients with mild (N = 13) and major (N = 54) neurocognitive disorder. The caregiver-based telephone interview was based on items of the neuropsychiatric inventory questionnaire, the AD8 Dementia Screening Instrument, and the Bristol Activities of Daily Living Scale. Regarding the mental impact of the COVID-19 crisis on caregivers, four single questions referring to their worries in the last seven days were posed, in addition to the scales Generalized Anxiety Disorder 7-Item (GAD-7) and the 22-item Impact of Event Scale-revised (IES-R). A stepwise linear regression model was employed for studying the relationship between caregiver distress and demographic and clinical data and caregiver mental reaction to COVID-19 pandemic outbreak. RESULTS: Caregiver distress severity during the confinement period was influenced not only by memory deficits (p = 0.009) and neuropsychiatric symptoms (p < 0.001) of patients, but also by caregiver hyperarousal (p = 0.003) and avoidance symptoms (p = 0.033) and worries directly linked to the COVID-19 crisis (p = 0.022). CONCLUSION: These observations provide further evidence for the urgent need for support of caregivers of patients with neurocognitive disorder during the COVID-19 pandemic.
Keywords: Aged; Aged, 80 and over; Caregivers; COVID-19; Female; Greece; Humans; Male; Middle Aged; Neurocognitive Disorders; Quarantine

Current and Future Prevalence Estimates of Mild Cognitive Impairment, Dementia, and Its Subtypes in a Population-Based Sample of People 70 Years and Older in Norway: The HUNT Study. - GjØra, Linda; Strand, Bjørn Heine; Bergh, Sverre; Borza, Tom; Brækhus, Anne; Engedal, Knut; Johannessen, Aud; Kvello-Alme, Marte; Krokstad, Steinar; Livingston, Gill; Matthews, Fiona E; Myrstad, Christian; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Having accurate, up-to-date information on the epidemiology of mild cognitive impairment (MCI) and dementia is imperative. OBJECTIVE: To determine the prevalence of MCI and dementia in Norway using data from a large population-based study. METHODS: All people 70 + years of age, n = 19,403, in the fourth wave of the Trøndelag Health Study (HUNT4) were invited to participate in the study HUNT4 70 + . Trained health personnel assessed participants using cognitive tests at a field station, at homes, or at their nursing home. Interviewers also completed a structured carer questionnaire in regard to participants suspected of having dementia. Clinical experts made diagnoses according to DSM-5 criteria. We calculated prevalence weighing the data to ensure population representativeness. RESULTS: A total of 9,930 (51.2%) of the possible 19,403 people participated, and 9,663 of these had sufficient information for analysis. Standardized prevalence of dementia and MCI was 14.6% (95% confidence interval (CI) 13.9-15.4) and 35.3% (95% CI 34.3-36.4), respectively. Dementia was more prevalent in women and MCI more prevalent in men. The most prevalent dementia subtype was Alzheimer's disease (57%). By adding data collected from a study of persons < 70 years in the same region, we estimate that there are 101,118 persons with dementia in Norway in 2020, and this is projected to increase to 236,789 and 380,134 in 2050 and 2100, respectively. CONCLUSION: We found a higher prevalence of dementia and MCI than most previous studies. The present prevalence and future projections are vital for preparing for future challenges to the healthcare system and the entire society.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Dementia; Female; Forecasting; Humans; Male; Mental Status and Dementia Tests; Neuropsychological Tests; Norway; Prevalence; Sex Factors; Surveys and Questionnaires

Different Inflammatory Signatures in Alzheimer's Disease and Frontotemporal Dementia Cerebrospinal Fluid. - Boström, Gustaf; Freyhult, Eva; Virhammar, Johan; Alcolea, Daniel; Tumani, Hayrettin; Otto, Markus; Brundin, Rose-Marie; Kilander, Lena; Löwenmark, Malin; Giedraitis, Vilmantas; Lleo, Alberto; von Arnim, Christine A F; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Neuroinflammatory processes are common in neurodegenerative diseases such as Alzheimer's disease (AD) and frontotemporal dementia (FTD), but current knowledge is limited as to whether cerebrospinal fluid (CSF) levels of neuroinflammatory proteins are altered in these diseases. OBJECTIVE: To identify and characterize neuroinflammatory signatures in CSF from patients with AD, mild cognitive impairment (MCI), and FTD. METHODS: We used proximity extension assay and ANOVA to measure and compare levels of 92 inflammatory proteins in CSF from 42 patients with AD, 29 with MCI due to AD (MCI/AD), 22 with stable MCI, 42 with FTD, and 49 control subjects, correcting for age, gender, collection unit, and multiple testing. RESULTS: Levels of matrix metalloproteinase-10 (MMP-10) were increased in AD, MCI/AD, and FTD compared with controls (AD: fold change [FC] = 1.32, 95% confidence interval [CI] 1.14-1.53, q = 0.018; MCI/AD: FC = 1.53, 95% CI 1.20-1.94, q = 0.045; and FTD: FC = 1.42, 95% CI 1.10-1.83, q = 0.020). MMP-10 and eleven additional proteins were increased in MCI/AD, compared with MCI (q < 0.05). In FTD, 36 proteins were decreased, while none was decreased in AD or MCI/AD, compared with controls (q < 0.05). CONCLUSION: In this cross-sectional multi-center study, we found distinct patterns of CSF inflammatory marker levels in FTD and in both early and established AD, suggesting differing neuroinflammatory processes in the two disorders.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Female; Frontotemporal Dementia; Humans; Inflammation; Male; Middle Aged; Peptide Fragments; tau Proteins

Economic Burden of Alzheimer's Disease Dementia in Japan. - Ikeda, Shunya; Mimura, Masaru; Ikeda, Manabu; Wada-Isoe, Kenji; Azuma, Mie; Inoue, Sachie; Tomita, Kiyoyuki (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease dementia (ADD) is the leading cause of long-term care in Japan. OBJECTIVE: This study estimates the annual healthcare and long-term care costs in fiscal year 2018 for adults over 65 years of age with ADD in Japan and the informal care costs and productivity loss for their families. METHODS: Healthcare and long-term care costs for ADD were estimated according to the disease severity classified by the clinical dementia rating (CDR) score, using reports from a literature review. For the costs of time spent on caregiving activities, productivity loss for ADD family caregivers aged 20-69 and informal care costs for all ADD family caregivers were estimated. RESULTS: The total healthcare cost of ADD was JPY 1,073 billion, of which 86% (JPY 923 billion) was attributed to healthcare costs other than ADD drug costs (JPY 151 billion). The healthcare costs other than ADD drug costs by severity were less than JPY 200 billion for CDR 0.5, CDR 1, and CDR 2, respectively, but increased to JPY 447 billion (48%) for CDR 3. The public long-term care costs were estimated to be JPY 4,783 billion, which increased according to the severity. Total productivity loss for ADD family caregivers aged 20-69 was JPY 1,547 billion and the informal care cost for all ADD family caregivers was JPY 6,772 billion. CONCLUSION: ADD costs have a significant impact on public-funded healthcare, long-term care systems, and families in Japan. To minimize the economic burden of ADD, prolonging healthy life expectancy is the key factor to address.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Caregivers; Female; Health Care Costs; Humans; Japan; Long-Term Care; Male

Effects of COVID-19 Home Confinement on Mental Health in Individuals with Increased Risk of Alzheimer's Disease. - Soldevila-Domenech, Natalia; Forcano, Laura; Boronat, Anna; Lorenzo, Thais; Piera, Iris; Puig-Pijoan, Albert; Mateus, Julian; González de Echevarri Gómez, José María; Knezevic, Iva; Soteras, Anna; Fauria, Karine; Pizarro, Nieves; et al. (J Alzheimers Dis, 2021)
We explored the impact of the Spanish COVID-19 strict home confinement on mental health and cognition in non-infected subjects (N = 16, 60-80 years) diagnosed with subjective cognitive decline and APOEɛ3/ɛ4 carriers. Mental health was monitored for 2 months on a daily, weekly, or monthly basis, and compared to pre-confinement values. Emotional distress, anxiety, and depression scores increased to pathological threshold values during and after confinement. Those with lower mood during confinement experienced a decline in their mood after confinement. Cognition did not change. These preliminary results suggest that mental health consequences of corona measures in preclinical stages of Alzheimer's disease should be further evaluated.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anxiety Disorders; Apolipoprotein E3; Apolipoprotein E4; Cognition Disorders; Cognitive Dysfunction; COVID-19; Depressive Disorder; Female; Humans; Male; Mental Health; Middle Aged; Psychological Distress; Quarantine; Risk; Spain

Elevated Norepinephrine Metabolism Gauges Alzheimer's Disease-Related Pathology and Memory Decline. - Riphagen, Joost M; van Egroo, Maxime; Jacobs, Heidi I L (J Alzheimers Dis, 2021)
The noradrenergic (NE) locus coeruleus (LC) is vulnerable to hyperphosphorylated tau, and dysregulated NE-metabolism is linked to greater tau and disease progression. We investigated whether elevated NE-metabolism alone predicts memory decline or whether concomitant presence of tau and amyloid-β is required. Among 114 memory clinic participants, time trends (max. six years) showed dose-response declines in learning across groups with elevated NE-metabolite 3-methoxy-4-hydroxyphenylethyleneglycol (MHPG) with no, one, or two Alzheimer's disease biomarkers; and no decline in the low MHPG group. Elevated MHPG is required and sufficient to detect learning declines, supporting a pathophysiologic model including the LC-NE system contributing to initial Alzheimer's disease-related processes.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Cohort Studies; Disease Progression; Female; Humans; Learning; Locus Coeruleus; Male; Memory Disorders; Methoxyhydroxyphenylglycol; Middle Aged; Neuropsychological Tests; Norepinephrine; Predictive Value of Tests; tau Proteins

Is Engagement in Intellectual and Social Leisure Activities Protective Against Dementia Risk? Evidence from the English Longitudinal Study of Ageing. - Almeida-Meza, Pamela; Steptoe, Andrew; Cadar, Dorina (J Alzheimers Dis, 2021)
BACKGROUND: Studies have suggested that mentally stimulating activities and socially engaged lifestyles may reduce dementia risk; however, it is unclear which activities are more beneficial. OBJECTIVE: We investigated intellectual and social leisure activities in relation to dementia incidence and explored the modifying role of sex and marital status in these associations. METHODS: The sample was comprised of 8,030 participants aged 50+ from the English Longitudinal Study of Ageing, who joined at wave 1 (2002-2003), or waves 3 (2006-2007), or 4 (2008-2009). The end of the study period was wave 8 (2016-2017). Subdistribution hazard models investigated the role of leisure activities grouped into intellectual and social domains in relation to dementia while accounting for the risk of death. Subsequent analyses were conducted with individual leisure activities. RESULTS: During the study period of up to 15 years, 412 participants developed dementia, and 2,192 died. We found that increased engagement in the intellectual activities' domain was associated with a decreased dementia incidence (SHR 0.85, 95% CI 0.76-0.96, p = 0.007), independent of the risk of death in married individuals, but not in those who were single, divorced, or widowed. Individual analyses for each leisure activity showed independent associations for reading newspapers in females (SHR 0.65, 95% CI 0.49-0.84, p = 0.001), mobile phone usage in males (SHR 0.61, 95% CI 0.45-0.84, p = 0.002), and having hobbies for married individuals (SHR 0.70, 95% CI 0.51-0.95, p = 0.02). CONCLUSION: We found that intellectual leisure activities contribute to lower dementia risk in a representative population of English adults, suggesting intervention opportunities.
Keywords: Aged; Aged, 80 and over; Aging; Dementia; Female; Humans; Incidence; Leisure Activities; Life Style; Longitudinal Studies; Male; Marital Status; Middle Aged; Proportional Hazards Models; Sex Factors; Social Behavior; Surveys and Questionnaires; Survival Analysis; United Kingdom

Gut Microbiome Features of Chinese Patients Newly Diagnosed with Alzheimer's Disease or Mild Cognitive Impairment. - Guo, Mingyan; Peng, Jun; Huang, Xiaoyan; Xiao, Lingjun; Huang, Fenyan; Zuo, Zhiyi (J Alzheimers Dis, 2021)
BACKGROUND: Patients with Alzheimer's disease (AD) have gut microbiome alterations compared with healthy controls. However, previous studies often assess AD patients who have been on medications or other interventions for the disease. Also, simultaneous determination of gut microbiome in patients with mild cognitive impairment (MCI) or AD in a study is rare. OBJECTIVE: To determine whether there was a gut microbiome alteration in patients newly diagnosed with AD or MCI and whether the degree of gut microbiome alteration was more severe in patients with AD than patients with MCI. METHODS: Fecal samples of 18 patients with AD, 20 patients with MCI, and 18 age-matched healthy controls were collected in the morning for 16S ribosomal RNA sequencing. No patient had medications or interventions for AD or MCI before the samples were collected. RESULTS: Although there was no difference in the microbial α-diversity among the three groups, patients with AD or MCI had increased β-diversity compared with healthy controls. Patients with AD had decreased Bacteroides, Lachnospira, and Ruminiclostridium_9 and increased Prevotella at the genus level compared with healthy controls. The changing direction of these genera in patients with MCI was the same as patients with AD. However, Lachnospira was the only genus whose abundance in patients with MCI was statistically significantly lower than healthy controls. Bacteroides, Lachnospira, and Ruminiclostridium_9 were positively associated with better cognitive functions whereas Prevotella was on the contrary when subjects of all three groups were considered. The negative correlation of Prevotella with cognitive functions remained among patients with MCI. CONCLUSION: Patients newly diagnosed with AD or MCI have gut dysbiosis that includes the decrease of potentially protective microbiome, such as Bacteroides, and the increase of microbiome that can promote inflammation, such as Prevotella. Our results support a novel idea that the degree of gut dysbiosis is worsened with the disease stage from MCI to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Asians; Biodiversity; China; Cognition; Cognitive Dysfunction; Disease Progression; Feces; Female; Gastrointestinal Microbiome; Humans; Male; Middle Aged; RNA, Ribosomal, 16S

Gut Microbiota Alterations and Cognitive Impairment Are Sexually Dissociated in a Transgenic Mice Model of Alzheimer's Disease. - Cuervo-Zanatta, Daniel; Garcia-Mena, Jaime; Perez-Cruz, Claudia (J Alzheimers Dis, 2021)
BACKGROUND: Normal aging is accompanied by cognitive deficiencies, affecting women and men equally. Aging is the main risk factor for Alzheimer's disease (AD), with women having a higher risk. The higher prevalence of AD in women is associated with the abrupt hormonal decline seen after menopause. However, other factors may be involved in this sex-related cognitive decline. Alterations in gut microbiota (GM) and its bioproducts have been reported in AD subjects and transgenic (Tg) mice, having a direct impact on brain amyloid-β pathology in male (M), but not in female (F) mice. OBJECTIVE: The aim of this work was to determine GM composition and cognitive dysfunction in M and F wildtype (WT) and Tg mice, in a sex/genotype segregation design. METHODS: Anxiety, short term working-memory, spatial learning, and long-term spatial memory were evaluated in 6-month-old WT and Tg male mice. Fecal short chain fatty acids were determined by chromatography, and DNA sequencing and bioinformatic analyses were used to determine GM differences. RESULTS: We observed sex-dependent differences in cognitive skills in WT mice, favoring F mice. However, the cognitive advantage of females was lost in Tg mice. GM composition showed few sex-related differences in WT mice. Contrary, Tg-M mice presented a more severe dysbiosis than Tg-F mice. A decreased abundance of Ruminococcaceae was associated with cognitive deficits in Tg-F mice, while butyrate levels were positively associated with better working- and object recognition-memory in WT-F mice. CONCLUSION: This report describes a sex-dependent association between GM alterations and cognitive impairment in a mice model of AD.
Keywords: Alzheimer Disease; Animals; Cognitive Dysfunction; Female; Gastrointestinal Microbiome; Humans; Male; Mice; Mice, Transgenic; Sex Characteristics; Spatial Memory

How Do Persons with Young and Late Onset Dementia Die? - Roβmeier, Carola; Hartmann, Julia; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Schneider-Schelte, Helga; Jox, Ralf J; Dinkel, Andreas; Diehl-Schmid, Janine (J Alzheimers Dis, 2021)
BACKGROUND: End of life symptoms and symptom management as well as the quality of dying (QoD) of persons with advanced dementia (PWAD) have not yet been systematically studied in Germany. OBJECTIVE: 1) To investigate symptoms, treatment and care at the end of life, advance care planning, and circumstances of death of recently deceased PWAD; 2) To determine whether there are differences between young and late onset dementia (YOD and LOD). METHODS: The study was performed in the context of the project EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of Young-onset and Late-Onset dementia in Germany). Closest relatives of recently deceased patients with advanced YOD (N = 46) and LOD (N = 54) living at home or in long term care were interviewed. RESULTS: Circumstances of death, symptoms, and treatment appeared to be similar between YOD and LOD, except that persons with LOD had significantly more somatic comorbidities and were admitted to hospital in the last three months of life more often than persons with LOD. At end of life, 60% of PWAD appeared to be "at peace". Difficulty swallowing, gurgling, shortness of breath, and discomfort were observed most frequently. Large interindividual differences in suffering and QoD were present. Determinants of QoD were not identified. CONCLUSION: Our findings suggest that low QoD was caused by inadequate recognition and/or insufficient treatment of burdensome physical and emotional symptoms. PWADs' needs should be assessed regularly, and strategies focusing on treatment and implementing support for both the patient and caregiver must be established.
Keywords: Advance Care Planning; Age of Onset; Aged; Aged, 80 and over; Caregivers; Dementia; Female; Humans; Long-Term Care; Male; Palliative Care; Quality of Life

The Impact of a Global Pandemic on People Living with Dementia and Their Care Partners: Analysis of 417 Lived Experience Reports. - Tam, Mallorie T; Dosso, Jill A; Robillard, Julie M (J Alzheimers Dis, 2021)
BACKGROUND: The COVID-19 pandemic is impacting the physical and emotional health of older adults living with dementia and their care partners. OBJECTIVE: Using a patient-centered approach, we explored the experiences and needs of people living with dementia and their care partners during the COVID-19 pandemic as part of an ongoing evaluation of dementia support services in British Columbia, Canada. METHODS: A survey instrument was developed around the priorities identified in the context of the COVID-19 and Dementia Task Force convened by the Alzheimer Society of Canada. RESULTS: A total of 417 surveys were analyzed. Overall, respondents were able to access information that was helpful for maintaining their own health and managing a period of social distancing. Care partners reported a number of serious concerns, including the inability to visit the person that they care for in long-term or palliative care. Participants also reported that the pandemic increased their levels of stress overall and that they felt lonelier and more isolated than they did before the pandemic. The use of technology was reported as a way to connect socially with their loved ones, with the majority of participants connecting with others at least twice per week. CONCLUSION: Looking at the complex effects of a global pandemic through the experiences of people living with dementia and their care partners is vital to inform healthcare priorities to restore their quality of life and health and better prepare for the future.
Keywords: Adaptation, Psychological; Aged; Alzheimer Disease; British Columbia; Caregivers; COVID-19; Disabled Persons; Female; Humans; Loneliness; Male; Needs Assessment; Psychosocial Support Systems; Social Isolation; Social Support; Stress, Psychological; Surveys and Questionnaires

Impact of Social Isolation on People with Dementia and Their Family Caregivers. - Azevedo, Lílian Viana Dos Santos; Calandri, Ismael Luis; Slachevsky, Andrea; Graviotto, Héctor Gastón; Vieira, Maria Carolina Santos; Andrade, Caíssa Bezerra de; Rossetti, Adriana Peredo; Generoso, Alana Barroso; Carmona, Karoline Carvalho; Pinto, Ludmilla Aparecida Cardoso; Sorbara, Marcos; Pinto, Alejandra; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with dementia and their family caregivers may face a great burden through social isolation due to the COVID-19 pandemic, which can be manifested as various behavioral and clinical symptoms. OBJECTIVE: To investigate the impacts of social isolation due to the COVID-19 pandemic on individuals with dementia and their family caregivers. METHODS: Two semi-structured questionnaires were applied via telephone to family caregivers of people diagnosed with dementia in three cities in Argentina, Brazil, and Chile, in order to assess clinical and behavioral changes in people with dementia and in their caregivers. RESULTS: In general, 321 interviews were conducted. A significant decline in memory function has been reported among 53.0%of people with dementia. In addition, 31.2%of individuals with dementia felt sadder and 37.4%had increased anxiety symptoms. These symptoms of anxiety were greater in individuals with mild to moderate dementia, while symptoms of agitation were greater in individuals with severe dementia. Moreover, compulsive-obsessive behavior, hallucinations, increased forgetfulness, altered appetite, and increased difficulty in activities of daily living were reported more frequently among individuals with moderate to severe dementia. Caregivers reported feeling more tired and overwhelmed during this period and these symptoms were also influenced by the severity of dementia. CONCLUSION: Social isolation during the COVID-19 pandemic triggered a series of negative behavioral repercussions, both for people with dementia and for their family caregivers in these three South American countries.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Argentina; Brazil; Caregivers; Chile; COVID-19; Dementia; Female; Humans; Male; Middle Aged; Pandemics; Physical Distancing; Social Isolation; Surveys and Questionnaires

Improving the Diagnosis of the Frontal Variant of Alzheimer's Disease with the DAPHNE Scale. - Lehingue, Elsa; Gueniat, Julien; Jourdaa, Sandra; Hardouin, Jean BenoÎt; Pallardy, Amandine; Courtemanche, Hélène; Rocher, Laetitia; Etcharry-Bouyx, Frédérique; Auriacombe, Sophie; Mollion, Hélène; Formaglio, Maıté; Rouaud, Olivier; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The frontal variant of Alzheimer's disease (fAD) is poorly understood and poorly defined. The diagnosis remains challenging. The main differential diagnosis is the behavioral variant of frontotemporal degeneration (bvFTD). For fAD, there is some dissociation between the clinical frontal presentation and imaging and neuropathological studies, which do not always find a specific involvement of the frontal lobes. DAPHNE is a behavioral scale, which demonstrated excellent performance to distinguish between bvFTD and AD. OBJECTIVE: The aim of the present study was to assess the reliability of this new tool to improve the clinical diagnosis of fAD. METHODS: Twenty fAD patients and their caregivers were prospectively included and were compared with 36 bvFTD and 22 AD patients. RESULTS: The three main behavioral disorders in the fAD patients were apathy, loss of empathy, and disinhibition. Three disorders were discriminant because they were less frequent and less severe in the fAD patients than in the bvFTD patients, namely hyperorality, neglect, and perseverations. This specific pattern of behavioral disorders was corroborated by SPECT or 18FDG PET-CT scan that showed that patients with fAD could have a medial frontal hypoperfusion, whereas in bvFTD patients the orbitofrontal cortex was the main involved region, with more diffuse hypoperfusion. CONCLUSION: We demonstrated that DAPHNE had good sensitivity and good specificity to discriminate between the three groups and in particular between fAD and bvFTD patients. DAPHNE is a quick tool that could help clinicians in memory clinics not only to differentiate bvFTD from typical AD but also from fAD.
Keywords: Aged; Alzheimer Disease; Cohort Studies; Diagnosis, Differential; Female; Frontal Lobe; Frontotemporal Dementia; Humans; Male; Middle Aged; Neuropsychological Tests

Incremental Healthcare Utilization and Cost Burden of Comorbid Insomnia in Alzheimer's Disease Patients. - Qureshi, Zaina P; Thiel, Ellen; Nelson, James; Khandker, Rezaul (J Alzheimers Dis, 2021)
BACKGROUND: Insomnia is associated with worsened clinical outcomes among Alzheimer's disease dementia (AD) patients, increased caregiver burden, and healthcare utilization. OBJECTIVE: This study aimed to characterize the incremental healthcare burden of insomnia in AD using real-world data. METHODS: A retrospective observational study was conducted on AD patients selected from the IBM® MarketScan Commercial and Medicare Supplemental Databases. AD patients with claims-based evidence of insomnia were direct matched to a non-insomnia cohort based on demographic factors. Healthcare utilization and associated costs were assessed for a 12-month follow-up period. RESULTS: A total of 3,500 insomnia AD patients and 9,884 non-insomnia AD patients were analyzed. The insomnia cohort had a higher comorbidity burden at baseline (mean score on Charlson Comorbidity Index 2.5 versus 2.2, p < 0.001) and higher proportions of patients with baseline diagnoses for other conditions including depression: 40%, insomnia cohort versus 25%, non-insomnia (p < 0.001). AD patients with insomnia were more likely to have a claim for inpatient hospitalizations (39.8%versus 32.3%), emergency room services (56.4%versus 48.0%), and skilled-nursing services (42.6%versus 31.9%) (all p < 0.05). Mean total annual healthcare costs during the 12-month follow-up period were significantly higher among AD patients with insomnia as compared to those without. (Mean costs: $37,356 versus $27,990, p < 0.001). CONCLUSION: AD patients with comorbid insomnia are more likely to use higher-cost healthcare services such as inpatient hospitalization, and skilled nursing, and have higher total healthcare costs. This real-world analysis provides evidence that AD disease management should consider proper treatment of comorbid insomnia due to the incremental burden and cost implications.
Keywords: Aged, 80 and over; Alzheimer Disease; Comorbidity; Databases, Factual; Female; Health Care Costs; Humans; Male; Medicare; Patient Acceptance of Health Care; Retrospective Studies; Sleep Initiation and Maintenance Disorders; United States

Life Course Air Pollution Exposure and Cognitive Decline: Modelled Historical Air Pollution Data and the Lothian Birth Cohort 1936. - Russ, Tom C; Cherrie, Mark P C; Dibben, Chris; Tomlinson, Sam; Reis, Stefan; Dragosits, Ulrike; Vieno, Massimo; Beck, Rachel; Carnell, Ed; Shortt, Niamh K; Muniz-Terrera, Graciela; Redmond, Paul; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Air pollution has been consistently linked with dementia and cognitive decline. However, it is unclear whether risk is accumulated through long-term exposure or whether there are sensitive/critical periods. A key barrier to clarifying this relationship is the dearth of historical air pollution data. OBJECTIVE: To demonstrate the feasibility of modelling historical air pollution data and using them in epidemiologicalmodels. METHODS: Using the EMEP4UK atmospheric chemistry transport model, we modelled historical fine particulate matter (PM2.5) concentrations for the years 1935, 1950, 1970, 1980, and 1990 and combined these with contemporary modelled data from 2001 to estimate life course exposure in 572 participants in the Lothian Birth Cohort 1936 with lifetime residential history recorded. Linear regression and latent growth models were constructed using cognitive ability (IQ) measured by the Moray House Test at the ages of 11, 70, 76, and 79 years to explore the effects of historical air pollution exposure. Covariates included sex, IQ at age 11 years, social class, and smoking. RESULTS: Higher air pollution modelled for 1935 (when participants would have been in utero) was associated with worse change in IQ from age 11-70 years (β = -0.006, SE = 0.002, p = 0.03) but not cognitive trajectories from age 70-79 years (p > 0.05). There was no support for other critical/sensitive periods of exposure or an accumulation of risk (all p > 0.05). CONCLUSION: The life course paradigm is essential in understanding cognitive decline and this is the first study to examine life course air pollution exposure in relation to cognitive health.
Keywords: Adolescent; Adult; Aged; Air Pollution; Child; Cognitive Dysfunction; Environmental Exposure; Female; History, 20th Century; Humans; Linear Models; Male; Middle Aged; Particulate Matter; Scotland; Young Adult

Low Doses of Ionizing Radiation as a Treatment for Alzheimer's Disease: A Pilot Study. - Cuttler, Jerry M; Abdellah, Eslam; Goldberg, Yael; Al-Shamaa, Sarmad; Symons, Sean P; Black, Sandra E; Freedman, Morris (J Alzheimers Dis, 2021)
BACKGROUND: In 2015, a patient in hospice with Alzheimer's disease (AD) was treated with ionizing radiation to her brain using repeated CT scans. Improvement in cognition, speech, movement, and appetite was observed. These improvements were so momentous that she was discharged from the hospice to a long-term care home. Based on this case, we conducted a pilot clinical trial to examine the effect of low-dose ionizing radiation (LDIR) in severe AD. OBJECTIVE: To determine whether the previously reported benefits of LDIR in a single case with AD could be observed again in other cases with AD when the same treatments are given. METHODS: In this single-arm study, four patients were treated with three consecutive treatments of LDIR, each spaced two weeks apart. Qualitative changes in communication and behavior with close relatives were observed and recorded. Quantitative measures of cognition and behavior were administered pre and post LDIR treatments. RESULTS: Minor improvements on quantitative measures were noted in three of the four patients following treatment. However, the qualitative observations of cognition and behavior suggested remarkable improvements within days post-treatment, including greater overall alertness. One patient showed no change. CONCLUSION: LDIR may be a promising, albeit controversial therapy for AD. Trials of patients with less severe AD, double-blind and placebo-controlled, should be carried out to determine the benefits of LDIR. Quantitative measures are needed that are sensitive to the remarkable changes induced by LDIR, such as biological markers of oxidative stress that are associated with AD.
Keywords: Aged, 80 and over; Alzheimer Disease; Cranial Irradiation; Female; Humans; Male; Pilot Projects; Radiation, Ionizing

Memory-Related Frontal Brainwaves Predict Transition to Mild Cognitive Impairment in Healthy Older Individuals Five Years Before Diagnosis. - Jiang, Yang; Li, Juan; Schmitt, Frederick A; Jicha, Gregory A; Munro, Nancy B; Zhao, Xiaopeng; Smith, Charles D; Kryscio, Richard J; Abner, Erin L (J Alzheimers Dis, 2021)
BACKGROUND: Early prognosis of high-risk older adults for amnestic mild cognitive impairment (aMCI), using noninvasive and sensitive neuromarkers, is key for early prevention of Alzheimer's disease. We have developed individualized measures in electrophysiological brain signals during working memory that distinguish patients with aMCI from age-matched cognitively intact older individuals. OBJECTIVE: Here we test longitudinally the prognosis of the baseline neuromarkers for aMCI risk. We hypothesized that the older individuals diagnosed with incident aMCI already have aMCI-like brain signatures years before diagnosis. METHODS: Electroencephalogram (EEG) and memory performance were recorded during a working memory task at baseline. The individualized baseline neuromarkers, annual cognitive status, and longitudinal changes in memory recall scores up to 10 years were analyzed. RESULTS: Seven of the 19 cognitively normal older adults were diagnosed with incident aMCI for a median 5.2 years later. The seven converters' frontal brainwaves were statistically identical to those patients with diagnosed aMCI (n = 14) at baseline. Importantly, the converters' baseline memory-related brainwaves (reduced mean frontal responses to memory targets) were significantly different from those who remained normal. Furthermore, differentiation pattern of left frontal memory-related responses (targets versus nontargets) was associated with an increased risk hazard of aMCI (HR = 1.47, 95% CI 1.03, 2.08). CONCLUSION: The memory-related neuromarkers detect MCI-like brain signatures about five years before diagnosis. The individualized frontal neuromarkers index increased MCI risk at baseline. These noninvasive neuromarkers during our Bluegrass memory task have great potential to be used repeatedly for individualized prognosis of MCI risk and progression before clinical diagnosis.
Keywords: Aged; Brain Waves; Cognition; Cognitive Dysfunction; Electroencephalography; Female; Humans; Longitudinal Studies; Male; Memory, Short-Term; Neuropsychological Tests; Prodromal Symptoms

Mild Behavioral Impairment and Subjective Cognitive Decline Predict Cognitive and Functional Decline. - Ismail, Zahinoor; McGirr, Alexander; Gill, Sascha; Hu, Sophie; Forkert, Nils D; Smith, Eric E (J Alzheimers Dis, 2021)
BACKGROUND: Mild behavioral impairment (MBI) and subjective cognitive decline (SCD) are dementia risk states, and potentially represent neurobehavioral and neurocognitive manifestations, respectively, of early stage neurodegeneration. Both MBI and SCD predict incident cognitive decline and dementia, are associated with known dementia biomarkers, and are both represented in the NIA-AA research framework for AD in Stage 2 (preclinical disease). OBJECTIVE: To assess the associations of MBI and SCD, alone and in combination, with incident cognitive and functional decline in a population of older adults. We tested the hypothesis that MBI and SCD confer additive risk for decline. METHODS: Cognitively normal participants were followed up annually at Alzheimer's Disease Centers. Logistic regression assessed the relationship between baseline classification (MBI-SCD-, MBI-SCD+, MBI+SCD-, or MBI+SCD+) and 3-year outcome. RESULTS: Of 2,769 participants (mean age=76), 1,536 were MBI-SCD-, 254 MBI-SCD+, 743 MBI+SCD-, and 236 MBI+SCD+. At 3 years, 349 (12.6%) declined to CDR >0, including 23.1% of the MBI+group, 23.5% of the SCD+group, and 30.9% of the intersection group of both MBI+and SCD+participants. Compared to SCD-MBI-, we observed an ordinal progression in risk (ORs [95% CI]): 3.61 [2.42-5.38] for MBI-SCD+ (16.5% progression), 4.76 [3.57-6.34] for MBI+SCD- (20.7%), and 8.15 [5.71-11.64] for MBI+SCD+(30.9%). CONCLUSION: MBI and SCD together were associated with the greatest risk of decline. These complementary dementia risk syndromes can be used as simple and scalable methods to identify high-risk patients for workup or for clinical trial enrichment.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Disease Progression; Executive Function; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Odds Ratio; Risk Assessment

MIND Diet, Common Brain Pathologies, and Cognition in Community-Dwelling Older Adults. - Dhana, Klodian; James, Bryan D; Agarwal, Puja; Aggarwal, Neelum T; Cherian, Laurel J; Leurgans, Sue E; Barnes, Lisa L; Bennett, David A; Schneider, Julie A (J Alzheimers Dis, 2021)
BACKGROUND: MIND diet, a hybrid of the Mediterranean diet and the Dietary Approaches to Stop Hypertension diet, is associated with a slower cognitive decline and lower risk of Alzheimer's disease (AD) dementia in older adults. OBJECTIVE: We aim to examine whether the association of the MIND diet with cognition is independent of common brain pathologies. METHODS: Utilizing data from the Rush Memory and Aging Project (MAP), a longitudinal clinical-pathologic study, we studied 569 decedents with valid dietary data, cognitive testing proximate to death, and complete autopsy data at the time of these analyses. A series of regression analyses were used to examine associations of the MIND diet, dementia-related brain pathologies, and global cognition proximate to death adjusting for age, sex, education, APOEɛ4, late-life cognitive activities, and total energy intake. RESULTS: A higher MIND diet score was associated with better global cognitive functioning proximate to death (β= 0.119, SE = 0.040, p = 0.003), and neither the strength nor the significance of association changed substantially when AD pathology and other brain pathologies were included in the model. The β-estimate after controlling for global AD pathology was 0.111 (SE = 0.037, p = 0.003). The MIND diet-cognition relationship remained significant when we restricted our analysis to individuals without mild cognitive impairment at the baseline (β= 0.121, SE = 0.042, p = 0.005) or in people diagnosed with postmortem diagnosis of AD based on NIA-Reagan consensus recommendations (β= 0.114, SE = 0.050, p = 0.023). CONCLUSION: MIND diet is associated with better cognitive functioning independently of common brain pathology, suggesting that the MIND diet may contribute to cognitive resilience in the elderly.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid; Autopsy; Brain; Chicago; Cognition; Diet, Mediterranean; Female; Humans; Independent Living; Longitudinal Studies; Male; Neuropsychological Tests; Surveys and Questionnaires

Mortality After Ischemic Stroke in Patients with Alzheimer's Disease Dementia and Other Dementia Disorders. - Zupanic, Eva; von Euler, Mia; Winblad, Bengt; Xu, Hong; Secnik, Juraj; Kramberger, Milica Gregoric; Religa, Dorota; Norrving, Bo; Garcia-Ptacek, Sara (J Alzheimers Dis, 2021)
BACKGROUND: Stroke and dementia are interrelated diseases and risk for both increases with age. Even though stroke incidence and age-standardized death rates have decreased due to prevention of stroke risk factors, increased utilization of reperfusion therapies, and other changes in healthcare, the absolute numbers are increasing due to population growth and aging. OBJECTIVE: To analyze predictors of death after stroke in patients with dementia and investigate possible time and treatment trends. METHODS: A national longitudinal cohort study 2007-2017 using Swedish national registries. We compared 12,629 ischemic stroke events in patients with dementia with matched 57,954 stroke events in non-dementia controls in different aspects of patient care and mortality. Relationship between dementia status and dementia type (Alzheimer's disease and mixed dementia, vascular dementia, other dementias) and death was analyzed using Cox regressions. RESULTS: Differences in receiving intravenous thrombolysis between patients with and without dementia disappeared after the year 2015 (administered to 11.1% dementia versus 12.3% non-dementia patients, p = 0.117). One year after stroke, nearly 50% dementia and 30% non-dementia patients had died. After adjustment for demographics, mobility, nursing home placement, and comorbidity index, dementia was an independent predictor of death compared with non-dementia patients (HR 1.26 [1.23-1.29]). CONCLUSION: Dementia before ischemic stroke is an independent predictor of death. Over time, early and delayed mortality in patients with dementia remained increased, regardless of dementia type. Patients with≤80 years with prior Alzheimer's disease or mixed dementia had higher mortality rates after stroke compared to patients with prior vascular dementia.
Keywords: Aged; Aged, 80 and over; Comorbidity; Dementia; Female; Fibrinolytic Agents; Humans; Incidence; Ischemic Stroke; Male; Registries; Survival Rate; Sweden; Thrombolytic Therapy

Needs of Dementia Family Caregivers in Spain During the COVID-19 Pandemic. - Carcavilla, Nuria; Pozo, Ana Sofía; González, Belén; Moral-Cuesta, Débora; Roldán, José Joaquín; Erice, Victoria; Remírez, Ana de Ganuza (J Alzheimers Dis, 2021)
We explored the experience from caregivers of people with dementia (PwD) during mandatory confinement due to the COVID-19 pandemic in Spain. An online survey, which studied the perceptions of the main problems and consequences experienced during confinement, was answered by 106 family caregivers of PwD. Results showed that family caregivers of PwD experienced psychological problems, like anxiety, mood, sleep, or eating disorders during confinement and felt less supported when they had to handle challenging behaviors or offer meaningful activities. An innovative multi-tiered supportive approach is needed which considers a post-pandemic reality and ensures the continuity of quality care for PwD and their family careers.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Alzheimer Disease; Anxiety Disorders; Caregivers; COVID-19; Feeding and Eating Disorders; Female; Humans; Male; Middle Aged; Mood Disorders; Needs Assessment; Sleep Wake Disorders; Social Isolation; Social Support; Spain

Neuropsychiatric Symptoms in Patients with Dementia Associated with Increased Psychological Distress in Caregivers During the COVID-19 Pandemic. - Borelli, Wyllians Vendramini; Augustin, Marina Coutinho; de Oliveira, Paola Bell Felix; Reggiani, Lorenzo Casagrande; Bandeira-de-Mello, Renato Gorga; Schumacher-Schuh, Artur Francisco; Chaves, Marcia Lorena Fagundes; Castilhos, Raphael Machado (J Alzheimers Dis, 2021)
BACKGROUND: The social isolation imposed by COVID-19 pandemic can have a major impact on the mental health of dementia patients and their caregivers. OBJECTIVE: We aim to evaluate the neurological decline of patients with dementia and the caregivers' burden during the pandemic. METHODS: We performed a cross-sectional study. Caregivers of dementia patients following in the outpatient clinic were included. A structured telephone interview composed of the Neuropsychiatric Inventory Questionnaire (NPI-Q), Zarit Burden Interview (ZBI), Beck Depression (BDI) and Anxiety (BAI) Inventories to address cognitive, behavioral, and functional changes associated with social distancing during the Sars-Cov-2 outbreak. Patients were divided in two groups according to caregivers' report: with perceived Altered Cognition (AC) and Stable Cognition (SC). RESULTS: A total of 58 patients (median age: 57 years [21-87], 58.6%females) and caregivers (median age: 76.5 years [55-89], 79.3%females) were included. Cognitive decline was shown by most patients (53.4%), as well as behavioral symptoms (48.3%), especially apathy/depression (24.1%), and functional decline (34.5%). The AC group (n = 31) presented increased behavioral (67.7%versus 25.9%, p = 0.002) and functional (61.3%versus 3.7%, p < 0.001) changes when compared to the SC group. In the AC group, ZBI, BDI, NPI-Q caregiver distress, and NPI-Q patient's severity of symptoms scores were worse than the SC group (p < 0.005 for all). CONCLUSION: Patients' neuropsychiatric worsening and caregiver burden were frequent during the pandemic. Worsening of cognition was associated with increased caregivers' psychological distress.
Keywords: Adult; Aged; Aged, 80 and over; Brazil; Caregivers; COVID-19; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Disorders; Middle Aged; Outpatient Clinics, Hospital; Pandemics; Psychological Distress; Social Isolation; Young Adult

Plasma Biomarkers of Alzheimer's Disease in African Americans. - Deniz, Kaancan; Ho, Charlotte C G; Malphrus, Kimberly G; Reddy, Joseph S; Nguyen, Thuy; Carnwath, Troy P; Crook, Julia E; Lucas, John A; Graff-Radford, Neill R; Carrasquillo, Minerva M; Ertekin-Taner, Nilufer (J Alzheimers Dis, 2021)
BACKGROUND/OBJECTIVE: The aim of this study was to determine if plasma concentrations of 5 surrogate markers of Alzheimer's disease (AD) pathology and neuroinflammation are associated with disease status in African Americans. METHODS: We evaluated 321 African Americans (159 AD, 162 controls) from the Florida Consortium for African-American Alzheimer's Disease Studies (FCA3DS). Five plasma proteins reflecting AD neuropathology or inflammation (Aβ42, tau, IL6, IL10, TNFα) were tested for associations with AD, age, sex, APOE and MAPT genotypes, and for pairwise correlations. RESULTS: Plasma tau levels were higher in AD when adjusted for biological and technical covariates. APOEɛ4 was associated with lower plasma Aβ42 and tau levels. Older age was associated with higher plasma Aβ42, tau, and TNFα. Females had lower IL10 levels. Inflammatory proteins had strong pairwise correlations amongst themselves and with Aβ42. CONCLUSION: We identified effects of demographic and genetic variants on five potential plasma biomarkers in African Americans. Plasma inflammatory biomarkers and Aβ42 may reflect correlated pathologies and elevated plasma tau may be a biomarker of AD in this population.
Keywords: African Americans; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Case-Control Studies; Female; Humans; Interleukin-10; Interleukin-6; Male; Middle Aged; Peptide Fragments; tau Proteins; Tumor Necrosis Factor-alpha

Quality of Life in Advanced Dementia with Late Onset, Young Onset, and Very Young Onset. - Hartmann, Julia; Roßmeier, Carola; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Slawik, Till; Fleischhaker, Mareike; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Haller, Bernhard; Schneider-Schelte, Helga; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Advanced stages of dementia are characterized by severe cognitive and physical impairment. It has not yet been investigated whether persons with young onset dementia (YOD) and late onset dementia (LOD) differ in advanced disease stages. OBJECTIVES: To compare quality of life (QoL) between persons with advanced YOD and LOD; to explore the determinants of QoL; to investigate whether YOD and LOD differ with regard to symptoms and care. METHODS: The study was performed in the context of EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of YOD and LOD in Germany). Persons with advanced dementia (PWAD) were assessed and caregivers were interviewed. QoL was measured with the proxy rating Quality of Life in Late Stage Dementia (QUALID) scale. RESULTS: 93 persons with YOD and 98 with LOD were included. No significant differences in QoL were detected. Determinants of QoL were similar in YOD and LOD. Behavioral and psychological symptoms of dementia (BPSD), suffering and other distressing symptoms were associated with a lower QoL. In YOD but not in LOD antipsychotic treatment was associated with low QoL. The group of persons who were younger than 65 years at the time of the study visit experienced significantly more distressing symptoms than older PWAD. CONCLUSION: Overall, persons with advanced YOD do not appear to be disadvantaged compared to old and oldest PWAD. Special attention, however, must be paid to the group of the very young persons who seem to be particularly vulnerable.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Antipsychotic Agents; Behavioral Symptoms; Caregivers; Dementia; Disease Progression; Female; Germany; Home Care Services; Humans; Individuality; Male; Middle Aged; Pain; Palliative Care; Psychotropic Drugs; Quality of Life

Race/Ethnic Disparities in Mild Cognitive Impairment and Dementia: The Northern Manhattan Study. - Wright, Clinton B; DeRosa, Janet T; Moon, Michelle P; Strobino, Kevin; DeCarli, Charles; Cheung, Ying Kuen; Assuras, Stephanie; Levin, Bonnie; Stern, Yaakov; Sun, Xiaoyan; Rundek, Tatjana; Elkind, Mitchell S V; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Variability in dementia rates across racial and ethnic groups has been estimated at 60%. Studies suggest disparities in Caribbean Hispanic and Black populations, but community-based data are limited. OBJECTIVE: Estimate the prevalence of mild cognitive impairment (MCI) and dementia in the racially and ethnically diverse community-based Northern Manhattan Study cohort and examine sociodemographic, vascular risk factor, and brain imaging correlates. METHODS: Cases of MCI and dementia were adjudicated by a team of neuropsychologists and neurologists and prevalence was estimated across race/ethnic groups. Ordinal proportional odds models were used to estimate race/ethnic differences in the prevalence of MCI or dementia adjusting for sociodemographic variables (model 1), model 1 plus potentially modifiable vascular risk factors (model 2), and model 1 plus structural imaging markers of brain integrity (model 3). RESULTS: There were 989 participants with cognitive outcome determinations (mean age 69±9 years; 68% Hispanic, 16% Black, 14% White; 62% women; mean (±SD) follow-up five (±0.6) years). Hispanic and Black participants had greater likelihood of MCI (20%) and dementia (5%) than White participants accounting for age and education differences. Hispanic participants had greater odds of MCI or dementia than both White and Black participants adjusting for sociodemographic variables, vascular risk factors, and brain imaging factors. White matter hyperintensity burden was significantly associated with greater odds of MCI or dementia (OR = 1.3, 1.1 to 1.6), but there was no significant interaction by race/ethnicity. CONCLUSION: In this diverse community-based cohort, cross-sectional data revealed significant race/ethnic disparities in the prevalence of MCI and dementia. Longer follow-up and incidence data are needed to further clarify these relationships.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Cross-Sectional Studies; Dementia; Ethnicity; Female; Humans; Male; Middle Aged; New York City; Prevalence

The Retinal Vessel Density Can Reflect Cognitive Function in Patients with Alzheimer's Disease: Evidence from Optical Coherence Tomography Angiography. - Yan, Yibing; Wu, Xingqi; Wang, Xiaojing; Geng, Zhi; Wang, Lu; Xiao, Guixian; Wu, Yue; Zhou, Shanshan; Liao, Rongfeng; Wei, Ling; Tian, Yanghua; Wang, Kai (J Alzheimers Dis, 2021)
BACKGROUND: There is increasing evidence that Alzheimer's disease (AD) patients may present decreased cerebral blood perfusion before pathological brain changes. Using the retina as a window to the brain, we can study disorders of the central nervous system through the eyes. OBJECTIVE: This study aimed to investigate differences in retinal structure and vessel density (VD) between patients with mild AD and healthy controls (HCs). Furthermore, we explored the relationship between retinal VD and cognitive function. METHODS: We enrolled 37 patients with AD and 29 age-matched HCs who underwent standard ophthalmic optical coherence tomography angiography (OCTA) for evaluation of the retinal layer thickness and VD parameters. Cognitive function was evaluated using a battery of neuropsychological assessments. Finally, the correlations among retinal layer thickness, VD parameters, and cognitive function were evaluated. RESULTS: The retinal fiber layer thickness and retinal VD of patients with AD were significantly reduced compared with HCs. The retinal VD was significantly correlated with overall cognition, memory, executive, and visual-spatial perception functions. However, there was no significant between-group difference in the macular thickness. CONCLUSION: Our findings indicate a positive correlation between retinal VD and some, but not all, cognitive function domains. Most importantly, we demonstrated the role of OCTA in detecting early capillary changes, which could be a noninvasive biomarker for early AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognition; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Retinal Vessels; Tomography, Optical Coherence

The Right Temporal Variant of Frontotemporal Dementia Is Not Genetically Sporadic: A Case Series. - Ulugut Erkoyun, Hulya; van der Lee, Sven J; Nijmeijer, Bas; van Spaendonk, Rosalina; Nelissen, Anne; Scarioni, Marta; Dijkstra, Anke; Samancı, Bedia; Gürvit, Hakan; Yıldırım, Zerrin; Tepgeç, Fatih; Bilgic, Basar; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Right temporal variant frontotemporal dementia (rtvFTD) has been generally considered as a right sided variant of semantic variant primary progressive aphasia (svPPA), which is a genetically sporadic disorder. Recently, we have shown that rtvFTD has a unique clinical syndrome compared to svPPA and behavioral variant frontotemporal dementia. OBJECTIVE: We challenge the assumption that rtvFTD is a sporadic, non-familial variant of FTD by identifying potential autosomal dominant inheritance and related genes in rtvFTD. METHODS: We collected all subjects with a diagnosis of FTD or primary progressive aphasia who had undergone genetic screening (n = 284) and subsequently who had a genetic variant (n = 48) with a diagnosis of rtvFTD (n = 6) in 2 specialized memory clinics. RESULTS: Genetic variants in FTD related genes were found in 33% of genetically screened rtvFTD cases; including MAPT (n = 4), GRN (n = 1), and TARDBP (n = 1) genes, whereas only one svPPA case had a genetic variant in our combined cohorts. Additionally, 4 out of 6 rtvFTD subjects had a strong family history for dementia. CONCLUSION: Our results demonstrate that rtvFTD, unlike svPPA, is not a pure sporadic, but a heterogeneous potential genetic variant of FTD, and screening for genetic causes for FTD should be performed in patients with rtvFTD.
Keywords: Aphasia, Primary Progressive; DNA-Binding Proteins; Female; Frontotemporal Dementia; Functional Laterality; Genetic Testing; Genetic Variation; Gyrus Cinguli; Humans; Male; Middle Aged; Progranulins; tau Proteins

Upregulation of Cortical A2A Adenosine Receptors Is Reflected in Platelets of Patients with Alzheimer's Disease. - Merighi, Stefania; Battistello, Enrica; Casetta, Ilaria; Gragnaniello, Daniela; Poloni, Tino Emanuele; Medici, Valentina; Cirrincione, Alice; Varani, Katia; Vincenzi, Fabrizio; Borea, Pier Andrea; Gessi, Stefania (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is a neurodegenerative pathology covering about 70%of all cases of dementia. Adenosine, a ubiquitous nucleoside, plays a key role in neurodegeneration, through interaction with four receptor subtypes. The A2A receptor is upregulated in peripheral blood cells of patients affected by Parkinson's and Huntington's diseases, reflecting the same alteration found in brain tissues. However, whether these changes are also present in AD pathology has not been determined. OBJECTIVE: In this study we verified any significant difference between AD cases and controls in both brain and platelets and we evaluated whether peripheral A2A receptors may reflect the status of neuronal A2A receptors. METHODS: We evaluated the expression of A2A receptors in frontal white matter, frontal gray matter, and hippocampus/entorhinal cortex, in postmortem AD patients and control subjects, through [3H]ZM 241385 binding experiments. The same analysis was performed in peripheral platelets from AD patients versus controls. RESULTS: The expression of A2A receptors in frontal white matter, frontal gray matter, and hippocampus/entorhinal cortex, revealed a density (Bmax) of 174±29, 219±33, and 358±84 fmol/mg of proteins, respectively, in postmortem AD patients in comparison to 104±16, 103±19, and 121±20 fmol/mg of proteins in controls (p < 0.01). The same trend was observed in peripheral platelets from AD patients versus controls (Bmax of 214±17 versus 95±4 fmol/mg of proteins, respectively, p < 0.01). CONCLUSION: AD subjects show significantly higher A2A receptor density than controls. Values on platelets seem to correlate with those in the brain supporting a role for A2A receptor as a possible marker of AD pathology and drug target for novel therapies able to modify the progression of dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Blood Platelets; Cerebral Cortex; Female; Humans; Male; Receptor, Adenosine A2A; Up-Regulation

White Matter Connectivity in Incident Mild Cognitive Impairment: A Diffusion Spectrum Imaging Study of World Trade Center Responders at Midlife. - Huang, Chuan; Kritikos, Minos; Clouston, Sean A P; Deri, Yael; Serrano-Sosa, Mario; Bangiyev, Lev; Santiago-Michels, Stephanie; Gandy, Sam; Sano, Mary; Bromet, Evelyn J; Luft, Benjamin J (J Alzheimers Dis, 2021)
BACKGROUND: Individuals who participated in response efforts at the World Trade Center (WTC) following 9/11/2001 are experiencing elevated incidence of mild cognitive impairment (MCI) at midlife. OBJECTIVE: We hypothesized that white matter connectivity measured using diffusion spectrum imaging (DSI) would be restructured in WTC responders with MCI versus cognitively unimpaired responders. METHODS: Twenty responders (mean age 56; 10 MCI/10 unimpaired) recruited from an epidemiological study were characterized using NIA-AA criteria alongside controls matched on demographics (age/sex/occupation/race/education). Axial DSI was acquired on a 3T Siemen's Biograph mMR scanner (12-channel head coil) using a multi-band diffusion sequence. Connectometry examined whole-brain tract-level differences in white matter integrity. Fractional anisotropy (FA), mean diffusivity (MD), and quantified anisotropy were extracted for region of interest (ROI) analyses using the Desikan-Killiany atlas. RESULTS: Connectometry identified both increased and decreased connectivity within regions of the brains of responders with MCI identified in the corticothalamic pathway and cortico-striatal pathway that survived adjustment for multiple comparisons. MCI was also associated with higher FA values in five ROIs including in the rostral anterior cingulate; lower MD values in four ROIs including the left rostral anterior cingulate; and higher MD values in the right inferior circular insula. Analyses by cognitive domain revealed nominal associations in domains of response speed, verbal learning, verbal retention, and visuospatial learning. CONCLUSIONS: WTC responders with MCI at midlife showed early signs of neurodegeneration characterized by both increased and decreased white matter diffusivity in regions commonly affected by early-onset Alzheimer's disease.
Keywords: Brain; Cognitive Dysfunction; Diffusion Tensor Imaging; Emergency Responders; Female; Humans; Incidence; Male; Middle Aged; September 11 Terrorist Attacks; White Matter

Awareness of the COVID-19 Outbreak and Resultant Depressive Tendencies in Patients with Severe Alzheimer's Disease. - Tsugawa, Akito; Sakurai, Shu; Inagawa, Yuta; Hirose, Daisuke; Kaneko, Yoshitsugu; Ogawa, Yusuke; Serisawa, Shuntaro; Takenoshita, Naoto; Sakurai, Hirofumi; Kanetaka, Hidekazu; Hirao, Kentaro; Shimizu, Soichiro (J Alzheimers Dis, 2020)
The ongoing coronavirus disease 2019 (COVID-19) pandemic has substantially affected patients with dementia and their caregivers. However, we found not all Alzheimer's disease (AD) patients were afraid of COVID-19 infection. Therefore, we investigated the association between rate of awareness of COVID-19 and depressive tendency in AD. 126 consecutive outpatients with AD were enrolled in this study from May 25, on the day when the declaration of emergency was lifted in Japan, through June 30, 2020. In addition to routine psychological tests, the participants were asked the following two questions: "Do you know COVID-19?" and "Why are you wearing a face mask?". Moderate to severe AD patients were found to have a low COVID-19 recognition rate and did not fully understand why they were wearing face masks. In addition, because they did not understand the seriousness of the COVID-19 outbreak, their Geriatric Depression Scale scores were also substantially lower. These results may appear to simply indicate that people with severe dementia are unaware of current events. However, these results provide insights into how to care for patients with dementia and how to allocate the time and support of our limited staff during the COVID-19 outbreak.
Keywords: Aged; Alzheimer Disease; Awareness; Betacoronavirus; Caregivers; Communicable Disease Control; Coronavirus Infections; COVID-19; Female; Humans; Japan; Male; Mental Competency; Pandemics; Patient Care; Pneumonia, Viral; Psychosocial Support Systems; SARS-CoV-2; Severity of Illness Index

Circulating Vitamin D Levels and Alzheimer's Disease: A Mendelian Randomization Study in the IGAP and UK Biobank. - Wang, Longcai; Qiao, Yanchun; Zhang, Haihua; Zhang, Yan; Hua, Jiao; Jin, Shuilin; Liu, Guiyou (J Alzheimers Dis, 2020)
Observational studies strongly supported the association of low levels of circulating 25-hydroxyvitamin D (25OHD) and cognitive impairment or dementia in aging populations. However, randomized controlled trials have not shown clear evidence that vitamin D supplementation could improve cognitive outcomes. In fact, some studies reported the association between vitamin D and cognitive impairment based on individuals aged 60 years and over. However, it is still unclear that whether vitamin D levels are causally associated with Alzheimer's disease (AD) risk in individuals aged 60 years and over. Here, we performed a Mendelian randomization (MR) study to investigate the causal association between vitamin D levels and AD using a large-scale vitamin D genome-wide association study (GWAS) dataset and two large-scale AD GWAS datasets from the IGAP and UK Biobank with individuals aged 60 years and over. Our results showed that genetically increased 25OHD levels were significantly associated with reduced AD risk in individuals aged 60 years and over. Hence, our findings in combination with previous literature indicate that maintaining adequate vitamin D status in older people especially aged 60 years and over, may contribute to slow down cognitive decline and forestall AD. Long-term randomized controlled trials are required to test whether vitamin D supplementation may prevent AD in older people especially those aged 60 years and may be recommended as preventive agents.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biological Specimen Banks; Cognition Disorders; Databases, Factual; Female; Genome-Wide Association Study; Humans; Hydroxycholecalciferols; Male; Mendelian Randomization Analysis; Middle Aged; Nutritional Status; United Kingdom; Vitamin D; Vitamin D Deficiency

Cognitive Impairment Is a Common Comorbidity in Deceased COVID-19 Patients: A Hospital-Based Retrospective Cohort Study. - Martín-Jiménez, Paloma; Muñoz-García, Mariana I; Seoane, David; Roca-Rodríguez, Lucas; García-Reyne, Ana; Lalueza, Antonio; Maestro, Guillermo; Folgueira, Dolores; Blanco-Palmero, Víctor A; Herrero-San Martín, Alejandro; Llamas-Velasco, Sara; Pérez-Martínez, David A; et al. (J Alzheimers Dis, 2020)
We analyzed the frequency of cognitive impairment (CI) in deceased COVID-19 patients at a tertiary hospital in Spain. Among the 477 adult cases who died after admission from March 1 to March 31, 2020, 281 had confirmed COVID-19. CI (21.1% dementia and 8.9% mild cognitive impairment) was a common comorbidity. Subjects with CI were older, tended to live in nursing homes, had shorter time from symptom onset to death, and were rarely admitted to the ICU, receiving palliative care more often. CI is a frequent comorbidity in deceased COVID-19 subjects and is associated with differences in care.
Keywords: Adolescent; Adult; Age Factors; Aged; Aged, 80 and over; Cognitive Dysfunction; Comorbidity; COVID-19; Female; Hospital Mortality; Hospitals; Humans; Male; Middle Aged; Palliative Care; Patient Admission; Retrospective Studies; Spain; Young Adult

Comparative Cognitive Effects of Choreographed Exercise and Multimodal Physical Therapy in Older Adults with Amnestic Mild Cognitive Impairment: Randomized Clinical Trial. - Bisbe, Marta; Fuente-Vidal, Andrea; López, Elisabet; Moreno, Marta; Naya, Marian; de Benetti, Claudio; Milà, Raimon; Bruna, Olga; Boada, Merce; Alegret, Montserrat (J Alzheimers Dis, 2020)
BACKGROUND: Recent research on mild cognitive impairment (MCI) has primarily focused on searching for measures to prevent or delay the progression of MCI to dementia. Physical exercise has shown to be effective in the prevention of age-related cognitive decline in elderly adults with MCI. However, the most effective type and dose of exercise for the improvement of cognition are yet to be determined. OBJECTIVE: To compare the cognitive effects of choreographed exercise (Choreography group) with a multimodal physical therapy program (Physical Therapy group) in elderly adults with amnestic MCI, a population with an increased risk of developing dementia. METHODS: We conducted a randomized clinical trial with two parallel groups under allocation concealment and assessor blinding. Participants were allocated into Choreography or Physical Therapy group and performed exercises twice per week in 60-minute sessions during 12 weeks. RESULTS: Thirty-six participants with amnestic MCI, ages 65 to 85, were assessed at baseline and after 12 weeks of intervention, by comprehensive validated neuropsychological and physical assessments. A Repeated measures General Lineal Model showed statistically significant differences in cognitive and physical outcomes. Both groups significantly improved in visual delayed recall. The Choreography group exhibited significantly more benefits on verbal recognition memory than the Physical Therapy group. CONCLUSION: Greater cognitive benefits were achieved in the choreographic intervention than in the multimodal physical therapy, mainly in those functions more related to the risk of conversion to dementia. Additional studies are needed to confirm whether the observed effects are related to delayed onset of Alzheimer's disease in elderly adults with amnestic MCI.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Combined Modality Therapy; Dance Therapy; Exercise Therapy; Female; Humans; Linear Models; Male; Neuropsychological Tests; Physical Therapy Modalities; Single-Blind Method

Death Rate Due to COVID-19 in Alzheimer's Disease and Frontotemporal Dementia. - Matías-Guiu, Jordi A; Pytel, Vanesa; Matías-Guiu, Jorge (J Alzheimers Dis, 2020)
We aimed to evaluate the frequency and mortality of COVID-19 in patients with Alzheimer's disease (AD) and frontotemporal dementia (FTD). We conducted an observational case series. We enrolled 204 patients, 15.2% of whom were diagnosed with COVID-19, and 41.9% of patients with the infection died. Patients with AD were older than patients with FTD (80.36±8.77 versus 72.00±8.35 years old) and had a higher prevalence of arterial hypertension (55.8% versus 26.3%). COVID-19 occurred in 7.3% of patients living at home, but 72.0% of those living at care homes. Living in care facilities and diagnosis of AD were independently associated with a higher probability of death. We found that living in care homes is the most relevant factor for an increased risk of COVID-19 infection and death, with AD patients exhibiting a higher risk than those with FTD.
Keywords: Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Coronavirus Infections; COVID-19; Female; Frontotemporal Dementia; Humans; Hypertension; Independent Living; Male; Nursing Homes; Pandemics; Pneumonia, Viral; Prevalence; Risk Factors

Dementia Care in Times of COVID-19: Experience at Fundació ACE in Barcelona, Spain. - Benaque, Alba; Gurruchaga, Miren Jone; Abdelnour, Carla; Hernandez, Isabel; Cañabate, Pilar; Alegret, Montserrat; Rodríguez, Isabel; Rosende-Roca, Maitee; Tartari, Juan Pablo; Esteban, Ester; López, Rogelio; Gil, Silvia; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Fundació ACE is a non-profit organization providing care based on a holistic model to persons with cognitive disorders and their families for 25 years in Barcelona, Spain. Delivering care to this vulnerable population amidst the COVID-19 pandemic has represented a major challenge to our institution. OBJECTIVE: To share our experience in adapting our model of care to the new situation to ensure continuity of care. METHODS: We detail the sequence of events and the actions taken within Fundació ACE to swiftly adapt our face-to-face model of care to one based on telemedicine consultations. We characterize individuals under follow-up by the Memory Unit from 2017 to 2019 and compare the number of weekly visits in 2020 performed before and after the lockdown was imposed. RESULTS: The total number of individuals being actively followed by Fundació ACE Memory Unit grew from 6,928 in 2017 to 8,147 in 2019. Among those newly diagnosed in 2019, most patients had mild cognitive impairment or mild dementia (42% and 25%, respectively). Weekly visits dropped by 60% following the suspension of face-to-face activity. However, by April 24 we were able to perform 78% of the visits we averaged in the weeks before confinement began. DISCUSSION: We have shown that Fundació ACE model of care has been able to successfully adapt to a health and social critical situation as COVID-19 pandemic. Overall, we were able to guarantee the continuity of care while preserving the safety of patients, families, and professionals. We also seized the opportunity to improve our model of care.
Keywords: Aged; Aged, 80 and over; Betacoronavirus; Coronavirus Infections; COVID-19; Dementia; Female; Follow-Up Studies; Holistic Health; Humans; Male; Pandemics; Patient-Centered Care; Pneumonia, Viral; SARS-CoV-2; Spain; Telemedicine

The Effects of Confinement on Neuropsychiatric Symptoms in Alzheimer's Disease During the COVID-19 Crisis. - Boutoleau-Bretonnière, Claire; Pouclet-Courtemanche, Hélene; Gillet, Aurelie; Bernard, Amelie; Deruet, Anne Laure; Gouraud, Ines; Mazoue, Aurelien; Lamy, Estelle; Rocher, Laetitia; Kapogiannis, Dimitrios; El Haj, Mohamad (J Alzheimers Dis, 2020)
BACKGROUND: Neuropsychiatric symptoms, such as depression, anxiety, apathy, agitation, and hallucinations, are frequent in Alzheimer's disease (AD) and their prevalence tends to increase with external stressors. OBJECTIVE: We offer the first investigation of the effects of confinement during the COVID-19 crisis on neuropsychiatric symptoms in patients with AD. METHODS: We contacted caregivers of 38 patients with AD who were confined to their homes for nearly two months and asked them to report whether patients experienced any change in neuropsychiatric symptoms during, compared to before, the confinement and rate its severity and impact on themselves using the Neuropsychiatric Inventory-Questionnaire. RESULTS: Among the 38 patients, only 10 demonstrated neuropsychiatric changes during the confinement. Cognitive function of these 10 patients, assessed with the Mini-Mental State Examination, was worse than that of patients who did not demonstrate neuropsychiatric changes. Interestingly, among the 10 patients with neuropsychiatric changes, the duration of confinement significantly correlated with the severity of symptoms as well as with their caregivers' distress. DISCUSSION: The confinement seems to impact neuropsychiatric symptomatology in AD patients with low baseline cognitive function.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Betacoronavirus; Cohort Studies; Coronavirus Infections; COVID-19; Female; Humans; Male; Mental Disorders; Mental Status and Dementia Tests; Middle Aged; Pandemics; Pneumonia, Viral; Quarantine; SARS-CoV-2

Resilience of Alzheimer's Disease to COVID-19. - Li, Jingwen; Long, Xi; Huang, Heqing; Tang, Jine; Zhu, Chunli; Hu, Shaoping; Wu, Jing; Li, Jinghong; Lin, Zhicheng; Xiong, Nian (J Alzheimers Dis, 2020)
BACKGROUND: Facing the novel coronavirus disease 2019 (COVID-19), most vulnerable individuals are seniors, especially those with comorbidities. More attention needs to been paid to the COVID-19 patients with Alzheimer's disease (AD), which is the top age-related neurodegenerative disease. OBJECTIVE: Since it is unclear whether AD patients are prone to COVID-19 infection and progression to severe stages, we report for the first time a retrospective analysis of the clinical characteristics of AD patients with COVID-19 pneumonia. METHODS: We conducted a retrospective cohort study of the clinical data of 19 AD patients with COVID-19 pneumonia, compared with 23 non-AD COVID-19 patients admitted at the same time to our hospital. Demographic, clinical, laboratory, radiological, and treatment data were collected and analyzed. RESULTS: Between AD patients and non-AD patients with COVID-19 pneumonia, the pneumonia severity was not significantly different. AD patients had a higher clustering onset than non-AD patients. The median duration from symptom onset to hospitalization were shorter in AD patients than non-AD patients, indicating the former were sent to the hospital by their family or from nursing home earlier than the later. The median duration from hospitalization to discharge seemed shorter in AD patients than non-AD patients. Dementia patients seemed less likely to report fatigue. It is noticed that more AD patients might have pericardial effusion than the non-AD patients. CONCLUSION: AD patients with COVID-19 were in milder conditions with a better prognosis than non-AD patients. AD patients who had adequate access to healthcare showed resilience to COVID-19 with shorter hospital stays.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cluster Analysis; Cohort Studies; Coronavirus Infections; COVID-19; Disease Progression; Fatigue; Female; Humans; Length of Stay; Male; Middle Aged; Pandemics; Patient Discharge; Pleural Effusion; Pneumonia; Pneumonia, Viral; Prognosis; Resilience, Psychological

Telemedicine for Delivery of Care in Frontotemporal Lobar Degeneration During COVID-19 Pandemic: Results from Southern Italy. - Capozzo, Rosa; Zoccolella, Stefano; Frisullo, Maria Elisa; Barone, Roberta; Dell'Abate, Maria Teresa; Barulli, Maria Rosaria; Musio, Marco; Accogli, Miriam; Logroscino, Giancarlo (J Alzheimers Dis, 2020)
BACKGROUND: The COVID-19 pandemic is changing clinical practice in neurology, after the governments decided the introduction of social distancing and interruption of medical non-emergency services in many countries. Teleneurology is an effective tool for the remote evaluation of patients but its adoption for frontotemporal lobar dementia (FTD) is in a preliminary stage. OBJECTIVE: We evaluated multidisciplinary assessment of patients with FTD using telehealth during the COVID-19 pandemic. METHODS: All patients received a diagnosis of FTD during 2018-2019 according to international criteria. A structured questionnaire and Clinical Dementia Rating Scale (CDR)-FTD were used by the neurologist with patients and/or caregivers. Index symptoms of COVID-19 infection were searched. RESULTS: Twenty-eight clinical interviews were completed with caregivers and four with both patients/caregivers. Most patients and caregivers were satisfied with the neurological interview and expressed their willingness to continue to be included in remote evaluation programs (90%). Fifty percent of patients experienced significant worsening of clinical picture and quality of life since the start of social distancing. The CDR-FTD scale revealed a significant worsening of behavior (p = 0.01) and language functions (p = 0.009), compared to the last in-person evaluation at the center. One patient presented index symptoms of COVID-19 infection and was confirmed to be positive for COVID-19 with pharyngeal swab. CONCLUSION: The study was conducted in Italy, one of the countries hit particularly hard by the COVID-19 pandemic, with interruption of all non-emergency medical services. Our study indicates that telemedicine is a valid tool to triage patients with FTD to increase practice outreach and efficiency.
Keywords: Aged; Aged, 80 and over; Behavior; Coronavirus Infections; COVID-19; Delivery of Health Care; Disease Progression; Female; Frontotemporal Lobar Degeneration; Humans; Italy; Language; Male; Mental Status and Dementia Tests; Middle Aged; Pandemics; Pneumonia, Viral; Quality of Life; Quarantine; Surveys and Questionnaires; Telemedicine; Triage

11C-CFT-PET in Presymptomatic FTDP-17: A Potential Biomarker Predicting Onset. - Wu, Liyong; Liu, Jia; Feng, Xueyan; Dong, Jing; Qin, Wei; Liu, Yang; Wang, Jingjuan; Lu, Jie; Chen, Kewei; Wang, Yuping; Jia, Jianping (J Alzheimers Dis, 2018)
Frontotemporal dementia with parkinsonism-linked to chromosome 17 (FTDP-17) is a rare autosomal dominant neurodegenerative disorder. Most patients with FTDP-17 carry the mutation in the microtubule-associated protein tau (MAPT) gene. Striatum is predominantly and early affected in FTDP-17. Five family members (two symptomatic patients and three presymptomatic mutation carriers) from a Chinese pedigree of FTDP-17 with N279K mutation in MAPT were enrolled. Parkinsonism was the initial symptom for symptomatic patients. 2b-carbomethoxy-3b-(4-trimethylstannylphenyl) tropane (11C-CFT) uptake was obviously affected in the putamen of two presymptomatic mutation carriers. Presymptomatic case 3, whose 11C-CFT uptake in the right putamen was normal at baseline, was still free of parkinsonism during follow-up. In conclusion, 11C-CFT-positron emission tomography could be a potential biomarker for the presymptomatic stage of FTDP-17 to predict the disease onset.
Keywords: Adult; Biomarkers; Brain; Carbon Radioisotopes; Female; Frontotemporal Dementia; Heterozygote; Humans; Male; Middle Aged; Mutation; Parkinsonian Disorders; Pedigree; Positron-Emission Tomography; tau Proteins

Age-Related Changes in the Spatial Frequency Threshold of Male and Female 3xTg-AD Mice Using OptoMotry. - King, Jillian L; Wong, Aimée A; Brown, Richard E (J Alzheimers Dis, 2018)
Visual impairments and retinal abnormalities occur in patients with Alzheimer's disease (AD) and in mouse models of AD. It is important to know the visual ability of mouse models of AD to ensure that age-related cognitive deficits are not confounded by visual impairments. Using OptoMotry, the spatial frequency thresholds of male and female 3xTg-AD mice did not differ from their B6129SF2 wildtype controls between 1-18 months of age, but females had higher spatial frequency thresholds than males. However, the differences were quite small, and the visual ability of all mice was comparable to that of C57BL/6 mice.
Keywords: Aging; Alzheimer Disease; Animals; Disease Models, Animal; Female; Humans; Male; Maze Learning; Mice; Mice, Inbred C57BL; Mice, Transgenic; Sex Characteristics; tau Proteins; Vision, Ocular

Albuminuria and Microalbuminuria as Predictors of Cognitive Performance in a General Population: An 11-Year Follow-Up Study. - Ekblad, Laura L; Toppala, Sini; Johansson, Jouni K; Koskinen, Seppo; Sundvall, Jouko; Rinne, Juha O; Puukka, Pauli; Viitanen, Matti; Jula, Antti (J Alzheimers Dis, 2018)
Microalbuminuria, defined as urine albumin-to-creatinine ratio (UACR)>3.0 mg/mmol and ≤ 30 mg/mmol, is an early marker of endothelial damage of the renal glomeruli. Recent research suggests an association among microalbuminuria, albuminuria (UACR > 3.0 mg/mmol), and cognitive impairment. Previous studies on microalbuminuria, albuminuria, and cognition in the middle-aged have not provided repeated cognitive testing at different time-points. We hypothesized that albuminuria (micro- plus macroalbuminuria) and microalbuminuria would predict cognitive decline independently of previously reported risk factors for cognitive decline, including cardiovascular risk factors. In addition, we hypothesized that UACR levels even below the cut-off for microalbuminuria might be associated with cognitive functioning. These hypotheses were tested in the Finnish nationwide, population-based Health 2000 Survey (n = 5,921, mean age 52.6, 55.0% women), and its follow-up, Health 2011 (n = 3,687, mean age at baseline 49.3, 55.6% women). Linear regression analysis was used to determine the associations between measures of albuminuria and cognitive performance. Cognitive functions were assessed with verbal fluency, word-list learning, word-list delayed recall (at baseline and at follow-up), and with simple and visual choice reaction time tests (at baseline only). Here, we show that micro- plus macroalbuminuria associated with poorer word-list learning and a slower reaction time at baseline, with poorer word-list learning at follow-up, and with a steeper decline in word-list learning during 11 years after multivariate adjustments. Also, higher continuous UACR consistently associated with poorer verbal fluency at levels below microalbuminuria. These results suggest that UACR might have value in evaluating the risk for cognitive decline.
Keywords: Adult; Aged; Albuminuria; Cognition; Cognitive Dysfunction; Creatinine; Cross-Sectional Studies; Female; Finland; Follow-Up Studies; Humans; Kidney; Linear Models; Male; Middle Aged; Multivariate Analysis; Neuropsychological Tests; Risk Factors

Alterations in Acrolein Metabolism Contribute to Alzheimer's Disease. - Tsou, Han-Hsing; Hsu, Wen-Chin; Fuh, Jong-Ling; Chen, Shih-Pin; Liu, Tsung-Yun; Wang, Hsiang-Tsui (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a detrimental neurodegenerative disease, and early diagnosis appears to be the key to successful treatment. Acrolein, a byproduct of lipid peroxidation, has been shown to contribute to the pathological process of AD. This study recruited 118 elderly subjects consisting of 58 non-demented control subjects and 62 AD patients. We analyzed the acrolein-related metabolites in the plasma, cerebrospinal fluid (CSF), and urine of all subjects. We found that the levels of acrolein-conjugated protein (Acr-PC) in the plasma (p = 0.00012) and CSF (p = 0.00161) of AD patients were significantly higher than those of control subjects, whereas the levels of a urinary acrolein metabolite, 3-hydroxypropyl mercapturic acid (3-HPMA), were markedly decreased (p = 0.00882) in AD patients. These data suggest that deregulated acrolein metabolism may be correlated with neuronal damage in AD patients, which might provide further insights into the disease progression and early diagnosis of AD.
Keywords: Acetylcysteine; Acrolein; Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Creatinine; Disease Progression; Early Diagnosis; Female; Humans; Male; Middle Aged

Altered Expression of Circulating Cdc42 in Frontotemporal Lobar Degeneration. - Saraceno, Claudia; Catania, Marcella; Paterlini, Anna; Fostinelli, Silvia; Ciani, Miriam; Zanardini, Roberta; Binetti, Giuliano; Di Fede, Giuseppe; Caroppo, Paola; Benussi, Luisa; Ghidoni, Roberta; Bolognin, Silvia (J Alzheimers Dis, 2018)
The term frontotemporal lobar degeneration (FTLD) defines a group of heterogeneous conditions histologically characterized by neuronal degeneration, inclusions of various proteins, and synaptic loss. However, the molecular mechanisms contributing to these alterations are still unknown. As the Rho-GTPase family member Cell division cycle 42 (Cdc42) plays a key role in the regulation of actin cytoskeleton dynamics and spine formation, we investigated whether Cdc42 protein levels were altered in the disease. Cdc42 was increased in the frontal cortex of FTLD patients compared to age-matched controls, but also in Alzheimer's disease (AD) patients included in the data-set. On the other hand, the pool of circulating Cdc42 in the plasma was altered in FTLD but not in AD patients. Interestingly, the stratification of the FTLD patients according to the different clinical variants showed a specific decrease of Cdc42 expression in the behavioral subgroup. This data support a role of Cdc42 in FTLD and specifically in the behavioral variant.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Case-Control Studies; cdc42 GTP-Binding Protein; Female; Frontotemporal Lobar Degeneration; Humans; Male; Middle Aged

Alzheimer-Like Pattern of Hypometabolism Emerges with Elevated Amyloid-β Burden in Down Syndrome. - Lao, Patrick J; Handen, Ben L; Betthauser, Tobey J; Mihaila, Iulia; Hartley, Sigan L; Cohen, Annie D; Tudorascu, Dana L; Bulova, Peter D; Lopresti, Brian J; Tumuluru, Rameshwari V; Murali, Dhanabalan; Mathis, Chester A; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The Down syndrome (DS) population is genetically predisposed to amyloid-β protein precursor overproduction and Alzheimer's disease (AD). OBJECTIVE: The temporal ordering and spatial association between amyloid-β, glucose metabolism, and gray matter (GM) volume in the DS population can provide insight into those associations in the more common sporadic AD. METHODS: Twenty-four adults (13 male, 11 female; 39±7 years) with DS underwent [11C]PiB, [18F]FDG, and volumetric MRI scans. Voxel-wise associations between PiB SUVR, FDG SUVR, and GM volume were investigated, with and without individual adjustments for variables of interest. RESULTS: Positive associations of PiB and age were widespread throughout the neocortex and striatum. Negative associations of FDG and age (frontal, parietal, and temporal cortex) and of GM volume and age (frontal and insular cortex) were observed. PiB and FDG were negatively associated in parietal cortex, after adjustment for GM volume. CONCLUSIONS: In adults with DS, early amyloid-β accumulation in the striatum is divergent from sporadic AD; however, despite the early striatal amyloid-β, glucose hypometabolism was confined to the typical AD-associated regions, which occurs similarly in autosomal dominant AD. Importantly, the glucose hypometabolism was not explained solely by increased partial volume effect due to GM volume reductions.
Keywords: Adult; Alzheimer Disease; Amyloid beta-Peptides; Down Syndrome; Female; Fluorodeoxyglucose F18; Gray Matter; Humans; Linear Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Positron-Emission Tomography; Radiopharmaceuticals; United States

Alzheimer's Disease Progression: Factors Influencing Cognitive Decline. - Ferrari, Camilla; Lombardi, Gemma; Polito, Cristina; Lucidi, Giulia; Bagnoli, Silvia; Piaceri, Irene; Nacmias, Benedetta; Berti, Valentina; Rizzuto, Debora; Fratiglioni, Laura; Sorbi, Sandro (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) patients present high variability in the rate of cognitive decline. Despite the wide knowledge on factors influencing dementia risk, little is known on what accounts for AD progression. Previous studies on this topic have mainly analyzed each factor separately without taking into account the interaction between genetic and non-genetic factors. OBJECTIVE: The aim of the present study is to evaluate the role of demographic, clinical, therapeutic, and genetic factors and their interaction on cognitive decline among newly diagnosed AD patients. METHODS: We retrospectively selected 160 AD patients diagnosed at the Neurology Unit of Careggi University Hospital of Florence. We evaluated the occurrence of rapid cognitive changes defined as the worsening of more than four points at the Mini-Mental State Examination after 2-year follow up period. RESULTS: Among the 160 AD patients, 50% presented rapid disease progression. Extrapyramidal signs at disease onset were predictors of worse outcome (OR 2.2), especially among Apolipoprotein E (APOE) ɛ4 allele carriers, while the presence of family history for dementia decreased the risk of rapid progression by about 50%. Higher educated ɛ4-carriers showed a slower AD progression. We identified the chronic use of aspirin as potential secondary preventative strategy for the non ɛ4-carriers. CONCLUSION: At dementia onset, some clinical and demographic data can be predictors of future progression. The outcomes of the present study support the already hypothesized interaction between genetic and non-genetic factors during disease course and suggest genetic-based approaches.
Keywords: Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Aspirin; Cognitive Dysfunction; Disease Progression; Female; Heterozygote; Humans; Italy; Male; Middle Aged; Neuropsychological Tests; Retrospective Studies; Secondary Prevention

Aphasia in Progressive Supranuclear Palsy: As Severe as Progressive Non-Fluent Aphasia. - Burrell, James R; Ballard, Kirrie J; Halliday, Glenda M; Hodges, John R (J Alzheimers Dis, 2018)
BACKGROUND: Adynamic speech is characteristic of progressive supranuclear palsy (PSP), but higher language deficits have been reported inconsistently, in the context of clinical and pathological overlaps with progressive non-fluent aphasia (PNFA). OBJECTIVE: The present study tested two hypotheses: 1) PSP and PNFA display impaired single word repetition, object naming, semantic knowledge, and syntactic comprehension; and 2) PSP have reduced speed on timed cognitive tasks. METHODS: Structured clinical and neuropsychological assessments of language were performed on patients with clinically defined PSP and PNFA. Language was tested using the Sydney Language Battery (SYDBAT) and the Test of Reception of Grammar (TROG). RESULTS: In total, 144 participants were studied (PSP 22, PNFA 29, and Control 93). PSP patients had prominent eye movement abnormalities, parkinsonism, and falls. All 4 PSP patients who underwent postmortem examination had 4-Repeat tauopathy, with PSP pathology in 3. The frequency and severity of impairment on the SYDBAT (naming, word comprehension, semantic association), and TROG (syntactic comprehension) did not differ between PSP and PNFA, but PSP were significantly slower on timed non-language cognitive tests. CONCLUSION: Tested formally, aphasia may be seen in PSP, with a severity similar to that seen in PNFA.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Cognition; Female; Humans; Language Tests; Male; Middle Aged; Primary Progressive Nonfluent Aphasia; Semantics; Speech; Supranuclear Palsy, Progressive

Apparent Cognitive Decline as Revealed by an Executive Function Test within a Cohort of Elderly Individuals Self-Reporting Normal Cognitive Performance. - Shea, Thomas B; Remington, Ruth (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) can be preceded by subtle memory decline that can last a decade or more before progressing to what would be diagnosed as the mild cognitive impairment stage. During this early stage of decline, individuals and even their caregivers can fail to perceive any serious difficulty or need to consult a physician. Herein, we present evidence in support of these concerns, and demonstrate how this can interfere not only with clinical trials of AD but also those involving cognitive performance of elderly individuals without intentional reference to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Cognitive Dysfunction; Cohort Studies; Executive Function; Female; Humans; Male; Memory; Neuropsychological Tests; Self Report

An Aspartyl Cathepsin Targeted PET Agent: Application in an Alzheimer's Disease Mouse Model. - Snir, Jonatan A; Suchy, Mojmir; Bindseil, Geron A; Kovacs, Michael; Chronik, Blaine A; Hudson, Robert H E; Pasternak, Stephen H; Bartha, Robert (J Alzheimers Dis, 2018)
BACKGROUND: Early detection of Alzheimer's disease (AD) pathology is a serious challenge for both diagnosis and clinical trials. The aspartyl protease, Cathepsin D (CatD), is overexpressed in AD and could be a biomarker of disease. We have previously designed a unique contrast agent (CA) for dual-optical and magnetic resonance imaging of the activity of the CatD class of enzymes. OBJECTIVE: To compare the uptake and retention of a novel, more sensitive, and clinically-translatable 68Ga PET tracer targeting CatD activity in 5XFAD mice and non-Tg littermates. METHODS: The targeted CA consisted of an HIV-1 Tat cell penetrating peptide (CPP) conjugated to a specialized cleavage sequence targeting aspartyl cathepsins and a DOTA conjugate chelating 68Ga. PET images were acquired using a Siemens Inveon preclinical microPET in female Tg AD mice and non-Tg age matched female littermates (n = 5-8) following intravenous CA administration at 2, 6, and 9 months of age. Additionally, 18F fluorodeoxyglucose (FDG) PET imaging was performed at 10 months to measure glucose uptake. RESULTS: The Tg mice showed significantly higher relative uptake rate of the targeting CA in the forebrain relative to hindbrain at all ages compared to controls, consistent with histology. In contrast, no differences were seen in CA uptake in other organs. Additionally, the Tg mice did not show any differences in relative uptake of FDG at 10 months of age in the forebrain relative to the hindbrain compared to age matched non-Tg controls. CONCLUSIONS: Elevated aspartryl cathepsin activity was detected in vivo in the 5XFAD mouse model of AD using a novel targeted PET contrast agent.
Keywords: Alzheimer Disease; Animals; Brain; Cathepsin D; Contrast Media; Disease Models, Animal; Female; Fluorodeoxyglucose F18; Glucose; Mice; Mice, Transgenic; Positron-Emission Tomography

Assay of Plasma Phosphorylated Tau Protein (Threonine 181) and Total Tau Protein in Early-Stage Alzheimer's Disease. - Yang, Che-Chuan; Chiu, Ming-Jang; Chen, Ta-Fu; Chang, Hui-Ling; Liu, Bing-Hsien; Yang, Shieh-Yueh (J Alzheimers Dis, 2018)
The feasibility of assaying plasma phosphorylated tau protein (threonine 181), denoted p-tau181, using immunomagnetic reduction (IMR) is explored. The reagent for assaying p-tau181 with IMR was synthesized, and its analytic performances were characterized. Seventy-three subjects were recruited. Each participant was examined with neuropsychological tests, magnetic resonance imaging, and IMR assay for plasma p-tau181. Using commercially available IMR kits, the plasma total tau protein (T-tau) of each subject was assayed. The dynamic range for assaying p-tau181 using IMR was 1.96×10-2 pg/ml to 104 pg/ml. There was no significant interference from total tau protein in the assay of p-tau181. The measured concentrations of plasma p-tau181 were 2.46±1.09 pg/ml for healthy controls, 4.41±1.85 pg/ml for MCI due to AD, and 6.14±1.59 pg/ml for very mild AD. Meanwhile, the measured concentrations of plasma T-tau were 18.85±10.16 pg/ml for healthy controls, 32.98±10.18 pg/ml for MCI due to AD, and 37.54±12.29 pg/ml for very mild AD. A significant difference in plasma p-tau181 was observed between healthy controls and MCI due to AD (p < 0.001) and between MCI due to AD and very mild AD (p < 0.001). However, for the plasma T-tau concentration, a significant difference existed only between healthy controls and MCI due to AD (p < 0.001). This implies that the plasma p-tau181 level is correlated more to AD severity than plasma T-tau is. Additionally, p-tau181 was observed as approximately 14% of T-tau in human plasma.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Phosphorylation; tau Proteins

Assessing Working Memory in Mild Cognitive Impairment with Serial Order Recall. - Emrani, Sheina; Libon, David J; Lamar, Melissa; Price, Catherine C; Jefferson, Angela L; Gifford, Katherine A; Hohman, Timothy J; Nation, Daniel A; Delano-Wood, Lisa; Jak, Amy; Bangen, Katherine J; Bondi, Mark W; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Working memory (WM) is often assessed with serial order tests such as repeating digits backward. In prior dementia research using the Backward Digit Span Test (BDT), only aggregate test performance was examined. OBJECTIVE: The current research tallied primacy/recency effects, out-of-sequence transposition errors, perseverations, and omissions to assess WM deficits in patients with mild cognitive impairment (MCI). METHODS: Memory clinic patients (n = 66) were classified into three groups: single domain amnestic MCI (aMCI), combined mixed domain/dysexecutive MCI (mixed/dys MCI), and non-MCI where patients did not meet criteria for MCI. Serial order/WM ability was assessed by asking participants to repeat 7 trials of five digits backwards. Serial order position accuracy, transposition errors, perseverations, and omission errors were tallied. RESULTS: A 3 (group)×5 (serial position) repeated measures ANOVA yielded a significant group×trial interaction. Follow-up analyses found attenuation of the recency effect for mixed/dys MCI patients. Mixed/dys MCI patients scored lower than non-MCI patients for serial position 3 (p < 0.003) serial position 4 (p < 0.002); and lower than both group for serial position 5 (recency; p < 0.002). Mixed/dys MCI patients also produced more transposition errors than both groups (p < 0.010); and more omissions (p < 0.020), and perseverations errors (p < 0.018) than non-MCI patients. CONCLUSIONS: The attenuation of a recency effect using serial order parameters obtained from the BDT may provide a useful operational definition as well as additional diagnostic information regarding working memory deficits in MCI.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Executive Function; Female; Humans; Male; Memory Disorders; Memory, Short-Term; Mental Recall; Neuropsychological Tests; Regression Analysis; Serial Learning

Assessment of the Genetic Architecture of Alzheimer's Disease Risk in Rate of Memory Decline. - Del-Aguila, Jorge L; Fernández, Maria Victoria; Schindler, Suzanne; Ibanez, Laura; Deming, Yuetiva; Ma, Shengmei; Saef, Ben; Black, Kathleen; Budde, John; Norton, Joanne; Chasse, Rachel; Harari, Oscar; et al. (J Alzheimers Dis, 2018)
Many genetic studies for Alzheimer's disease (AD) have been focused on the identification of common genetic variants associated with AD risk and not on other aspects of the disease, such as age at onset or rate of dementia progression. There are multiple approaches to untangling the genetic architecture of these phenotypes. We hypothesized that the genetic architecture of rate of progression is different than the risk for developing AD dementia. To test this hypothesis, we used longitudinal clinical data from ADNI and the Knight-ADRC at Washington University, and we calculated PRS (polygenic risk score) based on the IGAP study to compare the genetic architecture of AD risk and dementia progression. Dementia progression was measured by the change of Clinical Dementia Rating Sum of Boxes (CDR)-SB per year. Out of the 21 loci for AD risk, no association with the rate of dementia progression was found. The PRS rate was significantly associated with the rate of dementia progression (β= 0.146, p = 0.03). In the case of rare variants, TREM2 (β= 0.309, p = 0.02) was also associated with the rate of dementia progression. TREM2 variant carriers showed a 23% faster rate of dementia compared with non-variant carriers. In conclusion, our results indicate that the recently identified common and rare variants for AD susceptibility have a limited impact on the rate of dementia progression in AD patients.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Dementia; Disease Progression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Humans; Longitudinal Studies; Male; Membrane Glycoproteins; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Immunologic; Risk Assessment

Association between α-Klotho and Deep White Matter Lesions in the Brain: A Pilot Case Control Study Using Brain MRI. - Kuriyama, Nagato; Ozaki, Etsuko; Mizuno, Toshiki; Ihara, Masafumi; Mizuno, Shigeto; Koyama, Teruhide; Matsui, Daisuke; Watanabe, Isao; Akazawa, Kentaro; Takeda, Kazuo; Takada, Akihiro; Inaba, Masaaki; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The anti-aging protein, α-Klotho, may be involved in cognitive decline and has potential as a surrogate marker that reflects dementia. However, the role of α-Klotho in the brain has not been sufficiently investigated. OBJECTIVE: Here, we investigated the association between α-Klotho and cognitive decline that is associated with cerebral deep white matter lesions (DWMLs). METHODS: Two hundred-eighty participants (187 males and 93 females, mean age: 70.8 years old) were evaluated for DWMLs, and the Fazekas scale (Grade) was assessed following brain magnetic resonance imaging. A questionnaire concerning lifestyle and neuropsychological tests was administered, and their associations with the blood α-Klotho level were retrospectively investigated. RESULTS: The α-Klotho level was 685.1 pg/mL in Grade 0 (68 subjects), 634.1 in G1 (134), 596.0 in G2 (62), and 571.6 in G3 (16), showing that the level significantly decreased with advanced grades. Significant correlations were noted between the α-Klotho level and higher brain function tests including the Mini-Mental State Examination and word fluency tests (p < 0.05). When a 90th percentile value of the level in the G0 group (400 pg/mL) or lower was defined as a low α-Klotho level, the odds ratio of the high-grade G3 group was 2.9 (95% confidence interval: 1.4-7.8) (after correction for age, sex, hypertension, and chronic kidney disease), which was significant. CONCLUSION: A reduced blood α-Klotho level was correlated with grading of cerebral DWMLs and was accompanied by cognitive decline as an independent risk factor. The α-Klotho level may serve as a useful clinical index of vascular cognitive impairment.
Keywords: Aged; Aged, 80 and over; Apolipoprotein E4; Brain; C-Reactive Protein; Case-Control Studies; Cognition Disorders; Female; Glucuronidase; Humans; Image Processing, Computer-Assisted; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Pilot Projects; Severity of Illness Index

Association of Cerebrospinal Fluid (CSF) Insulin with Cognitive Performance and CSF Biomarkers of Alzheimer's Disease. - Geijselaers, Stefan L C; Aalten, Pauline; Ramakers, Inez H G B; De Deyn, Peter Paul; Heijboer, Annemieke C; Koek, Huiberdina L; OldeRikkert, Marcel G M; Papma, Janne M; Reesink, Fransje E; Smits, Lieke L; Stehouwer, Coen D A; Teunissen, Charlotte E; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Abnormal insulin signaling in the brain has been linked to Alzheimer's disease (AD). OBJECTIVE: To evaluate whether cerebrospinal fluid (CSF) insulin levels are associated with cognitive performance and CSF amyloid-β and Tau. Additionally, we explore whether any such association differs by sex or APOE ɛ4 genotype. METHODS: From 258 individuals participating in the Parelsnoer Institute Neurodegenerative Diseases, a nationwide multicenter memory clinic population, we selected 138 individuals (mean age 66±9 years, 65.2% male) diagnosed with subjective cognitive impairment (n = 45), amnestic mild cognitive impairment (n = 44), or AD (n = 49), who completed a neuropsychological assessment, including tests of global cognition and memory performance, and who underwent lumbar puncture. We measured CSF levels of insulin, amyloid-β1-42, total (t-)Tau, and phosphorylated (p-)Tau. RESULTS: CSF insulin levels did not differ between the diagnostic groups (p = 0.136). Across the whole study population, CSF insulin was unrelated to cognitive performance and CSF biomarkers of AD, after adjustment for age, sex, body mass index, diabetes status, and clinic site (all p≥0.131). Importantly, however, we observed effect modification by sex and APOE ɛ4 genotype. Specifically, among women, higher insulin levels in the CSF were associated with worse global cognition (standardized regression coefficient -0.483; p = 0.008) and higher p-Tau levels (0.353; p = 0.040). Among non-carriers of the APOE ɛ4 allele, higher CSF insulin was associated with higher t-Tau (0.287; p = 0.008) and p-Tau (0.246; p = 0.029). CONCLUSION: Our findings provide further evidence for a relationship between brain insulin signaling and AD pathology. It also highlights the need to consider sex and APOE ɛ4 genotype when assessing the role of insulin.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Brain; Cognition Disorders; Female; Humans; Insulin; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Signal Transduction; tau Proteins

Association of Low-Level Ozone with Cognitive Decline in Older Adults. - Cleary, Ekaterina Galkina; Cifuentes, Manuel; Grinstein, Georges; Brugge, Doug; Shea, Thomas B (J Alzheimers Dis, 2018)
Increasing evidence points to an association of airborne pollutant exposure with respiratory, cardiovascular, and neurological pathology. We examined whether or not ground-level ozone or fine particulate matter ≤ 2.5 μm in diameter (PM2.5) was associated with accelerated cognitive decline. Using repeated measures mixed regression modeling, we analyzed cognitive performance of a geographically diverse sampling of individuals from the National Alzheimer's Coordinating Center between 2004-2008. Ambient air concentrations of ozone and PM2.5 were established using a space-time Hierarchical Bayesian Model that statistically merged air monitor data and modeled air quality estimates. We then compared the ambient regional concentrations of ozone and PM2.5 with the rate of cognitive decline in residents within those regions. Increased levels of ozone correlated with an increased rate of cognitive decline, following adjustment for key individual and community-level risk factors. Furthermore, individuals harboring one or more APOE4 alleles exhibited a faster rate of cognitive decline. The deleterious association of ozone was confined to individuals with normal cognition who eventually became cognitively impaired as opposed to those who entered the study with baseline impairment. In contrast to ozone, we did not observe any correlation between ambient PM2.5 and cognitive decline at regulatory limits set by the Environmental Protection Agency. Our findings suggest that prolonged exposure to ground-level ozone may accelerate cognitive decline during the initial stages of dementia development.
Keywords: Age Distribution; Aged; Aged, 80 and over; Aging; Air Pollutants; Cognitive Dysfunction; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Ozone; Regression Analysis; Retrospective Studies; United States

Association of the New Variant Tyr424Asp at TBK1 Gene with Amyotrophic Lateral Sclerosis and Cognitive Decline. - Piaceri, Irene; Bessi, Valentina; Matà, Sabrina; Polito, Cristina; Tedde, Andrea; Berti, Valentina; Bagnoli, Silvia; Braccia, Arianna; Del Mastio, Monica; Pignone, Alberto Moggi; Pupi, Alberto; Sorbi, Sandro; et al. (J Alzheimers Dis, 2018)
A new risk gene associated with amyotrophic lateral sclerosis (ALS) has recently been identified: the Tank-binding kinase 1 (TBK1) gene. Up to now, 90 TBK1 variants have been described in ALS patients with or without frontotemporal dementia (FTD), thus making TBK1 the third or fourth most frequent genetic cause of ALS and FTD. A point mutation analysis in a cohort of 69 Italian ALS patients was performed in order to analyze the frequency of TBK1 mutations and the correlation with clinical phenotypes. The analysis identified the novel variant p.Tyr424Asp in a patient with a rapid progression of the disease. Our data supports the implication of TBK1 in ALS pathogenesis in Italy.
Keywords: Aged; Amyotrophic Lateral Sclerosis; Aspartic Acid; C9orf72 Protein; Cognitive Dysfunction; DNA Mutational Analysis; Female; Fluorodeoxyglucose F18; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Italy; Male; Mental Status and Dementia Tests; Middle Aged; Mutation; Neuropsychological Tests; Positron-Emission Tomography; Protein-Serine-Threonine Kinases; Tyrosine

Associations between Use of Specific Analgesics and Concentrations of Amyloid-β 42 or Phospho-Tau in Regions of Human Cerebral Cortex. - Flanagan, Margaret E; Larson, Eric B; Walker, Rod L; Keene, C Dirk; Postupna, Nadia; Cholerton, Brenna; Sonnen, Joshua A; Dublin, Sascha; Crane, Paul K; Montine, Thomas J (J Alzheimers Dis, 2018)
Analgesics are commonly used by older adults, raising the question of whether their use might contribute to dementia risk and neuropathologic changes of Alzheimer's disease (AD). The Adult Changes in Thought (ACT) study is a population-based study of brain aging and incident dementia among people 65 years or older who are community dwelling and not demented at entry. Amyloid-β (Aβ)42 and phospho-tau were quantified using Histelide in regions of cerebral cortex from 420 brain autopsies. Total standard daily doses of prescription opioid and non-aspirin nonsteroidal anti-inflammatory drug (NSAID) exposure during a defined 10-year exposure window were identified using automated pharmacy dispensing data and used to classify people as having no/low, intermediate, or high exposure. People with high NSAID exposure had significantly greater Aβ42 concentration in middle frontal gyrus and superior and middle temporal gyri, but not inferior parietal lobule; no Aβ42 regional concentration was associated with prescription opioid usage. People with high opioid usage had significantly greater concentration of phospho-tau in middle frontal gyrus than people with little-to-no opioid usage. Consistent with our previous studies, findings suggest that high levels of NSAID use in older individuals may promote Aβ42 accumulation in cerebral cortex.
Keywords: Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analgesics; Analgesics, Opioid; Anti-Inflammatory Agents, Non-Steroidal; Autopsy; Cerebral Cortex; Female; Humans; Logistic Models; Male; Peptide Fragments; Prospective Studies; tau Proteins

Associations of Dietary Protein and Fiber Intake with Brain and Blood Amyloid-β. - Fernando, W M A D Binosha; Rainey-Smith, Stephanie R; Gardener, Samantha L; Villemagne, Victor L; Burnham, Samantha C; Macaulay, S Lance; Brown, Belinda M; Gupta, Veer Bala; Sohrabi, Hamid R; Weinborn, Michael; Taddei, Kevin; Laws, Simon M; et al. (J Alzheimers Dis, 2018)
Accumulating evidence suggests a diet high in protein and fiber may confer some protection against Alzheimer's disease (AD). However, no human studies to-date have assessed the relationship between protein and fiber intake, and plasma and brain amyloid-β (Aβ). Consequently, this cross-sectional study, investigated the association of self-reported dietary intakes of protein and fiber, with plasma and brain Aβ burden (n = 541, and n = 162 respectively), in a well-characterized cohort of cognitively normal older adults, drawn from the larger Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging. We observed 12.59 and 8.43 higher odds of 'high' brain Aβ burden (PiB PET SUVR≥1.5) if protein intake fell in the lowest and middle tertile, respectively, compared to the highest tertile (p = 0.008; p = 0.013). Thus, in this cohort, the more protein consumed, the less likelihood of 'high' Aβ burden in the brain. No other significant associations were observed. The results of this study highlight the potentially protective impact of high dietary protein intake on brain Aβ burden in older adults, before objective memory decline is apparent. While longitudinal validation is required, these findings may assist in the development of dietary approaches aimed at preventing or delaying AD onset.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Australia; Biomarkers; Brain; Cognition; Cohort Studies; Cross-Sectional Studies; Dietary Fiber; Dietary Proteins; Female; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography

Biallelic Loss of Function of SORL1 in an Early Onset Alzheimer's Disease Patient. - Le Guennec, Kilan; Tubeuf, Hélène; Hannequin, Didier; Wallon, David; Quenez, Olivier; Rousseau, Stéphane; Richard, Anne-Claire; Deleuze, Jean-François; Boland, Anne; Frebourg, Thierry; Gaildrat, Pascaline; Campion, Dominique; et al. (J Alzheimers Dis, 2018)
Heterozygous SORL1 protein truncating variants (PTV) are a strong risk factor for early-onset Alzheimer's disease (EOAD). In case control studies performed at the genome-wide level, PTV definition is usually straightforward. Regarding splice site variants, only those affecting canonical sites are typically included. Some other variants, not annotated as PTV, could, however, affect splicing and hence result in a loss of SORL1 function. We took advantage of the whole exome sequencing data from the 9/484 patients with a previously reported SORL1 PTV in the French EOAD series and searched for a second variant which may affect splicing and eventually result in more than 50% loss of function overall. We found that one patient, known to carry a variant predicted to disrupt the canonical 5' splice site of exon 8, also carried a second novel intronic variant predicted to affect SORL1 splicing of exon 29. Segregation analysis showed that the second variant was located in trans from the known PTV. We performed ex vivo minigene splicing assays and showed that both variants led to the generation of transcripts containing a premature stop codon. This is therefore the first evidence of a human carrying biallelic SORL1 PTV. This patient had a family history of dementia in both maternal and paternal lineages with later ages of onset than the proband himself. However, his 55 years age at onset was in the same ranges as previously published SORL1 heterozygous PTV carriers. This suggests that biallelic loss of SORL1 function is an extremely rare event that was not associated with a dramatically earlier age at onset than heterozygous SORL1 loss-of-function variant carriers, in this single patient.
Keywords: Alzheimer Disease; Case-Control Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Humans; LDL-Receptor Related Proteins; Male; Membrane Transport Proteins; Middle Aged; Risk Factors

Biological Factors Contributing to the Response to Cognitive Training in Mild Cognitive Impairment. - Peter, Jessica; Schumacher, Lena V; Landerer, Verena; Abdulkadir, Ahmed; Kaller, Christoph P; Lahr, Jacob; Klöppel, Stefan (J Alzheimers Dis, 2018)
In mild cognitive impairment (MCI), small benefits from cognitive training were observed for memory functions but there appears to be great variability in the response to treatment. Our study aimed to improve the characterization and selection of those participants who will benefit from cognitive intervention. We evaluated the predictive value of disease-specific biological factors for the outcome after cognitive training in MCI (n = 25) and also considered motivation of the participants. We compared the results of the cognitive intervention group with two independent control groups of MCI patients (local memory clinic, n = 20; ADNI cohort, n = 302). The primary outcome measure was episodic memory as measured by verbal delayed recall of a 10-word list. Episodic memory remained stable after treatment and slightly increased 6 months after the intervention. In contrast, in MCI patients who did not receive an intervention, episodic memory significantly decreased during the same time interval. A larger left entorhinal cortex predicted more improvement in episodic memory after treatment and so did higher levels of motivation. Adding disease-specific biological factors significantly improved the prediction of training-related change compared to a model based simply on age and baseline performance. Bootstrapping with resampling (n = 1000) verified the stability of our finding. Cognitive training might be particularly helpful in individuals with a bigger left entorhinal cortex as individuals who did not benefit from intervention showed 17% less volume in this area. When extended to alternative treatment options, stratification based on disease-specific biological factors is a useful step towards individualized medicine.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Apolipoproteins E; Biological Factors; Cognitive Behavioral Therapy; Cognitive Dysfunction; Entorhinal Cortex; Female; Follow-Up Studies; Functional Laterality; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Mental Recall; Middle Aged; Neuropsychological Tests; Reaction Time; Spatial Navigation; Treatment Outcome

Cardiorespiratory Fitness and White Matter Neuronal Fiber Integrity in Mild Cognitive Impairment. - Ding, Kan; Tarumi, Takashi; Zhu, David C; Tseng, Benjamin Y; Thomas, Binu P; Turner, Marcel; Repshas, Justin; Kerwin, Diana R; Womack, Kyle B; Lu, Hanzhang; Cullum, C Munro; Zhang, Rong (J Alzheimers Dis, 2018)
BACKGROUND: Mounting evidence showed the self-reported levels of physical activity are positively associated with white matter (WM) integrity and cognitive performance in normal adults and patients with mild cognitive impairment (MCI). However, the objective measure of cardiorespiratory fitness (CRF) was not used in these studies. OBJECTIVE: To determine the associations of CRF measured by maximal oxygen uptake (VO2max) with WM fiber integrity and neurocognitive performance in older adults with MCI. METHODS: Eighty-one participants (age = 65±7 years, 43 women), including 26 cognitively normal older adults and 55 amnestic MCI patients, underwent VO2max test to measure CRF, diffusion tensor imaging (DTI) to assess WM fiber integrity, and neurocognitive assessment focused on memory and executive function. DTI data were analyzed by the tract-based spatial statistics and region-of-interest approach. RESULTS: Cognitively normal older adults and MCI patients were not different in global WM fiber integrity and VO2max. VO2max was associated positively with DTI metrics of fractional anisotropy in ∼54% WM fiber tracts, and negatively with mean and radial diffusivities in ∼46% and ∼56% of the WM fiber tracts. The associations of VO2max with DTI metrics remained statistically significant after adjustment of age, sex, body mass index, WM lesion burden, and MCI status. The DTI metrics obtained from the area that correlated to VO2max were associated with executive function performance in MCI patients. CONCLUSIONS: Higher levels of CRF are associated with better WM fiber integrity, which in turn is correlated with better executive function performance in MCI patients.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anisotropy; Cardiorespiratory Fitness; Case-Control Studies; Cognition; Cognitive Dysfunction; Diffusion Tensor Imaging; Executive Function; Female; Humans; Linear Models; Male; Memory; Middle Aged; Nerve Fibers, Myelinated; Neuropsychological Tests; Texas; White Matter

Cerebrospinal Fluid Amyloid-β Levels are Increased in Patients with Insomnia. - Chen, Dong-Wan; Wang, Jun; Zhang, Li-Li; Wang, Yan-Jiang; Gao, Chang-Yue (J Alzheimers Dis, 2018)
Previous studies demonstrate that patients with sleep disorders are at risk of developing Alzheimer's disease (AD), with the mechanism unknown. It is suggested that acute sleep deprivation induces an increase of amyloid-β (Aβ), the major pathological agent in AD, in the cerebrospinal fluid (CSF). In the present study, we recruited 23 patients with chronic insomnia aged between 46 to 67 years and 23 healthy controls aged between 43 to 67 years. We investigated the CSF levels of Aβ and tau, another pathological hallmark in the AD pathogenesis. We found that CSF Aβ42 levels were significantly increased in insomnia patients. However, no significant difference was found in Aβ40, total tau (t-Tau), and phosphorylated tau (p-Tau) between the two groups. Furthermore, we found that CSF Aβ40 and Aβ42 levels are significantly correlated with the sleep quality, as reflected by the Pittsburgh Sleep Quality Index (PSQI) scores. But no significant correlation was found in CSF t-Tau and p-Tau levels with PSQI. Our results indicate that chronic sleep disorders may induce the disruption of Aβ metabolism in the brain, thus increase the risk for developing AD.
Keywords: Adult; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Female; Humans; Male; Middle Aged; Phosphorylation; Sleep Initiation and Maintenance Disorders; tau Proteins

Cerebrospinal Fluid C-C Motif Chemokine Ligand 2 Correlates with Brain Atrophy and Cognitive Impairment in Alzheimer's Disease. - Kimura, Akio; Yoshikura, Nobuaki; Hayashi, Yuichi; Inuzuka, Takashi (J Alzheimers Dis, 2018)
BACKGROUND: Chronic neuroinflammation has been implicated in Alzheimer's disease (AD) pathology. OBJECTIVE: To investigate the association between cytokine and anti-amyloid-β (Aβ) autoantibody levels and the degree of brain atrophy and cognitive impairment in AD patients. METHODS: Cerebrospinal fluid (CSF) levels of C-C motif chemokine ligand 2 (CCL2), C-X-C motif chemokine ligand 8, C-X-C motif chemokine ligand 10, interleukin 6, and anti-Aβ autoantibody were evaluated in 69 AD patients. Serum levels of CCL2 and anti-Aβ autoantibody were also examined. The degree of brain atrophy was assessed using the voxel-based specific regional analysis system for AD, which targets the volumes of interest (VOI) in medial temporal structures. Cognitive function was evaluated by neuropsychological testing, including the Mini-Mental State Examination (MMSE) and Frontal Assessment Battery (FAB). RESULTS: CSF CCL2 levels correlated significantly with the severity (p = 0.023) and the extent (p = 0.022) of VOI atrophy, and with the extent of gray matter atrophy (p = 0.039) in AD patients. CSF anti-Aβ autoantibody levels were inversely correlated with the severity of VOI atrophy (p = 0.020), the extent of VOI atrophy (p = 0.015), and the ratio of VOI/GM atrophy (r = -0.358, p = 0.004). CSF CCL2 levels were also inversely correlated with MMSE (p = 0.0497) and FAB scores (p = 0.016). CONCLUSIONS: CSF CCL2 levels are associated with the degree of medial temporal lobe and gray matter atrophy, and cognitive decline in AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Atrophy; Biomarkers; Chemokine CCL2; Cognitive Dysfunction; Disease Progression; Female; Gray Matter; Humans; Linear Models; Magnetic Resonance Imaging; Male; Neuropsychological Tests; tau Proteins; Temporal Lobe

Cerebrospinal Fluid, MRI, and Florbetaben-PET in Cerebral Amyloid Angiopathy-Related Inflammation. - Renard, Dimitri; Collombier, Laurent; Demattei, Christophe; Wacongne, Anne; Charif, Mahmoud; Ayrignac, Xavier; Azakri, Souhayla; Gaillard, Nicolas; Boudousq, Vincent; Lehmann, Sylvain; Menjot de Champfleur, Nicolas; Thouvenot, Eric (J Alzheimers Dis, 2018)
BACKGROUND: Cerebral amyloid angiopathy-related inflammation (CAA-ri) is associated with a cerebrospinal fluid (CSF) biomarker profile similar to that observed in CAA. Few CAA-ri patients have been studied by fibrillar amyloid-β (Aβ) imaging (using 11C-Pittsburgh compound B and 18F-florbetapir, but not 18F-florbetaben). OBJECTIVE: To describe CSF biomarkers, magnetic resonance imaging (MRI), and 18F-florbetaben (FBB)-positron emission tomography (PET) changes in CAA-ri patients. METHODS: CSF levels of total tau, phosphorylated tau, Aβ1-42, and Aβ1-40, MRI (cerebral microbleeds count on susceptibility-weighted imaging and semi-quantitative analysis of fluid-attenuation inversion recovery white matter hyperintensities), and FBB-PET (using both cerebellar cortex and pons to calculate standardized uptake value ratios) were analyzed in nine consecutive CAA-ri patients. RESULTS: A median number of 769 cerebral microbleeds/patient were counted on MRI. When using the pons as reference region, amyloid load on FBB-PET was very strongly correlated to CSF Aβ1-40 levels (rho = -0.83, p = 0.008) and moderately correlated to cerebral microbleed numbers in the occipital lobes (rho = 0.59, p = 0.001), while comparisons with other CSF biomarkers were not statistically significant (total tau, rho = -0.63, p = 0.076; phosphorylated tau, rho = -0.68, p = 0.05; Aβ1-42, rho = -0.59, p = 0.09). All correlations were weaker, and not statistically significant, when using the cerebellum as reference region. A non-significant correlation (rho = -0.50, p = 0.18) was observed between CSF Aβ1-40 levels and cerebral microbleed numbers. CONCLUSION: In CAA-ri, CSF Aβ1-40 levels correlated well with amyloid load assessed by FBB-PET when the pons was used as reference, and to a lesser degree with cerebral microbleeds count on MRI. This confirms earlier data on CSF Aβ1-40 as an in vivo marker for CAA and CAA-ri.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Aniline Compounds; Biomarkers; Brain; Cerebral Amyloid Angiopathy; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Positron-Emission Tomography; Prospective Studies; Stilbenes; tau Proteins; Vasculitis, Central Nervous System

Characteristics of Cognitively Normal Mexican-Americans with Cognitive Complaints. - Hall, James R; Wiechmann, April; Johnson, Leigh A; Edwards, Melissa; O'Bryant, Sid E (J Alzheimers Dis, 2018)
BACKGROUND: Subjective cognitive complaints in cognitively normal adults have been linked to later cognitive decline and dementia. Research on the characteristics of this group has been conducted on a variety of clinical and community-based populations. The current study focuses on the rapidly expanding population of Mexican-American elders. OBJECTIVE: The objective of the study is the determination of characteristics of cognitively normal Mexican-Americans with cognitive complaints. METHODS: Data on 319 cognitively normal participants in a large-scale community-based study of elderly Mexican-Americans (HABLE) were analyzed comparing those with cognitive complaints with those without on clinical characteristics, affective status, neuropsychological functioning, and proteomic markers. RESULTS: Those expressing concern about cognitive decline scored lower on the MMSE, were more likely to have significantly more affective symptoms, higher levels of diabetic markers, poorer performance on attention and executive functioning, and a different pattern of inflammatory markers. CONCLUSION: Although longitudinal research is needed to determine the impact of these differences on later cognition, possible targets for early intervention with Mexican-Americans were identified.
Keywords: Aged; Biomarkers; Cognition; Cognitive Dysfunction; Executive Function; Female; Humans; Male; Mexican Americans; Middle Aged; Neuropsychological Tests; Risk Factors; Texas

Circulating Progenitor Cells Correlate with Memory, Posterior Cortical Thickness, and Hippocampal Perfusion. - Nation, Daniel A; Tan, Alick; Dutt, Shubir; McIntosh, Elissa C; Yew, Belinda; Ho, Jean K; Blanken, Anna E; Jang, Jung Yun; Rodgers, Kathleen E; Gaubert, Aimée (J Alzheimers Dis, 2018)
BACKGROUND: Bone marrow-derived progenitor cells survey the vasculature and home to sites of tissue injury where they can promote repair and regeneration. It has been hypothesized that these cells may play a protective role neurodegenerative and vascular cognitive impairment. OBJECTIVE: To evaluate progenitor cell levels in older adults with and without mild cognitive impairment (MCI), and to relate circulating levels to memory, brain volume, white matter lesion volume, and cerebral perfusion. METHOD: Thirty-two older adults, free of stroke and cardiovascular disease, were recruited from the community and evaluated for diagnosis of MCI versus cognitively normal (CN). Participants underwent brain MRI and blood samples were taken to quantify progenitor reserve using flow cytometry (CD34+, CD34+CD133+, and CD34+CD133+CD309+ cells). RESULTS: Participants with MCI (n = 10) exhibited depletion of all CPC markers relative to those who were CN (n = 22), after controlling for age, sex, and education. Post-hoc age, sex, and education matched comparisons (n = 10 MCI, n = 10 CN) also revealed the same pattern of results. Depletion of CD34+ cells correlated with memory performance, left posterior cortical thickness, and bilateral hippocampal perfusion. Participants exhibited low levels of vascular risk and white matter lesion burden that did not correlate with progenitor levels. CONCLUSIONS: Circulating progenitor cells are associated with cognitive impairment, memory, cortical atrophy, and hippocampal perfusion. We hypothesize that progenitor depletion contributes to, or is triggered by, cognitive decline and cortical atrophy. Further study of progenitor cell depletion in older adults may benefit efforts to prevent or delay dementia.
Keywords: Aged; Aged, 80 and over; Antigens, CD; Apolipoproteins E; Cerebral Cortex; Cognitive Dysfunction; Female; Flow Cytometry; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Perfusion; Stem Cells; White Matter

A Clinically-Translatable Machine Learning Algorithm for the Prediction of Alzheimer's Disease Conversion in Individuals with Mild and Premild Cognitive Impairment. - Grassi, Massimiliano; Perna, Giampaolo; Caldirola, Daniela; Schruers, Koen; Duara, Ranjan; Loewenstein, David A (J Alzheimers Dis, 2018)
BACKGROUND: Available therapies for Alzheimer's disease (AD) can only alleviate and delay the advance of symptoms, with the greatest impact eventually achieved when provided at an early stage. Thus, early identification of which subjects at high risk, e.g., with MCI, will later develop AD is of key importance. Currently available machine learning algorithms achieve only limited predictive accuracy or they are based on expensive and hard-to-collect information. OBJECTIVE: The current study aims to develop an algorithm for a 3-year prediction of conversion to AD in MCI and PreMCI subjects based only on non-invasively and effectively collectable predictors. METHODS: A dataset of 123 MCI/PreMCI subjects was used to train different machine learning techniques. Baseline information regarding sociodemographic characteristics, clinical and neuropsychological test scores, cardiovascular risk indexes, and a visual rating scale for brain atrophy was used to extract 36 predictors. Leave-pair-out-cross-validation was employed as validation strategy and a recursive feature elimination procedure was applied to identify a relevant subset of predictors. RESULTS: 16 predictors were selected from all domains excluding sociodemographic information. The best model resulted a support vector machine with radial-basis function kernel (whole sample: AUC = 0.962, best balanced accuracy = 0.913; MCI sub-group alone: AUC = 0.914, best balanced accuracy = 0.874). CONCLUSIONS: Our algorithm shows very high cross-validated performances that outperform the vast majority of the currently available algorithms, and all those which use only non-invasive and effectively assessable predictors. Further testing and optimization in independent samples will warrant its application in both clinical practice and clinical trials.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Area Under Curve; Atrophy; Brain; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Machine Learning; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Predictive Value of Tests; Prognosis; Regression Analysis; Sensitivity and Specificity; Support Vector Machine

Clinic-Based Validation of Cerebrospinal Fluid Biomarkers with Florbetapir PET for Diagnosis of Dementia. - Álvarez, Ignacio; Aguilar, Miquel; González, Jose Manuel; Ysamat, Montse; Lorenzo-Bosquet, Carles; Alonso, Alvaro; Tartari, Juan Pablo; Romero, Silvia; Diez-Fairen, Monica; Carcel, Maria; Pujalte, Francisco; Pastor, Pau (J Alzheimers Dis, 2018)
BACKGROUND: Cerebrospinal fluid (CSF) biomarker studies have shown variable accuracy for diagnosis of Alzheimer's disease (AD); therefore, internal validation is recommended. OBJECTIVE: To investigate the correlation between CSF biomarkers and cerebral 18-Florbetapir positron emission tomography (Amyloid-PET) and calculate their sensitivity and specificity to obtain the optimal clinical cut-off points to diagnose the etiology of cognitive impairment. METHODS: We performed Amyloid-PET scans and CSF biomarker levels analyses in 68 subjects (50 with mild cognitive impairment, 11 with AD dementia, and 7 with non-AD dementia). Visual examination of Amyloid-PET scans was performed. CSF analyses were performed using standard sandwich ELISA. RESULTS: Amyloid-PET was positive in 36 subjects, negative in 26, and inconclusive in 6. Optimal clinical cut-off points for CSF markers were the following: amyloid-β 1-42 (Aβ42) = 629 pg/ml, total tau (t-tau) = 532 pg/ml, phosphorylated tau (p-tau) = 88 pg/ml, and t-tau/Aβ42 ratio = 0.58. T-tau/Aβ42 ratio showed the best sensitivity and specificity (92 and 84%, respectively). T-tau and p-tau CSF levels (r2 = 0.867) followed by the t-tau and t-tau/Aβ42 CSF ratio (r2 = 0.666) showed the strongest inter-marker correlation. Interestingly, subjects with inconclusive Amyloid-PET showed intermediate values for all CSF markers between negative and positive Amyloid-PET groups. CONCLUSIONS: CSF t-tau/Aβ42 ratio appears to be the most accurate AD CSF marker. The presence of intermediate values for CSF markers among the subjects with inconclusive Amyloid-PET suggests the presence of other dementias associated with AD pathology or intermediate phenotypes.
Keywords: Aged; Amyloid beta-Peptides; Analysis of Variance; Aniline Compounds; Apolipoproteins E; Biomarkers; Cognition Disorders; Dementia; Ethylene Glycols; Female; Humans; Male; Middle Aged; Peptide Fragments; Positron-Emission Tomography; tau Proteins

Cognitive Variability Predicts Incident Alzheimer's Disease and Mild Cognitive Impairment Comparable to a Cerebrospinal Fluid Biomarker. - Gleason, Carey E; Norton, Derek; Anderson, Eric D; Wahoske, Michelle; Washington, Danielle T; Umucu, Emre; Koscik, Rebecca L; Dowling, N Maritza; Johnson, Sterling C; Carlsson, Cynthia M; Asthana, Sanjay (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) biomarkers are emerging as critically important for disease detection and monitoring. Most biomarkers are obtained through invasive, resource-intense procedures. A cognitive marker, intra-individual cognitive variability (IICV) may provide an alternative or adjunct marker of disease risk for individuals unable or disinclined to undergo lumbar puncture. OBJECTIVE: To contrast risk of incident AD and mild cognitive impairment (MCI) associated with IICV to risk associated with well-established biomarkers: cerebrospinal fluid (CSF) phosphorylated tau protein (p-tau181) and amyloid-β 42 (Aβ42) peptide. METHODS: Dispersion in cognitive performance, IICV, was estimated with a published algorithm, and included Trail Making Test A and B, Rey Auditory Verbal Learning Test (RAVLT), and the American National Adult Reading Test (ANART). CSF biomarkers were expressed as a ratio: p-tau181/Aβ42, wherein high values signified pathognomonic profiles. Logistic regression models included longitudinal data from 349 Alzheimer's Disease Neuroimaging Initiative (ADNI) participants who completed lumbar puncture. All subjects were cognitively healthy (n = 105) or diagnosed with MCI (n = 244) at baseline. We examined odds of conversion associated with baseline elevations in IICV and/or ratio of CSF p-tau181/Aβ42. RESULTS: When included in models alone or in combination with CSF p-tau181/Aβ42, one standard IICV unit higher was associated with an estimated odds ratio for incident AD or MCI of 2.81 (95% CI: 1.83-4.33) in the most inclusive sample, and an odds ratio of 3.41 (95% CI: 2.03-5.73) when restricted to participants with MCI. Iterative analyses suggested that IICV independently improved model fit even when individual index components were included in comparative models. CONCLUSIONS: These analyses provide preliminary support for IICV as a marker of incident AD and MCI. This easily-disseminated, non-invasive marker compared favorably to well-established CSF biomarkers.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Incidence; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Statistics, Nonparametric; tau Proteins

Combined Socio-Behavioral Evaluation Improves the Differential Diagnosis Between the Behavioral Variant of Frontotemporal Dementia and Alzheimer's Disease: In Search of Neuropsychological Markers. - Dodich, Alessandra; Cerami, Chiara; Cappa, Stefano F; Marcone, Alessandra; Golzi, Valeria; Zamboni, Michele; Giusti, Maria Cristina; Iannaccone, Sandro (J Alzheimers Dis, 2018)
BACKGROUND: Current diagnostic criteria for behavioral variant of frontotemporal dementia (bvFTD) and typical Alzheimer's disease (AD) include a differential pattern of neuropsychological impairments (episodic memory deficit in typical AD and dysexecutive syndrome in bvFTD). There is, however, large evidence of a frequent overlap in neuropsychological features, making the differential diagnosis extremely difficult. OBJECTIVES: In this retrospective study, we evaluated the diagnostic value of different cognitive and neurobehavioral markers in bvFTD and AD patient groups. METHODS: We included 95 dementia patients with a clinical and biomarker evidence of bvFTD (n = 48) or typical AD (n = 47) pathology. A clinical 2-year follow-up confirmed clinical classification. Performances at basic cognitive tasks (memory, executive functions, visuo-spatial, language) as well as social cognition skills and neurobehavioral profiles have been recorded. A stepwise logistic regression model compared the neuropsychological profiles between groups and assessed the accuracy of cognitive and neurobehavioral markers in discriminating bvFTD from AD. RESULTS: Statistical comparison between patient groups proved social cognition and episodic memory impairments as main cognitive signatures of bvFTD and AD neuropsychological profiles, respectively. Only half of bvFTD patients showed attentive/executive deficits, questioning their role as cognitive marker of bvFTD. Notably, the large majority of bvFTD sample (i.e., 70%) poorly performed at delayed recall tasks. Logistic regression analysis identified social cognition performances, Frontal Behavioral Inventory and Mini-Mental State Examination scores as the best combination in distinguishing bvFTD from AD. CONCLUSION: Social cognition tasks and socio-behavioral questionnaires are recommended in clinical settings to improve the accuracy of early diagnosis of bvFTD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cognition; Diagnosis, Differential; Female; Frontotemporal Dementia; Humans; Logistic Models; Male; Memory, Episodic; Mental Recall; Middle Aged; Neuropsychological Tests; Retrospective Studies; Social Skills

Comparison between FCSRT and LASSI-L to Detect Early Stage Alzheimer's Disease. - Matías-Guiu, Jordi A; Cabrera-Martín, María Nieves; Curiel, Rosie E; Valles-Salgado, María; Rognoni, Teresa; Moreno-Ramos, Teresa; Carreras, José Luis; Loewenstein, David A; Matías-Guiu, Jorge (J Alzheimers Dis, 2018)
BACKGROUND: The Free and Cued Selective Reminding Test (FCSRT) is the most accurate test for the diagnosis of prodromal Alzheimer's disease (AD). Recently, a novel cognitive test, the Loewenstein-Acevedo Scale for Semantic Interference and Learning (LASSI-L), has been developed in order to provide an early diagnosis. OBJECTIVE: To compare the diagnostic accuracy of the FCSRT and the LASSI-L for the diagnosis of AD in its preclinical and prodromal stages using 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) as a reference. METHODS: Fifty patients consulting for subjective memory complaints without functional impairment and at risk for AD were enrolled and evaluated using FCSRT, LASSI-L, and FDG-PET. Participants were evaluated using a comprehensive neurological and neuropsychological protocol and were assessed with the FCSRT and LASSI-L. FDG-PET was acquired concomitantly and used for classification of patients as AD or non-AD according to brain metabolism using both visual and semi-quantitative methods. RESULTS: LASSI-L scores allowed a better classification of patients as AD/non-AD in comparison to FCSRT. Logistic regression analysis showed delayed recall and failure to recovery from proactive semantic interference from LASSI-L as independent statistically significant predictors, obtaining an area under the curve of 0.894. This area under the curve provided a better discrimination than the best FCSRT score (total delayed recall, area under the curve 0.708, p = 0.029). CONCLUSIONS: The LASSI-L, a cognitive stress test, was superior to FCSRT in the prediction of AD features on FDG-PET. This emphasizes the possibility to advance toward an earlier diagnosis of AD from a clinical perspective.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cues; Female; Fluorodeoxyglucose F18; Humans; Male; Memory Disorders; Mental Recall; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Psychiatric Status Rating Scales; ROC Curve; Semantics

Concordance Between Cerebrospinal Fluid Biomarkers with Alzheimer's Disease Pathology Between Three Independent Assay Platforms. - Doecke, James D; Rembach, Alan; Villemagne, Victor L; Varghese, Shiji; Rainey-Smith, Stephanie; Sarros, Shannon; Evered, Lisbeth A; Fowler, Christopher J; Pertile, Kelly K; Rumble, Rebecca L; Trounson, Brett; Taddei, Kevin; et al. (J Alzheimers Dis, 2018)
BACKGROUND: To enhance the accuracy of clinical diagnosis for Alzheimer's disease (AD), pre-mortem biomarkers have become increasingly important for diagnosis and for participant recruitment in disease-specific treatment trials. Cerebrospinal fluid (CSF) biomarkers provide a low-cost alternative to positron emission tomography (PET) imaging for in vivo quantification of different AD pathological hallmarks in the brains of affected subjects; however, consensus around the best platform, most informative biomarker and correlations across different methodologies are controversial. OBJECTIVE: Assessing levels of Aβ-amyloid and tau species determined using three different versions of immunoassays, the current study explored the ability of CSF biomarkers to predict PET Aβ-amyloid (32 Aβ-amyloid-and 45 Aβ-amyloid+), as well as concordance between CSF biomarker levels and PET Aβ-amyloid imaging. METHODS: Prediction and concordance analyses were performed using a sub-cohort of 77 individuals (48 healthy controls, 15 with mild cognitive impairment, and 14 with AD) from the Australian Imaging Biomarker and Lifestyle study of aging. RESULTS: Across all three platforms, the T-tau/Aβ42 ratio biomarker had modestly higher correlation with SUVR/BeCKeT (ρ= 0.69-0.8) as compared with Aβ42 alone (ρ= 0.66-0.75). Differences in CSF biomarker levels between the PET Aβ-amyloid-and Aβ-amyloid+ groups were strongest for the Aβ42/Aβ40 and T-tau/Aβ42 ratios (p < 0.0001); however, comparison of predictive models for PET Aβ-amyloid showed no difference between Aβ42 alone and the T-tau/Aβ42 ratio. CONCLUSION: This study confirms strong concordance between CSF biomarkers and PET Aβ-amyloid status is independent of immunoassay platform, supporting their utility as biomarkers in clinical practice for the diagnosis of AD and for participant enrichment in clinical trials.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition Disorders; Female; Humans; Male; Mental Status Schedule; Peptide Fragments; Positron-Emission Tomography; ROC Curve; tau Proteins

Decreased Prefrontal Activation during Matrix Reasoning in Predementia Progranulin Mutation Carriers. - Alexander, Courtney; Zeithamova, Dagmar; Hsiung, Ging-Yuek R; Mackenzie, Ian R; Jacova, Claudia (J Alzheimers Dis, 2018)
We tested the potential of task-based functional neuroimaging as a biomarker of emerging prefrontal brain changes in progranulin (GRN) mutations carriers. Five GRN mutation carriers free of frontotemporal dementia (FTD) and 11 non-carriers from families with FTD-GRN underwent functional MRI while solving matrix-reasoning problems. Mutation carriers displayed slower responses for more difficult problems and lower lateral prefrontal activation across all problems. Overall task-evoked posterior ventrolateral prefrontal activation predicted mutation status with 100% sensitivity and 91% specificity. Volumetric differences did not account for activation differences. Prefrontal activation may have utility as a biomarker in GRN mutation.
Keywords: Adult; Biomarkers; Female; Frontotemporal Dementia; Functional Neuroimaging; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Prefrontal Cortex; Progranulins

Deep Brain Stimulation of Frontal Lobe Networks to Treat Alzheimer's Disease. - Scharre, Douglas W; Weichart, Emily; Nielson, Dylan; Zhang, Jun; Agrawal, Punit; Sederberg, Per B; Knopp, Michael V; Rezai, Ali R (J Alzheimers Dis, 2018)
The study objective was to evaluate the safety and efficacy of deep brain stimulation (DBS) at the ventral capsule/ventral striatum (VC/VS) region to specifically modulate frontal lobe behavioral and cognitive networks as a novel treatment approach for Alzheimer's disease (AD) patients. This is a non-randomized phase I prospective open label interventional trial of three subjects with matched comparison groups. AD participants given DBS for at least 18 months at the VC/VS target were compared on the Clinical Dementia Rating-Sum of Boxes (CDR-SB), our primary outcome clinical measure, to matched groups without DBS from the AD Neuroimaging Initiative (ADNI) cohort. Serial 2-Deoxy-2-[18F]fluoro-D-glucose (FDG) positron emission tomography (PET) images of AD participants were also compared longitudinally over time. Three AD DBS participants were matched to subjects from the ADNI cohort. All participants tolerated DBS well without significant adverse events. All three AD DBS participants had less performance decline and two of them meaningfully less decline over time on our primary outcome measure, CDR-SB, relative to matched comparison groups from the ADNI using score trajectory slopes. Minimal changes or increased metabolism on FDG-PET were seen in frontal cortical regions after chronic DBS at the VC/VS target. The first use of DBS in AD at a frontal lobe behavior regulation target (VC/VS) was well-tolerated and revealed less performance decline in CDR-SB. Frontal network modulation to improve executive and behavioral deficits should be furthered studied in AD.
Keywords: Aged; Alzheimer Disease; Deep Brain Stimulation; Female; Frontal Lobe; Humans; Male; Middle Aged; Ohio; Pilot Projects; Positron-Emission Tomography; Prospective Studies

Delirium Severity Post-Surgery and its Relationship with Long-Term Cognitive Decline in a Cohort of Patients without Dementia. - Vasunilashorn, Sarinnapha M; Fong, Tamara G; Albuquerque, Asha; Marcantonio, Edward R; Schmitt, Eva M; Tommet, Douglas; Gou, Yun; Travison, Thomas G; Jones, Richard N; Inouye, Sharon K (J Alzheimers Dis, 2018)
BACKGROUND: Delirium has been associated with more rapid cognitive decline. However, it is unknown whether increased delirium severity is associated with a higher rate of long-term cognitive decline. OBJECTIVE: To evaluate delirium severity and the presence and rate of cognitive decline over 36 months following surgery. METHODS: We examined patients from the Successful Aging after Elective Surgery Study, who were age ≥70 years undergoing major elective surgery (N = 560). Delirium severity was determined by the peak Confusion Assessment Method-Severity (CAM-S) score for each patient's hospitalization and grouped based on the sample distribution: scores of 0-2, 3-7, and 8-19. A neuropsychological composite, General Cognitive Performance (GCP), and proxy-reported Informant Questionnaire for Cognitive Decline (IQCODE) were used to examine cognitive outcomes following surgery at 0, 1, and 2 months, and then every 6 months for up to 3 years. RESULTS: No significant cognitive decline was observed for patients with peak CAM-S scores 0-2 (-0.17 GCP units/year, 95% confidence interval [CI] -0.35, 0.01). GCP scores decreased significantly in the group with peak CAM-S scores 3-7 (-0.30 GCP units/year, 95% CI -0.51, -0.09), and decreased almost three times faster in the highest delirium severity group (peak CAM-S scores 8-19; -0.82 GCP units/year, 95% CI -1.28, -0.37). A similar association was found for delirium severity and the proportion of patients who developed IQCODE impairment over time. CONCLUSION: Patients with the highest delirium severity experienced the greatest rate of cognitive decline, which exceeds the rate previously observed for patients with dementia, on serial neuropsychological testing administered over 3 years, with a dose-response relationship between delirium severity and long-term cognitive decline.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Delirium; Elective Surgical Procedures; Female; Humans; Male; Neuropsychological Tests; Postoperative Complications; Severity of Illness Index

Designing an Internet-Based Multidomain Intervention for the Prevention of Cardiovascular Disease and Cognitive Impairment in Older Adults: The HATICE Trial. - Barbera, Mariagnese; Mangialasche, Francesca; Jongstra, Susan; Guillemont, Juliette; Ngandu, Tiia; Beishuizen, Cathrien; Coley, Nicola; Brayne, Carol; Andrieu, Sandrine; Richard, Edo; Soininen, Hilkka; Kivipelto, Miia (J Alzheimers Dis, 2018)
BACKGROUND: Many dementia and cardiovascular disease (CVD) cases in older adults are attributable to modifiable vascular and lifestyle-related risk factors, providing opportunities for prevention. In the Healthy Aging Through Internet Counselling in the Elderly (HATICE) randomized controlled trial, an internet-based multidomain intervention is being tested to improve the cardiovascular risk (CVR) profile of older adults. OBJECTIVE: To design a multidomain intervention to improve CVR, based on the guidelines for CVR management, and administered through a coach-supported, interactive, platform to over 2500 community-dwellers aged 65+ in three European countries. METHODS: A comparative analysis of national and European guidelines for primary and secondary CVD prevention was performed. Results were used to define the content of the intervention. RESULTS: The intervention design focused on promoting awareness and self-management of hypertension, dyslipidemia, diabetes mellitus, and overweight, and supporting smoking cessation, physical activity, and healthy diet. Overall, available guidelines lacked specific recommendations for CVR management in older adults. The comparative analysis of the guidelines showed general consistency for lifestyle-related recommendations. Key differences, identified mostly in methods used to assess the overall CVR, did not hamper the intervention design. Minor country-specific adaptations were implemented to maximize the intervention feasibility in each country. CONCLUSION: Despite differences in CVR management within the countries considered, it was possible to design and implement the HATICE multidomain intervention. The study can help define preventative strategies for dementia and CVD that are applicable internationally.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cognitive Dysfunction; Counseling; Europe; Exercise; Female; Healthy Aging; Humans; Internet; Life Style; Male; Practice Guidelines as Topic; Risk Factors; Telemedicine

Detection of Dementia Cases in Two Swedish Health Registers: A Validation Study. - Rizzuto, Debora; Feldman, Adina L; Karlsson, Ida K; Dahl Aslan, Anna K; Gatz, Margaret; Pedersen, Nancy L (J Alzheimers Dis, 2018)
BACKGROUND: Population-based health registers are potential assets in epidemiological research; however, the quality of case ascertainment is crucial. OBJECTIVE: To compare the case ascertainment of dementia, from the National Patient Register (NPR) and the Cause of Death Register (CDR) with dementia diagnoses from six Swedish population based studies. METHODS: Sensitivity, specificity, and positive predictive value (PPV) of dementia identification in NPR and CDR were estimated by individual record linkage with six Swedish population based studies (n = 19,035). Time to detection in NPR was estimated using data on dementia incidence from longitudinal studies with more than two decades of follow-up. RESULTS: Barely half of the dementia cases were ever detected by NPR or CDR. Using data from longitudinal studies we estimated that a record with a dementia diagnosis appears in the NPR on average 5.5 years after first diagnosis. Although the ability of the registers to detect dementia cases was moderate, the ability to detect non-dementia cases was almost perfect (99%). When registers indicate that there is a dementia diagnosis, there are very few instances in which the clinicians determined the person was not demented. Indeed, PPVs were close to 90%. However, misclassification between dementia subtype diagnoses is quite common, especially in NPR. CONCLUSIONS: Although the overall sensitivity is low, the specificity and the positive predictive value are very high. This suggests that hospital and death registers can be used to identify dementia cases in the community, but at the cost of missing a large proportion of the cases.
Keywords: Aged; Aged, 80 and over; Cause of Death; Dementia; Female; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Registries; Sensitivity and Specificity; Sweden; Twin Studies as Topic

Development of a High-Sensitivity Method for the Measurement of Human Nasal Aβ42, Tau, and Phosphorylated Tau. - Liu, Ziyi; Kameshima, Naoko; Nanjo, Toshifumi; Shiino, Akihiko; Kato, Tomoko; Shimizu, Shino; Shimizu, Takeshi; Tanaka, Sachiko; Miura, Katsuyuki; Tooyama, Ikuo (J Alzheimers Dis, 2018)
Cost-effective and feasible methods for early diagnosis of Alzheimer's disease (AD) are needed. We present two methods to measure AD-related biomarkers simultaneously from one nasal smear for the purpose of diagnosing AD. Japanese men and women aged 63-85 years old were recruited in 2015-2016 for this case-control study. A total of 25 AD cases and 25 controls (22 men and 28 women) participated in this research. Nasal smears were collected from the common nasal meatus, inferior concha, middle nasal meatus, and olfactory cleft, and the proteins in the samples were analyzed by two methods, which we named PGD (Pre-treatment with guanidine- n-Dodecyl-beta-D-maltoside solution) method 1 (PGD-I) and 2 (PGD-II). The PGD-I method measured total tau and amyloid-β (Aβ)42, but no differences in median levels of total tau and Aβ42 between AD cases and controls were found in any of the nasal locations. The PGD-II method measured Aβ42, total tau, and phosphorylated tau, but levels of Aβ40 in all nasal locations of both groups were near zero. Median levels of phosphorylated tau to total tau (p-tau/t-tau) ratios in the middle nasal meatus and in the olfactory cleft were significantly higher in AD cases than in controls, and could significantly predict AD. To assess diagnostic reliability, areas under the ROC curve were 0.74 (95% CL = 0.52-0.95, p = 0.030) for the middle nasal meatus and 0.72 (95% CL = 0.52-0.92, p = 0.029) for the olfactory cleft. Thus, PGD-I and PGD-II can detect AD-related biomarkers in nasal smears and PGD-II may be a useful tool for diagnosing AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Female; Humans; Male; Middle Aged; Nasal Mucosa; Peptide Fragments; Phosphorylation; Reproducibility of Results; ROC Curve; tau Proteins

The Diagnostic and Prognostic Value of a Dual-Tasking Paradigm in a Memory Clinic. - Nielsen, Malene Schjnning; Simonsen, Anja Hviid; Siersma, Volkert; Hasselbalch, Steen Gregers; Hoegh, Peter (J Alzheimers Dis, 2018)
BACKGROUND: Daily living requires the ability to perform dual-tasking. As cognitive skills decrease in dementia, performing a cognitive and motor task simultaneously become increasingly challenging and subtle gait abnormalities may even be present in pre-dementia stages. Therefore, a dual-tasking paradigm, such as the Timed Up and Go-Dual Task (TUG-DT), may be useful in the diagnostic assessment of mild cognitive impairment (MCI). OBJECTIVE: To investigate the diagnostic and prognostic ability of a dual-tasking paradigm in patients with MCI or mild Alzheimer's disease (AD) and to evaluate the association between the dual-tasking paradigm and cerebrospinal fluid (CSF) AD biomarkers. METHODS: The study is a prospective cohort study conducted in a clinical setting in two memory clinics. Eighty-six patients were included (28 MCI, 17 AD, 41 healthy controls (HC)). The ability to perform dual-tasking was evaluated by the TUG-DT. Patients underwent a standardized diagnostic assessment and were evaluated to determine progression yearly. RESULTS: ROC curve analysis illustrated a high discriminative ability of the dual-tasking paradigm in separating MCI patients from HC (AUC: 0.78, AUC: 0.82) and a moderate discriminative ability in separating MCI from AD (AUC: 0.73, AUC: 0.55). Performance discriminated clearly between all groups (p < 0.01). Logistic regression analyses revealed a low prognostic value of the dual-tasking paradigm for progression and rate of cognitive decline. A moderately strong correlation between the dual-tasking paradigm and CSF AD biomarkers was observed. CONCLUSION: In our study, we found that patients with MCI and mild AD have increasing difficulties in dual-tasking compared to healthy elderly. Hence, the dual-tasking paradigm may be a potential complement in the diagnostic assessment in a typical clinical setting.
Keywords: Aged; Alzheimer Disease; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Male; Memory; Middle Aged; Neuropsychological Tests; Prognosis; Prospective Studies; ROC Curve

Differential Pattern of Phospholipid Profile in the Temporal Cortex from E280A-Familiar and Sporadic Alzheimer's Disease Brains. - Villamil-Ortiz, Javier Gustavo; Barrera-Ocampo, Alvaro; Arias-Londoño, Julián David; Villegas, Andrés; Lopera, Francisco; Cardona-Gómez, Gloria Patricia (J Alzheimers Dis, 2018)
Lipids are considered important factors in the pathogenesis of Alzheimer's disease (AD). In this study, we realized a comparative analysis of the phospholipid profile and phospholipid composition of the temporal cortex from E280A-familiar AD (FAD), sporadic AD (SAD), and healthy human brains. Findings showed a significant decrease of lysophosphatidylcholine and phosphatidylethanolamine formed by low levels of polyunsaturated fatty acids (20 : 4, 22 : 6) in AD brains. However, phosphatidylethanolamine-ceramide and phosphoglycerol were significantly increased in SAD, conformed by high levels of (18 : 0/18 : 1) and (30/32/36 : 0/1/2), respectively. Together, the findings suggest a deficiency in lysophosphacholine and phosphatidylethanolamine, and alteration in the balance between poly- and unsaturated fatty acids in both types of AD, and a differential pattern of phospholipid profile and fatty acid composition between E280A FAD and SAD human brains.
Keywords: Adult; Aged; Aged, 80 and over; Alanine; Alzheimer Disease; Analysis of Variance; Fatty Acids; Female; Gene Expression Regulation; Glutamic Acid; Humans; Lysophosphatidylcholines; Male; Mass Spectrometry; Middle Aged; Mutation; Phosphatidylethanolamines; Phospholipids; Presenilin-1; Temporal Lobe

Dilated Perivascular Spaces in the Centrum Semiovale Begin to Develop in Middle Age. - Ishikawa, Masatsune; Yamada, Shigeki; Yamamoto, Kazuo (J Alzheimers Dis, 2018)
BACKGROUND: Dilated perivascular spaces in the centrum semiovale (CSO-PVS) are closely related to small vessel disease. However, recent studies have revealed that cerebral amyloid angiopathy can cause dilation of the CSO-PVS and obstruction of interstitial fluid flow along the intramural periarterial drainage. OBJECTIVE: To examine the severity and age-related prevalence of CSO-PVS through magnetic resonance imaging (MRI) and investigate their clinically relevant factors. METHODS: This study included 1,060 subjects who participated in our brain program. The subjects ranged from 23 to 83 years in age and were active in society. The frequencies of the MRI abnormalities of small vessel diseases, including CSO-PVS, were examined. The CSO-PVS severity was classified into three grades: G0, G1, G2, according to the visual rating. The subjects were divided into five age groups and their age-related frequencies were also studied. Using the clinico-laboratory data of 712 subjects, the clinically relevant factors of CSO-PVS were investigated using logistic regression analysis. RESULTS: The frequencies of all G0 ("normal") MRI abnormalities significantly decreased with age. A high prevalence of G2 CSO-PVS was observed (24%) in the youngest group aged≤39 years, whereas other MRI abnormalities in this group were not or rarely observed. In multivariable logistic regression analyses, G2 CSO-PVS was found to be closely associated with age, hypertension, and the estimated glomerular filtration ratio. CONCLUSIONS: This study reveals that CSO-PVS begin to develop in subjects aged less than 39 years. Age-related changes are involved. Further studies are necessary to elucidate the pathophysiological role of the CSO-PVS.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cerebral Amyloid Angiopathy; Corpus Callosum; Cross-Sectional Studies; Female; Humans; Japan; Logistic Models; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Prospective Studies; Young Adult

Does Fatty Acid Composition in Subcutaneous Adipose Tissue Differ between Patients with Alzheimer's Disease and Cohabiting Proxies? - Faxen-Irving, Gerd; Falahati, Farshad; Basun, Hans; Eriksdotter, Maria; Vedin, Inger; Wahlund, Lars-Olof; Schultzberg, Marianne; Hjorth, Erik; Palmblad, Jan; Cederholm, Tommy; Freund-Levi, Yvonne (J Alzheimers Dis, 2018)
Low tissue levels of the major marine ω3 fatty acids (FAs) DHA and EPA are found in Alzheimer's disease (AD). We investigated if healthy proxies to AD patients have higher levels of these ω3 FAs. We observed lower levels of EPA and DHA in subcutaneous adipose tissue biopsies from 64 AD patients compared with 16 cognitively healthy proxies. No significant difference was observed when pairwise comparisons were made between a subset of 16 AD patients and their co-habiting proxies. Larger studies are needed to replicate these findings and to determine if they could depend on FA intake or differences in metabolism.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Dietary Supplements; Fatty Acids, Omega-3; Female; Humans; Male; Regression Analysis; Subcutaneous Fat

Drugs for Dementia and Excess of Hospitalization: A Longitudinal French Study. - François, Mathilde; Sicsic, Jonathan; Pelletier Fleury, Nathalie (J Alzheimers Dis, 2018)
BACKGROUND: The impact of adverse effects of drugs for dementia on the risk of hospitalization has not been much studied despite the impact of hospitalizations on cognitive decline. OBJECTIVE: To determine if the main adverse effects of cholinesterase inhibitors and memantine may be associated with excess of hospitalization and to quantify the subsequent impact on healthcare expenditures. METHODS: A representative sample of the French national health insurance beneficiaries aged 65 and older and suffering from dementia were included and followed from 2007 to 2014. Binary logit models for longitudinal data (GEE estimation technique) were used to estimate the excess of hospitalization events related to the adverse effects of anti-dementia drugs and then to derive the additional costs of hospitalizations for the public health insurance fund. RESULTS: In total, 7,668 patients were followed, generating 111,133 individual observations over the 8-year period. Treated patients were hospitalized significantly more than non-treated patients (adjusted Odd Ratio (OR) = 1.08, 95% confidence interval (95% CI) = [1.02 to 1.13], p = 0.004), mainly with cholinesterase inhibitors for cardiac (OR = 1.21, 95% CI = [1.01 to 1.46], p = 0.034) and gastrointestinal events (OR = 1.43, 95% CI = [1.01-2.05], p = 0.045), especially with rivastigmine. When extrapolated to the entire population, this corresponded to an annual additional cost of € 55,000. CONCLUSION: Prescription of antidementia drugs, more specifically rivastigmine, increases the risk of hospitalizations via their cardiac and gastrointestinal adverse effects and lead to additional health care expenditures. Even though these results must be confirmed, they may encourage cautious consideration of the balance between benefits and harms before a prescription is given.
Keywords: Aged; Aged, 80 and over; Cholinesterase Inhibitors; Dementia; Female; France; Health Expenditures; Hospitalization; Humans; Longitudinal Studies; Male; Rivastigmine

Dysregulation and Dislocation of SFPQ Disturbed DNA Organization in Alzheimer's Disease and Frontotemporal Dementia. - Lu, Jing; Shu, Runzhe; Zhu, Yan (J Alzheimers Dis, 2018)
SFPQ (Splicing factor proline- and glutamine-rich) is a DNA and RNA binding protein involved in transcription, pre-mRNA splicing, and DNA damage repair. SFPQ was found dysregulated in a few tauopathies such as Alzheimer's disease (AD) and frontotemporal dementia (FTD). In addition, knock-down of SFPQ induced FTD-like behavior in mouse. To confirm the role of SFPQ in AD and FTD, we analyzed the brain sections from the AD and FTD brain samples with SFPQ upregulation and dislocation. Specifically, we observed SFPQ dislocated to the cytoplasm and nuclear envelopes, and DNA structures and organizations were associated with these dislocation phenotypes in AD and FTD brains. Consistently, we also found decreased DAPI intensities and smaller chromocenters associated with SFPQ dislocation in nerural-2a (N2a) cells. As the upregulation and hyperphosphorylation of tau protein is a hallmark of AD and FTD, our study sought to investigate potential interactions between tau and SFPQ by co-transfection and co-immunoprecipitation assays in N2a cells. SFPQ dislocation was found enhanced with tau co-transfection and tau co-transfection further resulted in extended DNA disorganization in N2a cells. Overall, our results indicate that dysregulation and dislocation of SFPQ and subsequent DNA disorganization might be a novel pathway in the progression of AD and FTD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Animals; Brain; Cell Line, Tumor; DNA Damage; Female; Frontotemporal Dementia; Gene Expression Regulation; Humans; Male; Mice; PTB-Associated Splicing Factor; tau Proteins; Translocation, Genetic

Early Stage Alterations in CA1 Extracellular Region Proteins Indicate Dysregulation of IL6 and Iron Homeostasis in the 5XFAD Alzheimer's Disease Mouse Model. - Gurel, Busra; Cansev, Mehmet; Sevinc, Cansu; Kelestemur, Seda; Ocalan, Busra; Cakir, Aysen; Aydin, Sami; Kahveci, Nevzat; Ozansoy, Mehmet; Taskapilioglu, Ozlem; Ulus, Ismail Hakki; Başar, Merve Karayel; et al. (J Alzheimers Dis, 2018)
In recent years, an increasing number of research papers revealed that the compositional and volumetric alterations in the extracellular matrix are the consequences of aging and may be related to Alzheimer's disease (AD). In this study, we aimed to demonstrate the alterations in hippocampal extracellular fluid proteins in vivo using the 5XFAD mouse model. Samples were obtained from hippocampi of 5XFAD mice (n = 6) and their non-transgenic littermates by intracerebral push-pull perfusion technique at 3 months of age, representing the pre-pathological stage of the AD. Proteins in the hippocampal perfusates were analyzed by Ultra Performance Liquid Chromatography-Electrospray Ionization Quadrupole Time-of-Flight Mass Spectrometry (UPLC-ESI-qTOF-MS/MS). 178 proteins were identified and 19 proteins of them were found to be statistically significantly altered (p≤0.05, fold change ≥40%, unique peptide count ≥3) in the hippocampal CA1 extracellular fluid of the 5XFAD mouse model. Ingenuity pathway analysis of the protein expression results identified IL6 as an upstream regulator. The upregulation of IL6 was validated by immunohistochemical staining of the hippocampus and cortex of the 5XFAD mice prior to Aβ plaque formation. Furthermore, the iron level in the hippocampus was measured by inductively coupled plasma-mass spectrometry as IL6 is mentioned in several studies to take part in iron homeostasis and inflammation and found to be increased in 5XFAD mice hippocampus. Alterations in extracellular matrix proteins in addition to increasing amount of hippocampal IL6 and iron in the early stages of AD may reveal inflammation-mediated iron dyshomeostasis in the early stages of neurodegeneration.
Keywords: Alzheimer Disease; Animals; CA1 Region, Hippocampal; Chromatography, Liquid; Disease Models, Animal; Female; Homeostasis; Interleukin-6; Iron; Mice; Mice, Transgenic; Proteomics; Tandem Mass Spectrometry

Economic Burden, Mortality, and Institutionalization in Patients Newly Diagnosed with Alzheimer's Disease. - Black, Christopher M; Fillit, Howard; Xie, Lin; Hu, Xiaohan; Kariburyo, M Furaha; Ambegaonkar, Baishali M; Baser, Onur; Yuce, Huseyin; Khandker, Rezaul K (J Alzheimers Dis, 2018)
BACKGROUND: Current information is scarce regarding comorbid conditions, treatment, survival, institutionalization, and health care utilization for Alzheimer's disease (AD) patients. OBJECTIVES: Compare all-cause mortality, rate of institutionalization, and economic burden between treated and untreated newly-diagnosed AD patients. METHODS: Patients aged 65-100 years with ≥1 primary or ≥2 secondary AD diagnoses (ICD-9-CM:331.0] with continuous medical and pharmacy benefits for ≥12 months pre-index and ≥6 months post-index date (first AD diagnosis date) were identified from Medicare fee-for-service claims 01JAN2011-30JUN2014. Patients with AD treatment claims or AD/AD-related dementia diagnosis during the pre-index period were excluded. Patients were assigned to treated and untreated cohorts based on AD treatment received post-index date. Total 8,995 newly-diagnosed AD patients were identified; 4,037 (44.8%) were assigned to the treated cohort. Time-to-death and institutionalization were assessed using Cox regression. To compare health care costs and utilizations, 1 : 1 propensity score matching (PSM) was used. RESULTS: Untreated patients were older (83.85 versus 81.44 years; p < 0.0001), with more severe comorbidities (mean Charlson comorbidity index: 3.54 versus 3.22; p < 0.0001). After covariate adjustment, treated patients were less likely to die (hazard ratio[HR] = 0.69; p < 0.0001) and were associated with 20% lower risk of institutionalization (HR = 0.801; p = 0.0003). After PSM, treated AD patients were less likely to have hospice visits (3.25% versus 9.45%; p < 0.0001), and incurred lower annual all-cause costs ($25,828 versus $30,110; p = 0.0162). CONCLUSION: After controlling for comorbidities, treated AD patients have better survival, lower institutionalization, and sometimes fewer resource utilizations, suggesting that treatment and improved care management could be beneficial for newly-diagnosed AD patients from economic and clinical perspectives.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Comorbidity; Cost of Illness; Female; Humans; Institutionalization; Male; Neuropsychological Tests

The Effects and Meanings of Receiving a Diagnosis of Mild Cognitive Impairment or Alzheimer's Disease When One Lives Alone. - Portacolone, Elena; Johnson, Julene K; Covinsky, Kenneth E; Halpern, Jodi; Rubinstein, Robert L (J Alzheimers Dis, 2018)
BACKGROUND: One third of older adults with cognitive impairment live alone and are at high risk for poor health outcomes. Little is known about how older adults who live alone experience the process of receiving a diagnosis of mild cognitive impairment (MCI) or Alzheimer's disease (AD). OBJECTIVE: The aim of this study was to understand the effects and meanings of receiving a diagnosis of MCI or AD on the lived experience of older adults living alone. METHODS: This is a qualitative study of adults age 65 and over living alone with cognitive impairment. Participants' lived experiences were elicited through ethnographic interviews and participant observation in their homes. Using a qualitative content analysis approach, interview transcripts and fieldnotes were analyzed to identify codes and themes. RESULTS: Twenty-nine older adults and 6 members of their social circles completed 114 ethnographic interviews. Core themes included: relief, distress, ambiguous recollections, and not knowing what to do. Participants sometimes felt uplifted and relieved by the diagnostic process. Some participants did not mention having received a diagnosis or had only partial recollections about it. Participants reported that, as time passed, they did not know what to do with regard to the treatment of their condition. Sometimes they also did not know how to prepare for a likely worsening of their condition, which they would experience while living alone. CONCLUSION: Findings suggest the need for more tailored care and follow-up as soon as MCI or AD is diagnosed in persons living alone.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Emotions; Female; Health Services; Humans; Interviews as Topic; Male; Residence Characteristics; Single Person

Endogenous Murine Amyloid-β Peptide Assembles into Aggregates in the Aged C57BL/6J Mouse Suggesting These Animals as a Model to Study Pathogenesis of Amyloid-β Plaque Formation. - Ahlemeyer, Barbara; Halupczok, Sascha; Rodenberg-Frank, Elke; Valerius, Klaus-Peter; Baumgart-Vogt, Eveline (J Alzheimers Dis, 2018)
Amyloid-β peptide (Aβ), paired helical filament-tau (PHF-tau), and α-synuclein are in the focus of neuroscience research because they aggregate in brains of patients with Alzheimer's and Parkinson's diseases. For this purpose, transgenic mouse models were used containing the human genes for AβPP/presenilin/tau or α-synuclein with the most frequent mutations. This is not ideal because most patients develop sporadic forms of the diseases with no causative single gene defect and furthermore the aggregation of human proteins in man is not necessarily the same in rodents. We hypothesized that for such cases the aged mouse could be an alternative model and analyzed the distribution of endogenous Aβ, PHF-tau, and α-synuclein in mouse brains at different ages. Whereas Aβ was below detectable levels at birth, it was present at high levels in the 15-month-old mouse. Aβ was found in the cytosol and lysosomes of neurons of the temporal cortex, cingulate area, pons, and cerebellum as well as extracellularly in the periventricular zone. Contrary to Aβ, mouse brain was devoid of PHF-tau-positive neurofibrillary tangles. α-Synuclein was detectable in the newborn mouse with highest levels in the marginal zone of the lateral cortex and average levels in the hippocampus, pons, and cerebellum. Brain-area specific differences in the α-synuclein level persisted up to 15 months of age, but increased 3-fold in all areas over time. α-Synuclein resided in the neuropil, but not in intracellular aggregates even in the aged mouse. We suggest the aged mouse as a model to study Aβ plaque formation.
Keywords: Age Factors; Aged; Aged, 80 and over; alpha-Synuclein; Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Female; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Neurofibrillary Tangles; Neurons; Plaque, Amyloid; tau Proteins

Erythromyeloid-Derived TREM2: A Major Determinant of Alzheimer's Disease Pathology in Down Syndrome. - Raha-Chowdhury, Ruma; Henderson, James W; Raha, Animesh Alexander; Stott, Simon R W; Vuono, Romina; Foscarin, Simona; Wilson, Liam; Annus, Tiina; Fincham, Robert; Allinson, Kieren; Devalia, Vinod; Friedland, Robert P; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Down syndrome (DS; trisomy 21) individuals have a spectrum of hematopoietic and neuronal dysfunctions and by the time they reach the age of 40 years, almost all develop Alzheimer's disease (AD) neuropathology which includes senile plaques and neurofibrillary tangles. Inflammation and innate immunity are key players in AD and DS. Triggering receptor expressed in myeloid cells-2 (TREM2) variants have been identified as risk factors for AD and other neurodegenerative diseases. OBJECTIVE: To investigate the effects of TREM2 and the AD-associated R47H mutation on brain pathology and hematopoietic state in AD and DS. METHODS: We analyzed peripheral blood, bone marrow, and brain tissue from DS, AD, and age-matched control subjects by immunohistochemistry and western blotting. TREM2-related phagocytosis was investigated using a human myeloid cell line. RESULTS: TREM2 protein levels in brain and sera declined with age and disease progression in DS. We observed soluble TREM2 in brain parenchyma that may be carried by a subset of microglia, macrophages, or exosomes. Two DS cases had the AD-associated TREM2-R47H mutation, which manifested a morphologically extreme phenotype of megakaryocytes and erythrocytes in addition to impaired trafficking of TREM2 to the erythroid membrane. TREM2 was shown to be involved in phagocytosis of red blood cells. TREM2 was seen in early and late endosomes. Silencing TREM2 using siRNA in THP1 cells resulted in significant cell death. CONCLUSION: We provide evidence that peripheral TREM2 originating from erythromyeloid cells significantly determines AD neuropathology in DS subjects. Understanding the molecular signaling pathways mediated by TREM2 may reveal novel therapeutic targets.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cell Line; Disease Progression; Down Syndrome; Exosomes; Female; Humans; Immunity, Innate; Macrophages; Male; Membrane Glycoproteins; Microglia; Middle Aged; Phagocytosis; Polymorphism, Single Nucleotide; Receptors, Immunologic

Establishing a New Screening System for Mild Cognitive Impairment and Alzheimer's Disease with Mental Rotation Tasks that Evaluate Visuospatial Function. - Suzuki, Ayuko; Shinozaki, Jun; Yazawa, Shogo; Ueki, Yoshino; Matsukawa, Noriyuki; Shimohama, Shun; Nagamine, Takashi (J Alzheimers Dis, 2018)
BACKGROUND: The mental rotation task is well-known for the assessment of visuospatial function; however, it has not been used for screening of dementia patients. OBJECTIVE: The aim of this study was to create a simple screening test for patients with mild cognitive impairment (MCI) and Alzheimer's disease (AD) by focusing on non-amnestic symptoms. METHODS: Age-matched healthy controls (age 75.3±6.8), patients with MCI (76.5±5.5), and AD (78.2±5.0) participated in this study. They carried out mental rotation tasks targeting geometric graphics or alphabetical characters with three rotating angles (0°, 90°, and 180°) and indicated the correct answer. Response accuracy and reaction time were recorded along with their eye movements using an eye tracker. To quantify their visual processing strategy, the run count ratio (RC ratio) was calculated by dividing the mean number of fixations in incorrect answers by that in correct answers. RESULTS: AD patients showed lower accuracy and longer reaction time than controls. They also showed a significantly greater number of fixation and smaller saccade amplitude than controls, while fixation duration did not differ significantly. The RC ratio was higher for AD, followed by MCI and control groups. By setting the cut-off value to 0.47 in the 180° rotating angle task, we could differentiate MCI patients from controls with a probability of 80.0%. CONCLUSIONS: We established a new screening system for dementia patients by evaluating visuospatial function. The RC ratio during a mental rotation task is useful for discriminating MCI patients from controls.
Keywords: Aged; Aged, 80 and over; Agnosia; Alzheimer Disease; Case-Control Studies; Cognition; Cognitive Dysfunction; Disease Progression; Early Diagnosis; Eye Movements; Female; Humans; Male; Mental Status Schedule; Reaction Time; ROC Curve

Examining the Relationship between Trace Lithium in Drinking Water and the Rising Rates of Age-Adjusted Alzheimer's Disease Mortality in Texas. - Fajardo, Val Andrew; Fajardo, Val Andrei; LeBlanc, Paul J; MacPherson, Rebecca E K (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) mortality rates have steadily increased over time. Lithium, the current gold standard treatment for bipolar disorder, can exert neuroprotective effects against AD. OBJECTIVE: We examined the relationship between trace levels of lithium in drinking water and changes in AD mortality across several Texas counties. METHODS: 6,180 water samples from public wells since 2007 were obtained and averaged for 234 of 254 Texas counties. Changes in AD mortality rates were calculated by subtracting aggregated age-adjusted mortality rates obtained between 2000-2006 from those obtained between 2009-2015. Using aggregated rates maximized the number of counties with reliable mortality data. Correlational analyses between average lithium concentrations and changes in AD mortality were performed while also adjusting for gender, race, education, rural living, air pollution, physical inactivity, obesity, and type 2 diabetes. RESULTS: Age-adjusted AD mortality rate was significantly increased over time (+27%, p < 0.001). Changes in AD mortality were negatively correlated with trace lithium levels (p = 0.01, r = -0.20), and statistical significance was maintained after controlling for most risk factors except for physical inactivity, obesity, and type 2 diabetes. Furthermore, the prevalence of obesity and type 2 diabetes positively correlated with changes in AD mortality (p = 0.01 and 0.03, respectively), but also negatively correlated with trace lithium in drinking water (p = 0.05 and <0.0001, respectively). CONCLUSION: Trace lithium in water is negatively linked with changes in AD mortality, as well as obesity and type 2 diabetes, which are important risk factors for AD.
Keywords: Adult; Age Factors; Alzheimer Disease; Drinking Water; Female; Humans; Lithium; Longitudinal Studies; Male; Obesity; Prevalence; Risk Factors; Statistics as Topic; Texas; Young Adult

Executive and Language Subjective Cognitive Decline Complaints Discriminate Preclinical Alzheimer's Disease from Normal Aging. - Valech, Natalia; Tort-Merino, Adrià; Coll-Padrós, Nina; Olives, Jaume; León, María; Rami, Lorena; Molinuevo, José Luis (J Alzheimers Dis, 2018)
BACKGROUND: There is a need to specify the profile of subjective cognitive decline in preclinical Alzheimer's disease (preAD). OBJECTIVES: To explore specific items of the Subjective Cognitive Decline Questionnaire (SCD-Q) that discriminate preAD from normal aging. METHODS: 68 cognitively normal older adults were classified as controls (n = 52) or preAD (n = 16) according to amyloid-β (Aβ) levels. An exploratory factor analysis and item analysis of the SCD-Q were performed. Informant reports of the SCD-Q were used to corroborate the findings of self-reports. One-year neuropsychological follow-up was available. RESULTS: Four SCD-Q factors were extracted: EM-factor (episodic memory), A-factor (attention), O-factor (organization), and L-factor (language). PreAD reported a significantly higher decline in L-factor (F(1) = 6.49; p = 0.014) and A-factor (F(1) = 4.04; p = 0.049) compared to controls, and showed a higher frequency of perceived decline in SCD-Q items related with language and executive tasks (Sig-items.) Significant discriminative powers for Aβ-positivity were found for L-factor (AUC = 0.75; p = 0.003) and A-factor (AUC = 0.74; p = 0.004). Informants in the preAD group confirmed significantly higher scores in L-factor and Sig-items. A significant time×group interaction was found in the Semantic Fluency and Stroop tests, with the preAD group showing a decrease in performance at one-year. CONCLUSIONS: Our results suggest that SCD-Q items related with language and executive decline may help in prediction algorithms to detect preAD. Validation in an independent population is needed.
Keywords: Aged; Aging; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Executive Function; Factor Analysis, Statistical; Female; Humans; Language; Male; Middle Aged; Neuropsychological Tests; Self Report

Executive Dysfunction Detected with the Frontal Assessment Battery in Alzheimer's Disease Versus Vascular Dementia. - D'Onofrio, Grazia; Panza, Francesco; Sancarlo, Daniele; Addante, Filomena; Solfrizzi, Vincenzo; Cantarini, Chiara; Mangiacotti, Antonio; Lauriola, Michele; Cascavilla, Leandro; Paris, Francesco; Lozupone, Madia; Daniele, Antonio; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) and vascular dementia (VaD) lead to progressive decline in executive function. We estimated the prevalence of executive dysfunction in AD and VaD patients, investigating cognitive, functional, and clinical correlates and also using a multidimensional approach based on a standardized comprehensive geriatric assessment (CGA). We included 215 patients (115 AD patients and 100 VaD patients) consecutively evaluated with a complete cognitive and affective assessment, a CGA, and the Frontal Assessment Battery (FAB) with six subtests investigating conceptualization, mental flexibility, motor programming, sensitivity to interference, inhibitory control, and environmental autonomy. The prevalence of dysexecutive syndrome screened with a FAB score <12 points was high in both AD (97 patients) and VaD (77 patients) (84.3% versus 77.0%, p = 0.171). AD patients were significantly younger, with higher grade of cognitive impairment and less severe comorbidity and polypharmacy than VaD patients. AD patients showed a significantly higher impairment in FAB total score and five FAB subtests (conceptualization, motor programming, sensitivity to interference, inhibitory control, and environmental autonomy) than VaD patients. These findings were largely confirmed in a sub-analysis conducted subdividing the sample in mild and moderate-to-severe demented patients and suggesting that in moderate-to-severe AD there was higher impairment in FAB total score and four FAB subtests (conceptualization, sensitivity to interference, inhibitory control, and environmental autonomy). Executive dysfunction could be greater in AD patients with moderate-to-severe dementia compared to VaD patients, although our groups were also not matched for age, comorbidity or polypharmacy, which could also exert an effect.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Comorbidity; Dementia, Vascular; Executive Function; Female; Frontal Lobe; Geriatric Assessment; Humans; Logistic Models; Male; Polypharmacy; Severity of Illness Index

Exercise Training on Locomotion in Patients with Alzheimer's Disease: A Feasibility Study. - Pedrinolla, Anna; Venturelli, Massimo; Fonte, Cristina; Munari, Daniele; Benetti, Maria Vittoria; Rudi, Doriana; Tamburin, Stefano; Muti, Ettore; Zanolla, Luisa; Smania, Nicola; Schena, Federico (J Alzheimers Dis, 2018)
BACKGROUND: Although current literature has shown that patients with Alzheimer's disease (AD) have worse locomotion compared with healthy counterparts, no studies have focused on the efficacy of exercise training in improving gait abnormalities including biomechanics and metabolic aspects, in this population. OBJECTIVE: To verify the effectiveness of exercise training (ET) on gait parameters (i.e., speed, step and stride length, single and double support, and energy cost of walking (Cw)) in patients with AD with respect to a standard cognitive treatment (CT). METHODS: In this study, we included a small portion of data belonging to a larger study (ClinicalTrials.gov number, NCT03034746). Patients with AD (Mini-Mental State Examination 22±5) were included in the study. Gait parameters and Cw were assessed at baseline and after 6 months (72 treatment sessions) of treatment. ET included 90 min of aerobic and strength training. CT included 90 min of cognitive stimuli. RESULTS: The 16 patients assigned to ET exhibited significant improvement of Cw (-0.9±0.1 J/kg·m-1), while differences in gait parameters were negligible. The effect on gait parameters were undetectable in the 18 patients assigned to CT (-0.2±0.5 J/kg·m-1). CONCLUSIONS: Data from this study showed that ET program seems effective in improving Cw in patients with AD. Interestingly, the positive effect of ET on Cw was not coupled with ameliorations of patient's gait parameters, suggesting that the gain of metabolic aspects of locomotion were the main factors responsible for this positive result.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomechanical Phenomena; Exercise Test; Exercise Therapy; Feasibility Studies; Female; Gait; Humans; Italy; Male; Single-Blind Method

The First Historically Reported Italian Family with FTD/ALS Teaches a Lesson on C9orf72 RE: Clinical Heterogeneity and Oligogenic Inheritance. - Giannoccaro, Maria Pia; Bartoletti-Stella, Anna; Piras, Silvia; Casalena, Alfonsina; Oppi, Federico; Ambrosetto, Giovanni; Montagna, Pasquale; Liguori, Rocco; Parchi, Piero; Capellari, Sabina (J Alzheimers Dis, 2018)
BACKGROUND: In 1969, Dazzi and Finizio reported the second observation of frontotemporal dementia (FTD) - amyotrophic lateral sclerosis (ALS) association in a large Italian kindred affected by an autosomal dominant form of ALS with high penetrance, frequent bulbar onset, and frequent cognitive decline. OBJECTIVE: To expand the original characterization of this family and report the link with the C9orf72 repeat expansion (RE). METHODS: We followed or reviewed the medical records of thirteen patients belonging to the original family and performed genetic analyses in four individuals. RESULTS: Eight patients presented with ALS, four with FTD, and one with schizophrenia. The C9orf72 RE was found in three patients but not in the healthy survivor. Additionally, we found a novel possible pathogenic variant in the ITM2B gene in one patient with a complex phenotype, associating movement disorders, psychiatric and cognitive features, deafness, and optic atrophy. The neuropathological examination of this patient did not show the classical features of ITM2B mutation related dementias suggesting that the putative pathogenic mechanism does not involve cellular mislocalization of the protein or the formation of amyloid plaques. CONCLUSION: We showed that the original Italian pedigree described with FTD/ALS carries the C9orf72 RE. Moreover, the finding of an additional mutation in another dementia causing gene in a patient with a more complex phenotype suggests a possible role of genetic modifiers in the disease. Together with other reports showing the coexistence of mutations in multiple ALS/FTD causative genes in the same family, our study supports an oligogenic etiology of ALS/FTD.
Keywords: Adult; Amyotrophic Lateral Sclerosis; C9orf72 Protein; Cerebral Cortex; DNA Repeat Expansion; Female; Frontotemporal Dementia; Genetic Testing; Humans; Male; Membrane Glycoproteins; Middle Aged; Multifactorial Inheritance; Mutation; Pedigree

Frequency of Cardiovascular Genetic Risk Factors in a Calabrian Population and Their Effects on Dementia. - Maletta, Raffaele; Smirne, Nicoletta; Bernardi, Livia; Anfossi, Maria; Gallo, Maura; Conidi, Maria Elena; Colao, Rosanna; Puccio, Gianfranco; Curcio, Sabrina A M; Laganà, Valentina; Frangipane, Francesca; Cupidi, Chiara; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Several genetic variants playing a key role in cholesterol levels, blood pressure, and vascular dysfunction influence the risk of Alzheimer's disease (AD) and vascular dementia (VaD). The many meta-analysis studies carried out on large numbers of samples in different populations have not provided clear results to date, because a trans-ethnic shift of risk genotypes in different populations is often observed. OBJECTIVES: To determine genotypes allele frequencies of the polymorphisms most frequently identified to be correlated with cardio-cerebrovascular disease and AD in a Southern Italy population and to investigate their possible association with dementia. METHODS: The genotype and allele frequencies of 13 cardio-cerebrovascular risk polymorphisms were assessed and their possible association with dementia was investigated in a case-control study, including 221 consecutive unrelated subjects diagnosed with dementia (120 subjects affected by AD, 55 by frontotemporal dementia, and 33 by vascular dementia) and 218 matched controls of Calabrian origin. RESULTS: Carriers of at least one APOEɛ4 allele resulted to be at higher risk of AD [OR(95% CI) = 2.721(1.477-5.011)] and VaD [OR(95% CI) = 6.205(2.356-16.342)] compared to non-carriers. Individuals with the IV genotype of the CETP polymorphism were more likely to have AD [OR(95% CI) = 2.427(1.364-4.319)] and VaD [OR(95% CI) = 3.649(1.455-9.152)] compared to subjects with the II-VV genotypes. CONCLUSION: CETP I405V polymorphism is likely a risk factor for AD and VaD in our cohort, independent of APOEɛ4 status. Unmodifiable genetic risk factors should be taken into account to promote a healthy lifestyle to prevent dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Case-Control Studies; Cholesterol Ester Transfer Proteins; Cohort Studies; Dementia, Vascular; Female; Frontotemporal Dementia; Gene Frequency; Humans; Italy; Male; Middle Aged; Polymorphism, Genetic; Risk Factors

General Practice Clinical Data Help Identify Dementia Hotspots: A Novel Geospatial Analysis Approach. - Bagheri, Nasser; Wangdi, Kinley; Cherbuin, Nicolas; Anstey, Kaarin J (J Alzheimers Dis, 2018)
We have a poor understanding of whether dementia clusters geographically, how this occurs, and how dementia may relate to socio-demographic factors. To shed light on these important questions, this study aimed to compute a dementia risk score for individuals to assess spatial variation of dementia risk, identify significant clusters (hotspots), and explore their association with socioeconomic status. We used clinical records from 16 general practices (468 Statistical Area level 1 s, N = 14,746) from the city of west Adelaide, Australia for the duration of 1 January 2012 to 31 December 2014. Dementia risk was estimated using The Australian National University-Alzheimer's Disease Risk Index. Hotspot analyses were applied to examine potential clusters in dementia risk at small area level. Significant hotspots were observed in eastern and southern areas while coldspots were observed in the western area within the study perimeter. Additionally, significant hotspots were observed in low socio-economic communities. We found dementia risk scores increased with age, sex (female), high cholesterol, no physical activity, living alone (widow, divorced, separated, or never married), and co-morbidities such as diabetes and depression. Similarly, smoking was associated with a lower dementia risk score. The identification of dementia risk clusters may provide insight into possible geographical variations in risk factors for dementia and quantify these risks at the community level. As such, this research may enable policy makers to tailor early prevention strategies to the correct individuals within their precise locations.
Keywords: Age Factors; Aged; Aged, 80 and over; Australia; Dementia; Demography; Epidemiological Monitoring; Female; General Practice; Humans; Male; Retrospective Studies; Sex Factors; Topography, Medical

Geographical Distribution and Diversity of Gut Microbial NADH:Ubiquinone Oxidoreductase Sequence Associated with Alzheimer's Disease. - Paley, Elena L; Merkulova-Rainon, Tatiana; Faynboym, Aleksandr; Shestopalov, Valery I; Aksenoff, Igor (J Alzheimers Dis, 2018)
Earlier we reported induction of neurotoxicity and neurodegeneration by tryptophan metabolites that link the metabolic alterations to Alzheimer's disease (AD). Tryptophan is a product of Shikimate pathway (SP). Human cells lack SP, which is found in human gut bacteria exclusively using SP to produce aromatic amino acids (AAA). This study is a first attempt toward gene-targeted analysis of human gut microbiota in AD fecal samples. The oligonucleotide primers newly-designed for this work target SP-AAA in environmental bacteria associated with human activity. Using polymerase chain reaction (PCR), we found unique gut bacterial sequence in most AD patients (18 of 20), albeit rarely in controls (1 of 13). Cloning and sequencing AD-associated PCR products (ADPP) enables identification of Na(+)-transporting NADH: Ubiquinone reductase (NQR) in Clostridium sp. The ADPP of unrelated AD patients possess near identical sequences. NQR substrate, ubiquinone is a SP product and human neuroprotectant. A deficit in ubiquinone has been determined in a number of neuromuscular and neurodegenerative disorders. Antibacterial therapy prompted an ADPP reduction in an ADPP-positive control person who was later diagnosed with AD-dementia. We explored the gut microbiome databases and uncovered a sequence similarity (up to 97%) between ADPP and some healthy individuals from different geographical locations. Importantly, our main finding of the significant difference in the gut microbial genotypes between the AD and control human populations is a breakthrough.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Anti-Bacterial Agents; Biological Transport; DNA Primers; Electron Transport Complex I; Feces; Female; Gastrointestinal Microbiome; Geography; Host-Pathogen Interactions; Humans; Male; Middle Aged; Sequence Analysis, DNA; Young Adult

Healthy versus Entorhinal Cortical Atrophy Identification in Asymptomatic APOE4 Carriers at Risk for Alzheimer's Disease. - Konishi, Kyoko; Joober, Ridha; Poirier, Judes; MacDonald, Kathleen; Chakravarty, Mallar; Patel, Raihaan; Breitner, John; Bohbot, Véronique D (J Alzheimers Dis, 2018)
Early detection of Alzheimer's disease (AD) has been challenging as current biomarkers are invasive and costly. Strong predictors of future AD diagnosis include lower volume of the hippocampus and entorhinal cortex, as well as the ɛ4 allele of the Apolipoprotein E gene (APOE) gene. Therefore, studying functions that are critically mediated by the hippocampus and entorhinal cortex, such as spatial memory, in APOE ɛ4 allele carriers, may be key to the identification of individuals at risk of AD, prior to the manifestation of cognitive impairments. Using a virtual navigation task developed in-house, specifically designed to assess spatial versus non-spatial strategies, the current study is the first to differentiate functional and structural differences within APOE ɛ4 allele carriers. APOE ɛ4 allele carriers that predominantly use non-spatial strategies have decreased fMRI activity in the hippocampus and increased atrophy in the hippocampus, entorhinal cortex, and fimbria compared to APOE ɛ4 allele carriers who use spatial strategies. In contrast, APOE ɛ4 allele carriers who use spatial strategies have grey matter levels comparable to non-APOE ɛ4 allele carriers. Furthermore, in a leave-one-out analysis, grey matter in the entorhinal cortex could predict navigational strategy with 92% accuracy.
Keywords: Aged; Alleles; Alzheimer Disease; Apolipoprotein E4; Atrophy; Case-Control Studies; Entorhinal Cortex; Female; Heterozygote; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Risk Factors; Spatial Memory

Hedonic Assessment of Odors: A Comparison of Two Sensory Scales for Use with Alzheimer's Disease Patients and Elderly Individuals. - Atanasova, Boriana; Mondon, Karl; Dreyfuss, Lise; Beaufils, Emilie; Desmidt, Thomas; Hommet, Caroline; El-Hage, Wissam; Belzung, Catherine (J Alzheimers Dis, 2018)
BACKGROUND: Several clinical studies concerning the olfactory function of patients with cognitive impairment have used sensory scales to investigate hedonic perception. However, no study has focused on the choice of the most appropriate sensory hedonic scale for the individuals with neurodegenerative disorders or other psychiatric diseases involving cognitive deficits. OBJECTIVE: The aim of this study was to investigate the ability of patients with Alzheimer's disease (AD) to use two hedonic scales (category scale and linear scale) and compare their discriminatory capacity, repeatability, and ease of use. This should allow us to identify the most appropriate hedonic scale for patients with AD. METHODS: We recruited 18 patients with mild to moderate AD, and 20 healthy volunteers matched for gender, age, smoking status, and educational level. The participants underwent a clinical assessment and hedonic evaluation of three odorants (pleasant, unpleasant, and neutral), using a five-point category scale and a 10-cm linear scale with a marked mid-point. RESULTS: AD patients were able to use hedonic scales as well as paired healthy elderly subjects. The linear scale performed slightly better in terms of ease of use for both patients and healthy controls and discriminatory capacity for AD patients. The results for AD patients and controls with both scales were repeatable. CONCLUSION: The linear scale may be more appropriate for AD patients pending further studies involving a larger population of patients, using several odorants.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognitive Dysfunction; Female; Humans; Linear Models; Male; Olfaction Disorders; Olfactory Perception; Severity of Illness Index; Smell

The Heritability of Frontotemporal Lobar Degeneration: Validation of Pedigree Classification Criteria in a Northern Italy Cohort. - Fostinelli, Silvia; Ciani, Miriam; Zanardini, Roberta; Zanetti, Orazio; Binetti, Giuliano; Ghidoni, Roberta; Benussi, Luisa (J Alzheimers Dis, 2018)
A large portion of frontotemporal lobar degeneration (FTLD) patients has a family history of disease and the presence of a pathogenic mutation confirms the clinical diagnosis. Recently, standardized criteria to evaluate FTLD pedigree, based on first- and second-degree affected relatives, their age at onset, and clinical phenotype, were proposed and validated in an American cohort. Herein we applied these criteria to 402 Italian FTLD pedigrees and assessed mutation frequencies in GRN, C9orf72, and MAPT genes with the aim of validating these criteria. Moreover, we evaluated whether genetic counseling requests reflect the estimated family risk. 12.4% of pedigrees had high family history, 6.5% medium, 15.4% low; 39% were apparent sporadic cases and 26.6% had family history of unknown significance. Mutations frequencies were in line with the categorization proposed: the highest rate was found in the most at-risk families (74%) and decreased in other categories (medium: 15.4%; low: 9.7%; sporadic: 1.3%). Mutation carriers with unknown family history (5.6%) were mostly early-onset patients. Detected mutation frequency was comparable with the US-cohort (13.7%), but mutations distribution among genes was different, with higher frequency of GRN mutations (9.4%) in our cohort. An elevated proportion of FTLD patients belonging to "high risk" pedigrees asked for genetic counseling (42%); requests decreased according to the estimated family risk (medium: 26.9%; low: 17.7%; sporadic: 5.1%). In conclusion, the proposed pedigree classification criteria, herein further validated, should be incorporated in the FTLD diagnostic work-up. Moreover, our data suggest to extend genetic screening to early-onset patients with unknown family history.
Keywords: Age of Onset; Aged; C9orf72 Protein; Cohort Studies; Female; Frontotemporal Lobar Degeneration; Genetic Counseling; Genetic Testing; Humans; Italy; Male; Middle Aged; Mutation; Pedigree; Progranulins; tau Proteins

High Caregiver Burden in Young Onset Dementia: What Factors Need Attention? - Lim, Linda; Zhang, Angeline; Lim, Levinia; Choong, Tanya-Marie; Silva, Eveline; Ng, Adeline; Kandiah, Nagaendran (J Alzheimers Dis, 2018)
BACKGROUND: There is an increase in prevalence of young onset dementia (YOD). The specific problems among YOD patients and levels of caregiver burden (CB) in this group warrants further evaluation. OBJECTIVE: To evaluate and compare level of CB in YOD and late onset dementia (LOD). Also, we sought to understand the specific factors, such as neuropsychiatric symptoms, that may affect the levels of caregiver burden in the YOD group. METHODS: Patient-caregiver dyads with YOD and LOD were recruited from a tertiary neurology center. Levels of CB between YOD and LOD were compared among 183 patient-caregiver dyads. CB was quantified using the Zarit Burden Inventory (ZBI). Neuropsychological evaluations as well as the Neuropsychiatric Inventory were performed. Factors that influenced level of CB in YOD group was investigated with regression analyses. RESULTS: There were 57 YOD and 126 LOD dyads. Caregivers of YOD subjects reported significantly higher levels of burden compared to caregivers of LOD subjects (ZBI: 17.3 versus 13.94; p = 0.015). 52.6% of YOD caregivers reported a high caregiver burden. When compared to caregivers of LOD, the odds of a caregiver of YOD reporting high caregiver burden was 2.34 (95% CI: 1.22-4.49: p = 0.010). YOD dyads with a high caregiver burden had significantly higher neuropsychiatric inventory scores. Risk factors for high caregiver burden in YOD included family history of dementia and behavioral symptoms including disinhibited behavior, delusions, and apathy. CONCLUSION: Targeted support for caregivers of patients with YOD is needed to address the higher CB in this group.
Keywords: Adaptation, Psychological; Age of Onset; Aged; Aged, 80 and over; Behavioral Symptoms; Caregivers; Cost of Illness; Cross-Sectional Studies; Dementia; Female; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Stress, Psychological; Surveys and Questionnaires

Hippocampal Stratum Radiatum, Lacunosum, and Moleculare Sparing in Mild Cognitive Impairment. - Su, Li; Hayes, Lawrence; Soteriades, Soteris; Williams, Guy; Brain, Susannah A E; Firbank, Michael J; Longoni, Giulia; Arnold, Robert J; Rowe, James B; O'Brien, John T (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is associated with atrophy in entorhinal cortex (ERC), the hippocampus, and its subfields Cornu Ammonis 1 (CA1) and subiculum, which predict conversion from mild cognitive impairment (MCI) to clinical AD. The stratum radiatum, lacunosum, and moleculare (SRLM) are also important gateways involving ERC and CA1, which are affected by early AD pathology. OBJECTIVE: To assess whether the SRLM is affected in MCI and AD. METHODS: In this proof-of-concept study, 27 controls, 13 subjects with AD, and 22 with MCI underwent 3T MRI. T1 maps were used for whole-hippocampal volumetry, T2 maps were segmented for hippocampal subfield areas, entorhinal cortex and subiculum thickness, and evaluated for SRLM integrity. RESULTS: Significant CA1 atrophy and subiculum thinning were found in both AD and MCI compared to similarly aged controls. However, SRLM integrity was only significantly reduced in AD but not in MCI compared to controls. There were no significant differences in other hippocampal subfields (CA2, CA3/dentate gyrus) or ERC thickness between the groups. Finally, CA1 and CA3/DG areas and SRLM clarity were correlated with clinical and cognitive measurements of disease severity. CONCLUSION: Although this study was cross sectional, it suggests a progression of specific subfield changes from MCI to established AD that is associated with the reduced integrity of SRLM, which may reflect more widespread hippocampal involvement as the disease progresses and the relative preservation of SRLM in MCI. These results provide new MRI biomarkers for disease staging and understanding of the neurobiology in AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Cognitive Dysfunction; Disease Progression; Entorhinal Cortex; Female; Hippocampus; Humans; Imaging, Three-Dimensional; Magnetic Resonance Imaging; Male; Middle Aged; Reproducibility of Results

Homocysteine and Cerebral Atrophy: The Epidemiology of Dementia in Singapore Study. - Tan, Bryce; Venketasubramanian, Narayanaswamy; Vrooman, Henri; Cheng, Ching-Yu; Wong, Tien Yin; Ikram, Mohammad Kamran; Chen, Christopher; Hilal, Saima (J Alzheimers Dis, 2018)
BACKGROUND: Plasma homocysteine levels are increasingly studied as a potential risk factor for dementia. Elevated homocysteine levels have been linked with gray and white matter volume reduction among individuals with mild cognitive impairment and Alzheimer's disease. However, the effects of homocysteine on brain changes in preclinical stages of dementia remain unexplored. OBJECTIVE: To examine the association of elevated homocysteine levels with markers of neurodegeneration, i.e., white and gray matter volume in an elderly population. METHODS: The study included 768 participants (mean age: 69.6±6.5 years, 51.3% women) from the Epidemiology of Dementia In Singapore study. Participants underwent a brain MRI scan and blood tests. Serum homocysteine was measured using competitive immunoassay. Cortical thickness and subcortical structural volume were quantified using FreeSurfer whereas white matter volume was quantified using a previous validated method. RESULTS: Higher homocysteine levels were significantly associated with decreased global white matter volume [mean difference (β) in volume (ml) per micromole per liter (μmol/l) increase in homocysteine levels: - 0.555, 95% Confidence Interval (CI): - 0.873; - 0.237], decreased parietal cortical thickness [β in thickness (μm) per μmol/l increase in homocysteine levels:- 1.429, 95% CI: - 2.781; - 0.077], and smaller volumes of the thalamus [β: - 0.017, 95% CI: - 0.026; - 0.008], brainstem [β: - 0.037, 95% CI: - 0.058; - 0.016], and accumbens [β: - 0.004, 95% CI: - 0.006; - 0.002]. CONCLUSION: Higher homocysteine levels were associated with cerebral atrophy. Further studies are required to assess whether lowering plasma homocysteine levels may prevent neurodegenerative changes or delay progression of clinical symptoms before the development of dementia.
Keywords: Aged; Atrophy; Biomarkers; Dementia; Female; Homocysteine; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Organ Size; Risk Factors; Singapore; White Matter

Impact of a Virtual Dementia Experience on Medical and Pharmacy Students' Knowledge and Attitudes Toward People with Dementia: A Controlled Study. - Gilmartin-Thomas, Julia F-M; McNeil, John; Powell, Anne; Malone, Daniel T; Wolfe, Rory; Larson, Ian C; O'Reilly, Claire L; Kirkpatrick, Carl M; Kipen, Eva; Petrovich, Tanya; Bell, J Simon (J Alzheimers Dis, 2018)
BACKGROUND: Clinical practice guidelines for dementia highlight the importance of providing patient-centered care. This can be achieved by improving health professionals' attitudes and knowledge toward people with dementia. OBJECTIVE: Quantitatively evaluate the impact of a virtual dementia experience on medical and pharmacy students' knowledge and attitudes toward people with dementia. METHODS: A non-randomized controlled study from September-October 2016. The intervention group received a 1.5-hour multisensory, virtual simulation of light, sound, color, and visual content to experience the cognitive and perceptual difficulties faced by people with dementia. Controls participated in the standard curriculum only. All students were invited to complete the 20-item Dementia Attitudes Scale (DAS) pre- and post-intervention. RESULTS: A total of 278 students (n = 64 medical, n = 214 pharmacy) were analyzed (n = 80 intervention, n = 198 control). The majority of students were female (n = 184, 66.2%), with an average age of 22.5 years. The intervention improved the DAS total score and subdomains of comfort and knowledge (p < 0.001). CONCLUSION: The intervention had a positive impact on medical and pharmacy students' knowledge and attitudes toward people with dementia.
Keywords: Australia; Curriculum; Dementia; Female; Health Knowledge, Attitudes, Practice; Humans; Male; Students, Medical; Students, Pharmacy; Virtual Reality; Young Adult

The Impact of APOE ɛ4 in Alzheimer's Disease Differs According to Age. - Kim, Jaeho; Park, Seongbeom; Yoo, Heejin; Jang, Hyemin; Kim, Yeshin; Kim, Ko Woon; Jang, Young Kyoung; Lee, Jin San; Kim, Sung Tae; Kim, Seonwoo; Lee, Jong Min; Ki, Chang-Seok; et al. (J Alzheimers Dis, 2018)
We evaluated how the impact of apolipoprotein E4 (APOE4) differs according to age in Alzheimer's disease (AD) patients. We recruited 846 AD patients and 815 cognitively normal controls and categorized into three groups with respect to their age (<65, 65-74, and ≥75 years). We evaluated the risk of AD in APOE4 carriers and compared cortical thickness and cognitive function according to APOE4 status in each age group. At the point of this study, in young (<65 years) AD, APOE4 noncarriers had the most severe frontal and perisylvian atrophy, while in old (≥75 years) AD, APOE4 carriers had the most severe medial temporal atrophy. In AD under 75 years, APOE4 noncarriers and heterozygotes showed worse performance in language, visuospatial, and frontal function compared to homozygotes, while, in old (≥75 years) AD, APOE4 homozygotes showed worse performance in memory compared to noncarriers. As the detrimental effects of APOE4 seen in older AD patients were not found in younger AD patients, we suggest that some unrevealed factors are associated with cortical atrophy and non-amnestic cognitive dysfunction in young AD with APOE4 noncarriers.
Keywords: Age Factors; Aged; Alzheimer Disease; Apolipoprotein E4; Atrophy; Brain; Case-Control Studies; Cognition; Female; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Memory; Middle Aged; Republic of Korea

Impaired IL-17 Production in Gut-Residing Immune Cells of 5xFAD Mice with Alzheimer's Disease Pathology. - Saksida, Tamara; Koprivica, Ivan; Vujičić, Milica; Stošić-Grujičić, Stanislava; Perović, Milka; Kanazir, Selma; Stojanović, Ivana (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by accumulation of amyloid-β plaques that further promotes microglia-mediated neuroinflammatory responses and inflammation in the brain. Emerging data are revealing the relation between gut-associated lymphoid tissue (GALT) cells and CNS, as effector cells primed in the gut might home to the brain. This study aimed to determine cell composition of GALT in 5xFAD mice, an established model for AD. Immune cells isolated from Peyer's patches (PP) and mesenteric lymph nodes (MLN) were stained with surface and intracellular markers for T helper (Th) subpopulations, B lymphocytes and macrophages and analyzed cytofluorimetrically, while cytokine expression and production were determined by qPCR and ELISA, respectively. Inflammation was detected in GALT of 5xFAD mice with established AD pathology. Although the production of IFN-γ, IL-4, and IL-10 was comparable between the strains, lower IL-17 production was observed in PP and MLN cells. This phenomenon could not be attributed to a lower abundance of Th17 cells, or cytokines that initiate their formation or propagation (TGF-β, IL-6, and IL-23). Also, reduced IL-17 production was not a consequence of altered Il-17 mRNA transcription or deficiency of Rorγt, a key transcription factor for IL-17. However, the expression of miR-155 (a non-coding micro RNA that promotes the development of Th17 cells), was significantly lower in MLN cells of 5xFAD mice. In contrast, mice without AD neuropathology did not have inflammation in GALT or altered Th17 numbers, nor decreased IL-17 production. In conclusion, the observed changes in GALT of 5xFAD mice mirror the disease progression and might reflect inadequate immune surveillance in the gut and lead to enhanced AD pathology.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; B-Lymphocytes; Disease Models, Animal; Female; Interleukin-17; Lymph Nodes; Male; Mice; Mice, Transgenic; MicroRNAs; Peyer's Patches; Th17 Cells

In vivo Depiction of α7 Nicotinic Receptor Loss for Cognitive Decline in Alzheimer's Disease. - Nakaizumi, Kyoko; Ouchi, Yasuomi; Terada, Tatsuhiro; Yoshikawa, Etsuji; Kakimoto, Akihiro; Isobe, Takashi; Bunai, Tomoyasu; Yokokura, Masamichi; Suzuki, Katsuaki; Magata, Yasuhiro (J Alzheimers Dis, 2018)
BACKGROUND: The α7 subtype of the nicotinic acetylcholine receptor (nAChR) is considered important in higher cognitive functions, and cholinergic loss underpins the pathophysiology of Alzheimer's disease (AD). However, the relationships between α7 nAChR function and clinical functions or amyloid-β (Aβ) deposition remain to be explored in the living AD brain. OBJECTIVE: We aimed to elucidate the relationship between α7 nAChR availability in the specific cholinergic region and cognitive decline in the Aβ-confirmed AD brain. METHODS: Twenty AD patients and ten age-matched healthy subjects were examined. The α7-nAChR availability and Aβ deposition were evaluated using positron emission tomography with an α7 nAChR radiotracer 11C-(R)-MeQAA and 11C-Pittsburg compound B (11C-PiB), respectively. Semi-quantified values of tracer binding were estimated with a simplified reference tissue method for BPND of 11C-(R)-MeQAA and a tissue ratio method for SUVR of 11C-PiB. These parameters and clinical scores were compared voxel-wise using a statistical parametric mapping method. RESULTS: The levels of 11C-(R)-MeQAA BPND in the temporal and prefrontal cholinergic projection regions were significantly lower in AD, and negative correlations were found between 11C-PiB SUVR and 11C-(R)-MeQAA BPND in the region of the nucleus basalis magnocellularis and medial prefrontal cortex. Levels of 11C-(R)-MeQAA BPND were significantly correlated with memory and frontal function scores in AD. CONCLUSION: The association between Aβ burden and α7-nAChR reduction in the basal forebrain cholinergic system was highlighted in relation to cognitive decline in AD. This suggests that Aβ-linked α7-nAChR reduction is clinico-pathophyisologically important for considering a good therapeutic target in AD.
Keywords: Adult; Aged; alpha7 Nicotinic Acetylcholine Receptor; Alzheimer Disease; Brain; Case-Control Studies; Cognitive Dysfunction; Female; Humans; Male; Middle Aged; Positron-Emission Tomography; Young Adult

In Vivo Visualization of Tau Accumulation, Microglial Activation, and Brain Atrophy in a Mouse Model of Tauopathy rTg4510. - Ishikawa, Ai; Tokunaga, Masaki; Maeda, Jun; Minamihisamatsu, Takeharu; Shimojo, Masafumi; Takuwa, Hiroyuki; Ono, Maiko; Ni, Ruiqing; Hirano, Shigeki; Kuwabara, Satoshi; Ji, Bin; Zhang, Ming-Rong; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Tau imaging using PET is a promising tool for the diagnosis and evaluation of tau-related neurodegenerative disorders, but the relationship among PET-detectable tau, neuroinflammation, and neurodegeneration is not yet fully understood. OBJECTIVE: We aimed to elucidate sequential changes in tau accumulation, neuroinflammation, and brain atrophy by PET and MRI in a tauopathy mouse model. METHODS: rTg4510 transgenic (tg) mice expressing P301L mutated tau and non-tg mice were examined with brain MRI and PET imaging (analyzed numbers: tg = 17, non-tg = 13; age 2.5∼14 months). As PET probes, [11C]PBB3 (Pyridinyl-Butadienyl-Benzothiazole 3) and [11C]AC-5216 were used to visualize tau pathology and 18-kDa translocator protein (TSPO) neuroinflammation. Tau pathology and microglia activation were subsequently analyzed by histochemistry. RESULTS: PET studies revealed age-dependent increases in [11C]PBB3 and [11C]AC-5216 signals, which were correlated with age-dependent volume reduction in the forebrain on MRI. However, the increase in [11C]PBB3 signals reached a plateau at age 7 months, and therefore its significant correlation with [11C]AC-5216 disappeared after age 7 months. In contrast, [11C]AC-5216 showed a strong correlation with both age and volume reduction until age 14 months. Histochemical analyses confirmed the relevance of pathological tau accumulation and elevated TSPO immunoreactivity in putative microglia. CONCLUSION: Our results showed that tau accumulation is associated with neuroinflammation and brain atrophy in a tauopathy mouse model. The time-course of the [11C]PBB3- and TSPO-PET finding suggests that tau deposition triggers progressive neuroinflammation, and the sequential changes can be evaluated in vivo in mouse brains.
Keywords: Animals; Atrophy; Benzothiazoles; Brain; Disease Models, Animal; Female; Magnetic Resonance Imaging; Male; Mice; Mice, Transgenic; Microglia; Positron-Emission Tomography; Receptors, GABA; tau Proteins; Tauopathies

Increased Serum Acylated Ghrelin Levels in Patients with Mild Cognitive Impairment. - Cao, Xi; Zhu, Min; He, Yan; Chu, Wenzheng; Du, Yifeng; Du, Heng (J Alzheimers Dis, 2018)
Ghrelin is a stomach-derived circulating hormone. In addition to its function as an orexigenic stimulant, the role of ghrelin in the consolidation of learning and memory has been implicated in recent years. However, the status of circulating acylated ghrelin (AG, that is, the functional form of ghrelin) in the symptomatic predementia stage of Alzheimer's disease (AD) has rarely been investigated. In the current study, we examined the serum levels of acylated and total ghrelin in 22 patients with mild cognitive impairment (MCI) and 30 cognitively normal controls. We have found that patients with MCI had significantly increased serum AG levels, which were inversely associated with defected short- and long-term memory as well as language skills. Of note, the levels of total circulating ghrelin were similar between the two groups. Intriguingly, serum AG but not total ghrelin was associated with AD risk factors including the age, hypertension, and hyperlipidemia. Therefore, circulating AG may serve as a potential early systemic biomarker for AD-related cognitive impairments. Nevertheless, the simplest interpretation of the results is that the levels of circulating AG are associated with cognitive impairments in patients with MCI, thereby forming the groundwork for our future studies on the systemic mechanisms of AD pertaining to the ghrelin system.
Keywords: Aged; Alzheimer Disease; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Female; Ghrelin; Humans; Male; Middle Aged; Risk Factors

Increased Vulnerability of the Hippocampus in Transgenic Mice Overexpressing APP and Triple Repeat Tau. - Arner, Andrew; Rockenstein, Edward; Mante, Michael; Florio, Jazmin; Masliah, Deborah; Salehi, Bahar; Adame, Anthony; Overk, Cassia; Masliah, Eliezer; Rissman, Robert A (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the most common tauopathy, characterized by progressive accumulation of amyloid-β (Aβ) and hyperphosphorylated tau. While pathology associated with the 4-repeat (4R) tau isoform is more abundant in corticobasal degeneration and progressive supranuclear palsy, both 3R and 4R tau isoforms accumulate in AD. Many studies have investigated interactions between Aβ and 4R tau in double transgenic mice, but few, if any, have examined the effects of Aβ with 3R tau. To examine this relationship, we crossed our APP751 mutant line with our recently characterized 3R tau mutant model to create a bigenic line (hAPP-3RTau) to model AD neuropathology. Mice were analyzed at 3 and 6 months of age for pathological and behavioral endpoints. While both the 3RTau and the hAPP-3RTau mice showed neuronal loss, increased tau aggregation, Aβ plaques and exhibited more behavioral deficits compared to the non-tg control, the bigenic mice often displaying relatively worsening levels. We found that even in young animals we found that the presence of APP/Aβ increased the accumulation of 3R tau in the neocortex and hippocampus. This observation was accompanied by activation of GSK3 and neurodegeneration in the neocortex and CA1 region. These results suggest that in addition to 4R tau, APP/Aβ may also enhance accumulation of 3R tau, a process which may be directly relevant to pathogenic pathways in AD. Our results demonstrate that this bigenic model closely parallels the pathological course of AD and may serve as a valuable model for testing new pharmacological interventions.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; Female; Glycogen Synthase Kinase 3; Hippocampus; Humans; Male; Mice; Mice, Transgenic; Neocortex; tau Proteins; Tauopathies

Influence of Butyrylcholinesterase in Progression of Mild Cognitive Impairment to Alzheimer's Disease. - Gabriel, António José; Almeida, Maria Rosário; Ribeiro, Maria Helena; Carneiro, Diogo; Valério, Daniela; Pinheiro, Ana Cristina; Pascoal, Rui; Santana, Isabel; Baldeiras, Ines (J Alzheimers Dis, 2018)
BACKGROUND: Several demographic and genetic prognostic factors of conversion from mild cognitive impairment (MCI) to Alzheimer's disease (AD) have been recognized so far. The most frequent polymorphism of butyrylcholinesterase (BuChE), the K-variant, has been proposed as a risk factor for AD, but data regarding its influence on early disease progression is still limited. OBJECTIVE: To investigate the influence of the BuChE-K variant in MCI progression to AD. METHODS: 96 MCI patients were included in the study and were genotyped for BuChE-K variant and Apolipoprotein E (ApoE). Cerebrospinal fluid (CSF) BuChE activity, as well as the levels of AD biomarkers amyloid-β 42 (Aβ42), total and hyperphosphorylated tau (t-tau and p-tau) were also determined. RESULTS: No significant differences were found in either BuChE-K variant or BuChE activity between MCI patients that progressed to AD (MCI-AD) and patients that remained stable during clinical follow-up (MCI-St). As expected, baseline CSF levels of Aβ42 were significantly lower and t-Tau, p-Tau, and ApoE ɛ4 allele frequency were significantly higher in MCI-AD patients. An association between the ApoE ɛ4 allele and the BuChE-K variant in MCI-AD, but not in MCI-St patients, was found with patients carrying both alleles presenting the highest incidence of progression and the lowest estimated time of progression to AD. CONCLUSION: Although BuChE-K alone does not seem to play a major role in progression to AD in MCI patients, a synergistic effect with the ApoE ɛ4 allele was found, highlighting the importance of assessing these combined genotypes for evaluating risk progression in MCI patients.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Biomarkers; Butyrylcholinesterase; Cognitive Dysfunction; Disease Progression; Female; Genetic Predisposition to Disease; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Risk Factors; tau Proteins

Interaction between Cytomegalovirus and Herpes Simplex Virus Type 1 Associated with the Risk of Alzheimer's Disease Development. - Lövheim, Hugo; Olsson, Jan; Weidung, Bodil; Johansson, Anders; Eriksson, Sture; Hallmans, Göran; Elgh, Fredrik (J Alzheimers Dis, 2018)
BACKGROUND: Several environmental factors, including infectious agents, have been suggested to cause Alzheimer's disease (AD). Cytomegalovirus (CMV) has been associated with AD in several recent studies. OBJECTIVE: To investigate whether carriage of CMV, alone or in combination with Herpes simplex virus (HSV), increased the risk of developing AD. METHODS: Plasma samples from 360 AD cases (75.3% women, mean age 61.2 years), taken an average of 9.6 years before AD diagnosis, and 360 age-, sex-, cohort-, and sampling date matched dementia-free controls were analyzed to detect anti-CMV (immunoglobulin [Ig] G and IgM), group-specific anti-HSV (IgG and IgM), and specific anti-HSV1 and HSV2 IgG antibodies by enzyme-linked immunosorbent assays. AD cases and dementia-free controls were compared using conditional logistic regression analyses. RESULTS: The presence of anti-CMV IgG antibodies did not increase the risk of AD (odds ratio [OR], 0.857; p = 0.497). Among AD cases, an association between CMV and HSV1 carriage was detected (OR 7.145, p < 0.001); in a conditional logistic regression model, the interaction between CMV and HSV1 was associated with AD development (OR 5.662; p = 0.007). CONCLUSION: The present findings do not support a direct relationship between CMV infection and the development of AD; however, an interaction between CMV and HSV1 was found to be associated significantly with AD development. These findings suggest that CMV infection facilitates the development of HSV1-associated AD, possibly via its effects on the immune system.
Keywords: Aged; Alzheimer Disease; Antibodies, Viral; Case-Control Studies; Cytomegalovirus; Cytomegalovirus Infections; Enzyme-Linked Immunosorbent Assay; Female; Herpes Simplex; Herpesvirus 1, Human; Humans; Immunoglobulin G; Immunoglobulin M; Logistic Models; Male; Middle Aged

Interactions between Atrial Fibrillation, Cardiovascular Risk Factors, and ApoE Genotype in Promoting Cognitive Decline in Patients with Alzheimer's Disease: A Prospective Cohort Study. - Falsetti, Lorenzo; Viticchi, Giovanna; Buratti, Laura; Grigioni, Francesco; Capucci, Alessandro; Silvestrini, Mauro (J Alzheimers Dis, 2018)
BACKGROUND: An association between non-valvular atrial fibrillation (NVAF) and cognitive impairment has been hypothesized. OBJECTIVE: We sought to evaluate whether and how permanent NVAF (pNVAF) is associated with progression of cognitive impairment in patients with Alzheimer's disease (AD) in the presence of vascular or genetic risk factors. METHODS: 310 consecutive patients affected by mild-moderate AD were included and followed for a 24-month period. At the end of the follow-up, based on the results of the neuropsychological evaluation patients were classified as stable or deteriorated to severe AD. Clinical history, therapy, time in therapeutic range for anticoagulation, Framingham cardiovascular risk profile (FCRP), CHA2DS2-VASc score, Mini-Mental State Examination (MMSE), ApoE genotype, brain CT-scan, carotid ultrasound, and ECG were collected. Binary logistic and path analysis were adopted to assess relationships between pNVAF, ApoE, and cognitive outcome. RESULTS: Despite anticoagulant therapy, pNVAF was associated with lower entry MMSE, higher mean intima-media thickness (mIMT) and higher FCRP. Among patients carrying ApoE ɛ4 allele and affected by pNVAF, the lowest MMSE (14.90±7.62) and the highest mIMT (1.16±0.17 mm) and FCRP (26.24±3.96) values were detected. In this group, the risk of cognitive deterioration reached the highest probability. pNVAF was associated with an increased cognitive deterioration in subjects with high FCRP, CHA2DS2-VASc, or mIMT. CONCLUSIONS: pNVAF seems to identify AD patients with a significant atherosclerotic burden and reduced cognitive performances. The interaction between pNVAF and ApoE ɛ4 genotype, especially with aggregated risk factors and an advanced stage of vascular damage is associated with higher risk of fast cognitive deterioration.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Atherosclerosis; Atrial Fibrillation; Carotid Intima-Media Thickness; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Prospective Studies; Risk Factors; Tomography, X-Ray Computed

A Link between Subjective Perceptions of Memory and Physical Function: Implications for Subjective Cognitive Decline. - Cosentino, Stephanie; Devanand, Davangere; Gurland, Barry (J Alzheimers Dis, 2018)
Subjective impairment in memory is a frequently defining feature of subjective cognitive decline (SCD), a state hypothesized to precede objectively apparent cognitive symptoms of Alzheimer's disease (AD) and to hold promise as a non-invasive, inexpensive, preclinical indicator of AD. However, a full model of the factors that contribute to subjective memory (SM), and therefore to SCD, has yet to be articulated. While SM impairment is widely known to be associated with negative affect, the extent to which SM functioning may also reflect other factors, particularly subjective beliefs or perceptions about one's health, is not known. To examine the extent to which SM is associated with subjective perceptions of health more broadly, the current study investigated the link between SM and subjective physical functioning (independent of depressive affect, and objective cognitive and physical function) in an ethnically diverse sample of 471 older adults enrolled in the population-based Northern Manhattan Aging Project. 199 (42%) participants endorsed no difficulty on a 5-point SM index while 272 (58%) endorsed some degree of difficulty. As hypothesized, SM correlated with both depression and subjective physical function, but not with age, education, global cognition, or objective physical function. When objective and subjective physical function were entered in two separate, adjusted linear regressions predicting SM, only subjective physical function and depressive affect independently predicted SM. Subjective perceptions of memory appear to reflect individuals' broader health perceptions in part. Articulating the various correlates of SM will improve identification of SCD specific to preclinical AD.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Executive Function; Female; Humans; Linear Models; Male; Memory; Neuropsychological Tests; New York City; Perception

Lipid Metabolism and Survival Across the Frontotemporal Dementia-Amyotrophic Lateral Sclerosis Spectrum: Relationships to Eating Behavior and Cognition. - Ahmed, Rebekah M; Highton-Williamson, Elizabeth; Caga, Jashelle; Thornton, Nicolette; Ramsey, Eleanor; Zoing, Margaret; Kim, Woojin Scott; Halliday, Glenda M; Piguet, Olivier; Hodges, John R; Farooqi, I Sadaf; Kiernan, Matthew C (J Alzheimers Dis, 2018)
BACKGROUND: Patients with frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) exhibit changes in eating behavior that could potentially affect lipid levels. OBJECTIVE: This study aimed to document changes in lipid metabolism across the ALS-FTD spectrum to identify potential relationships to eating behavior (including fat intake), cognitive change, body mass index (BMI), and effect on survival. METHODS: One hundred and twenty-eight participants were recruited: 37 ALS patients, 15 ALS patients with cognitive and behavioral change (ALS-Plus), 13 ALS-FTD, 31 behavioral variant FTD, and 32 healthy controls. Fasting total cholesterol, low density lipoprotein cholesterol (LDL), high density lipoprotein cholesterol (HDL) and triglyceride levels were measured and correlated to eating behavior (caloric, fat intake), cognitive change, and BMI; effect on survival was examined using cox regression analyses. RESULTS: There was a spectrum of lipid changes from ALS to FTD with increased triglyceride (p < 0.001), total cholesterol/HDL ratio (p < 0.001), and lower HDL levels (p = 0.001) in all patient groups compared to controls. While there was no increase in total cholesterol levels, a higher cholesterol level was found to correlate with 3.25 times improved survival (p = 0.008). Triglyceride and HDL cholesterol levels correlated to fat intake, BMI, and measures of cognition and disease duration. CONCLUSION: A spectrum of changes in lipid metabolism has been identified in ALS-FTD, with total cholesterol levels found to potentially impact on survival. These changes were mediated by changes in fat intake, and BMI, and may also be mediated by the neurodegenerative process, offering the potential to modify these factors to slow disease progression and improve survival.
Keywords: Adult; Aged; Amyotrophic Lateral Sclerosis; Australia; Body Mass Index; Case-Control Studies; Cholesterol; Cholesterol, HDL; Cognition; Energy Intake; Feeding Behavior; Female; Frontotemporal Dementia; Humans; Lipid Metabolism; Male; Middle Aged; Neuropsychological Tests; Survival Analysis

Longitudinal Changes in Serum Glucose Levels are Associated with Metabolic Changes in Alzheimer's Disease Related Brain Regions. - Burns, Christine M; Kaszniak, Alfred W; Chen, Kewei; Lee, Wendy; Bandy, Daniel J; Caselli, Richard J; Reiman, Eric M (J Alzheimers Dis, 2018)
BACKGROUND: The association between longitudinal changes in serum glucose level and longitudinal changes in [18F] Fluorodeoxyglucose-PET (FDG PET) measurements of Alzheimer's disease (AD) risk are unknown. OBJECTIVE: To investigate whether variation in serum glucose levels across time are associated with changes in FDG PET measurements of cerebral metabolic rate for glucose (rCMRgl) in brain regions preferentially affected by Alzheimer's disease (AD). METHODS: Participants are a subset of a prospective cohort study investigating FDG PET, apolipoprotein E (APOE) ɛ4, and risk for AD which includes data from baseline, interim, and follow up visits over 4.4±1.0-years. An automated brain-mapping algorithm was utilized to characterize and compare associations between longitudinal changes in serum glucose levels and longitudinal changes in rCMRgl. RESULTS: This study included 80 adults aged 61.5±5 years, including 38 carriers and 42 non-carriers of the APOE ɛ4 allele. Longitudinal increases in serum glucose levels were associated with longitudinal CMRgl decline in the vicinity of parietotemporal, precuneus/posterior cingulate, and prefrontal brain regions preferentially affected by AD (p < 0.05, corrected for multiple comparisons). Findings remained significant when controlled for APOE ɛ4 status and baseline and advancing age. CONCLUSIONS: Additional studies are needed to clarify and confirm the relationship between longitudinal changes in peripheral glucose and FDG PET measurements of AD risk. Future findings will set the stage on the use of FDG PET in the evaluation of possible interventions that target risk factors for the development of AD.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Blood Glucose; Brain; Brain Mapping; Female; Fluorodeoxyglucose F18; Heterozygote; Humans; Longitudinal Studies; Male; Middle Aged; Positron-Emission Tomography; Prospective Studies; Radiopharmaceuticals

Longitudinal Neuroimaging Analysis in Mild-Moderate Alzheimer's Disease Patients Treated with Plasma Exchange with 5% Human Albumin. - Cuberas-Borrós, Gemma; Roca, Isabel; Boada, Merce; Tárraga, Lluís; Hernandez, Isabel; Buendia, Mar; Rubio, Lourdes; Torres, Gustavo; Bittini, Ángel; Guzmán-de-Villoria, Juan A; Pujadas, Francesc; Torres, Mireia; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Recently, modifications of Aβ1-42 levels in CSF and plasma associated with improvement in memory and language functions have been observed in patients with mild-moderate Alzheimer's disease (AD) treated with plasma exchange (PE) with albumin replacement. OBJECTIVE: To detect structural and functional brain changes in PE-treated AD patients as part of a Phase II clinical trial. METHODS: Patients received between 3 and 18 PE with albumin (Albutein® 5%, Grifols) or sham-PE (controls) for 21 weeks (divided in one intensive and two maintenance periods) followed by 6-month follow-up. Brain perfusion assessed by SPECT scans using an automated software (NeuroGam®) and brain structural changes assessed by MRI were performed at weeks 0 (baseline), 21, and 44 (with additional SPECT at weeks 9 and 33). Statistical parametric mapping (voxel-based analysis, SPM) and Z-scores calculations were applied to investigate changes to baseline. RESULTS: 42 patients were recruited (39 evaluable; 37 analyzed: 18 PE-treated; 19 controls). There was a trend toward decreasing hippocampi and total intracranial volume for both patient groups during the study (p < 0.05). After six months, PE-treated patients had less cerebral perfusion loss than controls in frontal, temporal, and parietal areas, and perfusion stabilization in Brodmann area BA38-R during the PE-treatment period (p < 0.05). SPM analysis showed stabilization or absence of progression of perfusion loss in PE-treated patients until week 21, not observed in controls. CONCLUSIONS: Mild-moderate AD patients showed decreased brain volume and impairment of brain perfusion as expected for the progression of the disease. PE-treatment with albumin replacement favored the stabilization of perfusion.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Plasma Exchange; Serum Albumin, Human; Time Factors; Tomography, Emission-Computed, Single-Photon; Treatment Outcome

A Longitudinal Study of Total and Phosphorylated α-Synuclein with Other Biomarkers in Cerebrospinal Fluid of Alzheimer's Disease and Mild Cognitive Impairment. - Wang, Hua; Stewart, Tessandra; Toledo, Jon B; Ginghina, Carmen; Tang, Lu; Atik, Anzari; Aro, Patrick; Shaw, Leslie M; Trojanowski, John Q; Galasko, Douglas R; Edland, Steven; Jensen, Poul H; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) features a dynamic sequence of amyloid deposition, neurodegeneration, and cognitive impairment. A significant fraction of AD brains also displays Lewy body pathology, suggesting that addition of classically Parkinson's disease-related proteins to the AD biomarker panel may be of value. To determine whether addition of cerebrospinal fluid (CSF) total α-synuclein and its form phosphorylated at S129 (pS129) to the AD biomarker panel [Amyloid-β1-42 (Aβ42), tau, and phosphorylated tau (p-tau181)] improves its performance, we examined CSF samples collected longitudinally up to 7 years as part of the Alzheimer's Disease Neuroimaging Initiative. From 87 AD, 177 mild cognitive impairment (MCI), and 104 age-matched healthy controls, 792 baseline and longitudinal CSF samples were tested for total α-synuclein, pS129, Aβ42, tau, and p-tau181. pS129, but not total α-synuclein, was weakly associated with diagnosis at baseline when t-tau/Aβ42 was included in the statistical model (β= 0.0026, p = 0.041, 95% CI [(0.0001)-(0.005)]). CSF α-synuclein predicted Alzheimer's Disease Assessment Scale-Cognitive (β= -0.59, p = 0.0015, 95% CI [(-0.96)-(-0.23)]), memory (β= 0.4, p = 0.00025, 95% CI [(0.16)-(0.59)]), and executive (0.62,<0.0001, 95% CI [(0.31)-(0.93)]) function composite scores, and progression from MCI to AD (β= 0.019, p = 0.0011, 95% CI [(0.002)-(0.20)]). pS129 was associated with executive function (β= -2.55, p = 0.0085, 95% CI [(-4.45)-(-0.66)]). Lower values in the mismatch between α-synuclein and p-tau181 predicted faster cognitive decline (β= 0.64, p = 0.0012, 95% CI [(0.48)-(0.84)]). Longitudinal biomarker changes did not differ between groups, and may not reflect AD progression. The α-synuclein-p-tau181-Mismatch could better predict longitudinal cognitive changes than classical AD markers alone, and its pathological correlates should be investigated further.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Executive Function; Female; Humans; Linear Models; Longitudinal Studies; Male; Memory Disorders; Multivariate Analysis; Neuropsychological Tests; Phosphorylation; tau Proteins

Low Prevalence of Cancer in Patients with Frontotemporal Lobar Degeneration. - Katisko, Kasper; Haapasalo, Annakaisa; Koivisto, Anne; Krüger, Johanna; Hartikainen, Päivi; Korhonen, Ville; Helisalmi, Seppo; Herukka, Sanna-Kaisa; Remes, Anne M; Solje, Eino (J Alzheimers Dis, 2018)
Several studies have reported reduced risk of cancer in patients with Alzheimer's disease (AD) or Parkinson's disease. The relationship between cancer and frontotemporal lobar degeneration (FTLD) has not been previously reported. Here, our aim was to evaluate the occurrence of cancer in Finnish FTLD patients with a high proportion of C9ORF72 repeat expansion carriers in comparison to age- and sex-matched group of AD patients and control subjects classified as not cognitively impaired (NCI). The prevalence of cancer was 9.7% in FTLD, 18.7% in AD, and 17.4% in NCI (FTLD versus AD p = 0.012, FTLD versus NCI p = 0.029) groups. No differences were observed between C9ORF72 repeat expansion carriers and non-carriers inside the FTLD group. To our knowledge, this is the first study showing significantly lower prevalence of cancer in FTLD patients compared to patients with AD or NCI subjects. Our data suggest an inverse association between neurodegeneration and cancer and that FTLD-specific mechanisms may underlie the especially strong inverse association observed in this study.
Keywords: Aged; Alzheimer Disease; C9orf72 Protein; DNA Repeat Expansion; Female; Finland; Frontotemporal Lobar Degeneration; Heterozygote; Humans; Male; Middle Aged; Neoplasms; Prevalence

Mental States in Moving Shapes: Distinct Cortical and Subcortical Contributions to Theory of Mind Impairments in Dementia. - Synn, Artemis; Mothakunnel, Annu; Kumfor, Fiona; Chen, Yu; Piguet, Olivier; Hodges, John R; Irish, Muireann (J Alzheimers Dis, 2018)
Impaired capacity for Theory of Mind (ToM) represents one of the hallmark features of the behavioral variant of frontotemporal dementia (bvFTD) and is suggested to underpin an array of socioemotional disturbances characteristic of this disorder. In contrast, while social processing typically remains intact in Alzheimer's disease (AD), the cognitive loading of socioemotional tasks may adversely impact mentalizing performance in AD. Here, we employed the Frith-Happé animations as a dynamic on-line assessment of mentalizing capacity with reduced incidental task demands in 18 bvFTD, 18 AD, and 25 age-matched Controls. Participants viewed silent animations in which geometric shapes interact in Random, Goal-Directed, and ToM conditions. An exclusive deficit in ToM classification was observed in bvFTD relative to Controls, while AD patients were impaired in the accurate classification of both Random and ToM trials. Correlation analyses revealed robust associations between ToM deficits and carer ratings of affective empathy disruption in bvFTD, and with episodic memory dysfunction in AD. Voxel-based morphometry analyses further identified dissociable neural correlates contingent on patient group. A distributed network of medial prefrontal, frontoinsular, striatal, lateral temporal, and parietal regions were implicated in the bvFTD group, whereas the right hippocampus correlated with task performance in AD. Notably, subregions of the cerebellum, including lobules I-IV and V, bilaterally were implicated in task performance irrespective of patient group. Our findings reveal new insights into the mechanisms potentially mediating ToM disruption in dementia syndromes, and suggest that the cerebellum may play a more prominent role in social cognition than previously appreciated.
Keywords: Aged; Alzheimer Disease; Brain; Case-Control Studies; Female; Frontotemporal Dementia; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory, Episodic; Mentalization; Middle Aged; Neuropsychological Tests; Task Performance and Analysis; Theory of Mind

microRNA 221 Targets ADAM10 mRNA and is Downregulated in Alzheimer's Disease. - Manzine, Patricia R; Pelucchi, Silvia; Horst, Maria A; Vale, Francisco A C; Pavarini, Sofia C I; Audano, Matteo; Mitro, Nico; Di Luca, Monica; Marcello, Elena; Cominetti, Márcia R (J Alzheimers Dis, 2018)
ADAM10 is the α-secretase that cleaves amyloid-β protein precursor in the non-amyloidogenic pathway in Alzheimer's disease (AD) and is known to be regulated by different microRNAs (miRNAs), which are post-transcriptional regulators related to several biological and pathological processes, including AD. Here we proposed to explore and validate miRNAs that have direct or indirect relations to the AD pathophysiology and ADAM10 gene. Approximately 700 miRNAs were analyzed and 21 differentially expressed miRNAs were validated in a sample of 21 AD subjects and 17 cognitively healthy matched controls. SH-SY5Y cells were transfected with miR-144-5p, miR-221, and miR-374 mimics and inhibitors, and ADAM10 protein levels were evaluated. miR-144-5p, miR-221, and miR-374 were downregulated in AD. The overexpression of miR-221 in SH-SY5Y cells resulted in ADAM10 reduction and its inhibition in ADAM10 increased. These findings show that miR-221 can be a new potential therapeutic target for increasing ADAM10 levels in AD. In addition, these results can contribute to the better understanding of ADAM10 post-transcriptional regulation.
Keywords: ADAM10 Protein; Aged; Aged, 80 and over; Alzheimer Disease; Cell Line, Tumor; Cohort Studies; Down-Regulation; Female; Humans; Male; MicroRNAs; Middle Aged; Neuroblastoma; Psychiatric Status Rating Scales; RNA, Messenger; ROC Curve; Transfection

Mitochondrial Translocase of the Outer Membrane Alterations May Underlie Dysfunctional Oxidative Phosphorylation in Alzheimer's Disease. - Chai, Yuek Ling; Xing, Huayang; Chong, Joyce R; Francis, Paul T; Ballard, Clive G; Chen, Christopher P; Lai, Mitchell K P (J Alzheimers Dis, 2018)
BACKGROUND: The translocase of the outer membrane (TOM) is a vital mitochondrial transport system facilitating the importation of nuclear encoded proteins into the organelle. While mitochondrial dysfunction, including perturbation of oxidative phosphorylation (OXPHOS) complex, is evident in Alzheimer's disease (AD), it remains unclear whether the observed OXPHOS deficits may be associated with TOM alterations. OBJECTIVES: To correlate TOM subunits with OXPHOS complex proteins in AD. METHODS: Postmortem neocortex (BA40) from AD and age-matched controls were processed to obtain mitochondrial enriched homogenates for the measurement of Tom20, Tom22, Tom40, and Tom70 as well as components of OXPHOS complex I-V by immunoblotting. RESULTS: Tom20 and Tom70 immunoreactivities were significantly reduced in AD, as were components of OXPHOS complex I and III. Both Tom20 and Tom70 positively correlated with complex III and V, while Tom20 also correlated withcomplex IV. CONCLUSION: Reductions in certain TOM subunits and their correlations with specific OXPHOS complex proteins suggest that an impaired mitochondrial transportation system may contribute to previously observed oxidative phosphorylation deficits in AD. Follow-up studies are needed to corroborate the present correlative study.
Keywords: Aged, 80 and over; Alzheimer Disease; Autopsy; Brain; Female; Humans; Male; Mitochondria; Mitochondrial Membrane Transport Proteins; Multivariate Analysis; Oxidative Phosphorylation

Mutation Screening of the CHCHD2 Gene for Alzheimer's Disease and Frontotemporal Dementia in Chinese Mainland Population. - Che, Xiang-Qian; Zhao, Qian-Hua; Huang, Yue; Li, Xia; Ren, Ru-Jing; Chen, Sheng-Di; Guo, Qi-Hao; Wang, Gang (J Alzheimers Dis, 2018)
As an important multifunctional protein involved in regulation of mitochondrial metabolism, CHCHD2 was identified as a causative gene for Parkinson's disease (PD), yet the relationship between CHCHD2 and neurodegenerative dementia is not well understood. We directly sequenced the entire coding region of CHCHD2 gene in 150 AD patients, 84 FTD patients, and 417 controls. Four rare putative pathogenic variants of CHCHD2, including rs142444896 (c.5C>T, p.P2L), rs752705344 (c.15C>G, p.S5R), rs145190179 (c.94G>A, p.A32T), and rs182992574 (c.255T>A, p.S85R) were identified from a cohort composed of 150 AD and 84 FTD patients. These results suggest that CH CHD2 gene play an important role in other neurodegenerative disorders from our dementia study in China.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Asian Continental Ancestry Group; Case-Control Studies; China; Female; Frontotemporal Dementia; Genetic Association Studies; Humans; Male; Middle Aged; Mitochondrial Proteins; Mutation; Transcription Factors

Negative Prospective Memory in Alzheimer's Disease: "Do Not Perform That Action". - El Haj, Mohamad; Coello, Yann; Kapogiannis, Dimitrios; Gallouj, Karim; Antoine, Pascal (J Alzheimers Dis, 2018)
Relatively to "standard" prospective memory, i.e., remembering to perform a future action, little is known about negative prospective memory, i.e., remembering not to perform a future action. This study investigated the latter ability in Alzheimer's disease (AD). AD participants and healthy older adults were asked to click on the keyboard or not to click on it when a cue word was encountered. Results showed more omissions (i.e., forgetting to click the keyboard when the instruction was to do so) in AD participants than in healthy older adults, suggesting a prospective memory deficit. Interestingly, more commissions (i.e., clicking the keyboard when the instruction was not to do so) were also observed in AD participants than in healthy older adults. Similar levels of commissions and omissions were observed in AD participants and in healthy older adults. Also, commissions and omissions were correlated with performance on an inhibition assessment task. Our findings reveal that AD is characterized by not only difficulty in the retrieval of recent information, but also difficulty to inhibit no-longer appropriate stimulus-response associations previously learned, suggesting a specific deficit of negative prospective memory in AD.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Female; Humans; Inhibition (Psychology); Male; Memory Disorders; Memory, Episodic; Mental Recall; Neuropsychological Tests

A Network of Genetic Effects on Non-Demented Cognitive Aging: Alzheimer's Genetic Risk (CLU + CR1 + PICALM) Intensifies Cognitive Aging Genetic Risk (COMT + BDNF) Selectively for APOEɛ4 Carriers. - Sapkota, Shraddha; Dixon, Roger A (J Alzheimers Dis, 2018)
BACKGROUND: Trajectories of complex neurocognitive phenotypes in preclinical aging may be produced differentially through selective and interactive combinations of genetic risk. OBJECTIVE: We organize three possible combinations into a "network" of genetic risk indices derived from polymorphisms associated with normal and impaired cognitive aging, as well as Alzheimer's disease (AD). Specifically, we assemble and examine three genetic clusters relevant to non-demented cognitive trajectories: 1) Apolipoprotein E (APOE), 2) a Cognitive Aging Genetic Risk Score (CA-GRS; Catechol-O-methyltransferase + Brain-derived neurotrophic factor), and 3) an AD-Genetic Risk Score (AD-GRS; Clusterin + Complement receptor 1 + Phosphatidylinositol-binding clathrin assembly protein). METHOD: We use an accelerated longitudinal design (n = 634; age range = 55-95 years) to test whether AD-GRS (low versus high) moderates the effect of increasing CA-GRS risk on executive function (EF) performance and change as stratified by APOE status (ɛ4+ versus ɛ4-). RESULTS: APOEɛ4 carriers with high AD-GRS had poorer EF performance at the centering age (75 years) and steeper 9-year decline with increasing CA-GRS but this association was not present in APOEɛ4 carriers with low AD-GRS. CONCLUSIONS: APOEɛ4 carriers with high AD-GRS are at elevated risk of cognitive decline when they also possess higher CA-GRS risk. Genetic risk from both common cognitive aging and AD-related indices may interact in intensification networks to differentially predict (1) level and trajectories of EF decline and (2) potential selective vulnerability for transitions into impairment and dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Brain-Derived Neurotrophic Factor; Canada; Catechol O-Methyltransferase; Clusterin; Cognitive Aging; Cognitive Dysfunction; Executive Function; Female; Genetic Predisposition to Disease; Heterozygote; Humans; Longitudinal Studies; Male; Middle Aged; Monomeric Clathrin Assembly Proteins; Neuropsychological Tests; Receptors, Complement 3b

Neuroanatomical Comparison of the "Word" and "Picture" Versions of the Free and Cued Selective Reminding Test in Alzheimer's Disease. - Slachevsky, Andrea; Barraza, Paulo; Hornberger, Michael; Muñoz-Neira, Carlos; Flanagan, Emma; Henriquez, Fernando; Bravo, Eduardo; Farías, Mauricio; Delgado, Carolina (J Alzheimers Dis, 2018)
Episodic memory tests with cued recall, such as the Free and Cued Selective Reminding Test (FCSRT), allow for the delineation of hippocampal and prefrontal atrophy contributions to memory performance in Alzheimer's disease (AD). Both Word and Picture versions of the test exist but show different profiles, with the Picture version usually scoring higher across different cohorts. One possible explanation for this divergent performance between the different modality versions of the test might be that they rely on different sets of neural correlates. The current study explores this by contrasting the neural correlates of the Word and Picture versions of the FCSRT with voxel-based morphometry (VBM) in AD and healthy subjects. We predicted that the Picture version would be associated with different cortical regions than the Word version, which might be more hippocampal-centric. When comparing 35 AD patients and 34 controls, AD patients exhibited impairments on both versions of the FCSRT and both groups performed higher in the Picture version. A region of interest analysis based on prior work revealed significant correlations between free recall of either version with atrophy of the temporal pole and hippocampal regions. Thus, contrary to expectations, performance on both the Word and the Picture version of the FCSRT is associated with largely overlapping networks. Free recall is associated with hippocampal volume and might be properly considered as an indicator of hippocampal structural integrity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Cues; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Memory, Episodic; Mental Recall; Middle Aged; Neuropsychological Tests; Photic Stimulation

Neuropsychiatric and Cognitive Subtypes among Community-Dwelling Older Persons and the Association with DSM-5 Mild Neurocognitive Disorder: Latent Class Analysis. - Liew, Tau Ming; Yu, Junhong; Mahendran, Rathi; Ng, Tze-Pin; Kua, Ee-Heok; Feng, Lei (J Alzheimers Dis, 2018)
BACKGROUND: Neuropsychiatric symptoms (NPS) have been shown to increase the risk of neurocognitive disorders (NCD), leading to the recently-published criteria of mild behavioral impairment (MBI) to identify pre-dementia using NPS alone. However, MBI drew concerns about over-diagnosing subclinical psychiatric disorders. OBJECTIVE: We hypothesized that the specificity of NPS in predicting NCD may be improved by considering NPS together with various domains of cognitive deficits. We tested this hypothesis by identifying subtypes based on the combination of NPS and cognitive deficits among community-dwelling older persons, and evaluating how the identified subtypes were associated with mild NCD. METHODS: Our participants were from a community-based cohort study. They completed assessments such as Geriatric Depression Scale (GDS), Geriatric Anxiety Inventory (GAI), and Montreal Cognitive Assessment (MoCA). Those with possible cognitive impairment underwent further evaluations for mild NCD. Latent class analysis was conducted using GDS, GAI, and MoCA domains. Logistic regression was performed to investigate the association between the latent-classes and mild NCD. RESULTS: We included 825 participants, and identified four distinct subtypes: Subtype 1 (no NPS or cognitive deficits), Subtype 2 (NPS alone), Subtype 3 (cognitive deficits alone), and Subtype 4 (both NPS and cognitive deficits). Subtype 1 and 2 had low risk of prevalent mild NCD (OR 0.92- 1.00), while Subtype 3 conferred a moderate risk (OR 4.47- 4.85) and Subtype 4 had the highest risk (OR 7.95- 8.63). CONCLUSION: We demonstrated the benefits of combining NPS and cognitive deficits to predict those at highest risk of prevalent mild NCD. Our findings highlighted the relevance of subclinical psychiatric symptoms in predicting NCD, and indirectly supported the need for longer durations of NPS to improve its specificity.
Keywords: Aged; Cognition; Cognitive Dysfunction; Diagnostic and Statistical Manual of Mental Disorders; Female; Humans; Latent Class Analysis; Logistic Models; Longitudinal Studies; Male; Middle Aged; Neuropsychological Tests; Sensitivity and Specificity

An Objective Method to Accurately Measure Cardiorespiratory Fitness in Older Adults Who Cannot Satisfy Widely Used Oxygen Consumption Criteria. - Dougherty, Ryan J; Lindheimer, Jacob B; Stegner, Aaron J; Van Riper, Stephanie; Okonkwo, Ozioma C; Cook, Dane B (J Alzheimers Dis, 2018)
Cardiorespiratory fitness (CRF) is routinely investigated in older adults; however, the most appropriate CRF measure to use for this population has received inadequate attention. This study aimed to 1) evaluate the reliability and validity of the oxygen uptake efficiency slope (OUES) as a sub-maximal measurement of CRF; 2) examine demographic, risk-factor, and exercise testing differences in older adults who satisfied standardized criteria for a peak oxygen consumption (V̇O2peak) test compared to those who did not; and 3) determine the difference between directly measured V̇O2peak values and OUES-predicted V̇O2peak values. One hundred ten enrollees from the Wisconsin Registry for Alzheimer's Prevention participated in this study. Participants performed a graded maximal exercise test and wore an accelerometer for 7 days. For each participant, the OUES was calculated at 75%, 90%, and 100% of exercise duration. V̇O2peak was recorded at peak effort, and one week of physical activity behavior was measured. OUES values calculated at separate relative exercise durations displayed excellent reliability (ICC = 0.995; p < 0.001), and were strongly correlated with V̇O2peak (rrange = 0.801-0.909; p < 0.001). As hypothesized, participants who did not satisfy V̇O2peak criteria were significantly older than those who satisfied criteria (p = 0.049) and attained a directly measured V̇O2peak that was 2.31 mL·kg·min-1 less than the value that was predicted by OUES V̇O2peak (p = 0.003). Older adults are less likely to satisfy V̇O2peak criteria, which results in an underestimation of their CRF. Without adhering to standardized criteria, V̇O2peak measurement error may lead to misinterpretation of CRF and age-related associations. Here, we conclude that OUES is a reliable, valid measurement of CRF which does not require achievement of standardized criteria.
Keywords: Aged; Cardiorespiratory Fitness; Exercise Test; Female; Humans; Male; Middle Aged; Oxygen Consumption; Reproducibility of Results; Wisconsin

Patient Characteristics and Outcomes Associated with Receiving an Earlier Versus Later Diagnosis of Probable Alzheimer's Disease. - Kirson, Noam Y; Scott Andrews, J; Desai, Urvi; King, Sarah B; Schonfeld, Sophie; Birnbaum, Howard G; Ball, Daniel E; Kahle-Wrobleski, Kristin (J Alzheimers Dis, 2018)
BACKGROUND: Effectiveness of Alzheimer's disease (AD) treatments may depend critically on the timeliness of intervention. OBJECTIVE: To compare characteristics and outcomes of patients diagnosed with probable AD (prAD) based on time elapsed from first onset of cognitive decline. METHODS: Patients with ≥1 prAD diagnosis and ≥1 follow-up visit were selected from the National Alzheimer's Coordinating Center (NACC) Uniform Data Set (UDS; 9/2005-6/2015) and stratified based on the time between the perceived onset of cognitive decline at baseline and first prAD diagnosis (i.e., earlier versus later diagnosis). Characteristics at baseline and prAD diagnosis, clinically meaningful progression, and medication use following prAD diagnosis were compared. RESULTS: Median time from perceived onset of cognitive decline to prAD diagnosis was 4.5 years (earlier diagnosis: ≤3.46; later diagnosis: >5.71). Earlier-diagnosed patients (n = 1,476) were younger at baseline (74.3 versus 76.3 years) and had better cognitive and functional scores than later-diagnosed patients (n = 1,474). At first prAD diagnosis, earlier-diagnosed patients had lower mean global Clinical Dementia Rating (CDR) score (0.8 versus 1.1), higher mean Mini-Mental State Examination (MMSE) (22.6 versus 20.0), and lower mean Functional Activities Questionnaire (11.6 versus 17.3). Earlier- and later-diagnosed patients experienced similar time to a decrease of ≥3 points in MMSE (median 23.2 versus 23.1 months, p = 0.83), but earlier-diagnosed patients had longer time to a CDR score of ≥2 points, and longer times to initiation of AD medication and antipsychotic agents (all p < 0.01). CONCLUSION: Earlier prAD diagnosis in NACC data is associated with higher cognitive function and lower functional impairment at diagnosis.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Cohort Studies; Datasets as Topic; Disease Progression; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Statistics, Nonparametric; Time Factors

Perspectives on Communicating Biomarker-Based Assessments of Alzheimer's Disease to Cognitively Healthy Individuals. - Milne, Richard; Bunnik, Eline; Diaz, Ana; Richard, Edo; Badger, Shirlene; Gove, Dianne; Georges, Jean; Fauria, Karine; Molinuevo, Jose-Luis; Wells, Katie; Ritchie, Craig; Brayne, Carol (J Alzheimers Dis, 2018)
In clinical trials which target pathophysiological mechanisms associated with Alzheimer's disease, research participants who are recruited based on biomarker test results should be informed about their increased risk of developing Alzheimer's dementia. This paper presents the results of a qualitative focus group study of attitudes and concerns toward learning information about biomarker-based risk status among healthy research participants in the United Kingdom and Spain and people with dementia and their supporters/caregivers from countries represented in the European Working Group of People with Dementia of Alzheimer Europe. The study identified expectations related to learning risk status and preferences related to the content, quality, and follow-up of the disclosure process. The latter emphasize distinctions between risk and diagnoses, the importance of clear information about risk, and suggestions for risk reduction, as well as expectations for follow up and support. The implications of these preferences for practice are discussed. Providing details of research participants' experience and views may serve as a guide for the development of processes for the responsible disclosure of Alzheimer's disease biomarkers.
Keywords: Adult; Aged; Alzheimer Disease; Biomarkers; Caregivers; Disclosure; Female; Focus Groups; Humans; Male; Middle Aged; Qualitative Research; Risk Factors; Spain; United Kingdom

Physical Activity and Hippocampal Sub-Region Structure in Older Adults with Memory Complaints. - Siddarth, Prabha; Rahi, Berna; Emerson, Natacha D; Burggren, Alison C; Miller, Karen J; Bookheimer, Susan; Lavretsky, Helen; Dobkin, Bruce; Small, Gary; Merrill, David A (J Alzheimers Dis, 2018)
BACKGROUND: Physical activity (PA) plays a major role in maintaining cognition in older adults. PA has been shown to be correlated with total hippocampal volume, a memory-critical region within the medial temporal lobe (MTL). However, research on associations between PA and MTL sub-region integrity is limited. OBJECTIVE: To examine the relationship between PA, MTL thickness, and its sub-regions, and cognitive function in non-demented older adults with memory complaints. METHODS: Twenty-nine subjects aged ≥60 years, with memory complaints were recruited for this cross-sectional study. PA was tracked for 7 days using accelerometers, and average number of steps/day determined. Subjects were categorized into two groups: those who walked ≤4000 steps/day (lower PA) and those with >4000 steps/day (higher PA). Subjects received neuropsychological testing and 3T MRI scans. Nonparametric ANCOVAs controlling for age examined differences between the two groups. RESULTS: Twenty-six subjects aged 72.7(8.1) years completed the study. The higher PA group (n = 13) had thicker fusiform gyrus (median difference = 0.11 mm, effect size (ES) = 1.43, p = 0.001) and parahippocampal cortex (median difference = 0.12 mm, ES = 0.93, p = 0.04) compared to the lower PA group. The higher PA group also exhibited superior performance in attention and information-processing speed (median difference = 0.90, ES = 1.61, p = 0.003) and executive functioning (median difference = 0.97, ES = 1.24, p = 0.05). Memory recall was not significantly different between the two groups. CONCLUSION: Older non-demented individuals complaining of memory loss who walked >4000 steps each day had thicker MTL sub-regions and better cognitive functioning than those who walked ≤4000 steps. Future studies should include longitudinal analyses and explore mechanisms mediating hippocampal related atrophy.
Keywords: Aged; Aged, 80 and over; Cognition; Cross-Sectional Studies; Executive Function; Exercise; Female; Geriatric Assessment; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Memory; Memory Disorders; Middle Aged; Neuropsychological Tests

Potential of Low Dose Leuco-Methylthioninium Bis(Hydromethanesulphonate) (LMTM) Monotherapy for Treatment of Mild Alzheimer's Disease: Cohort Analysis as Modified Primary Outcome in a Phase III Clinical Trial. - Wilcock, Gordon K; Gauthier, Serge; Frisoni, Giovanni B; Jia, Jianping; Hardlund, Jiri H; Moebius, Hans J; Bentham, Peter; Kook, Karin A; Schelter, Bjoern O; Wischik, Damon J; Davis, Charles S; Staff, Roger T; et al. (J Alzheimers Dis, 2018)
BACKGROUND: LMTM is being developed as a treatment for AD based on inhibition of tau aggregation. OBJECTIVES: To examine the efficacy of LMTM as monotherapy in non-randomized cohort analyses as modified primary outcomes in an 18-month Phase III trial in mild AD. METHODS: Mild AD patients (n = 800) were randomly assigned to 100 mg twice a day or 4 mg twice a day. Prior to unblinding, the Statistical Analysis Plan was revised to compare the 100 mg twice a day as monotherapy subgroup (n = 79) versus 4 mg twice a day as randomized (n = 396), and 4 mg twice a day as monotherapy (n = 76) versus 4 mg twice a day as add-on therapy (n = 297), with strong control of family-wise type I error. RESULTS: The revised analyses were statistically significant at the required threshold of p < 0.025 in both comparisons for change in ADAS-cog, ADCS-ADL, MRI atrophy, and glucose uptake. The brain atrophy rate was initially typical of mild AD in both add-on and monotherapy groups, but after 9 months of treatment, the rate in monotherapy patients declined significantly to that reported for normal elderly controls. Differences in severity or diagnosis at baseline between monotherapy and add-on patients did not account for significant differences in favor of monotherapy. CONCLUSIONS: The results are consistent with earlier studies in supporting the hypothesis that LMTM might be effective as monotherapy and that 4 mg twice a day may serve as well as higher doses. A further suitably randomized trial is required to test this hypothesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antipsychotic Agents; Cohort Studies; Double-Blind Method; Female; Humans; International Cooperation; Male; Mental Status and Dementia Tests; Methylene Blue; Middle Aged; Treatment Outcome

Pramlintide: The Effects of a Single Drug Injection on Blood Phosphatidylcholine Profile for Alzheimer's Disease. - Tao, Qiushan; Zhu, Haihao; Chen, Xi; Stern, Robert A; Kowall, Neil; Au, Rhoda; Blusztajn, Jan Krzysztof; Qiu, Wei Qiao (J Alzheimers Dis, 2018)
Studies suggest that a single injection of pramlintide, an amylin analog, induces changes in Alzheimer's disease (AD) biomarkers in the blood of AD mouse models and AD patients. The aim of this study was to examine whether a pramlintide challenge combined with a phosphatidylcholine (PC) profile diagnoses of AD and mild cognitive impairment (MCI) better than PC alone. Non-diabetic subjects with cognitive status were administered a single subcutaneous injection of 60 mcg of pramlintide under fasting condition. A total of 71 PCs, amyloid-β peptide (Aβ), and total tau (t-tau) in plasma at different time points were measured and treated as individual variables. A single injection of pramlintide altered the levels of 7 PCs in the blood, while a pramlintide injection plus food modulated the levels of 10 PCs in the blood (p < 0.05). The levels of 2 PCs in MCI and 12 PCs in AD in the pramlintide challenge were significantly lower than the ones in controls. We found that while some PCs were associated with only Aβ levels, other PCs were associated with both Aβ and t-tau levels. A receiver operating characteristic analysis of the PCs was combined with the Aβ and t-tau data to produce an area under the curve predictive value of 0.9799 between MCI subjects and controls, 0.9794 between AD subjects and controls, and 0.9490 between AD and MCI subjects. A combination of AD biomarkers and a group of PCs post a pramlintide challenge may provide a valuable diagnostic and prognostic test for AD and MCI.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Female; Humans; Islet Amyloid Polypeptide; Logistic Models; Male; Middle Aged; Phosphatidylcholines; ROC Curve; tau Proteins

Prediction of Alzheimer's Dementia in Patients with Amnestic Mild Cognitive Impairment in Clinical Routine: Incremental Value of Biomarkers of Neurodegeneration and Brain Amyloidosis Added Stepwise to Cognitive Status. - Lange, Catharina; Suppa, Per; Pietrzyk, Uwe; Makowski, Marcus R; Spies, Lothar; Peters, Oliver; Buchert, Ralph (J Alzheimers Dis, 2018)
The aim of this study was to evaluate the incremental benefit of biomarkers for prediction of Alzheimer's disease dementia (ADD) in patients with mild cognitive impairment (MCI) when added stepwise in the order of their collection in clinical routine. The model started with cognitive status characterized by the ADAS-13 score. Hippocampus volume (HV), cerebrospinal fluid (CSF) phospho-tau (pTau), and the FDG t-sum score in an AD meta-region-of-interest were compared as neurodegeneration markers. CSF-Aβ1-42 was used as amyloidosis marker. The incremental prognostic benefit from these markers was assessed by stepwise Kaplan-Meier survival analysis in 402 ADNI MCI subjects. Predefined cutoffs were used to dichotomize patients as 'negative' or 'positive' for AD characteristic alteration with respect to each marker. Among the neurodegeneration markers, CSF-pTau provided the best incremental risk stratification when added to ADAS-13. FDG PET outperformed HV only in MCI subjects with relatively preserved cognition. Adding CSF-Aβ provided further risk stratification in pTau-positive subjects, independent of their cognitive status. Stepwise integration of biomarkers allows stepwise refinement of risk estimates for MCI-to-ADD progression. Incremental benefit strongly depends on the patient's status according to the preceding diagnostic steps. The stepwise Kaplan-Meier curves might be useful to optimize diagnostic workflow in individual patients.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloidosis; Brain; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Imaging, Three-Dimensional; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Survival Analysis; tau Proteins

Predictors of Age of Diagnosis and Survival of Alzheimer's Disease in Down Syndrome. - Sinai, Amanda; Mokrysz, Claire; Bernal, Jane; Bohnen, Ingrid; Bonell, Simon; Courtenay, Ken; Dodd, Karen; Gazizova, Dina; Hassiotis, Angela; Hillier, Richard; McBrien, Judith; McCarthy, Jane; et al. (J Alzheimers Dis, 2018)
BACKGROUND: People with Down syndrome (DS) are an ultra-high risk population for Alzheimer's disease (AD). Understanding the factors associated with age of onset and survival in this population could highlight factors associated with modulation of the amyloid cascade. OBJECTIVE: This study aimed to establish the typical age at diagnosis and survival associated with AD in DS and the risk factors associated with these. METHODS: Data was obtained from the Aging with Down Syndrome and Intellectual Disabilities (ADSID) research database, consisting of data extracted from clinical records of patients seen by Community Intellectual Disability Services (CIDS) in England. Survival times when considering different risk factors were calculated. RESULTS: The mean age of diagnosis was 55.80 years, SD 6.29. Median survival time after diagnosis was 3.78 years, and median age at death was approximately 60 years. Survival time was associated with age of diagnosis, severity of intellectual disability, living status, anti-dementia medication status, and history of epilepsy. Age at diagnosis and treatment status remained predictive of survival time following adjustment. CONCLUSION: This study provides the best estimate of survival in dementia within the DS population to date, and is in keeping with previous estimates from smaller studies in the DS population. This study provides important estimates and insights into possible predictors of survival and age of diagnosis of AD in adults with DS, which will inform selection of participants for treatment trials in the future.
Keywords: Age of Onset; Alzheimer Disease; Down Syndrome; England; Female; Humans; Male; Middle Aged; Risk Factors; Survival Analysis

Prevalence of Delirium in a Population of Elderly Outpatients with Dementia: A Retrospective Study. - Addesi, Desirée; Maio, Raffaele; Smirne, Nicoletta; Laganà, Valentina; Altomari, Natalia; Puccio, Gianfranco; Colao, Rosanna; Cupidi, Chiara; Perticone, Francesco; Bruni, Amalia Cecilia (J Alzheimers Dis, 2018)
BACKGROUND: Delirium is a multifactorial geriatric syndrome and often occurs in patients with cognitive impairment. It also remains under-recognized, specifically in elderly outpatients, because signs of delirium might overlap with symptoms of dementia. OBJECTIVE: The aim of the present study is to retrospectively apply the chart-based delirium instrument on a cohort of elderly outpatients with dementia, to assess prevalence and features of delirium in this population. METHODS: We randomly selected 650 medical records of outpatients referred to the "Neurogenetic Regional Centre" (CRN) of Lamezia Terme. Each evaluation included demographics, medical history, drugs, type and severity of dementia, and cognitive and functional status. Delirium was identified by the application of the chart-based delirium instrument. RESULTS: The prevalence of delirium was 13.3%. The study population was divided, according to the presence of delirium, into two subgroups. Compared to the no delirium group, the delirium group was significantly older and had greater cognitive impairment with lower MMSE scores both at baseline and at the end of the follow up. They also had a significant lower score on the ADL and IADL. In this group, a higher intake of antihypertensive and antipsychotic drugs, together with a lower intake of cholinesterase inhibitors and memantine, was observed. CONCLUSIONS: In this study, the chart-based delirium instrument was applied to an outpatient population affected by dementia and followed for a long time. Our data confirm the importance that age and frailty play on the genesis of delirium and suggest attention should be paid to the pharmacological treatment of these patients.
Keywords: Aged; Aged, 80 and over; Antipsychotic Agents; Cohort Studies; Delirium; Dementia; Female; Geriatric Assessment; Humans; Male; Outpatients; Prevalence; Severity of Illness Index

Profiling of Specific Gene Expression Pathways in Peripheral Cells from Prodromal Alzheimer's Disease Patients. - Serpente, Maria; Fenoglio, Chiara; Cioffi, Sara Maria Giulia; Oldoni, Emanuela; Arcaro, Marina; Arighi, Andrea; Fumagalli, Giorgio Giulio; Ghezzi, Laura; Scarpini, Elio; Galimberti, Daniela (J Alzheimers Dis, 2018)
Herein, we performed a gene expression profiling in a cohort of 10 mild cognitive impairment (MCI), subdivided, according to the analysis of cerebrospinal fluid biomarkers, in prodromal Alzheimer's disease (AD) and non-AD MCI, as compared with 27 AD patients and 24 controls, in order to detect early gene expression alterations. We observed a significant upregulation of insulin (INS) and INS Receptor (INSR) expression levels in AD both prodromal and fully symptomatic, as compared with controls, but not in MCI subjects. Our results suggest an early dysregulation of INS and INSR in AD pathogenesis and pave the way to a possible utility of these transcripts as peripheral biomarkers.
Keywords: Aged; Alzheimer Disease; Antigens, CD; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Female; Gene Expression Profiling; Humans; Insulin; Male; Middle Aged; Receptor, Insulin

Progression of Alzheimer's Disease: A Longitudinal Study in Norwegian Memory Clinics. - Eldholm, Rannveig Sakshaug; Barca, Maria Lage; Persson, Karin; Knapskog, Anne-Brita; Kersten, Hege; Engedal, Knut; Selbæk, Geir; Brækhus, Anne; Skovlund, Eva; Saltvedt, Ingvild (J Alzheimers Dis, 2018)
BACKGROUND: The course of Alzheimer's disease (AD) varies considerably between individuals. There is limited evidence on factors important for disease progression. OBJECTIVE: The primary aim was to study the progression of AD, as measured by the Clinical Dementia Rating Scale Sum of Boxes (CDR-SB). Secondary aims were to investigate whether baseline characteristics are important for differences in progression, and to examine the correlation between progression assessed using three different instruments: CDR-SB (0-18), the cognitive test Mini-Mental State Examination (MMSE, 0-30), and the functional measure Instrumental Activities of Daily Living (IADL, 0-1). METHODS: The Progression of AD and Resource use (PADR) study is a longitudinal observational study in three Norwegian memory clinics. RESULTS: In total, 282 AD patients (mean age 73.3 years, 54% female) were followed for mean 24 (16-37) months. The mean annual increase in CDR-SB was 1.6 (SD 1.8), the mean decrease in MMSE score 1.9 (SD 2.6), and the mean decrease in IADL score 0.13 (SD 0.14). Of the 282 patients, 132 (46.8%) progressed slowly, with less than 1 point yearly increase in CDR-SB. Cognitive test results at baseline predicted progression rate, and together with age, ApoE, history of hypertension, and drug use could explain 17% of the variance in progression rate. The strongest correlation of change was found between CDR-SB and IADL scores, the weakest between MMSE and IADL scores. CONCLUSION: Progression rate varied considerably among AD patients; about half of the patients progressed slowly. Cognitive test results at baseline were predictors of progression rate.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Disease Progression; Female; Humans; Linear Models; Longitudinal Studies; Male; Memory; Neuropsychological Tests; Norway

Progression of Alzheimer's Disease-Related Pathology and Cell Counts in a Patient with Idiopathic Normal Pressure Hydrocephalus. - Libard, Sylwia; Laurell, Katarina; Cesarini, Kristina Giuliana; Alafuzoff, Irina (J Alzheimers Dis, 2018)
We had an opportunity to assess the change observed in the brain regarding Alzheimer's disease (AD)-related alterations, cell count, and inflammation that took place during a period of 21 months in a subject with a definite diagnosis of AD and idiopathic Normal Pressure Hydrocephalus (iNPH). Four neuronal markers, i.e., synaptophysin, microtubule associated protein 2, non-phosphorylated neurofilament H (SMI32), and embryonic lethal abnormal visual system proteins 3/4 HuC/HuD (HuC/HuD); three microglial markers CD68, Human Leucocytic Antigen DR, ionized calcium-binding adaptor molecule 1, glial fibrillary acidic protein (GFAP); and AD-related markers, hyperphosphorylated τ (HPτ) and amyloid-β (Aβ, Aβ40, Aβ42) were assessed. Morphometrically assessed immunoreactivity of all neuronal and all microglial markers and Aβ42 decreased parallel with an increase in the HPτ in the frontal cortex. The expression of GFAP was stable with time. The first sample was obtained during the therapeutic shunting procedure for iNPH, and the second sample was obtained postmortem. Negligible reactive changes were observed surrounding the shunt channel. In conclusion, in the late stage of AD with time, a neuronal loss, increase in the HPτ, and decrease in Aβ42 and microglia was observed, whereas the expression of GFAP was rather stable. The observations described here suggest that when a brain biopsy has been obtained from an adult subject with iNPH, the assessment of postmortem brain is of major significance.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Biopsy; Brain; Cell Count; Disease Progression; Female; Glial Fibrillary Acidic Protein; Humans; Hydrocephalus, Normal Pressure; Microglia; tau Proteins

The Progression of Neuropsychiatric Symptoms in Alzheimer's Disease During a Five-Year Follow-Up: Kuopio ALSOVA Study. - Hallikainen, Ilona; Hongisto, Kristiina; Välimäki, Tarja; Hänninen, Tuomo; Martikainen, Janne; Koivisto, Anne M (J Alzheimers Dis, 2018)
BACKGROUND: An improved understanding of the role of neuropsychiatric symptoms (NPS) in the course of Alzheimer's disease (AD) has recently emerged. NPS lead to hospitalization and caregiver stress, but are more variable during the course of the disease than other symptoms. Knowledge about the role of specific NPS in disease progression and prognosis is especially limited. OBJECTIVES: To examine the relationship between specific NPS and AD severity during a 5-year follow-up period, and to determine which baseline NPS predict AD progression. METHODS: 236 persons with very mild (CDR 0.5) or mild (CDR 1) AD at baseline and their caregivers were followed up for five years as part of the ALSOVA study. The Neuropsychiatric Inventory was used to assess NPS, and AD severity progression was measured with the Clinical Dementia Rating Sum of Boxes. Data was analyzed with Generalized Estimated Equations and Linear Mixed Models. RESULTS: The baseline NPS that best predicted AD progression were delusions, agitation, and aberrant motor behavior, while AD severity during follow-up was associated with hallucinations, delusions, agitation, apathy, aberrant motor behavior, and sleep and appetite disturbances. CONCLUSIONS: Persons with mild AD presenting delusions, agitation, and aberrant motor behavior at the time of diagnosis could have a more rapidly progressing disease, and some NPS are associated with AD severity. These results highlight the importance of evaluating NPS at the time of AD diagnosis, and the need to offer additional support to persons presenting delusions, agitation and aberrant motor behavior, and their caregivers.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anxiety; Caregivers; Delusions; Disease Progression; Female; Finland; Hallucinations; Humans; Linear Models; Male; Motor Activity; Multivariate Analysis; Neuropsychological Tests; Severity of Illness Index

Putative Dementia Cases Fluctuate as a Function of Mini-Mental State Examination Cut-Off Points. - Rosa, Ilka M; Henriques, Ana G; Wiltfang, Jens; da Cruz E Silva, Odete A B (J Alzheimers Dis, 2018)
As the population ages, there is a growing need to quickly and accurately identify putative dementia cases. Many cognitive tests are available; among those commonly used are the Cognitive Dementia Rating (CDR) and the Mini-Mental Status Examination (MMSE). The aim of this work was to compare the validity and reliability of these cognitive tests in a primary care based cohort (pcb-Cohort). The MMSE and the CDR were applied to 568 volunteers in the pcb-Cohort. Distinct cut-off points for the MMSE were considered, namely MMSE 27, MMSE 24, and MMSE PT (adapted for the Portuguese population). The MMSE 27 identified the greatest number of putative dementia cases, and, as determined by the ROC curve, it was the most sensitive and specific of the MMSE cut-offs considered. Putative predictive or risk factors identified included age, literacy, depression, and diabetes mellitus (DM). DM has previously been indicated as a risk factor for dementia and Alzheimer's disease. Comparatively, the MMSE 27 cut-off has the greatest sensibility (94.9%) and specificity (66.3%) when compared to MMSE PT and MMSE 24. Upon comparing MMSE and CDR scores, the latter identified a further 146 putative dementia cases, thus permitting one to propose that in an ideal situation, both tests should be employed. This increases the likelihood of identifying putative dementia cases for subsequent follow up work, thus these cognitive tests represent important tools in patient care. Further, this is a significant study for Portuguese populations, where few of these studies have been carried out.
Keywords: Age Factors; Aged; Aged, 80 and over; Cohort Studies; Community Health Planning; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Neuropsychological Tests; ROC Curve

Rationale and Design of the Mechanistic Potential of Antihypertensives in Preclinical Alzheimer's (HEART) Trial. - Wharton, Whitney; Goldstein, Felicia C; Tansey, Malú G; Brown, Alexandra L; Tharwani, Sonum D; Verble, Danielle D; Cintron, Amarallys; Kehoe, Patrick G (J Alzheimers Dis, 2018)
Research indicates that certain antihypertensive medications alter Alzheimer's disease (AD) biomarkers in Caucasians. The renin angiotensin system (RAS) regulates blood pressure (BP) in the body and the brain and may directly influence AD biomarkers, including amyloid-β (Aβ) neuropathology, cerebral blood flow (CBF), and inflammatory markers. This hypothesis is supported by studies, including ours, showing that antihypertensives targeting the RAS reduce the risk and slow the progression of AD in Caucasians. While mounting evidence supports a protective role of RAS medications in Caucasians, this mechanism has not been explored in African Americans. To assess the mechanism by which RAS medications modify the brain RAS, cerebrospinal fluid (CSF) Aβ, CBF, and inflammatory markers in African Americans, we are conducting an eight month, Phase Ib randomized, placebo controlled trial, enrolling 60 middle-aged (45-70 years), non-demented individuals, at risk for AD by virtue of a parental history. Participants include normotensive and treated hypertensives that have never been exposed to a RAS medication. Participants are randomized (1 : 1:1) by gender and BP medication use (yes/no) to one of three groups: placebo, or 20 mg, or 40 mg telmisartan (Micardis), to determine the dose required to penetrate the CNS. Our overarching hypothesis is that, compared to placebo, both doses of telmisartan will penetrate the CNS and produce salutary, dose dependent effects on the brain RAS as well as CSF Aβ, CBF, and CSF inflammatory markers in African Americans, over eight months. This manuscript describes the trial rationale and design.
Keywords: African Americans; Aged; Alzheimer Disease; Amyloid beta-Peptides; Antihypertensive Agents; Biomarkers; Blood Pressure; Brain; Clinical Trials, Phase I as Topic; Female; Georgia; Humans; Linear Models; Male; Middle Aged; Randomized Controlled Trials as Topic; Renin-Angiotensin System; Telmisartan

The Rationale and Design of the Reducing Pathology in Alzheimer's Disease through Angiotensin TaRgeting (RADAR) Trial. - Kehoe, Patrick G; Blair, Peter S; Howden, Beth; Thomas, David L; Malone, Ian B; Horwood, Jeremy; Clement, Clare; Selman, Lucy E; Baber, Hannah; Lane, Athene; Coulthard, Elizabeth; Passmore, Anthony Peter; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Anti-hypertensives that modify the renin angiotensin system may reduce Alzheimer's disease (AD) pathology and reduce the rate of disease progression. OBJECTIVE: To conduct a phase II, two arm, double-blind, placebo-controlled, randomized trial of losartan to test the efficacy of Reducing pathology in Alzheimer's Disease through Angiotensin TaRgeting (RADAR). METHODS: Men and women aged at least 55 years with mild-to-moderate AD will be randomly allocated 100 mg encapsulated generic losartan or placebo once daily for 12 months after successful completion of a 2-week open-label phase and 2-week placebo washout to establish drug tolerability. 228 participants will provide at least 182 subjects with final assessments to provide 84% power to detect a 25% difference in atrophy rate (therapeutic benefit) change over 12 months at an alpha level of 0.05. We will use intention-to-treat analysis, estimating between-group differences in outcomes derived from appropriate (linear or logistic) multivariable regression models adjusting for minimization variables. RESULTS: The primary outcome will be rate of whole brain atrophy as a surrogate measure of disease progression. Secondary outcomes will include changes to 1) white matter hyperintensity volume and cerebral blood flow; 2) performance on a standard series of assessments of memory, cognitive function, activities of daily living, and quality of life. Major assessments (for all outcomes) and relevant safety monitoring of blood pressure and bloods will be at baseline and 12 months. Additional cognitive assessment will also be conducted at 6 months along with safety blood pressure and blood monitoring. Monitoring of blood pressure, bloods, and self-reported side effects will occur during the open-label phase and during the majority of the post-randomization dispensing visits. CONCLUSION: This study will identify whether losartan is efficacious in the treatment of AD and whether definitive Phase III trials are warranted.
Keywords: Activities of Daily Living; Alzheimer Disease; Antihypertensive Agents; Atrophy; Blood Pressure Monitors; Brain; Clinical Trials, Phase II as Topic; Disease Progression; Double-Blind Method; Female; Humans; Losartan; Magnetic Resonance Imaging; Male; Multivariate Analysis; Quality of Life; Randomized Controlled Trials as Topic; Regression Analysis; Renin-Angiotensin System

Real World Recruiting of Older Subjects with Mild Cognitive Impairment for Exercise Trials: Community Readiness is Pivotal. - Sanders, Marit L; Stuckenschneider, Tim; Devenney, Kate E; Lawlor, Brian; Schneider, Stefan; Olde Rikkert, Marcel G M (J Alzheimers Dis, 2018)
Prevention trials in subjects with mild cognitive impairment (MCI), especially lifestyle interventions, can be difficult to carry out, particularly the recruitment and retention of subjects. We experienced these challenges in our multi-site one-year exercise trial in MCI, NeuroExercise. Trial recruitment rates differed significantly across sites; the non-medical sport university site, providing free access to a range of group exercise in a sports environment, proved far more successful than memory clinics linked to hospitals. This suggests that non-medical settings and a non-medical research community facilitating physical activities may be important factors in recruitment of subjects with MCI for large prevention trials.
Keywords: Aged; Cognitive Dysfunction; Europe; Exercise; Female; Humans; Life Style; Male; Middle Aged; Patient Selection

Reduced Gray Matter Volume of the Thalamus and Hippocampal Region in Elderly Healthy Adults with no Impact of APOE ɛ4: A Longitudinal Voxel-Based Morphometry Study. - Squarzoni, Paula; Duran, Fabio Luis Souza; Busatto, Geraldo F; Alves, Tania Correa Toledo de Ferraz (J Alzheimers Dis, 2018)
BACKGROUND: Many cross-sectional voxel-based morphometry (VBM) investigations have shown significant inverse correlations between chronological age and gray matter (GM) volume in several brain regions in healthy humans. However, few VBM studies have documented GM decrements in the healthy elderly with repeated MRI measurements obtained in the same subjects. Also, the extent to which the APOE ɛ4 allele influences longitudinal findings of GM reduction in the healthy elderly is unclear. OBJECTIVE: Verify whether regional GM changes are associated with significant decrements in cognitive performance taking in account the presence of the APOE ɛ4 allele. METHODS: Using structural MRI datasets acquired in 55 cognitively intact elderly subjects at two time-points separated by approximately three years, we searched for voxels showing significant GM reductions taking into account differences in APOE genotype. RESULTS: We found global GM reductions as well as regional GM decrements in the right thalamus and left parahippocampal gyrus (p < 0.05, family-wise error corrected for multiple comparisons over the whole brain). These findings were not affected by APOE ɛ4. CONCLUSIONS: Irrespective of APOE ɛ4, longitudinal VBM analyses show that the hippocampal region and thalamus are critical sites where GM shrinkage is greater than the degree of global volume reduction in healthy elderly subjects.
Keywords: Aged; Aging; Apolipoprotein E4; Atrophy; Cross-Sectional Studies; Female; Gray Matter; Healthy Volunteers; Hippocampus; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Organ Size; Thalamus

Relationships Between Lower Olfaction and Brain White Matter Lesions in Elderly Subjects with Mild Cognitive Impairment. - Heinrich, Juliette; Vidal, Jean-Sébastien; Simon, Axelle; Rigaud, Anne-Sophie; Hanon, Olivier; Epelbaum, Jacques; Viollet, Cécile; Duron, Emmanuelle (J Alzheimers Dis, 2018)
BACKGROUND: Olfactory impairment is reported in mild cognitive impairment (MCI) and Alzheimer's disease (AD) and is associated with hippocampal atrophy. In elderly people, dementia with AD neuropathology and white matter lesions (WML) is common. In this context, olfactory impairment could also depend on the presence of WML. OBJECTIVE: To assess the cross-sectional relationship between olfaction and WML in elderly subjects with MCI. METHODS: Consecutive subjects, >65 years old, diagnosed as MCI after a comprehensive neuropsychological assessment in an expert memory center, with a brain MRI performed within a year and without major depressive state, were included. Olfaction was assessed by the Brief Smell Identification Test (BSIT). Two trained neuroradiologists, blind to cognitive and olfaction status, visually assessed hippocampal atrophy according to Scheltens' scale and WML according to Fazekas criteria. RESULTS: Seventy-five MCI subjects (mean age (SD) = 77.1 (6.2) years, 74.7% of women) were included. After adjustment for age and sex, factors associated with low BSIT scores were older age (p = 0.007), lower BMI (p = 0.08), lower MMSE score (p = 0.05), lower FCRST (p = 0.008), hippocampal atrophy (p = 0.04), periventricular WML (p = 0.007), and deep WML burden (p = 0.005). In multivariate analysis, severe deep WML (OR (95% CI) = 6.29 (1.4-35.13), p = 0.02) remained associated with low BSIT score independently from hippocampal atrophy. CONCLUSION: In elderly MCI subjects, low olfactory performances are associated with WML, whose progression may be slowed by vascular treatments. A longitudinal study to evaluate whether the progression of WML, hippocampal atrophy and low olfactory function, can predict accurately conversion from MCI to dementia is ongoing.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Multivariate Analysis; Neuropsychological Tests; Olfaction Disorders; Severity of Illness Index; White Matter

The Role of Verb Fluency in the Detection of Early Cognitive Impairment in Alzheimer's Disease. - Alegret, Montserrat; Peretó, Mar; Pérez, Alba; Valero, Sergi; Espinosa, Ana; Ortega, Gemma; Hernandez, Isabel; Mauleón, Ana; Rosende-Roca, Maitee; Vargas, Liliana; Rodríguez-Gómez, Octavio; Abdelnour, Carla; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Verb fluency (VF) is the less commonly used fluency test, despite several studies suggesting its potential as a neuropsychological assessment tool. OBJECTIVE: To investigate the presence of VF deficits in mild cognitive impairment (MCI) and mild Alzheimer's disease (AD) dementia; to assess the usefulness of VF in the detection of cognitively healthy (CH) people who will convert to MCI, and from MCI to dementia; and to establish the VF cut-offs useful in the cognitive assessment of Spanish population. METHODS: 568 CH, 885 MCI, and 367 mild AD dementia individuals were administered the VF test and a complete neuropsychological battery. Longitudinal analyses were performed in 231 CH and 667 MCI subjects to search for VF predictors of diagnosis conversion. RESULTS: A worsening on VF performance from CH, MCI to AD dementia groups was found. Lower performances on VF were significantly related to conversion from CH to MCI/MCI to dementia. When the effect of time to conversion was analyzed, a significant effect of VF was found on the faster conversion from CH to MCI, but not from MCI to dementia. Moreover, VF cut-off scores and sensitivity/specificity values were calculated for 6 conditions (3 age ranges by 2 educational levels). CONCLUSION: The VF test may be a useful tool for the differential diagnosis of cognitive failure in the elderly. Since VF deficits seem to take place in early stages of the disease, it is a suitable neuropsychological tool for the detection not only of CH people who will convert to MCI, but also from MCI to dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognitive Dysfunction; Cross-Sectional Studies; Early Diagnosis; Executive Function; Female; Humans; Language Tests; Logistic Models; Longitudinal Studies; Male; Middle Aged; Proportional Hazards Models; Sensitivity and Specificity; Spain

Sally-Anne Test in Patients with Alzheimer's Disease Dementia. - Takenoshita, Shintaro; Terada, Seishi; Yokota, Osamu; Kutoku, Yumiko; Wakutani, Yosuke; Nakashima, Makoto; Maki, Yohko; Hattori, Hideyuki; Yamada, Norihito (J Alzheimers Dis, 2018)
Social cognition has recently been recognized as one of the essential cognitive domains. Some reports suggested that patients with Alzheimer's disease dementia (ADD) presented significant theory of mind deficits even in the mild condition. However, most previous studies included only small numbers of patients with ADD. The present study administered the first-order false belief (Sally-Anne) test to 116 consecutive patients with ADD from the outpatient units of the Memory Clinic and compared the characteristics of the two groups with correct and incorrect answers on the test. Then various clinical characteristics were evaluated. Only 37.1% of patients with ADD correctly answered the Sally-Anne test with the right explanation. Comparison between the two groups of correct and incorrect answers revealed a significant association between the frontal assessment battery score and the result of the Sally-Anne test in the multiple logistic regression analyses. Thus, patients with ADD presented a significant deficit in social cognition even in the mild condition. Frontal dysfunction was thought to be related to the deficits in mild ADD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Disease Progression; Female; Humans; Logistic Models; Male; Neuropsychological Tests; Social Behavior Disorders; Theory of Mind

Serum C-Peptide, Visfatin, Resistin, and Ghrelin are Altered in Sporadic and GRN-Associated Frontotemporal Lobar Degeneration. - Zanardini, Roberta; Benussi, Luisa; Fostinelli, Silvia; Saraceno, Claudia; Ciani, Miriam; Borroni, Barbara; Padovani, Alessandro; Binetti, Giuliano; Ghidoni, Roberta (J Alzheimers Dis, 2018)
Frontotemporal lobar degeneration (FTLD) is a group of complex neurodegenerative disease characterized by progressive deterioration of the frontal and anterior temporal lobes of the brain resulting in different heterogeneous conditions, mainly characterized by personality changes, behavioral disturbances, such as binge eating, and deficits in language and executive functions. Null mutations in progranulin gene (GRN) are one of the most frequent genetic determinants in familial frontotemporal dementia. Recently, progranulin was recognized as an adipokine involved in diet-induced obesity and insulin resistance revealing its metabolic function. Increasing evidence suggests that neurodegenerative dementias are associated with a higher prevalence of metabolic changes than in the general population. According to these findings, the aim of this study is to investigate putative alterations in markers linked to metabolic functions (i.e., C-peptide, ghrelin, glucose-dependent insulinotropic polypeptide, glucagon-like peptide-1, glucagon, insulin, resistin, and three adipokines as visfatin, leptin, and plasminogen activator inhibitor-1 total) in sporadic and GRN-related FTLD. We found that 1) C-peptide is increased in sporadic and GRN-mutated FTLD patients; in addition, we demonstrated an anticipation of the disease in patients with the highest C-peptide concentrations; 2) visfatin is slightly reduced in the whole FTLD group; 3) resistin, an adipokine involved in inflammatory-related diseases, is specifically increased in FTLD due to GRN null mutations; 4) ghrelin concentration is specifically increased in pre-symptomatic subjects and FTLD patients with GRN mutations. These findings support the hypothesis that alterations in metabolic pattern are involved in FTLD progression highlighting novel putative targets for the development of preventive and personalized therapies.
Keywords: Aged; Biomarkers; C-Peptide; Female; Frontotemporal Lobar Degeneration; Ghrelin; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Mutation; Nicotinamide Phosphoribosyltransferase; Progranulins; Resistin

Serum Non-Ceruloplasmin Non-Albumin Copper Elevation in Mild Cognitive Impairment and Dementia due to Alzheimer's Disease: A Case Control Study. - Rozzini, Luca; Lanfranchi, Francesco; Pilotto, Andrea; Catalani, Simona; Gilberti, Maria Enrica; Paganelli, Matteo; Apostoli, Pietro; Padovani, Alessandro (J Alzheimers Dis, 2018)
Several studies showed high serum copper levels in Alzheimer's disease (AD). The present study applied a newly developed method to detect serum copper free from proteins (free-Cu). Forty-four patients affected by dementia due to AD, thirty-six patients affected by mild cognitive impairment (MCI) due to AD, and twenty-eight healthy controls underwent clinical, cognitive, and MRI assessment. The new method showed higher free-Cu concentrations in MCI and dementia due to AD compared to controls (p < 0.0001). No correlation between copper levels, cognitive or MRI measures were found.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognitive Dysfunction; Copper; Female; Humans; Magnetic Resonance Imaging; Male; Psychiatric Status Rating Scales

Sex Influences the Accuracy of Subjective Memory Complaint Reporting in Older Adults. - Sundermann, Erin E; Edmonds, Emily C; Delano-Wood, Lisa; Galasko, Douglas R; Salmon, David P; Rubin, Leah H; Bondi, Mark W (J Alzheimers Dis, 2018)
Subjective memory complaints (SMC) are required when diagnosing amnestic mild cognitive impairment (aMCI), although their relationship with objective memory performance and Alzheimer's disease (AD) pathology remains unclear. We investigated whether the sex of the patient/participant moderates these associations. Participants were 940 normal control (NC) and aMCI participants from the Alzheimer's Disease Neuroimaging Initiative. SMC were assessed via the memory scale of the Everyday Cognition questionnaire. Discrepancy scores were calculated between self- and informant-reports and categorized into "overestimates," "comparable estimates", and "underestimates" of SMC. We conducted linear and logistic regressions to examine the interaction of sex with self- and informant-reported SMC and discrepancy group on the Rey Auditory Verbal Learning Test (RAVLT) Immediate and Delayed Recall and on PET measures of amyloid-β (Aβ) positivity. Diagnosis-stratified analyses were also conducted. Overall, there were sex by self- and informant-reported SMC interactions for Immediate and Delayed Recall. Despite a higher proportion of "overestimates" in women, greater self- and informant-reported SMC showed a stronger relationship to poorer RAVLT scores in women versus men. Diagnosis-stratified analyses revealed that results were driven by aMCI participants. Conversely, overall, greater self- and informant-reported SMC related to greater odds of Aβ positivity regardless of sex. In diagnosis-stratified analyses, only informant-reported SMC related to Aβ positivity in aMCI. Relative to "comparable estimates," "underestimates" of SMC were associated with poorer RAVLT scores across sexes in the overall sample and in aMCI. The predictive utility of self-report SMC may be limited to women in aMCI. Sex differences should be considered when evaluating SMC.
Keywords: Aged; Cognitive Dysfunction; Female; Humans; Logistic Models; Male; Memory Disorders; Mental Recall; Neuropsychological Tests; Self Report; Sex Factors

Simultaneous Aerobic Exercise and Memory Training Program in Older Adults with Subjective Memory Impairments. - McEwen, Sarah C; Siddarth, Prabha; Abedelsater, Berna; Kim, Yena; Mui, Wenli; Wu, Pauline; Emerson, Natacha D; Lee, Jacob; Greenberg, Shayna; Shelton, Tiffany; Kaiser, Scott; Small, Gary W; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Several modifiable lifestyle factors have been shown to have potential beneficial effects in slowing cognitive decline. Two such factors that may affect cognitive performance and slow the progression of memory loss into dementia in older adults are cognitive training and physical activity. There are currently no effective treatments for dementia; therefore, preventative strategies to delay or prevent the onset of dementia are of critical importance. OBJECTIVE: The aim of this study was to determine the relative effectiveness of simultaneous performance of memory training and aerobic exercise to a sequential performance intervention on memory functioning in older adults. METHODS: 55 older adults (aged 60- 75) with subjective memory impairments (non-demented and non-MCI) completed the intervention that consisted of 90-minute small group classes held twice weekly. Participants were randomized to either 4-weeks of supervised strategy-based memory training done simultaneously while stationary cycling (SIM) or sequentially after the stationary cycling (SEQ). Standardized neurocognitive measures of memory, executive functioning, speed of processing, attention, and cognitive flexibility were assessed at baseline and post-intervention. RESULTS: The SIM group, but not the SEQ group, had a significant improvement on composite memory following the intervention (t(51) = 2.7, p = 0.01, effect size (ES) = 0.42) and transfer to non-trained reasoning abilities (t(51) = 6.0, ES = 0.49) and complex attention (t(51) = 3.1, p = 0.003, ES = 0.70). Conversely, the SEQ group, but not the SIM, showed significant improvement in executive functioning (t(51) = 5.0, p = 0.0001, ES = 0.96). CONCLUSION: These findings indicate that a 4-week simultaneous memory training and aerobic exercise program is sufficient to improve memory, attention, and reasoning abilities in older adults.
Keywords: Aged; Attention; California; Cognition; Executive Function; Exercise; Female; Humans; Learning; Male; Memory; Memory Disorders; Middle Aged; Treatment Outcome

SORL1 Variants in Familial Alzheimer's Disease. - Gómez-Tortosa, Estrella; Ruggiero, María; Sainz, Ma José; Villarejo-Galende, Alberto; Prieto-Jurczynska, Cristina; Venegas Pérez, Begoña; Ordás, Carlos; Agüero, Pablo; Guerrero-López, Rosa; Pérez-Pérez, Julián (J Alzheimers Dis, 2018)
The SORL1 gene encodes a protein involved in the amyloidogenic process, and its variants have been associated with Alzheimer's disease (AD) physiopathology. We screened for SORL1 variants in 124 familial (44 early- and 80 late-onset) dementia of Alzheimer type (DAT) cases. Nine potentially pathogenic changes (three not previously reported and six rare variants) were found in nine probands (7%). After screening the control population and siblings (presence in at least 1/200 controls and/or absence of segregation pattern), a causal relationship with the disease was considered unlikely in six variants and uncertain in one. The change Trp848Ter and a splice-site variant remained likely correlated with the disease. SORL1 mutations are present in 7% of our familial DAT cohort, though in most cases cannot be considered the direct cause of the disease.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; LDL-Receptor Related Proteins; Male; Membrane Transport Proteins; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Siblings; Spain

SPARCL1 Accelerates Symptom Onset in Alzheimer's Disease and Influences Brain Structure and Function During Aging. - Seddighi, Sahba; Varma, Vijay R; An, Yang; Varma, Sudhir; Beason-Held, Lori L; Tanaka, Toshiko; Kitner-Triolo, Melissa H; Kraut, Michael A; Davatzikos, Christos; Thambisetty, Madhav (J Alzheimers Dis, 2018)
We recently reported that alpha-2 macroglobulin (A2M) is a biomarker of neuronal injury in Alzheimer's disease (AD) and identified a network of nine genes co-expressed with A2M in the brain. This network includes the gene encoding SPARCL1, a protein implicated in synaptic maintenance. Here, we examine whether SPARCL1 is associated with longitudinal changes in brain structure and function in older individuals at risk for AD in the Baltimore Longitudinal Study of Aging. Using data from the Gene-Tissue Expression Project, we first identified two single nucleotide polymorphisms (SNPs), rs9998212 and rs7695558, associated with lower brain SPARCL1 gene expression. We then analyzed longitudinal trajectories of cognitive performance in 591 participants who remained cognitively normal (average follow-up interval: 11.8 years) and 129 subjects who eventually developed MCI or AD (average follow-up interval: 9.4 years). Cognitively normal minor allele carriers of rs7695558 who developed incident AD showed accelerated memory loss prior to disease onset. Next, we compared longitudinal changes in brain volumes (MRI; n = 120 participants; follow-up = 6.4 years; 826 scans) and resting-state cerebral blood flow (rCBF; 15O-water PET; n = 81 participants; follow-up = 7.7 years; 664 scans) in cognitively normal participants. Cognitively normal minor allele carriers of rs9998212 showed accelerated atrophy in several global, lobar, and regional brain volumes. Minor allele carriers of both SNPs showed longitudinal changes in rCBF in several brain regions, including those vulnerable to AD pathology. Our findings suggest that SPARCL1 accelerates AD pathogenesis and thus link neuroinflammation with widespread changes in brain structure and function during aging.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Brain; Calcium-Binding Proteins; Cerebrovascular Circulation; Cognition Disorders; Extracellular Matrix Proteins; Female; Humans; Independent Living; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Positron-Emission Tomography

Structural Connectivity Alterations Along the Alzheimer's Disease Continuum: Reproducibility Across Two Independent Samples and Correlation with Cerebrospinal Fluid Amyloid-β and Tau. - Tucholka, Alan; Grau-Rivera, Oriol; Falcon, Carles; Rami, Lorena; Sánchez-Valle, Raquel; Lladó, Albert; Gispert, Juan Domingo; Molinuevo, José Luis (J Alzheimers Dis, 2018)
BACKGROUND: Gray matter changes associated with the progression of Alzheimer's disease (AD) have been thoroughly studied. However, alterations in white matter tracts have received less attention, particularly during early or preclinical stages of the disease. OBJECTIVE: To identify the structural connectivity changes across the AD continuum. METHODS: We performed probabilistic tractography in a total of 183 subjects on two independent samples that include control (n = 68) and preclinical AD individuals (n = 28), patients diagnosed with mild cognitive impairment (MCI) due to AD (n = 44), and AD patients (n = 43). We compared the connectivity between groups, and with CSF Aβ42 and tau biomarkers. RESULTS: We observed disconnections in preclinical individuals, mainly located in the temporal lobe. This pattern of disconnection spread to the parietal and frontal lobes at the MCI stage and involved almost all the brain in AD. These findings were not driven by gray matter atrophy. DISCUSSION: Using tractography, we were able to identify white matter changes between subsequent disease stages and, notably, also in preclinical AD. Therefore, this method may be useful for detecting early and specific brain structural changes during preclinical AD stage.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Atrophy; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Cohort Studies; Disease Progression; Female; Gray Matter; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Reproducibility of Results; Spain; tau Proteins; White Matter

Supplemental Retinal Carotenoids Enhance Memory in Healthy Individuals with Low Levels of Macular Pigment in A Randomized, Double-Blind, Placebo-Controlled Clinical Trial. - Power, Rebecca; Coen, Robert F; Beatty, Stephen; Mulcahy, Riona; Moran, Rachel; Stack, Jim; Howard, Alan N; Nolan, John M (J Alzheimers Dis, 2018)
BACKGROUND: There is a biologically plausible rationale whereby the dietary carotenoids lutein (L), zeaxanthin (Z), and meso-zeaxanthin (MZ), which are collectively referred to as macular pigment (MP) in the central retina (macula), support the maintenance of cognition via their antioxidant and anti-inflammatory properties. OBJECTIVE: To investigate the impact of supplemental L, Z, and MZ on memory, executive function, and verbal fluency among healthy individuals with low MP levels. METHODS: In this double-blind, placebo-controlled, randomized clinical trial, subjects (n = 91; mean±SD age = 45.42±12.40; % male = 51.6) consumed a daily formulation of 10 mg L, 10 mg MZ, and 2 mg Z (n = 45) or placebo (n = 46) for 12 months. Cognitive domains assessed included verbal and visual learning, immediate and delayed memory, executive function, and verbal fluency. MP and serum carotenoid concentrations of L, Z, and MZ were also measured. RESULTS: Following 12-month supplementation, individuals in the active group exhibited statistically significant improvements in memory when compared to the placebo group (paired associated learning [PAL] memory score [rANOVA, p = 0.009]; PAL errors [rANOVA, p = 0.017]). Furthermore, the observed reduction in the number of errors made in the PAL task among those in the intervention group was positively and significantly related to observed increases in MP volume (p = 0.005) and observed increases in serum concentrations of L (p = 0.009). CONCLUSION: This randomized, double-blind, placebo-controlled clinical trial demonstrates a memory-enhancing effect of daily supplementation with L, Z, and MZ in healthy subjects with low MP at baseline. The implications of these findings for intellectual performance throughout life, and for risk of cognitive decline in later life, warrant further study.
Keywords: Adult; Cognition; Dietary Supplements; Double-Blind Method; Executive Function; Female; Healthy Volunteers; Humans; Lutein; Macular Pigment; Male; Memory, Episodic; Middle Aged; Retina; Vision Tests; Zeaxanthins

Tau and Amyloid Positron Emission Tomography Imaging Predict Driving Performance Among Older Adults with and without Preclinical Alzheimer's Disease. - Roe, Catherine M; Babulal, Ganesh M; Mishra, Shruti; Gordon, Brian A; Stout, Sarah H; Ott, Brian R; Carr, David B; Ances, Beau M; Morris, John C; Benzinger, Tammie L S (J Alzheimers Dis, 2018)
Abnormal levels of Alzheimer's disease (AD) biomarkers, measured by positron emission tomography imaging using amyloid-based radiotracers and cerebrospinal fluid, are associated with impaired driving performance in older adults. We examined whether preclinical AD staging, defined using amyloid imaging and tau imaging using the radiotracer T807 (AKA flortaucipir or AV-1451), was associated with receiving a marginal/fail rating on a standardized road test (n = 42). Participants at Stage 2 (positive amyloid and tau scans) of preclinical AD were more likely to receive a marginal/fail rating compared to participants at Stage 0 or 1. Stage 2 preclinical AD may manifest in worse driving performance.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Automobile Driving; Biomarkers; Carbolines; Female; Humans; Logistic Models; Male; Neuroimaging; Positron-Emission Tomography; tau Proteins

Testamentary Capacity Assessment Tool (TCAT): A Brief Instrument for Patients with Dementia. - Papageorgiou, Sokratis G; Voskou, Panagiota; Economou, Alexandra; Beratis, Ion; Douzenis, Athanasios (J Alzheimers Dis, 2018)
BACKGROUND: In current practice, it is common for the medical practitioner to assess a person's testamentary capacity (TC) and give evidence to the Courts about a potential will contest. TC is an advanced cognitive activity that is both situation- and task-specific. OBJECTIVE: The aim of the present study was the development of a brief, specialized instrument for TC assessment in patients with dementia. METHOD: We developed a short tool consisting of four subtests, assessing the person's core functions which are required for TC: memory (orientation, autobiographical memory and realistic perception of beneficiaries), absence of serious psychopathology, knowledge of financial parameters (value of assets, everyday life products, bills), and intention (vignettes, theory of mind). For its validation, we examined 64 outpatients from the Cognitive Disorders/Dementia Unit, 2nd Department of Behavioral Neurology, University of Athens. The decision of the expert served as the gold standard for the evaluation of TC. RESULTS: Of the 64 participants, 39 were judged by the expert as capable of TC and the remaining 25 as incapable. For the total scale (maximum score of 48), the best combination of sensitivity (82.6%) and specificity (100%) was obtained for a cut-off score of 32/33. Cronbach's alpha showed high levels of internal reliability for the scale (α= 0.86) and the point-biserial correlation coefficients showed high levels of criterion-related validity (rbp = 0.797, p < 0.001). CONCLUSION: The new instrument appears to be a reliable screening tool for the evaluation of TC in dementia, which can be used by both the expert and the non-expert. Further research is needed to confirm these promising findings.
Keywords: Adult; Aged; Cognition Disorders; Dementia; Female; Humans; Male; Memory; Mental Competency; Middle Aged; Neuropsychological Tests; Reproducibility of Results; Sensitivity and Specificity; Wills

Treatment of Atrial Fibrillation in Patients with Dementia: A Cohort Study from the Swedish Dementia Registry. - Subic, Ana; Cermakova, Pavla; Religa, Dorota; Han, Shuang; von Euler, Mia; Kåreholt, Ingemar; Johnell, Kristina; Fastbom, Johan; Bognandi, Liselia; Winblad, Bengt; Kramberger, Milica G; Eriksdotter, Maria; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Patients with dementia might have higher risk for hemorrhagic complications with anticoagulant therapy prescribed for atrial fibrillation (AF). OBJECTIVE: This study assesses the risks and benefits of warfarin, antiplatelets, and no treatment in patients with dementia and AF. METHODS: Of 49,792 patients registered in the Swedish Dementia Registry 2007-2014, 8,096 (16%) had a previous diagnosis of AF. Cox proportional hazards models were used to calculate the risk for ischemic stroke (IS), nontraumatic intracranial hemorrhage, any-cause hemorrhage, and death. RESULTS: Out of the 8,096 dementia patients with AF, 2,143 (26%) received warfarin treatment, 2,975 (37%) antiplatelet treatment, and 2,978 (37%) had no antithrombotic treatment at the time of dementia diagnosis. Patients on warfarin had fewer IS than those without treatment (5.2% versus 8.7%; p < 0.001) with no differences compared to antiplatelets. In adjusted analyses, warfarin was associated with a lower risk for IS (HR 0.76, CI 0.59-0.98), while antiplatelets were associated with increased risk (HR 1.25, CI 1.01-1.54) compared to no treatment. For any-cause hemorrhage, there was a higher risk with warfarin (HR 1.28, CI 1.03-1.59) compared to antiplatelets. Warfarin and antiplatelets were associated with a lower risk for death compared to no treatment. CONCLUSIONS: Warfarin treatment in Swedish patients with dementia is associated with lower risk of IS and mortality, and a small increase in any-cause hemorrhage. This study supports the use of warfarin in appropriate cases in patients with dementia. The low percentage of patients on warfarin treatment indicates that further gains in stroke prevention are possible.
Keywords: Aged; Aged, 80 and over; Anticoagulants; Atrial Fibrillation; Dementia; Female; Hemorrhage; Humans; Longitudinal Studies; Male; Registries; Risk Factors; Stroke; Survival Analysis; Sweden; Warfarin

The Uniform Data Set, Czech Version: Normative Data in Older Adults from an International Perspective. - Nikolai, Tomas; Stepankova, Hana; Kopecek, Miloslav; Sulc, Zdenek; Vyhnálek, Martin; Bezdicek, Ondrej (J Alzheimers Dis, 2018)
BACKGROUND: Outside of the United States, international perspectives on normative data for neuropsychological test performance, within diverse populations, have been scarce. The neuropsychological test battery from the Uniform Data Set (UDS) of the Alzheimer's Disease Centers (ADC) program of the United States National Institute on Aging (NIA) is one of the most sensitive batteries for the evaluation of both normal cognitive aging and pathological cognitive decline. OBJECTIVE: This study aimed to determine the feasibility of the Czech Neuropsychological Test Battery from the Uniform Data Set (UDS-Cz 2.0), while also evaluating the results obtained from an international perspective. METHODS: This paper describes data from 520 cognitively normal participants. Regression analyses were used to describe the influence of demographic variables on UDS-Cz test performance. RESULTS: Cognitive performance on all measures declined with age, with patient education level serving as a protective factor. Therefore, the present study provides normative data for the UDS-Cz, adjusted for the demographic variables of age and education. CONCLUSION: The present study determines the psychometric properties of the UDS-Cz and establishes normative values in the aging Czech population, which can be used in clinical settings.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Czech Republic; Female; Humans; Internationality; Male; Middle Aged; National Institute on Aging (U.S.); Neuropsychological Tests; Psychometrics; Reference Values; Regression Analysis; United States

Validation of the Delayed Matching-to-Sample Task 48 (DMS48) in Elderly Chinese. - Feng, Xueyan; Zhou, Aihong; Liu, Zhixin; Li, Fangyu; Wei, Cuibai; Zhang, Guili; Jia, Jianping (J Alzheimers Dis, 2018)
BACKGROUND: Delayed Matching-to-Sample Task 48 (DMS48), a brief tool measuring visual recognition memory, is valid to identify the early stage of Alzheimer's disease (AD) in Caucasians. However, little data is available in Chinese. OBJECTIVE: To develop norms and optimal cutoff points for the DMS48 in Chinese elders. METHODS: A cross-sectional study was conducted in seven memory clinics from five cities across China. DMS48 was applied to 369 Chinese aged 50 or older (138 cognitively normal [CN], 112 mild cognitive impairment due to AD (MCI-A), and 119 mild AD dementia). The demographic factors which influence DMS48 scores were investigated and the norms were established considering those factors. Receiver operating characteristic (ROC) analysis was used to determine the optimal cutoff points. RESULTS: Age was shown to influence DMS48 scores (r = -0.36, p < 0.05), and we presented the age-stratified normative data for the DMS48. The optimal cutoff point is 42/43 for identifying cognitive impairment (MCI-A and AD dementia) against CN (sensitivity 97.80% and specificity 89.13%) and MCI-A against CN (sensitivity 86.60% and specificity 94.20%). A cutoff of 39/40 obtained good sensitivity (100.00%) and specificity (94.90%) in discriminating AD dementia from CN. The age-stratified optimal cutoff points for identifying MCI-A were 43/44 for individuals aged 50 to 59 years old, 42/43 for 60 to 69 years old, 41/42 for 70 to 79 years old, and 40/41 for 80 or older, respectively (sensitivity 84.80% and specificity 95.70%). CONCLUSION: This study proved that DMS48 is of good validation in screening MCI-A in elderly Chinese.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; China; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Linear Models; Male; Memory Disorders; Middle Aged; Neuropsychological Tests; ROC Curve; Sensitivity and Specificity; Severity of Illness Index

VEGFR1 and VEGFR2 in Alzheimer's Disease. - Harris, Rachel; Miners, James Scott; Allen, Shelley; Love, Seth (J Alzheimers Dis, 2018)
Vascular endothelial growth factor (VEGF) is a potent angiogenic factor. Despite upregulation of VEGF in the brain in Alzheimer's disease (AD), probably in response to amyloid-β, vasoconstriction, and tissue hypoxia, there is no consequent increase in microvessel density. VEGF binds to and activates VEGF receptor 2 (VEGFR2), but also binds to VEGF receptor 1 (VEGFR1), which exists in less-active membrane-bound and inactive soluble (sVEGFR1) forms and inhibits pro-angiogenic signaling. We have investigated whether altered expression of VEGF receptors might account for the lack of angiogenic response to VEGF in AD. We assessed the cellular distribution and protein level of VEGFR1 and VEGFR2 in parietal cortex from 50 AD and 36 age-matched control brains, and related the findings to measurements of VEGF and von Willebrand factor level (a marker of microvessel density) in the same tissue samples. VEGFR2 was expressed by neurons, astrocytes and endothelial cells. VEGFR1 was expressed predominantly neuronally and was significantly reduced in AD (p = 0.02). Western blot analysis on a subset of brains showed reduction in VEGFR1:sVEGFR1 in AD (p = 0.046). The lack of angiogenesis despite cerebral hypoperfusion in AD is not explained by altered expression of VEGFR2 or total VEGFR1; indeed, the downregulation of VEGFR1 may represent a pro-angiogenic response to the hypoperfusion. However, the relative increase in sVEGFR1 would be expected to have an anti-angiogenic effect which may be a factor in AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Case-Control Studies; Endothelial Cells; Female; Gene Expression Regulation; Humans; Male; Middle Aged; Neovascularization, Pathologic; RNA, Messenger; Signal Transduction; Vascular Endothelial Growth Factor A; Vascular Endothelial Growth Factor Receptor-1; Vascular Endothelial Growth Factor Receptor-2

Vestibular Loss Predicts Poorer Spatial Cognition in Patients with Alzheimer's Disease. - Wei, Eric X; Oh, Esther S; Harun, Aisha; Ehrenburg, Matthew; Agrawal, Yuri (J Alzheimers Dis, 2018)
The vestibular system is an important contributor to balance control, spatial orientation, and falls risk. Recent evidence has shown that Alzheimer's disease (AD) patients have a higher prevalence of vestibular impairment relative to healthy controls. We sought to evaluate whether vestibular loss is specifically associated with poor spatial cognitive skills among patients with mild cognitive impairment (MCI) and AD. We enrolled 50 patients (22 MCI and 28 AD) from an interdisciplinary Memory Clinic and measured vestibular physiologic function in all patients. Spatial cognitive function was assessed using the Money Road Map Test (MRMT) and the Trail Making Test Part B (TMT-B). General cognitive function was assessed with the Mini-Mental Status Examination (MMSE). In multivariable linear regression analyses adjusted for age, gender, education level, and MMSE, MCI and AD patients with vestibular loss made significantly more errors on the MRMT relative to patients with normal vestibular function (β= 7.3, 95% CI 2.4, 12.1 for unilateral vestibular loss and β= 6.4, 95% CI 1.9, 10.9 for bilateral vestibular loss). We further stratified AD patients into "spatially normal" and "spatially impaired" groups based on MRMT performance, and found that the prevalence of vestibular loss was significantly higher in the spatially impaired AD group relative to the spatially normal AD group. These findings support the hypothesis that vestibular loss contributes specifically to a decline in spatial cognitive ability in MCI and AD patients, independently of general cognitive decline, and may predict a "spatially impaired" subtype of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Bilateral Vestibulopathy; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Linear Models; Male; Multivariate Analysis; Neuropsychological Tests; Prospective Studies; Spatial Navigation; Vestibular Function Tests

Visit-To-Visit Blood Pressure Variability and the Risk of Dementia in Older People. - van Middelaar, Tessa; van Dalen, Jan W; van Gool, Willem A; van den Born, Bert-Jan H; van Vught, Lonneke A; Moll van Charante, Eric P; Richard, Edo (J Alzheimers Dis, 2018)
BACKGROUND: High visit-to-visit variability (VVV) in blood pressure (BP) is associated with cerebrovascular lesions on neuroimaging. OBJECTIVE: Our primary objective was to investigate whether VVV is associated with incident all-cause dementia. As a secondary objective, we studied the association of VVV with cognitive decline and cardiovascular disease (CVD). METHODS: We included community-dwelling people (age 70-78 year) from the 'Prevention of Dementia by Intensive Vascular Care' (preDIVA) trial with three to five 2-yearly BP measurements during 6-8 years follow-up. VVV was defined using coefficient of variation (CV; SD/mean×100). Cognitive decline was assessed using the Mini-Mental State Examination (MMSE). Incident CVD was defined as myocardial infarction or stroke. We used a Cox proportional hazard regression and mixed-effects model adjusted for sociodemographic factors and cardiovascular risk factors. RESULTS: In 2,305 participants (aged 74.2±2.5), mean systolic BP over all available visits was 150.1 mmHg (SD 13.6), yielding a CV of 9.0. After 6.4 years (SD 0.8) follow-up, 110 (4.8%) participants developed dementia and 140 (6.1%) CVD. Higher VVV was not associated with increased risk of dementia (hazard ratio [HR] 1.00 per point CV increase; 95% confidence interval [CI] 0.96-1.05), although the highest quartile of VVV was associated with stronger decline in MMSE (β -0.09, 95% CI -0.17 to -0.01). Higher VVV was associated with incident CVD (HR 1.07; 95% CI 1.04-1.11). CONCLUSION: In our study among older people, high VVV is not associated with incident all-cause dementia. It is associated with decline in MMSE and incident CVD.
Keywords: Aged; Antihypertensive Agents; Blood Pressure; Cardiovascular Diseases; Dementia; Female; Humans; Hypertension; Incidence; Male; Netherlands; Proportional Hazards Models; Risk Factors

White Matter Hyperintensity Predicts the Risk of Incident Cognitive Decline in Community Dwelling Elderly. - Ding, Ding; Xiong, Yunyun; Zhao, Qianhua; Guo, Qihao; Chu, Shuguang; Chu, Winnie W C; Luo, Jianfeng; Liang, Xiaoniu; Zheng, Li; Hong, Zhen; Wong, Lawrence K S; Mok, Vincent C T (J Alzheimers Dis, 2018)
BACKGROUND: Unlike western countries, data on white matter hyperintensity (WMH) in community dwelling elderly in Asian population is very limited. OBJECTIVE: To examine the relation between baseline WMH burden and the risk of incident cognitive decline in a community-based cohort with Chinese-dwelling elderly. METHODS: We prospectively evaluated the incident cognitive decline for 226 participants in the Shanghai Aging Study. Baseline WMH severity was visually rated by the age-related white matter changes (ARWMC) scale based on MRI. Cox proportional hazards regression model was used to estimate the relative risk (RR) of total ARWMC scale, global ARWMC score, presence of lacune and microbleed, for incident cognitive decline by adjusting potential confounders. RESULTS: Forty subjects were identified with incident cognitive decline (new onset 34 mild cognitive impairment and 6 dementia) during a median duration of 6 years follow-up. The incidence of cognitive decline was 3.0 (95% confidence interval [CI] 2.2-4.1) per 100 person-years. Increasing total ARWMC scale [RR1.21 (95% CI 1.06-1.39), p = 0.004)], confluent WMH [RR3.16 (95% CI 1.50-6.64), p = 0.002), and presence of lacunes [RR 2.73 (95% CI 1.21-6.15)] at baseline were independent predictors of incident cognitive decline. CONCLUSION: Our study demonstrated that confluent WMH may increase the risk of incident cognitive decline by 3 folds in community dwelling subjects. Small vessel disease may cause heavy burden of cognitive impairment in the elderly in China.
Keywords: Aged; China; Cognitive Dysfunction; Female; Humans; Independent Living; Kaplan-Meier Estimate; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; White Matter

Word and Picture Version of the Free and Cued Selective Reminding Test (FCSRT): Is There Any Difference? - Arighi, Andrea; Carandini, Tiziana; Mercurio, Matteo; Carpani, Giovanni; Pietroboni, Anna Margherita; Fumagalli, Giorgio; Ghezzi, Laura; Basilico, Paola; Calvi, Alberto; Scarioni, Marta; De Riz, Milena; Fenoglio, Chiara; et al. (J Alzheimers Dis, 2018)
The Free and Cued Selective Reminding Test (FCSRT) is the most commonly used neuropsychological test to evaluate episodic memory. Two variants of FCSRT exist, using the recall of words (FCSRT-w) or pictures (FCSRT-p). Fourteen patients with mild cognitive impairment underwent neuropsychological evaluation and brain magnetic resonance. We found differences in FCSRT-w and FCSRT-p variants scores. FCSRT-p was correlated with atrophy in areas involved in visual stimuli processing while FCSRT-w was correlated to hippocampal atrophy. Our study suggests that FCSRT-w and FCSRT-p scores are not equivalent, but a larger cohort of patients is needed to validate these results.
Keywords: Aged; Aged, 80 and over; Association Learning; Cognitive Dysfunction; Cues; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Recall; Middle Aged; Neuropsychological Tests; Photic Stimulation; Vocabulary

18F-AV-1451 PET Imaging in Three Patients with Probable Cerebral Amyloid Angiopathy. - Kim, Hee Jin; Cho, Hanna; Werring, David J; Jang, Young Kyoung; Kim, Yeo Jin; Lee, Jin San; Lee, Juyoun; Jun, Soomin; Park, Seongbeom; Ryu, Young Hoon; Choi, Jae Yong; Cho, Young Seok; et al. (J Alzheimers Dis, 2017)
Cerebrovascular deposition of amyloid-β, known as cerebral amyloid angiopathy (CAA), is associated with MRI findings of lobar hemorrhage, cerebral microbleeds, and cortical superficial siderosis. Although pathological studies suggest that tau may co-localize with vascular amyloid, this has not yet been investigated in CAA in vivo. Three patients with probable CAA underwent 11C-Pittsburgh Compound B (PiB) PET or 18F-florbetaben PET to evaluate amyloid burden, and 18F-AV-1451 PET to evaluate paired helical filament tau burden. Regions that had cerebral microbleeds or cortical superficial siderosis largely overlapped with those showing increased 18F-AV-1451. Our preliminary study raised the possibility that lobar cerebral microbleeds, and cortical superficial siderosis, which are characteristic markers of vascular amyloid, may be associated with local production of paired helical filament tau.
Keywords: Aged; Aged, 80 and over; Aniline Compounds; Brain; Carbolines; Cerebral Amyloid Angiopathy; Female; Humans; Image Processing, Computer-Assisted; Male; Positron-Emission Tomography; Thiazoles

Abnormalities of Cerebral Deep Medullary Veins on 7 Tesla MRI in Amnestic Mild Cognitive Impairment and Early Alzheimer's Disease: A Pilot Study. - Bouvy, Willem H; Kuijf, Hugo J; Zwanenburg, Jaco J M; Koek, Huiberdina L; Kappelle, L Jaap; Luijten, Peter R; Ikram, M Kamran; Biessels, Geert Jan (J Alzheimers Dis, 2017)
Cerebral small vessel disease (SVD) contributes to cognitive impairment and dementia. SVD may affect veins, but veins are difficult to detect with 1.5 and 3T MRI. We compared deep medullary veins (DMVs) visualized on 7T-MRI between patients with early Alzheimer's disease (eAD; n = 17) or amnestic MCI (aMCI; n = 12) and controls (n = 40). The number and density of DMVs was similar in patients and controls, but tortuosity was higher in eAD (Cohen's d = 0.7, 95% CI: 0.1-1.2, p = 0.02) and aMCI (Cohen's d = 0.8, 95% CI: 0.2-1.5, p = 0.01), independent of brain atrophy. Venous changes provide a new perspective on vascular involvement in dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Brain; Cerebral Small Vessel Diseases; Cognitive Dysfunction; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male

Amyloid-β Deposition and Long-Term Progression in Mild Cognitive Impairment due to Alzheimer's Disease Defined with Amyloid PET Imaging. - Hatashita, Shizuo; Wakebe, Daichi (J Alzheimers Dis, 2017)
The aim was to evaluate brain amyloid-β (Aβ) deposition in patients with mild cognitive impairment (MCI) due to Alzheimer's disease (AD) using amyloid PET imaging and clarify the relationship between the annual change in Aβ deposition and disease progression. Forty-eight MCI patients underwent neuropsychological assessment and amyloid PET imaging using [11C]-PIB over a follow-up of 5.7±1.5 years. Thirty-nine MCI patients who had an amyloid-positive scan were defined as MCI due to AD, and 9 MCI patients who had an amyloid-negative scan were included. Regions of interest were defined on co-registered MRI, and the PIB standardized uptake value ratio (SUVR) on the same regions was used over follow-up. Annual change in PIB SUVR was calculated. Patients with MCI due to AD had higher baseline PIB SUVR (1.81±0.32, n = 39, p < 0.01) and a greater annual rate of change in PIB SUVR (0.044±0.027, n = 39, p < 0.01) compared to amyloid-negative MCI patients. Twenty-eight (71.8%) progressed to AD. In patients who progressed during a short duration of 1.7±0.8 years, the annual rate of increase in PIB SUVR was 0.101±0.094 (n = 16, p < 0.05), which was greater compared to patients with long conversion or stable patients. There was a negative correlation between the annual rate of increase in PIB SUVR and duration of progression to AD among individual MCI converters (r = -0.47, n = 28, p < 0.05). The patients defined as MCI due to AD could progress to AD with a shorter period if they have a greater increased annual rate in brain Aβ deposition.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Aniline Compounds; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Positron-Emission Tomography; Thiazoles

Combined Dual-Task Gait Training and Aerobic Exercise to Improve Cognition, Mobility, and Vascular Health in Community-Dwelling Older Adults at Risk for Future Cognitive Decline1. - Gregory, Michael A; Boa Sorte Silva, Narlon C; Gill, Dawn P; McGowan, Cheri L; Liu-Ambrose, Teresa; Shoemaker, J Kevin; Hachinski, Vladimir; Holmes, Jeff; Petrella, Robert J (J Alzheimers Dis, 2017)
This 6-month experimental case series study investigated the effects of a dual-task gait training and aerobic exercise intervention on cognition, mobility, and cardiovascular health in community-dwelling older adults without dementia. Participants exercised 40 min/day, 3 days/week for 26 weeks on a Biodex GaitTrainer2 treadmill. Participants were assessed at baseline (V0), interim (V1: 12-weeks), intervention endpoint (V2: 26-weeks), and study endpoint (V3: 52-weeks). The study outcomes included: cognition [executive function (EF), processing speed, verbal fluency, and memory]; mobility: usual & dual-task gait (speed, step length, and stride time variability); and vascular health: ambulatory blood pressure, carotid arterial compliance, and intima-media thickness (cIMT). Fifty-six participants [age: 70(6) years; 61% female] were included in this study. Significant improvements following the exercise program (V2) were observed in cognition: EF (p = 0.002), processing speed (p < 0.001), verbal fluency [digit symbol coding (p < 0.001), phonemic verbal fluency (p < 0.001)], and memory [immediate recall (p < 0.001) and delayed recall (p < 0.001)]; mobility: usual & dual-task gait speed (p = 0.002 and p < 0.001, respectively) and step length (p = 0.001 and p = 0.003, respectively); and vascular health: cIMT (p = 0.002). No changes were seen in the remaining outcomes. In conclusion, 26 weeks of dual-task gait training and aerobic exercise improved performance on a number of cognitive outcomes, while increasing usual & dual-task gait speed and step length in a sample of older adults without dementia.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Blood Pressure; Blood Pressure Monitoring, Ambulatory; Carotid Intima-Media Thickness; Cognition Disorders; Exercise; Exercise Therapy; Female; Follow-Up Studies; Gait; Humans; Independent Living; Male; Middle Aged; Neuropsychological Tests

The Efficacy of Emotion Recognition Rehabilitation for People with Alzheimer's Disease. - García-Casal, J Antonio; Goñi-Imizcoz, Miguel; Perea-Bartolomé, M Victoria; Soto-Pérez, Felipe; Smith, Sarah Jane; Calvo-Simal, Sara; Franco-Martín, Manuel (J Alzheimers Dis, 2017)
BACKGROUND: The ability to recognize emotional expression is essential for social interactions, adapting to the environment, and quality of life. Emotion recognition is impaired in people with Alzheimer's disease (AD), thus rehabilitation of these skills has the potential to elicit significant benefits. OBJECTIVE: This study sought to establish whether emotion recognition capacity could be rehabilitated in people with AD. METHODS: Thirty-six participants with AD were assigned to one of three conditions: an experimental group (EG) that received 20 sessions of rehabilitation of emotion recognition and 20 sessions of cognitive stimulation therapy (CST), a control group (CG) that received 40 sessions of CST, and a treatment as usual group (TAU). RESULTS: A positive treatment effect favoring the EG was found; participants were better able to correctly identify emotions (p = 0.021), made fewer errors of commission (p = 0.002), had greater precision of processing (p = 0.021), and faster processing speed (p = 0.001). Specifically, the EG were better able to identify sadness (p = 0.016), disgust (p = 0.005), and the neutral expression (p = 0.014), with quicker processing speed for disgust (p = 0.002). These gains were maintained at one month follow-up with the exception of processing speed for surprise, which improved. CONCLUSION: Capacity to recognize facial expressions of emotions can be improved through specific rehabilitation in people with AD, and gains are still present at a one month follow up. These findings have implications for the design of rehabilitation techniques for people with AD that may lead to improved quality of life and social interactions for this population.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Therapy; Depression; Emotions; Female; Follow-Up Studies; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Outcome Assessment (Health Care); Recognition (Psychology); Single-Blind Method; Statistics, Nonparametric

Exercise Training and Functional Connectivity Changes in Mild Cognitive Impairment and Healthy Elders. - Chirles, Theresa J; Reiter, Katherine; Weiss, Lauren R; Alfini, Alfonso J; Nielson, Kristy A; Smith, J Carson (J Alzheimers Dis, 2017)
BACKGROUND: Effective interventions are needed to improve brain function in mild cognitive impairment (MCI), an early stage of Alzheimer's disease (AD). The posterior cingulate cortex (PCC)/precuneus is a hub of the default mode network (DMN) and is preferentially vulnerable to disruption of functional connectivity in MCI and AD. OBJECTIVE: We investigated whether 12 weeks of aerobic exercise could enhance functional connectivity of the PCC/precuneus in MCI and healthy elders. METHODS: Sixteen MCI and 16 healthy elders (age range = 60-88) engaged in a supervised 12-week walking exercise intervention. Functional MRI was acquired at rest; the PCC/precuneus was used as a seed for correlated brain activity maps. RESULTS: A linear mixed effects model revealed a significant interaction in the right parietal lobe: the MCI group showed increased connectivity while the healthy elders showed decreased connectivity. In addition, both groups showed increased connectivity with the left postcentral gyrus. Comparing pre to post intervention changes within each group, the MCI group showed increased connectivity in 10 regions spanning frontal, parietal, temporal and insular lobes, and the cerebellum. Healthy elders did not demonstrate any significant connectivity changes. CONCLUSION: The observed results show increased functional connectivity of the PCC/precuneus in individuals with MCI after 12 weeks of moderate intensity walking exercise training. The protective effects of exercise training on cognition may be realized through the enhancement of neural recruitment mechanisms, which may possibly increase cognitive reserve. Whether these effects of exercise training may delay further cognitive decline in patients diagnosed with MCI remains to be demonstrated.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Exercise; Exercise Test; Female; Gyrus Cinguli; Humans; Image Processing, Computer-Assisted; Linear Models; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Oxygen; Psychiatric Status Rating Scales

Family History of Alzheimer's Disease is Associated with Impaired Perceptual Discrimination of Novel Objects. - Mason, Emily J; Hussey, Erin P; Molitor, Robert J; Ko, Philip C; Donahue, Manus J; Ally, Brandon A (J Alzheimers Dis, 2017)
Early detection may be the key to developing therapies that will combat Alzheimer's disease (AD). It has been consistently demonstrated that one of the main pathologies of AD, tau, is present in the brain decades before a clinical diagnosis. Tau pathology follows a stereotypical route through the medial temporal lobe beginning in the entorhinal and perirhinal cortices. If early pathology leads to very subtle changes in behavior, it may be possible to detect these changes in subjects years before a clinical diagnosis can currently be made. We aimed to discover if cognitively normal middle-aged adults (40-60 years old) at increased risk for AD due to family history would have impaired performance on a cognitive task known to challenge the perirhinal cortex. Using an oddity detection task, we found that subjects with a family history of AD had lowered accuracy without demonstrating differences in rate of acquisition. There were no differences between subjects' medial temporal lobe volume or cortical thickness, indicating that the changes in behavior were not due to significant atrophy. These results demonstrate that subtle changes in perceptual processing are detectable years before a typical diagnosis even when there are no differences detectable in structural imaging data. Anatomically-targeted cognitive testing may be useful in identifying subjects in the earliest stages of AD.
Keywords: Adult; Alzheimer Disease; Cerebral Cortex; Discrimination (Psychology); Family Health; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Perceptual Disorders; Photic Stimulation; Recognition (Psychology); Signal Detection, Psychological

Long-Term Cognitive Decline in Dementia with Lewy Bodies in a Large Multicenter, International Cohort. - Kramberger, Milica G; Auestad, Bjørn; Garcia-Ptacek, Sara; Abdelnour, Carla; Olmo, Josep Garre; Walker, Zuzana; Lemstra, Afina W; Londos, Elisabet; Blanc, Frédéric; Bonanni, Laura; McKeith, Ian; Winblad, Bengt; et al. (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: The aim of this study was to describe the rate and clinical predictors of cognitive decline in dementia with Lewy bodies (DLB), and compare the findings with Alzheimer's disease (AD) and Parkinson's disease dementia (PDD) patients. METHODS: Longitudinal scores for the Mini-Mental State Examination (MMSE) in 1,290 patients (835 DLB, 198 PDD, and 257 AD) were available from 18 centers with up to three years longitudinal data. Linear mixed effects analyses with appropriate covariates were used to model MMSE decline over time. Several subgroup analyses were performed, defined by anti-dementia medication use, baseline MMSE score, and DLB core features. RESULTS: The mean annual decline in MMSE score was 2.1 points in DLB, compared to 1.6 in AD (p = 0.07 compared to DLB) and 1.8 in PDD (p = 0.19). Rates of decline were significantly higher in DLB compared to AD and PDD when baseline MMSE score was included as a covariate, and when only those DLB patients with an abnormal dopamine transporter SPECT scan were included. Decline was not predicted by sex, baseline MMSE score, or presence of specific DLB core features. CONCLUSIONS: The average annual decline in MMSE score in DLB is approximately two points. Although in the overall analyses there were no differences in the rate of decline between the three neurodegenerative disorders, there were indications of a more rapid decline in DLB than in AD and PDD. Further studies are needed to understand the predictors and mechanisms of cognitive decline in DLB.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Cognition Disorders; Cohort Studies; Female; Humans; International Cooperation; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged

Modeling the Relationships Among Late-Life Body Mass Index, Cerebrovascular Disease, and Alzheimer's Disease Neuropathology in an Autopsy Sample of 1,421 Subjects from the National Alzheimer's Coordinating Center Data Set. - Alosco, Michael L; Duskin, Jonathan; Besser, Lilah M; Martin, Brett; Chaisson, Christine E; Gunstad, John; Kowall, Neil W; McKee, Ann C; Stern, Robert A; Tripodis, Yorghos (J Alzheimers Dis, 2017)
The relationship between late-life body mass index (BMI) and Alzheimer's disease (AD) is poorly understood due to the lack of research in samples with autopsy-confirmed AD neuropathology (ADNP). The role of cerebrovascular disease (CVD) in the interplay between late-life BMI and ADNP is unclear. We conducted a retrospective longitudinal investigation and used joint modeling of linear mixed effects to investigate causal relationships among repeated antemortem BMI measurements, CVD (quantified neuropathologically), and ADNP in an autopsy sample of subjects across the AD clinical continuum. The sample included 1,421 subjects from the National Alzheimer's Coordinating Center's Uniform Data Set and Neuropathology Data Set with diagnoses of normal cognition (NC; n = 234), mild cognitive impairment (MCI; n = 201), or AD dementia (n = 986). ADNP was defined as moderate to frequent neuritic plaques and Braak stageIII-VI. Ischemic Injury Scale (IIS) operationalized CVD. Joint modeling examined relationships among BMI, IIS, and ADNP in the overall sample and stratified by initial visit Clinical Dementia Rating score. Subject-specific random intercept for BMI was the predictor for ADNP due to minimal BMI change (p = 0.3028). Analyses controlling for demographic variables and APOE ɛ4 showed lower late-life BMI predicted increased odds of ADNP in the overall sample (p < 0.001), and in subjects with CDR of 0 (p = 0.0021) and 0.5 (p = 0.0012), but not ≥1.0 (p = 0.2012). Although higher IIS predicted greater odds of ADNP (p < 0.0001), BMI did not predict IIS (p = 0.2814). The current findings confirm lower late-life BMI confers increased odds for ADNP. Lower late-life BMI may be a preclinical indicator of underlying ADNP.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Autopsy; Body Mass Index; Cerebrovascular Disorders; Datasets as Topic; Female; Humans; Male; National Institute on Aging (U.S.); Neuropathology; Neuropsychological Tests; Retrospective Studies; United States

The Progression of Alzheimer's Disease: Are Fast Decliners Really Fast? A Four-Year Follow-Up. - Barocco, Federica; Spallazzi, Marco; Concari, Letizia; Gardini, Simona; Pelosi, Annalisa; Caffarra, Paolo (J Alzheimers Dis, 2017)
BACKGROUND: The rate of cognitive and functional decline in Alzheimer's disease (AD) changes across individuals. OBJECTIVES: Our purpose was to assess whether the concept of "fast decline" really fits its definition and whether cognitive and functional variables at onset can predict the progression of AD. METHODS: 324 AD patients were included. We retrospectively examined their Mini-Mental State Examination (MMSE) total score and sub-items, Activities of Daily Living (ADL), and Instrumental Activities of Daily Living (IADL) at baseline and every six months for a 4-year follow-up. Patients were divided into "fast decliners" (n = 62), defined by a loss ≥5 points on the MMSE score within the first year from the baseline; "intermediate decliners" (n = 37), by a loss ≥5 points after the first year and before the 18th month; or "slow decliners" (n = 225), composed of the remaining patients. RESULTS: At baseline, the groups did not differ on demographic, clinical, and cognitive variables. The decline at the end of the 4-year follow-up period seems to be similar among the different decline clusters. Predictors of disease progression have not been identified; only the MMSE total score at 12 months <14/30 was indicative of a poor prognosis. CONCLUSIONS: Even with the limitation due to the small sample size, the lack of differences in the disease progression in time in the different clusters suggest the inconsistency of the so-called "fast decliners". This study was unable to show any significant difference among clusters of AD progression within a 4-year time interval. Further studies should better clarify whether a more consistent distinction exists between slow and fast decliners.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Cognition Disorders; Disease Progression; Female; Humans; Longitudinal Studies; Male; Psychiatric Status Rating Scales; ROC Curve; Time Factors

Role of Suppressor of Cytokine Signaling 3 (SOCS3) in Altering Activated Microglia Phenotype in APPswe/PS1dE9 Mice. - Iwahara, Naotoshi; Hisahara, Shin; Kawamata, Jun; Matsumura, Akihiro; Yokokawa, Kazuki; Saito, Taro; Fujikura, Mai; Manabe, Tatsuo; Suzuki, Hiromi; Matsushita, Takashi; Suzuki, Syuuichirou; Shimohama, Shun (J Alzheimers Dis, 2017)
In response to changes of the central nervous system environment, microglia are capable of acquiring diverse phenotypes for cytotoxic or immune regulation and resolution of injury. Alzheimer's disease (AD) pathology also induces several microglial activations, resulting in production of pro-inflammatory cytokines and reactive oxygen species or clearance of amyloid-β (Aβ) through phagocytosis. We previously demonstrated that microglial activation and increase in oxidative stress started from the middle age in APPswe/PS1dE9 mice, and hypothesized that M1 activation occurs in middle-aged AD mice by Aβ stimulation. In the present study, we analyzed in vivo expressions of pro-inflammatory cytokines (M1 microglial markers), M2 microglial markers, and suppressor of cytokine signaling (SOCS) family, and examined the microglial phenotypic profile in APPswe/PS1dE9 mice. Then we compared the in vitro gene expression patterns of Aβ- and lipopolysaccharide (LPS)-stimulated primary-cultured microglia. Microglia in APPswe/PS1dE9 mice exhibited an M1-like phenotype, expressing tumor necrosis factor α (TNFα) but not interleukin 6 (IL6). Aβ-stimulated primary-cultured microglia also expressed TNFα but not IL6, whereas LPS-stimulated primary-cultured microglia expressed both pro-inflammatory cytokines. Furthermore, both microglia in APPswe/PS1dE9 mice and Aβ-stimulated primary-cultured microglia expressed SOCS3. Reduction of SOCS3 expression in Aβ-challenged primary-cultured microglia resulted in upregulation of IL6 expression. Our findings indicate that SOCS3 suppresses complete polarization to M1 phenotype through blocking IL6 production, and Aβ-challenged primary-cultured microglia replicate the in vivo gene expression pattern of microglia in APPswe/PS1dE9 mice. Aβ may induce the M1-like phenotype through blocking of IL6 by SOCS3.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Brain; Cells, Cultured; Disease Models, Animal; Female; Humans; Interleukin-6; Lipopolysaccharides; Male; Mice, Inbred C57BL; Mice, Transgenic; Microglia; Neurons; Presenilin-1; Suppressor of Cytokine Signaling 3 Protein; Tumor Necrosis Factor-alpha

Sleep Deprivation Induced Plasma Amyloid-β Transport Disturbance in Healthy Young Adults. - Wei, Meng; Zhao, Beiyu; Huo, Kang; Deng, Yongning; Shang, Suhang; Liu, Jie; Li, Yanbo; Ma, Louyan; Jiang, Yu; Dang, Liangjun; Chen, Chen; Wei, Shan; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Sleep is an important physiological process and beneficial in the removal of brain metabolites and functional recovery. Prior studies have shown that sleep disorders are significant risk factors for Alzheimer's disease (AD). OBJECTIVE: The present study was designed to characterize the effect of short-term total sleep deprivation (TSD) on plasma amyloid-β (Aβ) concentrations. METHODS: A clinical trial was conducted between March 1, 2016, and April 1, 2016. Twenty volunteers (age 27.3±3.4 years) with normal cognitive function and sleeping habits were recruited from the local population. Participants underwent 24 h of TSD. Periprocedural blood samples were collected to compare the changes of plasma Aβ42, Aβ40, low-density lipoprotein receptor-related protein (sLRP-1), soluble receptors for advanced glycation end products (sRAGE), and serum superoxide dismutase (SOD) and malonaldehyde (MDA). RESULTS: TSD increased morning plasma Aβ40 levels by 32.6% (p < 0.001) and decreased the Aβ42/Aβ40 ratio by 19.3% (p < 0.001). A positive relationship was found between TSD duration and plasma Aβ40 level (r = 0.51, p < 0.001) and Aβ40/Aβ42 ratio (r = 0.25, p = 0.003). Plasma concentrations of sLRP1 (p = 0.018) and sRAGE (p = 0.001) decreased significantly after TSD. Aβ40 and Aβ42 plasma concentrations correlated with plasma levels of sLRP1 and sRAGE. Serum SOD decreased after TSD (p = 0.005), whereas serum MDA was increased (p = 0.001). CONCLUSION: Sleep deprivation can lead to an elevation of plasma Aβ40 and decrease of the Aβ42/Aβ40 ratio. The underlying mechanisms may be related to increased oxidative stress and impaired peripheral Aβ clearance as pathomechanisms of AD.
Keywords: Adult; Amyloid beta-Peptides; Female; Humans; Low Density Lipoprotein Receptor-Related Protein-1; Male; Malondialdehyde; Peptide Fragments; Receptor for Advanced Glycation End Products; Sleep Deprivation; Superoxide Dismutase; Time Factors; Young Adult

Trends, Predictors, and Outcomes of Healthcare Resources Used in Patients Hospitalized with Alzheimer's Disease with at Least One Procedure: The Nationwide Inpatient Sample. - Beydoun, May A; Gamaldo, Alyssa A; Beydoun, Hind A; Shaked, Danielle; Zonderman, Alan B; Eid, Shaker M (J Alzheimers Dis, 2017)
We assessed trends, predictors and outcomes of resource utilization in hospital inpatient discharges with a principal diagnosis of Alzheimer's disease (AD) with at least one procedure. Using Nationwide Inpatient Sample data (NIS, 2002-2012), discharges primarily diagnosed with AD, aged ≥60 y and with ≥1 procedure, were selected (Weighted N = 92,300). Hospital resource utilization were assessed using ICD-9-CM codes, while hospitalization outcomes included total charges (TC, 2012$), length of stay (LOS, days), and mortality risk (MR, %). Brain and respiratory/gastrointestinal procedure utilization both dropped annually by 3-7%, while cardiovascular procedures/evaluations, blood evaluations, blood transfusion, and resuscitation ("CVD/Blood") as well as neurophysiological and psychological evaluation and treatment ("Neuro") procedures increased by 5-8%. Total charges, length of stay, and mortality risk were all markedly higher with use of respiratory/gastrointestinal procedures as opposed to being reduced with use of "Brain" procedures. Procedure count was positively associated with all three hospitalization outcomes. In sum, patterns of hospital resources that were used among AD inpatients changed over-time, and were associated with hospitalization outcomes such as total charges, length of stay, and mortality risk.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Female; Health Resources; Hospitalization; Humans; Inpatients; Length of Stay; Male; Middle Aged; Morbidity; Outcome Assessment (Health Care); Predictive Value of Tests; United States

What Drives Country Differences in Cost of Alzheimer's Disease? An Explanation from Resource Use in the GERAS Study. - Reed, Catherine; Happich, Michael; Argimon, Josep Maria; Haro, Josep Maria; Wimo, Anders; Bruno, Giuseppe; Dodel, Richard; Jones, Roy W; Vellas, Bruno; Belger, Mark (J Alzheimers Dis, 2017)
BACKGROUND: Country differences in resource use and costs of Alzheimer's disease (AD) may be driven by differences in health care systems and resource availability. OBJECTIVE: To compare country resource utilization drivers of societal costs for AD dementia over 18 months. METHODS: GERAS is an observational study in France (n = 419), Germany (n = 550), and the UK (n = 526). Resource use of AD patients and caregivers contributing to >1% of total societal costs (year 2010) was assessed for country differences, adjusting for participant characteristics. RESULTS: Mean 18-month societal costs per patient were France €33,339, Germany €38,197, and UK €37,899 (£32,501). Caregiver time spent on basic and instrumental activities of daily living (ADL) contributed the most to societal costs (54% France, 64% Germany, 65% UK). Caregivers in France spent less time on ADL than UK caregivers and missed fewer work days than in other countries. Compared with other countries, patients in France used more community care services overall and were more likely to use home aid. Patients in Germany were least likely to use temporary accommodation or to be institutionalized at 18 months. UK caregivers spent the most time on instrumental ADL, UK patients used fewest outpatient resources, and UK patients/caregivers were most likely to receive financial support. CONCLUSION: Caregiver time on ADL contributed the most to societal costs and differed across countries, possibly due to use of community care services and institutionalization. Other resources had different patterns of use across countries, reflecting country-specific health and social care systems.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Caregivers; Cohort Studies; Cost of Illness; Europe; Female; Health Resources; Humans; International Cooperation; Male; Surveys and Questionnaires

Aberrant Spontaneous Brain Activity in Patients with Mild Cognitive Impairment and concomitant Lacunar Infarction: A Resting-State Functional MRI Study. - Ni, Ling; Liu, Renyuan; Yin, Zhenyu; Zhao, Hui; Nedelska, Zuzana; Hort, Jakub; Zhou, Fei; Wu, Wenbo; Zhang, Xin; Li, Ming; Yu, Haiping; Zhu, Bin; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Lacunar infarctions (LI) have been associated with a cognitive decline and an increased risk of dementia. Whether and how the pattern of spontaneous brain activity in patients with mild cognitive impairment (MCI) differs in subjects with and without concomitant LI remains unclear. OBJECTIVE: To compare the pattern of spontaneous brain activity in MCI patients with versus those without LI using resting-state functional magnetic resonance imaging (rs-fMRI). METHODS: Forty-eight MCI patients, including 22 with LI [MCI-LI] and 26 without LI [MCI-no LI], and 28 cognitive normal subjects underwent rs-fMRI post-processed using regional homogeneity (ReHo) and the amplitude of low-frequency fluctuation (ALFF) methods. RESULTS: Compared with cognitively normal subjects, the MCI-LI patients had decreased ReHo in the precuneus/cuneus (Pcu/CU) and insula; decreased ALFF in the Pcu/CU and frontal lobe; and increased ALFF and ReHo in the temporal lobe. While the MCI-no LI group had increased ReHo and ALFF in the bilateral hippocampus and parahippocampal gyrus, frontal lobe, and decreased ALFF and ReHo in the temporal lobe. Compared with the MCI-no LI patients, those with MCI-LI had decreased ALFF in the frontal lobe; decreased ReHo in the Pcu/CU and insula; and increased ALFF and ReHo in the temporal lobe (p <  0.05, AlphaSim corrected). In MCI-LI patients, the MOCA scores showed a relatively weak correlation with ALFF values in the medial frontal gyrus (r = 0.432, p = 0.045) (of borderline significance after Bonferroni correction). CONCLUSIONS: The spontaneous brain activities in MCI-LI were distinct from MCI-no LI. The probable compensatory mechanism observed in MCI-no LI might be disrupted in MCI with LI due to vascular damage.
Keywords: Aged; Aged, 80 and over; Brain; Brain Mapping; Cognitive Dysfunction; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Rest; Stroke, Lacunar

Accurate Prediction of Conversion to Alzheimer's Disease using Imaging, Genetic, and Neuropsychological Biomarkers. - Dukart, Juergen; Sambataro, Fabio; Bertolino, Alessandro (J Alzheimers Dis, 2016)
A variety of imaging, neuropsychological, and genetic biomarkers have been suggested as potential biomarkers for the identification of mild cognitive impairment (MCI) in patients who later develop Alzheimer's disease (AD). Here, we systematically evaluated the most promising combinations of these biomarkers regarding discrimination between stable and converter MCI and reflection of disease staging. Alzheimer's Disease Neuroimaging Initiative data of AD (n = 144), controls (n = 112), stable (n = 265) and converter (n = 177) MCI, for which apolipoprotein E status, neuropsychological evaluation, and structural, glucose, and amyloid imaging were available, were included in this study. Naïve Bayes classifiers were built on AD and controls data for all possible combinations of these biomarkers, with and without stratification by amyloid status. All classifiers were then applied to the MCI cohorts. We obtained an accuracy of 76% for discrimination between converter and stable MCI with glucose positron emission tomography as a single biomarker. This accuracy increased to about 87% when including further imaging modalities and genetic information. We also identified several biomarker combinations as strong predictors of time to conversion. Use of amyloid validated training data resulted in increased sensitivities and decreased specificities for differentiation between stable and converter MCI when amyloid was included as a biomarker but not for other classifier combinations. Our results indicate that fully independent classifiers built only on AD and controls data and combining imaging, genetic, and/or neuropsychological biomarkers can more reliably discriminate between stable and converter MCI than single modality classifiers. Several biomarker combinations are identified as strongly predictive for the time to conversion to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Area Under Curve; Brain; Cognitive Dysfunction; Disease Progression; Female; Fluorodeoxyglucose F18; Follow-Up Studies; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Prognosis; Radiopharmaceuticals; ROC Curve; Sensitivity and Specificity

Activation of p53 in Down Syndrome and in the Ts65Dn Mouse Brain is Associated with a Pro-Apoptotic Phenotype. - Tramutola, Antonella; Pupo, Gilda; Di Domenico, Fabio; Barone, Eugenio; Arena, Andrea; Lanzillotta, Chiara; Broekaart, Diede; Blarzino, Carla; Head, Elizabeth; Butterfield, D Allan; Perluigi, Marzia (J Alzheimers Dis, 2016)
Down syndrome (DS) is the most common genetic cause of intellectual disability, resulting from trisomy of chromosome 21. The main feature of DS neuropathology includes early onset of Alzheimer's disease (AD), with deposition of senile plaques and tangles. We hypothesized that apoptosis may be activated in the presence of AD neuropathology in DS, thus we measured proteins associated with upstream and downstream pathways of p53 in the frontal cortex from DS cases with and without AD pathology and from Ts65Dn mice, at different ages. We observed increased acetylation and phosphorylation of p53, coupled to reduced MDM2/p53 complex level and lower levels of SIRT1. Activation of p53 was associated with a number of targets (BAX, PARP1, caspase-3, p21, heat shock proteins, and PGC1α) that were modulated in both DS and DS/AD compared with age-matched controls. In particular, the most relevant changes (increased p-p53 and acetyl-p53 and reduced formation of MDM2/p53 complex) were found to be modified only in the presence of AD pathology in DS. In addition, a similar pattern of alterations in the p53 pathway was found in Ts65Dn mice. These results suggest that p53 may integrate different signals, which can result in a pro-apoptotic-phenotype contributing to AD neuropathology in people with DS.
Keywords: Acetylation; Alzheimer Disease; Animals; Apoptosis; Blotting, Western; Disease Models, Animal; Down Syndrome; Female; Frontal Lobe; Humans; Immunoprecipitation; Male; Mice, Inbred C3H; Mice, Inbred C57BL; Mice, Transgenic; Middle Aged; Phenotype; Phosphorylation; Tumor Suppressor Protein p53; Young Adult

Activities of Daily Living and Depressive Symptoms in Patients with Subjective Cognitive Decline, Mild Cognitive Impairment, and Alzheimer's Disease. - Stogmann, Elisabeth; Moser, Doris; Klug, Stefanie; Gleiss, Andreas; Auff, Eduard; Dal-Bianco, Peter; Pusswald, Gisela; Lehrner, Johann (J Alzheimers Dis, 2016)
BACKGROUND: Subjective cognitive decline (SCD) may be an early indicator for an increased risk of dementia. The exact definition of SCD remains unclear and has recently become a major research interest. OBJECTIVES: To determine impairments in activities of daily living (ADL) and depressive symptoms in elderly individuals with SCD, mild cognitive impairment (MCI), and Alzheimer's disease (AD). METHODS: We included 752 consecutive patients suffering from SCD, non-amnestic (naMCI) or amnestic MCI (aMCI), AD, and 343 healthy controls into this prospective cohort study. A neuropsychological test battery, B-ADL and BDI-II was performed. RESULTS: SCD patients showed a decreased performance in ADL compared to controls. Performance in ADL declined concurrently with cognitive abilities along the controls-SCD-naMCI-aMCI-AD continuum. Individuals with cognitive complains, no matter if SCD, MCI, or AD patients, reported more often depressive symptoms compared to healthy controls without complaints. Within all five cognitive subgroups, patients with depressive symptoms reported more difficulties in ADL in comparison to patients without depressive symptoms. Adjusting for depressive symptoms, there was no significant group difference between the control versus the SCD group (OR 1.1, CI 0.6-1.7). CONCLUSIONS: SCD is a heterogeneous clinical condition. Specific features such as slightly impaired ADL and depressive symptoms are associated with SCD. Clinical markers may serve as an indicator for preclinical AD and in combination with biomarkers guide to an early diagnosis of a progressive neurodegenerative disease.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Cognitive Dysfunction; Depression; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Odds Ratio; Perception; Prospective Studies

Age and its association with low insulin and high amyloid-β peptides in blood. - Li, Huajie; Zhu, Haihao; Wallack, Max; Mwamburi, Mkaya; Abdul-Hay, Samer O; Leissring, Malcolm A; Qiu, Wei Qiao (J Alzheimers Dis, 2016)
Age is the major risk factor for developing Alzheimer's disease (AD), and modifying age-related factors may help to delay the onset of the disease. The goal of this study was to investigate the relationship between age and the metabolic factors related to the risk of developing AD. The concentrations of insulin, amylin, and amyloid-β peptide (Aβ) in plasma were measured. We further measured the activity of serum Aβ degradation by using fluorescein- and biotin-labeled Aβ40. Apolipoprotein E4 allele (ApoE4) and cognitive impairment were characterized. Subjects were divided into three age groups: 60-70, 70-80, and ≥80 years old. We found that the older the subjects, the lower the concentration of insulin (p = 0.001) and the higher the concentration of Aβ1-40 (p = 0.004) in plasma. However, age was not associated with the concentration of another pancreatic peptide, amylin, and only marginally with Aβ1-42. These relationships remained in the absence of diabetes, cardiovascular disease, and stroke, and regardless of the presence of ApoE4 and cognitive impairment. Both age and ApoE4 were inversely associated with, while insulin was positively associated with, the activities of Aβ degradation in serum. Our study suggested that low concentration of insulin and high concentration of Aβ40 are aging factors related to the risk of AD.
Keywords: Age Distribution; Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Biomarkers; Cognition Disorders; Cross-Sectional Studies; Female; Humans; Insulin; Islet Amyloid Polypeptide; Linear Models; Male; Middle Aged; Multivariate Analysis; Peptide Fragments

Alterations in the Levels of Amyloid-β, Phospholipid Hydroperoxide, and Plasmalogen in the Blood of Patients with Alzheimer's Disease: Possible Interactions between Amyloid-β and These Lipids. - Yamashita, Shinji; Kiko, Takehiro; Fujiwara, Hironori; Hashimoto, Michio; Nakagawa, Kiyotaka; Kinoshita, Mikio; Furukawa, Katsutoshi; Arai, Hiroyuki; Miyazawa, Teruo (J Alzheimers Dis, 2016)
Aside from accumulation of amyloid-β (Aβ) peptide in the brain, Alzheimer's disease (AD) has been reported as being associated with peroxidation of major phospholipids (e.g., phosphatidylcholine (PtdCho)) and degradation of antioxidative phospholipids (e.g., ethanolamine plasmalogen (PlsEtn)). In addition to its presence in the brain, Aβ is also found in blood; however, there is still little information about the levels of PtdCho hydroperoxide (PCOOH) and PlsEtn in the blood of patients with AD. In this study, by assuming a possible interaction among Aβ, PCOOH, and PlsEtn in blood circulation, we evaluated the levels of these molecules and correlations in blood samples that had been obtained from our former AD study for PCOOH measurement (Kiko et al., J Alzheimers Dis28, 593-600, 2012). We found that when compared to controls, plasma from patients with AD showed lower concentrations of PlsEtn species, especially PlsEtn bearing the docosahexaenoic acid (DHA) moiety. In addition, lower PlsEtn and higher PCOOH levels were observed in red blood cells (RBCs) of patients with AD. In both AD and control blood samples, RBC PCOOH levels tended to correlate with plasma levels of Aβ40, and each PlsEtn species showed different correlations with plasma Aβ. These results, together with in vitro data suggesting Aβ aggregation due to a decrease in levels of PlsEtn having DHA, led us to deduce that Aβ is involved in alterations in levels of PCOOH and PlsEtn species observed in the blood of patients with AD.
Keywords: Aged; Amyloid beta-Peptides; Female; Humans; Hydrogen Peroxide; Male; Phosphatidylcholines; Plasmalogens

Altered Affective Evaluations of Smells in Alzheimer's Disease. - Joussain, Pauline; Bessy, Marion; Fournel, Arnaud; Ferdenzi, Camille; Rouby, Catherine; Delphin-Combe, Floriane; Krolak-Salmon, Pierre; Bensafi, Moustafa (J Alzheimers Dis, 2016)
BACKGROUND: Studies of olfaction in Alzheimer's disease (AD) mainly focused on deficits in odor detection and identification, with very few investigations of olfactory emotional changes and their consequences for hedonics. OBJECTIVE: The aim of the present study was to characterize affective evaluations of odors in AD patients. METHODS: To this end, 20 AD patients and 20 matched controls were tested. Participants were screened for odor detection and identification ability and then asked to rate the intensity, pleasantness, and edibility of 20 odorants. RESULTS: Results showed that, overall, AD patients had lower detection ability and perceived all odors as weaker than controls. As expected, they had lower identification ability on both cued and non-cued tasks. In addition, when smelling pleasant odors, patients had significantly lower hedonic ratings than controls (p <  0.02), whereas no group difference was found for neutral or unpleasant odors (p >  0.05 in both cases). Moreover, an analysis combining both intensity and pleasantness ratings showed that whereas intensity increased as a function of pleasantness and unpleasantness in controls, this quadratic relationship was not observed in AD patients. CONCLUSIONS: The study suggests that the simplest categorization criteria of odors (intensity and hedonic valence) are impaired in AD patients (especially for pleasant odors).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Case-Control Studies; Emotions; Female; Humans; Male; Mood Disorders; Odorants; Olfaction Disorders; Psychiatric Status Rating Scales; Smell; Surveys and Questionnaires

Altered sense of humor in dementia. - Clark, Camilla N; Nicholas, Jennifer M; Gordon, Elizabeth; Golden, Hannah L; Cohen, Miriam H; Woodward, Felix J; Macpherson, Kirsty; Slattery, Catherine F; Mummery, Catherine J; Schott, Jonathan M; Rohrer, Jonathan D; Warren, Jason D (J Alzheimers Dis, 2016)
Sense of humor is potentially relevant to social functioning in dementias, but has been little studied in these diseases. We designed a semi-structured informant questionnaire to assess humor behavior and preferences in patients with behavioral variant frontotemporal dementia (bvFTD; n = 15), semantic dementia (SD; n = 7), progressive nonfluent aphasia (PNFA; n = 10), and Alzheimer's disease (AD; n = 16) versus healthy age-matched individuals (n = 21). Altered (including frankly inappropriate) humor responses were significantly more frequent in bvFTD and SD (all patients) than PNFA or AD (around 40% of patients). All patient groups liked satirical and absurdist comedy significantly less than did healthy controls. This pattern was reported premorbidly for satirical comedy in bvFTD, PNFA, and AD. Liking for slapstick comedy did not differ between groups. Altered sense of humor is particularly salient in bvFTD and SD, but also frequent in AD and PNFA. Humor may be a sensitive probe of social cognitive impairment in dementia, with diagnostic, biomarker and social implications.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Cognition Disorders; Emotions; Female; Frontotemporal Dementia; Humans; Male; Middle Aged; Neuropsychological Tests; Primary Progressive Nonfluent Aphasia; Psychiatric Status Rating Scales; Surveys and Questionnaires

Analysis of the MIRIAD Data Shows Sex Differences in Hippocampal Atrophy Progression. - Ardekani, Babak A; Convit, Antonio; Bachman, Alvin H (J Alzheimers Dis, 2016)
BACKGROUND: Hippocampus (HC) atrophy is a hallmark of early Alzheimer's disease (AD). Atrophy rates can be measured by high-resolution structural MRI. Longitudinal studies have previously shown sex differences in the progression of functional and cognitive deficits and rates of brain atrophy in early AD dementia. It is important to corroborate these findings on independent datasets. OBJECTIVE: To study temporal rates of HC atrophy over a one-year period in probable AD patients and cognitively normal (CN) subjects by longitudinal MRI scans obtained from the Minimal Interval Resonance Imaging in AD (MIRIAD) database. METHODS: We used a novel algorithm to compute an index of hippocampal (volumetric) integrity (HI) at baseline and one-year follow-up in 43 mild-moderate probable AD patients and 22 CN subjects in MIRIAD. The diagnostic power of longitudinal HI measurement was assessed using a support vector machines (SVM) classifier. RESULTS: The HI was significantly reduced in the AD group (p <  10(-20)). In addition, the annualized percentage rate of reduction in HI was significantly greater in the AD group (p <  10(-13)). Within the AD group, the annual reduction of HI in women was significantly greater than in men (p = 0.008). The accuracy of SVM classification between AD and CN subjects was estimated to be 97% by 10-fold cross-validation. CONCLUSION: In the MIRIAD patients with probable AD, the HC atrophies at a significantly faster rate in women as compared to men. Female sex is a risk factor for faster descent into AD. The HI measure has potential for AD diagnosis, as a biomarker of AD progression and a therapeutic target in clinical trials.
Keywords: Alzheimer Disease; Atrophy; Disease Progression; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male

Anemia and Mild Cognitive Impairment in the German General Population. - Dlugaj, Martha; Winkler, Angela; Weimar, Christian; Dürig, Jan; Broecker-Preuss, Martina; Dragano, Nico; Moebus, Susanne; Jöckel, Karl-Heinz; Erbel, Raimund; Eisele, Lewin (J Alzheimers Dis, 2016)
There is increasing evidence that anemia is associated with cognitive impairment. Therefore, the aim of the study was to examine the cross-sectional association of anemia as well as the persistence of anemia over the last five years with mild cognitive impairment (MCI) and MCI subtypes (amnestic/non-amnestic MCI (aMCI/naMCI)). Out of 4,157 participants (50% men, 50-80 years) of the second examination (t1) of a cohort study (baseline (t0) 2000-2003), we included 4,033 participants with available hemoglobin information and complete cognitive assessment. Anemia was defined as hemoglobin <13 g/dl in men (n = 84) and <12 g/dl in women (n = 79). Group comparisons were used to compare the cognitive subtests. To determine the association of MCI with anemia at t1, with anemia five years prior to the cognitive assessment (t0) and anemia at both time points, we used logistic regression models and included 579 participants with MCI and 1,438 cognitively normal participants out of the total cohort. Anemic participants showed lower performances in verbal memory and executive functions. The fully adjusted odds ratios (OR) for MCI, aMCI, and naMCI in anemic versus non-anemic participants were 1.92 (95% -CI, 1.09-3.39), 1.96 (1.00-3.87), and 1.88 (0.91-3.87). Anemia at both times points showed a non-significant association with naMCI (OR 3.74, 0.94-14.81, fully adjusted). Our results suggest that anemia is associated with an increased risk of MCI independent of traditional cardiovascular risk factors. The association of anemia and MCI has important clinical relevance, because many causes of anemia can be treated effectively.
Keywords: Aged; Aged, 80 and over; Anemia; Cognitive Dysfunction; Cohort Studies; Executive Function; Female; Follow-Up Studies; Germany; Humans; Male; Memory; Middle Aged; Neuropsychological Tests; Prevalence; Speech Perception

Anti-Correlated Cerebrospinal Fluid Biomarker Trajectories in Preclinical Alzheimer's Disease. - Gomar, Jesus J; Conejero-Goldberg, Concepcion; Davies, Peter; Goldberg, Terry E (J Alzheimers Dis, 2016)
BACKGROUND: The earliest stage of preclinical Alzheimer's disease (AD) is defined by low levels of cerebrospinal fluid (CSF) amyloid-β (Aβ42). However, covariance in longitudinal dynamic change of Aβ42 and tau in incipient preclinical AD is poorly understood. OBJECTIVE: To examine dynamic interrelationships between Aβ42 and tau in preclinical AD. METHODS: We followed 47 cognitively intact participants (CI) with available CSF data over four years in ADNI. Based on longitudinal Aβ42 levels in CSF, CI were classified into three groups: 1) Aβ42 stable with normal levels of Aβ42 over time (n = 15); 2) Aβ42 declining with normal Aβ42 levels at baseline but showing decline over time (n = 14); and 3) Aβ42 levels consistently abnormal (n = 18). RESULTS: In the Aβ42 declining group, suggestive of incipient preclinical AD, CSF phosphorylated tau (p-tau) showed a similar longitudinal pattern of increasing abnormality over time (p = 0.0001). Correlation between longitudinal slopes of Aβ42 and p-tau confirmed that both trajectories were anti-correlated (rho = -0.60; p = 0.02). Regression analysis showed that Aβ42 slope (decreasing Aβ42) predicted p-tau slope (increasing p-tau) (R2 = 0.47, p = 0.03). Atrophy in the hippocampus was predicted by the interaction of Aβ42 and p-tau slopes (p <  0.0001) only in this incipient preclinical AD group. In all groups combined, memory decline was predicted by p-tau. CONCLUSIONS: The evolution of Aβ42 and p-tau CSF biomarkers in CI subjects follows an anti-correlated trajectory, i.e., as Aβ42 declined, p-tau increased, and thus was suggestive of strong temporal coincidence. Rapid pathogenic cross-talk between Aβ42 and p-tau thus may be evident in very early stages of preclinical AD.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Atrophy; Brain; Disease Progression; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Prodromal Symptoms; Regression Analysis; Statistics, Nonparametric; tau Proteins

Apathy and Attentional Biases in Alzheimer's Disease. - Chau, Sarah A; Chung, Jonathan; Herrmann, Nathan; Eizenman, Moshe; Lanctôt, Krista L (J Alzheimers Dis, 2016)
BACKGROUND: Apathy, one of the most prevalent neuropsychiatric symptoms in Alzheimer's disease (AD), can be difficult to assess as cognition deteriorates. There is a need for more objective assessments that do not rely on patient insight, communicative capacities, or caregiver observation. OBJECTIVE: We measured visual scanning behavior, using an eye-tracker, to explore attentional bias in the presence of competing stimuli to assess apathy in AD patients. METHODS: Mild-to-moderate AD patients (Standardized Mini-Mental Status Examination, sMMSE >10) were assessed for apathy (Neuropsychiatric Inventory [NPI] apathy, Apathy Evaluation Scale [AES]). Participants were presented with 16 slides, each containing 4 images of different emotional themes (2 neutral, 1 social, 1 dysphoric). The duration of time spent, and fixation frequency on images were measured. RESULTS: Of the 36 AD patients (14 females, age = 78.2±7.8, sMMSE = 22.4±3.5) included, 17 had significant apathy (based on NPI apathy ≥4) and 19 did not. These groups had comparable age and sMMSE. Repeated-measures analysis of covariance models, controlling for total NPI, showed group (apathetic versus non-apathetic) by image (social versus dysphoric) interactions for duration (F(1,32) = 4.31, p = 0.046) and fixation frequency (F(1,32) = 11.34, p = 0.002). Apathetic patients demonstrated reduced duration and fixation frequency on social images compared with non-apathetic patients. Additionally, linear regression models suggest that more severe apathy predicted decreasing fixation frequency on social images (R2 = 0.26, Adjusted R2 = 0.19, F(3,32) = 3.65, p = 0.023). CONCLUSION: These results suggest that diminished attentional bias toward social-themed stimuli is a marker of apathy in AD. Measurements of visual scanning behavior may have the potential to predict and monitor treatment response in apathy.
Keywords: Aged; Alzheimer Disease; Apathy; Attentional Bias; Cognition; Cross-Sectional Studies; Emotions; Eye Movement Measurements; Eye Movements; Female; Humans; Linear Models; Male; Neuropsychological Tests; Photic Stimulation; Severity of Illness Index; Social Perception

Apolipoprotein ɛ4 is Associated with Dementia and Cognitive Impairment Predominantly Due to Alzheimer's Disease and Not with Vascular Cognitive Impairment: A Singapore-Based Cohort. - Chai, Yuek Ling; Yeo, Hazel Kai-Hui; Wang, Jiehao; Hilal, Saima; Ikram, Mohammad Kamran; Venketasubramanian, Narayanaswamy; Wong, Boon-Seng; Chen, Christopher Li-Hsian (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: While the association for apolipoprotein ɛ4 allele (APOE4) with Alzheimer's disease (AD) has been consistently confirmed, the association with vascular cognitive impairment (VCI) is unclear. We therefore explored the relationship of APOE with both AD and cerebrovascular disease (CeVD) by examining the prevalence of APOE4 in AD, AD with CeVD and vascular dementia (VaD), as well as in cognitive impairment no dementia (CIND) with and without CeVD. METHODS: We performed a case-control study with subjects recruited from memory clinics and the community. All subjects underwent standardized brain neuroimaging, clinical and neuropsychological assessments, following which they were classified using research criteria. RESULTS: A total of 411 subjects; 92 controls with no cognitive impairment (NCI), 77 CIND without CeVD, 87 CIND with CeVD, 55 AD without CeVD, 68 AD with CeVD, and 32 VaD patients were recruited. Compared to NCI (16.3%), the prevalence of APOE4 carriers was significantly higher only in CIND (37.7%) and AD in the absence of CeVD (45.5%), but not in the three subgroups of VCI, namely CIND with CeVD (20.7%), AD with CeVD (27.9%) and VaD (25.0%). Logistic regression analyses also showed that APOE4 carriers were more likely to have CIND without CeVD (Odds Ratio [OR]: 3.34; 95% Confidence Interval [CI]: 1.59-7.03) and AD without CeVD (OR: 7.21; 95% CI: 2.74-18.98), but no such association was observed in the VCI subgroups. CONCLUSION: APOE4 is significantly associated with dementia and CIND due to AD pathology, but not with VCI.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Apolipoprotein E4; Cognition Disorders; Cohort Studies; Dementia; Female; Genetic Association Studies; Genotype; Humans; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Psychiatric Status Rating Scales; Singapore; Vascular Diseases

Application of the IWG-2 Diagnostic Criteria for Alzheimer's Disease to the ADNI. - Wang, Hui-Fu; Tan, Lan; Cao, Lei; Zhu, Xi-Chen; Jiang, Teng; Tan, Meng-Shan; Liu, Ying; Wang, Chong; Tsai, Richard M; Jia, Jian-Ping; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: The International Working Group (IWG) recently proposed the revised diagnostic criteria for Alzheimer's disease (AD) to define and refine several types of AD, and to reclassify AD-related biomarkers into diagnostic and progression markers, but its performance is not known. OBJECTIVE: This study was designed to describe the application of the revised IWG criteria in the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset, and to ascertain whether diagnostic and progression markers show significant differences in their relationships to AD severity and progression. METHODS: Based on the requirements of the refined criteria, 857 ADNI subjects with memory evaluation and at least one pathophysiological marker (CSF or amyloid imaging biomarkers) were eligible and reclassified in this study, and we calculated the associations of diagnostic (CSF and amyloid PET) and progression markers (MRI and fluorodeoxyglucose-PET) with AD severity and progression respectively. RESULTS: The majority (84.2% ) of ADNI AD group (n = 117) and 173 MCI (37.4% ) subjects in ADNI met the definition of typical AD; and 105 cognitively normal (41.0% ) individuals were diagnosed as asymptomatic AD. Furthermore, diagnostic and progression markers showed significant differences when correlated to AD severity and progression. CONCLUSION: A large proportion of AD dementia subjects were categorized as typical AD, and the revised criteria could identify typical AD from MCI status as well as asymptomatic AD at the asymptomatic stage. Moreover, the significant differences between diagnostic and progression markers further supported the new biomarkers categorization in the refined criteria.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid Precursor Protein Secretases; Aspartic Acid Endopeptidases; Cognitive Dysfunction; Databases, Factual; Disease Progression; Female; Humans; Longitudinal Studies; Male; Multicenter Studies as Topic; Neuroimaging; Psychiatric Status Rating Scales; tau Proteins

Association between Coffee Consumption and Incident Risk of Disabling Dementia in Elderly Japanese: The Ohsaki Cohort 2006 Study. - Sugiyama, Kemmyo; Tomata, Yasutake; Kaiho, Yu; Honkura, Kenji; Sugawara, Yumi; Tsuji, Ichiro (J Alzheimers Dis, 2016)
Epidemiological studies of the association between coffee consumption and dementia have yielded inconsistent results. Therefore, we investigated the association between coffee consumption and incident risk of dementia in an elderly Japanese population. 23,091 subjects aged ≥65 y living in Ohsaki City, northeastern Japan, responded to the baseline survey in 2006. Of these, we analyzed 13,137 subjects who gave informed consent and were not disabled at baseline. The outcome was the incidence of disabling dementia defined by usage of the Long-term Care Insurance database. We used the Cox proportional hazards regression model for multivariate analysis. During 5.7 y of follow-up period, we identified 1,107 cases of incident dementia. Overall, coffee consumption was significantly associated with a lower risk of incident dementia. The multivariate-adjusted HRs for the incidence of dementia according to coffee consumption categories (never, occasionally, 1-2 cups/d, and ≥3 cups/d) were 1.00, 0.73 (95% CI, 0.62-0.86), 0.72 (95% CI, 0.61-0.84), and 0.82 (95% CI, 0.65-1.02; p for trend = 0.009), respectively. In addition, this significant inverse association was more remarkable among women, non-smokers, and non-drinkers. Coffee consumption is significantly associated with a lower risk of incident dementia.
Keywords: Aged; Aged, 80 and over; Coffee; Dementia; Female; Health Surveys; Humans; Incidence; Japan; Male; Prospective Studies; Risk Factors

Association Between Serum Ceruloplasmin Specific Activity and Risk of Alzheimer's Disease. - Siotto, Mariacristina; Simonelli, Ilaria; Pasqualetti, Patrizio; Mariani, Stefania; Caprara, Deborah; Bucossi, Serena; Ventriglia, Mariacarla; Molinario, Rossana; Antenucci, Mirca; Rongioletti, Mauro; Rossini, Paolo Maria; Squitti, Rosanna (J Alzheimers Dis, 2016)
Meta-analyses demonstrate copper involvement in Alzheimer's disease (AD), and the systemic ceruloplasmin status in relation to copper is an emerging issue. To deepen this matter, we evaluated levels of ceruloplasmin concentration, ceruloplasmin activity, ceruloplasmin specific activity (eCp/iCp), copper, non-ceruloplasmin copper iron, transferrin, the ceruloplasmin/transferrin ratio, and the APOE genotype in a sample of 84 AD patients and 58 healthy volunteers. From the univariate logistic analyses we found that ceruloplasmin concentration, eCp/iCp, copper, transferrin, the ceruloplasmin/transferrin ratio, and the APOE genotype were significantly associated with the probability of AD. In the multivariable logistic regression analysis, we selected the best subset of biological predictors by the forward stepwise procedure. The analysis showed a decrease of the risk of having AD for eCp/iCp (p = 0.001) and an increase of this risk for non-ceruloplasmin copper (p = 0.008), age (p = 0.001), and APOE-ɛ4 allele (p <  0.001). The estimated model showed a good power in discriminating AD patients from healthy controls (area under curve: 88% ; sensitivity: 66% ; specificity 93%). These data strength the breakdown of copper homeostasis and propose eCp/iCp as a reliable marker of ceruloplasmin status.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Area Under Curve; Biomarkers; Blood Chemical Analysis; Ceruloplasmin; Copper; Female; Genotype; Genotyping Techniques; Humans; Logistic Models; Male; Multivariate Analysis; Prognosis; Risk; ROC Curve; Sensitivity and Specificity; Transferrin

Association of Butyrylcholinesterase-K Allele and Apolipoprotein E ɛ4 Allele with Cognitive Decline in Dementia with Lewy Bodies and Alzheimer's Disease. - Vijayaraghavan, Swetha; Darreh-Shori, Taher; Rongve, Arvid; Berge, Guro; Sando, Sigrid B; White, Linda R; Auestad, Bjørn H; Witoelar, Aree; Andreassen, Ole A; Ulstein, Ingun D; Aarsland, Dag (J Alzheimers Dis, 2016)
BACKGROUND: A common polymorphism of the butyrylcholinesterase gene, the K-variant (BCHE-K) is associated with reduced butyrylcholinesterase (BuChE) activity. Insufficient studies exist regarding the frequency and role of BCHE-K in dementias. OBJECTIVE: To determine the association of BCHE-K and APOEɛ4 with diagnosis and rate of cognitive decline in dementia with Lewy bodies (DLB) and Alzheimer's disease (AD) patients. METHODS: Genomic DNA from 368 subjects (108 AD, 174 DLB, and 86 controls) from two routine clinical cohort studies in Norway; DemVest and TrønderBrain, were genotyped for BCHE-K and APOEɛ4. The mild dementia DemVest subjects received annual Mini-Mental State Examination assessments for five years. RESULTS: BCHE-K frequency was lower in DLB (33.9% ; p <  0.01) than in control subjects (51.2%), and was numerically lower in AD as well (38.9% ; p = 0.11). More rapid cognitive decline was associated with the APOEɛ4 genotype, but not with the BCHE-K genotype. In an exploratory analysis of patients who completed all five follow-up visits, there was greater cognitive decline in BCHE-K carriers in the presence of the APOEɛ4 allele than in the absence of these polymorphisms. CONCLUSION: BCHE-K is associated with a reduced risk for AD and DLB whereas APOEɛ4 is associated with more rapid cognitive decline. The greater cognitive decline in individuals with both APOEɛ4 and BCHE-K alleles require prospective confirmation in well-controlled trials.
Keywords: Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Butyrylcholinesterase; Cognition; Disease Progression; Female; Gene Frequency; Genotype; Humans; Lewy Body Disease; Male; Neuropsychological Tests

Association of Frontotemporal Dementia GWAS Loci with Late-Onset Alzheimer's Disease in a Northern Han Chinese Population. - Tan, Chen-Chen; Wan, Yu; Tan, Meng-Shan; Zhang, Wei; Wang, Zi-Xuan; Sun, Fu-Rong; Miao, Dan; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: Both Alzheimer's disease (AD) and frontotemporal dementia (FTD) are a class of neurodegenerative diseases. Strong similarities in cerebrospinal fluid biomarker, imaging markers, and disease progression profiles suggest that some or most of the pathophysiology is shared between AD and FTD. A recent large genome-wide association study reported several single nucleotide polymorphisms (SNPs) at the RAB38, RAB38/CTSC, HLA-DRA/HLA-DRB5, and BTNL2 in association with FTD. OBJECTIVE: To explore whether these SNPs are associated with AD risk. METHODS: We conducted a case-control study to investigate the association of FTD-associated loci in 2338 Han Chinese subjects. RESULTS: We observed significant differences in genotype distributions of rs302668 (pc = 0.025), rs9268877 (pc = 0.025), rs9268856 (p <  0.001), and rs1980493 (pc = 0.045) between cases and controls. The SNPs rs16913634 for RAB38/CTSC was unrelated to LOAD risk (p = 0.088). CONCLUSION: The SNPs rs302668 in RAB38, rs9268877 and rs9268856 polymorphism in HLA-DRA/HLA-DRB5, and rs1980493 polymorphism in BTNL2 might play a role in the susceptibility to late-onset AD in the Han Chinese population.
Keywords: Age of Onset; Aged; Alzheimer Disease; Apolipoprotein E4; Asian Continental Ancestry Group; Case-Control Studies; China; Female; Frontotemporal Dementia; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Genotyping Techniques; Humans; Linkage Disequilibrium; Male; Mental Status Schedule; Polymorphism, Single Nucleotide

Association of Serum Vitamin D with the Risk of Incident Dementia and Subclinical Indices of Brain Aging: The Framingham Heart Study. - Karakis, Ioannis; Pase, Matthew P; Beiser, Alexa; Booth, Sarah L; Jacques, Paul F; Rogers, Gail; DeCarli, Charles; Vasan, Ramachandran S; Wang, Thomas J; Himali, Jayandra J; Annweiler, Cedric; Seshadri, Sudha (J Alzheimers Dis, 2016)
BACKGROUND: Identifying nutrition- and lifestyle-based risk factors for cognitive impairment and dementia may aid future primary prevention efforts. OBJECTIVE: We aimed to examine the association of serum vitamin D levels with incident all-cause dementia, clinically characterized Alzheimer's disease (AD), MRI markers of brain aging, and neuropsychological function. METHODS: Framingham Heart Study participants had baseline serum 25-hydroxyvitamin D (25(OH)D) concentrations measured between 1986 and 2001. Vitamin D status was considered both as a continuous variable and dichotomized as deficient (<10 ng/mL), or at the cohort-specific 20th and 80th percentiles. Vitamin D was related to the 9-year risk of incident dementia (n = 1663), multiple neuropsychological tests (n = 1291) and MRI markers of brain volume, white matter hyperintensities and silent cerebral infarcts (n = 1139). RESULTS: In adjusted models, participants with vitamin D deficiency (n = 104, 8% of the cognitive sample) displayed poorer performance on Trail Making B-A (β= -0.03 to -0.05±0.02) and the Hooper Visual Organization Test (β= -0.09 to -0.12±0.05), indicating poorer executive function, processing speed, and visuo-perceptual skills. These associations remained when vitamin D was examined as a continuous variable or dichotomized at the cohort specific 20th percentile. Vitamin D deficiency was also associated with lower hippocampal volumes (β= -0.01±0.01) but not total brain volume, white matter hyperintensities, or silent brain infarcts. No association was found between vitamin D deficiency and incident all-cause dementia or clinically characterized AD. CONCLUSIONS: In this large community-based sample, low 25(OH)D concentrations were associated with smaller hippocampal volume and poorer neuropsychological function.
Keywords: Adult; Aging; Brain; Cohort Studies; Dementia; Female; Humans; Incidence; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Neuropsychological Tests; Regression Analysis; Risk; Sensitivity and Specificity; Vitamin D

Associations between Neuropsychiatric Symptoms and Cerebral Amyloid Deposition in Cognitively Impaired Elderly People. - Bensamoun, David; Guignard, Renaud; Furst, Ansgar J; Derreumaux, Alexandre; Manera, Valeria; Darcourt, Jacques; Benoit, Michel; Robert, Philippe H; David, Renaud (J Alzheimers Dis, 2016)
BACKGROUND: Neuropsychiatric symptoms, also known as behavioral and psychological symptoms of dementia (BPSD), affect the majority of patients with dementia, and result in a greater cognitive and functional impairment. OBJECTIVE: To investigate associations between BPSD and amyloid cerebral deposition as measured by 18F-Florbetapir-PET quantitative uptake in elderly subjects with and without cognitive impairment. METHODS: Participants with cognitive impairment [mild cognitive impairment (MCI) or Alzheimer's disease (AD)] and healthy controls (HC) from the ADNI cohort (Alzheimer Disease Neuroimaging Initiative) who underwent an 18F-florbetapir PET scan between May 2010 and March 2014 were included. Clinical assessments included the Clinical Dementia Rating, the Mini-Mental State Examination (MMSE), and the Neuropsychiatric Inventory. Freesurfer software was used to extract PET counts based on T1-based structural ROI (frontal, cingulate, parietal, and temporal). Spearman's partial correlation scores between BPSD severity and regional amyloid uptake were calculated. RESULTS: Data for 657 participants [age = 72.6 (7.19); MMSE = 27.4 (2.67)] were analyzed, including 230 HC [age = 73.1 (6.02); MMSE = 29 (1.21)], 308 MCI [age = 71.5 (7.44); MMSE = 28.0 (1.75)], and 119 AD subjects [age = 74.7 (8.05); MMSE = 23.1 (2.08)]. Considering all diagnostic groups together, positive significant correlations were found between anxiety and 18F-florbetapir uptake in the frontal (r = 0.102; p = 0.009), cingulate (r = 0.083; p = 0.034), and global cerebral uptake (r = 0.099; p = 0.011); between irritability and frontal (r = 0.089; p = 0.023), cingulate (r = 0.085; p = 0.030), parietal (r = 0.087; p = 0.025), and global cerebral uptake (r = 0.093; p = 0.017); in the MCI subgroup, between anxiety and frontal (r = 0.126; p = 0.03) and global uptake (r = 0.14; p = 0.013); in the AD subgroup, between irritability and parietal uptake (r = 0.201; p = 0.03). CONCLUSION: Anxiety and irritability are associated with greater amyloid deposition in the neurodegenerative process leading to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloidogenic Proteins; Cerebral Cortex; Cognition Disorders; Cohort Studies; Female; Fluorodeoxyglucose F18; Humans; Male; Mental Status Schedule; Mood Disorders; Neuropsychological Tests; Positron-Emission Tomography

Associations between Serum Omega-3 Fatty Acid Levels and Cognitive Functions among Community-Dwelling Octogenarians in Okinawa, Japan: The KOCOA Study. - Nishihira, Junko; Tokashiki, Takashi; Higashiuesato, Yasushi; Willcox, Donald Craig; Mattek, Nora; Shinto, Lynne; Ohya, Yusuke; Dodge, Hiroko H (J Alzheimers Dis, 2016)
BACKGROUND: Epidemiological studies have found frequent consumption of fatty fish is protective against cognitive decline. However, the association between circulating omega-3 polyunsaturated fatty acid (PUFA) levels and cognitive functions among the oldest old is not well known. OBJECTIVE: To examine the association between serum PUFA levels and cognitive function among community-dwelling, non-demented elderly aged over 80 years old. METHODS: The data came from the Keys to Optimal Cognitive Aging (KOCOA) study; an ongoing cohort of relatively healthy volunteers aged over 80 years old, living in Okinawa, Japan. One hundred eighty five participants (mean age 84.1±3.4 years) assessed in 2011 who were free from frank dementia (defined as Clinical Dementia Rating <1.0) were used for the current cross-sectional study. We examined whether serum omega-3 PUFAs (docosahexaenoic acid [DHA] and eicosapentaenoic acid [EPA]), arachidonic acid (AA), EPA/AA ratio, DHA/AA ratio, and DHA+EPA are associated with (1) age and (2) global cognitive function (Japanese MMSE) and executive function (Verbal Fluency Letter). Data was analyzed univariately by t-test and multivariately by cumulative logistic regression models controlling for age, gender, years of education, obesity, hypertension, diabetes, and dyslipidemia. RESULTS: Serum DHA levels decreased with increasing age (p = 0.04). Higher global cognitive function was associated with higher levels of serum EPA (p = 0.03) and DHA + EPA (p = 0.03) after controlling for confounders. CONCLUSIONS: Higher serum EPA and DHA + EPA levels were independently associated with better scores on global cognitive function among the oldest old, free from dementia. Longitudinal follow-up studies are warranted.
Keywords: Age Factors; Aged, 80 and over; Arachidonic Acid; Blood Chemical Analysis; Cognition; Cross-Sectional Studies; Educational Status; Fatty Acids, Omega-3; Female; Humans; Japan; Logistic Models; Male; Mental Status Schedule; Obesity; Prospective Studies; Sex Factors

AZD3293: A Novel, Orally Active BACE1 Inhibitor with High Potency and Permeability and Markedly Slow Off-Rate Kinetics. - Eketjäll, Susanna; Janson, Juliette; Kaspersson, Karin; Bogstedt, Anna; Jeppsson, Fredrik; Fälting, Johanna; Haeberlein, Samantha Budd; Kugler, Alan R; Alexander, Robert C; Cebers, Gvido (J Alzheimers Dis, 2016)
A growing body of pathological, biomarker, genetic, and mechanistic data suggests that amyloid accumulation, as a result of changes in production, processing, and/or clearance of brain amyloid-β peptide (Aβ) concentrations, plays a key role in the pathogenesis of Alzheimer's disease (AD). Beta-secretase 1 (BACE1) mediates the first step in the processing of amyloid-β protein precursor (AβPP) to Aβ peptides, with the soluble N terminal fragment of AβPP (sAβPPβ) as a direct product, and BACE1 inhibition is an attractive target for therapeutic intervention to reduce the production of Aβ. Here, we report the in vitro and in vivo pharmacological profile of AZD3293, a potent, highly permeable, orally active, blood-brain barrier (BBB) penetrating, BACE1 inhibitor with unique slow off-rate kinetics. The in vitro potency of AZD3293 was demonstrated in several cellular models, including primary cortical neurons. In vivo in mice, guinea pigs, and dogs, AZD3293 displayed significant dose- and time-dependent reductions in plasma, cerebrospinal fluid, and brain concentrations of Aβ40, Aβ42, and sAβPPβ. The in vitro potency of AZD3293 in mouse and guinea pig primary cortical neuronal cells was correlated to the in vivo potency expressed as free AZD3293 concentrations in mouse and guinea pig brains. In mice and dogs, the slow off-rate from BACE1 may have translated into a prolongation of the observed effect beyond the turnover rate of Aβ. The preclinical data strongly support the clinical development of AZD3293, and patients with AD are currently being recruited into a combined Phase 2/3 study to test the disease-modifying properties of AZD3293.
Keywords: Administration, Oral; Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Animals; Blood Chemical Analysis; Blood-Brain Barrier; Brain; Dogs; Dose-Response Relationship, Drug; Drug Evaluation, Preclinical; Enzyme Inhibitors; Female; Guinea Pigs; Humans; Imidazoles; Kinetics; Male; Mice, Inbred C57BL; Peptide Fragments; Spiro Compounds

Beneficial Effects of an Integrated Psychostimulation Program in Patients with Alzheimer's Disease. - Ibarria, Marta; Alegret, Montserrat; Valero, Sergi; Morera, Amèrica; Guitart, Marina; Cañabate, Pilar; Moreno, Mariola; Lara, Susana; Diego, Susana; Hernández, Joan; Tantinyá, Natàlia; Vera, Maribel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The existing pharmacological treatments for Alzheimer's disease (AD) can only slow the progression of symptoms or delay admission to long-term care facilities. The beneficial effects of non-drug treatments are poorly studied. OBJECTIVE: To describe the effects of an Integrated Psychostimulation Program (IPP) in patients with mild-moderate AD treated with acetylcholinesterase inhibitors; and to identify factors related to greater benefit of the IPP. METHODS: 206 patients (mean age = 75.9 years; MMSE = 19.6) were evaluated before starting the IPP and 3, 6, 9, and 12 months later. Measures included: Mini-Mental State Examination (MMSE), Cognitive Subscale of Alzheimer's Disease Assessment Scale (ADAS-Cog), Rapid Disability Rating Scale (RDRS-2), and Neuropsychiatric Inventory Questionnaire (NPI-Q). RESULTS: Patients remained cognitively stable (MMSE/ADAS-Cog) for more than 6 months and significantly worsened at 9-month and 12-month follow-ups, without clinically significant functional changes (RDRS-2) or psychiatric symptoms(NPI-Q). The mean annual change on MMSE and ADAS-Cog were 2.06 and 3.56 points, respectively, lower than the annual decline demonstrated previously in similar patients (2.4 and 4.5, respectively). 42.7% of patients maintained or improved global cognitive scores between baseline and 12-month follow-up. The patients who maintained cognitive functions were older than those who did not (77.5 versus 74.7 years). CONCLUSIONS: The IPP may be an effective treatment to maintain cognition, functionality, and psychiatric symptoms in AD patients pharmacologically treated, and older age seems to increase beneficial effects of IPP.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cholinesterase Inhibitors; Cognition; Combined Modality Therapy; Disease Progression; Female; Humans; Male; Neuropsychological Tests; Psychotherapy; Severity of Illness Index; Treatment Outcome

Blood-Borne Activity-Dependent Neuroprotective Protein (ADNP) is Correlated with Premorbid Intelligence, Clinical Stage, and Alzheimer's Disease Biomarkers. - Malishkevich, Anna; Marshall, Gad A; Schultz, Aaron P; Sperling, Reisa A; Aharon-Peretz, Judith; Gozes, Illana (J Alzheimers Dis, 2016)
Biomarkers for Alzheimer's disease (AD) are vital for disease detection in the clinical setting. Discovered in our laboratory, activity-dependent neuroprotective protein (ADNP) is essential for brain formation and linked to cognitive functions. Here, we revealed that blood borne expression of ADNP and its paralog ADNP2 is correlated with premorbid intelligence, AD pathology, and clinical stage. Age adjustment showed significant associations between: 1) higher premorbid intelligence and greater serum ADNP, and 2) greater cortical amyloid and lower ADNP and ADNP2 mRNAs. Significant increases in ADNP mRNA levels were observed in patients ranging from mild cognitive impairment (MCI) to AD dementia. ADNP2 transcripts showed high correlation with ADNP transcripts, especially in AD dementia lymphocytes. ADNP plasma/serum and lymphocyte mRNA levels discriminated well between cognitively normal elderly, MCI, and AD dementia participants. Measuring ADNP blood-borne levels could bring us a step closer to effectively screening and tracking AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Chi-Square Distribution; Cognitive Dysfunction; Cohort Studies; Female; Homeodomain Proteins; Humans; Independent Living; Intelligence; Male; Mental Status Schedule; Middle Aged; Nerve Tissue Proteins; Peptide Fragments; RNA, Messenger; tau Proteins

Brain Metabolism Correlates of the Free and Cued Selective Reminding Test in Mild Cognitive Impairment. - Caffarra, Paolo; Ghetti, Caterina; Ruffini, Livia; Spallazzi, Marco; Spotti, Annamaria; Barocco, Federica; Guzzo, Caterina; Marchi, Massimo; Gardini, Simona (J Alzheimers Dis, 2016)
Free and Cued Selective Reminding Test (FCSRT) measures immediate and delayed episodic memory and cueing sensitivity and is suitable to detect prodromal Alzheimer's disease (AD). The present study aimed at investigating the segregation effect of FCSRT scores on brain metabolism of memory-related structures, usually affected by AD pathology, in the Mild Cognitive Impairment (MCI) stage. A cohort of forty-eight MCI patients underwent FCSRT and 18F-FDG-PET. Multiple regression analysis showed that Immediate Free Recall correlated with brain metabolism in the bilateral anterior cingulate and delayed free recall with the left anterior cingulate and medial frontal gyrus, whereas semantic cueing sensitivity with the left posterior cingulate. FCSRT in MCI is associated with neuro-functional activity of specific regions of memory-related structures connected to hippocampal formation, such as the cingulate cortex, usually damaged in AD.
Keywords: Aged; Brain; Cognitive Dysfunction; Cues; Female; Fluorodeoxyglucose F18; Humans; Male; Memory Disorders; Memory, Episodic; Mental Recall; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography

Bridging Integrator 1 (BIN1) Genotypes Mediate Alzheimer's Disease Risk by Altering Neuronal Degeneration. - Wang, Hui-Fu; Wan, Yu; Hao, Xiao-Ke; Cao, Lei; Zhu, Xi-Chen; Jiang, Teng; Tan, Meng-Shan; Tan, Lin; Zhang, Dao-Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: Bridging integrator 1 (BIN1) has been identified as one of the most associated loci for Alzheimer's disease (AD), and recently was reported to modulate tau pathology to mediate AD in vitro. However, the effects of BIN1 on the AD related biomarkers in AD continuum were not specifically assessed. OBJECTIVE: We explored the effects of BIN1 loci on AD specific biomarkers (CSF proteins, brain structures, glucose and amyloid-β (Aβ) metabolisms) to investigate the role BIN1 in AD pathogenesis. METHODS: We calculated the associations of BIN1 loci with these markers at baseline and follow-up in multiple linear models in 812 ADNI subjects. RESULTS: BIN1 loci were significantly associated with the levels of T-tau (rs744373: pc = 0.047, rs13031703: pc = 0.042) and P-tau (rs744373: pc = 0.044, rs13031703: pc = 0.019), but not with Aβ in CSF test. BIN1 genotypes were strongly related to atrophy of hippocampus (rs7561528: pc = 0.011), CA1 (rs1469980: pc = 0.029) and parahippocampus (rs72838284, pc = 0.017) on MRI, and to glucose metabolism on FDG-PET, but not to Aβ deposition on AV45-PET imaging. Furthermore, haplotype and subgroup analysis confirmed these significant findings. In addition, the loci associated with these markers were also identified to influence the risk for AD in the meta-analysis of 74 046 European individuals. CONCLUSION: This study supported that BIN1 contributes to the risk of AD by altering neural degeneration (abnormal tau, brain atrophy and glucose metabolism) but not Aβ pathology.
Keywords: Adaptor Proteins, Signal Transducing; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Brain; Databases, Factual; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Predisposition to Disease; Glucose; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Nerve Degeneration; Nuclear Proteins; Polymorphism, Single Nucleotide; Positron-Emission Tomography; Risk; tau Proteins; Tumor Suppressor Proteins

Capillary amyloid-β protein deposition in a population-based study (Vantaa 85+). - Mäkelä, Mira; Paetau, Anders; Polvikoski, Tuomo; Myllykangas, Liisa; Tanskanen, Maarit (J Alzheimers Dis, 2016)
BACKGROUND: Capillary amyloid-β (capAβ) deposition in the cerebral cortex is the neuropathological feature providing the basis for categorizing cerebral amyloid angiopathy (CAA) into two distinct types, CAA-Type1 with capAβ and CAA-Type2 without capAβ. OBJECTIVE: We investigated the neuropathological and clinical characteristics of capAβ deposition in a prospective population-based study. METHODS: Vantaa 85+ includes 601 individuals aged ≥85 years, of which 300 were studied clinically and neuropathologically. 278 subjects were analyzed for the apolipoprotein E (APOE) genotype. The diagnosis of capAβ was determined using immunohistochemistry against Aβ, and of CAA using Congo red confirmed by Aβ immunohistochemistry, both analyzed in six brain areas. The severity of capAβ was graded semi-quantitatively, and the severity of CAA was based on the percentage of affected vessels. Alzheimer's disease (AD)-type neuropathology (CERAD score and Braak stage) was analyzed using standard methods. RESULTS: CAA-Type1 was present in 86/300, CAA-Type2 in 135/300, and 79/300 had no CAA. CapAβ was most frequent in the occipital lobe (79/86). CAA-Type1 was associated with the severity of CAA (p <  0.001), dementia (p <  0.001), severe AD-type neuropathology (p-value 0.09 for CERAD C and 0.017 for Braak stages V-VI), and APOE ɛ4 allele carrier status (p <  0.001). CONCLUSIONS: This population-based study confirmed the presence of distinct CAA-Type1 and its association with the severity of CAA, severe AD-type neuropathology, and the APOE ɛ4 carrier status. Both the severity and localization of the deposition seemed to determine the clinical significance of capAβ.
Keywords: Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Autopsy; Capillaries; Cerebral Amyloid Angiopathy; Female; Finland; Genotype; Humans; Immunohistochemistry; Logistic Models; Male; Multivariate Analysis; Occipital Lobe; Prospective Studies; Severity of Illness Index

Cerebral Small Vessel Disease and Motoric Cognitive Risk Syndrome: Results from the Kerala-Einstein Study. - Wang, Nan; Allali, Gilles; Kesavadas, Chandrasekharan; Noone, Mohan L; Pradeep, Vayyattu G; Blumen, Helena M; Verghese, Joe (J Alzheimers Dis, 2016)
BACKGROUND: The contribution of cerebral small vessel disease to cognitive decline, especially in non-Caucasian populations, is not well established. OBJECTIVE: We examined the relationship between cerebral small vessel disease and motoric cognitive risk syndrome (MCR), a recently described pre-dementia syndrome, in Indian seniors. METHODS: 139 participants (mean age 66.6 ± 5.4 y, 33.1% female) participating in the Kerala-Einstein study in Southern India were examined in a cross-sectional study. The presence of cerebral small vessel disease (lacunar infarcts and cerebral microbleeds (CMB)) and white matter hyperintensities on MRI was ascertained by raters blinded to clinical information. MCR was defined by the presence of cognitive complaints and slow gait in older adults without dementia or mobility disability. RESULTS: Thirty-eight (27.3%) participants met MCR criteria. The overall prevalence of lacunar infarcts and CMB was 49.6% and 9.4% , respectively. Lacunar infarcts in the frontal lobe, but no other brain regions, were associated with MCR even after adjusting for vascular risk factors and presence of white matter hyperintensities (adjusted Odds Ratio (aOR): 4.67, 95% CI: 1.69-12.94). Frontal lacunar infarcts were associated with slow gait (aOR: 3.98, 95% CI: 1.46-10.79) and poor performance on memory test (β: -1.24, 95% CI: -2.42 to -0.05), but not with cognitive complaints or non-memory tests. No association of CMB was found with MCR, individual MCR criterion or cognitive tests. CONCLUSIONS: Frontal lacunar infarcts are associated with MCR in Indian seniors, perhaps, by contributing to slow gait and poor memory function.
Keywords: Aged; Brain; Cerebral Small Vessel Diseases; Cognition Disorders; Female; Humans; Image Processing, Computer-Assisted; India; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Risk Factors; Stroke, Lacunar; White Matter

Cerebrospinal Fluid Alzheimer's Disease Biomarkers in Cerebral Amyloid Angiopathy-Related Inflammation. - Renard, Dimitri; Wacongne, Anne; Ayrignac, Xavier; Charif, Mahmoud; Fourcade, Genevieve; Azakri, Souhayla; Le Floch, Anne; Bouly, Stephane; Marelli, Cecilia; Arquizan, Caroline; Hirtz, Christophe; Gabelle, Audrey; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Decreased cerebrospinal fluid (CSF) amyloid-β 1-40 (Aβ40) and amyloid-β 1-42 (Aβ42) and increased total and phosphorylated tau (t-tau, p-tau) concentrations have been described in cerebral amyloid angiopathy (CAA). OBJECTIVE: Our aim was to analyze these biomarkers in patients with CAA-related inflammation (CAA-I). METHODS: We prospectively recruited nine patients with acute phase CAA-I fulfilling Chung criteria. CSF was analyzed for t-tau, p-tau, Aβ42, and Aβ40. Data were compared to controls (n = 14), patients with Alzheimer's disease (AD, n = 42), CAA (n = 10), and primary angiitis of the central nervous system (PACNS, n = 3). RESULTS: For the CAA-I group, statistically significant differences were: lower Aβ42 (p = 0.00053) compared to the control group; lower t-tau (p = 0.018), p-tau (p <  0.001), and Aβ40 (p <  0.001) compared to AD; lower Aβ42 (p = 0.027) compared to CAA; lower Aβ42 (p = 0.012) compared to PACNS. Nearly significantly lower Aβ40 (p = 0.051) and higher t-tau (p = 0.051) were seen in CAA-I compared to controls. CONCLUSION: CSF biomarkers profile similar to that of CAA was observed in CAA-I (with even lower levels of Aβ42 compared to CAA). Based on our findings, high p-tau seems more specific for AD, whereas low Aβ42 differentiates CAA-I from CAA, PACNS, and controls, and low Aβ40 differentiates CAA-I from AD.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cerebral Amyloid Angiopathy; Female; Humans; Inflammation; Male; Middle Aged; Retrospective Studies; tau Proteins

Cerebrospinal Fluid Anti-Amyloid-β Autoantibodies and Amyloid PET in Cerebral Amyloid Angiopathy-Related Inflammation. - Carmona-Iragui, María; Fernández-Arcos, Ana; Alcolea, Daniel; Piazza, Fabrizio; Morenas-Rodriguez, Estrella; Antón-Aguirre, Sofía; Sala, Isabel; Clarimón, Jordi; Dols-Icardo, Oriol; Camacho, Valle; Sampedro, Frederic; Munuera, Josep; et al. (J Alzheimers Dis, 2016)
We report a biomarker and genetic evaluation of four patients with cerebral amyloid angiopathy-related inflammation (CAA-ri) treated with corticosteroids. Patients presented with focal symptomatology and cognitive impairment. MRI revealed cortical microbleeds and asymmetrical hyperintense white matter lesions (WML). Cerebrospinal fluid (CSF) biomarker analyses showed increased anti-Aβ autoantibodies, t-Tau, and p-Tau and decreased Aβ40 and Aβ42. After treatment, focal symptomatology disappeared, and WML and anti-Aβ autoantibodies decreased. The APOEɛ4 allele was overrepresented. Florbetapir-PET showed cortical deposition with lower retention in swollen areas. In the case of suspected CAA-ri, both CSF anti-Aβ autoantibodies levels and Florbetapir-PET could provide highly useful data to guide the correct diagnosis.
Keywords: Aged; Amyloid beta-Peptides; Aniline Compounds; Apolipoproteins E; Autoantibodies; Cerebral Amyloid Angiopathy; Ethylene Glycols; Female; Humans; Magnetic Resonance Imaging; Male; Meningoencephalitis; Peptide Fragments; Positron-Emission Tomography; Statistics, Nonparametric; tau Proteins

Cerebrospinal Fluid Fatty Acid-Binding Protein 3 is Related to Dementia Development in a Population-Based Sample of Older Adult Women Followed for 8 Years. - Bjerke, Maria; Kern, Silke; Blennow, Kaj; Zetterberg, Henrik; Waern, Margda; Börjesson-Hanson, Anne; Östling, Svante; Kern, Jürgen; Skoog, Ingmar (J Alzheimers Dis, 2016)
BACKGROUND: Increased fatty acid-binding protein 3 (FABP-3) levels have been reported in neurodegenerative diseases, including Alzheimer's disease (AD). Cerebrospinal fluid (CSF) FABP-3 has therefore been proposed as a putative marker for dementia. Population-based studies examining whether CSF FABP-3 predicts later development of dementia are lacking. OBJECTIVE: The aim of this study was to examine CSF levels of FABP-3 in relation to later development of dementia in elderly women and in relation to Aβ42, T-tau, P-tau181, and CSF: serum albumin ratio. METHODS: 86 non-demented women aged 70-84 years who participated in the Prospective Population Study of Women in Gothenburg, Sweden took part in a lumbar puncture in 1992-93. CSF-FABP-3, Aβ42, T-tau, P-tau181, and the CSF: serum albumin ratio were measured at baseline. Participants were examined with a neuropsychiatric exam at baseline and at follow-up in 2000. Dementia was diagnosed in accordance with DSM-III-R criteria. RESULTS: Between 1992 and 2000, 8 women developed dementia (4 AD, 3 vascular dementia, 1 mixed vascular dementia and AD). Higher levels of CSF-FABP-3 at baseline were related to development of dementia (OR 1.36 CI [1.05-1.76] p = 0.022) and the subtype AD (OR 1.38 CI [1.06-1.82), p = 0.019) during follow-up. FABP-3 correlated with CSF T-tau (r = 0.88, p <  0.001), P-tau181 (r = 0.619, p <  0.001), and CSF:serum albumin ratio (r = 0.233, p = 0.031), but not with Aβ42 (r = -0.08, p = 0.444)CONCLUSION:CSF FABP-3 may be an early marker for later development of dementia, probably related to neuronal degeneration, but independent of Aβ metabolism.
Keywords: Aged; Aged, 80 and over; Albumins; Amyloid beta-Peptides; Community Health Planning; Dementia; Fatty Acid-Binding Proteins; Female; Humans; Longitudinal Studies; Peptide Fragments; Sweden; tau Proteins

Cerebrospinal Fluid Markers of Alzheimer's Disease Pathology and Microglial Activation are Associated with Altered White Matter Microstructure in Asymptomatic Adults at Risk for Alzheimer's Disease. - Melah, Kelsey E; Lu, Sharon Yuan-Fu; Hoscheidt, Siobhan M; Alexander, Andrew L; Adluru, Nagesh; Destiche, Daniel J; Carlsson, Cynthia M; Zetterberg, Henrik; Blennow, Kaj; Okonkwo, Ozioma C; Gleason, Carey E; Dowling, N Maritza; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The immune response in Alzheimer's disease (AD) involves activation of microglia which may remove amyloid-β (Aβ). However, overproduction of inflammatory compounds may exacerbate neural damage in AD. AD pathology accumulates years before diagnosis, yet the extent to which neuroinflammation is involved in the earliest disease stages is unknown. OBJECTIVE: To determine whether neuroinflammation exacerbates neural damage in preclinical AD. METHODS: We utilized cerebrospinal fluid (CSF) and magnetic resonance imaging collected in 192 asymptomatic late-middle-aged adults (mean age = 60.98 years). Neuroinflammatory markers chitinase-3-like protein 1 (YKL-40) and monocyte chemoattractant protein-1 (MCP-1) in CSF were utilized as markers of neuroinflammation. Neural cell damage was assessed using CSF neurofilament light chain protein (NFL), CSF total tau (T-Tau), and neural microstructure assessed with diffusion tensor imaging (DTI). With regard to AD pathology, CSF Aβ42 and tau phosphorylated at threonine 181 (P-Tau181) were used as markers of amyloid and tau pathology, respectively. We hypothesized that higher YKL-40 and MCP-1 in the presence of AD pathology would be associated with higher NFL, T-Tau, and altered microstructure on DTI. RESULTS: Neuroinflammation was associated with markers of neural damage. Higher CSF YKL-40 was associated with both higher CSF NFL and T-Tau. Inflammation interacted with AD pathology, such that greater MCP-1 and lower Aβ42 was associated with altered microstructure in bilateral frontal and right temporal lobe and that greater MCP-1 and greater P-Tau181 was associated with altered microstructure in precuneus. CONCLUSION: Inflammation may play a role in neural damage in preclinical AD.
Keywords: Adipokines; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Chemokine CCL2; Chitinase-3-Like Protein 1; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Lectins; Male; Microglia; Middle Aged; Peptide Fragments; tau Proteins; White Matter

Changes in Brain Volume with Bapineuzumab in Mild to Moderate Alzheimer's Disease. - Novak, Gerald; Fox, Nick; Clegg, Shona; Nielsen, Casper; Einstein, Steven; Lu, Yuan; Tudor, Iulia Cristina; Gregg, Keith; Di, Jianing; Collins, Peter; Wyman, Bradley T; Yuen, Eric; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Bapineuzumab, an anti-amyloid-β monoclonal antibody, was evaluated in two placebo-controlled trials in APOE*ɛ4 carriers and noncarriers, respectively, with Alzheimer's disease. OBJECTIVES: A volumetric magnetic resonance imaging substudy was performed to determine if bapineuzumab altered brain volume rate of change. METHODS: Bapineuzumab dosages included 0.5 mg/kg in carriers and 0.5 or 1.0 mg/kg in noncarriers, every 13 weeks for 78 weeks. Volumetric outcomes included annualized brain, ventricular, and mean hippocampal boundary shift integrals (BBSI; VBSI; HBSI) up to Week 71. Treatment differences were estimated using mixed models for repeated measures. RESULTS: For BBSI and HBSI, there were no significant treatment-related differences within either study, but, compared to pooled carriers and noncarriers receiving placebo, noncarriers receiving1.0 mg/kg bapineuzumab had greater increases in these measures. Bapineuzumab-treated patients showed significantly greater VBSI rates compared with placebo for 0.5 mg/kg in carriers and 1.0 mg/kg (but not 0.5 mg/kg) in noncarriers. CONCLUSIONS: Bapineuzumab produced an increase in ventricular volume compared with placebo. Etiology for this increase is unclear but may be related to amyloid-β clearance or its consequences.
Keywords: Aged; Alzheimer Disease; Antibodies, Monoclonal, Humanized; Apolipoprotein E4; Brain; Double-Blind Method; Female; Heterozygote; Humans; Least-Squares Analysis; Magnetic Resonance Imaging; Male; Nootropic Agents; Organ Size; Severity of Illness Index; Treatment Outcome

Characteristics of Alzheimer's Disease Patients with Severe Executive Disorders. - Godefroy, Olivier; Bakchine, Serge; Verny, Marc; Delabrousse-Mayoux, Jean-Philippe; Roussel, Martine; Pere, Jean-Jacques (J Alzheimers Dis, 2016)
BACKGROUND: Executive dysfunctions in Alzheimer's disease (AD) have been assessed using variable batteries and/or in selected populations. OBJECTIVE: The primary objective of this observational study was to determine the prevalence and severity of executive dysfunction in AD patients using a previously validated battery. The secondary objective was to determine the characteristics including treatment outcomes of AD patients with severe executive dysfunction. METHODS: The study included AD patients with mild-to-moderate dementia aged 60 or over, consulting in various clinical settings including memory clinics and requiring the introduction of an antidementia drug. Executive dysfunction was examined using a validated, shortened executive battery. RESULTS: 381 patients were included. Executive dysfunctions were observed in 88.2% of the patients (95% CI: 84.9-91.4) and were severe (defined as ≥2/3 impaired scores) in 80.4% (95% CI: 76.9-84.8). Global hypoactivity with apathy was more frequent (p = 0.0001) than impairment in executive function tests. The 308 patients with severe executive dysfunction were older (p = 0.003) and had more severe dementia (p = 0.0001). Similarly, in the subset of 257 patients with mild dementia, individuals with severe executive dysfunction were older (p = 0.003) and had more severe dementia. Global hypoactivity was independently associated with difficulties in IADL and a higher caregiver burden (p = 0.0001 for both). The severity of executive dysfunction did not significantly influence the patients' outcomes at 6 months. CONCLUSIONS: Executive dysfunction is a very common disorder in a representative population of patients with mild-to-moderate AD. It was independently correlated with impaired autonomy and increased caregiver burden but did not significantly influence treatment outcomes.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Caregivers; Cost of Illness; Executive Function; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Prevalence; Severity of Illness Index; Treatment Outcome

Characterizing Aging, Mild Cognitive Impairment, and Dementia with Blood-Based Biomarkers and Neuropsychology. - Kleinschmidt, Martin; Schoenfeld, Robby; Göttlich, Claudia; Bittner, Daniel; Metzner, Jürgen Erich; Leplow, Bernd; Demuth, Hans-Ulrich (J Alzheimers Dis, 2016)
BACKGROUND: Current treatment in Alzheimer's disease (AD) is initiated at a stage where the brain already has irreversible structural deteriorations. Therefore, the concept of treatment prior to obvious cognitive deficits has become widely accepted, and simple biochemical tests to discriminate normal aging from prodromal or demented stages are now common practice. OBJECTIVE: The objective of the study was the differentiation of controls, mild cognitive impairment (MCI) and AD patients by novel blood-based assays in combination with neuropsychological tests. METHODS: In a cross-sectional study, 143 subjects aged 18 to 85 years were recruited. All participants were classified by a comprehensive neuropsychological assessment. Blood samples were analyzed for several amyloid-β (Aβ) species, pro-inflammatory markers, anti-Aβ autoantibodies, and ApoE allele status, respectively. RESULTS: Plasma Aβ1-42 was significantly decreased in MCI and AD compared to age-matched controls, whereas Aβ1-40 did not differ, but increases with age in healthy controls. The Aβ1-42 to Aβ1-40 ratio was stepwise decreased from age-matched controls via MCI to AD, and shows a clear correlation with memory scores. Reduced Aβ1-42 and Aβ1-42 to Aβ1-40 ratio have strongly correlated with carrying ApoE ɛ4 allele. Autoantibodies against pyroglutamate-modified Aβ, but only a certain subclass, were significantly decreased in AD compared to MCI and age-matched controls, whereas autoantibodies against the unmodified N-terminus of Aβ did not differ. CONCLUSION: Comprehensive sample preparation and assay standardization enable reliable usage of plasma Aβ for diagnosis of MCI and AD. Anti-pGlu-Aβ autoantibodies correlate with cognition, but not with ApoE, supporting the associated plasma Aβ analysis with additional and independent information.
Keywords: Activities of Daily Living; Adolescent; Adult; Aged; Aged, 80 and over; Aging; Amyloid beta-Peptides; Analysis of Variance; Apolipoproteins E; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Cross-Sectional Studies; Cytokines; Dementia; Female; Humans; Male; Memory Disorders; Middle Aged; Neuropsychological Tests; Young Adult

Characterizing White Matter Tract Degeneration in Syndromic Variants of Alzheimer's Disease: A Diffusion Tensor Imaging Study. - Madhavan, Ajay; Schwarz, Christopher G; Duffy, Joseph R; Strand, Edythe A; Machulda, Mary M; Drubach, Daniel A; Kantarci, Kejal; Przybelski, Scott A; Reid, Robert I; Senjem, Matthew L; Gunter, Jeffrey L; Apostolova, Liana G; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Different clinical syndromes can arise from Alzheimer's disease (AD) neuropathology, including dementia of the Alzheimer's type (DAT), logopenic primary progressive aphasia (lvPPA), and posterior cortical atrophy (PCA). OBJECTIVE: To assess similarities and differences in patterns of white matter tract degeneration across these syndromic variants of AD. METHODS: Sixty-four subjects (22 DAT, 24 lvPPA, and 18 PCA) that had diffusion tensor imaging and showed amyloid-β deposition on PET were assessed in this case-control study. A whole-brain voxel-based analysis was performed to assess differences in fractional anisotropy, mean diffusivity, axial diffusivity, and radial diffusivity across groups. RESULTS: All three groups showed overlapping diffusion abnormalities in a network of tracts, including fornix, corpus callosum, posterior thalamic radiations, superior longitudinal fasciculus, inferior longitudinal fasciculus, inferior fronto-occipital fasciculus, and uncinate fasciculus. Subtle regional differences were also observed across groups, with DAT particularly associated with degeneration of fornix and cingulum, lvPPA with left inferior fronto-occipital fasciculus and uncinate fasciculus, and PCA with posterior thalamic radiations, superior longitudinal fasciculus, posterior cingulate, and splenium of the corpus callosum. CONCLUSION: These findings show that while each AD phenotype is associated with degeneration of a specific structural network of white matter tracts, striking spatial overlap exists among the three network patterns that may be related to AD pathology.
Keywords: Aged; Alzheimer Disease; Aniline Compounds; Anisotropy; Aphasia, Primary Progressive; Case-Control Studies; Diffusion Tensor Imaging; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Nerve Fibers, Myelinated; Neurodegenerative Diseases; Neuropsychological Tests; Positron-Emission Tomography; Psychiatric Status Rating Scales; Retrospective Studies; Thiazoles; White Matter

Classification of Neuropsychiatric Symptoms Requiring Antipsychotic Treatment in Patients with Alzheimer's Disease: Analysis of the CATIE-AD Study. - Nagata, Tomoyuki; Shinagawa, Shunichiro; Nakajima, Shinichiro; Plitman, Eric; Mihashi, Yukiko; Hayashi, Shogo; Mimura, Masaru; Nakayama, Kazuhiko (J Alzheimers Dis, 2016)
BACKGROUND: The Neuropsychiatric Inventory (NPI) comprises 12 items, which were conventionally determined by psychopathological symptoms of patients with dementia. The clinical rating scales with structured questionnaires have been useful to evaluate neuropsychiatric symptoms (NPSs) of patients with dementia over the past twenty year. OBJECTIVE: The aim of this study was to classify the conventional NPSs in patients with Alzheimer's disease (AD) requiring antipsychotic treatment for their NPSs into distinct clusters to simplify assessment of these numerous symptoms. METHODS: Twelve items scores (product of severity and frequency of each symptom) in the NPI taken from the baseline visit were classified into subgroups by principle component analysis using data from 421 outpatients with AD enrolled in the Clinical Antipsychotic Trials of Intervention Effectiveness-Alzheimer's Disease (CATIE-AD) Phase 1. Chi square tests were conducted to examine the co-occurrence of the subgroups. RESULTS: We found four distinct clusters: aggressiveness (agitation and irritabilities), apathy and eating problems (apathy and appetite/eating disturbance), psychosis (delusions and hallucinations), and emotion and disinhibition (depression, euphoria, and disinhibition). Anxiety, aberrant motor behavior, and sleep disturbance were not included by these clusters. Apathy and eating problems, and emotion and disinhibition co-occurred (p = 0.002), whereas aggressiveness and psychosis occurred independent of the other clusters. CONCLUSIONS: Four distinct category clusters were identified from NPSs in patients with AD requiring antipsychotic treatment. Future studies should investigate psychosocial backgrounds or risk factors of each distinct cluster, in addition to their longitudinal course over treatment intervention.
Keywords: Aged; Aged, 80 and over; Aggression; Alzheimer Disease; Antipsychotic Agents; Apathy; Cluster Analysis; Female; Humans; Male; Psychiatric Status Rating Scales; Psychomotor Agitation; Psychotic Disorders; Retrospective Studies; Severity of Illness Index

Clearing Amyloid-β through PPARγ/ApoE Activation by Genistein is a Treatment of Experimental Alzheimer's Disease. - Bonet-Costa, Vicent; Herranz-Pérez, Vicente; Blanco-Gandía, MariCarmen; Mas-Bargues, Cristina; Inglés, Marta; Garcia-Tarraga, Patricia; Rodriguez-Arias, Marta; Miñarro, Jose; Borras, Consuelo; Garcia-Verdugo, Jose Manuel; Viña, Jose (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) clearance from brain, which is decreased in Alzheimer's disease, is facilitated by apolipoprotein E (ApoE). ApoE is upregulated by activation of the retinoid X receptor moiety of the RXR/PPARγ dimeric receptor. Genistein, a non-toxic, well-tested, and inexpensive drug activates the other moiety of the receptor PPARγ. Treatment of an Alzheimer's disease mouse model with genistein results in a remarkable and rapid improvement in various parameters of cognition, such as hippocampal learning, recognition memory, implicit memory, and odor discrimination. This is associated with a lowering of Aβ levels in brain, in the number and the area of amyloid plaques (confirmed in vivo by positron emission tomography) as well as in microglial reactivity. Finally, incubation of primary astrocytes with genistein results in a PPARγ-mediated increased release of ApoE. Our results strongly suggest that controlled clinical trials should be performed to test the effect of genistein as treatment of human Alzheimer's disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Apolipoproteins E; Astrocytes; Avoidance Learning; Brain; Cells, Cultured; Disease Models, Animal; Female; Genistein; Habituation, Psychophysiologic; Maze Learning; Mice, Inbred C57BL; Mice, Transgenic; Neuroprotective Agents; Nootropic Agents; Olfactory Perception; Plaque, Amyloid; PPAR gamma; Recognition (Psychology); Tetrahydronaphthalenes

Clinical and Demographic Factors Associated with the Cognitive and Emotional Efficacy of Regular Musical Activities in Dementia. - Särkämö, Teppo; Laitinen, Sari; Numminen, Ava; Kurki, Merja; Johnson, Julene K; Rantanen, Pekka (J Alzheimers Dis, 2016)
Recent evidence suggests that music-based interventions can be beneficial in maintaining cognitive, emotional, and social functioning in persons with dementia (PWDs). Our aim was to determine how clinical, demographic, and musical background factors influence the cognitive and emotional efficacy of caregiver-implemented musical activities in PWDs. In a randomized controlled trial, 89 PWD-caregiver dyads received a 10-week music coaching intervention involving either singing or music listening or standard care. Extensive neuropsychological testing and mood and quality of life (QoL) measures were performed before and after the intervention (n = 84) and six months later (n = 74). The potential effects of six key background variables (dementia etiology and severity, age, care situation, singing/instrument playing background) on the outcome of the intervention were assessed. Singing was beneficial especially in improving working memory in PWDs with mild dementia and in maintaining executive function and orientation in younger PWDs. Music listening was beneficial in supporting general cognition, working memory, and QoL especially in PWDs with moderate dementia not caused by Alzheimer's disease (AD) who were in institutional care. Both music interventions alleviated depression especially in PWDs with mild dementia and AD. The musical background of the PWD did not influence the efficacy of the music interventions. Our findings suggest that clinical and demographic factors can influence the cognitive and emotional efficacy of caregiver-implemented musical activities and are, therefore, recommended to take into account when applying and developing the intervention to achieve the greatest benefit.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Caregivers; Case-Control Studies; Cognition Disorders; Dementia; Executive Function; Female; Follow-Up Studies; Humans; Male; Memory, Short-Term; Middle Aged; Mood Disorders; Music Therapy; Neuropsychological Tests; Orientation; Outcome Assessment (Health Care); Psychiatric Status Rating Scales; Quality of Life

Clinical Dementia Rating Scale Detects White Matter Changes in Older Adults at Risk for Alzheimer's Disease. - Chang, Yu-Ling; Yen, Yu-Shiuan; Chen, Ta-Fu; Yan, Sui-Hing; Tseng, Wen-Yih Isaac (J Alzheimers Dis, 2016)
This study investigated the putative changes in regional gray matter and cingulum bundle segments in mild cognitive impairment (MCI) by using two diagnostic criteria. Participants comprised 50 older adults with MCI and 22 healthy older controls (HC). The older adults with MCI were further divided into two groups defined by a global Clinical Dementia Rating (CDR) score of 0.5 and with (the CDR/NPT MCI group) or without (the CDR MCI group) objective cognitive impairments determined using neuropsychological tests (NPTs). Comparable regional gray matter integrity was observed among the three groups. However, the integrity of the right inferior segment of the cingulum bundle in the two MCI groups was more reduced than that in the HC group, and the CDR/NPT MCI group exhibited additional disruption in the left inferior cingulum bundle. The results also demonstrated that neuropsychological measures have greater predictive value for changes in white matter beyond the contribution of an informant-based instrument alone. Overall, the findings confirm the utility of informant-based assessment in detecting microstructural brain changes in high-risk older adults, even before objective cognitive impairment is evident. The findings also suggest that combining the neuropsychological measures with the informant-based assessment provided the greatest predictive value in assessing white matter disruption. The essential role of the white matter measurement as a biomarker for detecting individuals at a high risk of developing dementia was highlighted.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cognition Disorders; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory; Middle Aged; Neuropsychological Tests; Risk Factors; White Matter

Clinical Impact of a Second FDG-PET in Atypical/Unclear Dementia Syndromes. - Bergeron, David; Beauregard, Jean-Mathieu; Guimond, Jean; Fortin, Marie-Pierre; Houde, Michèle; Poulin, Stéphane; Verret, Louis; Bouchard, Rémi W; Laforce, Robert (J Alzheimers Dis, 2016)
Diagnosis of atypical/unclear dementia is often difficult and this delays treatment initiation. Several authors have shown that beyond standard dementia workup, 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) reduces the number of unclear diagnoses, leads to earlier treatment, and has a beneficial impact on families. However, it is not uncommon that the FDG-PET findings are equivocal in this setting. For those cases, a repeat FDG-PET may clarify the diagnosis and prevent treatment delay. We retrospectively assessed the clinical impact of a repeat FDG-PET in 59 patients with atypical/unclear dementia syndromes and inconclusive initial FDG-PET. Changes in primary diagnosis, diagnostic confidence, and management following the second FDG-PET were examined. Conducting a second FDG-PET reduced the number of unclear diagnoses from 80% to 34% , led to diagnostic change in 24% of cases, and treatment modification in 22% of patients. Overall, the clinical impact was higher when initial diagnostic confidence was low and the second FDG-PET repeated ≥12 months after the first one. In tertiary care memory clinic settings, when diagnostic incertitude persists despite extensive evaluation and an equivocal FDG-PET, repeating the FDG-PET 12 months later can greatly clarify the diagnosis and improve management.
Keywords: Adult; Brain; Dementia; Diagnosis, Differential; Female; Fluorodeoxyglucose F18; Humans; Male; Middle Aged; Positron-Emission Tomography; Radiopharmaceuticals; Retrospective Studies

Clinical utility of the informant AD8 as a dementia case finding instrument in primary healthcare. - Chan, Qun Lin; Xu, Xin; Shaik, Muhammad Amin; Chong, Steven Shih Tsze; Hui, Richard Jor Yeong; Chen, Christopher Li-Hsian; Dong, YanHong (J Alzheimers Dis, 2016)
The informant AD8 has excellent discriminant ability for dementia case finding in tertiary healthcare settings. However, its clinical utility for dementia case finding at the forefront of dementia management, primary healthcare, is unknown. Therefore, we recruited participants from two primary healthcare centers in Singapore and measured their performance on the Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Clinical Dementia Rating (CDR), and a local formal neuropsychological battery, in addition to the AD8. Logistic regression was conducted to examine the associations between demographic factors and dementia. Area under the receiver operating characteristics (ROC) curve analysis was used to establish the optimal cut-off points for dementia case finding. Of the 309 participants recruited, 243 (78.7%) had CDR = 0, 22 (7.1%) CDR = 0.5, and 44 (14.2%) CDR ≥1. Age was strongly associated with dementia, and the optimal age for dementia case finding in primary healthcare settings was ≥75 years. In this age group, the AD8 has excellent dementia case finding capability and was superior to the MMSE and equivalent to the MoCA [AD8 AUC (95% CI): 0.95 (0.91-0.99), cut-off: ≥3, sensitivity: 0.90, specificity: 0.88, PPV: 0.79 and NPV: 0.94; MMSE AUC (95% CI): 0.87 (0.79-0.94), p = 0.04; MoCA AUC (95% CI): 0.88 (0.82-0.95), p = 0.06]. In conclusion, the AD8 is well suited for dementia case finding in primary healthcare settings.
Keywords: Aged; Aged, 80 and over; Dementia; Female; Humans; Language; Logistic Models; Male; Mass Screening; Middle Aged; Neuropsychological Tests; Primary Health Care; Reproducibility of Results; ROC Curve; Sensitivity and Specificity; Singapore; Surveys and Questionnaires

The Cognitive Change Index as a Measure of Self and Informant Perception of Cognitive Decline: Relation to Neuropsychological Tests. - Rattanabannakit, Chatchawan; Risacher, Shannon L; Gao, Sujuan; Lane, Kathleen A; Brown, Steven A; McDonald, Brenna C; Unverzagt, Frederick W; Apostolova, Liana G; Saykin, Andrew J; Farlow, Martin R (J Alzheimers Dis, 2016)
BACKGROUND: The perception of cognitive decline by individuals and those who know them well ("informants") has been inconsistently associated with objective cognitive performance, but strongly associated with depressive symptoms. OBJECTIVE: We investigated associations of self-report, informant-report, and discrepancy between self- and informant-report of cognitive decline obtained from the Cognitive Change Index (CCI) with cognitive test performance and self-reported depressive symptoms. METHODS: 267 participants with normal cognition, mild cognitive impairment (MCI), or mild dementia were included from a cohort study and memory clinic. Association of test performance and self-rated depression (Geriatric Depression Scale, GDS) with CCI scores obtained from subjects (CCI-S), their informants (CCI-I), and discrepancy scores between subjects and informants (CCI-D; CCI-S minus CCI-I) were analyzed using correlation and analysis of covariance (ANCOVA) models. RESULTS: CCI-S and CCI-I scores showed high internal consistency (Cronbach alpha 0.96 and 0.98, respectively). Higher scores on CCI-S and CCI-I, and lower scores on the CCI-D, were associated with lower performance on various cognitive tests in both univariate and in ANCOVA models adjusted for age, gender, and education. Adjustment for GDS slightly weakened the relationships between CCI and test performance but most remained significant. CONCLUSION: Self- and informant-report of cognitive decline, as measured by the CCI, show moderately strong relationships with objective test performance independent of age, gender, education, and depressive symptoms. The CCI appears to be a valid cross-sectional measure of self and informant perception of cognitive decline across the continuum of functioning. Studies are needed to address the relationship of CCI scores to longitudinal outcome.
Keywords: Adult; Aged; Aged, 80 and over; Analysis of Variance; Cognitive Dysfunction; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Perception; Self Report

Cognitive Impairment after Mild Stroke: Development and Validation of the SIGNAL2 Risk Score. - Kandiah, Nagaendran; Chander, Russell Jude; Lin, Xuling; Ng, Aloysius; Poh, Yen Yeong; Cheong, Chin Yee; Cenina, Alvin Rae; Assam, Pryseley Nkouibert (J Alzheimers Dis, 2016)
BACKGROUND: Post stroke cognitive impairment (PSCI), an important complication of strokes, has numerous risk factors. A scale adequately classifying risk of cognitive impairment 3-6 months after mild stroke will be useful for clinicians. OBJECTIVE: To develop a risk score based on clinical and neuroimaging variables that will be useful in identifying mild ischemic stroke patients at high risk for PSCI. METHODS: The risk score development cohort comprised of a retrospective dataset of 209 mild stroke patients with MRI confirmed infarcts, without pre-stroke cognitive impairment, and evaluated within 6 months post-stroke for PSCI. Logistic regression identified factors predictive of PSCI and a risk score was developed based on regression coefficients. The risk score was checked for stability using 10-fold cross-validation and validated in an independent prospective cohort of 185 ischemic mild stroke patients. RESULTS: Within 6 months post-stroke, 37.32% developed PSCI in the retrospective dataset. A 15-point risk score based on age, education, acute cortical infarcts, white matter hyperintensity, chronic lacunes, global cortical atrophy, and intracranial large vessel stenosis was highly predictive of PSCI with an AUC of 0.829. 10.11% with low scores, 52.69% with moderate scores, and 74.07% with high scores developed PSCI. In the prospective validation cohort, the model had an AUC of 0.776, and exhibited similar accuracy and stability statistics at both 6 and 12 months. CONCLUSION: The seven item risk score adequately identified mild stroke patients who are at an increased risk of developing PSCI.
Keywords: Aged; Aging; Area Under Curve; Brain; Brain Ischemia; Cognition Disorders; Constriction, Pathologic; Educational Status; Female; Follow-Up Studies; Humans; Logistic Models; Male; Middle Aged; Prospective Studies; Retrospective Studies; Risk; Severity of Illness Index; Stroke; White Matter

Cognitive Profile and its Association with Neuroimaging Markers of Non-Demented Cerebral Amyloid Angiopathy Patients in a Stroke Unit. - Xiong, Li; Davidsdottir, Sigurros; Reijmer, Yael D; Shoamanesh, Ashkan; Roongpiboonsopit, Duangnapa; Thanprasertsuk, Sekh; Martinez-Ramirez, Sergi; Charidimou, Andreas; Ayres, Alison M; Fotiadis, Panagiotis; Gurol, Edip; Blacker, Deborah L; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Cerebral amyloid angiopathy (CAA) is increasingly recognized as a cause of cognitive impairment in the elderly, but the cognitive profile in patients with the disease has not been well characterized. OBJECTIVE: To characterize the neuropsychological profile of CAA patients without dementia and to determine the association between cognitive performance in different domains and neuroimaging lesions characteristic of CAA. METHODS: Fifty-eight non-demented CAA patients were compared to 138 cognitively normal subjects using a standard neuropsychological test battery. Total brain volume (TBV), white matter hyperintensities, number of lobar cerebral microbleeds, hippocampal volume, and cortical superficial siderosis in all CAA patients were assessed. The association between these neuroimaging markers and neuropsychological performance in different cognitive domains in the CAA group were analyzed. RESULTS: Patients with CAA had significantly worse performance on all individual neuropsychological domains tested, when compared to the cognitive normal group. The cognitive decline of CAA patients was most noticeable in tests for processing speed with a Z score of -1.92±1.56 (mean±SD), then followed by executive function (-0.93±1.01), episodic memory (-0.87±1.29), semantic fluency (-0.73±1.06), and attention (-0.42±0.98). TBV of the CAA patients was correlated with processing speed (β= 0.335, p = 0.03) and executive function (β= 0.394, p = 0.01). CONCLUSIONS: Non-demented patients with CAA had cognitive deficits in multiple areas. Lower TBV was related to slower processing speed and worse executive function.
Keywords: Aged; Atrophy; Brain; Cerebral Amyloid Angiopathy; Cognition; Cognition Disorders; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Stroke

Cohort Effects in the Prevalence and Survival of People with Dementia in a Rural Area in Northern Sweden. - Wimo, Anders; Sjölund, Britt-Marie; Sköldunger, Anders; Qiu, Chengxuan; Klarin, Inga; Nordberg, Gunilla; von Strauss, Eva (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies suggest that trends in cardiovascular risk may result in a decrease in age-specific prevalence of dementia. Studies in rural areas are rare. OBJECTIVES: To study cohort effects in dementia prevalence and survival of people with dementia in a Swedish rural area. METHODS: Participants were from the 1995-1998 Nordanstig Project (NP) (n = 303) and the 2001-2003 Swedish National study on Aging and Care in Nordanstig (SNAC-N) (n = 384). Overall 6-year dementia prevalence and mortality in NP and SNAC-N were compared for people 78 years and older. Logistic regression analyses were used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for dementia occurrence using the NP study population as the reference group. Cox regression models were used to analyze time to death. RESULTS: The crude prevalence of dementia was 21.8% in NP and 17.4% in SNAC-N. When the NP cohort was used as the reference group, the age- and gender-adjusted OR of dementia was 0.71 (95% CI 0.48-1.04) in SNAC-N; the OR was 0.47 (0.24-0.90) for men and 0.88 (0.54-1.44) for women. In the extended model, the OR of dementia was significantly lower in SNAC-N than in the NP cohort as a whole (0.63; 0.39-0.99) and in men (0.34; 0.15-0.79), but not in women (0.81; 0.46-1.44). The Cox regression models indicated that the hazard ratio of dying was lower in the SNAC-N than NP population. CONCLUSIONS: Trends toward a lower prevalence of dementia in high-income countries seem to be evident in this Swedish rural area, at least in men.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Effect; Dementia; Female; Humans; Male; Prevalence; Risk Factors; Rural Population; Sex Factors; Survival Rate; Sweden

Comparing the Effects of Multisensory Stimulation and Individualized Music Sessions on Elderly People with Severe Dementia: A Randomized Controlled Trial. - Sánchez, Alba; Maseda, Ana; Marante-Moar, M Pilar; de Labra, Carmen; Lorenzo-López, Laura; Millán-Calenti, José Carlos (J Alzheimers Dis, 2016)
The objective of this study was to compare the effects of a multisensory stimulation environment (MSSE) and individualized music sessions on agitation, emotional and cognitive status, and dementia severity in a sample of institutionalized patients with severe dementia. Twenty-two participants with a diagnosis of severe or very severe dementia were randomly assigned to two groups: MSSE and individualized music sessions. Both groups participated in two 30-min weekly sessions over 16 weeks. Outcomes were agitation (Cohen-Mansfield Agitation Inventory, CMAI), mood (Cornell Scale for Depression in Dementia, CSDD), anxiety (Rating Anxiety in Dementia, RAID), cognitive function (Severe Mini-Mental State Examination, SMMSE), and the overall severity of dementia (Bedford Alzheimer Nursing Severity Scale, BANS-S). They were assessed at baseline (pre-trial), in the middle (mid-trial), at the end of the intervention (post-trial), and 8 weeks after the intervention (follow-up). Patients in the MSSE group showed significant improvement in their RAID and BANS-S scores compared with the individualized music group post- versus pre-trial. With regard to agitation, there was improvement during the intervention in both the MSSE and individualized music groups in the CMAI total score after 16 weeks of intervention, with no significant differences between the groups. The results suggest that MSSE could have better effects on anxiety symptoms and dementia severity in comparison with individualized music sessions in elderly patients with severe dementia.
Keywords: Affect; Aged; Aged, 80 and over; Anxiety; Cognition; Dementia; Environment; Female; Follow-Up Studies; Humans; Male; Mental Status Schedule; Music Therapy; Precision Medicine; Sensory Art Therapies; Severity of Illness Index; Treatment Outcome

Comparison of Prefrontal Atrophy and Episodic Memory Performance in Dysexecutive Alzheimer's Disease and Behavioral-Variant Frontotemporal Dementia. - Wong, Stephanie; Bertoux, Maxime; Savage, Greg; Hodges, John R; Piguet, Olivier; Hornberger, Michael (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) sometimes presents with prominent executive dysfunction and associated prefrontal cortex atrophy. The impact of such executive deficits on episodic memory performance as well as their neural correlates in AD, however, remains unclear. The aim of the current study was to investigate episodic memory and brain atrophy in AD patients with relatively spared executive functioning (SEF-AD; n = 12) and AD patients with relatively impaired executive functioning (IEF-AD; n = 23). We also compared the AD subgroups with a group of behavioral-variant frontotemporal dementia patients (bvFTD; n = 22), who typically exhibit significant executive deficits, and age-matched healthy controls (n = 38). On cognitive testing, the three patient groups showed comparable memory profiles on standard episodic memory tests, with significant impairment relative to controls. Voxel-based morphometry analyses revealed extensive prefrontal and medial temporal lobe atrophy in IEF-AD and bvFTD, whereas this was limited to the middle frontal gyrus and hippocampus in SEF-AD. Moreover, the additional prefrontal atrophy in IEF-AD and bvFTD correlated with memory performance, whereas this was not the case for SEF-AD. These findings indicate that IEF-AD patients show prefrontal atrophy in regions similar to bvFTD, and suggest that this contributes to episodic memory performance. This has implications for the differential diagnosis of bvFTD and subtypes of AD.
Keywords: Aged; Alzheimer Disease; Atrophy; Databases, Factual; Diagnosis, Differential; Executive Function; Female; Frontotemporal Dementia; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory, Episodic; Middle Aged; Neuropsychological Tests; Prefrontal Cortex

Concanavalin agglutinin levels are decreased in peripheral blood of Alzheimer's disease patients. - Sun, Xuying; Ma, Ronghong; Yao, Xiuqing; Shang, Xiaoling; Wang, Qun; Wang, Jian-Zhi; Liu, Gongping (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) seriously threatens patients' lives and causes severe burden to the families. Early prevention and treatment can alleviate the development of the disease; therefore it is important to find new effective and non-traumatic biomarkers for early diagnosis. In this study, peripheral blood samples were collected from 24 AD patients and the same number of age- and gender-matched control subjects. Lectin reactive glycosylation levels including beta-D-galactosyl ricinus communis agglutinin 120 (RCA), peanut agglutinin (PNA), concanavalin agglutinin (Con A), alpha-L-fucosyl ulex europeus agglutinin (UEA), dolichos biflorus agglutinin (DBA), and galanthus nivalis (GNL), in the red blood cells of peripheral blood were examined by western blotting. We found that lectin levels were altered with aging and gender; some lectin levels were different between AD patients and the control subjects. Only Con A levels were significantly decreased in AD patients compared to age-matched control subjects. These results suggest that Con A levels in peripheral blood may be a potent diagnostic marker for AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Concanavalin A; Female; Humans; Lectins; Male; Plant Lectins

Cost Related to Dementia in the Young and the Impact of Etiological Subtype on Cost. - Kandiah, Nagaendran; Wang, Vivian; Lin, Xuling; Nyu, Mei Mei; Lim, Linda; Ng, Adeline; Hameed, Shahul; Wee, Hwee Lin (J Alzheimers Dis, 2016)
BACKGROUND: Young onset dementia (YOD) presents in individuals who are economically productive and socially active. While the cost related to dementia in the elderly has been widely studied, the cost related to YOD is largely unknown. OBJECTIVE: To study the economic burden of community dwelling YOD in relation to late onset dementia (LOD) and cost of YOD based on etiology. METHODS: In this prospective cross-sectional study of 255 patients attending a tertiary neurology center, data on economic burden, clinical features, and caregiver burden were collected using structured financial questionnaire, standard cognitive and neuropsychiatric measures, and Zarit caregiver burden scale. Cost components were grouped into those relating to direct medical costs, direct non-medical costs, and those related to indirect costs. Cost was also categorized based on etiology of YOD. RESULTS: The mean age at symptom onset in the YOD and LOD cohort was 57.0 (SD 5.1) and 75.0 (SD 5.9) years, respectively. The median annual cost for patients with YOD was almost twice that of LOD (USD 15,815 versus USD 8,396). Indirect cost contributed heavily to cost related to YOD. Even when grouped by dementia etiology, YOD patients with Alzheimer's disease, frontotemporal dementia (FTD), and vascular dementia had higher cost compared to their elderly counterparts. Young onset FTD had the highest cost. 43.2% of YOD reported loss of employment due to dementia, which was significantly higher than that in LOD (2.4%). CONCLUSION: Patients with YOD have a high economic burden. Young patients with FTD have the highest cost followed by vascular dementia and Alzheimer's disease.
Keywords: Age of Onset; Aged; Cohort Studies; Costs and Cost Analysis; Cross-Sectional Studies; Dementia; Female; Humans; Independent Living; Male; Mental Disorders; Middle Aged; Perceptual Disorders; Prospective Studies; Psychiatric Status Rating Scales; Severity of Illness Index; Surveys and Questionnaires; Young Adult

Course and Determinants of Anosognosia in Alzheimer's Disease: A 12-Month Follow-up. - Turró-Garriga, Oriol; Garre-Olmo, Josep; Calvó-Perxas, Laia; Reñé-Ramírez, Ramón; Gascón-Bayarri, Jordi; Conde-Sala, Josep Lluís (J Alzheimers Dis, 2016)
Anosognosia in Alzheimer's disease (AD) has been associated with greater cognitive impairment and more behavioural and psychological symptoms of dementia (BPSD). This study examines the incidence, persistence, and remission rates of anosognosia over a 12-month period, as well as the related risk factors. This was an observational 12-month prospective study. The longitudinal sample comprised 177 patients with mild or moderate AD, and their respective caregivers. Anosognosia was assessed using the Anosognosia Questionnaire in Dementia, and we also evaluated cognitive status (Mini-Mental State Examination), functional disability (Disability Assessment in Dementia), and the presence of BPSD (Neuropsychiatric Inventory). Multinomial logistic regression was used to determine the variables associated with the incidence, persistence and remission of anosognosia. The prevalence of anosognosia was 39.5% (95% CI = 32.1-47.1) at baseline. At 12 months, incidence was 38.3% (95% CI = 28.6-48.0), persistence was 80.0% (95% CI = 69.9-90.1) and remission was 20.0% (95% CI = 9.9-30.1). The regression model identified lower age, more education, and the presence of delusions as variables associated with incidence, and more education, lower instrumental DAD score, and disinhibition as variables associated with persistence. No variables were associated with remission (n = 14). The presence of anosognosia in AD patients is high. Education and certain neuropsychiatric symptoms may explain a greater and earlier incidence of anosognosia. However, anosognosia also increases with greater cognitive impairment and disease severity.
Keywords: Age Factors; Aged; Agnosia; Alzheimer Disease; Disability Evaluation; Disease Progression; Educational Status; Female; Follow-Up Studies; Humans; Incidence; Logistic Models; Longitudinal Studies; Male; Mental Status Schedule; Neuropsychological Tests; Prevalence; Prospective Studies; Risk Factors; Severity of Illness Index

Decreased Inter-Hemispheric Functional Connectivity in Cognitively Intact Elderly APOE ɛ4 Carriers: A Preliminary Study. - Luo, Xiao; Qiu, Tiantian; Xu, Xiaojun; Huang, Peiyu; Gu, Quanquan; Shen, Zhujing; Yu, Xinfeng; Jia, YunLu; Guan, Xiaojun; Song, Ruirui; Zhang, Minming (J Alzheimers Dis, 2016)
The apolipoprotein E (APOE) ɛ4 allele is the best-known genetic risk factor for developing sporadic Alzheimer's disease (AD). According to neuroimaging studies, the APOE ɛ4 allele is associated with localized altered brain function. However, in long-range circuitry, APOE ɛ4 allele-related alterations in functional communication between hemispheres have rarely been directly investigated. We examined the alteration of resting-state functional connectivity (RSFC) between inter-hemispheric homotopic regions in cognitively intact, elderly APOE ɛ4 carriers. The voxel-mirrored homotopic connectivity method was used to assess the inter-hemispheric RSFC. The current study included 13 cognitively intact, elderly APOE ɛ4 carriers (with at least one copy of APOE ɛ4 allele) and 22 well-matched ɛ3 homozygotes. Comparisons between the two groups were conducted, and subsequently, the correlation between the differential inter-hemispheric RSFC and cognitive ability was analyzed. Compared with ɛ3 homozygotes, APOE ɛ4 carriers showed decreased inter-hemispheric RSFC in the bilateral medial temporal lobe (MTL) and orbital frontal cortex (OFC). Moreover, in APOE ɛ4 carriers, the inter-hemispheric RSFC of the MTL correlated with the Wechsler Memory Scale-Logical Memory (WMS-LM) (immediate and delayed performance, r = 0.64, p <  0.05; r = 0.65, p <  0.05, respectively), and the inter-hemispheric RSFC of the OFC correlated with the WMS-LM delayed performance (r = 0.71, p <  0.05). In our study, the presence of the APOE ɛ4 allele was linked with decreased inter-hemispheric RSFC, which was attributed to memory performance in carriers.
Keywords: Aged; Aging; Apolipoprotein E4; Brain; Brain Mapping; Female; Functional Laterality; Genotyping Techniques; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Memory; Neuropsychological Tests; Rest

Decreased Levels of VAMP2 and Monomeric Alpha-Synuclein Correlate with Duration of Dementia. - Vallortigara, Julie; Whitfield, David; Quelch, William; Alghamdi, Amani; Howlett, David; Hortobágyi, Tibor; Johnson, Mary; Attems, Johannes; O'Brien, John T; Thomas, Alan; Ballard, Clive G; Aarsland, Dag; et al. (J Alzheimers Dis, 2016)
Alpha-synuclein (α-syn) aggregations are the key pathological hallmark of dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD), but are also frequently present in Alzheimer's disease (AD). Much remains unknown about the role of α-syn in the synapse and the wider role of synaptic dysfunction in these dementias. Changes in concentrations of key 'SNAP (Soluble N-ethylmaleimide Sensitive Factor Attachment Protein) Receptor' (SNARE) proteins as a consequence of alterations in the aggregation state of α-syn may contribute to synaptic dysfunction in patients with DLB, PDD, and AD and result in impaired cognition. We have studied a large cohort (n = 130) of autopsy confirmed DLB, PDD, AD, and control brains. Using semi-quantitative western blotting, we have demonstrated significant changes across the diagnostic groups of DLB, PDD, and AD in the SNARE and vesicle proteins syntaxin, Munc18, VAMP2, and monomeric α-syn in the prefrontal cortex, with a significant reduction of Munc18 in AD patients (p <  0.001). This correlated to the final MMSE score before death (p = 0.016). We also identified a significant negative correlation between the duration of dementia and the levels of the binding partners VAMP2 (p = 0.0004) and monomeric α-syn (p = 0.0002). Our findings may indicate that an upregulation of SNARE complex related proteins occurs in the early stages of disease as an attempt at compensating for failing synapses, prior to widespread deposition of pathological α-syn.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Amyloid beta-Peptides; Analysis of Variance; Cognition Disorders; Dementia; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Regression Analysis; Synaptophysin; tau Proteins; Vesicle-Associated Membrane Protein 2

Delusions in Patients with Alzheimer's Disease: A Multidimensional Approach. - D'Onofrio, Grazia; Panza, Francesco; Sancarlo, Daniele; Paris, Francesco F; Cascavilla, Leandro; Mangiacotti, Antonio; Lauriola, Michele; Paroni, Giulia H; Seripa, Davide; Greco, Antonio (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD) patients with delusions, clinical outcomes and mortality result from a combination of psychological, biological, functional, and environmental factors. We determined the effect of delusions on mortality risk, clinical outcomes linked to comprehensive geriatric assessment (CGA), cognitive, depressive, and neuropsychiatric symptoms (NPS) in 380 consecutive AD patients with Mini-Mental State Examination, Clinical Dementia Rating scale, 15-item Geriatric Depression Scale, and Neuropsychiatric Inventory (NPI), assessing one-year mortality risk using the Multidimensional Prognostic Index (MPI). We included 121 AD patients with delusions (AD-D) and 259 AD patients without delusions (AD-noD). AD-D patients were significantly older, with higher age at onset and cognitive impairment, a more severe stage of dementia, and more depressive symptoms than AD-noD patients. Disease duration was slightly higher in AD-D patients than in those without delusions, although this difference was not statistically significant. At CGA, AD-D patients showed a higher grade of disability in basic and instrumental activities of daily living, and an increased risk of malnutrition and bedsores. The two groups of patients significantly differed in MPI score (AD-D: 0.65 versus AD-noD: 0.51, p <  0.0001) and MPI grade. AD-D patients showed also a significant higher score in NPI of the following NPS than AD-noD patients: hallucinations, agitation/aggression, depression mood, apathy, irritability/lability, aberrant motor activity, sleep disturbances, and eating disorders. Therefore, AD-D patients showed higher dementia severity, and higher impairment in cognitive and depressive symptoms, and several neuropsychiatric domains than AD-noD patients, and this appeared to be associated with higher multidimensional impairment and increased risk of mortality.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Delusions; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Prognosis; Risk; Severity of Illness Index; Time Factors

Dementia Apraxia Test (DATE): A Brief Tool to Differentiate Behavioral Variant Frontotemporal Dementia from Alzheimer's Dementia Based on Apraxia Profiles. - Johnen, Andreas; Frommeyer, Jana; Modes, Fenja; Wiendl, Heinz; Duning, Thomas; Lohmann, Hubertus (J Alzheimers Dis, 2016)
BACKGROUND: Standardized praxis assessments with modern, empirically validated screening tests have substantially improved clinical evaluation of apraxia in patients with stroke. Although apraxia may contribute to early differential diagnosis of Alzheimer's dementia (AD) and behavioral variant frontotemporal dementia (bvFTD), no comparable test is readily available to clinicians for this purpose to date. OBJECTIVE: To design a clinically useful apraxia test for the differentiation of AD and bvFTD. METHODS: 84 test items pertaining to twelve praxis subdomains were evaluated for their efficacy to discriminate between patients with bvFTD (n = 24), AD (n = 28), and elderly healthy controls (HC; n = 35). Items were then selected based on discriminative value and psychometric properties. RESULTS: Items indicative of mild AD comprised spatially complex imitation of hand and finger postures and to a lesser degree, pantomime of common object-use. Buccofacial apraxia including imitation of face postures, emblematic face postures, and repetition of multisyllabic pseudowords differentiated bvFTD from HC and AD. The final test version consisting of 20 items proved highly efficient for the discrimination of biologically confirmed dementia patients from HC (sensitivity 91% , specificity 71%) but also for differential diagnosis of bvFTD and AD (sensitivity 74% , specificity 93%). CONCLUSIONS: Assessment of praxis profiles effectively contributes to diagnosis and differential diagnosis of AD and bvFTD. The Dementia Apraxia Test (DATE) is a brief and easy to administer cognitive tool for dementia assessment, has a high inter-rater reliability (Cohen's κ= 0.885) and demonstrates content validity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Apraxias; Diagnosis, Differential; Female; Frontotemporal Dementia; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Psychometrics; Reference Values

Depressive Symptoms and Small Hippocampal Volume Accelerate the Progression to Dementia from Mild Cognitive Impairment. - Chung, Jun Ku; Plitman, Eric; Nakajima, Shinichiro; Chakravarty, M Mallar; Caravaggio, Fernando; Takeuchi, Hiroyoshi; Gerretsen, Philip; Iwata, Yusuke; Patel, Raihaan; Mulsant, Benoit H; Graff-Guerrero, Ariel (J Alzheimers Dis, 2016)
Previous studies have highlighted that decreased hippocampal volume, an early neural correlate of dementia, is commonly observed in patients with mild cognitive impairment (MCI). However, it is unclear whether neurodegenerative and resultant clinical trajectories are accelerated in MCI patients with concomitant depressive symptoms, leading to a faster conversion to dementia stages than those who are not depressed. No longitudinal study has investigated whether depressed amnestic MCI (DEP+aMCI) patients show an earlier onset of progression to dementia than non-depressed amnestic MCI (DEP-aMCI) patients and whether progressive hippocampal volume reductions are related in the conversion process. Using data from Alzheimer's Disease Neuroimaging Initiative, we examined 2-year follow-up data from 38 DEP+aMCI patients and 38 matched DEP-aMCI patients and compared their ages of conversion from aMCI to AD and trajectories of progressive hippocampal volume changes. DEP+ and DEP- patients were defined as having baseline Geriatric Depression Scale scores of 5 or above and 0, respectively. DEP+ converters showed earlier ages of conversion to dementia (p = 0.009) and greater left hippocampal volume loss than both DEP- converters and DEP+ non-converters over the 2-year period (p = 0.003, p = 0.001, respectively). These findings could not be explained by changes in total brain volume, differences in their clinical symptoms of dementia, daily functioning, or apolipoprotein E4 genotypes. No difference in conversion rate to dementia or progressive hippocampal volume change was found between DEP+ patients and DEP-patients, which suggested depressive symptoms themselves may not lead to progression of dementia from MCI. In conclusion, there is a synergistic effect of depressive symptoms and smaller left hippocampal volume in MCI patients that accelerates conversion to dementia.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Dementia; Depression; Disease Progression; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Psychiatric Status Rating Scales

Detection of Alzheimer's Disease by Three-Dimensional Displacement Field Estimation in Structural Magnetic Resonance Imaging. - Wang, Shuihua; Zhang, Yudong; Liu, Ge; Phillips, Preetha; Yuan, Ti-Fei (J Alzheimers Dis, 2016)
BACKGROUND: Within the past decade, computer scientists have developed many methods using computer vision and machine learning techniques to detect Alzheimer's disease (AD) in its early stages. OBJECTIVE: However, some of these methods are unable to achieve excellent detection accuracy, and several other methods are unable to locate AD-related regions. Hence, our goal was to develop a novel AD brain detection method. METHODS: In this study, our method was based on the three-dimensional (3D) displacement-field (DF) estimation between subjects in the healthy elder control group and AD group. The 3D-DF was treated with AD-related features. The three feature selection measures were used in the Bhattacharyya distance, Student's t-test, and Welch's t-test (WTT). Two non-parallel support vector machines, i.e., generalized eigenvalue proximal support vector machine and twin support vector machine (TSVM), were then used for classification. A 50 × 10-fold cross validation was implemented for statistical analysis. RESULTS: The results showed that "3D-DF+WTT+TSVM" achieved the best performance, with an accuracy of 93.05 ± 2.18, a sensitivity of 92.57 ± 3.80, a specificity of 93.18 ± 3.35, and a precision of 79.51 ± 2.86. This method also exceled in 13 state-of-the-art approaches. Additionally, we were able to detect 17 regions related to AD by using the pure computer-vision technique. These regions include sub-gyral, inferior parietal lobule, precuneus, angular gyrus, lingual gyrus, supramarginal gyrus, postcentral gyrus, third ventricle, superior parietal lobule, thalamus, middle temporal gyrus, precentral gyrus, superior temporal gyrus, superior occipital gyrus, cingulate gyrus, culmen, and insula. These regions were reported in recent publications. CONCLUSIONS: The 3D-DF is effective in AD subject and related region detection.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Brain Mapping; Datasets as Topic; Female; Humans; Imaging, Three-Dimensional; Machine Learning; Magnetic Resonance Imaging; Male

Development and Validation of the RxDx-Dementia Risk Index to Predict Dementia in Patients with Type 2 Diabetes and Hypertension. - Mehta, Hemalkumar B; Mehta, Vinay; Tsai, Chu-Lin; Chen, Hua; Aparasu, Rajender R; Johnson, Michael L (J Alzheimers Dis, 2016)
BACKGROUND: Elderly patients with type 2 diabetes mellitus and hypertension are at high risk for developing dementia. In addition to comorbid disease conditions (Dx), prescription drugs (Rx) are important risk factors for dementia. OBJECTIVE: Develop and validate the RxDx-Dementia risk index by combining diagnosis and prescription information in a single risk index to predict incident dementia, and compare its performance with diagnosis-based Charlson comorbidity score (CCS) and prescription-based chronic disease score (CDS). METHODS: Elderly patients diagnosed with type 2 diabetes mellitus and hypertension, and without prior dementia were identified from the Clinical Practice Research Datalink (2003-2012). A Cox proportional hazard model was constructed to model the time to dementia by incorporating age, gender, and 31 RxDx disease conditions as independent variables. Points were assigned to risk factors to obtain summary risk score. Discrimination and calibration of the risk index were evaluated. Different risk indices were compared against RxDx-Dementia risk index using c-statistic, net reclassification improvement (NRI) and integrated discrimination improvement (IDI). RESULTS: Of 133,176 patients with type 2 diabetes mellitus and hypertension, 3.42% patients developed dementia.The c-statistics value for RxDx-Dementia risk index was 0.806 (95% CI, 0.799-0.812). Based on the c-statistics, NRI and IDI values, the RxDx-Dementia risk index performed better compared to CCS, CDS, and their combinations. CONCLUSION: The RxDx-Dementia risk index can be a useful tool to identify hypertensive and diabetic patients who are at high risk of developing dementia. This has implications for clinical management of patients with multiple comorbid conditions as well as risk adjustment for database studies.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Dementia; Diabetes Mellitus, Type 2; Female; Humans; Hypertension; Male; Middle Aged; Predictive Value of Tests; Prescription Drugs; Proportional Hazards Models; Reproducibility of Results; Risk Assessment; Risk Factors

Development of a Standardized Approach to Disclosing Amyloid Imaging Research Results in Mild Cognitive Impairment. - Lingler, Jennifer H; Butters, Meryl A; Gentry, Amanda L; Hu, Lu; Hunsaker, Amanda E; Klunk, William E; Mattos, Meghan K; Parker, Lisa A; Roberts, J Scott; Schulz, Richard (J Alzheimers Dis, 2016)
The increased use of PET amyloid imaging in clinical research has sparked numerous concerns about whether and how to return such research test results to study participants. Chief among these is the question of how best to disclose amyloid imaging research results to individuals who have cognitive symptoms that could impede comprehension of the information conveyed. We systematically developed and evaluated informational materials for use in pre-test counseling and post-test disclosures of amyloid imaging research results in mild cognitive impairment (MCI). Using simulated sessions, persons with MCI and their family care partners (N = 10 dyads) received fictitious but realistic information regarding brain amyloid status, followed by an explanation of how results impact Alzheimer's disease risk. Satisfaction surveys, comprehension assessments, and focus group data were analyzed to evaluate the materials developed. The majority of persons with MCI and their care partners comprehended and were highly satisfied with the information presented. Focus group data reinforced findings of high satisfaction and included 6 recommendations for practice: 1) offer pre-test counseling, 2) use clear graphics, 3) review participants' own brain images during disclosures, 4) offer take-home materials, 5) call participants post-disclosure to address emerging questions, and 6) communicate seamlessly with primary care providers. Further analysis of focus group data revealed that participants understood the limitations of amyloid imaging, but nevertheless viewed the prospect of learning one's amyloid status as valuable and empowering.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Brain; Brain Chemistry; Cognitive Dysfunction; Disclosure; Family; Female; Focus Groups; Health Communication; Humans; Male; Middle Aged; Patient Satisfaction; Pilot Projects; Positron-Emission Tomography

Diagnostic Impact of Cerebrospinal Fluid Biomarker (Pre-)Analytical Variability in Alzheimer's Disease. - Niemantsverdriet, Ellis; Goossens, Joery; Struyfs, Hanne; Martin, Jean-Jacques; Goeman, Johan; De Deyn, Peter Paul; Vanderstichele, Hugo; Engelborghs, Sebastiaan (J Alzheimers Dis, 2016)
Intra- and inter-laboratory variability of cerebrospinal fluid (CSF) biomarker analyses remains an important issue. We investigated the clinical-diagnostic impact of CSF biomarker concentration shifts in mild cognitive impairment (MCI) and autopsy-confirmed Alzheimer's disease (AD) dementia patients. MCI patients (n = 85), autopsy-confirmed AD dementia patients (n = 72), and cognitively healthy controls (n = 100) were included in this prospective, longitudinal study. AD dementia patients were followed up until death, and controls were included from 1992 until 2003. In-house validated cutoff values of biomarkers were applied: Aβ1-42 <638.5 pg/mL, T-tau>296.5 pg/mL, P-tau(181P) >56.5 pg/mL. Both increments and decrements (from ± 5% to ± 40% ) were added to the true (=observed) CSF biomarker values, imitating the anticipated differences in biomarker concentrations. Within certain limits, the clinical diagnostic performance of AD CSF biomarkers remains largely unchanged and clinical diagnostic accuracy deviated less than 8.2% from the reference when concentration shifts ranging between -20% and +20% were added to one of the three CSF biomarkers in MCI and autopsy-confirmed AD patients. Notwithstanding the fact that (pre- and post-)analytical parameters can affect the clinical classification, the present exploratory study provides evidence that for a specific context of use, the impact on clinical accuracy of biomarker concentration shifts might be lower than originally expected. In conclusion, induced shifts of ±20% in only one of the three biomarkers has limited impact on the clinical accuracy of AD CSF biomarkers in MCI and autopsy-confirmed AD patients when using the IWG-2 criteria.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Autopsy; Cognitive Dysfunction; Enzyme-Linked Immunosorbent Assay; Exercise; Female; Follow-Up Studies; Humans; Male; Middle Aged; Peptide Fragments; Psychiatric Status Rating Scales; Retrospective Studies; Statistics, Nonparametric; tau Proteins

Diagnostic Value of Cerebrospinal Fluid Biomarkers (Phospho-Tau181, total-Tau, Aβ42, and Aβ40) in Prodromal Stage of Alzheimer's Disease and Dementia with Lewy Bodies. - Bousiges, Olivier; Cretin, Benjamin; Lavaux, Thomas; Philippi, Nathalie; Jung, Barbara; Hezard, Sylvie; Heitz, Camille; Demuynck, Catherine; Gabel, Aurelia; Martin-Hunyadi, Catherine; Blanc, Frédéric (J Alzheimers Dis, 2016)
BACKGROUND: Dementia with Lewy bodies (DLB) symptoms are close to those of Alzheimer's disease (AD), and the differential diagnosis is difficult especially early in the disease. Unfortunately, AD biomarkers in cerebrospinal fluid (CSF), and more particularly Aβ1 - 42, appear to be altered in dementia with Lewy bodies (DLB). However, the level of these biomarkers has never been studied in the prodromal stage of the disease. OBJECTIVE: To compare these biomarkers between DLB and AD, with a particular focus on the prodromal stage. METHODS: A total of 166 CSF samples were collected at the memory clinic of Strasbourg. They were obtained from prodromal DLB (pro-DLB), DLB dementia, prodromal AD (pro-AD), and AD dementia patients, and elderly controls. Phospho-Tau181, total-Tau, Aβ42, and Aβ40 were measured in the CSF. RESULTS: At the prodromal stage, contrary to AD patients, DLB patients' biomarker levels in the CSF were not altered. At the demented stage of DLB, Aβ42 levels were reduced as well as Aβ40 levels. Thus, the Aβ42/Aβ40 ratio remained unchanged between the prodromal and demented stages, contrary to what was observed in AD. Tau and Phospho-Tau181 levels were unaltered in DLB patients. CONCLUSIONS: We have shown that at the prodromal stage the DLB patients had no pathological profile. Consequently, CSF AD biomarkers are extremely useful for differentiating AD from DLB patients particularly at this stage when the clinical diagnosis is difficult. Thus, these results open up new perspectives on the interpretation of AD biomarkers in DLB.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Enzyme-Linked Immunosorbent Assay; Female; Humans; Lewy Body Disease; Male; Middle Aged; Peptide Fragments; Prodromal Symptoms; Psychiatric Status Rating Scales; Retrospective Studies; Statistics, Nonparametric; tau Proteins

Different Expression Patterns of Amyloid-β Protein Precursor Secretases in Human and Mouse Hippocampal Neurons: A Potential Contribution to Species Differences in Neuronal Susceptibility to Amyloid-β Pathogenesis. - Xu, Zhi-Qiang; Huang, Huang; Chen, Ya-Li; Gao, Yun-Ying; Xu, Jun; Marshall, Charles; Cai, Zhi-You; Xiao, Ming (J Alzheimers Dis, 2016)
Extensive loss of hippocampal neurons serves a pathological basis for irreversible cognitive impairment in patients with Alzheimer's disease (AD). However, this characteristic cannot be replicated by transgenic mouse models, and its underlying mechanisms are unclear. Here, we present evidence that different expression patterns of amyloid-β protein precursor (AβPP) secretases in human and mouse hippocampal neurons are a decisive cause of species difference in the susceptibility to Aβ pathogenesis. Cell bodies of both pyramidal and granular neurons did not appear to undergo Aβ deposits in the 10-month-old transgenic mutant human AβPP/presenilin-1 (PS1) mice. They expressed high levels of non-amyloidogenic α-secretase, and its neuroprotective products soluble AβPPα, but low levels of amyloidogenic β-secretase and γ-secretase, and a neurotoxic product, Aβ42 peptide. Unlike those found in the mouse, human hippocampal neuronal cell bodies expressed β-secretase and γ-secretase, but not α-secretase, which could increase Aβ generation, thus undergoing death in response to various pathological conditions. Increased hippocampal neuronal apoptosis at 48 h following local microinjection of α-secretase antibody ADAM10 into the hippocampus of AβPP/PS1 mice further suggests that high α-secretase expression in mouse neuronal cell bodies is a factor in the paucity of neuronal loss in AD-like pathology. Therefore, selective down-regulation of brain α-secretase in transgenic AD models will better replicate the disease spectrum, including decreased brain soluble AβPPα levels and massive neuronal loss in AD patients, and be beneficial for preclinical therapeutic evaluation of AD.
Keywords: ADAM10 Protein; Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Animals; Antibodies; Aspartic Acid Endopeptidases; Cell Count; Dose-Response Relationship, Drug; Female; Gene Expression Regulation; Hippocampus; Humans; Low Density Lipoprotein Receptor-Related Protein-1; Male; Mice; Mice, Transgenic; Middle Aged; Mutation; Neurons; Peptide Fragments; Presenilin-1; Species Specificity; Time Factors

Different Patterns of Correlation between Grey and White Matter Integrity Account for Behavioral and Psychological Symptoms in Alzheimer's Disease. - Makovac, Elena; Serra, Laura; Spanò, Barbara; Giulietti, Giovanni; Torso, Mario; Cercignani, Mara; Caltagirone, Carlo; Bozzali, Marco (J Alzheimers Dis, 2016)
Behavioral disorders and psychological symptoms (BPSD) in Alzheimer's disease (AD) are known to correlate with grey matter (GM) atrophy and, as shown recently, also with white matter (WM) damage. WM damage and its relationship with GM atrophy are reported in AD, reinforcing the interpretation of the AD pathology in light of a disconnection syndrome. It remains uncertain whether this disconnection might account also for different BPSD observable in AD. Here, we tested the hypothesis of different patterns of association between WM damage of the corpus callosum (CC) and GM atrophy in AD patients exhibiting one of the following BPSD clusters: Mood (i.e., anxiety and depression; ADmood), Frontal (i.e., dishinibition and elation; ADfrontal), and Psychotic (delusions and hallucinations; ADpsychotic) related symptoms, as well as AD patients without BPSD. Overall, this study brings to light the strict relationship between WM alterations in different parts of the CC and GM atrophy in AD patients exhibiting BPSD, supporting the hypothesis that such symptoms are likely to be caused by characteristic patterns of neurodegeneration of WM and GM, rather than being a reactive response to accumulation of cognitive disabilities, and should therefore be regarded as potential markers of diagnostic and prognostic value in AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Brain; Depression; Female; Gray Matter; Hallucinations; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; White Matter

Differential Diagnosis of Dementia with High Levels of Cerebrospinal Fluid Tau Protein. - Grangeon, Lou; Paquet, Claire; Bombois, Stephanie; Quillard-Muraine, Muriel; Martinaud, Olivier; Bourre, Bertrand; Lefaucheur, Romain; Nicolas, Gaël; Dumurgier, Julien; Gerardin, Emmanuel; Jan, Mary; Laplanche, Jean-Louis; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Total Tau concentration in cerebrospinal fluid (CSF) is widely used as a biomarker in the diagnosis of neurodegenerative process primarily in Alzheimer's disease (AD). A particularly high Tau level may indicate AD but may also be associated with Creutzfeldt-Jakob disease (CJD). In such situations little is known about the distribution of differential diagnoses. OBJECTIVE: Our study aimed to describe the different diagnoses encountered in clinical practice for patients with dementia and CSF Tau levels over 1000 pg/ml. We studied the p-Tau/Tau ratio to specify its ability to distinguish AD from CJD. METHODS: Patients (n = 202) with CSF Tau levels over 1000 pg/ml were recruited in three memory clinics in France. All diagnoses were made using the same diagnostic procedure and criteria. RESULTS: Patients were diagnosed with AD (n = 148, 73.2%), mixed dementia (n = 38, 18.8%), CJD, vascular dementia (n = 4, 2.0% for each), Lewy body dementia, and frontotemporal dementia (n = 3, 1.5% for each). Dispersion of CSF Tau levels clearly showed an overlap between all diagnoses. Using the p-Tau/Tau ratio suggestive of CJD (<0.075), all CJD patients were correctly categorized and only two AD patients were miscategorized. This ratio was highly associated with CJD compared to AD (p < 0.0001). CONCLUSION: Our study showed that in clinical practice, extremely high CSF Tau levels are mainly related to diagnosis of AD. CJD patients represent a minority. Our results support a sequential interpretation algorithm for CSF biomarkers in dementia. High CSF Tau levels should alert clinicians to check the p-Tau/Tau ratio to consider a probable diagnosis of CJD.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Creutzfeldt-Jakob Syndrome; Dementia, Vascular; Diagnosis, Differential; Female; France; Frontotemporal Dementia; Humans; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged; Phosphorylation; Retrospective Studies; Sex Factors; tau Proteins

Differential Impairment of Cognitive and Affective Mentalizing Abilities in Neurodegenerative Dementias: Evidence from Behavioral Variant of Frontotemporal Dementia, Alzheimer's Disease, and Mild Cognitive Impairment. - Dodich, Alessandra; Cerami, Chiara; Crespi, Chiara; Canessa, Nicola; Lettieri, Giada; Iannaccone, Sandro; Marcone, Alessandra; Cappa, Stefano F; Cacioppo, John T (J Alzheimers Dis, 2016)
Cognitive and affective theory of mind (ToM) can be impaired in the course of neurodegenerative dementias. Experimental tests based on different task conditions and/or complexity may fail to capture disease-specific patterns of impairments. In this study, we assessed with a single task both the affective and the cognitive facets of ToM ability in a sample of 47 patients (i.e., 12 AD, 20 bvFTD, and 15 aMCI fulfilling IWG criteria for AD in predementia phase) and 65 healthy controls. Subjects were administered the Story-based Empathy task (SET), a non-verbal task measuring the ability to infer others' intentions (IA) and emotions (EA) compared to a control condition (causal inferences, CI). Global and single sub-condition scores were evaluated with a vectorial method, analyzing the relationship between social abilities and basic cognitive functioning by means of two indices representing the basic ability to perform the task and the balance between basic functions and ToM skills.Dementia (AD and bvFTD) patients showed impaired performances on all SET sub-conditions, whereas aMCI subjects' performance was not different from healthy controls. Vectorial analysis revealed a specific change in the balance between EA and CI conditions only in the bvFTD group, supporting a disproportionate deficit in mental states attribution based on affective cues. The overall deficit in the task in AD appears to be more general and related to the severity of dementia. This latter finding is further supported by the normal performance of the prodromal AD group.
Keywords: Aged; Alzheimer Disease; Cognition; Cognitive Dysfunction; Emotions; Female; Frontotemporal Dementia; Humans; Male; Theory of Mind

Differential Mass Spectrometry Profiles of Tau Protein in the Cerebrospinal Fluid of Patients with Alzheimer's Disease, Progressive Supranuclear Palsy, and Dementia with Lewy Bodies. - Barthélemy, Nicolas R; Gabelle, Audrey; Hirtz, Christophe; Fenaille, François; Sergeant, Nicolas; Schraen-Maschke, Susanna; Vialaret, Jérôme; Buée, Luc; Junot, Christophe; Becher, François; Lehmann, Sylvain (J Alzheimers Dis, 2016)
Microtubule-associated Tau proteins are major actors in neurological disorders, the so-called tauopathies. In some of them, and specifically in Alzheimer's disease (AD), hyperphosphorylated forms of Tau aggregate into neurofibrillary tangles. Following and understanding the complexity of Tau's molecular profile with its multiple isoforms and post-translational modifications represent an important issue, and a major analytical challenge. Immunodetection methods are, in fact, limited by the number, specificity, sensitivity, and capturing property of the available antibodies. Mass spectrometry (MS) has recently allowed protein quantification in complex biological fluids using isotope-labeled recombinant standard for absolute quantification (PSAQ). To study Tau proteins, which are found at very low concentrations within the cerebrospinal fluid (CSF), we relied on an innovative two-step pre-fractionation strategy, which was not dependent on immuno-enrichment. We then developed a sensitive multiplex peptide detection capability using targeted high-resolution MS to quantify Tau-specific peptides covering its entire sequence. This approach was used on a clinical cohort of patients with AD, progressive supranuclear palsy (PSP), and dementia with Lewy body (DLB) and with control non-neurodegenerative disorders. We uncovered a common CSF Tau molecular profile characterized by a predominance of central core expression and 1N/3R isoform detection. While PSP and DLB tau profiles showed minimal changes, AD was characterized by a unique pattern with specific modifications of peptide distribution. Taken together these results provide important information on Tau biology for future therapeutic interventions, and improved molecular diagnosis of tauopathies.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analysis of Variance; Chromatography, Liquid; Enzyme-Linked Immunosorbent Assay; Female; Humans; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged; Neuroimaging; Neuropsychological Tests; Peptide Fragments; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Statistics as Topic; Supranuclear Palsy, Progressive; tau Proteins

The Disconnection Hypothesis in Alzheimer's Disease Studied Through Multimodal Magnetic Resonance Imaging: Structural, Perfusion, and Diffusion Tensor Imaging. - Lacalle-Aurioles, María; Navas-Sánchez, Francisco Javier; Alemán-Gómez, Yasser; Olazarán, Javier; Guzmán-De-Villoria, Juan Adán; Cruz-Orduña, Isabel; Mateos-Pérez, José María; Desco, Manuel (J Alzheimers Dis, 2016)
According to the so-called disconnection hypothesis, the loss of synaptic inputs from the medial temporal lobes (MTL) in Alzheimer's disease (AD) may lead to reduced activity of target neurons in cortical areas and, consequently, to decreased cerebral blood flow (CBF) in those areas. The aim of this study was to assess whether hypoperfusion in parietotemporal and frontal cortices of patients with mild cognitive impairment who converted to AD (MCI-c) and patients with mild AD is associated with atrophy in the MTL and/or microstructural changes in the white matter (WM) tracts connecting these areas. We assessed these relationships by investigating correlations between CBF in hypoperfused areas, mean cortical thickness in atrophied regions of the MTL, and fractional anisotropy (FA) in WM tracts. In the MCI-c group, a strong correlation was observed between CBF of the superior parietal gyri and FA in the parahippocampal tracts (left: r = 0.90, p <  0.0001; right: r = 0.597, p = 0.024), and between FA in the right parahippocampal tract and the right precuneus (r = 0.551, p = 0.041). No significant correlations between CBF in hypoperfused regions and FA in the WM tract were observed in the AD group. These results suggest an association between perfusion deficits and altered WM tracts in prodromal AD, while microvasculature impairments may have a greater influence in more advanced stages. We did not find correlations between cortical thinning in the medial temporal lobes and decreased FA in the WM tracts of the limbic system in either group.
Keywords: Aged; Alzheimer Disease; Brain; Brain Mapping; Cerebral Angiography; Cerebrovascular Circulation; Cognitive Dysfunction; Diffusion Tensor Imaging; Female; Functional Laterality; Humans; Magnetic Resonance Imaging; Male; Mental Status Schedule; Models, Neurological; Multimodal Imaging; Organ Size; Prospective Studies

Discovering New Genes in the Pathways of Common Sporadic Neurodegenerative Diseases: A Bioinformatics Approach. - Kim, Yong Hwan; Beak, Seung Han; Charidimou, Andreas; Song, Min (J Alzheimers Dis, 2016)
Late onset Alzheimer's disease (AD) and Parkinson's disease (PD) are mostly "sporadic" age-related neurodegenerative disorders, but with a clear genetic component. However, their genetic architecture is complex and heterogeneous, largely remaining a conundrum, with only a handful of well-established genetic risk factors consistently associated with these diseases. It is possible that numerous, yet undiscovered, AD and PD related genes might exist. We focused on the 'gene' as a mediator to find new potential genes that might have a relationship with both disorders using bio-literature mining techniques. Based on Entrez Gene, we extracted the genes and directional gene-gene relation in the entire MEDLINE records and then constructed a directional gene-gene network. We identified common genes associated with two different but related diseases by performing shortest path analysis on the network. With our approach, we were able to identify and map already known genes that have a direct relationship with PD and AD. In addition, we identified 7 genes previously unknown to be a bridge between these two disorders. We confirmed 4 genes, ROS1, FMN1, ATP8A2, and SNORD12C, by biomedical literature and further checked 3 genes, ERVK-10, PRS, and C7orf49, that might have a high possibility to be related with both diseases. Additional experiments were performed to demonstrate the effectiveness of our proposed method. Comparing to the co-occurrence approach, our approach detected 25% more candidate genes and verified 10% more genes that have the relationship between both diseases than the co-occurrence approach did.
Keywords: Computational Biology; Female; Gene Regulatory Networks; Genetic Predisposition to Disease; Humans; Male; MEDLINE; Neurodegenerative Diseases

Discovery and Subsequent Confirmation of Novel Serum Biomarkers Diagnosing Alzheimer's Disease. - Shah, Dipti Jigar; Rohlfing, Frederick; Anand, Swati; Johnson, W Evan; Alvarez, MeiHwa Tanielle Bench; Cobell, Jesse; King, Jackson; Young, Sydney A; Kauwe, John S K; Graves, Steven W (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) remains challenging to diagnose, especially early disease. Having serum AD biomarkers would be of significant interest both in the clinical setting and in drug development efforts. OBJECTIVE: We applied a novel serum proteomic approach to interrogate the low-molecular weight proteome for serum AD biomarkers. METHODS: A discovery study used sera from 58 any-stage AD cases and 55 matched controls analyzed by capillary liquid chromatography-electrospray ionization-tandem mass spectrometry. Candidate biomarkers were statistically modeled and promising biomarkers were retested in a second, blinded confirmatory study (AD cases = 68, controls = 57). Biomarkers that replicated in the second study were modeled for the diagnosis of any-stage and very early stage AD. Further, they were chemically identified by tandem MS. RESULTS: The initial discovery study found 59 novel potential AD biomarkers. Thirteen recurred in more than one multi-marker panel. In a second, blinded, confirmatory study, these same biomarkers were retested in separate specimens. In that study, four markers validated comparing controls to patients with any-stage AD and also with very early AD. The four biomarkers with replicable ability to diagnose AD were then chemically identified. CONCLUSION: These results suggest novel serum AD diagnostic biomarkers can be found using this approach.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Chromatography, Liquid; Female; Humans; Male; Psychiatric Status Rating Scales; Reproducibility of Results; ROC Curve; Tandem Mass Spectrometry

Discrepancy in Expression of β-Secretase and Amyloid-β Protein Precursor in Alzheimer-Related Genes in the Rat Medial Temporal Lobe Cortex Following Transient Global Brain Ischemia. - Pluta, Ryszard; Kocki, Janusz; Ułamek-Kozioł, Marzena; Petniak, Alicja; Gil-Kulik, Paulina; Januszewski, Sławomir; Bogucki, Jacek; Jabłoński, Mirosław; Brzozowska, Judyta; Furmaga-Jabłońska, Wanda; Bogucka-Kocka, Anna; Czuczwar, Stanisław J (J Alzheimers Dis, 2016)
Brain ischemia may be causally related with Alzheimer's disease. Presumably, β-secretase and amyloid-β protein precursor gene expression changes may be associated with Alzheimer's disease neuropathology. Consequently, we have examined quantitative changes in both β-secretase and amyloid-β protein precursor genes in the medial temporal lobe cortex with the use of quantitative rtPCR analysis following 10-min global brain ischemia in rats with survival of 2, 7, and 30 days. The greatest significant overexpression of β-secretase gene was noted on the 2nd day, while on days 7-30 the expression of this gene was only modestly downregulated. Amyloid-β protein precursor gene was downregulated on the 2nd day, but on days 7-30 postischemia, there was a significant reverse tendency. Thus, the demonstrated alterations indicate that the considerable changes of expression of β-secretase and amyloid-β protein precursor genes may be connected with a response of neurons in medial temporal lobe cortex to transient global brain ischemia. Finally, the ischemia-induced gene changes may play a key role in a late and slow onset of Alzheimer-type pathology.
Keywords: Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Brain Ischemia; Disease Models, Animal; Down-Regulation; Female; Rats; Rats, Wistar; Temporal Lobe; Time Factors

Distinct Patterns of Cognitive Aging Modified by Education Level and Gender among Adults with Limited or No Formal Education: A Normative Study of the Mini-Mental State Examination. - Xie, Haiqun; Zhang, Chengguo; Wang, Yukai; Huang, Shuyun; Cui, Wei; Yang, Wenbin; Koski, Lisa; Xu, Xiping; Li, Youbao; Zheng, Meili; He, Mingli; Fu, Jia; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Dementia is increasingly prevalent due to rapid aging of the population, but under-recognized among people with low education levels. This is partly due to a lack of appropriate and precise normative data, which underestimates cognitive aging in the use of screening tools for dementia. OBJECTIVE: We aimed to improve the precision of screening for cognitive impairment, by characterizing the patterns of cognitive aging and derived normative data of the Mini-Mental State Examination (MMSE) for illiterate and low-educated populations. METHODS: This community-based study included data from 2,280 individuals aged 40 years or older from two rural areas. Multiple linear modeling examined the effect of aging on cognition reflected by the MMSE, stratified by education level and gender. Threshold effect of age on cognition was performed using a smoothing function. RESULTS: The majority of participants (60.4%) were illiterate or had attended only primary school (24.6%). The effect of aging on cognition varied by gender and education. Primary-school educated females and males remained cognitively stable up to 62 and 71 years of age, respectively, with MMSE score declining 0.4 and 0.8 points/year in females and males thereafter. Illiterates females scored 2.3 points lower than illiterate males, and scores for both declined 0.2 points/year. According to these results, normative data stratified by age, education and gender was generated. CONCLUSION: This study suggests gender and educational differences exist in cognitive aging among adults with limited or no formal education. To improve screening precision for cognitive impairment with the use of MMSE in low-educated population, age, gender, and education level should be considered.
Keywords: Adult; Aged; Aged, 80 and over; China; Cognition Disorders; Cognitive Aging; Educational Status; Female; Humans; Male; Mental Status Schedule; Middle Aged; Reference Values; Rural Population; Sex Characteristics

Distinctive Resting State Network Disruptions Among Alzheimer's Disease, Subcortical Vascular Dementia, and Mixed Dementia Patients. - Kim, Hee Jin; Cha, Jungho; Lee, Jong-Min; Shin, Ji Soo; Jung, Na-Yeon; Kim, Yeo Jin; Choe, Yearn Seong; Lee, Kyung Han; Kim, Sung Tae; Kim, Jae Seung; Lee, Jae Hong; Na, Duk L; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recent advances in resting-state functional MRI have revealed altered functional networks in Alzheimer's disease (AD), especially those of the default mode network (DMN) and central executive network (CEN). However, few studies have evaluated whether small vessel disease (SVD) or combined amyloid and SVD burdens affect the DMN or CEN. OBJECTIVE: The aim of this study was to evaluate whether SVD or combined amyloid and SVD burdens affect the DMN or CEN. METHODS: In this cross-sectional study, we investigated the resting-state functional connectivity within DMN and CEN in 37 Pittsburgh compound-B (PiB)(+) AD, 37 PiB(-) subcortical vascular dementia (SVaD), 13 mixed dementia patients, and 65 normal controls. RESULTS: When the resting-state DMN of PiB(+) AD and PiB(-) SVaD patients were compared, the PiB(+) AD patients displayed lower functional connectivity in the inferior parietal lobule while the PiB(-) SVaD patients displayed lower functional connectivity in the medial frontal and superior frontal gyri. Compared to the PiB(-) SVaD or PiB(+) AD, the mixed dementia patients displayed lower functional connectivity within the DMN in the posterior cingulate gyrus. When the resting-state CEN connectivity of PiB(+) AD and PiB(-) SVaD patients were compared, the PiB(-) SVaD patients displayed lower functional connectivity in the anterior insular region. Compared to the PiB(-) SVaD or PiB(+) AD, the mixed dementia patients displayed lower functional connectivity within the CEN in the inferior frontal gyrus. CONCLUSIONS: Our findings suggest that in PiB(+) AD and PiB(-) SVaD, there is divergent disruptions in resting-state DMN and CEN. Furthermore, patients with combined amyloid and SVD burdens exhibited more disrupted resting-state DMN and CEN than patients with only amyloid or SVD burden.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Cerebral Cortex; Cross-Sectional Studies; Dementia; Dementia, Vascular; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Models, Neurological; Neural Pathways; Neuropsychological Tests; Oxygen; Psychiatric Status Rating Scales; Radionuclide Imaging; Rest; Thiazoles

Divergent Longitudinal Propagation of White Matter Degradation in Logopenic and Semantic Variants of Primary Progressive Aphasia. - Tu, Sicong; Leyton, Cristian E; Hodges, John R; Piguet, Olivier; Hornberger, Michael (J Alzheimers Dis, 2016)
BACKGROUND: Clinico-pathological distinction of primary progressive aphasia (PPA) can be challenging at clinic presentation. In particular, cross-sectional neuroimaging signatures across the logopenic (lvPPA) and semantic (svPPA) variants are difficult to establish, with longitudinal profiles showing greater divergence. OBJECTIVE: Assess longitudinal propagation of white matter degradation in lvPPA and svPPA to determine disease progression over time, and whether this reflects distinct underlying pathology. METHOD: A cohort of 27 patients with dementia (12 lvPPA; 15 svPPA) and 12 healthy controls were assessed at baseline and 1-year follow-up on the Addenbrooke's Cognitive Examination-Revised and Sydney Language Battery. Diffusion weighted images were collected at both time-points and analyzed for longitudinal white matter change using DTI-TK and TBSS. RESULTS: LvPPA patients showed a significant decline in naming and repetition, over 1 year, while svPPA patients declined in naming and comprehension. Longitudinal imaging revealed widespread bilateral degradation of white matter tracts in lvPPA over a 1-year period with early involvement of the left posterior inferior longitudinal fasciculus (ILF). SvPPA demonstrated focal left lateralized white matter degradation involving the uncinate fasciculus (UF) and anterior ILF, propagating to the right UF with disease progression. CONCLUSIONS: LvPPA and svPPA cohorts showed distinct longitudinal cognitive and white matter profiles. We propose differences in multi-centric and focal white matter dysfunction in lvPPA and svPPA, respectively, reflect underlying pathological differences. The clinical relevance of white matter degradation and mechanisms underlying disease propagation are discussed.
Keywords: Aged; Analysis of Variance; Aphasia, Primary Progressive; Brain; Cohort Studies; Cross-Sectional Studies; Disease Progression; Female; Humans; Image Processing, Computer-Assisted; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Middle Aged; Names; Neuropsychological Tests; Semantics

Diversity of Cognitive Phenotypes Associated with C9ORF72 Hexanucleotide Expansion. - Gómez-Tortosa, Estrella; Prieto-Jurczynska, Cristina; Serrano, Soledad; Franco-Macías, Emilio; Olivié, Laura; Gallego, Jesús; Guerrero-López, Rosa; Trujillo-Tiebas, María José; Ayuso, Carmen; García Ruiz, Pedro; Pérez-Pérez, Julián; Sainz, María José (J Alzheimers Dis, 2016)
For diagnostic purposes, we screened for the C9ORF72 mutation in a) 162 FTLD cases, and b) 145 cases with other diagnoses but with some frontotemporal features or manifestations previously reported in C9 carriers. Ten cases (onset 50 to 75 years) harbored the expansion: seven had FTLD syndromes (4.3% of total, 11% of familial cases), and three (2%) had a different diagnosis. All positive cases had family history of dementia, psychiatric disease, or ALS, but only 20% of families with mixed FTLD/ALS phenotypes carried the expansion. Language impairment was the most common symptom, followed by behavioral changes, memory deficits, and parkinsonism. C9ORF72 mutation has a low frequency in our dementia series and very diverse clinical manifestations.
Keywords: Adult; Age of Onset; Apolipoprotein E4; Cognition; DNA Repeat Expansion; Family; Female; Follow-Up Studies; Frontotemporal Lobar Degeneration; Genetic Association Studies; Genetic Predisposition to Disease; Genotyping Techniques; Humans; Male; Middle Aged; Prevalence; Proteins; Spain

Does Microglial Activation Influence Hippocampal Volume and Neuronal Function in Alzheimer's Disease and Parkinson's Disease Dementia? - Femminella, Grazia D; Ninan, Siddharth; Atkinson, Rebecca; Fan, Zhen; Brooks, David J; Edison, Paul (J Alzheimers Dis, 2016)
BACKGROUND: The influence of neuroinflammation on neuronal function and hippocampal atrophy in Alzheimer's disease (AD) and Parkinson's disease dementia (PDD) is still unclear. OBJECTIVES: Here we investigated whether microglial activation measured by [11C]PK11195 PET is associated with neuronal function measured by cerebral glucose metabolic rate (rCMRGlc) using FDG-PET and hippocampal volume measurements. METHODS: We enrolled 25 subjects (9 PDD, 8 AD, and 8 controls) who underwent PET scans with [11C](R)PK11195, [18F]FDG, and volumetric MRI scanning. RESULTS: SPM correlation analysis in AD and PDD showed a negative correlation between hippocampal volume and microglial activation within hippocampus or parahippocampus and with cortical and subcortical areas of projections from hippocampus, while there was a positive correlation between rCMRGlc in cortical and subcortical areas of projections from hippocampus and hippocampal volume. Hippocampal volume was significantly reduced in AD compared to controls but not in PDD. CONCLUSIONS: These findings indicate that microglial activation inversely correlated with hippocampal volume and hippocampal rCMRGlc in neurodegenerative diseases with dementia, providing further evidence for the central role of microglial activation in neurodegenerative diseases.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antineoplastic Agents; Brain Mapping; Cognition; Female; Fluorodeoxyglucose F18; Hippocampus; Humans; Isoquinolines; Magnetic Resonance Imaging; Male; Microglia; Middle Aged; Neurons; Neuropsychological Tests; Parkinson Disease; Positron-Emission Tomography; Psychiatric Status Rating Scales; Supranuclear Palsy, Progressive

Dogs with Cognitive Dysfunction as a Spontaneous Model for Early Alzheimer's Disease: A Translational Study of Neuropathological and Inflammatory Markers. - Schütt, Trine; Helboe, Lone; Pedersen, Lars Østergaard; Waldemar, Gunhild; Berendt, Mette; Pedersen, Jan Torleif (J Alzheimers Dis, 2016)
Aged companion dogs with canine cognitive dysfunction (CCD) spontaneously develop varying degrees of progressive cognitive decline and particular neuropathological features correspondent to the changes associated with Alzheimer's disease (AD) in humans. The aim of the present study was to characterize certain aspects of neuropathology and inflammatory markers related to aging and CCD in dogs in comparison with human AD. Fifteen brains from aged dogs with normal cognitive function, mild cognitive impairment, or CCD were investigated and compared with two control brains from young dogs and brain sections from human AD subjects. The neuropathological investigations included evaluation of amyloid-β (Aβ) plaque deposition (N-terminally truncated and pyroglutamyl-modified Aβ included), tau pathology, and inflammatory markers in prefrontal cortex. Cortical Aβ deposition was found to be only of the diffuse subtype as no dense-core or neuritic plaques were found. The Aβ deposition followed a progressive pattern in four maturation stages. Accumulation of the Aβ peptide was also observed in the vessel walls. Both immunohistochemically and biochemically measured levels of Aβ pathology in prefrontal cortex showed a consistent positive correlation to age but not to cognitive deficit severity. No evidence of neurofibrillary tau pathology was found. The level of pro-inflammatory cytokines was generally low and showed no significant association to cognitive status. The findings of the present study support the senescent dog with spontaneous cognitive dysfunction as a valuable non-transgenic model for further investigations of the molecular events involved in the neurodegenerative processes associated with aging and early stage AD, especially the Aβ-related pathology.
Keywords: Aging; Alzheimer Disease; Animals; Brain; Cognitive Dysfunction; Cytokines; Denmark; Disease Models, Animal; Disease Progression; Dog Diseases; Dogs; Female; Humans; Immunohistochemistry; Longitudinal Studies; Male; Plaque, Amyloid; Severity of Illness Index; Species Specificity; tau Proteins; Translational Medical Research

Drivers: A Biologically Contextualized, Cross-Inferential View of the Epidemiology of Neurodegenerative Disorders. - de Pedro-Cuesta, Jesús; Martínez-Martín, Pablo; Rábano, Alberto; Alcalde-Cabero, Enrique; José García López, Fernando; Almazán-Isla, Javier; Ruiz-Tovar, María; Medrano, Maria-José; Avellanal, Fuencisla; Calero, Olga; Calero, Miguel (J Alzheimers Dis, 2016)
BACKGROUND: Sutherland et al. (2011) suggested that, instead of risk factors for single neurodegenerative disorders (NDDs), there was a need to identify specific "drivers", i.e., risk factors with impact on specific deposits, such as amyloid-β, tau, or α-synuclein, acting across entities. OBJECTIVES AND METHODS: Redefining drivers as "neither protein/gene- nor entity-specific features identifiable in the clinical and general epidemiology of conformational NDDs (CNDDs) as potential footprints of templating/spread/transfer mechanisms", we conducted an analysis of the epidemiology of ten CNDDs, searching for patterns. RESULTS: We identified seven potential drivers, each of which was shared by at least two CNDDs: 1) an age-at-exposure-related susceptibility to Creutzfeldt-Jakob disease (CJD) and several late-life CNDDs; 2) a relationship between age at onset, survival, and incidence; 3) shared genetic risk factors for CJD and late-life CNNDs; 4) partly shared personal (diagnostic, educational, behavioral, and social risk factors) predating clinical onset of late-life CNDDs; 5) two environmental risk factors, namely, surgery for sporadic CJD and amyotrophic lateral sclerosis, and Bordetella pertussis infection for Parkinson's disease; 6) reticulo-endothelial system stressors or general drivers (andropause or premenopausal estrogen deficiency, APOEɛ4, and vascular risk factors) for late-life CNDDs such as dementia/Alzheimer's disease, type-2 diabetes mellitus, and some sporadic cardiac and vascular degenerative diseases; and 7) a high, invariant incidence ratio of sporadic to genetic forms of mid- and late-life CNDDs, and type-2 diabetes mellitus. CONCLUSION: There might be a systematic epidemiologic pattern induced by specific proteins (PrP, TDP-43, SOD1, α-synuclein, amyloid-β, tau, Langerhans islet peptide, and transthyretin) or established combinations of these.
Keywords: Age Factors; Aging; Amyloid Precursor Protein Secretases; Apolipoproteins E; Aspartic Acid Endopeptidases; Creutzfeldt-Jakob Syndrome; Environment; Female; Humans; Incidence; Male; Neurodegenerative Diseases; Personality; Risk Factors; Vascular Diseases

Early-Life Exposure to Lead (Pb) Alters the Expression of microRNA that Target Proteins Associated with Alzheimer's Disease. - Masoud, Anwar M; Bihaqi, Syed W; Machan, Jason T; Zawia, Nasser H; Renehan, William E (J Alzheimers Dis, 2016)
There is a growing recognition of the impact of environmental toxins on the epigenetic regulation of gene expression, including the genes that play a critical role in neural development, neural function, and neurodegeneration. We have shown previously that exposure to the heavy metal lead (Pb) in early life results in a latent over-expression of AD-related proteins in rodents and primates. The present study provides evidence that early postnatal exposure to Pb also alters the expression of select miRNA. Mice were exposed to 0.2% Pb acetate from Postnatal Day 1 (PND 1, first 24 h after birth) to PND 20 via their mother's milk. Brain tissue was harvested at PND 20, 180, or 700, and miRNA were isolated and quantified by qPCR. This exposure produced a transient increase (relative to control) in the expression of miR-106b (binds to AβPP mRNA), miR-29b (targets the mRNA for the transcription factor SP1) and two miRNAs (miR-29b and miR-132) that have the ability to inhibit translation of proteins involved in promoter methylation. The expression of miR-106b decreased over time in the Pb-exposed animals and was significantly less than the levels exhibited by the control animals at PND700. The level of miR-124, which binds to SP1 mRNA, was also reduced (relative to controls) at PND700. In summary, we show that exposure to the heavy metal Pb in early life has a significant impact on the short- and long-term expression of miRNA that target epigenetic mediators and neurotoxic proteins.
Keywords: Age Factors; Amyloid beta-Protein Precursor; Animals; Animals, Newborn; Disease Models, Animal; Dose-Response Relationship, Drug; Female; Gene Expression Regulation, Developmental; Lead; Male; Mice; Mice, Inbred C57BL; MicroRNAs; Pregnancy; RNA, Messenger; Sp1 Transcription Factor

Economic Analysis of Formal Care, Informal Care, and Productivity Losses in Primary Care Patients who Screened Positive for Dementia in Germany. - Michalowsky, Bernhard; Thyrian, Jochen René; Eichler, Tilly; Hertel, Johannes; Wucherer, Diana; Flessa, Steffen; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: The majority of people with dementia (PwD) live at home and require professional formal care and informal care that is generally provided by close relatives. OBJECTIVE: To determine the utilization and costs of formal and informal care for PwD, indirect costs because of productivity losses of caregivers, and the associations between cost, socio-demographic and clinical variables. METHODS: The analysis includes the data of 262 community-dwelling PwD and their caregivers. Socio-demographics, clinical variables, and the utilization of formal care were assessed within the baseline assessment. To evaluate informal care costs, the Resource Utilization in Dementia (RUD) questionnaire was used. Costs were calculated from a social perspective. Associations were evaluated using multiple linear and logistic regression models. RESULTS: Formal care services were utilized less (26.3%) than informal care (85.1%), resulting in a cost ratio of one to ten(1,646 €; 16,473 €, respectively). In total, 29% of caregivers were employed, and every seventh (14.3%) experienced productivity losses, which corresponded to 1,258 € annually. Whereas increasing deficits in daily living activities were associated with higher formal and higher informal costs, living alone was significantly associated with higher formal care costs and the employment of a caregiver was associated with lower informal care costs. CONCLUSION: Informal care contributes the most to total care costs. Living alone is a major cost driver for formal costs because of the lower availability of potential informal care. The availability of informal care is limited and productivity losses are increased when a caregiver is employed.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Cost of Illness; Cross-Sectional Studies; Dementia; Female; Germany; Health Care Costs; Home Care Services; Humans; Male; Patient Care; Sensitivity and Specificity; Surveys and Questionnaires

Effect of Anserine/Carnosine Supplementation on Verbal Episodic Memory in Elderly People. - Hisatsune, Tatsuhiro; Kaneko, Jun; Kurashige, Hiroki; Cao, Yuan; Satsu, Hideo; Totsuka, Mamoru; Katakura, Yoshinori; Imabayashi, Etsuko; Matsuda, Hiroshi (J Alzheimers Dis, 2016)
Our goal in this study was to determine whether or not anserine/carnosine supplementation (ACS) is capable of preserving cognitive function of elderly people. In a double-blind randomized controlled trial, volunteers were randomly assigned to an ACS or placebo group at a 1:1 ratio. The ACS group took 1.0 g of an anserine/carnosine (3:1) formula daily for 3 months. Participants were evaluated by psychological tests before and after the 3-month supplementation period. Thirty-nine healthy elderly volunteers (60-78 years old) completed the follow-up tests. Among the tests, delayed recall verbal memory assessed by the Wechsler Memory Scale-Logical Memory showed significant preservation in the ACS group, compared to the placebo group (p = 0.0128). Blood analysis revealed a decreased secretion of inflammatory cytokines, including CCL-2 and IL-8, in the ACS group. MRI analysis using arterial spin labeling showed a suppression in the age-related decline in brain blood flow in the posterior cingulate cortex area in the ACS group, compared to the placebo group (p = 0.0248). In another randomized controlled trial, delayed recall verbal memory showed significant preservation in the ACS group, compared to the placebo group (p = 0.0202). These results collectively suggest that ACS may preserve verbal episodic memory and brain perfusion in elderly people, although further study is needed.
Keywords: Adult; Aged; Aging; Anserine; Brain; Carnosine; Cytokines; Dietary Supplements; Double-Blind Method; Female; Gene Expression Regulation; Humans; Image Processing, Computer-Assisted; Male; Memory, Episodic; Middle Aged; Neuropsychological Tests; Oligonucleotide Array Sequence Analysis; Verbal Learning

Effect of Early Referral to Specialist in Dementia on Institutionalization and Functional Decline: Findings from a Population-Based Study. - Pimouguet, Clément; Le-Goff, Mélanie; Rizzuto, Debora; Berr, Claudine; Leffondré, Karen; Pérès, Karine; Dartigues, Jean François; Helmer, Catherine (J Alzheimers Dis, 2016)
BACKGROUND: Although early diagnosis has been hypothesized to benefit both patients and caregivers, until now studies evaluating the effect of early dementia diagnosis are lacking. OBJECTIVE: To investigate the influence of early specialist referral for dementia on the risk of institutionalization and functional decline in Activity of Daily Living (ADL). METHODS: Incident dementia cases were screened in a prospective population-based cohort, the Three-City Study, and initial specialist consultation for cognitive complaint was assessed at dementia diagnosis. Proportional hazard regression and illness-death models were used to test the association between specialist referral and, respectively, institutionalization and functional decline. RESULTS: Only one third of the incident individuals with dementia had consulted a specialist for cognitive problems early (36%). After adjustment on potential confounders (including cognitive and functional decline) and competing risk of death, participants who had consulted a specialist early in the disease course presented a higher rate of being institutionalized than those who did not (Hazard Ratio = 2.00, 95% Confidence Interval (CI): 1.09- 3.64). But early specialist referral was not associated with further functional decline (HR = 1.09, 95% CI: 0.71- 1.67). CONCLUSIONS: Early specialist referral in dementia is associated with increased risk of institutionalization but not with functional decline in ADL. These findings suggest that early care referral in dementia may be a marker of concern for patients and/or caregivers; subsequent medical and social care could be suboptimal or inappropriate to allow patients to stay longer at home.
Keywords: Activities of Daily Living; Cognition Disorders; Community Health Planning; Dementia; Disability Evaluation; Female; Finland; Follow-Up Studies; Humans; Institutionalization; Male; Psychiatric Status Rating Scales; Referral and Consultation; Specialization

Effect of Tween-20 on Core Biomarkers Measured in Cerebrospinal Fluid from Patients with Alzheimer's Disease, Mild Cognitive Impairment, or Healthy Control Individuals. - Berge, Guro; Lauridsen, Camilla; Sando, Sigrid Botne; Holder, Daniel Joseph; Møller, Ina; Aasly, Jan Olav; Bråthen, Geir; Savage, Mary Josephine; White, Linda Rosemary (J Alzheimers Dis, 2016)
BACKGROUND: There is substantial variation caused by preanalytical procedures in the measurement of cerebrospinal fluid (CSF) biomarkers for Alzheimer's disease (AD) reported in the literature. OBJECTIVE: Determine whether the detergent Tween-20 improves diagnostic accuracy. METHODS: CSF proteins (Aβ42, Aβ40, total tau, and phosphorylated tau) were measured by standard ELISA, in uncentrifuged CSF with or without 0.05% Tween-20 from patients with AD or amnestic mild cognitive impairment, and healthy elderly controls. In the main study, collection tubes containing Tween-20 (Sarstedt 15 mL) were filled with 5 mL CSF to ensure consistent detergent concentration across subsequent aliquots into Corning 2 mL tubes. These latter were also the primary collection vessel for samples without Tween-20. The effect of centrifugation, and extra tube transfer of samples with Tween-20 were also examined. RESULTS: 0.05% Tween-20 significantly increased mean measured CSF concentration of Aβ42 (30% ), Aβ40 (23% ), and total tau (4% ), but not phosphorylated tau. Generally, these increases were similar in all groups, although for Aβ42, the mean percentage increase with Tween-20 was slightly larger for AD. Areas under receiver-operator characteristic curves were similar whether Tween-20 was present or not. Centrifuged CSF without Tween-20 significantly reduced the measured concentration of Aβ42 versus non-centrifuged samples, a difference not seen when detergent was added. Similar CSF Aβ42 levels were found whether Tween-20 was added at collection in an extra tube or directly to the main collection tube. CONCLUSION: Addition of Tween-20 to CSF did not improve differentiation of patients from controls.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Enzyme-Linked Immunosorbent Assay; Female; Humans; Longitudinal Studies; Male; Middle Aged; Peptide Fragments; Phosphorylation; Polysorbates; ROC Curve; Surface-Active Agents; tau Proteins

The Effects of Amnestic Mild Cognitive Impairment on Go/NoGo Semantic Categorization Task Performance and Event-Related Potentials. - Mudar, Raksha A; Chiang, Hsueh-Sheng; Eroh, Justin; Nguyen, Lydia T; Maguire, Mandy J; Spence, Jeffrey S; Kung, Fanting; Kraut, Michael A; Hart, John (J Alzheimers Dis, 2016)
We examined the effects of amnestic mild cognitive impairment (aMCI) on behavioral (response times and error rates) and scalp-recorded event-related potential (ERP) measures of response execution and inhibition, using Go/NoGo tasks involving basic and superordinate semantic categorization. Twenty-five aMCI (16 F; 68.5±8 years) and 25 age- and gender-matched normal control subjects (16 F; 65.4±7.1 years) completed two visual Go/NoGo tasks. In the single car task, responses were made based on single exemplars of a car (Go) and a dog (NoGo) (basic). In the object animal task, responses were based on multiple exemplars of objects (Go) and animals (NoGo) (superordinate). The aMCI subjects had higher commission errors on the NoGo trials compared to the control subjects, whereas both groups had comparable omission errors and reaction times during the Go trials. The aMCI subjects had significantly prolonged N2 ERP latency during Go and NoGo trials across tasks compared to the controls. Both groups showed similar categorization effects and response type effects in N2/P3 ERP latencies and P3 amplitude. Our findings indicate that altered early neural processing indexed by N2 latency distinguishes subjects with aMCI from controls during the Go/NoGo task. Prolonged Go-N2 latency in aMCI appears to precede behavioral changes in response execution, whereas prolonged NoGo-N2 latency underlies behavioral deterioration in response inhibition.
Keywords: Aged; Aged, 80 and over; Amnesia; Brain; Brain Mapping; Cognitive Dysfunction; Electroencephalography; Evoked Potentials; Female; Humans; Inhibition (Psychology); Male; Middle Aged; Neuropsychological Tests; Reaction Time

Effects of Hypertension and Anti-Hypertensive Treatment on Amyloid-β (Aβ) Plaque Load and Aβ-Synthesizing and Aβ-Degrading Enzymes in Frontal Cortex. - Ashby, Emma L; Miners, James S; Kehoe, Patrick G; Love, Seth (J Alzheimers Dis, 2016)
Epidemiological data associate hypertension with a predisposition to Alzheimer's disease (AD), and a number of postmortem and in vivo studies also demonstrate that hypertension increases amyloid-β (Aβ) pathology. In contrast, anti-hypertensive medications reportedly improve cognition and decrease the risk of AD, while certain classes of anti-hypertensive drugs are associated with decreased AD-related pathology. We investigated the effects of hypertension and anti-hypertensive treatment on Aβ plaque load in postmortem frontal cortex in AD. Aβ load was significantly increased in hypertensive (n = 20) relative to normotensive cases (n = 62) and was also significantly higher in treated (n = 9) than untreated hypertensives (n = 11). We then looked into mechanisms by which hypertension and treatment might increase Aβ load, focusing on Aβ-synthesizing enzymes, β- and γ-secretase, and Aβ-degrading enzymes, angiotensin-converting enzyme (ACE), insulin-degrading enzyme (IDE) and neprilysin. ACE and IDE protein levels were significantly lower in hypertensive (n = 21) than normotensive cases (n = 64), perhaps translating to decreased Aβ catabolism in hypertensives. ACE level was significantly higher in treated (n = 9) than untreated hypertensives (n = 12), possibly reflecting feedback upregulation of the renin-angiotensin system. Prospective studies in larger cohorts stratified according to anti-hypertensive drug class are needed to confirm these initial findings and to elucidate the interactions between hypertension, anti-hypertensive treatments, and Aβ metabolism.
Keywords: Aged; Aged, 80 and over; Amyloid Precursor Protein Secretases; Antihypertensive Agents; Female; Frontal Lobe; Humans; Hypertension; Immunohistochemistry; Insulysin; Male; Neprilysin; Peptidyl-Dipeptidase A; Plaque, Amyloid; Retrospective Studies

Efficacy and Safety of ABT-126 in Subjects with Mild-to-Moderate Alzheimer's Disease on Stable Doses of Acetylcholinesterase Inhibitors: A Randomized, Double-Blind, Placebo-Controlled Study. - Florian, Hana; Meier, Andreas; Gauthier, Serge; Lipschitz, Stanley; Lin, Yunzhi; Tang, Qi; Othman, Ahmed A; Robieson, Weining Z; Gault, Laura M (J Alzheimers Dis, 2016)
BACKGROUND: ABT-126 is a potent, selective α7 nicotinic acetylcholine receptor agonist with putative procognitive effects as a monotherapy in treating Alzheimer's disease (AD). OBJECTIVE: This randomized, double-blind, placebo-controlled multicenter study (NCT01549834) investigated the efficacy and safety of ABT-126 in subjects with mild-to-moderate AD who were taking stable doses of acetylcholinesterase inhibitors (AChEIs). METHODS: Subjects received 25 mg ABT-126 (n = 143), 75 mg ABT-126 (n = 145), or placebo (n = 146) once daily for 24 weeks. Subjects who completed the 24-week double-blind study were eligible to enroll in a 28-week open-label extension study (NCT01690195) and received 75 mg ABT-126 daily. The primary efficacy endpoint was the change from baseline to week 24 in the 11-item total score of the Alzheimer's Disease Assessment Scale- Cognitive Subscale (ADAS-Cog). RESULTS: Neither dose of ABT-126 demonstrated significant improvement compared with placebo in the primary efficacy endpoint. However, 25 mg ABT-126 demonstrated significant improvement compared with placebo in ADAS-Cog scores at week 4 (least squares mean difference, -1.21; standard error, 0.51; p <  0.010, one-sided); 75 mg ABT-126 did not demonstrate significant improvements in ADAS-Cog scores compared with placebo at any time point. A treatment effect was not observed for any secondary efficacy measures of cognition, function, or global improvement. ABT-126 was generally well tolerated; the most common adverse events were agitation, constipation, diarrhea, fall, and headache. CONCLUSIONS: Overall, the efficacy profile of ABT-126 did not warrant further development as add-on therapy to AChEIs to treat mild-to-moderate AD.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cholinesterase Inhibitors; Disease Progression; Dose-Response Relationship, Drug; Double-Blind Method; Female; Humans; Indans; International Cooperation; Male; Medication Adherence; Middle Aged; Piperidines; Psychiatric Status Rating Scales; Treatment Outcome

Efficacy and Safety of MMFS-01, a Synapse Density Enhancer, for Treating Cognitive Impairment in Older Adults: A Randomized, Double-Blind, Placebo-Controlled Trial. - Liu, Guosong; Weinger, Jason G; Lu, Zhong-Lin; Xue, Feng; Sadeghpour, Safa (J Alzheimers Dis, 2016)
BACKGROUND: Cognitive impairment is a major problem in elderly, affecting quality of life. Pre-clinical studies show that MMFS-01, a synapse density enhancer, is effective at reversing cognitive decline in aging rodents. OBJECTIVE: Since brain atrophy during aging is strongly associated with both cognitive decline and sleep disorder, we evaluated the efficacy of MMFS-01 in its ability to reverse cognitive impairment and improve sleep. METHODS: We conducted a randomized, double-blind, placebo-controlled, parallel-designed trial in older adult subjects (age 50-70) with cognitive impairment. Subjects were treated with MMFS-01 (n = 23) or placebo (n = 21) for 12 weeks and cognitive ability, sleep quality, and emotion were evaluated. Overall cognitive ability was determined by a composite score of tests in four major cognitive domains. RESULTS: With MMFS-01 treatment, overall cognitive ability improved significantly relative to placebo (p = 0.003; Cohen's d = 0.91). Cognitive fluctuation was also reduced. The study population had more severe executive function deficits than age-matched controls from normative data and MMFS-01 treatment nearly restored their impaired executive function, demonstrating that MMFS-01 may be clinically significant. Due to the strong placebo effects on sleep and anxiety, the effects of MMFS-01 on sleep and anxiety could not be determined. CONCLUSIONS: The current study demonstrates the potential of MMFS-01 for treating cognitive impairment in older adults.
Keywords: Aged; Anxiety; Butyrates; Cognition; Cognition Disorders; Double-Blind Method; Emotions; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Nootropic Agents; Sleep; Synapses; Treatment Outcome

Efficacy and Safety of Sustained Release Donepezil High Dose versus Immediate Release Donepezil Standard Dose in Japanese Patients with Severe Alzheimer's Disease: A Randomized, Double-Blind Trial. - Homma, Akira; Atarashi, Hirotsugu; Kubota, Naoki; Nakai, Kenya; Takase, Takao (J Alzheimers Dis, 2016)
BACKGROUND: Donepezil is an established treatment for mild, moderate, and severe Alzheimer's disease (AD). An international study demonstrated superior efficacy of sustained release (SR) 23 mg/day donepezil over immediate release (IR) 10 mg/day donepezil for cognitive function, but not global function in moderate-to-severe AD. OBJECTIVE: To demonstrate the superiority of SR 23 mg/day donepezil over IR 10 mg/day donepezil in Japanese patients with severe AD (SAD). METHODS: In this multicenter, randomized, double-blind, parallel-group study, Japanese outpatients with SAD were randomly assigned to continue IR 10 mg/day or switch to SR 23 mg/day for 24 weeks. Endpoints included the Severe Impairment Battery (SIB), Clinician's Interview-Based Impression of Change Plus Caregiver Input (CIBIC-plus), and safety. RESULTS: Overall, 166 and 185 patients were randomized to receive IR 10 mg/day and SR 23 mg/day, respectively. SR 23 mg/day was not statistically superior to IR 10 mg/day by SIB (least squares mean difference [LSMD]: 0.0; 95% confidence interval [CI]: -1.7, 1.8; p = 0.981) or CIBIC-plus (LSMD: 0.2; 95% CI: 0.0, 0.4; p = 0.080). Common adverse events in the SR 23 mg group were decreased appetite, vomiting, diarrhea, and contusion. Safety findings were consistent with known safety profiles of donepezil. CONCLUSION: SR 23 mg/day donepezil was not superior to IR 10 mg/day donepezil regarding the efficacy endpoints for Japanese SAD. Considering that a 10 mg/day dose is approved for SAD in Japan, the present findings suggest that IR 10 mg/day donepezil is the optimal dosage for Japanese patients with SAD.
Keywords: Aged; Alzheimer Disease; Cholinesterase Inhibitors; Delayed-Action Preparations; Double-Blind Method; Female; Humans; Indans; Japan; Male; Mental Status Schedule; Nootropic Agents; Outpatients; Piperidines; Psychiatric Status Rating Scales; Severity of Illness Index; Treatment Outcome

Empirically Defining Trajectories of Late-Life Cognitive and Functional Decline. - Hochstetler, Helen; Trzepacz, Paula T; Wang, Shufang; Yu, Peng; Case, Michael; Henley, David B; Degenhardt, Elisabeth; Leoutsakos, Jeannie-Marie; Lyketsos, Constantine G (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) is associated with variable cognitive and functional decline, and it is difficult to predict who will develop the disease and how they will progress. OBJECTIVE: This exploratory study aimed to define latent classes from participants in the Alzheimer's Disease Neuroimaging Initiative (ADNI) database who had similar growth patterns of both cognitive and functional change using Growth Mixture Modeling (GMM), identify characteristics associated with those trajectories, and develop a decision tree using clinical predictors to determine which trajectory, as determined by GMM, individuals will most likely follow. METHODS: We used ADNI early mild cognitive impairment (EMCI), late MCI (LMCI), AD dementia, and healthy control (HC) participants with known amyloid-β status and follow-up assessments on the Alzheimer's Disease Assessment Scale - Cognitive Subscale or the Functional Activities Questionnaire (FAQ) up to 24 months postbaseline. GMM defined trajectories. Classification and Regression Tree (CART) used certain baseline variables to predict likely trajectory path. RESULTS: GMM identified three trajectory classes (C): C1 (n = 162, 13.6%) highest baseline impairment and steepest pattern of cognitive/functional decline; C3 (n = 819, 68.7%) lowest baseline impairment and minimal change on both; C2 (n = 211, 17.7%) intermediate pattern, worsening on both, but less steep than C1. C3 had fewer amyloid- or apolipoprotein-E ɛ4 (APOE4) positive and more healthy controls (HC) or EMCI cases. CART analysis identified two decision nodes using the FAQ to predict likely class with 82.3% estimated accuracy. CONCLUSIONS: Cognitive/functional change followed three trajectories with greater baseline impairment and amyloid and APOE4 positivity associated with greater progression. FAQ may predict trajectory class.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Apolipoprotein E4; Cognition Disorders; Databases, Factual; Dementia; Disease Progression; Female; Follow-Up Studies; Humans; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Surveys and Questionnaires

Enalapril Alone or Co-Administered with Losartan Rescues Cerebrovascular Dysfunction, but not Mnemonic Deficits or Amyloidosis in a Mouse Model of Alzheimer's Disease. - Ongali, Brice; Nicolakakis, Nektaria; Tong, Xing-Kang; Aboulkassim, Tahar; Imboden, Hans; Hamel, Edith (J Alzheimers Dis, 2016)
The co-administration of angiotensin converting enzyme inhibitors (ACEi) and angiotensin II (AngII) receptor blockers (ARB) that bind angiotensin type 1 receptors (AT1R) may protect from Alzheimer's disease (AD) better than each treatment taken alone. We tested the curative potential of the non brain-penetrant ACEi enalapril (3 mg/kg/day) administered for 3 months either alone or in combination with the brain penetrant ARB losartan (10 mg/kg/day) in aged (∼15 months) transgenic mice overexpressing a mutated form of the human amyloid-β protein precursor (AβPP, thereafter APP mice). We studied cerebrovascular function, protein levels of oxidative stress markers (superoxide dismutases SOD1, SOD2 and the NADPH oxidase subunit p67phox), amyloid-β (Aβ) pathology, astrogliosis, cholinergic innervation, AT1R and angiotensin IV receptor (AT4R) levels, together with cognitive performance. Both treatments normalized cerebrovascular reactivity and p67phox protein levels, but they did not reduce the cerebrovascular levels of SOD1. Combined treatment normalized cerebrovascular SOD2 levels, significantly attenuated astrogliosis, but did not reduce the increased levels of cerebrovascular AT1R. Yet, combined therapy enhanced thioflavin-S labeled Aβ plaque burden, a tendency not significant when Aβ1 - 42 plaque load was considered. None of the treatments rescued cognitive deficits, cortical AT4R or cholinergic innervation. We conclude that both treatments normalized cerebrovascular function by inhibiting the AngII-induced oxidative stress cascade, and that the positive effects of the combined therapy on astrogliosis were likely due to the ability of losartan to enter brain parenchyma. However, enalapril did not potentiate, and may even dampen, the reported cognitive benefits of losartan, raising caution when selecting the most appropriate antihypertensive therapy in AD patients.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloidosis; Analysis of Variance; Animals; Antihypertensive Agents; Cerebrovascular Disorders; Cholinesterases; Disease Models, Animal; Drug Combinations; Enalapril; Female; Glial Fibrillary Acidic Protein; Humans; Losartan; Male; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Mutation

Evaluation of Cerebrospinal Fluid Assay Variability in Alzheimer's Disease. - White, Matthew T; Shaw, Leslie M; Xie, Sharon X (J Alzheimers Dis, 2016)
Studies of cerebrospinal fluid (CSF) biomarkers in Alzheimer's disease (AD) have indicated that much of the variability observed in the biomarkers may be due to measurement error. Biomarkers are often obtained with measurement error, which may make the diagnostic biomarker appear less effective than it truly is. In the Alzheimer's Disease Neuroimaging Initiative (ADNI) database, technical replicates of CSF biomarkers are available; the National Alzheimer's Coordinating Center database contains longitudinal replicates of CSF biomarkers. We focus on the area under the receiver operating characteristic curve (AUC) as the measure of diagnostic effectiveness for differentiating AD from normal cognition using CSF biomarkers and compare AUC estimates obtained by a more standard, naïve method (which uses a single observation per subject and ignores measurement error) to a maximum likelihood (ML) based method (which uses all replicates per subject and adjusts for measurement error). The choice of analysis method depends upon the noise to signal ratio (i.e., the magnitude of the measurement error variability relative to the true biomarker variability); moderate to high ratios may significantly bias the naïve AUC estimate, and the ML-based method would be preferred. The noise to signal ratios were low for the ADNI biomarkers but high for the tTau and pTau biomarkers in NACC. Correspondingly, the naïve and ML-based AUC estimates were nearly identical in the ADNI data but dissimilar for the tTau and pTau biomarkers in the NACC data. Therefore, using the naïve method is adequate for analysis of CSF biomarkers in the ADNI study, but the ML method is recommended for the NACC data.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Area Under Curve; Biomarkers; Databases, Factual; Female; Humans; Likelihood Functions; Male; Peptide Fragments; Phosphorylation; ROC Curve; tau Proteins

The Evolution of Caregiver Burden in Frontotemporal Dementia with and without Amyotrophic Lateral Sclerosis. - Hsieh, Sharpley; Leyton, Cristian E; Caga, Jashelle; Flanagan, Emma; Kaizik, Cassandra; O'Connor, Claire M; Kiernan, Matthew C; Hodges, John R; Piguet, Olivier; Mioshi, Eneida (J Alzheimers Dis, 2016)
BACKGROUND AND AIMS: Frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) represent a disease spectrum. Caregiver burden in subtypes of FTD has not yet been directly compared with those patients who have co-existent FTD and ALS (ALSFTD). METHOD: Perceived caregiver burden was evaluated using the short Zarit Burden Interview (ZBI) in patients with behavioral-variant FTD (bvFTD, n = 21), semantic dementia (SD, n = 18), and ALSFTD (n = 15) at the initial clinical presentation and follow-up assessments. The Mini-Addenbrooke's Cognitive Examination (M-ACE) and the Motor Neuron Disease Behaviour Scale (MiND-B) were also used. Linear mixed effects models examined longitudinal changes on the ZBI, M-ACE, and MiND-B across groups. RESULTS: Burden at baseline was highest for the bvFTD group. Longitudinally, perceived burden increased for the SD and ALSFTD groups whereas in bvFTD, the level of burden which was high at baseline and remained high with disease progression. The severity of abnormal behaviors at baseline, as assessed by the MiND-B, correlated with baseline levels of caregiver burden and further accounted for 23% of the variance in caregiver burden at clinical follow-up. CONCLUSIONS: The trajectory of perceived burden differs across the FTD-ALS spectrum, with SD and ALSFTD caregivers demonstrating an increased burden that develops over time, compared to a persistently high level for bvFTD caregivers, evident throughout the disease course. The evolution of burden in these three syndromes likely reflects the initial presentation and clinical characterization that develops with time. Psycho-education programs for caregivers, which provide better coping strategies for challenging behaviors, may reduce levels of burden experienced with disease progression.
Keywords: Adaptation, Psychological; Aged; Amyotrophic Lateral Sclerosis; Analysis of Variance; Caregivers; Case-Control Studies; Cost of Illness; Disease Progression; Female; Frontotemporal Dementia; Humans; Interviews as Topic; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Surveys and Questionnaires

Examining the Relationship Between Autobiographical Memory Impairment and Carer Burden in Dementia Syndromes. - Kumfor, Fiona; Teo, Drusilla; Miller, Laurie; Lah, Suncica; Mioshi, Eneida; Hodges, John R; Piguet, Olivier; Irish, Muireann (J Alzheimers Dis, 2016)
BACKGROUND: Autobiographical memory (ABM) refers to the capacity to remember one's own past, and is known to be central for supporting one's identity and sense of self. This capacity is commonly affected in Alzheimer's disease (AD), as well as semantic dementia (SD) and behavioral-variant frontotemporal dementia (bvFTD). Importantly, ABM plays a critical social function, facilitating relationship intimacy and empathy, and thus loss of ABM may also negatively affect families and carers. OBJECTIVE: To explore the relationship between ABM disruption and carer burden in AD, SD, and bvFTD, and establish whether characteristic ABM profiles differentially relate to carer burden across dementia syndromes. METHODS: We recruited 12 AD, 10 SD, and 13 bvFTD patients and their primary carer. All participants completed the Autobiographical Interview to assess memory for recent and remote events. Carers completed: the Zarit Burden Interview; Depression, Anxiety and Stress Scale (DASS-21); and the Intimate Bond Measure (IBM). RESULTS: In AD, loss of recent ABM was associated with worse psychological wellbeing of carers on the DASS-21. In contrast in SD, remote ABM dysfunction was associated with SD patients showing greater controlling behavior within their intimate relationships. In bvFTD, surprisingly, despite pervasive ABM impairment, no relationship between extent of ABM loss and carer burden was observed. CONCLUSION: These preliminary results reveal that ABM impairment impacts on patients' families and carers and suggest that these influences vary according to the pattern of ABM dysfunction. Disease-specific interventions focusing on preserved aspects of ABM may improve quality of life for both patients and carers.
Keywords: Adaptation, Psychological; Aged; Alzheimer Disease; Analysis of Variance; Behavioral Symptoms; Caregivers; Female; Frontotemporal Dementia; Humans; Male; Memory Disorders; Memory, Episodic; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Statistics as Topic

Exercise Plus Cognitive Performance Over and Above Exercise Alone in Subjects with Mild Cognitive Impairment. - Sacco, Guillaume; Caillaud, Corinne; Ben Sadoun, Gregory; Robert, Philippe; David, Renaud; Brisswalter, Jeanick (J Alzheimers Dis, 2016)
BACKGROUND: Epidemiological studies highlight the relevance of regular exercise interventions to enhance or maintain neurocognitive function in subjects with cognitive impairments. OBJECTIVES: The aim of this study was to ascertain the effect of aerobic exercise associated with cognitive enrichment on cognitive performance in subjects with mild cognitive impairment (MCI). METHOD: Eight participants with MCI (72 ± 2 years) were enrolled in a 9-month study that consisted of two 3-months experimental interventions separated by a training cessation period of 3 months. The interventions included either aerobic exercise alone or aerobic exercise combined with cognitive enrichment. The exercise program involved two 20-min cycling exercise bouts per week at an intensity corresponding to 60% of the heart rate reserve. Cognitive performance was assessed using a task of single reaction time (SRT) and an inhibition task (Go-no-Go) before, immediately after, and 1 month after each intervention. RESULTS: The exercise intervention improved the speed of responses during the Go-no-Go task without any increase in errors. This improvement was enhanced by cognitive enrichment (6 ± 1% ; p >  0.05), when compared with exercise alone (4 ± 0.5% ,). Following exercise cessation, this positive effect disappeared. No effect was observed on SRT performance. CONCLUSION: Regular aerobic exercise improved cognitive performance in MCI subjects and the addition of cognitive tasks during exercise potentiated this effect. However, the influence of aerobic exercise on cognitive performance did not persist after cessation of training. Studies involving a larger number of subjects are necessary to confirm these results.
Keywords: Aged; Analysis of Variance; Cognitive Dysfunction; Cognitive Therapy; Exercise; Exercise Therapy; Female; Humans; Inhibition (Psychology); Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Reaction Time; Retrospective Studies; Treatment Outcome

Fibrillar Amyloid-β Accumulation Triggers an Inflammatory Mechanism Leading to Hyperphosphorylation of the Carboxyl-Terminal End of Tau Polypeptide in the Hippocampal Formation of the 3×Tg-AD Transgenic Mouse. - Ontiveros-Torres, Miguel Ángel; Labra-Barrios, María Luisa; Díaz-Cintra, Sofía; Aguilar-Vázquez, Azucena Ruth; Moreno-Campuzano, Samadhi; Flores-Rodríguez, Paola; Luna-Herrera, Claudia; Mena, Raúl; Perry, George; Florán-Garduño, Benjamín; Luna-Muñoz, José; Luna-Arias, Juan Pedro (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a degenerative and irreversible disorder whose progressiveness is dependent on age. It is histopathologically characterized by the massive accumulation of insoluble forms of tau and amyloid-β (Aβ) asneurofibrillary tangles and neuritic plaques, respectively. Many studies have documented that these two polypeptides suffer several posttranslational modifications employing postmortem tissue sections from brains of patients with AD. In order to elucidate the molecular mechanisms underlying the posttranslational modifications of key players in this disease, including Aβ and tau, several transgenic mouse models have been developed. One of these models is the 3×Tg-AD transgenic mouse, carrying three transgenes encoding APPSWE, S1M146V, and TauP301L proteins. To further characterize this transgenicmouse, we determined the accumulation of fibrillar Aβ as a function of age in relation to the hyperphosphorylation patterns of TauP301L at both its N- and C-terminus in the hippocampal formation by immunofluorescence and confocal microscopy. Moreover, we searched for the expression of activated protein kinases and mediators of inflammation by western blot of wholeprotein extracts from hippocampal tissue sections since 3 to 28 months as well. Our results indicate that the presence of fibrillar Aβ deposits correlates with a significant activation of astrocytes and microglia in subiculum and CA1 regions of hippocampus. Accordingly, we also observed a significant increase in the expression of TNF-α associated to neuritic plaques and glial cells. Importantly, there is an overexpression of the stress activated protein kinases SAPK/JNK and Cdk-5 in pyramidal neurons, which might phosphorylate several residues at the C-terminus of TauP301L. Therefore, the accumulation of Aβ oligomers results in an inflammatory environment that upregulates kinases involved in hyperphosphorylation of TauP301L polypeptide.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; Female; Hippocampus; Humans; Male; Mice, Inbred C57BL; Mice, Transgenic; Neuroglia; Phosphorylation; Plaque, Amyloid; Presenilin-1; Pyramidal Cells; tau Proteins

Formal Psychiatric Disorders are not Overrepresented in Behavioral Variant Frontotemporal Dementia. - Gossink, Flora T; Dols, Annemieke; Krudop, Welmoed A; Sikkes, Sietske A; Kerssens, Cora J; Prins, Niels D; Scheltens, Philip; Stek, Max L; Pijnenburg, Yolande A L (J Alzheimers Dis, 2016)
While psychiatric misdiagnosis is well-known in behavioral variant frontotemporal dementia (bvFTD), a systematic evaluation of standardized criteria for psychiatric disorders in bvFTD is still missing. Our aim was to define frequency and character of DSM-IV psychiatric disorders among patients with probable and definite bvFTD compared to possible bvFTD, other neurodegenerative diseases, and psychiatric diagnoses, using MINI-International Neuropsychiatric Interview. We additionally compared psychiatric prodromes between these groups. Subjects were participants of the late-onset frontal lobe (LOF) study, a longitudinal multicenter study. In each patient, after baseline diagnostic procedure, a neurologist and geriatric psychiatrist made a joint clinical diagnosis. Independently, a structured diagnostic interview according to DSM-IV and ICD-10 criteria (MINI-Plus) was performed by a trained professional blinded to clinical diagnosis. Out of 91 patients, 23 with probable and definite bvFTD, 3 with possible bvFTD, 25 with a non bvFTD neurodegenerative disease, and 40 with a clinical psychiatric diagnosis were included. Overall frequency of formal current and past psychiatric disorders in probable and definite bvFTD (21.7% current, 8.7% past) did not differ from other neurodegenerative diseases (12.0% current, 16.0% past) or possible bvFTD (66.7% current, 66.7% past), but was less than in patients with a clinical psychiatric diagnosis (57.5% current, 62.5% past; p <  0.01). In probable and definite bvFTD unipolar mood disorders were most common. Formally diagnosed psychiatric disorders are not overrepresented in probable bvFTD, suggesting that psychiatric misdiagnosis in bvFTD can be reduced by strictly applying diagnostic criteria. In suspected bvFTD close collaboration between neurologists and psychiatrists will advance diagnostics and subsequent treatment.
Keywords: Aged; Cohort Studies; Diagnostic and Statistical Manual of Mental Disorders; Female; Frontotemporal Dementia; Humans; Male; Mental Disorders; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales

Functional Connectivity of Ventral and Dorsal Visual Streams in Posterior Cortical Atrophy. - Migliaccio, Raffaella; Gallea, Cécile; Kas, Aurélie; Perlbarg, Vincent; Samri, Dalila; Trotta, Laura; Michon, Agnès; Lacomblez, Lucette; Dubois, Bruno; Lehéricy, Stéphane; Bartolomeo, Paolo (J Alzheimers Dis, 2016)
BACKGROUND: Posterior cortical atrophy (PCA) induces progressive dysfunction of ventral and dorsal visual networks. Little is known, however, about corresponding changes in functional connectivity (FC). OBJECTIVES: To investigate FC changes in the visual networks, their relationship with cortical atrophy, and the association with Alzheimer's disease (AD) pathology. METHODS: Ten PCA patients and 28 age-matched controls participated in the study. Using resting state fMRI, we measured FC in ventral and dorsal cortical visual networks, defined on the basis of a priori knowledge of long-range white matter connections. To assess the relationships with AD, we determined AD biomarkers in cerebrospinal fluid and FC in the default mode network (DMN), which is vulnerable to AD pathology. Voxel-based morphometry analysis assessed the pattern of grey matter (GM) atrophy. RESULTS: PCA patients showed GM atrophy in bilateral occipital and inferior parietal regions. PCA patients had lower FC levels in a ventral network than controls, but higher FC in inferior components of the dorsal network. In particular, the increased connectivity correlated with greater GM atrophy in occipital regions. All PCA patients had positive cerebrospinal fluid biomarkers for AD; however, FC in global DMN did not differ from controls. CONCLUSIONS: FC in PCA reflects brain structure in a non-univocal way. Hyperconnectivity of dorsal networks may indicate aberrant communication in response to posterior brain atrophy or processes of neural resilience during the initial stage of brain dysfunction. The lack of difference from controls in global DMN FC highlights the atypical nature of PCA with respect to typical AD.
Keywords: Aged; Alzheimer Disease; Atrophy; Case-Control Studies; Cerebral Cortex; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Oxygen; Visual Pathways

Future Dementia Severity is Almost Entirely Explained by the Latent Variable δ's Intercept and Slope. - Palmer, Raymond F; Royall, Donald R (J Alzheimers Dis, 2016)
BACKGROUND: Structural equation models (SEM) can explicitly distinguish dementia-relevant variance in cognitive task performance. The resulting latent construct "δ" (for dementia) provides a relatively "error free" continuously varying dementia-specific phenotype. OBJECTIVE: To estimate δ's change over time (Δδ) and determine Δδ's predictive validity using future dementia status as an outcome. METHODS: Data from n = 2,191 participants of the Texas Alzheimer's Research and Care Consortium (TARCC) were used to construct a latent growth curve model of longitudinal change over four years using five cognitive measures and one measure of Instrumental Activities of Daily Living. Four final latent factors, including baseline δ and Δδ, were simultaneously entered as predictors of wave 4 dementia severity, as estimated by the Clinical Dementia Rating Scale "sum of boxes" (CDR). RESULTS: All observed measures exhibited significant change [χ2 = 1,152 (df = 229); CFI = 0.968; RMSEA = 0.043]. The final model demonstrated excellent fit to the data [χ2 = 543 (df = 245); CFI = 0.991; RMSEA = 0.023]. All latent indicator loadings were significant, yielding four distinct factors. After adjustment for demographic covariates and baseline CDR scores, d and Δd were significantly independently associated with CDR4, explaining 25% and 49% of its variance, respectively. The latent variable g' significantly explained 3% of CDR4 variance independently of d and Δd. Δg' was not significantly associated with CDR4. Baseline CDR explained 16% of CDR4 variance. CONCLUSIONS: Future dementia severity is almost entirely explained by the latent construct δ's intercept and slope.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Cognitive Dysfunction; Factor Analysis, Statistical; Female; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Psychiatric Status Rating Scales

Genetic Counseling and Testing for Alzheimer's Disease and Frontotemporal Lobar Degeneration: An Italian Consensus Protocol. - Bocchetta, Martina; Mega, Anna; Bernardi, Livia; Di Maria, Emilio; Benussi, Luisa; Binetti, Giuliano; Borroni, Barbara; Colao, Rosanna; Di Fede, Giuseppe; Fostinelli, Silvia; Galimberti, Daniela; Gennarelli, Massimo; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Genetic testing of familial Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD) is attracting interest thanks to innovative primary prevention clinical trials and increased request for information by at-risk individuals. However, ethical, social, and psychological implications are paramount and genetic testing must be supported by structured genetic counseling. In Italy, practice parameters and guidelines for genetic counseling in dementia are not available. OBJECTIVE: To develop a nationally harmonized protocol for genetic counseling and testing of familial AD and FTLD. METHODS: Activities were carried out in the context of the Italian Dominantly Inherited Alzheimer's and Frontotemporal Network (IT-DIAfN) project, a national network of centers of excellence with expertise in managing patients with familial AD and FTLD. A survey of the literature on genetic counseling protocols and guidelines was conducted. Local protocols for genetic counseling were surveyed. Differences and commonalities among protocols were identified and discussed among project partners. Consensus was reached following implicit aggregation methods. RESULTS: Consensus was reached on a protocol for patients with clinically diagnosed familial AD or FTLD and a distinct protocol for their at-risk relatives. Genetic counseling should be provided by a multidisciplinary team including a geneticist, a neurologist/geriatrician, and a psychologist/psychiatrist, according to the following schedule: (i) initial consultation with tailored information on the genetics of the dementias; (ii) clinical, psychological, and cognitive assessment; if deemed appropriate (iii) genetic testing following a structured decision tree for gene mutation search; (iv) genetic testing result disclosure; (v) psychological support follow-up. CONCLUSION: This genetic counseling protocol provides Italian centers with a line of shared practice for dealing with the requests for genetic testing for familial AD and FTLD from patients and at-risk relatives, who may also be eligible participants for novel prevention clinical trials.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Consensus; Female; Follow-Up Studies; Frontotemporal Lobar Degeneration; Genetic Counseling; Genetic Testing; Humans; Italy; Male; Peptide Fragments; Psychiatric Status Rating Scales

Genetic Influences on Plasma Homocysteine Levels in African Americans and Yoruba Nigerians. - Kim, Sungeun; Nho, Kwangsik; Ramanan, Vijay K; Lai, Dongbing; Foroud, Tatiana M; Lane, Katie; Murrell, Jill R; Gao, Sujuan; Hall, Kathleen S; Unverzagt, Frederick W; Baiyewu, Olusegun; Ogunniyi, Adesola; et al. (J Alzheimers Dis, 2016)
Plasma homocysteine, a metabolite involved in key cellular methylation processes seems to be implicated in cognitive functions and cardiovascular health with its high levels representing a potential modifiable risk factor for Alzheimer's disease (AD) and other dementias. A better understanding of the genetic factors regulating homocysteine levels, particularly in non-white populations, may help in risk stratification analyses of existing clinical trials and may point to novel targets for homocysteine-lowering therapy. To identify genetic influences on plasma homocysteine levels in individuals with African ancestry, we performed a targeted gene and pathway-based analysis using a priori biological information and then to identify new association performed a genome-wide association study. All analyses used combined data from the African American and Yoruba cohorts from the Indianapolis-Ibadan Dementia Project. Targeted analyses demonstrated significant associations of homocysteine and variants within the CBS (Cystathionine beta-Synthase) gene. We identified a novel genome-wide significant association of the AD risk gene CD2AP (CD2-associated protein) with plasma homocysteine levels in both cohorts. Minor allele (T) carriers of identified CD2AP variant (rs6940729) exhibited decreased homocysteine level. Pathway enrichment analysis identified several interesting pathways including the GABA receptor activation pathway. This is noteworthy given the known antagonistic effect of homocysteine on GABA receptors. These findings identify several new targets warranting further investigation in relation to the role of homocysteine in neurodegeneration.
Keywords: Adaptor Proteins, Signal Transducing; African Americans; African Continental Ancestry Group; Aged; Aged, 80 and over; Cohort Studies; Cystathionine beta-Synthase; Cytoskeletal Proteins; Female; Genetic Variation; Genome-Wide Association Study; Heterozygote; Homocysteine; Humans; Indiana; Longitudinal Studies; Male; Nigeria; Prospective Studies

The Genetic Variability of UCP4 Affects the Individual Susceptibility to Late-Onset Alzheimer's Disease and Modifies the Disease's Risk in APOE-ɛ4 Carriers. - Montesanto, Alberto; Crocco, Paolina; Anfossi, Maria; Smirne, Nicoletta; Puccio, Gianfranco; Colao, Rosanna; Maletta, Raffaele; Passarino, Giuseppe; Bruni, Amalia C; Rose, Giuseppina (J Alzheimers Dis, 2016)
Uncoupling proteins (UCPs) are a group of five mitochondrial inner membrane transporters with a tissue specific expression that uncouple biofuel oxidation from ATP synthesis and function as regulators of energy homeostasis and antioxidants. Previous data suggested that neuronal UCPs (UCP2, UCP4, and UCP5) can directly influence synaptic plasticity, neurotransmission, and neurodegenerative processes, and have a crucial role in the function and protection of the central nervous system. In fact, it has been observed that the expression of neuronal UCPs significantly decreases in Alzheimer's disease (AD) patients. Here we analyzed the variability of UCP2, -3, -4, and 5 genes in sporadic and familial cases (n = 465) of late-onset AD (LOAD) with respect to healthy controls (n = 442). We showed that a genetic variant in the human UCP4, rs9472817, not only significantly affects the individual susceptibility to LOAD, but also modulates the effect of APOE-ɛ4 on AD risk. In fact, rs9472817-C allele was significantly more frequent in both groups of patients with respect to the control group (p = 6.934*10-4 for familial and p = 1.033*10-3 for sporadic cases). In addition, gene-gene interaction analysis revealed that the effect of APOE-ɛ4 allele on LOAD risk was doubled in homozygote CC subjects; conversely, the risk conferred by the APOE-ɛ4 allele was annulled in subjects with two copies of the G allele. Our findings are further evidence that the efficiency in mitochondrial energy metabolism and oxidative stress are important factors in AD pathogenesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Female; Genetic Association Studies; Genotype; Humans; Male; Mental Status Schedule; Mitochondrial Uncoupling Proteins; Neuroimaging; Polymorphism, Single Nucleotide

Greater specificity for cerebrospinal fluid P-tau231 over P-tau181 in the differentiation of healthy controls from Alzheimer's disease. - Spiegel, Jonathan; Pirraglia, Elizabeth; Osorio, Ricardo S; Glodzik, Lidia; Li, Yi; Tsui, Wai; Saint Louis, Leslie A; Randall, Catherine; Butler, Tracy; Xu, Jinfeng; Zinkowski, Raymond P; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) measures of phosphorylated-tau (P-tau) 231 and P-tau181 are two biomarkers for the identification of tau pathology as related to Alzheimer's disease (AD). While both are pathologically validated, their relative diagnostic performances are not well known. This cross-sectional diagnostic study of 87 normal (NL) subjects and 28 AD subjects compared CSF P-tau231 with CSF P-tau181. Logistic regression modeling demonstrated that the P-tau231 was superior to the P-tau181 in the diagnostic classifications. At a fixed 85% sensitivity cutoff, the ROC analysis shows that P-tau231 has greater overall specificity than P-tau181. While both P-tau analytes demonstrated equivalent negative predictive accuracies, P-tau231 yielded significantly fewer false positives. Moreover, P-tau231, but not P-tau181, demonstrated sensitivity to the E4 genotype. A postmortem validation with 9 AD subjects confirmed the superiority of the CSF P-tau231 specificity. This study suggests that P-tau231 has the potential to improve the CSF tau biomarker diagnosis of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Cross-Sectional Studies; Female; Humans; Logistic Models; Male; Middle Aged; Phosphorylation; ROC Curve; Sensitivity and Specificity; tau Proteins

Greater than the Sum of Its Parts: δ can be Constructed from Item Level Data. - Royall, Donald R; Palmer, Raymond F; Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Nakaaki, Shutaro; Koumi, Hiroyuki; et al. (J Alzheimers Dis, 2016)
"δ", a latent variable constructed from cognitive performance and functional status measures, can accurately diagnose dementia. The minimal assessment needed is unknown. We have constructed a δ homolog, "dTEXAS", from Telephone Executive Assessment Scale (TEXAS) items, and validated it in a convenience sample of Japanese persons (n = 176). dTEXAS scores correlated strongly with both Instrumental Activities of Daily Living (IADL) (r = -0.86, p <  0.001) and Clinical Dementia Rating Scale (CDR) (r = 0.71, p <  0.001). Constructed independently of their diagnoses, dTEXAS scores accurately distinguished dementia versus controls (area under the receiver operating curve [(AUC; ROC) = 0.92], dementia versus mild cognitive impairment (MCI) (AUC = 0.80) and controls versus MCI (AUC = 0.74). These AUCs are higher than those of multiple observed executive measures, as reported recently by Matsuoka et al., 2014. A dTEXAS score of -0.58 best discriminated between dementia versus controls with 90.1% sensitivity and 80.0% specificity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Executive Function; Female; Humans; Japan; Male; Neuropsychological Tests; Psychiatric Status Rating Scales; ROC Curve; United States

Health-Related Quality of Life in Patients with Alzheimer's Disease in Different German Health Care Settings. - Heßmann, Philipp; Seeberg, Greta; Reese, Jens Peter; Dams, Judith; Baum, Erika; Müller, Matthias J; Dodel, Richard; Balzer-Geldsetzer, Monika (J Alzheimers Dis, 2016)
The purpose of this study is to evaluate the health-related quality of life (HrQoL) of patients with Alzheimer's disease (AD) in different care settings (institutionalized versus community-dwelling) across all severity stages of dementia. Patients were consecutively recruited with their primary caregivers (123 inpatients and 272 outpatients), and the impact of patient-related parameters such as behavioral and psychological symptoms of dementia (BPSD) (Geriatric Depression Scale [GDS] and Neuropsychiatric Inventory [NPI]) and functional capacity (Alzheimer's Disease Cooperative Study-Activities of Daily Living [ADCS-ADL]) on HrQoL was analyzed. Patients' HrQoL was assessed using self-reported and caregiver-rated generic (EuroQoL Instrument) and dementia-specific (Quality of Life-Alzheimer's Disease [Qol-AD]) scales. Patients reported a considerably higher HrQoL than their caregivers on the QoL-AD, EQ-5D, and EQ VAS (p <  0.001). Different dementia severity groups showed significantly worse results in HrQoL for patients with lower MMSE scores. The mean self-reported QoL-AD decreased from 32.3±5.7 in the group with the highest MMSE scores to 27.1±5.5 in patients with the lowest MMSE scores (p <  0.001). A considerably lower HrQoL was shown for institutionalized patients versus participants in outpatient settings (proxy-rated QoL-AD 19.7±4.6 versus 26.0±7.1, p <  0.001). Depressive symptoms (GDS), BPSD (NPI), and reduced functional capacity (ADCS-ADL) were evaluated for their impact on patients' HrQoL. Multivariate models explained between 22% and 54% of the variance in patients' HrQoL. To analyze the causative direction of the reported associations, further longitudinal studies should be conducted.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Caregivers; Depression; Female; Germany; Humans; Inpatients; Male; Multivariate Analysis; Neuropsychological Tests; Outpatients; Psychiatric Status Rating Scales; Quality of Life; Residential Facilities; Self Report; Severity of Illness Index

Heterogeneity of Cognitive Anosognosia and its Variation with the Severity of Dementia in Patients with Alzheimer's Disease. - Avondino, Emilie; Antoine, Pascal (J Alzheimers Dis, 2016)
Currently, the lack of awareness of deficits, i.e., anosognosia, is a major obstacle in the healthcare circuit that delays the diagnosis of Alzheimer's disease (AD). However, a clear framework is lacking in the literature related to this phenomenon in terms of its definition, mechanisms, and objects. The aim of this study is to assess the different levels of cognitive anosognosia using a prediction-performance procedure and to identify the potential correlates of these levels. A sample of patients with probable AD was divided into three groups according to the severity of dementia (mild (MiD), moderate (MoD), and moderately severe (MSD) dementia), ranked according to the results of the Mini-Mental State Examination. We observed the following three scores: the real score, the prediction score, and the anosognosia score. These scores were calculated based on the prediction-performance task MISAwareness from the Dementia Rating Scale for cognitive processes (i.e., Attention, Initiation, Conceptualization, Construction, and Memory). We obtained a strong plateau effect between the MiD and MoD groups for anosognosia scores for actual performance or prediction for both the level of overall functioning and for specific processes. The sole exception was the result for memory processes. Moreover, the profiles of the patients' responses on the Memory subscale were substantially different and, indeed, opposite from those for the other processes. The main results confirm the multidimensionality of anosognosia and its variability with the stage of dementia and specifically implicate memory processes that indicate a cleavage between memory and other cognitive functions.
Keywords: Agnosia; Alzheimer Disease; Attention; Chi-Square Distribution; Cognition Disorders; Dementia; Female; Humans; Male; Memory; Neuropsychological Tests; Predictive Value of Tests; Prospective Studies; Psychiatric Status Rating Scales; Severity of Illness Index

Heterogeneous Language Profiles in Patients with Primary Progressive Aphasia due to Alzheimer's Disease. - Louwersheimer, Eva; Keulen, M Antoinette; Steenwijk, Martijn D; Wattjes, Mike P; Jiskoot, Lize C; Vrenken, Hugo; Teunissen, Charlotte E; van Berckel, Bart N M; van der Flier, Wiesje M; Scheltens, Philip; van Swieten, John C; Pijnenburg, Yolande A L (J Alzheimers Dis, 2016)
BACKGROUND: The logopenic variant of Primary Progressive Aphasia (lvPPA) is associated with underlying Alzheimer's disease (AD) pathology and characterized by impaired single word retrieval and repetition of phrases and sentences. OBJECTIVE: We set out to study whether logopenic aphasia is indeed the prototypic language profile in PPA patients with biomarker evidence of underlying AD pathology and to correlate language profiles with cortical atrophy patterns on MRI. METHODS: Inclusion criteria: (I) clinical diagnosis of PPA; (II) CSF profile and/or PiB-PET scan indicative for amyloid pathology; (III) availability of expert language evaluation. Based on language evaluation, patients were classified as lvPPA (fulfilling lvPPA core criteria), lvPPA extended (fulfilling core criteria plus other language disturbances), or PPA unclassifiable (not fulfilling lvPPA core criteria). Cortical atrophy patterns on MRI were visually rated and quantitative measurements of cortical thickness were performed using FreeSurfer. RESULTS: We included 22 patients (age 67±7 years, 50% female, MMSE 21±6). 41% were classified as lvPPA, 36% as lvPPA extended with additional deficits in language comprehension and/or confrontation naming, and 23% as PPA unclassifiable. By both qualitative and quantitative measurements, patients with lvPPA showed mild global cortical atrophy on MRI, whereas patients with lvPPA extended showed more focal cortical atrophy, predominantly at the left tempo-parietal side. For PPA unclassifiable, qualitative measurements revealed a heterogeneous atrophy pattern. CONCLUSION: Although most patients fulfilled the lvPPA criteria, we found that their language profiles were heterogeneous. The clinical and radiological spectrum of PPA due to underlying AD pathology is broader than pure lvPPA.
Keywords: Aged; Alzheimer Disease; Aphasia, Primary Progressive; Atrophy; Biomarkers; Brain; Female; Humans; Language; Language Tests; Magnetic Resonance Imaging; Male; Mental Status Schedule; Organ Size; Positron-Emission Tomography; Retrospective Studies

Higher Fasting Plasma Glucose Levels, within the Normal Range, are Associated with Decreased Processing Speed in High Functioning Young Elderly. - Raizes, Meytal; Elkana, Odelia; Franko, Motty; Ravona Springer, Ramit; Segev, Shlomo; Beeri, Michal Schnaider (J Alzheimers Dis, 2016)
We explored the association of plasma glucose levels within the normal range with processing speed in high functioning young elderly, free of type 2 diabetes mellitus (T2DM). A sample of 41 participants (mean age = 64.7, SD = 10; glucose 94.5 mg/dL, SD = 9.3), were examined with a computerized cognitive battery. Hierarchical linear regression analysis showed that higher plasma glucose levels, albeit within the normal range (<110 mg/dL), were associated with longer reaction times (p <  0.01). These findings suggest that even in the subclinical range and in the absence of T2DM, monitoring plasma glucose levels may have an impact on cognitive function.
Keywords: Aged; Blood Glucose; Cognition; Diabetes Mellitus, Type 2; Fasting; Female; Humans; Linear Models; Male; Middle Aged; Neuropsychological Tests; Psychomotor Performance; Reaction Time; Reference Values

Homotaurine Effects on Hippocampal Volume Loss and Episodic Memory in Amnestic Mild Cognitive Impairment. - Spalletta, Gianfranco; Cravello, Luca; Gianni, Walter; Piras, Federica; Iorio, Mariangela; Cacciari, Claudia; Casini, Anna Rosa; Chiapponi, Chiara; Sancesario, Giuseppe; Fratangeli, Claudia; Orfei, Maria Donata; Caltagirone, Carlo; et al. (J Alzheimers Dis, 2016)
Homotaurine supplementation may have a positive effect on early Alzheimer's disease. Here, we investigated its potential neuroprotective effect on the hippocampus structure and episodic memory performances in amnestic mild cognitive impairment (aMCI). Neuropsychological, clinical, and neuroimaging assessment in 11 treated and 22 untreated patients were performed at baseline and after 1 year. Magnetic resonance data were analyzed using voxel-based morphometry to explore significant differences (Family Wise Error corrected) between the two groups over time. Patients treated with homotaurine showed decreased volume loss in the left and right hippocampal tail, left and right fusiform gyrus, and right inferior temporal cortex which was associated with improved short-term episodic memory performance as measured by the recency effect of the Rey 15-word list learning test immediate recall. Thus, homotaurine supplementation in individuals with aMCI has a positive effect on hippocampus atrophy and episodic memory loss. Future studies should further clarify the mechanisms of its effects on brain morphometry.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Chi-Square Distribution; Cognitive Dysfunction; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Memory, Episodic; Mental Status Schedule; Middle Aged; Neuroprotective Agents; Neuropsychological Tests; Taurine

"I Don't Think Of It As An Illness": Illness Representations in Mild to Moderate Dementia. - Clare, Linda; Quinn, Catherine; Jones, Ian Rees; Woods, Robert T (J Alzheimers Dis, 2016)
The self-regulatory model proposes that illness representations influence adjustment and coping in chronic conditions. Better understanding of the illness representations held by people with dementia could help with targeting information and support so as to optimize adjustment and coping. In this mixed-methods study of illness representations among people with mild to moderate Alzheimer's, vascular, or mixed dementia we aimed to clarify the nature of the representations held, to determine whether specific profiles can be identified based on perceptions of the identity and cause of the condition, and to examine associations between these profiles and other participant characteristics. Data were collected in the second wave of the Memory Impairment and Dementia Awareness Study (MIDAS). Sixty-four people with dementia, who had been told their diagnosis at a memory clinic, completed interviews and responded to questionnaires. In each case a carer was also interviewed. Cluster analysis based on responses about identity and cause identified three profiles. 'Illness' cluster participants saw themselves as living with an illness and used diagnostic labels, 'ageing' cluster participants did not use diagnostic labels and viewed their difficulties as related to ageing, and 'no problem' cluster participants considered that they did not have any difficulties. 'Illness' cluster participants had better cognition and better awareness, but lower mood, and perceived more practical consequences, than 'ageing' cluster participants. Holding an 'illness' model may not be advantageous. Rather than encouraging adoption of such a model, it may be preferable to target information and select interventions in line with the person's representation profile.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Aging; Awareness; Caregivers; Dementia; Female; Follow-Up Studies; Humans; Male; Middle Aged; Psychiatric Status Rating Scales; Residence Characteristics; Self Concept; Statistics, Nonparametric; Surveys and Questionnaires

Impact of Depressive Symptoms on Conversion from Mild Cognitive Impairment Subtypes to Alzheimer's Disease: A Community-Based Longitudinal Study. - Kida, Jiro; Nemoto, Kiyotaka; Ikejima, Chiaki; Bun, Shogyoku; Kakuma, Tatsuyuki; Mizukami, Katsuyoshi; Asada, Takashi (J Alzheimers Dis, 2016)
BACKGROUND: While longitudinal studies have investigated the relationships between mild cognitive impairment (MCI) subtypes and dementia subtypes, the results have been contradictory. In addition, some research shows that depression accompanied by MCI might increase the risk of Alzheimer's disease (AD). OBJECTIVE: The aim of this study is to longitudinally investigate the relationships between MCI subtypes and dementia subtypes, with special attention to the effect of comorbid depressive symptoms in a Japanese rural community. METHODS: Non-demented participants (n = 802) completed a baseline and follow-up study. Outcomes were conversion to dementia especially AD, MCI, or no conversion. A complementary log-log analysis was conducted to investigate the risk of dementia and AD in amnestic MCI (aMCI) compared to nonamnestic MCI (naMCI) groups. The impact of depressive symptoms on the transition from MCI to AD and from cognitively normal to MCI or AD was also analyzed. RESULTS: The risk of developing dementia, in particular AD, for the aMCI group was significantly higher than that for the naMCI group. In the aMCI group, the presence of depressive symptoms increased the risk of developing AD, but depressive symptoms in the naMCI group did not. In the cognitively normal group, the presence of depressive symptoms increased the risk of aMCI but not naMCI or AD. CONCLUSION: MCI subtyping could be useful in finding a prodrome for dementia and in particular for AD. The differing impacts of depressive symptoms on the development of AD suggest that the relationship between depressive symptoms and cognitive impairment could differ in aMCI and naMCI patients.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Cognitive Dysfunction; Depression; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Prodromal Symptoms; Prognosis; Risk

Impact of Omega-3 Fatty Acid Supplementation on Memory Functions in Healthy Older Adults. - Külzow, Nadine; Witte, A Veronica; Kerti, Lucia; Grittner, Ulrike; Schuchardt, Jan Philipp; Hahn, Andreas; Flöel, Agnes (J Alzheimers Dis, 2016)
As the process of Alzheimer's disease (AD) begins years before disease onset, searching for prevention strategies is of major medical and economic importance. Nutritional supplementation with long-chain polyunsaturated omega-3 fatty acids (LC-n3-FA) may exert beneficial effects on brain structure and function. However, experimental evidence in older adults without clinical dementia is inconsistent, possibly due to low sensitivity of previously employed test batteries for detecting subtle improvements in cognition in healthy individuals. Here we used LOCATO, recently described as a robust and sensitive tool for assessing object-location memory (OLM) in older adults, to evaluate the impact of LC-n3-FA supplementation on learning and memory formation. In a double-blind placebo-controlled proof-of-concept study, 44 (20 female) cognitively healthy individuals aged 50-75 years received either LC-n3-FA (2,200 mg/day, n = 22) or placebo (n = 22) for 26 weeks. Before and after intervention, memory performance in the OLM-task (primary) was tested. As secondary outcome parameters, performance in Rey Auditory Verbal Learning Test (AVLT), dietary habits, omega-3-index, and other blood-derived parameters were assessed. Omega-3 index increased significantly in the LC-n3-FA group compared with the placebo group. Moreover, recall of object locations was significantly better after LC-n3-FA supplementation compared with placebo. Performance in the AVLT was not significantly affected by LC-n3-FA. This double-blind placebo-controlled proof-of-concept study provides further experimental evidence that LC-n3-FA exert positive effects on memory functions in healthy older adults. Our findings suggest novel strategies to maintain cognitive functions into old age.
Keywords: Aged; Apolipoproteins E; Auditory Perception; Blood Chemical Analysis; Cognitive Aging; Dietary Supplements; Double-Blind Method; Fatty Acids, Omega-3; Feeding Behavior; Female; Humans; Learning; Male; Memory; Middle Aged; Neuropsychological Tests; Nootropic Agents; Treatment Outcome

Impacts of High Serum Total Cholesterol Level on Brain Functional Connectivity in Non-Demented Elderly. - Zhang, Ting; Li, He; Zhang, Junying; Li, Xin; Qi, Di; Wang, Nuo; Zhang, Zhanjun (J Alzheimers Dis, 2016)
Epidemiological and clinical studies suggest that high serum cholesterol is a risk factor of dementia. However, the effects of cholesterol on cognition and brain remain largely unclear. This study aims to investigate the associations between serum total cholesterol (TC) and neuropsychological performance, and intrinsic functional networks in non-demented elderly. Among a cohort of 120 community-dwelling Beijing residents, 29 subjects in the high-TC group (1st quartile) and 31 in the low-TC group (4th quartile) were included in this study, and underwent a battery of neuropsychological tests and magnetic resonance imaging (MRI) scans, including T2- and T1-weighted imaging, and resting-state functional MRI. No significant group difference was found in any of the neuropsychological tests used. Stronger connectivity in the default mode network was observed in the high-TC group compared to that in the low-TC group (p <  0.001, uncorrected). While in the salience network (SN), the high-TC group showed lower connectivity in the anterior cingulate cortex and frontal regions, compared to the low-TC group (p <  0.05, FWE corrected). Our findings suggest that in non-demented elderly persons, high serum cholesterol is associated with disruption of functional connectivity in the SN. The results not only deepen our understanding of how cholesterol affects the brain, but are also significant for selecting sensitive indicators for monitoring the impairments of cholesterol on the neural system.
Keywords: Aged; Brain; Brain Mapping; Cholesterol; Cognition; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Nerve Net; Neuropsychological Tests

Impaired Parahippocampus Connectivity in Mild Cognitive Impairment and Alzheimer's Disease. - Liu, Jieqiong; Zhang, Xinqing; Yu, Chunshui; Duan, Yunyun; Zhuo, Junjie; Cui, Yue; Liu, Bing; Li, Kuncheng; Jiang, Tianzi; Liu, Yong (J Alzheimers Dis, 2016)
BACKGROUND: The parahippocampal gyrus (PHG) is an important region of the limbic system that plays an important role in episodic memory. Elucidation of the PHG connectivity pattern will aid in the understanding of memory deficits in neurodegenerative diseases. OBJECTIVE: To investigate if disease severity associated altered PHG connectivity in Alzheimer's disease (AD) exists. METHODS: We evaluated resting-state functional magnetic resonance imaging data from 18 patients with amnestic mild cognitive impairment (MCI), 35 patients with AD, and 21 controls. The PHG connectivity pattern was examined by calculating Pearson's correlation coefficients between the bilateral PHG and whole brain. Group comparisons were performed after controlling for the effects of age and gender. The functional connectivity strength in each identified region was correlated with the MMSE score to evaluate the relationship between connectivity and cognitive ability. RESULTS: Several brain regions of the default mode network showed reduced PHG connectivity in the AD patients, and PHG connectivity was associated with disease severity in the MCI and AD subjects. More importantly, correlation analyses showed that there were positive correlations between the connectivity strengths of the left PHG-PCC/Pcu and left PHG-left MTG and the Mini-Mental State Examination, indicating that with disease progression from MCI to severe AD, damage to the functional connectivity of the PHG becomes increasingly severe. CONCLUSIONS: These results indicate that disease severity is associated with altered PHG connectivity, contributing to knowledge about the reduction in cognitive ability and impaired brain activity that occur in AD/MCI. These early changes in the functional connectivity of the PHG might provide some potential clues for identification of imaging markers for the early detection of MCI and AD.
Keywords: Aged; Alzheimer Disease; Apolipoproteins E; Brain Mapping; Cognitive Dysfunction; Female; Hippocampus; Humans; Limbic System; Magnetic Resonance Imaging; Male; Mental Status Schedule; Neural Pathways; Rest; Severity of Illness Index

The Incidence of Benzodiazepine and Related Drug Use in Persons with and without Alzheimer's Disease. - Saarelainen, Laura; Taipale, Heidi; Koponen, Marjaana; Tanskanen, Antti; Tolppanen, Anna-Maija; Tiihonen, Jari; Hartikainen, Sirpa (J Alzheimers Dis, 2016)
BACKGROUND: Benzodiazepines and related drugs (BZDR) are occasionally used to treat certain symptoms of Alzheimer's disease (AD). However, the risks related to BZDR use are high in older persons. Although frequent BZDR use has been reported in persons with AD, no previous study has focused specifically on the incidence of BZDR use in this population. OBJECTIVE: We investigated the incidence of BZDR use in persons with and without AD during a five-year follow-up. METHODS: The Finnish nationwide, register-based MEDALZ cohort includes all AD cases who received a clinically verified AD diagnosis in 2005-2011 (n = 70,718) and their matched comparison persons. Incidence of BZDR, including benzodiazepines (lorazepam, oxazepam, temazepam, alprazolam, chlordiazepoxide, diazepam, and nitrazepam) and Z-drugs (zolpidem and zopiclone), use was investigated in the cohort from two years before to three years after the diagnosis of AD. Further, initial BZDRs were investigated. RESULTS: The incidence of BZDR use was higher in persons with AD starting from 12 months before the diagnosis and peaked at six months after the diagnosis of AD (incidence rate ratio [IRR] = 2.6, 95% confidence interval [CI] = 2.5-2.8). Benzodiazepines were more frequently initiated by persons with AD, with the incidence peaking at six months after the diagnosis (IRR = 4.5, 95% CI = 4.1-4.9) and remaining over three times higher than in comparison persons until three years after the diagnosis. CONCLUSION: Early symptomatic treatment with BZDRs is contrary to AD treatment guidelines. As BZDRs impair cognition, the observed early treatment with BZDRs may complicate the monitoring of AD treatment effectiveness.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Antipsychotic Agents; Benzodiazepines; Cohort Studies; Female; Finland; Humans; Incidence; Male; Middle Aged; Substance-Related Disorders

Increase of α-Secretase ADAM10 in Platelets Along Cognitively Healthy Aging. - Schuck, Florian; Wolf, Dominik; Fellgiebel, Andreas; Endres, Kristina (J Alzheimers Dis, 2016)
ADAM10 is one of the key players in ectodomain-shedding of the amyloid-β protein precursor (AβPP). Previous research with postmortem tissue has shown reduced expression and activity of ADAM10 within the central nervous system (CNS) of Alzheimer's disease (AD) patients. Determination of cerebral ADAM10 in living humans is hampered by its transmembrane property; only the physiological AβPP cleavage product generated by ADAM10, sAβPPα, can be assessed in cerebrospinal fluid. Establishment of surrogate markers in easily accessible material therefore is crucial. It has been demonstrated that ADAM10 is expressed in platelets and that platelet amount is decreased in AD patients. Just recently it has been shown that platelet ADAM10 and cognitive performance of AD patients positively correlate. In contrast to AD patients, to our knowledge almost no information has been published regarding ADAM10 expression during normal aging. We investigated ADAM10 amount and activity in platelets of cognitively healthy individuals from three different age groups ranging from 22-85 years. Interestingly, we observed an age-dependent increase in ADAM10 levels and activity in platelets.
Keywords: ADAM Proteins; ADAM10 Protein; Adult; Age Factors; Aged; Aged, 80 and over; Aging; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Analysis of Variance; Apolipoprotein E4; Cognition; Female; Healthy Volunteers; Humans; Integrin beta3; Male; Membrane Proteins; Middle Aged; Neuropsychological Tests; Young Adult

Increased Electron Paramagnetic Resonance Signal Correlates with Mitochondrial Dysfunction and Oxidative Stress in an Alzheimer's disease Mouse Brain. - Fang, Du; Zhang, Zhihua; Li, Hang; Yu, Qing; Douglas, Justin T; Bratasz, Anna; Kuppusamy, Periannan; Yan, Shirley ShiDu (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized clinically by cognitive decline and memory loss. The pathological features are amyloid-β peptide (Aβ) plaques and intracellular neurofibrillary tangles. Many studies have suggested that oxidative damage induced by reactive oxygen species (ROS) is an important mechanism for AD progression. Our recent study demonstrated that oxidative stress could further impair mitochondrial function. In the present study, we adopted a transgenic mouse model of AD (mAPP, overexpressing AβPP/Aβ in neurons) and performed redox measurements using in vivo electron paramagnetic resonance (EPR) imaging with methoxycarbamyl-proxyl (MCP) as a redox-sensitive probe for studying oxidative stress in an early stage of pathology in a transgenic AD mouse model. Through assessing oxidative stress, mitochondrial function and cognitive behaviors of mAPP mice at the age of 8-9 months, we found that oxidative stress and mitochondrial dysfunction appeared in the early onset of AD. Increased ROS levels were associated with defects of mitochondrial and cognitive dysfunction. Notably, the in vivo EPR method offers a unique way of assessing tissue oxidative stress in living animals under noninvasive conditions, and thus holds a potential for early diagnosis and monitoring the progression of AD.
Keywords: Adenosine Triphosphate; Age of Onset; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognition; Disease Models, Animal; Electron Spin Resonance Spectroscopy; Electron Transport Complex IV; Female; Humans; Male; Maze Learning; Mice, Transgenic; Mitochondria; Oxidative Stress; Reactive Oxygen Species; Spatial Memory

Increased Intrinsic Activity of Medial-Temporal Lobe Subregions is Associated with Decreased Cortical Thickness of Medial-Parietal Areas in Patients with Alzheimer's Disease Dementia. - Pasquini, Lorenzo; Scherr, Martin; Tahmasian, Masoud; Myers, Nicholas E; Ortner, Marion; Kurz, Alexander; Förstl, Hans; Zimmer, Claus; Grimmer, Timo; Akhrif, Atae; Wohlschläger, Afra M; Riedl, Valentin; et al. (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD), disrupted connectivity between medial-parietal cortices and medial-temporal lobes (MTL) is linked with increased MTL local functional connectivity, and parietal atrophy is associated with increased MTL memory activation. We hypothesized that intrinsic activity in MTL subregions is increased and associated with medial-parietal degeneration and impaired memory in AD. To test this hypothesis, resting-state-functional and structural-MRI was assessed in 22 healthy controls, 22 mild cognitive impairment patients, and 21 AD-dementia patients. Intrinsic activity was measured by power-spectrum density of blood-oxygenation-level-dependent signal, medial-parietal degeneration by cortical thinning. In AD-dementia patients, intrinsic activity was increased for several right MTL subregions. Raised intrinsic activity in dentate gyrus and cornu ammonis 1 was associated with cortical thinning in posterior cingulate cortices, and at-trend with impaired delayed recall. Critically, increased intrinsic activity in the right entorhinal cortex was associated with ipsilateral posterior cingulate degeneration. Our results provide evidence that in AD, intrinsic activity in MTL subregions is increased and associated with medial-parietal atrophy. Results fit a model in which medial-parietal degeneration contributes to MTL dysconnectivity from medial-parietal cortices, potentially underpinning disinhibition-like changes in MTL activity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory Disorders; Middle Aged; Nerve Net; Parietal Lobe; Temporal Lobe

Increased Total Homocysteine Levels Predict the Risk of Incident Dementia Independent of Cerebral Small-Vessel Diseases and Vascular Risk Factors. - Miwa, Kaori; Tanaka, Makiko; Okazaki, Shuhei; Yagita, Yoshiki; Sakaguchi, Manabu; Mochizuki, Hideki; Kitagawa, Kazuo (J Alzheimers Dis, 2016)
BACKGROUND: Homocysteine has been identified as a potential risk factor for stroke, cerebral small-vessel diseases (SVD), and dementia. OBJECTIVE: The present study aimed to investigate the predictive value of homocysteine levels on incident dementia while simultaneously controlling for MRI findings and vascular risk factors. METHODS: Within a Japanese cohort of participants with vascular risk factors in an observational study, we evaluated the association between baseline total homocysteine (tHcy) levels (per 1 μmol/L and the tertile of tHcy), the prevalence of MRI-findings at baseline, and incident all-cause dementia. Baseline brain MRI was used to determine SVD (lacunas, white matter hyperintensities, and cerebral microbleeds [CMBs]) and atrophy (medial-temporal lobe atrophy and bicaudate ratio). Logistic regression analyses were used to estimate the cross-sectional association between tHcy and each of MRI findings. Cox proportional hazards analyses were performed to estimate the longitudinal association between tHcy and dementia. RESULTS: In the 643 subjects (age: 67.2 ± 8.4 years, male: 59% ; education: 12.9 ± 2.6 years), multivariable analyses adjusted for several potential confounders, including estimated glomerular filtration rate (eGFR) and intima-media thickness, showed that highest tHcy tertile was associated with lacunas, CMBs, and strictly deep CMBs. During the mean 7.3-year follow-up (range: 2-13), 47 patients were diagnosed with dementia (Alzheimer's disease: 24; vascular dementia: 18; mixed-type: 3; other: 2). After adjusting for age, gender, APOE ɛ4, education, BMI, MMSE, hypertension, cerebrovascular events, eGFR, and MRI-findings, tHcy level (hazard ratios [HR]: 1.08, p = 0.043) and the highest tertile of tHcy (HR: 2.50, p = 0.047) for all-cause dementia remained significant. CONCLUSIONS: Our results provide additional evidence of tHcy that contributes to increased susceptibility to dementia risk.
Keywords: Aged; Carotid Intima-Media Thickness; Cerebral Small Vessel Diseases; Dementia; Female; Homocysteine; Humans; Incidence; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Predictive Value of Tests; Proportional Hazards Models; Risk Factors; Statistics, Nonparametric

Influence of Incipient Dementia on Hospitalization for Primary Care Sensitive Conditions: A Population-Based Cohort Study. - Pimouguet, Clément; Rizzuto, Debora; Fastbom, Johan; Lagergren, Mårten; Fratiglioni, Laura; Xu, Weili (J Alzheimers Dis, 2016)
BACKGROUND: Studies have reported that moderate/severe stages of dementia are linked to increased hospitalization rates, but little is known about the influence of incipient dementia on hospitalizations for primary care sensitive conditions (PCSCs). OBJECTIVE: To examine the associations between incipient dementia and hospitalization outcomes, including all-cause and PCSC hospitalization. METHODS: A total of 2,268 dementia-free participants in the Swedish National study on Aging and Care-Kungsholmen were interviewed and clinically examined at baseline. Participants aged ≥78 years were followed for 3 years, and those aged 60-72 years, for 6 years. Number of hospitalizations was retrieved from the National Patient Register. Dementia was diagnosed in accordance with Diagnostic and Statistical Manual of Mental Disorders-IV criteria. Hospitalization outcomes were compared in participants who did and did not develop dementia. Zero-inflated Poisson regressions and logistic regressions were used in data analysis. RESULTS: During the follow-up, 175 participants developed dementia. The unadjusted PCSC admission rate was 88.2 per 1000 person-years in those who developed dementia and 25.6 per 1000 person-years in those who did not. In the fully adjusted logistic regression model, incipient dementia was associated with an increased risk of hospitalization for PCSCs (OR = 2.3, 95% CI 1.3-3.9) but not with the number of hospitalizations or with all-cause hospitalization. Risks for hospitalization for diabetes, congestive heart failure, and pyelonephritis were higher in those who developed dementia than in those who did not. About 10% participants had a PCSC hospitalization attributable to incipient dementia. CONCLUSION: People with incipient dementia are more prone to hospitalization for PCSCs but not to all-cause hospitalization.
Keywords: Acute Disease; Age Factors; Aged; Aged, 80 and over; Chronic Disease; Dementia; Female; Follow-Up Studies; Hospitalization; Humans; Logistic Models; Longitudinal Studies; Male; Primary Health Care; Registries; Risk; Sensitivity and Specificity; Socioeconomic Factors; Sweden

Integrating Biomarkers for Underlying Alzheimer's Disease in Mild Cognitive Impairment in Daily Practice: Comparison of a Clinical Decision Support System with Individual Biomarkers. - Rhodius-Meester, Hanneke F M; Koikkalainen, Juha; Mattila, Jussi; Teunissen, Charlotte E; Barkhof, Frederik; Lemstra, Afina W; Scheltens, Philip; Lötjönen, Jyrki; van der Flier, Wiesje M (J Alzheimers Dis, 2016)
BACKGROUND: Recent criteria allow biomarkers to provide evidence of Alzheimer's disease (AD) pathophysiology. How they should be implemented in daily practice remains unclear, especially in mild cognitive impairment (MCI) patients. OBJECTIVE: We evaluated how a clinical decision support system such as the PredictAD tool can aid clinicians to integrate biomarker evidence to support AD diagnosis. METHODS: With available data on demographics, cerebrospinal fluid (CSF), and MRI, we trained the PredictAD tool on a reference population of 246 controls and 491 AD patients. We then applied the identified algorithm to 211 MCI patients. For comparison, we also classified patients based on individual biomarkers (MRI; CSF) and the NIA-AA criteria. Progression to dementia was used as outcome measure. RESULTS: After a median follow up of 3 years, 72 (34%) MCI patients remained stable and 139 (66%) progressed to AD. The PredictAD tool assigned a likelihood of underlying AD to each patient (AUC 0.82). Excluding patients with missing data resulted in an AUC of 0.87. According to the NIA-AA criteria, half of the MCI patients had uninformative biomarkers, precluding an assignment of AD likelihood. A minority (41%) was assigned to high or low AD likelihood with good predictive value. The individual biomarkers showed best value for CSF total tau (AUC 0.86). CONCLUSION: The ability of the PredictAD tool to identify AD pathophysiology was comparable to individual biomarkers. The PredictAD tool has the advantage that it assigns likelihood to all patients, regardless of missing or conflicting data, allowing clinicians to integrate biomarker data in daily practice.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Area Under Curve; Biomarkers; Cognitive Dysfunction; Cohort Studies; Decision Support Systems, Clinical; Disease Progression; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Outcome Assessment (Health Care); Predictive Value of Tests

Japanese Care Location and Medical Procedures for People with Dementia in the Last Month of Life. - Nakanishi, Miharu; Nakashima, Taeko; Shindo, Yumi; Niimura, Junko; Nishida, Atsushi (J Alzheimers Dis, 2016)
BACKGROUND: Dementia-related societies worldwide have called for palliative end-of-life care for those suffering dementia; meanwhile, the Japanese dementia plan was revised on January 2015 to introduce into its objectives the support for end-of-life care via increased social and health care collaboration. OBJECTIVE: The study focus was the use of medical procedures in the last month of life among dementia patients in different care locations in Japan. METHODS: This study was conducted using a retrospective study design. Data from the Survey of Institutions and Establishments for Long-Term Care, which is a nationally representative cross-sectional survey of the public long-term care insurance services, were used. The 6,148 patients who received end-of-life care in their own home, nursing homes, or hospitals in September 2007, 2010, and 2013 were included for analysis. The primary disease of each patient was based on the ICD-10 code; a diagnosis of dementia included F00 (Alzheimer's), F01 (vascular), F02 (other), and F03 (unspecified). RESULTS: Of 6,148 patients, 886 (14.4%) had dementia as a primary disease; most received care in the last month of life in nursing homes (48.0%) or hospitals (44.8%) rather than in their own home (7.2%). Patients were less likely to undergo pain management when their primary disease was dementia (adjusted odds ratio, 0.44; 95% confidence interval, 0.21-0.91). CONCLUSION: Education and policy efforts are required to provide palliative end-of-life care to people with dementia at home. The national dementia plan should also explore possible approaches regarding pain management for dying people who have dementia.
Keywords: Aged, 80 and over; Cross-Sectional Studies; Dementia; Female; Hospitals; Housing; Humans; Japan; Male; Nursing Homes; Pain Management; Retrospective Studies; Terminal Care; Time Factors

JNK: A Putative Link Between Insulin Signaling and VGLUT1 in Alzheimer's Disease. - Rodriguez-Perdigon, Manuel; Solas, Maite; Ramirez, Maria Javier (J Alzheimers Dis, 2016)
In the present work, the involvement of JNK in insulin signaling alterations and its role in glutamatergic deficits in Alzheimer's disease (AD) has been studied. In postmortem cortical tissues, pJNK levels were increased, while insulin signaling and the expression of VGLUT1 were decreased. A significant correlation was found between reduced expression of insulin receptor and VGLUT1. The administration of a JNK inhibitor reversed the decrease in VGLUT1 expression found in a mice model of insulin resistance. It is suggested that activation of JNK in AD inhibits insulin signaling which could lead to a decreased expression of VGLUT1, therefore contributing to the glutamatergic deficit in AD.
Keywords: Aged; Alzheimer Disease; Animals; Brain; Corticosterone; Disease Models, Animal; Female; Humans; Insulin; Insulin Resistance; Male; MAP Kinase Kinase 4; Mice, Inbred C57BL; Mitogen-Activated Protein Kinase 1; Neuroprotective Agents; RNA, Messenger; Vesicular Glutamate Transport Protein 1

The Korean Size/Weight Attribute Test: A Semantic Knowledge Test for Korean Older Adults and Brain-Imaging Evidence. - Yoo, Yongjoon; Shin, Seong A; Park, Soowon; Lee, Ji-Hye; Youn, Jung-Hae; Kim, Yu Kyeong; Lee, Jun-Young (J Alzheimers Dis, 2016)
BACKGROUND: A standardized tool for evaluating semantic knowledge of the Korean population is needed. OBJECTIVE: The purpose of this study was to develop a neuropsychological test for the evaluation of semantic knowledge in the Korean elderly population. METHODS: The Korean version of the Size/Weight Attribute Test (SWAT-K) was developed in reference to the original version. The diagnostic validity of SWAT-K was evaluated with 95 elderly outpatients [67 normal controls; 18 with Alzheimer's disease (AD); 10 with semantic-variant progressive aphasia (SV-PPA)]. Voxel-based morphometry (VBM) was employed to examine associations between SWAT-K scores and morphological changes of the brain. RESULTS: SWAT-K could discriminate the three subject groups (normal >AD, p <  0.001; AD >SV-PPA, p = 0.040), whereas Boston Naming Test could not distinguish SV-PPA from AD. ROC curve analysis confirmed high levels of sensitivity (0.90) and specificity (0.93) for SWAT-K. The test's inter-rater reliability (ICC = 0.827) and test-retest reliability (ICC = 0.666) were assessed as well. VBM found a significant positive correlation (uncorrected p <  0.005, k >  100) between SWAT-K scores and gray matter volume in right inferior frontal cortex (T = 4.08, k = 191) and bilateral temporal cortices (left, T = 4.42, k = 135; right, T = 3.55, k = 253), the areas the most affected in SV-PPA. CONCLUSIONS: SWAT-K is a sensitive and reliable test for evaluating semantic knowledge in the Korean elderly population. Strong positive correlations between SWAT-K scores and the brain areas responsible for semantic processing further corroborate the validity of SWAT-K.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Analysis of Variance; Brain; Dementia; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Psychiatric Status Rating Scales; Republic of Korea; ROC Curve; Semantics

Lack of evidence for a role of HHV-6 in the pathogenesis of Alzheimer's disease. - Agostini, Simone; Mancuso, Roberta; Baglio, Francesca; Cabinio, Monia; Hernis, Ambra; Guerini, Franca Rosa; Calabrese, Elena; Nemni, Raffaello; Clerici, Mario (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD), the most common form of dementia worldwide, is associated with impairment in the mechanisms of the clearing of amyloid-β within a scenario of neuroinflammation. The etiopathogenesis of the AD is unclear, but a role for viral infection is suspected to play a role in initiating the disease. We recently described a positive correlation between high titers of HSV-1-specific antibodies (Ab) and the volumes of brain regions typically affected in disease. OBJECTIVE: The exploration of a possible role for Herpesviridae in AD was extended by analyzing HHV-6-specific humoral immunity in individuals with AD or a diagnosis of amnestic mild cognitive impairment (aMCI), a condition that is often prodromic of the development of AD. METHODS: 59 AD, 60 aMCI, and 61 age-matched healthy controls were enrolled in the study. Serum HHV-6 IgG antibody titers and avidity index were tested by ELISA. Two randomly selected subgroups of AD and aMCI in whom HHV-6 serum antibodies were detected underwent brain magnetic resonance imaging (MRI) by 1.5 T scanner. RESULTS: HHV-6 seroprevalence, antibody titers, and avidity were similar in the three groups. No correlation was found between Ab titers or avidity and brain volumes, either overall or in the regions typically affected by disease. CONCLUSIONS: The lack of any relation between humoral immune response against HHV-6 and AD and aMCI seems to rule out a role for this virus in the pathogenesis of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antibodies; Case-Control Studies; Cognitive Dysfunction; Female; Herpesvirus 1, Human; Herpesvirus 6, Human; Humans; Immunity, Humoral; Magnetic Resonance Imaging; Male; Seroepidemiologic Studies; Temporal Lobe

The Language Profile of Behavioral Variant Frontotemporal Dementia. - Hardy, Chris J D; Buckley, Aisling H; Downey, Laura E; Lehmann, Manja; Zimmerer, Vitor C; Varley, Rosemary A; Crutch, Sebastian J; Rohrer, Jonathan D; Warrington, Elizabeth K; Warren, Jason D (J Alzheimers Dis, 2016)
BACKGROUND: The language profile of behavioral variant frontotemporal dementia (bvFTD) remains to be fully defined. OBJECTIVE: We aimed to quantify the extent of language deficits in this patient group. METHODS: We assessed a cohort of patients with bvFTD (n = 24) in relation to patients with semantic variant primary progressive aphasia (svPPA; n = 14), nonfluent variant primary progressive aphasia (nfvPPA; n = 18), and healthy age-matched individuals (n = 24) cross-sectionally and longitudinally using a comprehensive battery of language and general neuropsychological tests. Neuroanatomical associations of language performance were assessed using voxel-based morphometry of patients' brain magnetic resonance images. RESULTS: Relative to healthy controls, and after accounting for nonverbal executive performance, patients with bvFTD showed deficits of noun and verb naming and single word comprehension, diminished spontaneous propositional speech, and deterioration in naming performance over time. Within the bvFTD group, patients with MAPT mutations had more severe impairments of noun naming and single word comprehension than patients with C9orf72 mutations. Overall the bvFTD group had less severe language deficits than patients with PPA, but showed a language profile that was qualitatively similar to svPPA. Neuroanatomical correlates of naming and word comprehension performance in bvFTD were identified predominantly in inferior frontal and antero-inferior temporal cortices within the dominant hemispheric language network. CONCLUSIONS: bvFTD is associated with a language profile including verbal semantic impairment that warrants further evaluation as a novel biomarker.
Keywords: Aged; Aphasia, Primary Progressive; Atrophy; Brain; Cognition; Comprehension; Female; Frontotemporal Dementia; Humans; Language; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Primary Progressive Nonfluent Aphasia

A Late Life Risk Index for Severe Cognitive Impairment in Mexico. - Downer, Brian; Veeranki, Sreenivas P; Wong, Rebeca (J Alzheimers Dis, 2016)
BACKGROUND: Several dementia risk indices have been developed for older adults in high-income countries. However, no index has been developed for populations in low- or middle-income countries. OBJECTIVE: To create a risk index for predicting severe cognitive impairment among adults aged ≥60 in Mexico and to compare the accuracy of this index to the Dementia Screening Indicator (DSI). METHODS: This study included 3,002 participants from the Mexican Health and Aging Study (MHAS) interviewed in 2001 and 2012. The MHAS risk index included sociodemographic, health, and functional characteristics collected in 2001. A point value based on the beta coefficients from a multivariable logistic regression model was assigned to each risk factor and the total score was calculated. RESULTS: The MHAS risk index (AUC = 0.74 95% CI = 0.70-0.77) and DSI (AUC = 0.72 95% CI = 0.69-0.77) had similar accuracy for discriminating between participants who developed severe cognitive impairment from those who did not. A score of ≥16 on the MHAS risk index had a sensitivity of 0.69 (95% CI = 0.64-0.70) and specificity of 0.67 (95% CI = 0.66-0.69). A score of ≥23 on the DSI had a sensitivity of 0.56 (95% CI = 0.50-0.63) and specificity of 0.78 (95% CI = 0.76-0.79). DISCUSSION: The MHAS risk index and DSI have moderate accuracy for predicting severe cognitive impairment among older adults in Mexico. This provides evidence that existing dementia risk indices may be applicable in low- and middle-income countries such as Mexico. Future research should seek to identify additional risk factors that can improve the accuracy of the MHAS risk index.
Keywords: Age Factors; Aged; Cognitive Dysfunction; Female; Humans; Life Style; Logistic Models; Longitudinal Studies; Male; Mexico; Middle Aged; Multivariate Analysis; Risk Factors; Social Behavior; Socioeconomic Factors

The Latent Dementia Phenotype δ is Associated with Cerebrospinal Fluid Biomarkers of Alzheimer's Disease and Predicts Conversion to Dementia in Subjects with Mild Cognitive Impairment. - Koppara, Alexander; Wolfsgruber, Steffen; Kleineidam, Luca; Schmidtke, Klaus; Frölich, Lutz; Kurz, Alexander; Schulz, Stefanie; Hampel, Harald; Heuser, Isabella; Peters, Oliver; Reischies, Friedel M; Jahn, Holger; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The recently proposed latent variable δ is a new tool for dementia case finding. It is built in a structural equation modeling framework of cognitive and functional data and constitutes a novel endophenotype for Alzheimer's disease (AD) research and clinical trials. OBJECTIVE: To investigate the association of δ with AD biomarkers and to compare the prediction of δ with established scales for conversion to dementia in patients with mild cognitive impairment (MCI). METHODS: Using data from a multicenter memory clinic study, we examined the external associations of the latent variable δ and compared δ with well-established cognitive and functional scales and cognitive-functional composite scores. For that purpose, logistic regressions with cerebrospinal fluid (CSF) biomarkers and conversion to dementia as dependent variables were performed with the investigated scores. The models were tested for significant differences. RESULTS: In patients with MCI, δ based on a broad range of cognitive scales (including the ADAS-cog, the MMSE, and the CERAD neuropsychological battery) predicted an abnormal CSF Aβ42/tau ratio indicative of AD (n = 340, AUC = 0.78, p <  0.001), and predicted incident dementia within 1-3 years of follow-up (n = 525, AUC = 0.84, p <  0.001). These associations were generally stronger than for any other scale or cognitive-functional composite examined. Homologs of δ based on reduced test batteries yielded somewhat lower effects. CONCLUSION: These findings support the interpretation of δ as a construct capturing the disease-related "essence" of cognitive and functional impairments in patients with MCI and dementia, and suggest that δ might become an analytical tool for dementia research.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Phenotype; Predictive Value of Tests; Retrospective Studies; tau Proteins

Lewy Bodies, Vascular Risk Factors, and Subcortical Arteriosclerotic Leukoencephalopathy, but not Alzheimer Pathology, are Associated with Development of Psychosis in Alzheimer's Disease. - Fischer, Corinne E; Qian, Winnie; Schweizer, Tom A; Millikin, Colleen P; Ismail, Zahinoor; Smith, Eric E; Lix, Lisa M; Shelton, Paul; Munoz, David G (J Alzheimers Dis, 2016)
BACKGROUND: The neuropathological correlates of psychosis in Alzheimer's disease (AD) is unclear, with some studies reporting a correlation between psychosis and increased AD pathology while others have found no association. OBJECTIVE: To determine the demographic, clinical, and neuropathological features associated with psychotic symptoms in clinically attributed and neuropathologically proven AD. METHOD: We separately reviewed two overlapping groups of clinically diagnosed (cAD) AD patients with neuropathology data and neuropathologically definite (npAD) cases (regardless of clinical diagnosis) from the NACC database, and explored the relationships between psychosis and clinical variables, neuropathologic correlates, and vascular risk factors. Delusions and hallucinations, defined according to the NPI-Q, were analyzed separately. RESULTS: 1,073 subjects in the database fulfilled our criteria (890 cAD and 728 npAD patients). 34% of cAD and 37% of npAD had psychotic symptoms during their illness. Hallucinations were associated with greater cognitive and functional impairments on the MMSE and CDR, while delusional patients showed less impairment on CDR, consistent across cAD and npAD groups. Burden of AD pathology appears to relate to presence of psychotic symptoms in the clinical AD group, but this result is not confirmed in the neuropathologically confirmed group suggesting the findings in the clinical group were due to misdiagnosis of AD. Lewy body pathology, subcortical arteriosclerotic leukoencephalopathy, and vascular risk factors, including a history of hypertension and diabetes, were associated with the development of psychosis. METHOD: Vascular and Lewy body pathologies and vascular risk factors are important modifiers of the risk of psychosis in AD.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Databases, Factual; Dementia, Vascular; Female; Hemorrhage; Humans; Lewy Bodies; Male; Middle Aged; Psychiatric Status Rating Scales; Psychotic Disorders; Retrospective Studies; Risk Factors; Severity of Illness Index; Surveys and Questionnaires

Lifelong Reading Disorder and Mild Cognitive Impairment: Implications for Diagnosis. - Lebowitz, Brian K; Weinstein, Cheryl; Beiser, Alexa; Seshadri, Sudha; Wolf, Philip A; Auerbach, Sandford; Au, Rhoda (J Alzheimers Dis, 2016)
Although neuropsychological tests are commonly used in the evaluation of possible mild cognitive impairment (MCI), poor test scores may be indicative of factors other than neurological compromise. The current study assessed the role of lifelong reading disorder on MCI classification. Community dwelling older adults with a suspected developmental reading disorder were identified by inference based on reading test performance. Individuals with a suspected reading disorder were significantly more likely to perform at a level consistent with MCI on several commonly used neuropsychological tests. The findings suggest a relationship between a history of reading disorder and MCI classification.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Dyslexia; Female; Humans; Independent Living; Longitudinal Studies; Male; Neuropsychological Tests; Psychometrics; Retrospective Studies

Linguistic Features Identify Alzheimer's Disease in Narrative Speech. - Fraser, Kathleen C; Meltzer, Jed A; Rudzicz, Frank (J Alzheimers Dis, 2016)
BACKGROUND: Although memory impairment is the main symptom of Alzheimer's disease (AD), language impairment can be an important marker. Relatively few studies of language in AD quantify the impairments in connected speech using computational techniques. OBJECTIVE: We aim to demonstrate state-of-the-art accuracy in automatically identifying Alzheimer's disease from short narrative samples elicited with a picture description task, and to uncover the salient linguistic factors with a statistical factor analysis. METHODS: Data are derived from the DementiaBank corpus, from which 167 patients diagnosed with "possible" or "probable" AD provide 240 narrative samples, and 97 controls provide an additional 233. We compute a number of linguistic variables from the transcripts, and acoustic variables from the associated audio files, and use these variables to train a machine learning classifier to distinguish between participants with AD and healthy controls. To examine the degree of heterogeneity of linguistic impairments in AD, we follow an exploratory factor analysis on these measures of speech and language with an oblique promax rotation, and provide interpretation for the resulting factors. RESULTS: We obtain state-of-the-art classification accuracies of over 81% in distinguishing individuals with AD from those without based on short samples of their language on a picture description task. Four clear factors emerge: semantic impairment, acoustic abnormality, syntactic impairment, and information impairment. CONCLUSION: Modern machine learning and linguistic analysis will be increasingly useful in assessment and clustering of suspected AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Diagnosis, Computer-Assisted; Factor Analysis, Statistical; Female; Humans; Language Disorders; Linguistics; Logistic Models; Machine Learning; Male; Mental Status Schedule; Middle Aged; Narration; Photic Stimulation; Speech; Verbal Behavior

Longitudinal Changes in Functional Brain Connectivity Predicts Conversion to Alzheimer's Disease. - Serra, Laura; Cercignani, Mara; Mastropasqua, Chiara; Torso, Mario; Spanò, Barbara; Makovac, Elena; Viola, Vanda; Giulietti, Giovanni; Marra, Camillo; Caltagirone, Carlo; Bozzali, Marco (J Alzheimers Dis, 2016)
This longitudinal study investigates the modifications in structure and function occurring to typical Alzheimer's disease (AD) brains over a 2-year follow-up, from pre-dementia stages of disease, with the aim of identifying biomarkers of prognostic value. Thirty-one patients with amnestic mild cognitive impairment were recruited and followed-up with clinical, neuropsychological, and MRI assessments. Patients were retrospectively classified as AD Converters or Non-Converters, and the data compared between groups. Cross-sectional MRI data at baseline, assessing volume and functional connectivity abnormalities, confirmed previous findings, showing a more severe pattern of regional grey matter atrophy and default-mode network disconnection in Converters than in Non-Converters. Longitudinally, Converters showed more grey matter atrophy in the frontotemporal areas, accompanied by increased connectivity in the precuneus. Discriminant analysis revealed that functional connectivity of the precuneus within the default mode network at baseline is the parameter able to correctly classify patients in Converters and Non-Converters with high sensitivity, specificity, and accuracy.
Keywords: Aged; Alzheimer Disease; Atrophy; Brain; Brain Mapping; Cognitive Dysfunction; Cross-Sectional Studies; Discriminant Analysis; Disease Progression; Female; Follow-Up Studies; Gray Matter; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Neural Pathways; Neuropsychological Tests; Prognosis; Rest

Longitudinal Memory Profiles in Behavioral-Variant Frontotemporal Dementia and Alzheimer's Disease. - Schubert, Samantha; Leyton, Cristian E; Hodges, John R; Piguet, Olivier (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) and behavioral-variant of frontotemporal dementia (bvFTD) can present with an overlapping neuropsychological profile, which often hinders their clinical differentiation. OBJECTIVE: To compare changes over time in memory, general cognition tasks, and functional scales between bvFTD and AD. METHODS: Consecutive cases diagnosed with probable bvFTD (n = 22) and typical AD (n = 31) with at least two clinical visits were selected. Of these, 13 (9 AD, 4 bvFTD) underwent Pittsburgh compound B PET scan, which supported the clinical diagnosis in all cases. Mixed-model regressions were used to estimate the differential rate of decline on selected tasks between cohorts. RESULTS: Analyses demonstrated that, despite equivalent baseline performance, bvFTD patients experienced a more rapid functional deterioration and a steeper decline in global cognition than AD patients. At baseline, both groups were impaired on executive function and memory tasks compared to controls, but these deficits were more marked in the bvFTD group. In addition, performance on these domains continued to decline more rapidly in this group. CONCLUSIONS: Neither the initial neuropsychological assessment nor projected performances can reliably distinguish the totality of bvFTD and AD individuals. Nevertheless, annual rates of progression on cognitive tasks provide valuable information and will potentially help establish the impact of future therapeutic treatments in these dementia syndromes.
Keywords: Alzheimer Disease; Aniline Compounds; Brain; Diagnosis, Differential; Disease Progression; Executive Function; Female; Follow-Up Studies; Frontotemporal Dementia; Humans; Longitudinal Studies; Male; Memory; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Thiazoles

Longitudinal Protein Changes in Blood Plasma Associated with the Rate of Cognitive Decline in Alzheimer's Disease. - Sattlecker, Martina; Khondoker, Mizanur; Proitsi, Petroula; Williams, Stephen; Soininen, Hilkka; Kłoszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Dobson, Richard Jb (J Alzheimers Dis, 2016)
Biomarkers of Alzheimer's disease (AD) progression are needed to support the development of urgently needed disease modifying drugs. We employed a SOMAscan assay for quantifying 1,001 proteins in blood samples from 90 AD subjects, 37 stable mild cognitive impaired (MCI) subjects, 39 MCI subjects converting to AD within a year and 69 controls at baseline and one year follow up. We used linear mixed effects models to identify proteins changing significantly over one year with the rate of cognitive decline, which was quantified as the reduction in Mini Mental State Examination (MMSE) scores. Additionally, we investigated proteins changing differently across disease groups and during the conversion from MCI to AD. We found that levels of proteins belonging to the complement cascade increase significantly in fast declining AD patients. Longitudinal changes in the complement cascade might be a surrogate biomarker for disease progression. We also found that members of the cytokine-cytokine receptor interaction pathway change during AD when compared to healthy aging subjects.
Keywords: Aged; Alzheimer Disease; Biomarkers; Cognition; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Humans; Linear Models; Longitudinal Studies; Male; Mental Status Schedule; Neuropsychological Tests

Looking for Neuroimaging Markers in Frontotemporal Lobar Degeneration Clinical Trials: A Multi-Voxel Pattern Analysis Study in Granulin Disease. - Premi, Enrico; Cauda, Franco; Costa, Tommaso; Diano, Matteo; Gazzina, Stefano; Gualeni, Vera; Alberici, Antonella; Archetti, Silvana; Magoni, Mauro; Gasparotti, Roberto; Padovani, Alessandro; Borroni, Barbara (J Alzheimers Dis, 2016)
In light of future pharmacological interventions, neuroimaging markers able to assess the response to treatment would be crucial. In Granulin (GRN) disease, preclinical data will prompt pharmacological trials in the future. Two main points need to be assessed: (1) to identify target regions in different disease stages and (2) to determine the most accurate functional and structural neuroimaging index to be used. To this aim, we have taken advantage of the multivariate approach of multi-voxel pattern analysis (MVPA) to explore the information of brain activity patterns in a cohort of GRN Thr272fs carriers at different disease stages (14 frontotemporal dementia (FTD) patients and 17 asymptomatic carriers) and a group of 33 healthy controls. We studied structural changes by voxel-based morphometry (VBM), functional connectivity by assessing salience, default mode, fronto-parietal, dorsal attentional, executive networks, and local connectivity by regional homogeneity, amplitude of low frequency fluctuations (ALFF), fractional ALFF (fALFF), degree centrality, and voxel-mirrored homotopic connectivity. In FTD patients with GRN mutation, the most predictive measure was VBM structural analysis, while in asymptomatic carriers the best predictor marker was the local connectivity measure (fALFF). Altogether, all indexes demonstrated fronto-temporo-parietal damage in GRN pathology, with widespread structural damage of fronto-parietal and temporal regions when disease is overt. MVPA could be of aid in identifying the most accurate neuroimaging marker for clinical trials. This approach was able to identify both the target region and the best neuroimaging approach, which would be specific in the different disease stages. Further studies are needed to simultaneously integrate multimodal indexes in a classifier able to trace the disease progression moving from preclinical to clinical stage of the disease.
Keywords: Adult; Aged; Brain; Brain Mapping; Cohort Studies; Female; Frontotemporal Lobar Degeneration; Humans; Image Processing, Computer-Assisted; Intercellular Signaling Peptides and Proteins; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Neural Pathways; Oxygen; Phenylalanine; Threonine

Low Plasma Cholinesterase Activities are Associated with Deficits in Spatial Orientation, Reduced Ability to Perform Basic Activities of Daily Living, and Low Body Mass Index in Patients with Progressed Alzheimer's Disease. - Dingova, Dominika; Fazekas, Tomas; Okuliarova, Petra; Strbova, Jaroslava; Kucera, Matej; Hrabovska, Anna (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a progressive and irreversible neurodegenerative disorder characterized by a central cholinergic deficit. Non-neuronal cholinergic changes are, however, described as well. Here we focused on possible changes in the activity of the plasma cholinesterases, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), in hospitalized AD patients. We analyzed plasma AChE and BChE activities with regards to age, gender, body mass index (BMI), cognitive functions, and ability to perform activities of daily living in AD patients in comparison to healthy subjects. We observed lower AChE activity and trend toward lower BChE activity in AD patients, which both correlated with low BMI. AD patients unable to perform basic activities of daily living (feeding, bathing, dressing, and grooming) showed reduced plasma AChE activities, while worse spatial orientation was linked to lower BChE activities. Three out of four AD patients with the lowest BChE activities died within one year. In conclusion, progressed AD was accompanied by lower plasma AChE activity and trend toward lower BChE activity, which correlated with BMI and deficits in different components of the AD.
Keywords: Acetylcholinesterase; Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Blood Chemical Analysis; Body Mass Index; Butyrylcholinesterase; Female; Hospitalization; Humans; Male; Middle Aged; Orientation, Spatial

Low Prevalence of Mixed Dementia in a Cohort of 2,000 Elderly Patients in a Memory Clinic Setting. - Claus, Jules J; Staekenborg, Salka S; Roorda, Jelmen J; Stevens, Martijn; Herderschee, Dirk; van Maarschalkerweerd, Willy; Schuurmans, Lilly; Tielkes, Caroline E M; Koster, Pieter; Bavinck, Chris; Scheltens, Philip (J Alzheimers Dis, 2016)
BACKGROUND: It is generally assumed that with increasing age, pathology in clinically diagnosed Alzheimer's disease (AD) becomes more mixed, i.e., co-existence of amyloid plaques and cerebrovascular pathology. OBJECTIVE: To test the hypothesis of increasing prevalence of mixed dementia in late-onset clinically diagnosed Alzheimer's disease (AD) in a single-center memory clinic population. METHODS: Patients included had diagnoses of AD (n = 832), subjective cognitive impairment (SCI, n = 333), mild cognitive impairment (MCI, n = 492), vascular dementia (VaD, n = 57), other dementia (n = 53), or other diagnosis (n = 233). Prevalence of severe white matter lesions (WML) was defined as a score of 2 or higher on the Fazekas-scale on brain computed tomography to classify AD patients as having mixed dementia. We examined the effect of age on WML using multiple linear regression analysis, and AD patients were compared to SCI to determine the effect of disease on WML. RESULTS: Prevalence of severe WML was 33.6% in AD patients (mixed dementia), 11.4% in SCI, 22.7% in MCI, 75.4% in VaD, 3.8% in other dementia, and 15.5% in other diagnosis. With increasing age there was a significant and similar increase of WML scores in SCI, MCI, AD, other dementia, and other diagnosis, indicating no effect modification by AD. The difference between AD patients and SCI averaged 0.16 on the WML score and difference in percentage severe WML between AD and SCI patients was 15% across all ages. CONCLUSION: We found a low prevalence of mixed dementia. Furthermore, severe WML in AD was largely explained by age rather than effect of disease.
Keywords: Age Factors; Aged; Aged, 80 and over; Analysis of Variance; Cognitive Dysfunction; Cohort Studies; Dementia; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Prevalence; Regression Analysis; Risk Factors; Tomography Scanners, X-Ray Computed

Lower Prevalence of Alzheimer's Disease among Tibetans: Association with Religious and Genetic Factors. - Huang, Fukai; Shang, Ying; Luo, Yuandai; Wu, Peng; Huang, Xue; Tan, Xiaohui; Lu, Xingyi; Zhen, Lifang; Hu, Xianda (J Alzheimers Dis, 2016)
BACKGROUND: The prevalence of dementia differs among racial groups, the highest prevalence being in Latin America (8.5%) compared to sub-Saharan African regions (2-4%). The most common type of dementia is Alzheimer's disease (AD). OBJECTIVE: To estimate the prevalence of AD in the Qinghai-Tibet plateau and to investigate the related factors. METHODS: This was a cross-sectional, multistage cluster sampling design survey. Data was collected from May 2014 to September 2014 from 4,060 Tibetan aged >60 years. Participants underwent clinical examinations and neuropsychological evaluations. MALDI-TOF was used to test the genotypes of CLU, TFAM, TP53INP1, IGHV1-67, CR1, ApoE, and BIN1. Logistic regression models were used to ascertain the associations with AD. RESULTS: The prevalence of AD among Tibetan individuals aged >60 years was 1.33% (95% CI: 0.98-1.69). The CLU haplotypes AA+GA (odds ratio (OR) = 4.483; 95% CI: 1.069-18.792) of rs2279590 was correlated with AD. The CLU haplotypes GG+GC (OR = 0.184; 95% CI: 0.038-0.888) of rs9331888 and kowtow (OR = 0.203; 95% CI 0.046-0.896) were negatively correlated with AD. CONCLUSION: A low prevalence of AD was found in Tibetans from the Qinghai-Tibet plateau. Multivariate analysis might suggest that regular "mind-body" religious meditative activities may be negatively associated with AD in this population, as well as the CLU genotype at rs9331888.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Clusterin; Cognition Disorders; Cross-Sectional Studies; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Psychiatric Status Rating Scales; Religion; Risk Factors; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Tibet

Maintenance of Cognitive Performance and Mood for Individuals with Alzheimer's Disease Following Consumption of a Nutraceutical Formulation: A One-Year, Open-Label Study. - Remington, Ruth; Bechtel, Cynthia; Larsen, David; Samar, Annemarie; Page, Robert; Morrell, Christopher; Shea, Thomas B (J Alzheimers Dis, 2016)
Nutritional interventions have shown varied efficacy on cognitive performance during Alzheimer's disease (AD). Twenty-four individuals diagnosed with AD received a nutraceutical formulation (NF: folate, alpha-tocopherol, B12, S-adenosyl methioinine, N-acetyl cysteine, acetyl-L-carnitine) under open-label conditions (ClinicalTrials.gov NCT01320527). Primary outcome was cognitive performance. Secondary outcomes were behavioral and psychological symptoms of dementia (BPSD) and activities of daily living. Participants maintained their baseline cognitive performance and BPSD over 12 months. These findings are consistent with improvement in cognitive performance and BPSD in prior placebo-controlled studies with NF, and contrast with the routine decline for participants receiving placebo.
Keywords: Aged; Aged, 80 and over; alpha-Tocopherol; Alzheimer Disease; Cognition Disorders; Dietary Supplements; Disease Progression; Female; Folic Acid; Follow-Up Studies; Humans; Male; Mood Disorders; Neuropsychological Tests; Psychiatric Status Rating Scales; Time Factors; Vitamin B 12

MAPT H1 Haplotype is Associated with Late-Onset Alzheimer's Disease Risk in APOEɛ4 Noncarriers: Results from the Dementia Genetics Spanish Consortium. - Pastor, Pau; Moreno, Fermín; Clarimón, Jordi; Ruiz, Agustin; Combarros, Onofre; Calero, Miguel; López de Munain, Adolfo; Bullido, Maria J; de Pancorbo, Marian M; Carro, Eva; Antonell, Anna; Coto, Eliecer; et al. (J Alzheimers Dis, 2016)
The MAPT H1 haplotype has been linked to several disorders, but its relationship with Alzheimer's disease (AD) remains controversial. A rare variant in MAPT (p.A152T) has been linked with frontotemporal dementia (FTD) and AD. We genotyped H1/H2 and p.A152T MAPT in 11,572 subjects from Spain (4,327 AD, 563 FTD, 648 Parkinson's disease (PD), 84 progressive supranuclear palsy (PSP), and 5,950 healthy controls). Additionally, we included 101 individuals from 21 families with genetic FTD. MAPT p.A152T was borderline significantly associated with FTD [odds ratio (OR) = 2.03; p = 0.063], but not with AD. MAPT H1 haplotype was associated with AD risk (OR = 1.12; p = 0.0005). Stratification analysis showed that this association was mainly driven by APOE ɛ4 noncarriers (OR = 1.14; p = 0.0025). MAPT H1 was also associated with risk for PD (OR = 1.30; p = 0.0003) and PSP (OR = 3.18; p = 8.59 × 10-8) but not FTD. Our results suggest that the MAPT H1 haplotype increases the risk of PD, PSP, and non-APOE ɛ4 AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Female; Frontotemporal Dementia; Genetic Predisposition to Disease; Haplotypes; Humans; Logistic Models; Male; Middle Aged; Polymorphism, Single Nucleotide; Spain; tau Proteins

Measuring Information Processing Speed in Mild Cognitive Impairment: Clinical Versus Research Dichotomy. - Haworth, Judy; Phillips, Michelle; Newson, Margaret; Rogers, Peter J; Torrens-Burton, Anna; Tales, Andrea (J Alzheimers Dis, 2016)
A substantial body of research evidence is indicative of disproportionately slowed information processing speed in a wide range of multi-trial, computer-based, neuroimaging- and electroencephalography-based reaction time (RT) tests in Alzheimer's disease and mild cognitive impairment (MCI). However, in what is arguably a dichotomy between research evidence and clinical practice, RT associated with different brain functions is rarely assessed as part of their diagnosis. Indeed, often only the time taken to perform a single, specific task, commonly the Trail making test (TMT), is measured. In clinical practice therefore, there can be a failure to assess adequately the integrity of the rapid, serial information processing and response, necessary for efficient, appropriate, and safe interaction with the environment. We examined whether a typical research-based RT task could at least match the TMT in differentiating amnestic MCI (aMCI) from cognitively healthy aging at group level. As aMCI is a heterogeneous group, typically containing only a proportion of individuals for whom aMCI represents the early stages of dementia, we examined the ability of each test to provide intra-group performance variation. The results indicate that as well as significant slowing in performance of the operations involved in TMT part B (but not part A), individuals with aMCI also experience significant slowing in RT compared to controls. The results also suggest that research-typical RT tests may be superior to the TMT in differentiating between cognitively healthy aging and aMCI at group level and in revealing the performance variability one would expect from an etiologically heterogeneous disorder such as aMCI.
Keywords: Aged; Aged, 80 and over; Attention; Cognitive Dysfunction; Electroencephalography; Female; Humans; Male; Mental Processes; Mental Status Schedule; Middle Aged; Neuroimaging; Neuropsychological Tests; Photic Stimulation; Reaction Time; Residence Characteristics

Memory for Public Events in Mild Cognitive Impairment and Alzheimer's Disease: The Importance of Rehearsal. - Langlois, Roxane; Joubert, Sven; Benoit, Sophie; Dostie, Valérie; Rouleau, Isabelle (J Alzheimers Dis, 2016)
Ribot's law refers to the better preservation of remote memories compared with recent ones that presumably characterizes retrograde amnesia. Even if Ribot-type temporal gradient has been extensively studied in retrograde amnesia, particularly in Alzheimer's disease (AD), this pattern has not been consistently found. One explanation for these results may be that rehearsal frequency rather than remoteness accounts for the better preservation of these memories. Thus, the aim of present study was to address this question by studying retrograde semantic memory in subjects with amnestic mild cognitive impairment (aMCI) (n = 20), mild AD (n = 20) and in healthy older controls (HC; n = 19). In order to evaluate the impact of repetition as well as the impact of remoteness, we used a test assessing memory for enduring and transient public events that occurred in the recent and remote past. Results show no clear temporal gradient across time periods (1960-1975; 1976-1990; 1991-2005; 2006-2011), but a better performance was observed in all three groups for enduring compared with transient events. Moreover, although deficits were globally found in both patients groups compared with HC, more specific analyses revealed that aMCI patients were only impaired on transient events while AD patients were impaired on both transient and enduring events. Exploratory analyses also revealed a tendency suggesting preservation of remote transient events in aMCI. These findings are discussed with regards to memory consolidation models.
Keywords: Aged; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Learning; Male; Memory; Psychological Tests; Semantics

A Meta-Analysis of Alzheimer's Disease Incidence and Prevalence Comparing African-Americans and Caucasians. - Steenland, Kyle; Goldstein, Felicia C; Levey, Allan; Wharton, Whitney (J Alzheimers Dis, 2016)
BACKGROUND: Several studies have shown higher Alzheimer's disease (AD) incidence rates are in African-Americans (AAs) than Caucasians (CCs). If this finding is consistent across studies, it raises important etiologic questions regarding factors responsible for this discrepancy. It also affects the likely public health burden of AD in the US in the future, as the non-Caucasian population becomes the majority. OBJECTIVE: Estimate the AA/CC rate ratio for AD incidence across all available studies. METHODS: We conducted a meta-analysis of population-based studies for the rate ratio (RR) of AD incidence for AAs versus CCs, after identifying six relevant studies from the literature. We calculated an AA/CC rate ratio across all studies using inverse-variance weighting, and assessed inter-study heterogeneity. Using these incidence data, as well as data on survival after diagnosis, and on all-cause mortality, we also estimated the US prevalence of AD among AAs and CCs. RESULTS: There were six population-based studies with data comparing AD incidence between AAs and CCs, with an estimated 370 AA and 640 CC incident cases. The meta-analysis RR showed that the AD rate for AAs was 64% higher than for CCs (RR = 1.64 (95% CI 1.35-2.00)) 1.35-2.00)), with no evidence of heterogeneity. We estimated the current US AD prevalence for ages 65-90 to be 5.5% for CCs, and 8.6% for AAs (prevalence ratio 1.56). CONCLUSION: AAs have an increased risk of incident and prevalent AD compared to CCs for reasons which are unknown, but are hypothesized to reflect biological, psychological, and socioeconomic factors.
Keywords: African Americans; Alzheimer Disease; Community Health Planning; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Male; Prevalence

Metabolic Syndrome and Mild Cognitive Impairment: A Case-Control Study among Elderly in a Shanghai Suburb. - Yao, Qian; Jiang, Guo-Xin; Zhou, Zhi-Ming; Chen, Jin-Mei; Cheng, Qi (J Alzheimers Dis, 2016)
BACKGROUND: Metabolic syndrome (MetS) maybe associated with mild cognitive impairment (MCI). OBJECTIVE: To investigate the relationship between MetS, with its individual or combined components, and MCI among elderly. METHODS: A case-control study was conducted among the elderly aged 65 years and over in a community located in the southwestern suburb of Shanghai, China. The Chinese version of the Mini-Mental Status Examination (C-MMSE) was used to screen subjects with MCI. Associations of MetS with its individual or combined components and MCI were analyzed using conditional regression analyses with or without adjustment for gender, education, current smoking, current drinking, and physical activities. RESULTS: There were 379 subjects with MCI and 379 gender- and age-matched healthy controls in the study. Compared with healthy controls in univariate analyses, subjects with MCI were more likely to have less time spent on physical activity, lower C-MMSE score, heavier weight, larger waistline and hipline, higher diastolic blood pressure, higher body mass index, higher abdominal obesity index, higher serum glycated hemoglobin, higher serum triglycerides, higher serum cholesterol, higher serum uric acid, and higher serum alanine aminotransferase. After multivariable adjustment, MetS was significantly associated with an increased risk of MCI (OR = 2.277; 95% CI: 1.086-4.773). Among MetS components, abdominal obesity (OR = 2.101; 95% CI: 1.224-3.608) and hypertension (OR = 2.075; 95% CI: 1.170-3.678) showed a significant association with MCI, respectively; while these two components were combined, the association was stronger (OR = 2.459; 95% CI: 1.360-4.447). CONCLUSION: MetS and its components, particularly abdominal obesity and hypertension, were found to be significantly associated with the risk of MCI.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Case-Control Studies; Chi-Square Distribution; China; Cities; Cognition Disorders; Community Health Planning; Female; Humans; Male; Mental Status Schedule; Metabolic Diseases; Risk Factors

Metformin Facilitates Amyloid-β Generation by β- and γ-Secretases via Autophagy Activation. - Son, Sung Min; Shin, Hong-Joon; Byun, Jayoung; Kook, Sun Young; Moon, Minho; Chang, Yu Jin; Mook-Jung, Inhee (J Alzheimers Dis, 2016)
The evidence of strong pathological associations between type 2 diabetes and Alzheimer's disease (AD) has increased in recent years. Contrary to suggestions that anti-diabetes drugs may have potential for treating AD, we demonstrate here that the insulin sensitizing anti-diabetes drug metformin (Glucophage®) increased the generation of amyloid-β (Aβ), one of the major pathological hallmarks of AD, by promoting β- and γ-secretase-mediated cleavage of amyloid-β protein precursor (AβPP) in SH-SY5Y cells. In addition, we show that metformin caused autophagosome accumulation in Tg6799 AD model mice. Extremely high γ-secretase activity was also detected in autophagic vacuoles, apparently a novel site of Aβ peptide generation. Together, these data suggest that metformin-induced accumulation of autophagosomes resulted in increased γ-secretase activity and Aβ generation. Additional experiments indicated that metformin increased phosphorylation of AMP-activated protein kinase, which activates autophagy by suppressing mammalian target of rapamycin (mTOR). The suppression of mTOR then induces the abnormal accumulation of autophagosomes. We conclude that metformin, an anti-diabetes drug, may exacerbate AD pathogenesis by promoting amyloidogenic AβPP processing in autophagosomes.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Autophagy; Cell Line, Tumor; Disease Models, Animal; Female; Humans; Hypoglycemic Agents; Lysosomes; Metformin; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microscopy, Electron; Mutation; Neuroblastoma; Signal Transduction

Metformin in Amnestic Mild Cognitive Impairment: Results of a Pilot Randomized Placebo Controlled Clinical Trial. - Luchsinger, Jose A; Perez, Thania; Chang, Helena; Mehta, Pankaj; Steffener, Jason; Pradabhan, Gnanavalli; Ichise, Masanori; Manly, Jennifer; Devanand, Davangere P; Bagiella, Emilia (J Alzheimers Dis, 2016)
Diabetes and hyperinsulinemia may be risk factors for Alzheimer's disease (AD). We conducted a pilot study of metformin, a medication efficacious in treating and preventing diabetes while reducing hyperinsulinemia, among persons with amnestic mild cognitive impairment (aMCI) with the goal of collecting preliminary data on feasibility, safety, and efficacy. Participants were 80 men and women aged 55 to 90 years with aMCI, overweight or obese, without treated diabetes. We randomized participants to metformin 1000 mg twice a day or matching placebo for 12 months. The co-primary clinical outcomes were changes from baseline to 12 months in total recall of the Selective Reminding Test (SRT) and the score of the Alzheimer's Disease Assessment Scale-cognitive subscale (ADAS-cog). The secondary outcome was change in relative glucose uptake in the posterior cingulate-precuneus in brain fluorodeoxyglucose positron emission tomography. Change in plasma Aβ42 was an exploratory outcome. The mean age of participants was 65 years. Fifty percent of participants were women. The only baseline variable that was different between the arms was the ADAS-Cog. Metformin could not be tolerated by 7.5% of participants; 15% tolerated 500 mg/day, 35% tolerated 1000 mg/day, 32.5% tolerated 1500 mg/day, and only 10% tolerated the maximum dose. There were no serious adverse events related to metformin. The 7.5% of persons who did not tolerate metformin reported gastrointestinal symptoms. After adjusting for baseline ADAS-cog, changes in total recall of the SRT favored the metformin group (9.7±8.5 versus 5.3±8.5; p = 0.02). Differences for other outcomes were not significant. A larger trial seems warranted to evaluate the efficacy and cognitive safety of metformin in prodromal AD.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Double-Blind Method; Female; Follow-Up Studies; Glucose; Humans; Male; Metformin; Middle Aged; Nootropic Agents; Overweight; Peptide Fragments; Pilot Projects; Positron-Emission Tomography; Psychological Tests; Severity of Illness Index; Treatment Outcome

Mild Cognitive Impairment and Susceptibility to Scams in Old Age. - Han, S Duke; Boyle, Patricia A; James, Bryan D; Yu, Lei; Bennett, David A (J Alzheimers Dis, 2016)
BACKGROUND: Falling victim to financial scams can have a significant impact upon social and financial wellbeing and independence. A large proportion of scam victims are older adults, but whether older victims with mild cognitive impairment (MCI) are at higher risk remains unknown. OBJECTIVE: We tested the hypothesis that older persons with MCI exhibit greater susceptibility to scams compared to those without cognitive impairment. METHODS: Seven hundred and thirty older adults without dementia were recruited from the Rush Memory and Aging Project, a community-based epidemiologic study of aging. Participants completed a five-item self-report measure of susceptibility to scams, a battery of cognitive measures, and clinical diagnostic evaluations. RESULTS: In models adjusted for age, education, and gender, the presence of MCI was associated with greater susceptibility to scams (B = 0.125, SE = 0.063, p-value = 0.047). Further, in analyses of the role of specific cognitive systems in susceptibility to scams among persons with MCI (n = 144), the level of performance in two systems, episodic memory and perceptual speed abilities, were associated with susceptibility. CONCLUSIONS: Adults with MCI may be more susceptible to scams in old age than older persons with normal cognition. Lower abilities in specific cognitive systems, particularly perceptual speed and episodic memory, may contribute to greater susceptibility to scams in those with MCI.
Keywords: Aged; Aged, 80 and over; Aging; Cognitive Dysfunction; Crime Victims; Disease Susceptibility; Female; Humans; Male; Memory, Episodic; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Residence Characteristics; Self Report

Mindfulness in the Maintenance of Cognitive Capacities in Alzheimer's Disease: A Randomized Clinical Trial. - Quintana-Hernández, Domingo J; Miró-Barrachina, María T; Ibáñez-Fernández, Ignacio J; Pino, Angelo Santana-Del; Quintana-Montesdeoca, María P; Rodríguez-de Vera, Bienvenida; Morales-Casanova, David; Pérez-Vieitez, María Del Carmen; Rodríguez-García, Javier; Bravo-Caraduje, Noelia (J Alzheimers Dis, 2016)
BACKGROUND: The Canary Islands longitudinal study on non-pharmacological treatments showed the overall effectiveness of mindfulness in Alzheimer's disease (AD). However, no specific data on the maintenance of cognitive capacities were presented. OBJECTIVE: To determine whether the practice of mindfulness modifies the course of cognitive impairment in AD. METHODS: DESIGN: Longitudinal, non-inferiority and equivalence, randomized clinical trial, repeated-measures design, with three experimental groups and one control group. PARTICIPANTS: Patients with AD who voluntarily attended the Lidia García Foundation (n = 502). Only those who were treated with donepezil and MMSE ≥18 were included (n = 120). INTERVENTION: Over a two-year period, each group carried out three weekly sessions of stimulation based on mindfulness, cognitive stimulation therapy, and progressive muscle relaxation. MEASURES: Cognitive assessment CAMDEX-R (MMSE and CAMCOG). STATISTICAL ANALYSIS: Repeated-measures ANOVA (p <  0.05) and the effect size Cohen's d were performed. RESULTS: The mindfulness group showed significant scores compared with the control and muscle relaxation groups (p <  0.05), while mindfulness and cognitive stimulation therapy were equivalent (p≥0.05). Group cognitive stimulation evolved better than the control (p <  0.05) group but not better than the muscle relaxation group (p≥0.05). The effect size compared over two years was large for the mindfulness group (p≥0.80), moderate for the relaxation group (p≥0.50), and low for the cognitive stimulation group (p≥0.20). CONCLUSION: The practice of mindfulness maintained cognitive function over a period of two years. This longitudinal study suggests that mindfulness can be used as a non-pharmacological treatment to slow cognitive impairment in AD.
Keywords: Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Cognition Disorders; Double-Blind Method; Female; Humans; Longitudinal Studies; Male; Mental Status Schedule; Mindfulness; Neuropsychological Tests; Treatment Outcome

miR-302 Attenuates Amyloid-β-Induced Neurotoxicity through Activation of Akt Signaling. - Li, Hsin-Hua; Lin, Shi-Lung; Huang, Chien-Ning; Lu, Fung-Jou; Chiu, Pai-Yi; Huang, Wen-Nung; Lai, Te-Jen; Lin, Chih-Li (J Alzheimers Dis, 2016)
Deficiency of insulin signaling has been linked to diabetes and ageing-related neurodegenerative diseases such as Alzheimer's disease (AD). In this regard, brains exhibit defective insulin receptor substrate-1 (IRS-1) and hence result in alteration of insulin signaling in progression of AD, the most common cause of dementia. Consequently, dysregulation of insulin signaling plays an important role in amyloid-β (Aβ)-induced neurotoxicity. As the derivation of induced pluripotent stem cells (iPSC) involves cell reprogramming, it may provide a means for regaining the control of ageing-associated dysfunction and neurodegeneration via affecting insulin-related signaling. To this, we found that an embryonic stem cell (ESC)-specific microRNA, miR-302, silences phosphatase and tensin homolog (PTEN) to activate Akt signaling, which subsequently stimulates nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) elevation and hence inhibits Aβ-induced neurotoxicity. miR-302 is predominantly expressed in iPSCs and is known to regulate several important biological processes of anti-oxidative stress, anti-apoptosis, and anti-aging through activating Akt signaling. In addition, we also found that miR-302-mediated Akt signaling further stimulates Nanog expression to suppress Aβ-induced p-Ser307 IRS-1 expression and thus enhances tyrosine phosphorylation and p-Ser 473-Akt/p-Ser 9-GSK3β formation. Furthermore, our in vivo studies revealed that the mRNA expression levels of both Nanog and miR-302-encoding LARP7 genes were significantly reduced in AD patients' blood cells, providing a novel diagnosis marker for AD. Taken together, our findings demonstrated that miR-302 is able to inhibit Aβ-induced cytotoxicity via activating Akt signaling to upregulate Nrf2 and Nanog expressions, leading to a marked restoration of insulin signaling in AD neurons.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Cell Line, Tumor; Cell Survival; Female; Glycogen Synthase Kinase 3 beta; Heme Oxygenase-1; Humans; Insulin; Male; Membrane Potential, Mitochondrial; MicroRNAs; Neurons; NF-E2-Related Factor 2; Oxidative Stress; Proto-Oncogene Proteins c-akt; PTEN Phosphohydrolase; Reactive Oxygen Species; Ribonucleoproteins

A Mitochondrial Role of SV2a Protein in Aging and Alzheimer's Disease: Studies with Levetiracetam. - Stockburger, Carola; Miano, Davide; Baeumlisberger, Marion; Pallas, Thea; Arrey, Tabiwang N; Karas, Michael; Friedland, Kristina; Müller, Walter E (J Alzheimers Dis, 2016)
Aberrant neuronal network activity associated with neuronal hyperexcitability seems to be an important cause of cognitive decline in aging and Alzheimer's disease (AD). Out of many antiepileptics, only levetiracetam improved cognitive dysfunction in AD patients and AD animal models by reducing hyperexcitability. As impaired inhibitory interneuronal function, rather than overactive neurons, seems to be the underlying cause, improving impaired neuronal function rather than quieting overactive neurons might be relevant in explaining the lack of activity of the other antiepileptics. Interestingly, improvement of cognitive deficits by levetiracetam caused by small levels of soluble Aβ was accompanied by improvement of synaptic function and plasticity. As the negative effects of Aβ on synaptic plasticity strongly correlate with mitochondrial dysfunction, wehypothesized that the effect of levetiracetam on synaptic activity might be raised by an improved mitochondrial function. Accordingly, we investigated possible effects of levetiracetam on neuronal deficits associated with mitochondrial dysfunction linked to aging and AD. Levetiracetam improved several aspects of mitochondrial dysfunction including alterations of fission and fusion balance in a cell model for aging and early late-onset AD. We demonstrate for the first time, using immunohistochemistry and proteomics, that the synaptic vesicle protein 2A (SV2a), the molecular target of levetiracetam, is expressed in mitochondria. In addition, levetiracetam shows significant effect on the opening of the mitochondrial permeability transition pore. Importantly, the effects of levetiracetam were significantly abolished when SV2a was knockdown using siRNA. In conclusion, interfering with the SV2a protein at the mitochondrial level and thereby improving mitochondrial function might represent an additional therapeutic effect of levetiracetam to improve symptoms of late-onset AD.
Keywords: Adenosine Triphosphate; Aging; Alzheimer Disease; Animals; Brain; Cell Line; Cognition Disorders; Female; GAP-43 Protein; Gene Expression Regulation; Humans; Male; Membrane Glycoproteins; Mitochondria; Mitochondrial Membrane Transport Proteins; Nerve Tissue Proteins; Nitroprusside; Nootropic Agents; Piracetam; Proteomics; Rats; RNA, Small Interfering

Moderate-to-High Intensity Physical Exercise in Patients with Alzheimer's Disease: A Randomized Controlled Trial. - Hoffmann, Kristine; Sobol, Nanna A; Frederiksen, Kristian S; Beyer, Nina; Vogel, Asmus; Vestergaard, Karsten; Brændgaard, Hans; Gottrup, Hanne; Lolk, Annette; Wermuth, Lene; Jacobsen, Søren; Laugesen, Lars P; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Studies of physical exercise in patients with Alzheimer's disease (AD) are few and results have been inconsistent. OBJECTIVE: To assess the effects of a moderate-to-high intensity aerobic exercise program in patients with mild AD. METHODS: In a randomized controlled trial, we recruited 200 patients with mild AD to a supervised exercise group (60-min sessions three times a week for 16 weeks) or to a control group. Primary outcome was changed from baseline in cognitive performance estimated by Symbol Digit Modalities Test (SDMT) in the intention-to-treat (ITT) group. Secondary outcomes included changes in quality of life, ability to perform activities of daily living, and in neuropsychiatric and depressive symptoms. RESULTS: The ITT analysis showed no significant differences between intervention and control groups in change from baseline of SDMT, other cognitive tests, quality of life, or activities of daily living. The change from baseline in Neuropsychiatric Inventory differed significantly in favor of the intervention group (mean: -3.5, 95% confidence interval (CI) -5.8 to -1.3, p = 0.002). In subjects who adhered to the protocol, we found a significant effect on change from baseline in SDMT as compared with the control group (mean: 4.2, 95% CI 0.5 to 7.9, p = 0.028), suggesting a dose-response relationship between exercise and cognition. CONCLUSIONS: This is the first randomized controlled trial with supervised moderate-to-high intensity exercise in patients with mild AD. Exercise reduced neuropsychiatric symptoms in patients with mild AD, with possible additional benefits of preserved cognition in a subgroup of patients exercising with high attendance and intensity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Depression; Exercise; Exercise Therapy; Female; Humans; Male; Middle Aged; Quality of Life; Treatment Outcome

Molecular markers of amnestic mild cognitive impairment among Mexican Americans. - Edwards, Melissa; Hall, James; Williams, Benjamin; Johnson, Leigh; O'Bryant, Sid (J Alzheimers Dis, 2016)
BACKGROUND: Mexican Americans face a significant health disparity when it comes to Alzheimer's disease (AD) as they present with higher rates of the disease and develop AD at an earlier age compared to other ethnic groups. Recent work identified a proteomic profile of AD among this population; however, no work to date has sought to examine the biological profile of pre-AD among Mexican Americans. OBJECTIVE: This study aims to identify an amnestic mild cognitive impairment (aMCI) proteomic profile among Mexican Americans. METHODS: Data were analyzed from 284 Mexican American participants (aMCI, n = 73; normal controls, n = 211) from the Health & Aging Brain among Latino Elders study. Fasting serum samples were analyzed using a multi-plex biomarker assay platform. A biomarker profile was generated using random forest analyses. RESULTS: Among aMCI cases, the biomarker profile was found to be largely inflammatory with the top three markers shown to include TNFα, IL10, and TARC. The overall diagnostic accuracy of the biomarkers in detecting aMCI was 96% (sensitivity = 0.82; specificity = 0.97). Inclusion of clinical variables with the selected biomarkers did not impact the overall detection accuracy (area under the curve = 0.96) but led to a slight improvement in specificity (specificity = 0.99) and decrease in sensitivity (sensitivity = 0.74). CONCLUSION: The biomarker profile of aMCI was shown to be different from our previously generated AD profile among Mexican Americans, which was largely metabolic in nature. The findings implicate a possible interplay between inflammatory and metabolic processes and additional work is needed to further examine this.
Keywords: Aged; Alzheimer Disease; Area Under Curve; Biomarkers; Cognitive Dysfunction; Female; Humans; Male; Mexican Americans; Middle Aged; Neuropsychological Tests; Proteome; Sensitivity and Specificity; United States

Multimodal Magnetic Resonance Imaging in Alzheimer's Disease Patients at Prodromal Stage. - Eustache, Pierre; Nemmi, Federico; Saint-Aubert, Laure; Pariente, Jérémie; Péran, Patrice (J Alzheimers Dis, 2016)
One objective of modern neuroimaging is to identify markers that can aid in diagnosis, monitor disease progression, and impact long-term drug analysis. In this study, physiopathological modifications in seven subcortical structures of patients with mild cognitive impairment (MCI) due to Alzheimer's disease (AD) were characterized by simultaneously measuring quantitative magnetic resonance parameters that are sensitive to complementary tissue characteristics (e.g., volume atrophy, shape changes, microstructural damage, and iron deposition). Fourteen MCI patients and fourteen matched, healthy subjects underwent 3T-magnetic resonance imaging with whole-brain, T1-weighted, T2*-weighted, and diffusion-tensor imaging scans. Volume, shape, mean R2*, mean diffusivity (MD), and mean fractional anisotropy (FA) in the thalamus, hippocampus, putamen, amygdala, caudate nucleus, pallidum, and accumbens were compared between MCI patients and healthy subjects. Comparisons were then performed using voxel-based analyses of R2*, MD, FA maps, and voxel-based morphometry to determine which subregions showed the greatest difference for each parameter. With respect to the micro- and macro-structural patterns of damage, our results suggest that different and distinct physiopathological processes are present in the prodromal phase of AD. MCI patients had significant atrophy and microstructural changes within their hippocampi and amygdalae, which are known to be affected in the prodromal stage of AD. This suggests that the amygdala is affected in the same, direct physiopathological process as the hippocampus. Conversely, atrophy alone was observed within the thalamus and putamen, which are not directly involved in AD pathogenesis. This latter result may reflect another mechanism, whereby atrophy is linked to indirect physiopathological processes.
Keywords: Aged; Alzheimer Disease; Biomarkers; Brain; Cognitive Dysfunction; Diffusion Tensor Imaging; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Mental Status Schedule; Multimodal Imaging; Neuropsychological Tests; Organ Size; Positron-Emission Tomography; Prodromal Symptoms; Radiopharmaceuticals

Naphthoquinone-Tryptophan Hybrid Inhibits Aggregation of the Tau-Derived Peptide PHF6 and Reduces Neurotoxicity. - Frenkel-Pinter, Moran; Tal, Sharon; Scherzer-Attali, Roni; Abu-Hussien, Malak; Alyagor, Idan; Eisenbaum, Tal; Gazit, Ehud; Segal, Daniel (J Alzheimers Dis, 2016)
Tauopathies, such as Alzheimer's disease (AD), are a group of disorders characterized neuropathologically by intracellular toxic accumulations of abnormal protein aggregates formed by misfolding of the microtubule-associated protein tau. Since protein self-assembly appears to be an initial key step in the pathology of this group of diseases, intervening in this process can be both a prophylactic measure and a means for modifying the course of the disease for therapeutic purposes. We and others have shown that aromatic small molecules can be effective inhibitors of aggregation of various protein assemblies, by binding to the aromatic core in aggregation-prone motifs and preventing their self-assembly. Specifically, we have designed a series of small aromatic naphthoquinone-tryptophan hybrid molecules as candidate aggregation inhibitors of β -sheet based assembly and demonstrated their efficacy toward inhibiting aggregation of the amyloid-β peptide, another culprit of AD, as well as of various other aggregative proteins involved in other protein misfolding diseases. Here we tested whether a leading naphthoquinone-tryptophan hybrid molecule, namely NQTrp, can be repurposed as an inhibitor of the aggregation of the tau protein in vitro and in vivo. We show that the molecule inhibits the in vitro assembly of PHF6, the aggregation-prone fragment of tau protein, reduces hyperphosphorylated tau deposits and ameliorates tauopathy-related behavioral defect in an established transgenic Drosophila model expressing human tau. We suggest that NQTrp, or optimized versions of it, could act as novel disease modifying drugs for AD and other tauopathies.
Keywords: Animals; Carrier Proteins; Disease Models, Animal; Drosophila; Drosophila Proteins; Eye; Female; Humans; Immunoprecipitation; In Vitro Techniques; Larva; Locomotion; Mice, Transgenic; Microscopy, Electron, Scanning; Naphthoquinones; Neurotoxicity Syndromes; Protein Aggregates; Retinal Pigments; tau Proteins; Tryptophan

Neurophysiological assessment of Alzheimer's disease individuals by a single electroencephalographic marker. - Lizio, Roberta; Del Percio, Claudio; Marzano, Nicola; Soricelli, Andrea; Yener, Görsev G; Başar, Erol; Mundi, Ciro; De Rosa, Salvatore; Triggiani, Antonio Ivano; Ferri, Raffaele; Arnaldi, Dario; Nobili, Flavio Mariano; et al. (J Alzheimers Dis, 2016)
Here we presented a single electroencephalographic (EEG) marker for a neurophysiological assessment of Alzheimer's disease (AD) patients already diagnosed by current guidelines. The ability of the EEG marker to classify 127 AD individuals and 121 matched cognitively intact normal elderly (Nold) individuals was tested. Furthermore, its relationship to AD patients' cognitive status and structural brain integrity was examined. Low-resolution brain electromagnetic tomography (LORETA) freeware estimated cortical sources of resting state eyes-closed EEG rhythms. The EEG marker was defined as the ratio between the activity of parieto-occipital cortical sources of delta (2-4 Hz) and low-frequency alpha (8-10.5 Hz) rhythms. Results showed 77.2% of sensitivity in the recognition of the AD individuals; 65% of specificity in the recognition of the Nold individuals; and 0.75 of area under the receiver-operating characteristic curve. Compared to the AD subgroup with the EEG maker within one standard deviation of the Nold mean (EEG-), the AD subgroup with EEG+ showed lower global cognitive status, as revealed by Mini-Mental State Evaluation score, and more abnormal values of white-matter and cerebrospinal fluid normalized volumes, as revealed by structural magnetic resonance imaging. We posit that cognitive and functional status being equal, AD patients with EEG+ should receive special clinical attention due to a neurophysiological "frailty". EEG+ label can be also used in clinical trials (i) to form homogeneous groups of AD patients diagnosed by current guidelines and (ii) as end-point to evaluate intervention effects.
Keywords: Aged; Alzheimer Disease; Biomarkers; Brain Mapping; Case-Control Studies; Cognition Disorders; Electroencephalography; Female; Humans; Italy; Magnetic Resonance Imaging; Male; Middle Aged; Occipital Lobe; Rest; ROC Curve; Turkey

Non-Verbal Episodic Memory Deficits in Primary Progressive Aphasias are Highly Predictive of Underlying Amyloid Pathology. - Ramanan, Siddharth; Flanagan, Emma; Leyton, Cristian E; Villemagne, Victor L; Rowe, Christopher C; Hodges, John R; Hornberger, Michael (J Alzheimers Dis, 2016)
Diagnostic distinction of primary progressive aphasias (PPA) remains challenging, in particular for the logopenic (lvPPA) and nonfluent/agrammatic (naPPA) variants. Recent findings highlight that episodic memory deficits appear to discriminate these PPA variants from each other, as only lvPPA perform poorly on these tasks while having underlying amyloid pathology similar to that seen in amnestic dementias like Alzheimer's disease (AD). Most memory tests are, however, language based and thus potentially confounded by the prevalent language deficits in PPA. The current study investigated this issue across PPA variants by contrasting verbal and non-verbal episodic memory measures while controlling for their performance on a language subtest of a general cognitive screen. A total of 203 participants were included (25 lvPPA; 29 naPPA; 59 AD; 90 controls) and underwent extensive verbal and non-verbal episodic memory testing, with a subset of patients (n = 45) with confirmed amyloid profiles as assessed by Pittsburgh Compound B and PET. The most powerful discriminator between naPPA and lvPPA patients was a non-verbal recall measure (Rey Complex Figure delayed recall), with 81% of PPA patients classified correctly at presentation. Importantly, AD and lvPPA patients performed comparably on this measure, further highlighting the importance of underlying amyloid pathology in episodic memory profiles. The findings demonstrate that non-verbal recall emerges as the best discriminator of lvPPA and naPPA when controlling for language deficits in high load amyloid PPA cases.
Keywords: Aged; Alzheimer Disease; Amyloid; Aniline Compounds; Aphasia, Primary Progressive; Brain; Diagnosis, Differential; Female; Humans; Logistic Models; Male; Memory, Episodic; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Speech Perception; Thiazoles

N-truncated Aβ2-X starting with position two in sporadic Alzheimer's disease cases and two Alzheimer mouse models. - Savastano, Adriana; Klafki, Hans; Haußmann, Ute; Oberstein, Timo Jan; Muller, Petr; Wirths, Oliver; Wiltfang, Jens; Bayer, Thomas A (J Alzheimers Dis, 2016)
According to the modified amyloid hypothesis, the key event in the pathogenesis of Alzheimer's disease (AD) is the deposition of neurotoxic amyloid β-peptides (Aβs) in plaques and cerebral blood vessels. Additionally to full-length peptides, a great diversity of N-truncated Aβ variants is derived from the larger amyloid-β protein precursor (AβPP). Vast evidence suggests that Aβx-42 isoforms play an important role in triggering neurodegeneration due to their high abundance, amyloidogenic propensity and toxicity. Although N-truncated Aβ peptides and Aβx-42 species appear to be the crucial players in AD etiology, the Aβ2-X isoforms did not receive much attention yet. The present study is the first to show immunohistochemical evidence of Aβ2-X in cases of AD and its distribution in AβPP/PS1KI and 5XFAD transgenic mouse models using a novel antibody pAB77 that has been developed using Aβ2-14 as antigen. Positive plaques and congophilic amyloid angiopathy (CAA) were observed in AD cases and in both mouse models. While in AD cases, abundant CAA and less pronounced plaque pathology was evident, the two mouse models showed predominantly extracellular Aβ deposits and minor CAA staining. Western blotting and a capillary isoelectric focusing immunoassay demonstrated the high specificity of the antibody pAb77 against Aβ-variants starting with the N-terminal Alanine-2.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Animals; Blotting, Western; Brain; Cerebral Amyloid Angiopathy; Disease Models, Animal; Female; Humans; Male; Mice; Mice, Transgenic; Plaque, Amyloid

Nutritional Status is Associated with Faster Cognitive Decline and Worse Functional Impairment in the Progression of Dementia: The Cache County Dementia Progression Study1. - Sanders, Chelsea; Behrens, Stephanie; Schwartz, Sarah; Wengreen, Heidi; Corcoran, Chris D; Lyketsos, Constantine G; Tschanz, JoAnn T (J Alzheimers Dis, 2016)
Nutritional status may be a modifiable factor in the progression of dementia. We examined the association of nutritional status and rate of cognitive and functional decline in a U.S. population-based sample. Study design was an observational longitudinal study with annual follow-ups up to 6 years of 292 persons with dementia (72% Alzheimer's disease, 56% female) in Cache County, UT using the Mini-Mental State Exam (MMSE), Clinical Dementia Rating Sum of Boxes (CDR-sb), and modified Mini Nutritional Assessment (mMNA). mMNA scores declined by approximately 0.50 points/year, suggesting increasing risk for malnutrition. Lower mMNA score predicted faster rate of decline on the MMSE at earlier follow-up times, but slower decline at later follow-up times, whereas higher mMNA scores had the opposite pattern (mMNA by time β= 0.22, p = 0.017; mMNA by time2 β= -0.04, p = 0.04). Lower mMNA score was associated with greater impairment on the CDR-sb over the course of dementia (β= 0.35, p <  0.001). Assessment of malnutrition may be useful in predicting rates of progression in dementia and may provide a target for clinical intervention.
Keywords: Age of Onset; Aged, 80 and over; Alzheimer Disease; Dementia, Vascular; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Mental Status Schedule; Nutritional Status; Severity of Illness Index; Sex Factors; Utah

Older Adults Taking AT1-Receptor Blockers Exhibit Reduced Cerebral Amyloid Retention. - Nation, Daniel A; Ho, Jean; Yew, Belinda (J Alzheimers Dis, 2016)
BACKGROUND: Evidence suggests that angiotensin II AT1-receptor blockers (ARBs) may be protective against dementia, and studies in transgenic animals indicate that this may be due to improved amyloid-β (Aβ) clearance. OBJECTIVE: We investigated whether taking ARBs was associated with an attenuation of age-related increases in cerebral Aβ retention, and reduced progression to dementia. METHODS: Eight hundred seventy-one stroke-free and dementia-free older adults from the Alzheimer's Disease Neuroimaging Initiative (ADNI) study underwent baseline lumbar puncture, and a subgroup (n = 124) underwent 12 and 24 month follow-up lumbar puncture. Participants were followed at variable intervals for clinical progression to dementia. Linear mixed models and ANCOVA compared ARBs users with those taking other antihypertensives (O-antiHTN) or no antihypertensives (No-antiHTN) on cerebrospinal fluid (CSF) Aβ and phosphorylated tau (P-tau) levels. Cox regression and chi-square analyses compared groups on progression to dementia. RESULTS: ARBs users exhibited greater vascular risk and lower educational attainment than the No-antiHTN group. Longitudinal analyses indicated higher CSF Aβ and lower P-tau in ARBs users versus other groups. Cross-sectional analyses revealed age-related decreases in CSF Aβ in other groups but not ARBs users. ARBs users were less likely to progress to dementia and showed reduced rate of progression relative to the No-antiHTN group. DISCUSSION: Patients taking ARBs showed an attenuation of age-related decreases in CSF Aβ, a finding that is consistent with studies done in transgenic animals. These findings may partly explain why ARBs users show reduced progression to dementia despite their lower educational attainment and greater vascular risk burden.
Keywords: Aged; Aged, 80 and over; Aging; Amyloid beta-Peptides; Angiotensin Receptor Antagonists; Antihypertensive Agents; Chi-Square Distribution; Cross-Sectional Studies; Dementia; Female; Humans; Longitudinal Studies; Male; Middle Aged; Peptide Fragments; Psychiatric Status Rating Scales; Regression Analysis; tau Proteins; Time Factors

Omega-3 Fatty Acid Status Enhances the Prevention of Cognitive Decline by B Vitamins in Mild Cognitive Impairment. - Oulhaj, Abderrahim; Jernerén, Fredrik; Refsum, Helga; Smith, A David; de Jager, Celeste A (J Alzheimers Dis, 2016)
A randomized trial (VITACOG) in people with mild cognitive impairment (MCI) found that B vitamin treatment to lower homocysteine slowed the rate of cognitive and clinical decline. We have used data from this trial to see whether baseline omega-3 fatty acid status interacts with the effects of B vitamin treatment. 266 participants with MCI aged ≥70 years were randomized to B vitamins (folic acid, vitamins B6 and B12) or placebo for 2 years. Baseline cognitive test performance, clinical dementia rating (CDR) scale, and plasma concentrations of total homocysteine, total docosahexaenoic and eicosapentaenoic acids (omega-3 fatty acids) were measured. Final scores for verbal delayed recall, global cognition, and CDR sum-of-boxes were better in the B vitamin-treated group according to increasing baseline concentrations of omega-3 fatty acids, whereas scores in the placebo group were similar across these concentrations. Among those with good omega-3 status, 33% of those on B vitamin treatment had global CDR scores >0 compared with 59% among those on placebo. For all three outcome measures, higher concentrations of docosahexaenoic acid alone significantly enhanced the cognitive effects of B vitamins, while eicosapentaenoic acid appeared less effective. When omega-3 fatty acid concentrations are low, B vitamin treatment has no effect on cognitive decline in MCI, but when omega-3 levels are in the upper normal range, B vitamins interact to slow cognitive decline. A clinical trial of B vitamins combined with omega-3 fatty acids is needed to see whether it is possible to slow the conversion from MCI to AD.
Keywords: Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Disease Progression; Fatty Acids, Omega-3; Female; Humans; Male; Neuropsychological Tests; Treatment Outcome; Vitamin B Complex

Optimization of Statistical Single Subject Analysis of Brain FDG PET for the Prognosis of Mild Cognitive Impairment-to-Alzheimer's Disease Conversion. - Lange, Catharina; Suppa, Per; Frings, Lars; Brenner, Winfried; Spies, Lothar; Buchert, Ralph (J Alzheimers Dis, 2016)
BACKGROUND: Positron emission tomography (PET) with the glucose analog F-18-fluorodeoxyglucose (FDG) is widely used in the diagnosis of neurodegenerative diseases. Guidelines recommend voxel-based statistical testing to support visual evaluation of the PET images. However, the performance of voxel-based testing strongly depends on each single preprocessing step involved. OBJECTIVE: To optimize the processing pipeline of voxel-based testing for the prognosis of dementia in subjects with amnestic mild cognitive impairment (MCI). METHODS: The study included 108 ADNI MCI subjects grouped as 'stable MCI' (n = 77) or 'MCI-to-AD converter' according to their diagnostic trajectory over 3 years. Thirty-two ADNI normals served as controls. Voxel-based testing was performed with the statistical parametric mapping software (SPM8) starting with default settings. The following modifications were added step-by-step: (i) motion correction, (ii) custom-made FDG template, (iii) different reference regions for intensity scaling, and (iv) smoothing was varied between 8 and 18 mm. The t-sum score for hypometabolism within a predefined AD mask was compared between the different settings using receiver operating characteristic (ROC) analysis with respect to differentiation between 'stable MCI' and 'MCI-to-AD converter'. The area (AUC) under the ROC curve was used as performance measure. RESULTS: The default setting provided an AUC of 0.728. The modifications of the processing pipeline improved the AUC up to 0.832 (p = 0.046). Improvement of the AUC was confirmed in an independent validation sample of 241 ADNI MCI subjects (p = 0.048). CONCLUSION: The prognostic value of voxel-based single subject analysis of brain FDG PET in MCI subjects can be improved considerably by optimizing the processing pipeline.
Keywords: Aged; Alzheimer Disease; Area Under Curve; Brain; Cognitive Dysfunction; Disease Progression; Female; Fluorodeoxyglucose F18; Follow-Up Studies; Glucose; Humans; Image Interpretation, Computer-Assisted; Male; Positron-Emission Tomography; Prognosis; Radiopharmaceuticals; ROC Curve

Overexpression of Metallothionein-1 Modulates the Phenotype of the Tg2576 Mouse Model of Alzheimer's Disease. - Manso, Yasmina; Comes, Gemma; López-Ramos, Juan C; Belfiore, Mónica; Molinero, Amalia; Giralt, Mercedes; Carrasco, Javier; Adlard, Paul A; Bush, Ashley I; Delgado-García, José María; Hidalgo, Juan (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is the most commonly diagnosed dementia, where signs of neuroinflammation and oxidative stress are prominent. In this study we intend to further characterize the roles of the antioxidant, anti-inflammatory, and heavy metal binding protein, metallothionein-1 (MT-1), by crossing Mt1 overexpressing mice with a well-known mouse model of AD, Tg2576 mice, which express the human amyloid-β protein precursor (hAβPP) with the Swedish K670N/M671L mutations. Mt1 overexpression increased overall perinatal survival, but did not affect significantly hAβPP-induced mortality and weight loss in adult mice. Amyloid plaque burden in ∼14-month-old mice was increased by Mt1 overexpression in the hippocampus but not the cortex. Despite full length hAβPP levels and amyloid plaques being increased by Mt1 overexpression in the hippocampus of both sexes, oligomeric and monomeric forms of Aβ, which may contribute more to toxicity, were decreased in the hippocampus of females and increased in males. Several behavioral traits such as exploration, anxiety, and learning were altered in Tg2576 mice to various degrees depending on the age and the sex. Mt1 overexpression ameliorated the effects of hAβPP on exploration in young females, and potentiated those on anxiety in old males, and seemed to improve the rate of spatial learning (Morris water maze) and the learning elicited by a classical conditioning procedure (eye-blink test). These results clearly suggest that MT-1 may be involved in AD pathogenesis.
Keywords: Age Factors; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Anxiety; Disease Models, Animal; Exploratory Behavior; Female; Gene Expression Regulation; Humans; Male; Matrix Metalloproteinase 16; Maze Learning; Metallothionein; Mice; Mice, Inbred C57BL; Mice, Transgenic; Motor Activity; Mutation; Phenotype; Psychomotor Disorders

Pain Assessment in Elderly with Behavioral and Psychological Symptoms of Dementia. - Malara, Alba; De Biase, Giuseppe Andrea; Bettarini, Francesco; Ceravolo, Francesco; Di Cello, Serena; Garo, Michele; Praino, Francesco; Settembrini, Vincenzo; Sgrò, Giovanni; Spadea, Fausto; Rispoli, Vincenzo (J Alzheimers Dis, 2016)
BACKGROUND: Pain is under-detected and undertreated in people with dementia. The present study investigates the prevalence of pain in people with dementia hospitalized in nursing homes that are members of National Association of Third Age Residences (ANASTE) Calabria, and evaluates the association among pain, mood, and behavioral and psychological symptoms of dementia (BPSD). OBJECTIVE: The aim of this study is to define the prevalence of pain in people with dementia in long term care facilities using scales of self-reporting and observational tools and, particularly, to study the relationship between pain and BPSD. METHODS: A prospective observational study was carried out on 233 patients. Pain assessment was performed using self-reporting tools such as the Numeric Rating Scale (NRS) for patients with slight cognitive impairment or no cognitive impairment and observational tools such as Pain Assessment In Advanced Dementia Scale (PAINAD) for patients with moderate or severe cognitive impairment. Mood was evaluated through the Cornell Scale for Depression in Dementia (CSDD) while behavioral problems were assessed through the Cohen-Mansfield Agitation Inventory (CMAI) and Neuropsychiatric Inventory (NPI). RESULTS: Only 42.5% of patients evaluated by NRS provided a reliable answer; of these, 20.4% reported no pain. The percentage of pain evaluated by PAINAD was 51.8% . Analysis of data showed a statistically significant correlation between diagnosis of pain and depressive symptoms, assessed with CSDD (p = 0.0113), as well as by single items of NPI, such as anxiety (p = 0.0362) and irritability (p = 0.0034), and F1 profile (Aggression) of CMAI (p = 0.01). CONCLUSION: This study confirms that self-report alone is not sufficient to assess pain in elderly people with dementia; the observational tool is a necessary and suitable way of assessing pain in patients with cognitive impairment. If not adequately treated, chronic pain can cause depression, agitation, and aggression in patients with dementia.
Keywords: Affect; Aged, 80 and over; Analgesics; Anxiety; Dementia; Depression; Female; Humans; Italy; Logistic Models; Long-Term Care; Male; Multivariate Analysis; Nursing Homes; Pain; Pain Measurement; Prevalence; Prospective Studies; Psychiatric Status Rating Scales; Self Report; Severity of Illness Index

Palmomental Reflex a Relevant Sign in Early Alzheimer's Disease Diagnosis? - Gabelle, Audrey; Gutierrez, Laure-Anne; Dartigues, Jean-François; Ritchie, Karen; Touchon, Jacques; Berr, Claudine (J Alzheimers Dis, 2016)
BACKGROUND: Sophisticated and expensive biomarkers are proposed for the diagnostic of Alzheimer's disease (AD). The amyloid process seems to be early in AD, and brain amyloid load affects the frontal lobe. OBJECTIVE: To determine if certain simple clinical signs, especially frontal-related signs, could help reach an earlier and better diagnosis. METHODS: In the frame of the 3-City cohort, we conducted a nested case-control study comparing incident cases of AD to controls matched for age, gender, and education. The standardized neurological exam included extrapyramidal signs (akinesia, rigidity, rest tremor), pyramidal symptoms (spastic rigidity, Babinski reflex), primitive reflexes (snout, palmomental reflex grasping), and tremor (essential, intentional, head) at the time of diagnosis and two years before. RESULTS: We compared 106 incident AD subjects (mean age at diagnosis 82.2 (SD = 5.9); median MMSE at diagnosis = 23) to 208 matched controls. In patients younger than 80, palmomental reflexes were more frequent in AD than controls, two years before diagnosis (25.0 versus 7.0% , p = 0.03) and at time of diagnosis (30.3 versus 12.3% , p = 0.02). No difference was observed for other signs two years before diagnosis or for patients older than 80. CONCLUSION: Before diagnosis, the clinical examination of AD patients is not strictly normal; the primitive reflexes appear to be pathological. It might be in connection with the frontal amyloid load at an early stage of the disease. Clinical examination can reveal simple and interesting signs that deserve consideration as well as the other more invasive and expensive biomarkers.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Early Diagnosis; Female; Follow-Up Studies; France; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Reflex

A Pathway Based Classification Method for Analyzing Gene Expression for Alzheimer's Disease Diagnosis. - Voyle, Nicola; Keohane, Aoife; Newhouse, Stephen; Lunnon, Katie; Johnston, Caroline; Soininen, Hilkka; Kloszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Hodges, Angela; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies indicate that gene expression levels in blood may be able to differentiate subjects with Alzheimer's disease (AD) from normal elderly controls and mild cognitively impaired (MCI) subjects. However, there is limited replicability at the single marker level. A pathway-based interpretation of gene expression may prove more robust. OBJECTIVES: This study aimed to investigate whether a case/control classification model built on pathway level data was more robust than a gene level model and may consequently perform better in test data. The study used two batches of gene expression data from the AddNeuroMed (ANM) and Dementia Case Registry (DCR) cohorts. METHODS: Our study used Illumina Human HT-12 Expression BeadChips to collect gene expression from blood samples. Random forest modeling with recursive feature elimination was used to predict case/control status. Age and APOE ɛ4 status were used as covariates for all analysis. RESULTS: Gene and pathway level models performed similarly to each other and to a model based on demographic information only. CONCLUSIONS: Any potential increase in concordance from the novel pathway level approach used here has not lead to a greater predictive ability in these datasets. However, we have only tested one method for creating pathway level scores. Further, we have been able to benchmark pathways against genes in datasets that had been extensively harmonized. Further work should focus on the use of alternative methods for creating pathway level scores, in particular those that incorporate pathway topology, and the use of an endophenotype based approach.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Cohort Studies; Datasets as Topic; Female; Gene Expression; Gene Expression Profiling; Humans; Male; Models, Genetic; Oligonucleotide Array Sequence Analysis; Signal Transduction

Patients with Mild Alzheimer's Disease Fail When Using Their Working Memory: Evidence from the Eye Tracking Technique. - Fernández, Gerardo; Manes, Facundo; Politi, Luis E; Orozco, David; Schumacher, Marcela; Castro, Liliana; Agamennoni, Osvaldo; Rotstein, Nora P (J Alzheimers Dis, 2016)
Patients with Alzheimer's disease (AD) develop progressive language, visuoperceptual, attentional, and oculomotor changes that can have an impact on their reading comprehension. However, few studies have examined reading behavior in AD, and none have examined the contribution of predictive cueing in reading performance. For this purpose we analyzed the eye movement behavior of 35 healthy readers (Controls) and 35 patients with probable AD during reading of regular and high-predictable sentences. The cloze predictability of words N - 1, and N + 1 exerted an influence on the reader's gaze duration. The predictabilities of preceding words in high-predictable sentences served as task-appropriate cues that were used by Control readers. In contrast, these effects were not present in AD patients. In Controls, changes in predictability significantly affected fixation duration along the sentence; noteworthy, these changes did not affect fixation durations in AD patients. Hence, only in healthy readers did predictability of upcoming words influence fixation durations via memory retrieval. Our results suggest that Controls used stored information of familiar texts for enhancing their reading performance and imply that contextual-word predictability, whose processing is proposed to require memory retrieval, only affected reading behavior in healthy subjects. In AD patients, this loss reveals impairments in brain areas such as those corresponding to working memory and memory retrieval. These findings might be relevant for expanding the options for the early detection and monitoring in the early stages of AD. Furthermore, evaluation of eye movements during reading could provide a new tool for measuring drug impact on patients' behavior.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Eye Movements; Female; Humans; Linear Models; Magnetic Resonance Imaging; Male; Memory Disorders; Memory, Short-Term; Mental Recall; Mental Status Schedule; Predictive Value of Tests; Semantics; Verbal Learning

Patterns of Brain Iron Accumulation in Vascular Dementia and Alzheimer's Dementia Using Quantitative Susceptibility Mapping Imaging. - Moon, Yeonsil; Han, Seol-Heui; Moon, Won-Jin (J Alzheimers Dis, 2016)
BACKGROUND: Emerging evidence suggests that the excessive accumulation of iron in subcortical and deep gray matter has been related to dementia. However, the presence and pattern of iron accumulation in vascular dementia (VaD) and Alzheimer's disease (AD) are rarely investigated. OBJECTIVE: To examine and compare the pattern and presence of brain iron accumulation of VaD and AD using quantitative susceptibility mapping (QSM). MATERIALS AND METHODS: Twelve patients with VaD, 27 patients with AD, and 18 control subjects were recruited in this institutional review-board approved study. Susceptibility maps were reconstructed from a three-dimensional multiecho spoiled gradient-echo sequence. Four regions of interest were drawn manually on QSM images, namely the globus pallidus, putamen, caudate nucleus, and pulvinar nucleus of the thalamus. Comparisons of patient demographics, and iron concentrations among the VaD, AD, and control subjects were assessed using analysis of variance and post-hoc analyses. The relationships of age and cognitive state with susceptibility values were assessed using partial correlation analysis. RESULTS: In VaD and AD, overall susceptibility values were higher than those of control subjects. A significant difference in susceptibility values was found in the putamen and caudate nucleus (p <  0.001 and p = 0.002, respectively). However, susceptibility values did not differ between VaD and AD. Age and cognitive deficit severity were not related to susceptibility values in the VaD and AD groups. CONCLUSION: Increased iron deposition in the putamen and caudate nucleus in VaD and AD patients was not associated with age or the severity of cognitive deficits. Further evaluations are needed to determine the temporal changes in iron load and their diagnostic role in dementia pathology.
Keywords: Aged; Aging; Alzheimer Disease; Brain; Brain Mapping; Cognition; Dementia, Vascular; Female; Humans; Imaging, Three-Dimensional; Iron; Magnetic Resonance Imaging; Male; Mental Status Schedule; Retrospective Studies; Severity of Illness Index

Pauses During Autobiographical Discourse Reflect Episodic Memory Processes in Early Alzheimer's Disease. - Pistono, Aurélie; Jucla, Mélanie; Barbeau, Emmanuel J; Saint-Aubert, Laure; Lemesle, Béatrice; Calvet, Benjamin; Köpke, Barbara; Puel, Michèle; Pariente, Jérémie (J Alzheimers Dis, 2016)
There is a large body of research on discourse production in Alzheimer's disease (AD). Some studies have focused on pause production, revealing that patients make extensive use of pauses during speech. This has been attributed to lexical retrieval difficulties, but pausing may also reflect other forms of cognitive impairment as it increases with cognitive load. The aim of the present study was to analyze autobiographical discourse impairment in AD from a broad perspective, looking at pausing behavior (frequency, duration, and location). Our first objective was to characterize discourse changes in mild cognitive impairment (MCI) due to AD. Our second objective was to determine the cognitive and neuroanatomical correlates of these changes. Fifteen patients with MCI due to AD and 15 matched cognitively normal controls underwent an ecological episodic memory task, a full neuropsychological assessment, and a 3D T1-weighted MRI scans. Autobiographical discourse collected from the ecological episodic memory task was recorded, transcribed, and analyzed, focusing on pausing. Intergroup comparisons showed that although patients did not produce more pauses than controls overall, they did make more between-utterance pauses. The number of these specific pauses was positively correlated with patients' episodic memory performance. Furthermore, neuroimaging analysis showed that, in the patient group, their use was negatively correlated with frontopolar area (BA 10) grey matter density. This region may therefore play an important role in the planning of autobiographical discourse production. These findings demonstrate that pauses in early AD may reflect a compensatory mechanism for improving mental time travel and memory retrieval.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Brain; Female; Humans; Male; Memory Disorders; Memory, Episodic; Mental Status Schedule; Neuropsychological Tests; Positron-Emission Tomography; Statistics as Topic

Performance on Specific Cognitive Domains and Cause of Death: A Prospective Population-Based Study in Non-Demented Older Adults (NEDICES). - Benito-León, Julián; Contador, Israel; Mitchell, Alex J; Domingo-Santos, Ángela; Bermejo-Pareja, Félix (J Alzheimers Dis, 2016)
Evidence regarding the relationship between performance on specific cognitive domains and cause of death is scarce. We assessed whether specific cognitive domains predicted mortality and the presence of any association with specific causes of death in a population-dwelling sample of non-demented older adults. In this population-based, prospective study (NEDICES), 2,390 non-demented subjects ≥65 years completed a brief neuropsychological battery. Cox's proportional hazards models, adjusted by sociodemographic and comorbidity factors, global cognitive performance, educational level, and premorbid intelligence were used to assess the risk of death. Participants were followed for a median of 9.2 years (range 0.01-10.7), after which the death certificates of those who died were examined. 880 (36.8%) of 2,390 participants died over a median follow-up of 5.5 years (range 0.01-10.5). Using adjusted Cox regression models, we found that hazard ratios for mortality in participants within the lowest tertiles (worse performance) were 1.31 (speed of cognitive processing, p = 0.03); 1.22 (semantic fluency, p = 0.04), 1.32 (delayed free recall, p = 0.003), and 1.23 (delayed logical memory, p = 0.03). Poor performance on delayed recall and speed of cognitive processing tests were associated with dementia and cerebrovascular disease mortality, respectively. Further, poor performance on semantic fluency was associated with decreased cancer mortality. In this study of community dwelling non-demented older adults, worse neuropsychological performance was associated with increased risk of mortality. Performance on specific cognitive domains were related to different causes of death. Of particular note there appears to be an inverse association between poor semantic fluency and cancer mortality.
Keywords: Aged; Cause of Death; Cerebrovascular Disorders; Cognitive Aging; Dementia; Educational Status; Female; Follow-Up Studies; Humans; Intelligence; Longitudinal Studies; Male; Neuropsychological Tests; Prospective Studies; Risk; Spain

Plasma Phospholipid and Sphingolipid Alterations in Presenilin1 Mutation Carriers: A Pilot Study. - Chatterjee, Pratishtha; Lim, Wei L F; Shui, Guanghou; Gupta, Veer B; James, Ian; Fagan, Anne M; Xiong, Chengjie; Sohrabi, Hamid R; Taddei, Kevin; Brown, Belinda M; Benzinger, Tammie; Masters, Colin; et al. (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: Aberrant lipid metabolism has been implicated in sporadic Alzheimer's disease (AD). The current study investigated plasma phospholipid and sphingolipid profiles in individuals carrying PSEN1 mutations responsible for autosomal dominant AD (ADAD). METHODS: Study participants evaluated were from the Perth and Melbourne sites of the Dominantly Inherited Alzheimer Network (DIAN) study. Plasma phospholipid and sphingolipid profiles were measured using liquid chromatography coupled with mass spectrometry in 20 PSEN1 mutation carriers (MC; eight of whom were symptomatic and twelve asymptomatic, based on Clinical Dementia Rating scores) and compared with six non carriers (NC) using linear mixed models. Further, AD gold standard biomarker data obtained from the DIAN database were correlated with lipid species significantly altered between MC and NC, using Spearman's correlation coefficient. RESULTS: One-hundred and thirty-nine plasma phospholipid and sphingolipid species were measured. Significantly altered species in MC compared to NC primarily belonged to choline and ethanolamine containing phospholipid classes and ceramides. Further phosphatidylcholine species (34:6, 36:5, 40:6) correlated with cerebrospinal fluid tau (p <  0.05), and plasmalogen ethanolamine species (34:2, 36:,4) correlated with both cerebrospinal fluid tau and brain amyloid load within the MC group (p <  0.05). CONCLUSION: These findings indicate altered phospholipid and sphingolipid metabolism in ADAD and provide insight into the pathomolecular changes occurring with ADAD pathogenesis. Further, findings reported in this study allow comparison of lipid alterations in ADAD with those reported previously in sporadic AD. The findings observed in the current pilot study warrant validation in the larger DIAN cohort.
Keywords: Adult; Alzheimer Disease; Apolipoproteins E; Female; Humans; Linear Models; Male; Middle Aged; Mutation; Phospholipids; Pilot Projects; Presenilin-1; Sphingolipids

Platelet Membrane β-Secretase Activity in Mild Cognitive Impairment and Conversion to Dementia: a Longitudinal Study. - McGuinness, Bernadette; Fuchs, Marc; Barrett, Suzanne L; Passmore, A Peter; Johnston, Janet A (J Alzheimers Dis, 2016)
A blood-based biomarker to complement the clinical and neuropsychological assessments used to evaluate the risk of individuals with mild cognitive impairment (MCI) developing Alzheimer's disease (AD) would be invaluable. Previous pilot studies by our group identified elevated platelet membrane β-secretase activity in patients with AD and MCI, as compared to controls, and this activity was influenced by membrane cholesterol levels. The present study investigated baseline platelet membrane β-secretase activity and cholesterol levels in 97 MCI participants and 85 controls and explored whether these parameters differed in individuals with stable MCI, as compared to those who subsequently developed AD. To evaluate signal specificity, β-secretase activity assays were conducted in the presence and absence of beta-site amyloid-β protein precursor-cleaving enzyme (BACE) inhibitors. Baseline platelet membrane β-secretase activity did not differ significantly in MCI participants, as compared to controls, and platelet membrane cholesterol levels were significantly lower in the MCI group. The longitudinal study indicated that the activities inhibited by two different BACE inhibitors did not predict conversion to AD; however, the activity that was not affected by BACE inhibitors was significantly (40%) higher in individuals with stable MCI, as compared with those who subsequently developed AD. These findings indicated that further research into the source of this activity could contribute to a measure facilitating prediction of the risk of conversion from MCI to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid Precursor Protein Secretases; Biomarkers; Blood Platelets; Cholesterol; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Middle Aged; Neuropsychological Tests; Sensitivity and Specificity

Prediction of Progressive Mild Cognitive Impairment by Multi-Modal Neuroimaging Biomarkers. - Xu, Lele; Wu, Xia; Li, Rui; Chen, Kewei; Long, Zhiying; Zhang, Jiacai; Guo, Xiaojuan; Yao, Li (J Alzheimers Dis, 2016)
For patients with mild cognitive impairment (MCI), the likelihood of progression to probable Alzheimer's disease (AD) is important not only for individual patient care, but also for the identification of participants in clinical trial, so as to provide early interventions. Biomarkers based on various neuroimaging modalities could offer complementary information regarding different aspects of disease progression. The current study adopted a weighted multi-modality sparse representation-based classification method to combine data from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database, from three imaging modalities: Volumetric magnetic resonance imaging (MRI), fluorodeoxyglucose (FDG) positron emission tomography (PET), and florbetapir PET. We included 117 normal controls (NC) and 110 MCI patients, 27 of whom progressed to AD within 36 months (pMCI), while the remaining 83 remained stable (sMCI) over the same time period. Modality-specific biomarkers were identified to distinguish MCI from NC and to predict pMCI among MCI. These included the hippocampus, amygdala, middle temporal and inferior temporal regions for MRI, the posterior cingulum, precentral, and postcentral regions for FDG-PET, and the hippocampus, amygdala, and putamen for florbetapir PET. Results indicated that FDG-PET may be a more effective modality in discriminating MCI from NC and in predicting pMCI than florbetapir PET and MRI. Combining modality-specific sensitive biomarkers from the three modalities boosted the discrimination accuracy of MCI from NC (76.7%) and the prediction accuracy of pMCI (82.5%) when compared with the best single-modality results (73.6% for MCI and 75.6% for pMCI with FDG-PET).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Biomarkers; Brain; Cognitive Dysfunction; Disease Progression; Ethylene Glycols; Female; Fluorodeoxyglucose F18; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Positron-Emission Tomography; Predictive Value of Tests; Psychiatric Status Rating Scales; Sensitivity and Specificity

Predictive factors for disease progression in patients with early-onset Alzheimer's disease. - Yoon, Bora; Shim, Yong S; Park, Hee-Kyung; Park, Sun Ah; Choi, Seong Hye; Yang, Dong Won (J Alzheimers Dis, 2016)
BACKGROUND: Only a few studies have investigated disease progression in patients with early-onset Alzheimer's disease (EOAD). Therefore, the aim of this study was to investigate disease progression in patients with EOAD and the influence of various factors, such as gender, education, and apolipoprotein E (APOE) genotype on disease progression. METHODS: A total of 288 EOAD patients were enrolled in the study. Linear mixed models were used to investigate the rate of cognitive and functional decline in terms of age at onset, gender, education, follow-up period, and APOE genotype. RESULTS: EOAD patients showed an annual decline of -1.54 points/years in the Korean version mini-mental examination score, an annual increase of 3.46 points/year in the Seoul instrumental activities of daily living (SIADL) score, and an annual increase of 1.15 points/year in the clinical dementia rating scale-sum of boxes score. After stratification, higher educated patients showed faster disease progression in all three parameters, and female patients demonstrated faster disease progression as assessed by the SIADL score. Age at onset and APOE genotype had no influence on disease progression. CONCLUSION: We confirmed the rate of disease progression in Korean patients with EOAD in real-life hospital-based clinical practice. The results of this study suggest that education and female gender, not APOE genotype, may be important as independent strong predictive factors for disease progression in patients with EOAD.
Keywords: Activities of Daily Living; Adult; Age Factors; Aged; Alleles; Alzheimer Disease; Apolipoproteins E; Disease Progression; Female; Genotype; Humans; Linear Models; Longitudinal Studies; Male; Middle Aged; Neuropsychological Tests; Risk Factors; Sex Factors

Predictive Value of Cerebrospinal Fluid Visinin-Like Protein-1 Levels for Alzheimer's Disease Early Detection and Differential Diagnosis in Patients with Mild Cognitive Impairment. - Babić Leko, Mirjana; Borovečki, Fran; Dejanović, Nenad; Hof, Patrick R; Šimić, Goran (J Alzheimers Dis, 2016)
Visinin-like protein 1 (VILIP-1) recently emerged as a potential biomarker of Alzheimer's disease (AD). This neuronal calcium sensor protein previously used as a marker of acute ischemic stroke is elevated in the cerebrospinal fluid (CSF) of AD patients. The goal of this study was to assess CSF VILIP-1 potential in early AD diagnosis and in differentiating mild cognitive impairment (MCI) patients with and without risk of AD. Additionally, we tested VILIP-1 ability to differentiate AD from other primary causes of dementia, and predict the progression of AD-related cognitive decline. VILIP-1 levels were compared with five CSF AD biomarkers (t-tau, Aβ1-42, p-tau181, p-tau199, and p-tau231). VILIP-1 successfully differentiated two MCI patient groups characterized by absence or presence of pathological levels of these CSF biomarkers, except for t-tau. VILIP-1/Aβ(1-42) and VILIP-1/p-tau181 ratios also differentiated MCI patients with pathological CSF biomarker levels. However, there was no difference in VILIP-1 levels between AD and MCI patients. VILIP-1/Aβ(1-42) and VILIP-1/p-tau231 ratios reached high sensitivities (above 70%) and very high specificities (above 85%) in differentiating AD patients from HC. Additionally, VILIP-1 differentiated AD from patients with Lewy body disease with 77.1% sensitivity and 100% specificity. VILIP-1 potential as a prognostic biomarker of cognitive decline in AD was also proved since VILIP-1/t-tau, VILIP-1/p-tau181, and VILIP-1/p-tau231 ratios correlated with MMSE scores. These data indicate that VILIP-1 alone or in combination with other AD CSF biomarkers represent a valuable marker for the early diagnosis of AD, recognition of MCI patients at higher risk to develop dementia, and in differentiating AD from LBD.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Diagnosis, Differential; Disease Progression; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neurocalcin; Peptide Fragments; Predictive Value of Tests; ROC Curve; Statistics as Topic; tau Proteins

Predictors of Response to Cholinesterase Inhibitors Treatment of Alzheimer's Disease: Date Mining from the TREDEM Registry. - Gallucci, Maurizio; Spagnolo, Pierpaolo; Aricò, Maria; Grossi, Enzo (J Alzheimers Dis, 2016)
BACKGROUND: The pharmacological treatment of Alzheimer's disease (AD) is based largely on cholinesterase inhibitors (ChEI). OBJECTIVE: To investigate whether or not some non-pharmacological and contextual factors measured prior to starting treatment such as past occupation, lifestyles, marital status, degree of autonomy and cognitive impairment, living alone or with others, and the degree of brain atrophy are associated with a better response to ChEI treatment. METHODS: Eighty-four AD and six AD with cerebrovascular disease (AD + CVD) outpatients of Treviso Dementia (TREDEM) Registry, with an average cholinesterase inhibitors treatment length of four years, were considered. The outpatients had undergone a complete evaluation and some non-pharmacological and contextual factors were collected. We defined responder a patient with a delta score T0 - T1 equal or inferior to 2.0 points per year of MMSE and a non-responder a patient with a delta score T0 - T1 superior to 2.0 points per year. In order to identify hidden relationships between variables related to response and non-response, we use a special kind of artificial neural network called Auto-CM, able to create a semantic connectivity map of the variables considered in the study. RESULTS: A higher cognitive profile, a previous intellectual occupation, healthier lifestyles, being married and not living alone, a higher degree of autonomy, and lower degree of brain atrophy at baseline resulted in affecting the response to long-term ChEI therapy. CONCLUSION: Non-pharmacological and contextual factors appear to influence the effectiveness of treatment with ChEI in the long term.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cerebrovascular Disorders; Cholinesterase Inhibitors; Female; Humans; Life Style; Male; Marital Status; Mental Status Schedule; Neural Networks (Computer); Neuropsychological Tests; Occupations; Outpatients; Prognosis; Registries; Treatment Outcome

The Presence of Select Tau Species in Human Peripheral Tissues and Their Relation to Alzheimer's Disease. - Dugger, Brittany N; Whiteside, Charisse M; Maarouf, Chera L; Walker, Douglas G; Beach, Thomas G; Sue, Lucia I; Garcia, Angelica; Dunckley, Travis; Meechoovet, Bessie; Reiman, Eric M; Roher, Alex E (J Alzheimers Dis, 2016)
Tau becomes excessively phosphorylated in Alzheimer's disease (AD) and is widely studied within the brain. Further examination of the extent and types of tau present in peripheral tissues and their relation to AD is warranted given recent publications on pathologic spreading. Cases were selected based on the presence of pathological tau spinal cord deposits (n = 18). Tissue samples from sigmoid colon, scalp, abdominal skin, liver, and submandibular gland were analyzed by western blot and enzyme-linked immunosorbent assays (ELISAs) for certain tau species; frontal cortex gray matter was used for comparison. ELISAs revealed brain to have the highest total tau levels, followed by submandibular gland, sigmoid colon, liver, scalp, and abdominal skin. Western blots with antibodies recognizing tau phosphorylated at threonine 231(pT231), serine 396 and 404 (PHF-1), and an unmodified total human tau between residues 159 and 163 (HT7) revealed multiple banding patterns, some of which predominated in peripheral tissues. As submandibular gland had the highest levels of peripheral tau, a second set of submandibular gland samples were analyzed (n = 36; 19 AD, 17 non-demented controls). ELISAs revealed significantly lower levels of pS396 (p = 0.009) and pT231 (p = 0.005) in AD cases but not total tau (p = 0.18). Furthermore, pT231 levels in submandibular gland inversely correlated with Braak neurofibrillary tangle stage (p = 0.04), after adjusting for age at death, gender, and postmortem interval. These results provide evidence that certain tau species are present in peripheral tissues. Of potential importance, submandibular gland pT231 is progressively less abundant with increasing Braak neurofibrillary tangle stage.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Blotting, Western; Colon; Enzyme-Linked Immunosorbent Assay; Female; Frontal Lobe; Gray Matter; Humans; Immunohistochemistry; Liver; Male; Neurofibrillary Tangles; Phosphorylation; Severity of Illness Index; Sex Characteristics; Skin; Submandibular Gland; tau Proteins

Prevalence and Risk Factor of Cognitive Impairment were Different between Urban and Rural Population: A Community-Based Study. - Tang, Hui-Dong; Zhou, Yi; Gao, Xiang; Liang, Liang; Hou, Miao-Miao; Qiao, Yuan; Ma, Jian-Fang; Chen, Sheng-Di (J Alzheimers Dis, 2016)
BACKGROUND: China is facing a continuously rising numbers of people with cognitive impairment (CI). OBJECTIVES: To investigate the prevalence and risk factors of CI among elderly people living in rural and urban communities. METHODS: We conducted a face-to-face survey of CI on 7,900 individuals aged 50 years or older meeting inclusion criteria in the Malu (rural community, n = 4,429) and Wuliqiao (urban community, n = 3,471) communities of Shanghai. The Mini-Mental State Examination (MMSE) was used to evaluate the cognitive function. Information on demographic features and potential risk factors for CI was collected during the interview. Multivariate logistic regression was performed to identify risk factors associated with CI. RESULTS: Based on the education modified MMSE score, we identified 329 CI cases in rural community and 227 in urban community. The prevalence of CI was 7.43% in rural population and 6.54% in urban population (p = 0.13). In the urban population, risk of having CI was associated with age (OR = 1.04; 95% CI: 1.01-1.08), lack of physical activities (OR = 2.25; 95% CI: 1.11-4.57), presence of diabetes mellitus (OR = 1.79; 95% CI: 1.04-3.07), and having three or more children (OR = 2.39; 95% CI: 1.27-4.50). In contrast, factors associated with rural populations included female gender (OR = 2.03; 95% CI: 1.08-3.82), age (OR = 1.06; 95% CI: 1.03-1.08), exposure to pesticides (OR = 4.68; 95% CI: 1.27-17.21), history of encephalitis or meningitis (OR = 6.02; 95% CI: 1.92-18.85) and head trauma (OR = 1.89; 95% CI: 1.10-3.24). CONCLUSIONS: Urban rural and populations showed different risk factors for CI, suggesting that different preventive strategies in these areas should be performed.
Keywords: Aged; Aged, 80 and over; China; Cognition Disorders; Female; Humans; Logistic Models; Male; Mental Status Schedule; Middle Aged; Multivariate Analysis; Prevalence; Risk Factors; Rural Population; Urban Population

Prognostic Significance of Mild Cognitive Impairment Subtypes for Dementia and Mortality: Data from the NEDICES Cohort. - Bermejo-Pareja, Félix; Contador, Israel; Trincado, Rocío; Lora, David; Sánchez-Ferro, Álvaro; Mitchell, Alex J; Boycheva, Elina; Herrero, Alejandro; Hernández-Gallego, Jesús; Llamas, Sara; Villarejo Galende, Alberto; Benito-León, Julián (J Alzheimers Dis, 2016)
BACKGROUND: The predictive value of diverse subtypes of mild cognitive impairment (MCI) for dementia and death is highly variable. OBJECTIVE: To compare the predictive value of several MCI subtypes in progression to dementia and/or mortality in the NEDICES (Neurological Disorders in Central Spain) elderly cohort. METHODS: Retrospect algorithmic MCI subgroups were established in a non-dementia baseline NEDICES cohort using Spanish adaptations of the original Mini-Mental State Examination (MMSE-37) and Pfeffer's Functional Activities Questionnaire (Pfeffer-11). The presence of MCI was defined according two cognitive criteria: using two cut-offs points on the total MMSE-37 score. Five cognitive domains were used to establish the MCI subtypes. Functional capacity (Pfeffer-11) was preserved or minimally impaired in all MCI participants. The incident dementia diagnoses were established by specialists and the mortality data obtained from Spanish official registries. RESULTS: 3,411 participants without dementia were assessed in 1994-5. The baseline prevalence of MCI varied according to the MCI definition (4.3%-31.8%). The follow-up was a mean of 3.2 years (1997-8). The dementia incidence varied between 14.9 and 71.8 per 1,000/person-years. The dementia conversion rate was increased in almost all MCI subgroups (p >  0.01), and mortality rate was raised only in four MCI subtypes. The amnestic-multi-domain MCI (aMd-MCI) had the best dementia predictive accuracy (highest positive likelihood ratio and highest clinical utility when negative). CONCLUSIONS: Those with aMd-MCI were at greatest risk of progression to dementia, as in other surveys and might be explored with increased attention in MCI research and in dementia preventive trials.
Keywords: Aged; Aged, 80 and over; Algorithms; Cognitive Dysfunction; Cohort Studies; Dementia; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Spain

Progranulin Protein Levels in Cerebrospinal Fluid in Primary Neurodegenerative Dementias. - Morenas-Rodriguez, Estrella; Cervera-Carles, Laura; Vilaplana, Eduard; Alcolea, Daniel; Carmona-Iragui, María; Dols-Icardo, Oriol; Ribosa-Nogué, Roser; Muñoz-Llahuna, Laia; Sala, Isabel; Belén Sánchez-Saudinós, M; Blesa, Rafael; Clarimón, Jordi; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Progranulin is implicated in frontotemporal dementia (FTD), but its role in other neurodegenerative disorders is unknown. OBJECTIVE: To investigate the levels of progranulin (PGRN) in cerebrospinal fluid (CSF) in different neurodegenerative dementias and their correlation with levels in plasma in cognitively normal subjects. METHODS: We measured PGRN in CSF in 229 patients with amnestic mild cognitive impairment, Alzheimer's disease dementia, sporadic FTD, dementia with Lewy bodies, corticobasal syndrome, or progressive supranuclear palsy. We also measured PGRN in CSF and plasma in 74 cognitively normal individuals. We examined the correlation between PGRN levels in CSF and diagnosis, cortical thickness, genetic factors and other CSF biomarkers. We also investigated the correlation between plasma and CSF levels of PGRN in cognitively normal individuals. RESULTS: CSF levels did not differ across diagnoses or correlate with cortical thickness. Polymorphism rs5848 in GRN influenced CSF PGRN levels, but APOEɛ4 allele did not. Amyloid-β42, t-tau, p-tau, and YKL-40 levels correlated weakly with PGRN in CSF. We found a weak correlation (r = 0.362) between plasma and CSF PGRN levels in cognitively normal individuals. CONCLUSIONS: Our findings do not support a diagnostic value of CSF PGRN in neurodegenerative diseases. Our data confirm that levels of PGRN in plasma do not reflect accurately levels in CSF in cognitively normal controls. These data should be considered in clinical trials aiming to increase PGRN.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Biomarkers; Dementia; Female; Humans; Intercellular Signaling Peptides and Proteins; Male; Middle Aged; Neurodegenerative Diseases; Polymorphism, Single Nucleotide; tau Proteins

Progression of Extrapyramidal Signs in Alzheimer's Disease: Clinical and Neuropathological Correlates. - Tosto, Giuseppe; Monsell, Sarah E; Hawes, Stephen E; Bruno, Giuseppe; Mayeux, Richard (J Alzheimers Dis, 2016)
BACKGROUND: Extrapyramidal signs (EPS) are frequent in Alzheimer's disease (AD) and core manifestation of related diseases, i.e., dementia with Lewy bodies and Parkinson's disease; furthermore, Lewy bodies and AD-type pathology occur in all three conditions. OBJECTIVE: To identify clusters of EPS progression over time and their clinical and neuropathological correlates. METHODS: 3,502 AD patients with longitudinal assessment from the National Alzheimer's Coordinating Center database were included; 394 provided neuropathological data. k-means algorithm was employed to identify clusters of EPS progression and those were compared in terms of cognitive profile, neuropsychiatric features and neuropathological findings. RESULTS: Three clusters of EPS progression were identified: no/low (n = 1,583), medium (n = 1,259), and high (n = 660) EPS burden. Compared to those with no/low and medium EPS, those with high EPS had greater cognitive and neuropsychiatric impairment, specifically hallucinations. Despite similar AD-pathology across the three clusters, the high EPS cluster had a significantly number of subjects diagnosed with dementia with Lewy bodies. CONCLUSIONS: Cluster analysis of EPS progression over time identified different subgroups of AD patients with distinct clinical and neuropathological features.
Keywords: Aged; Algorithms; Alzheimer Disease; Cluster Analysis; Databases, Factual; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Severity of Illness Index

Prospective Memory Impairments in Alzheimer's Disease and Behavioral Variant Frontotemporal Dementia: Clinical and Neural Correlates. - Dermody, Nadene; Hornberger, Michael; Piguet, Olivier; Hodges, John R; Irish, Muireann (J Alzheimers Dis, 2016)
BACKGROUND: Prospective memory (PM) refers to a future-oriented form of memory in which the individual must remember to execute an intended action either at a future point in time (Time-based) or in response to a specific event (Event-based). Lapses in PM are commonly exhibited in neurodegenerative disorders including Alzheimer's disease (AD) and frontotemporal dementia (FTD), however, the neurocognitive mechanisms driving these deficits remain unknown. OBJECTIVE: To investigate the clinical and neural correlates of Time- and Event-based PM disruption in AD and the behavioral-variant FTD (bvFTD). METHODS: Twelve AD, 12 bvFTD, and 12 healthy older Control participants completed a modified version of the Cambridge Prospective Memory test, which examines Time- and Event-based aspects of PM. All participants completed a standard neuropsychological assessment and underwent whole-brain structural MRI. RESULTS: AD and bvFTD patients displayed striking impairments across Time- and Event-based PM relative to Controls, however, Time-based PM was disproportionately affected in the AD group. Episodic memory dysfunction and hippocampal atrophy were found to correlate strongly with PM integrity in both patient groups, however, dissociable neural substrates were also evident for PM performance across dementia syndromes. CONCLUSION: Our study reveals the multifaceted nature of PM dysfunction in neurodegenerative disorders, and suggests common and dissociable neurocognitive mechanisms, which subtend these deficits in each patient group. Future studies of PM disturbance in dementia syndromes will be crucial for the development of successful interventions to improve functional independence in the patient's daily life.
Keywords: Aged; Alzheimer Disease; Atrophy; Brain; Brain Mapping; Female; Frontotemporal Dementia; Humans; Magnetic Resonance Imaging; Male; Memory Disorders; Memory, Episodic; Middle Aged; Neuropsychological Tests

Protein Kinase Activity Decreases with Higher Braak Stages of Alzheimer's Disease Pathology. - Rosenberger, Andrea F N; Hilhorst, Riet; Coart, Elisabeth; García Barrado, Leandro; Naji, Faris; Rozemuller, Annemieke J M; van der Flier, Wiesje M; Scheltens, Philip; Hoozemans, Jeroen J M; van der Vies, Saskia M (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by a long pre-clinical phase (20-30 years), during which significant brain pathology manifests itself. Disease mechanisms associated with pathological hallmarks remain elusive. Most processes associated with AD pathogenesis, such as inflammation, synaptic dysfunction, and hyper-phosphorylation of tau are dependent on protein kinase activity. The objective of this study was to determine the involvement of protein kinases in AD pathogenesis. Protein kinase activity was determined in postmortem hippocampal brain tissue of 60 patients at various stages of AD and 40 non-demented controls (Braak stages 0-VI) using a peptide-based microarray platform. We observed an overall decrease of protein kinase activity that correlated with disease progression. The phosphorylation of 96.7% of the serine/threonine peptides and 37.5% of the tyrosine peptides on the microarray decreased significantly with increased Braak stage (p-value <0.01). Decreased activity was evident at pre-clinical stages of AD pathology (Braak I-II). Increased phosphorylation was not observed for any peptide. STRING analysis in combination with pathway analysis and identification of kinases responsible for peptide phosphorylation showed the interactions between well-known proteins in AD pathology, including the Ephrin-receptor A1 (EphA1), a risk gene for AD, and sarcoma tyrosine kinase (Src), which is involved in memory formation. Additionally, kinases that have not previously been associated with AD were identified, e.g., protein tyrosine kinase 6 (PTK6/BRK), feline sarcoma oncogene kinase (FES), and fyn-associated tyrosine kinase (FRK). The identified protein kinases are new biomarkers and potential drug targets for early (pre-clinical) intervention.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Female; Hippocampus; Humans; Male; Middle Aged; Phosphorylation; Protein Kinases; Protein-Serine-Threonine Kinases; Severity of Illness Index

Psychometric Properties of the Memory Binding Test: Test-Retest Reliability and Convergent Validity. - Gramunt, Nina; Sánchez-Benavides, Gonzalo; Buschke, Herman; Lipton, Richard B; Masramon, Xavier; Gispert, Juan D; Peña-Casanova, Jordi; Fauria, Karine; Molinuevo, José L (J Alzheimers Dis, 2016)
BACKGROUND: Episodic memory testing is fundamental for the diagnosis of Alzheimer's disease (AD). Although the Free and Cued Selective Reminding Test (FCSRT) is widely used for this purpose, it may not be sensitive enough for early detection of subtle decline in preclinical AD. The Memory Binding Test (MBT) intends to overcome this limitation. OBJECTIVES: To analyze the test-retest reliability of the MBT and its convergent validity with the FCRST. METHODS: 36 cognitively healthy participants of the ALFA Study, aged 45 to 65, were included for the test-retest study and 69 for the convergent analysis. They were visited twice in a period of 6 ± 2 weeks. Test-retest reliability was determined by the calculation of the intra-class correlation coefficient (ICC). Score differences were studied by computing the mean percentage of score variation between visits and visualized by Bland-Altman plots. Convergent validity was determined by Pearson's correlations. RESULTS: ICC values in the test-retest reliability analysis of the MBT direct scores ranged from 0.64 to 0.76. Subjects showed consistent practice effects, with mean amounts of score increasing between 10% and 26%. Pearson correlation between MBT and FCSRT direct scores showed r values between 0.40 and 0.53. The FCSRT displayed ceiling effects not observed in the MBT. CONCLUSIONS: The MBT shows adequate test-retest reliability and overall moderate convergent validity with the FCSRT. Unlike the FCSRT, the MBT does not have ceiling effects and it may therefore be especially useful in longitudinal studies, facilitating the measurement of subtle memory performance decline and the detection of very early AD.
Keywords: Aged; Alzheimer Disease; Female; Humans; Male; Memory; Middle Aged; Psychological Tests; Psychometrics; Reproducibility of Results

Psychotropic Drug Prescription in Patients with Dementia: Nursing Home Residents Versus Patients Living at Home. - Jacquin-Piques, Agnès; Sacco, Guillaume; Tavassoli, Neda; Rouaud, Olivier; Bejot, Yannick; Giroud, Maurice; Robert, Philippe; Vellas, Bruno; Bonin-Guillaume, Sylvie (J Alzheimers Dis, 2016)
BACKGROUND: Psychotropic drugs are frequently prescribed in nursing homes (NH). Nonetheless, we hoped that institutionalization decreases the number of psychotropic drug classes prescribed, because NH residents may have more psychosocial interventions than patients living at home. OBJECTIVE: The aim was to compare the type and number of psychotropic drugs prescribed in elderly NH residents with dementia with those in community-living patients. METHODS: This cross-sectional study included elderly patients (at least 75 years old) with dementia recorded in the National Alzheimer's data Bank ("Banque Nationale Alzheimer") during the year 2012 and who were taking at least one psychotropic drug. Psychotropic drugs were classified as follows: antidepressant, anxiolytic, hypnotic, and antipsychotic drugs. Patients were classified into three categories of dementia severity according to the MMSE score. RESULTS: Among the 50,932 patients with dementia recorded in the BNA, 40.1% had at least one psychotropic drug prescribed. Most of the patients who were treated by at least one psychotropic drug class had antidepressant therapy (69.0%), whatever their residence type, and 16.1% were treated with antipsychotics. Among the study population, 51.9% of the NH residents and 67.4% of the patients living at home had only one psychotropic drug class prescribed. Living in a NH was significantly associated with the more frequent prescription of anxiolytic, hypnotic, and antipsychotic drugs, and with a greater number of psychotropic drug classes prescribed, whatever the severity of the dementia. CONCLUSION: We underlined the more frequent prescription of psychotropic drugs in NH residents regardless of MMSE scores.
Keywords: Aged; Aged, 80 and over; Chi-Square Distribution; Cross-Sectional Studies; Databases, Factual; Dementia; Drug Prescriptions; Female; Humans; Male; Nursing Homes; Psychotropic Drugs; Residence Characteristics

A Qualitative Impairment in Face Perception in Alzheimer's Disease: Evidence from a Reduced Face Inversion Effect. - Lavallée, Marie Maxime; Gandini, Delphine; Rouleau, Isabelle; Vallet, Guillaume T; Joannette, Maude; Kergoat, Marie-Jeanne; Busigny, Thomas; Rossion, Bruno; Joubert, Sven (J Alzheimers Dis, 2016)
Prevalent face recognition difficulties in Alzheimer's disease (AD) have typically been attributed to the underlying episodic and semantic memory impairment. The aim of the current study was to determine if AD patients are also impaired at the perceptual level for faces, more specifically at extracting a visual representation of an individual face. To address this question, we investigated the matching of simultaneously presented individual faces and of other nonface familiar shapes (cars), at both upright and inverted orientation, in a group of mild AD patients and in a group of healthy older controls matched for age and education. AD patients showed a reduced inversion effect (i.e., larger performance for upright than inverted stimuli) for faces, but not for cars, both in terms of error rates and response times. While healthy participants showed a much larger decrease in performance for faces than for cars with inversion, the inversion effect did not differ significantly for faces and cars in AD. This abnormal inversion effect for faces was observed in a large subset of individual patients with AD. These results suggest that AD patients have deficits in higher-level visual processes, more specifically at perceiving individual faces, a function that relies on holistic representations specific to upright face stimuli. These deficits, combined with their memory impairment, may contribute to the difficulties in recognizing familiar people that are often reported in patients suffering from the disease and by their caregivers.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Face; Facial Recognition; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Orientation; Pattern Recognition, Visual; Perceptual Disorders; Photic Stimulation; Psychiatric Status Rating Scales; Reaction Time; Statistics as Topic

Quantitative Neuroimaging Software for Clinical Assessment of Hippocampal Volumes on MR Imaging. - Ahdidan, Jamila; Raji, Cyrus A; DeYoe, Edgar A; Mathis, Jedidiah; Noe, Karsten Ø; Rimestad, Jens; Kjeldsen, Thomas K; Mosegaard, Jesper; Becker, James T; Lopez, Oscar (J Alzheimers Dis, 2016)
BACKGROUND: Multiple neurological disorders including Alzheimer's disease (AD), mesial temporal sclerosis, and mild traumatic brain injury manifest with volume loss on brain MRI. Subtle volume loss is particularly seen early in AD. While prior research has demonstrated the value of this additional information from quantitative neuroimaging, very few applications have been approved for clinical use. Here we describe a US FDA cleared software program, NeuroreaderTM, for assessment of clinical hippocampal volume on brain MRI. OBJECTIVE: To present the validation of hippocampal volumetrics on a clinical software program. METHOD: Subjects were drawn (n = 99) from the Alzheimer Disease Neuroimaging Initiative study. Volumetric brain MR imaging was acquired in both 1.5 T (n = 59) and 3.0 T (n = 40) scanners in participants with manual hippocampal segmentation. Fully automated hippocampal segmentation and measurement was done using a multiple atlas approach. The Dice Similarity Coefficient (DSC) measured the level of spatial overlap between NeuroreaderTM and gold standard manual segmentation from 0 to 1 with 0 denoting no overlap and 1 representing complete agreement. DSC comparisons between 1.5 T and 3.0 T scanners were done using standard independent samples T-tests. RESULTS: In the bilateral hippocampus, mean DSC was 0.87 with a range of 0.78-0.91 (right hippocampus) and 0.76-0.91 (left hippocampus). Automated segmentation agreement with manual segmentation was essentially equivalent at 1.5 T (DSC = 0.879) versus 3.0 T (DSC = 0.872). CONCLUSION: This work provides a description and validation of a software program that can be applied in measuring hippocampal volume, a biomarker that is frequently abnormal in AD and other neurological disorders.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Hippocampus; Humans; Image Interpretation, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Software

Quantitative phosphoproteomic analyses of the inferior parietal lobule from three different pathological stages of Alzheimer's disease. - Triplett, Judy C; Swomley, Aaron M; Cai, Jian; Klein, Jon B; Butterfield, D Allan (J Alzheimers Dis, 2016)
Alzheimer's disease (AD), the most common age-related neurodegenerative disorder, is clinically characterized by progressive neuronal loss resulting in loss of memory and dementia. AD is histopathologically characterized by the extensive distribution of senile plaques and neurofibrillary tangles, and synapse loss. Amnestic mild cognitive impairment (MCI) is generally accepted to be an early stage of AD. MCI subjects have pathology and symptoms that fall on the scale intermediately between 'normal' cognition with little or no pathology and AD. A rare number of individuals, who exhibit normal cognition on psychometric tests but whose brains show widespread postmortem AD pathology, are classified as 'asymptomatic' or 'preclinical' AD (PCAD). In this study, we evaluated changes in protein phosphorylation states in the inferior parietal lobule of subjects with AD, MCI, PCAD, and control brain using a 2-D PAGE proteomics approach in conjunction with Pro-Q Diamond phosphoprotein staining. Statistically significant changes in phosphorylation levels were found in 19 proteins involved in energy metabolism, neuronal plasticity, signal transduction, and oxidative stress response. Changes in the disease state phosphoproteome may provide insights into underlying mechanisms for the preservation of memory with expansive AD pathology in PCAD and the progressive memory loss in amnestic MCI that escalates to the dementia and the characteristic pathology of AD brain.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Disease Progression; Female; Humans; Male; Memory; Neurofibrillary Tangles; Oxidative Stress; Parietal Lobe; Phosphorylation; Plaque, Amyloid; Proteome

Reduction of Amyloid-β Plasma Levels by Hemodialysis: An Anti-Amyloid Treatment Strategy? - Tholen, Susanne; Schmaderer, Christoph; Chmielewski, Stefan; Förstl, Hans; Heemann, Uwe; Baumann, Marcus; Steubl, Dominik; Grimmer, Timo (J Alzheimers Dis, 2016)
BACKGROUND: Cognitive impairment in hemodialysis patients is common, but the underlying pathogenesis remains unclear. Alzheimer's disease is the most common cause of dementia in the general elderly population. Histopathological hallmarks are, among others, senile plaques, which consist of amyloid-β (Aβ). OBJECTIVE: To measure plasma levels of Aβ42 and Aβ40 during hemodialysis and to examine potential associations with cognitive performance in cognitively impaired hemodialysis patients. METHODS: Plasma samples of 26 hemodialysis patients were collected shortly before, after 50% of dialysis time, and at the end of a dialysis session. Aβ42 and Aβ40 levels were measured by a high-sensitivity ELISA for human amyloid-β. Cognition was tested under standardized conditions using the Montreal Cognitive Assessment (MoCA) as proposed previously. RESULTS: Clearance rates of both peptides during one dialysis session were 22% and 35% for Aβ42 and Aβ40, respectively. Aβ42 but not Aβ40 baseline levels were significantly associated with MoCA test results (r = 0.654, p = 0.001). CONCLUSION: In cognitively impaired hemodialysis patients plasma Aβ42 levels were associated with cognitive performance and both Aβ42 and Aβ40 plasma levels could be effectively reduced by dialysis. By inducing peripheral Aβ sink, hemodialysis may be considered as an anti-amyloid treatment strategy.
Keywords: Adult; Aged; Aged, 80 and over; Amyloid beta-Peptides; Cognition Disorders; Enzyme-Linked Immunosorbent Assay; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Renal Dialysis

Region-Specific Vulnerability to Oxidative Stress, Neuroinflammation, and Tau Hyperphosphorylation in Experimental Diabetes Mellitus Mice. - Elahi, Montasir; Hasan, Zafrul; Motoi, Yumiko; Matsumoto, Shin-Ei; Ishiguro, Koichi; Hattori, Nobutaka (J Alzheimers Dis, 2016)
Recent epidemiological evidence suggests that diabetes mellitus (DM) is a risk factor for Alzheimer's disease (AD). One of the pathological hallmarks of AD is hyperphosphorylated tau protein, which forms neurofibrillary tangles. Oxidative stress and the activation of inflammatory pathways are features that are associated with both DM and AD. However, the brain region specificity of AD-related neurodegeneration, which mainly occurs in the hippocampus while the cerebellum is relatively unaffected, has not yet been clarified. Therefore, we used experimental DM mice (caused by an intraperitoneal injection of streptozotocin [STZ]) to determine whether these neurodegeneration-associated mechanisms were associated with region-specific selective vulnerability or tau phosphorylation. The hippocampus, midbrain, and cerebellum of aged (14 to 18 months old) non-transgenic (NTg) and transgenic mice overexpressing wild-type human tau (Tg601 mice) were evaluated after a treatment with STZ. The STZ injection increased reactive oxygen species, lipid peroxidation markers such as 4-hydroxynonenal and malondialdehyde in the hippocampus, but not in the midbrain or cerebellum. The STZ treatment also increased the number of Iba-1-positive and CD68-positive microglial cells, astrocytes, and IL-1β, IL-6, IL-10, and IL-18 levels in the hippocampus, but not in the midbrain or cerebellum. Tau hyperphosphorylation was also enhanced in the hippocampus, but not in the midbrain or cerebellum. When the effects of STZ were compared between Tg601 and NTg mice, microglial proliferation and elevations in IL-6 and phosphorylated tau were higher in Tg601 mice. These results suggest that neuroinflammation and oxidative stress in STZ-treated mice are associated with tau hyperphosphorylation, which may contribute to selective neurodegeneration in human AD.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Antibiotics, Antineoplastic; Brain; Calcium-Binding Proteins; Calcium-Calmodulin-Dependent Protein Kinase Type 2; Cell Proliferation; Diabetes Mellitus, Experimental; Disease Models, Animal; Encephalitis; Female; Humans; Lipid Peroxidation; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microfilament Proteins; Neuroglia; Oxidative Stress; Reactive Oxygen Species; Streptozocin; tau Proteins

Reproductive history and risk of cognitive impairment in elderly women: a cross-sectional study in eastern China. - Li, Fu-Dong; He, Fan; Chen, Ting-Rui; Xiao, Yuan-Yuan; Lin, Shang-Tong; Shen, Wei; Wang, Xin-Yi; Zhai, Yu-Jia; Shang, Xiao-Peng; Lin, Jun-Fen (J Alzheimers Dis, 2016)
BACKGROUND: Epidemiological studies suggest that proxies of higher lifetime estrogen exposure are associated with better cognitive function in postmenopausal women, but this has not been found consistently. OBJECTIVE: To determine whether reproductive history, an important modifier of estrogen exposure across the lifetime, is associated with risk of cognitive impairment in postmenopausal women. METHODS: We analyzed the baseline data from Zhejiang Major Public Health Surveillance Program (ZPHS) including 4,796 postmenopausal women. Cognitive impairment was assessed through the application of Mini-Mental State Examination questionnaire. Logistic regression models, controlled for an extensive range of potential confounders, were generated to examine the associations between women's reproductive history and risk of cognitive impairment in their later life. RESULTS: The length of reproductive period was inversely associated with risk of cognitive impairment (p = 0.001). Odds ratio (OR) of cognitive impairment were 1.316 (95% CI 1.095∼1.582) for women with 5 or more times of full-term pregnancies, compared with those with 1∼4 times of full-term pregnancies. Women without incomplete pregnancy had a significant higher risk of cognitive impairment (OR = 1.194, 95% CI 1.000∼1.429), compared with the reference (1∼2 times of incomplete pregnancies). Oral contraceptive use (OR = 0.489, 95% CI 0.263∼0.910) and intrauterine device (IUD) use (OR = 0.684, 95% CI 0.575∼0.815) were associated with significantly reduced risk of cognitive impairment. CONCLUSION: Our results indicated that shorter reproductive period, higher number of full-term pregnancies and no incomplete pregnancy history were associated with an increased risk of cognitive impairment. In contrast, oral contraceptive and IUD use corresponded to reduced risk of cognitive impairment.
Keywords: Aged; Aged, 80 and over; China; Cognition; Cognition Disorders; Contraceptives, Oral; Cross-Sectional Studies; Estrogens; Female; Humans; Intrauterine Devices; Logistic Models; Middle Aged; Neuropsychological Tests; Odds Ratio; Postmenopause; Psychiatric Status Rating Scales; Reproductive History

Resting-State Cardiac Workload is Related to Both Increased Neocortical Aggregation of Amyloid-β and Relative Impairments in Spatial Working Memory in Pre-Clinical Alzheimer's Disease. - Santos, Cláudia Yang; Lim, Yen Ying; Wu, Wen-Chih; Machan, Jason Timothy; Polynice, Shahena; Schindler, Rachel; Maruff, Paul; Snyder, Peter Jeffrey (J Alzheimers Dis, 2016)
We sought to determine whether there is any association between a cardiac workload marker, rate pressure product (RPP), working memory, and cortical amyloid-β (Aβ) burden in 63 cognitively normal midlife adults (Mage = 62.8 years; range = 55 to 75 years) at risk for Alzheimer's disease (AD). The results show a small-to-moderate relationship between increasing cardiac workload (at rest) and neocortical amyloidosis in individuals at the preclinical stage of AD. Moreover, increasing RPP was linearly related to increasing relative impairments on a spatial working memory task (R2 = 0.30), but only for those individuals with neuroimaging evidence suggestive of preclinical AD. These results support a relationship between the aggregation of Aβ protein plaques in the neocortex, increased cognitive impairment, and more inefficient myocardial oxygen use in the absence of significant metabolic demands.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Blood Pressure; Disease Progression; Female; Heart Rate; Humans; Male; Maze Learning; Memory Disorders; Middle Aged; Neocortex; Neuropsychological Tests; Positron-Emission Tomography; Protein Aggregation, Pathological; Workload

Retinal oximetry imaging in Alzheimer's disease. - Einarsdottir, Anna Bryndis; Hardarson, Sveinn Hakon; Kristjansdottir, Jona Valgerdur; Bragason, David Thor; Snaedal, Jon; Stefánsson, Einar (J Alzheimers Dis, 2016)
BACKGROUND: Structural and physiological abnormalities have been reported in the retina in Alzheimer's disease (AD). Retinal oximetry detects changes in retinal oxygen metabolism in many eye diseases, where structural changes are seen. OBJECTIVE: To compare oxygen saturation in retinal blood vessels in patients with AD and a healthy cohort. METHODS: Oxygen saturation of hemoglobin was measured in retinal blood vessels, using imaging with spectrophotometric noninvasive retinal oximeter. 18 individuals with mild to moderate dementia of the Alzheimer-type (stage 3-5 according to the Global Deterioration Scale) and 18 healthy subjects underwent retinal oximetry in a case control study. RESULTS: Retinal oxygen saturation in arterioles and venules in patients with moderate AD was significantly elevated compared to healthy individuals. Retinal arterioles have 94.2 ± 5.4% oxygen saturation in moderate AD compared with 90.5 ± 3.1% in healthy subjects (mean ± SD, n = 10, p = 0.028). Retinal venules were 51.9 ± 6.0% saturated in moderate AD compared with 49.7 ± 7.0% in healthy subjects (mean ± SD, n = 10, p = 0.02). CONCLUSION: This is the first study of retinal oxygen metabolism in any central nervous system disease. It discovers abnormalities in retinal oxygen metabolism in AD. The findings are similar to those seen in age-related macular degeneration and diabetic retinopathy. Noninvasive retinal oximetry may offer new insights into pathophysiology of AD. Further studies are needed to confirm and expand these findings.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Female; Hemoglobins; Humans; Male; Middle Aged; Oximetry; Oxygen; Oxygen Consumption; Regional Blood Flow; Retina; Retinal Vessels

Reversal of LTP-Like Cortical Plasticity in Alzheimer's Disease Patients with Tau-Related Faster Clinical Progression. - Koch, Giacomo; Di Lorenzo, Francesco; Del Olmo, Miguel Fernandez; Bonní, Sonia; Ponzo, Viviana; Caltagirone, Carlo; Bozzali, Marco; Martorana, Alessandro (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) concentrations of amyloid-β (Aβ), total tau (t-tau), and phosphorylated tau proteins are associated with different clinical progression in Alzheimer's disease (AD). We enrolled forty newly diagnosed AD patients, who underwent lumbar puncture, and carried out a K-means cluster analysis based on CSF biomarkers levels, resulting in two AD patient groups: Cluster 1 showed relatively high levels of Aβ and low levels of tau; Cluster 2 showed relatively low levels of Aβ and high levels of tau. Cortical plasticity was tested using the intermittent and continuous theta burst stimulation (iTBS and cTBS) protocols evoking respectively long-term potentiation (LTP) and depression (LTD). Cholinergic transmission was tested by the short-latency afferent inhibition protocol. Neurophysiological evaluation showed that the two AD groups differed in terms of cortical plasticity: after iTBS, Cluster 2 patients showed a remarkable reversal of LTP toward LTD that was not observed in Cluster 1. LTD and central cholinergic transmission did not differ between groups. Patients were assessed longitudinally with Mini-Mental State Examination at 6, 12, and 18 month follow-ups. Cluster 2 AD had a faster cognitive decline already evident at the 12 month follow-up. High tau CSF levels were associated with LTD-like cortical plasticity and faster clinical progression. These results suggest that more aggressive tau pathology is associated with prominent LTD-like mechanisms of cortical plasticity and faster cognitive decline.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognition; Disease Progression; Evoked Potentials, Motor; Female; Humans; Male; Motor Cortex; Neuronal Plasticity; Neuropsychological Tests; Phosphorylation; tau Proteins; Transcranial Magnetic Stimulation

Reversible Mild Cognitive Impairment: The Role of Comorbidities at Baseline Evaluation. - Grande, Giulia; Cucumo, Valentina; Cova, Ilaria; Ghiretti, Roberta; Maggiore, Laura; Lacorte, Eleonora; Galimberti, Daniela; Scarpini, Elio; Clerici, Francesca; Pomati, Simone; Vanacore, Nicola; Mariani, Claudio (J Alzheimers Dis, 2016)
The prognostic value of mild cognitive impairment (MCI) is being questioned, with some MCI subjects reverting to normal cognition (NC). The reversion rate varies mostly depending on the study design, the setting, and both MCI and NC definitions. Previous studies have focused on the profile of subjects who revert to NC, but the role of comorbidities has not been entirely investigated. We aimed to evaluate the proportion of MCI subjects who revert to NC in a memory clinic context, focusing on the role of comorbidities. Between 2004 and 2013, 374 MCI subjects were recruited. During a mean time of 32 ± 25.5 months, 21 subjects (5.6%) reverted to NC. Subjects who reverted to NC were younger (p = 0.0001), more educated (p = 0.0001), had a better global cognition (p = 0.0001), as assessed by the Mini-Mental State Examination (MMSE) and suffered from more comorbidities (p = 0.002), as assessed by Cumulative Illness Rating Scale (CIRS) than those who developed dementia. The Cox Regression Model, constructed to adjust for the confounders, showed that the higher were the MMSE (HR = 1.83, CI 95%: 1.07-3.11) and the CIRS score (HR = 1.3, CI 95% 0.88-1.92) at baseline, the higher was the probability of returning to NC than developing dementia, though the last association was not significant. Subjects who reverted to NC were more frequently affected by respiratory (p = 0.002), urologic (p = 0.012), and psychiatric (p = 0.012) diseases. The cognitive performance of subjects with medical comorbidities could benefit from preventive strategies aimed at treating the underlying diseases.
Keywords: Analysis of Variance; Cognitive Dysfunction; Cohort Studies; Comorbidity; Female; Humans; Male; Memory; Mental Status Schedule; Neuropsychological Tests; Reference Values; Verbal Learning

Revisiting the Heidenhain Variant of Creutzfeldt-Jakob Disease: Evidence for Prion Type Variability Influencing Clinical Course and Laboratory Findings. - Baiardi, Simone; Capellari, Sabina; Ladogana, Anna; Strumia, Silvia; Santangelo, Mario; Pocchiari, Maurizio; Parchi, Piero (J Alzheimers Dis, 2016)
The Heidenhain variant defines a peculiar clinical presentation of sporadic Creutzfeldt-Jakob disease (sCJD) characterized by isolated visual disturbances at disease onset and reflecting the early targeting of prions to the occipital cortex. Molecular and histopathological typing, thus far performed in 23 cases, has linked the Heidenhain variant to the MM1 sCJD type. To contribute a comprehensive characterization of cases with the Heidenhain variant, we reviewed a series of 370 definite sCJD cases. Eighteen patients (4.9%) fulfilled the selection criteria. Fourteen of them belonging to sCJD types MM1 or MM1+2C had a short duration of isolated visual symptoms and overall clinical disease, a high prevalence of periodic sharp-wave complexes in EEG, and a marked increase of cerebrospinal fluid proteins t-tau and 14-3-3 levels. In contrast, three cases of the MM 2C or MM 2+1C types showed a longer duration of isolated visual symptoms and overall clinical disease, non-specific EEG findings, and cerebrospinal fluid concentration below threshold for the diagnosis of "probable" CJD of both 14-3-3 and t-tau. However, a brain DWI-MRI disclosed an occipital cortical hyperintensity in the majority of examined cases of both groups. While confirming the strong linkage with the methionine genotype at the polymorphic codon 129 of the prion protein gene, our results definitely establish that the Heidenhain variant can also be associated with the MM 2C sCJD type in addition to the more common MM1 type. Likewise, our results highlight the significant differences in clinical evolution and laboratory findings between cases according to the dominant PrPSc type (type 1 versus type 2).
Keywords: Aged; Aged, 80 and over; Brain; Creutzfeldt-Jakob Syndrome; Female; Genotype; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Phenotype; Prions

Risk of dementia in patients with celiac disease: a population-based cohort study. - Lebwohl, Benjamin; Luchsinger, Jose A; Freedberg, Daniel E; Green, Peter H R; Ludvigsson, Jonas F (J Alzheimers Dis, 2016)
BACKGROUND: Patients with celiac disease (CD) frequently report cognitive symptoms when they are exposed to gluten, and cognitive deficits have been quantified in patients with newly diagnosed CD. OBJECTIVE: To determine whether patients with CD have an increased risk of dementia. METHODS: Using a population-based database of older adults (age ≥50 years) with histologically proven CD (duodenal/jejunal villous atrophy) from all 28 pathology departments in Sweden, we compared the incidence of a subsequent dementia diagnosis to those of age- and gender-matched controls. RESULTS: Among patients with CD (n = 8,846) and controls (n = 43,474), the median age was 63 years and 56% were female. During a median follow-up time of 8.4 years, dementia was diagnosed in 4.3% of CD patients and 4.4% of controls (HR 1.07; 95% CI 0.95-1.20). Although there was an increased risk of dementia in the first year following a diagnosis of CD (HR 1.73; 95% CI 1.15-2.61), this risk was not present in the whole observation period. Among those subjects with a dementia subtype specified, the increased risk was restricted to vascular dementia (HR 1.28; 95% CI 1.00-1.64) and was not present for Alzheimer's dementia (HR 1.12; 95% CI 0.91-1.37). CONCLUSIONS: Patients with CD are not at increased risk for dementia overall, though subgroup analysis suggests that they may be at increased risk for vascular dementia.
Keywords: Aged; Celiac Disease; Cohort Studies; Databases, Factual; Dementia; Female; Humans; Incidence; Logistic Models; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Sweden

The Role of Alzheimer's and Cerebrovascular Pathology in Mediating the Effects of Age, Race, and Apolipoprotein E Genotype on Dementia Severity in Pathologically-Confirmed Alzheimer's Disease. - Gavett, Brandon E; John, Samantha E; Gurnani, Ashita S; Bussell, Cara A; Saurman, Jessica L (J Alzheimers Dis, 2016)
BACKGROUND: Dementia severity can be modeled as the construct δ, representing the "cognitive correlates of functional status." OBJECTIVE: We recently validated a model for estimating δ in the National Alzheimer's Coordinating Center's Uniform Data Set; however, the association of δ with neuropathology remains untested. METHODS: We used data from 727 decedents evaluated at Alzheimer's Disease (AD) Centers nationwide. Participants spoke English, had no genetic abnormalities, and were pathologically diagnosed with AD as a primary or contributing etiology. Clinical data from participants' last visit prior to death were used to estimate dementia severity (δ). RESULTS: A structural equation model using age, education, race, and apolipoprotein E (APOE) genotype (number of ɛ2 and ɛ4 alleles) as predictors and latent AD pathology and cerebrovascular disease (CVD) pathology as mediators fit the data well (RMSEA = 0.031; CFI = 0.957). AD pathology mediated the effects of age and APOE genotype on dementia severity. An older age at death and more ɛ2 alleles were associated with less AD pathology and, in turn, with less severe dementia. In contrast, more ɛ4 alleles were associated with more pathology and more severe dementia. Although age and race contributed to differences in CVD pathology, CVD pathology was not related to dementia severity in this sample of decedents with pathologically-confirmed AD. CONCLUSIONS: Using δ as an estimate of dementia severity fits well within a structural model in which AD pathology directly affects dementia severity and mediates the relationship between age and APOE genotype on dementia severity.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Apolipoproteins E; Cerebrovascular Disorders; Continental Population Groups; Dementia; Educational Status; Female; Genotype; Humans; Male; Mental Status Schedule; Middle Aged; Models, Theoretical

The Role of Ethnicity in Alzheimer's Disease: Findings From The C-PATH Online Data Repository. - Chen, Huei-Yang; Panegyres, Peter K (J Alzheimers Dis, 2016)
BACKGROUND: Ethnic minorities seem to be at an increased risk of Alzheimer's disease (AD). However, little is known about ethnic differences and the risks of early onset AD (EOAD). OBJECTIVE: Cognitive function changes over time and odds of EOAD by ethnicity were analyzed by the mixed model and the logistic regression. METHODS: Information on demographics, self-reported co-morbidities, cognitive functions (MMSE and ADAS-COG), and ApoE genotypes were collected for 6,500 subjects with AD obtained from the placebo arm of clinical trials; this data was examined by ethnicities: Caucasian, Asian, African American, Hispanic, and other minorities--including Native Alaskans, Americans, and Hawaiians. RESULTS: Of the total subjects, Caucasians accounted for 89.0% , followed by 4.7% Asians, 2.7% African Americans, 2.4% Hispanics, and 1.2% Native Americans, Alaskans, and Hawaiians. Age, gender, EOAD status, co-morbidities, family history of AD, and ApoE genotypes were significantly different by ethnicity. ApoE ɛ2 allele is possibly overrepresented in the Native Americans, Africans, Hawaiians, and African Americans. A significant interaction with time, ethnicity, and cognitive performance was found, indicating more cognitive deterioration in other minorities than Caucasians for mini-mental state (p <  0.01). After adjusting for co-morbidities and gender, the odds of EOAD among African Americans (OR: 1.6, 95% CI: 1.1-2.4) and Native Alaskans, Americans, and Hispanics (OR: 2.1, 95% CI: 1.2-3.5) were significantly higher, compared with Caucasians. CONCLUSIONS: Ethnicity may impact AD through age of onset, co-morbidities, family history, ApoE gene status, and cognitive change over time. The greater odds of EOAD among African Americans, Alaskans, and Hawaiians suggest that some ethnicities may be at risk of AD at a younger age.
Keywords: African Americans; Age Factors; Aged; Alaska Natives; Alzheimer Disease; Apolipoproteins E; Asian Continental Ancestry Group; Clinical Trials as Topic; Comorbidity; Databases, Factual; European Continental Ancestry Group; Female; Hispanic Americans; Humans; Indians, North American; Internet; Logistic Models; Male; Oceanic Ancestry Group; Risk; Sex Factors

Safety and Efficacy of Medical Cannabis Oil for Behavioral and Psychological Symptoms of Dementia: An-Open Label, Add-On, Pilot Study. - Shelef, Assaf; Barak, Yoram; Berger, Uri; Paleacu, Diana; Tadger, Shelly; Plopsky, Igor; Baruch, Yehuda (J Alzheimers Dis, 2016)
BACKGROUND: Tetrahydrocannabinol (THC) is a potential treatment for Alzheimer's disease (AD). OBJECTIVE: To measure efficacy and safety of medical cannabis oil (MCO) containing THC as an add-on to pharmacotherapy, in relieving behavioral and psychological symptoms of dementia (BPSD). METHODS: Eleven AD patients were recruited to an open label, 4 weeks, prospective trial. RESULTS: Ten patients completed the trial. Significant reduction in CGI severity score (6.5 to 5.7; p <  0.01) and NPI score were recorded (44.4 to 12.8; p <  0.01). NPI domains of significant decrease were: Delusions, agitation/aggression, irritability, apathy, sleep and caregiver distress. CONCLUSION: Adding MCO to AD patients' pharmacotherapy is safe and a promising treatment option.
Keywords: Aged; Aged, 80 and over; Antipsychotic Agents; Behavioral Symptoms; Cognition Disorders; Dementia; Female; Humans; Male; Medical Marijuana; Neuropsychological Tests; Outcome Assessment (Health Care); Physical Examination; Pilot Projects; Prospective Studies; Psychiatric Status Rating Scales

Safety and Tolerability of R(+) Pramipexole in Mild-to-Moderate Alzheimer's Disease. - Bennett, James; Burns, Jeffrey; Welch, Paul; Bothwell, Rebecca (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is an aging-related, degenerative brain disease of adults. Most (∼95%) of AD occurs sporadically and is associated with early-appearing deficits in brain regional glucose uptake, changes in cerebrospinal fluid (CSF) AD-related proteins, regional brain atrophy, and oxidative stress damage. We treated mild-moderate AD individuals with R(+)-pramipexole-dihydrochloride (R(+)PPX), a neuroprotective, lipophilic-cation, free-radical scavenger that accumulates into brain and mitochondria. 19 subjects took R(+)PPX twice a day in increasing daily doses up to 300 mg/day under a physician-sponsor IND (60,948, JPB), IRB-approved protocol and quarterly external safety committee monitoring. 15 persons finished and contributed baseline and post-treatment serum, lumbar spinal fluid, brain 18F-2DG PET scans, and ADAS-Cog scores. ADAS-Cog scores did not change (n = 1), improved (n = 2), declined 1-3 points (n = 5), or declined 4-13 points (n = 8) over 6 months of R(+)PPX treatment. Serum PPX levels were not related to changes in ADAS-Cog scores. Fasting AM serum PPX levels at 6 months varied considerably across subjects and correlated strongly with CSF [PPX] (r = 0.97, p <  0.0001). CSF [PPX] was not related to CSF [Aβ(42)], [Tau], or [P-Tau]. Regional 18F-2DG measures of brain glucose uptake demonstrated a 3-6% decline during R(+)PPX treatment. 56 mild-moderate adverse events occurred, 26 probably/definitely related to R(+)PPX use, with 4 withdrawals. R(+)PPX was generally well-tolerated and entered brain extracellular space linearly. Further studies of R(+)PPX in AD should include a detailed pharmacokinetic study of peak and trough serum [PPX] variations among subjects prior to planning any larger studies that would be needed to determine efficacy in altering disease progression.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Benzothiazoles; Biomarkers; Brain; Female; Glucose; Humans; Male; Neuropsychological Tests; Nootropic Agents; Peptide Fragments; Positron-Emission Tomography; Severity of Illness Index; tau Proteins; Treatment Outcome

Salidroside, a Bioactive Compound of Rhodiola Rosea, Ameliorates Memory and Emotional Behavior in Adult Mice. - Palmeri, Agostino; Mammana, Leonardo; Tropea, Maria Rosaria; Gulisano, Walter; Puzzo, Daniela (J Alzheimers Dis, 2016)
Rhodiola Rosea (R. Rosea) is a plant used in traditional popular medicine to enhance cognition and physical performance. R. Rosea medicinal properties have been related to its capability to act as an adaptogen, i.e., a substance able to increase the organism's resistance to a variety of chemical, biological, and physical stressors in a non-specific way. These adaptogen properties have been mainly attributed to the glycoside salidroside, one of the bioactive compounds present in the standardized extracts of R. Rosea. Here, we aimed to investigate whether a single dose of salidroside is able to affect memory and emotional behavior in wild type adult mice. We performed fear conditioning to assess cued and contextual memory, elevated plus maze and open field to evaluate anxiety, and tail suspension test to evaluate depression. Our results showed that a single i.p. administration of salidroside was able to enhance fear memory and exerted an anxiolytic and antidepressant effect. These data confirmed the adaptogenic effect of R. Rosea bioactive compounds in animal models and suggest that salidroside might represent an interesting pharmacological tool to ameliorate cognition and counteract mood disorders.
Keywords: Animals; Anti-Anxiety Agents; Antidepressive Agents; Anxiety Disorders; Conditioning (Psychology); Depressive Disorder; Disease Models, Animal; Drug Evaluation, Preclinical; Exploratory Behavior; Fear; Female; Freezing Reaction, Cataleptic; Glucosides; Male; Maze Learning; Memory; Mice, Inbred C57BL; Motor Activity; Nootropic Agents; Phenols; Phytotherapy; Plant Extracts; Rhodiola

Screening for Mild Cognitive Impairment: Comparison of "MCI Specific" Screening Instruments. - O'Caoimh, Rónán; Timmons, Suzanne; Molloy, D William (J Alzheimers Dis, 2016)
BACKGROUND: Sensitive and specific instruments are required to screen for cognitive impairment (CI) in busy clinical practice. The Montreal Cognitive Assessment (MoCA) is widely validated but few studies compare it to tests designed specifically to detect mild cognitive impairment (MCI). OBJECTIVE: Comparison of two "MCI specific" screens: the Quick Mild Cognitive Impairment screen (Qmci) and MoCA. METHODS: Patients with subjective memory complaints (SMC; n = 73), MCI (n = 103), or dementia (n = 274), were referred to a university hospital memory clinic and underwent comprehensive assessment. Caregivers, without cognitive symptoms, were recruited as normal controls (n = 101). RESULTS: The Qmci was more accurate than the MoCA in differentiating MCI from controls, area under the curve (AUC) of 0.90 versus 0.80, p = 0.009. The Qmci had greater (AUC 0.81), albeit non-significant, accuracy than the MoCA (AUC 0.73) in separating MCI from SMC, p = 0.09. At its recommended cut-off (<62/100), the Qmci had a sensitivity of 90% and specificity of 87% for CI (MCI/dementia). Raising the cut-off to <65 optimized sensitivity (94%), reducing specificity (80%). At <26/30 the MoCA had better sensitivity (96%) but poor specificity (58%). A MoCA cut-off of <24 provided the optimal balance. Median Qmci administration time was 4.5 (±1.3) minutes compared with 9.5 (±2.8) for the MoCA. CONCLUSIONS: Although both tests distinguish MCI from dementia, the Qmci is particularly accurate in separating MCI from normal cognition and has shorter administration times, suggesting it is more useful in busy hospital clinics. This study reaffirms the high sensitivity of the MoCA but suggests a lower cut-off (<24) in this setting.
Keywords: Aged; Aged, 80 and over; Area Under Curve; Cognitive Dysfunction; Dementia; Diagnosis, Differential; Female; Humans; Male; Neuropsychological Tests; Perception; ROC Curve; Sensitivity and Specificity; Time Factors

Self-Consciousness in Patients with Behavioral Variant Frontotemporal Dementia. - Arroyo-Anlló, Eva M; Bouston, Adèle Turpin; Fargeau, Marie-Noëlle; Orgaz Baz, Begõna; Gil, Roger (J Alzheimers Dis, 2016)
Self-consciousness (SC) is multifaceted and considered to be the consciousness of one's own mental states. The medial prefrontal cortex may play a critical role in SC. The main aim of this paper was to examine SC in patients with behavioral variant frontotemporal dementia, who are characterized more by changes in personal, social, and emotional conduct and loss of insight than by cognitive disturbances. Control and patient groups of 21 subjects each, matched by age, educational level, gender, and nationality were assessed using a SC questionnaire. It measures several aspects: Personal identity, Anosognosia, Affective state, Body representation, Prospective memory, Introspection, and Moral judgments. The most disturbed ones in patients were Anosognosia, Affective state, and Moral judgments, and the least disturbed aspects were awareness of identity and of body representation. No significant correlations were found between the SC score and any clinical or demographical characteristics. The core deficiency of SC in patients was related to behavioral SC aspects, which are more dependent on orbito-frontal functioning.
Keywords: Aged; Brain; Educational Status; Female; Frontotemporal Dementia; Humans; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Positron-Emission Tomography; Psychological Tests; Self Concept

Self-Reported Traumatic Brain Injury and Mild Cognitive Impairment: Increased Risk and Earlier Age of Diagnosis. - LoBue, Christian; Denney, David; Hynan, Linda S; Rossetti, Heidi C; Lacritz, Laura H; Hart, John; Womack, Kyle B; Woon, Fu L; Cullum, C Munro (J Alzheimers Dis, 2016)
This study examined whether history of traumatic brain injury (TBI) is associated with increased risk and earlier onset of mild cognitive impairment (MCI). Subjects with MCI (n = 3,187) and normal cognition (n = 3,244) were obtained from the National Alzheimer's Coordinating Center database. TBI was categorized based on lifetime reported TBI with loss of consciousness (LOC) without chronic deficit. Logistic regression was used to examine TBI history as a predictor of MCI, adjusted for demographics, apolipoprotein E-ɛ4 (ApoE4), a composite vascular risk score, and history of psychiatric factors. ANCOVA was used to examine whether age at MCI diagnosis and estimated age of onset differed between those with (TBI+) and without (TBI-) a history of TBI. TBI history was a significant predictor (p <  0.01) and associated with increased odds of MCI diagnosis in unadjusted (OR = 1.25; 95% CI = 1.05-1.49) and adjusted models, accounting for age, education, ApoE4, and a composite vascular score (OR = 1.32; 95% CI = 1.10-1.58). This association, however, was largely attenuated (OR = 1.14; 95% CI = 0.94-1.37; p = 0.18) after adjustment for reported history of depression. MCI was diagnosed a mean of 2.3 years earlier (p <  0.001) in the TBI+ group, and although TBI+ subjects had an estimated mean of decline 1.7 years earlier, clinician-estimated age of onset failed to differ (p = 0.13) when gender and psychiatric factors were controlled. This is the first report of a possible role for TBI as a risk factor in MCI, but its association may be related to other factors such as gender and depression and requires further investigation.
Keywords: Age of Onset; Aged; Apolipoproteins E; Brain Injuries, Traumatic; Cognitive Dysfunction; Cohort Studies; Databases, Factual; Depression; Educational Status; Female; Humans; Logistic Models; Male; Risk Factors; Self Report; United States

Sensitivity of Neuropsychological Tests to Identify Cognitive Decline in Highly Educated Elderly Individuals: 12 Months Follow up. - Elkana, Odelia; Eisikovits, Osnat Reichman; Oren, Noga; Betzale, Vered; Giladi, Nir; Ash, Elissa L (J Alzheimers Dis, 2016)
Highly educated individuals have a lower risk of developing dementia and Alzheimer's disease (AD). A common assumption is that their "cognitive reserve" protects them from cognitive decline and postpones the clinical manifestation of dementia. These highly educated individuals usually obtain normal scores on cognitive screening tests, although at the same time they can experience subjective cognitive decline and difficulty in multiple cognitive domains. Although comprehensive neuropsychological evaluations usually identify subtle changes in cognition, they demand extensive resources and thus are expensive and difficult to obtain. Therefore, lack of sensitivity of screening tests on the one hand, along with difficulty to acquire a comprehensive neuropsychological evaluation on the other hand, impede identification of cognitive decline at its earliest stages in this special population. Accordingly, this study aims to identify which neuropsychological tests have the highest sensitivity to detect the earliest stages of cognitive decline among highly educated elderly [n = 27, ages 66-80 (mean = 72.6 SD = 4.54), mean education level = 17.14 (SD = 3.21 range: 12-24 years)]. Baseline scores and scores at one-year follow up were obtained. We also conducted MRI scans to characterize the relation between brain volume and cognitive performance. Results show significant reductions in RVALT, Semantic verbal Fluency, ROCF copy, and MoCA scores whereas PF, TMT, ROCF delay, digit span, and knowledge tests were not significant. The study stresses the importance of using sensitive neuropsychological tests to examine this special population and the need to create norms that combine an individual's education with age.
Keywords: Aged; Aged, 80 and over; Aging; Brain; Cognition Disorders; Educational Status; Female; Follow-Up Studies; Humans; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Sensitivity and Specificity; Statistics as Topic

Shared Genetic Etiology between Type 2 Diabetes and Alzheimer's Disease Identified by Bioinformatics Analysis. - Gao, Lei; Cui, Zhen; Shen, Liang; Ji, Hong-Fang (J Alzheimers Dis, 2016)
Type 2 diabetes (T2D) and Alzheimer's disease (AD) are two major health issues, and increasing evidence in recent years supports the close connection between these two diseases. The present study aimed to explore the shared genetic etiology underlying T2D and AD based on the available genome wide association studies (GWAS) data collected through August 2014. We performed bioinformatics analyses based on GWAS data of T2D and AD on single nucleotide polymorphisms (SNPs), gene, and pathway levels, respectively. Six SNPs (rs111789331, rs12721046, rs12721051, rs4420638, rs56131196, and rs66626994) were identified for the first time to be shared genetic factors between T2D and AD. Further functional enrichment analysis found lipid metabolism related pathways to be common between these two disorders. The findings may have important implications for future mechanistic and interventional studies for T2D and AD.
Keywords: Alzheimer Disease; Apolipoprotein C-I; Computational Biology; Databases, Factual; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lipid Metabolism; Male; Polymorphism, Single Nucleotide

Social Cognition Deficits: The Key to Discriminate Behavioral Variant Frontotemporal Dementia from Alzheimer's Disease Regardless of Amnesia? - Bertoux, Maxime; de Souza, Leonardo Cruz; O'Callaghan, Claire; Greve, Andrea; Sarazin, Marie; Dubois, Bruno; Hornberger, Michael (J Alzheimers Dis, 2016)
Relative sparing of episodic memory is a diagnostic criterion of behavioral variant frontotemporal dementia (bvFTD). However, increasing evidence suggests that bvFTD patients can show episodic memory deficits at a similar level as Alzheimer's disease (AD). Social cognition tasks have been proposed to distinguish bvFTD, but no study to date has explored the utility of such tasks for the diagnosis of amnestic bvFTD. Here, we contrasted social cognition performance of amnestic and non-amnestic bvFTD from AD, with a subgroup having confirmed in vivo pathology markers. Ninety-six participants (38 bvFTD and 28 AD patients as well as 30 controls) performed the short Social-cognition and Emotional Assessment (mini-SEA). BvFTD patients were divided into amnestic versus non-amnestic presentation using the validated Free and Cued Selective Reminding Test (FCSRT) assessing episodic memory. As expected, the accuracy of the FCSRT to distinguish the overall bvFTD group from AD was low (69.7% ) with ∼50% of bvFTD patients being amnestic. By contrast, the diagnostic accuracy of the mini-SEA was high (87.9% ). When bvFTD patients were split on the level of amnesia, mini-SEA diagnostic accuracy remained high (85.1% ) for amnestic bvFTD versus AD and increased to very high (93.9% ) for non-amnestic bvFTD versus AD. Social cognition deficits can distinguish bvFTD and AD regardless of amnesia to a high degree and provide a simple way to distinguish both diseases at presentation. These findings have clear implications for the diagnostic criteria of bvFTD. They suggest that the emphasis should be on social cognition deficits with episodic memory deficits not being a helpful diagnostic criterion in bvFTD.
Keywords: Aged; Alzheimer Disease; Amnesia; Cognition; Diagnosis, Differential; Emotions; Female; Frontotemporal Dementia; Humans; Male; Memory, Episodic; Neuropsychological Tests; Social Perception

The Societal Cost of Dementia in Singapore: Results from the WiSE Study. - Abdin, Edimansyah; Subramaniam, Mythily; Achilla, Evanthia; Chong, Siow Ann; Vaingankar, Janhavi Ajit; Picco, Louisa; Sambasivam, Rajeswari; Pang, Shirlene; Chua, Boon Yiang; Ng, Li Ling; Chua, Hong Choon; Heng, Derrick; et al. (J Alzheimers Dis, 2016)
BACKGROUND: There is currently limited evidence on the economic burden that dementia exerts on multi-ethnic Asian populations. OBJECTIVE: The present study aimed to estimate the economic cost of dementia in Singapore. METHODS: We used data from the Well-being of the Singapore Elderly study, a nationally representative survey of the older Singapore Resident population aged 60 years and above. Generalized linear modeling was used to estimate factors associated with costs. RESULTS: The total cost of dementia in 2013 was estimated at S$532 million (95% CI, S$361 million to S$701 million) while the annual cost per person was estimated at S$10,245 per year (95% CI, S$6,954 to S$12,495). Apart from dementia, higher total societal cost were also significantly associated with older age, Indian ethnicity, and those who were diagnosed with heart problems, stroke, diabetes or depression, whereas being divorced/separated, lower education, and those who were diagnosed with hypertension were significantly associated with lower total societal cost. CONCLUSION: The study provides a rich body of information on healthcare utilization and cost of dementia, which is essential for future planning of services for the elderly population.
Keywords: Adult; Aged, 80 and over; Cost of Illness; Dementia; Female; Humans; Linear Models; Male; Middle Aged; Singapore

Spatial Navigation in Preclinical Alzheimer's Disease. - Allison, Samantha L; Fagan, Anne M; Morris, John C; Head, Denise (J Alzheimers Dis, 2016)
Although several previous studies have demonstrated navigational deficits in early-stage symptomatic Alzheimer's disease (AD), navigational abilities in preclinical AD have not been examined. The present investigation examined the effects of preclinical AD and early-stage symptomatic AD on spatial navigation performance. Performance on tasks of wayfinding and route learning in a virtual reality environment were examined. Comparisons were made across the following three groups: Clinically normal without preclinical AD (n = 42), clinically normal with preclinical AD (n = 13), and early-stage symptomatic AD (n = 16) groups. Preclinical AD was defined based on cerebrospinal fluid Aβ42 levels below 500 pg/ml. Preclinical AD was associated with deficits in the use of a wayfinding strategy, but not a route learning strategy. Moreover, post-hoc analyses indicated that wayfinding performance had moderate sensitivity and specificity. Results also confirmed early-stage symptomatic AD-related deficits in the use of both wayfinding and route learning strategies. The results of this study suggest that aspects of spatial navigation may be particularly sensitive at detecting the earliest cognitive deficits of AD.
Keywords: Aged; Alzheimer Disease; Biomarkers; Educational Status; Female; Humans; Learning; Male; Neuropsychological Tests; Prodromal Symptoms; Psychomotor Performance; ROC Curve; Spatial Navigation; tau Proteins; User-Computer Interface

Specific Features of Subjective Cognitive Decline Predict Faster Conversion to Mild Cognitive Impairment. - Fernández-Blázquez, Miguel A; Ávila-Villanueva, Marina; Maestú, Fernando; Medina, Miguel (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) is a silent disorder that needs the earliest possible intervention in order to reduce its high economic and social impact. It has been recently suggested that subjective cognitive decline (SCD) appears at preclinical stages many years before the onset of AD. Therefore, SCD could become an ideal target for early therapeutic intervention. OBJECTIVE: The goal of this study was to evaluate the clinical significance of SCD on the conversion from a cognitively healthy stage to a mild cognitive impairment (MCI) in one-year follow-up. METHODS: A total of 608 cognitively intact individuals from the Vallecas Project's cohort, a community-based prospective study to identify early markers of AD, were enrolled in this study. Participants were classified in three groups: i) No Complaints (NCg), ii) Subjects with complaints in one or more cognitive domains (SCDg), and iii) Subjects who, besides complaints, fulfilled the features of SCD Plus proposed by the International Working Group of SCD (SCD-Pg). RESULTS: Individuals were followed up for a mean of 13.1 months (range 10.7-22.4). During this time, 41 volunteers developed MCI (6.7% of total sample). The conversion rate for SCD-Pg (18.9%) was significantly higher than SCDg (5.6%) and NCg (4.9%). CONCLUSION: Specific features associated with SCD may help to identify individuals at high risk of fast conversion to MCI. These results highlight the importance of a close follow-up of subjects with SCD-P and include them in early intervention programs because of their increased risk for the development of MCI.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Genotyping Techniques; Humans; Kaplan-Meier Estimate; Male; Neuropsychological Tests; Perception; Prodromal Symptoms; Prognosis; Prospective Studies; Time Factors

Strategies for improving memory: a randomized trial of memory groups for older people, including those with mild cognitive impairment. - Kinsella, Glynda J; Ames, David; Storey, Elsdon; Ong, Ben; Pike, Kerryn E; Saling, Michael M; Clare, Linda; Mullaly, Elizabeth; Rand, Elizabeth (J Alzheimers Dis, 2016)
BACKGROUND: Governments are promoting the importance of maintaining cognitive health into older age to minimize risk of cognitive decline and dementia. Older people with amnestic mild cognitive impairment (aMCI) are particularly vulnerable to memory challenges in daily activities and are seeking ways to maintain independent living. OBJECTIVE: To evaluate the effectiveness of memory groups for improving memory strategies and memory ability of older people, especially those with aMCI. METHODS: 113 healthy older adults (HOA) and 106 adults with aMCI were randomized to a six-week memory group or a waitlist control condition. Outcome was evaluated through knowledge and use of memory strategies, memory ability (self-report and neuropsychological tests), and wellbeing. Assessments included a six-month follow-up. RESULTS: Using intention to treat analyses, there were intervention effects for HOA and aMCI groups in strategy knowledge (HOA: η2= 0.20; aMCI: η2= 0.06), strategy use (HOA: η2= 0.18; aMCI: η2= 0.08), and wellbeing (HOA: η2= 0.11; aMCI: η2= 0.05). There were also intervention effects in the HOA group, but not the aMCI group, in self-reported memory ability (η2= 0.06) and prospective memory tests (η2= 0.02). By six-month follow-up, gains were found on most HOA outcomes. In the aMCI group gains were found in strategy use, and by this stage, gains in prospective memory were also found. CONCLUSION: Memory groups can engage older people in techniques for maintaining cognitive health and improve memory performance, but more modest benefits are seen for older adults with aMCI.
Keywords: Aged; Aged, 80 and over; Aging; Cognitive Dysfunction; Cross-Over Studies; Female; Humans; Male; Memory, Episodic; Neuropsychological Tests; Self Report

Subjective Memory Complaints in APOEɛ4 Carriers are Associated with High Amyloid-β Burden. - Zwan, Marissa D; Villemagne, Victor L; Doré, Vincent; Buckley, Rachel; Bourgeat, Pierrick; Veljanoski, Robyn; Salvado, Olivier; Williams, Rob; Margison, Laura; Rembach, Alan; Macaulay, S Lance; Martins, Ralph; et al. (J Alzheimers Dis, 2016)
BACKGROUND: APOEɛ4 genotype and aging have been identified as risk factors for Alzheimer's disease (AD). In addition, subjective memory complaints (SMC) might be a first clinical expression of the effect of AD pathology on cognitive functioning. OBJECTIVE: To assess whether APOEɛ4 genotype, age, SMC, and episodic memory are risk factors for high amyloid-β (Aβ) burden in cognitively normal elderly. METHODS: 307 cognitively normal participants (72.7 ± 6.8 years, 53% female, 55% SMC) from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study underwent amyloid PET and APOE genotyping. Logistic regression analyses were performed to determine the association of APOEɛ4 genotype, age, SMC, and episodic memory with Aβ pathology. RESULTS: Odds of high Aβ burden were greater at an older age (OR = 3.21; 95% CI = 1.68-6.14), when SMC were present (OR = 1.90; 95% CI = 1.03-3.48), and for APOEɛ4 carriers (OR = 7.49; 95% CI = 3.96-14.15), while episodic memory was not associated with odds of high Aβ burden. Stratified analyses showed that odds of SMC for high Aβ burden were increased in specifically APOEɛ4 carriers (OR = 4.58, 95% CI = 1.83-11.49) and younger participants (OR = 3.73, 95% CI = 1.39-10.01). CONCLUSION: Aging, APOEɛ4 genotype, and SMC were associated with high Aβ burden. SMC were especially indicative of high Aβ burden in younger participants and in APOEɛ4 carriers. These findings suggest that selection based on the presence of SMC, APOEɛ4 genotype and age may help identify healthy elderly participants with high Aβ burden eligible for secondary prevention trials.
Keywords: Aged; Aging; Amyloid beta-Peptides; Aniline Compounds; Apolipoprotein E4; Benzothiazoles; Brain; Cognition Disorders; Female; Genotyping Techniques; Heterozygote; Humans; Logistic Models; Male; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Thiazoles

Tau Accumulation in Primary Motor Cortex of Variant Alzheimer's Disease with Spastic Paraparesis. - Lyoo, Chul Hyoung; Cho, Hanna; Choi, Jae Yong; Hwang, Mi Song; Hong, Sang Kyoon; Kim, Yun Joong; Ryu, Young Hoon; Lee, Myung Sik (J Alzheimers Dis, 2016)
We studied topographic distribution of tau and amyloid-β in a patient with variant Alzheimer's disease with spastic paraparesis (VarAD) by comparing AD patients. The proband developed progressive memory impairment, dysarthria, and spastic paraparesis at age 23. Heterozygous missense mutation (L166P) was found in exon 6 of presenilin-1 gene. The proband showed prominently increased amyloid binding in striatum and cerebellum and asymmetrical tau binding in the primary sensorimotor cortex contralateral to the side more affected by spasticity. We suspect that upper motor neuron dysfunctions may be attributed to excessive abnormal tau accumulation rather than amyloid-β in the primary motor cortex.
Keywords: Adult; Aged; Alzheimer Disease; Aniline Compounds; Brain Mapping; Carbolines; Female; Humans; Male; Motor Cortex; Mutation, Missense; Paraparesis, Spastic; Positron-Emission Tomography; Presenilin-1; Radiopharmaceuticals; Stilbenes; tau Proteins

A TgCRND8 Mouse Model of Alzheimer's Disease Exhibits Sexual Dimorphisms in Behavioral Indices of Cognitive Reserve. - Granger, Matthew W; Franko, Bettina; Taylor, Matthew W; Messier, Claude; George-Hyslop, Peter St; Bennett, Steffany A L (J Alzheimers Dis, 2016)
Cognitive decline is sexually dimorphic in Alzheimer's disease (AD). Men show higher incidences of amnestic mild cognitive impairment yet women disproportionally phenoconvert to AD. It is hypothesized that men maintain greater cognitive reserve than women under comparable amyloid-β (Aβ) challenge. One behavioral aspect of cognitive reserve in mice is the capacity to cope with Aβ-associated stereotypies by switching to increasingly effective navigational search strategies in the Morris water maze. To explore inherent sex differences in this paradigm, however, we require an AβPP mouse model wherein behavioral flexibility is impaired earlier in females than males despite equivalent Aβ load. Here, we show that when F1 C57Bl/6×C3H/HeJ TgCRND8 mice are placed on C57Bl/6 background, N5 Tg males and females exhibit equivalent Aβ pathologies at 2, 4, 6, and 8 months of age yet females display learning and memory deficits earlier than males. We further show that this N5 line does not carry the autosomal recessive pde6brd1 mutation that impairs visual acuity and that the estrous cycle is not disrupted on this genetic background. At 5.5 months of age, Tg males, but not females, compensate for Aβ-associated stereotypic behaviors (i.e., hyperactive tight circling) by alternating navigational search strategies and adopting increasingly productive spatial search strategies. Females fail to overcome Aβ-associated stereotypies and do not efficiently switch from systematic to spatial learning strategies. Together, these data identify a novel AβPP mouse model that can be used for preclinical testing of interventions targeting sexual dimorphisms in behavioral indices of cognitive reserve.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognitive Reserve; Cyclic Nucleotide Phosphodiesterases, Type 6; Disease Models, Animal; Female; Humans; Male; Maze Learning; Mice, Inbred C3H; Mice, Inbred C57BL; Mice, Transgenic; Plaque, Amyloid; Psychomotor Performance; Sex Characteristics; Spatial Memory; Spatial Navigation; Survival Analysis

Three-Dimensional Eigenbrain for the Detection of Subjects and Brain Regions Related with Alzheimer's Disease. - Zhang, Yudong; Wang, Shuihua; Phillips, Preetha; Yang, Jiquan; Yuan, Ti-Fei (J Alzheimers Dis, 2016)
BACKGROUND: Considering that Alzheimer's disease (AD) is untreatable, early diagnosis of AD from the healthy elderly controls (HC) is pivotal. However, computer-aided diagnosis (CAD) systems were not widely used due to its poor performance. OBJECTIVE: Inspired from the eigenface approach for face recognition problems, we proposed an eigenbrain to detect AD brains. Eigenface is only for 2D image processing and is not suitable for volumetric image processing since faces are usually obtained as 2D images. METHODS: We extended the eigenbrain to 3D. This 3D eigenbrain (3D-EB) inherits the fundamental strategies in either eigenface or 2D eigenbrain (2D-EB). All the 3D brains were transferred to a feature space, which encoded the variation among known 3D brain images. The feature space was named as the 3D-EB, and defined as eigenvectors on the set of 3D brains. We compared four different classifiers: feed-forward neural network, support vector machine (SVM) with linear kernel, polynomial (Pol) kernel, and radial basis function kernel. RESULTS: The 50x10-fold stratified cross validation experiments showed that the proposed 3D-EB is better than the 2D-EB. SVM with Pol kernel performed the best among all classifiers. Our "3D-EB + Pol-SVM" achieved an accuracy of 92.81% ± 1.99% , a sensitivity of 92.07% ± 2.48% , a specificity of 93.02% ± 2.22% , and a precision of 79.03% ± 2.37% . Based on the most important 3D-EB U1, we detected 34 brain regions related with AD. The results corresponded to recent literature. CONCLUSIONS: We validated the effectiveness of the proposed 3D-EB by detecting subjects and brain regions related to AD.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alzheimer Disease; Brain; Datasets as Topic; Early Diagnosis; Female; Humans; Image Interpretation, Computer-Assisted; Imaging, Three-Dimensional; Magnetic Resonance Imaging; Male; Middle Aged; Sensitivity and Specificity; Young Adult

Thyroid-Stimulating Hormone and Mild Cognitive Impairment: Results of the Heinz Nixdorf Recall Study. - Winkler, Angela; Weimar, Christian; Jöckel, Karl-Heinz; Erbel, Raimund; Dragano, Nico; Broecker-Preuss, Martina; Moebus, Susanne; Führer-Sakel, Dagmar; Dlugaj, Martha (J Alzheimers Dis, 2016)
BACKGROUND: Although some studies reported on the association of serum thyroid-stimulating hormone (TSH) concentration and cognition, only one population-based study investigated the association of TSH concentration and mild cognitive impairment (MCI). OBJECTIVE: To investigate the gender-specific association of low- and high-normal TSH concentrations with MCI in euthyroid participants. METHODS: Analysis sample 1 included 2,563 euthyroid participants (aged 50-80 years) from the second examination of the population-based Heinz Nixdorf Recall study. Gender-specific TSH quintiles (Q1 low, Q2-Q4 middle, Q5 high TSH concentration) were determined and group comparisons of age- and education-adjusted mean scores were performed for all cognitive subtests. Analysis sample 2 included 378 participants with MCI and 931 cognitively normal participants. MCI was diagnosed according to previously published MCI criteria. Multivariate logistic regression models were performed using TSH quintiles (Q2-Q4 as reference) to assess the association of low- and high-normal TSH concentration with MCI. Models were performed unadjusted and adjusted for sociodemographic and cardiovascular risk factors. RESULTS: Group comparisons showed significant differences only in the immediate recall of the verbal memory task in women. Only women showed a strong association of high-normal TSH concentration with MCI (unadjusted: odds ratio 2.09, 95% confidence interval 1.29-3.37, full adjusted: 1.86, 1.06-3.27). There was no association with low-normal TSH concentration in women and no association of either low- or high-normal TSH concentration with MCI in men. CONCLUSIONS: These results suggest that women with high-normal TSH concentration might be at higher risk of cognitive decline. This needs to be confirmed in the longitudinal analysis.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Case-Control Studies; Cognitive Dysfunction; Female; Follow-Up Studies; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Risk Factors; Sex Characteristics; Statistics, Nonparametric; Thyrotropin

Time trends in antipsychotic drug use in patients with dementia: a nationwide study. - Nørgaard, Ane; Jensen-Dahm, Christina; Gasse, Christiane; Hansen, Hanne Vibe; Waldemar, Gunhild (J Alzheimers Dis, 2016)
BACKGROUND: Antipsychotics are often used to treat neuropsychiatric symptoms in dementia, but the evidence for effect is limited. Antipsychotics have been associated with increased risk of adverse events and mortality in patients with dementia, leading to safety regulations worldwide. OBJECTIVE: To investigate time trends in use of antipsychotics and other psychotropic drugs in dementia care. METHODS: The study included longitudinal data on all Danish residents ≥65 years. The study population was defined on January 1 of each year from 2000-2012. Data included prescriptions, discharge diagnoses, and somatic and psychiatric comorbidities. Multivariate time trend analyses of psychotropic drug use in patients with dementia within 4-year age bands were performed. RESULTS: Overall, among patients with dementia the prevalence of antipsychotic drug use decreased from 31.3% in 2000 to 20.4% in 2012. The decreasing use of antipsychotics was accompanied by decreasing use of anxiolytics and hypnotics/sedatives, but an increase in the use of antidepressants from 43.3% in 2000 to 53.8% in 2012. These changes were significant across almost all age groups. Treatment intensity among patients using antipsychotics increased as the annual median number of defined daily doses (DDD) increased from 33.3 to 42.0 DDD. CONCLUSIONS: The changing patterns of psychotropic drug use may be caused by warnings against use of antipsychotics. Further research is needed to explore the implications for patient safety.
Keywords: Aged; Aged, 80 and over; Anti-Anxiety Agents; Antidepressive Agents; Antipsychotic Agents; Dementia; Denmark; Drug Prescriptions; Female; Homes for the Aged; Humans; Hypnotics and Sedatives; Longitudinal Studies; Male; Multivariate Analysis; Nursing Homes; Registries

Tract-Specific Correlates of Neuropsychological Deficits in Patients with Subcortical Vascular Cognitive Impairment. - Jung, Na-Yeon; Han, Cheol E; Kim, Hee Jin; Yoo, Sang Wook; Kim, Hee-Jong; Kim, Eun-Joo; Na, Duk L; Lockhart, Samuel N; Jagust, William J; Seong, Joon-Kyung; Seo, Sang Won (J Alzheimers Dis, 2016)
The white matter tract-specific correlates of neuropsychological deficits are not fully established in patients with subcortical vascular cognitive impairment (SVCI), where white matter tract damage may be a critical factor in cognitive impairment. The purpose of this study is to investigate the tract-specific correlates of neuropsychological deficits in SVCI patients using tract-specific statistical analysis (TSSA). We prospectively recruited 114 SVCI patients, and 55 age-, gender-, and education-matched individuals with normal cognition (NC). All participants underwent diffusion weighted imaging and neuropsychological testing. We classified tractography results into fourteen major fiber tracts and analyzed group comparison and correlation with cognitive impairments. Relative to NC subjects, SVCI patients showed decreased fractional anisotropy values in bilateral anterior-thalamic radiation, cingulum, superior-longitudinal fasciculus, uncinate fasciculus, corticospinal tract, and left inferior-longitudinal fasciculus. Focal disruptions in specific tracts were associated with specific cognitive impairments. Our findings suggest that disconnection of specific white matter tracts, especially those neighboring and providing connections between gray matter regions important to certain cognitive functions, may contribute to specific cognitive impairments in SVCI.
Keywords: Aged; Brain; Cerebrovascular Disorders; Cognitive Dysfunction; Diffusion Magnetic Resonance Imaging; Diffusion Tensor Imaging; Female; Gray Matter; Humans; Male; Neural Pathways; Neuropsychological Tests; White Matter

Two Phase 2 Multiple Ascending-Dose Studies of Vanutide Cridificar (ACC-001) and QS-21 Adjuvant in Mild-to-Moderate Alzheimer's Disease. - Pasquier, Florence; Sadowsky, Carl; Holstein, Ann; Leterme, Ghislaine Le Prince; Peng, Yahong; Jackson, Nicholas; Fox, Nick C; Ketter, Nzeera; Liu, Enchi; Ryan, J Michael (J Alzheimers Dis, 2016)
Vanutide cridificar (ACC-001), an immunotherapeutic vaccine, is a potentially disease-modifying therapy that aims to reduce brain amyloid-β (Aβ) plaques in patients with Alzheimer's disease (AD). ACC-001 was evaluated in two phase 2a, multicenter, randomized, third party-unblinded, placebo-controlled, multiple ascending-dose studies of ACC-001 (3μg, 10μg, 30μg) with and without QS-21 adjuvant that enrolled patients with mild-to-moderate AD (n = 245). Patients were treated with up to five doses of study vaccine or placebo and followed for safety and tolerability (primary objective) and anti-Aβ IgG immunogenicity (secondary objective) up to 12 months after the last vaccination. Exploratory assessments included cognitive/functional measures, brain magnetic resonance imaging (MRI) volumetry, and pharmacodynamic markers in plasma and cerebrospinal fluid (CSF). The most frequent treatment-emergent adverse events (≥10%) were local injection reactions and headache. Amyloid-related imaging abnormalities with vasogenic edema occurred in two (0.8%) patients (ACC-001 30μg + QS-21; ACC-001 10μg). ACC-001 + QS-21 elicited consistently higher peak and sustained anti-Aβ IgG titers compared with ACC-001 alone. Plasma Aβx-40 was significantly higher in all ACC-001 + QS-21 groups versus placebo (weeks 16-56), with no evidence of dose response. Exploratory cognitive evaluations, volumetric brain MRI, and CSF biomarkers did not show differences or trends between treatment groups and placebo. ACC-001 with or without QS-21 adjuvant has an acceptable safety profile in patients with mild-to-moderate AD.
Keywords: Adjuvants, Immunologic; Aged; Alzheimer Disease; Amyloid beta-Peptides; Antipsychotic Agents; Dose-Response Relationship, Drug; Female; Follow-Up Studies; Humans; Interferon-gamma; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Recombinant Fusion Proteins; Saponins; Single-Blind Method; Treatment Outcome

Unmet Needs of Community-Dwelling Primary Care Patients with Dementia in Germany: Prevalence and Correlates. - Eichler, Tilly; Thyrian, Jochen René; Hertel, Johannes; Richter, Steffen; Wucherer, Diana; Michalowsky, Bernhard; Teipel, Stefan; Kilimann, Ingo; Dreier, Adina; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: To provide an optimal care for persons with dementia (PWD), their individual unmet needs have to be identified and comprehensively addressed. OBJECTIVES: Present analyses aim to describe the number and types of unmet needs of German primary care patients screened positive for dementia and factors associated with the number of unmet needs. METHODS: DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, cluster-randomized controlled intervention trial. Analyses are based on the baseline data of 227 PWD (≥70 years, living at home) of the intervention group who had screened positive for dementia (DemTect<9) and received a standardized computer-assisted needs assessment. RESULTS: PWD had on average 8.77±5.04 unmet needs (Range = 0-31). More than 90% of the PWD had three or more unmet needs. Unmet needs were identified across all predefined 26 subcategories. The majority of unmet needs occurred in the domains "nursing treatment and care" (38%), "social counseling and legal support" (20%), and "pharmacological treatment and care" (15%). More impairment in the activities of daily living was the only factor that was significantly associated with a higher number of unmet needs, independent of age, gender, living situation, presence of an informal caregiver, cognitive impairment, and depression. CONCLUSIONS: Present results demonstrate that community-dwelling PWD had a broad range of varying unmet needs. These findings emphasize the importance of a comprehensive needs assessment that allows the identification of individual needs as the basis for a tailored intervention- such as Dementia Care Management- that can address these needs.
Keywords: Aged, 80 and over; Caregivers; Cross-Sectional Studies; Dementia; Depression; Female; Germany; Health Services Needs and Demand; Humans; Male; Needs Assessment; Prevalence

Unstable Body Mass Index and Progression to Probable Alzheimer's Disease Dementia in Patients with Amnestic Mild Cognitive Impairment. - Ye, Byoung Seok; Jang, Eun Young; Kim, Seong Yoon; Kim, Eun-Joo; Park, Sun Ah; Lee, Yunhwan; Hong, Chang Hyung; Choi, Seong Hye; Yoon, Bora; Yoon, Soo Jin; Na, Hae Ri; Lee, Jae-Hong; et al. (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: We investigated the influence of body mass index (BMI) status at baseline and changes in BMI over a follow-up period on the development of dementia in amnestic mild cognitive impairment (aMCI) patients. METHODS: The longitudinal data of 747 aMCI patients were used to investigate the relationships among baseline BMI status, subsequent changes in BMI (median follow-up duration: 1.6 years, interquartile range: 1.0-2.3 years), and risk of progression to probable Alzheimer's disease dementia (pADD). The aMCI patients were classified into underweight, normal weight, overweight, and obese subgroups, and further categorized into increased BMI, stable BMI, and decreased BMI subgroups during follow-up using a 4% mean annual change in BMI cut-off value. RESULTS: Compared to the normal weight group, the underweight group had a higher risk of pADD (hazard ratio [HR]: 1.89, 95% confidence interval [CI]: 1.07-3.37) while the obese group had a lower risk (HR: 0.70, 95% CI: 0.49-0.999). After controllingfor baseline BMI status, the decreased BMI (HR: 2.29, 95% CI: 1.41-3.72) and increased BMI (HR: 3.96, 95% CI: 2.62-6.00) groups were at increased risk of progression to pADD. CONCLUSIONS: Our findings suggested that underweight at baseline was associated with a higher risk of progression to pADD, while obesity at baseline predicted a lower risk. Furthermore, significant changes in BMI during the follow-up period reflected an increased risk of progression to pADD, regardless of BMI status at baseline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Body Mass Index; Body Weight; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Kaplan-Meier Estimate; Longitudinal Studies; Male; Neuropsychological Tests; Registries

Usefulness of an Integrated Analysis of Different Memory Tasks to Predict the Progression from Mild Cognitive Impairment to Alzheimer's Disease: The Episodic Memory Score (EMS). - Marra, Camillo; Gainotti, Guido; Fadda, Lucia; Perri, Roberta; Lacidogna, Giordano; Scaricamazza, Eugenia; Piccininni, Chiara; Quaranta, Davide (J Alzheimers Dis, 2016)
Taking into the account both the severity and the consistency of performances obtained on memory tests by patients with amnestic mild cognitive impairment (aMCI) could improve the power to predict their progression to Alzheimer's disease. For this purpose, we constructed the Episodic Memory Score (EMS), which is obtained by subdividing in tertiles performances obtained at baseline in verbal (RAVLT) and visual episodic memory (Rey-Osterrieth Figure-delayed recall) and giving a score ranging from 1 (worst result) to 3 (best result) to results falling within each tertile. The EMS was computed for each patient by summing the tertile score obtained on each memory task, so that the total score ranged from 4 (worst performance) to 12 (best performance). The aMCI sample consisted of 198 subjects who completed the two-year follow-up, at the end of which 55 subjects had converted to dementia. The mean EMS score obtained by aMCI converters was significantly lower than that of aMCI-stable patients. In detecting conversion to dementia, the comparison between EMS and individual memory scores obtained at baseline was made by computing ROC curves, and estimating the respective area under the curve (AUC). The EMS had a larger AUC than the individual memory scores. At baseline aMCI converters performed worse than non-converters not only on memory tasks, but also on executive functions tasks. However, in a multiple variables logistic regression analysis in which all scores showing statistically significant differences between aMCI-converters and aMCI-stable were entered, the EMS was the only reliable predictor of progression from aMCI to dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Memory, Episodic; Mental Recall; Neuropsychological Tests; ROC Curve

The Utilization of Retinal Nerve Fiber Layer Thickness to Predict Cognitive Deterioration. - Shi, Zhongyong; Zhu, Yingbo; Wang, Meijuan; Wu, Yujie; Cao, Jing; Li, Chunbo; Xie, Zhongcong; Shen, Yuan (J Alzheimers Dis, 2016)
Our previous studies have shown that longitudinal reduction in retinal nerve fiber layer (RNFL) thickness is associated with cognitive deterioration. However, whether the combination of longitudinal reduction in RNFL thickness with baseline episodic memory performance can better predict cognitive deterioration remains unknown. Therefore, we set out to re-analyze the data obtained from our previous studies with 78 elderly adults (mean age 74.4 ± 3.83 years, 48.7% male) in the community over a 25-month period. The participants were categorized as either stable participants whose cognitive status did not change (n = 60) or converted participants whose cognitive status deteriorated (n = 18). A logistic regression analysis was applied to determine a conversion score for predicting the cognitive deterioration in the participants. We found that the area under the receiver operating characteristic curve (AUC) for the multivariable model was 0.854 (95% CI 0.762-0.947) using baseline story recall as a predictor, but the AUC increased to 0.915 (95% CI 0.849-0.981) with the addition of the longitudinal reduction of RNFL thickness in the inferior quadrant. The conversion score was significantly higher for the converted participants than the stable participants (0.59 ± 0.30 versus 0.12 ± 0.19, p <  0.001). Finally, the optimal cutoff value of the conversion score (0.134) was determined by the analysis of receiver operating characteristic curve, and this conversion score generated a sensitivity of 0.944 and a specificity of 0.767 in predicting the cognitive deterioration. These findings have established a system to perform a larger scale study to further test whether the longitudinal reduction in RNFL thickness could serve as a biomarker of Alzheimer's disease.
Keywords: Aged; Cognition Disorders; Female; Humans; Logistic Models; Longitudinal Studies; Male; Nerve Fibers; Neuropsychological Tests; Predictive Value of Tests; Retina; ROC Curve; Statistics, Nonparametric; Tomography, Optical Coherence

Validation of the Spanish version of the Baylor Profound Mental Status Examination. - Salmerón, Sergio; Huedo, Isabel; López-Utiel, Melisa; Soler-Moratalla, Isabel; Flores-Ruano, Teresa; Fernández-Sánchez, Miguel; Noguerón, Alicia; Doody, Rachelle S; Abizanda, Pedro (J Alzheimers Dis, 2016)
BACKGROUND: There are no short valid instruments to evaluate cognitive status in severe Alzheimer's disease (AD) patients in the Spanish language. OBJECTIVE: To validate the Spanish version of the Baylor Profound Mental Status Examination (BPMSE-Sp). METHODS: The Baylor Profound Mental Status Examination (BPMSE) was translated to Spanish and back translated. Validation was conducted in 100 patients with severe probable AD with a Mini-Mental State Examination (MMSE) <12. We assessed internal consistency (Cronbach's alpha), concurrent validity (Pearson's correlations) with the MMSE, Severe Impairment Battery (SIB), Neuropsychiatric Inventory Short Form (NPI-Q) and the Functional Assessment Staging and reliability. RESULTS: The mean age of patients was 84.9; 74% were female; 64% were institutionalized. The mean MMSE was 5.6; the mean BPMSE-Sp was 13.6; the mean BPMSE-Sp behavior was 1.2; the mean SIB was 42.2; and the mean NPI-Q was 4.7. BPMSE-Sp presented good internal consistency (Cronbach α= 0.84). There were significant correlations between the BPMSE-Sp and MMSE (r = 0.86, p <  0.001), and between the BPMSE-Sp and SIB (r = 0.92, p <  0.001). Inter-rater and test-retest reliability were in both cases excellent, ranging between 0.96 and 0.99 (p <  0.001). BPMSE-Sp had fewer floor and ceiling effects than the MMSE. CONCLUSIONS: The BPMSE-Sp is a valid tool for use in daily practice and research in the evaluation of cognitive function of patients with severe AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Cognition Disorders; Female; Humans; Language; Male; Mental Status Schedule; Neuropsychological Tests; Reproducibility of Results; Severity of Illness Index; Spain

The Vanderbilt Memory & Aging Project: Study Design and Baseline Cohort Overview. - Jefferson, Angela L; Gifford, Katherine A; Acosta, Lealani Mae Y; Bell, Susan P; Donahue, Manus J; Davis, L Taylor; Gottlieb, JoAnn; Gupta, Deepak K; Hohman, Timothy J; Lane, Elizabeth M; Libon, David J; Mendes, Lisa A; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Vascular health factors frequently co-occur with Alzheimer's disease (AD). A better understanding of how systemic vascular and cerebrovascular health intersects with clinical and pathological AD may inform prevention and treatment opportunities. OBJECTIVE: To establish the Vanderbilt Memory & Aging Project, a case-control longitudinal study investigating vascular health and brain aging, and describe baseline methodology and participant characteristics. METHODS: From September 2012 to November 2014, 335 participants age 60- 92 were enrolled, including 168 individuals with mild cognitive impairment (MCI, 73±8 years, 41% female) and 167 age-, sex-, and race-matched cognitively normal controls (NC, 72±7 years, 41% female). At baseline, participants completed a physical and frailty examination, fasting blood draw, neuropsychological assessment, echocardiogram, cardiac MRI, and brain MRI. A subset underwent 24-hour ambulatory blood pressure monitoring and lumbar puncture for cerebrospinal fluid (CSF) collection. RESULTS: As designed, participant groups were comparable for age (p = 0.31), sex (p = 0.95), and race (p = 0.65). MCI participants had greater Framingham Stroke Risk Profile scores (p = 0.008), systolic blood pressure values (p = 0.008), and history of left ventricular hypertrophy (p = 0.04) than NC participants. As expected, MCI participants performed worse on all neuropsychological measures (p-values < 0.001), were more likely to be APOEɛ4 carriers (p = 0.02), and had enhanced CSF biomarkers, including lower Aβ42 (p = 0.02), higher total tau (p = 0.004), and higher p-tau (p = 0.02) compared to NC participants. CONCLUSION: Diverse sources of baseline and longitudinal data will provide rich opportunities to investigate pathways linking vascular and cerebrovascular health, clinical and pathological AD, and neurodegeneration contributing to novel strategies to delay or prevent cognitive decline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Blood Pressure Monitoring, Ambulatory; Brain; Case-Control Studies; Cerebral Angiography; Cognitive Dysfunction; Echocardiography; Epidemiologic Research Design; Female; Follow-Up Studies; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Research Design

Vascular Health Indices and Cognitive Domain Function: Singapore Longitudinal Ageing Studies. - Lim, Shir Lynn; Gao, Qi; Nyunt, Ma Shwe Zin; Gong, Lingli; Lunaria, Josephine B; Lim, May Li; Ling, Audrey; Lam, Carolyn Su-Ping; Richards, Arthur Mark; Ling, Lieng Hsi; Ng, Tze Pin (J Alzheimers Dis, 2016)
BACKGROUND: Few studies have comprehensively evaluated the relationship between vascular disease and cognition of older adults without cardiac disease. OBJECTIVE: We explored the associations of structural atherosclerosis, vascular stiffness, and reactivity with global, memory, attention, language, visuospatial ability, and executive function in community-dwelling, non-demented older Asians without cardiac diseases. METHODS: Cognition was assessed by Mini-Mental State Examination (MMSE) (n = 308) and detailed neuropsychological tests (n = 155). Vascular measures included carotid intima-media thickness; aortic stiffness [carotid-femoral pulse wave velocity (CFPWV), aortic augmentation index (AI), and aortic pulse pressure (PP)]; carotid stiffness [elasticity modulus (Ep), beta index (β), arterial compliance (AC), carotid AI]; and endothelial function [reactive hyperemia index (RHI)]. Multivariable analyses controlled for potential confounding by demographics, apolipoprotein E genotype and cardiovascular risk factors. RESULTS: The participants' mean age was 63.0 ± 6.1 years. Inverse associations with MMSE were found for AC (β= 0.128, p = 0.019), Ep (β= -0.151, p = 0.008), β index (β= -0.122, p = 0.029), carotid stiffness z-score (β= -0.154, p = 0.007); with executive function for CFPWV (β= -0.209, p = 0.026), AC (β= 0.214, p = 0.005), Ep (β= -0.160, p = 0.050), β index (β= -0.165, p = 0.041), and both aortic (β= -0.229, p = 0.010) and carotid (β= -0.208, p = 0.010) stiffness z-scores; with verbal memory for AI (β= -0.229, p = 0.004) and aortic (β= -0.263, p = 0.004) stiffness z-score; with language for AI (β= -0.155, p = 0.025), aortic stiffness z-score (β= -0.196, p = 0.011). RHI positively correlated with visuospatial ability (β= 0.195, p = 0.013) and executive function (β= 0.151, p = 0.045). CONCLUSION: The results support a link between systemic vascular health and neurocognitive function in older Asian adults. Subclinical noninvasive measures of arterial stiffness and reactivity may identify individuals vulnerable to cognitive impairment.
Keywords: Aged; Blood Flow Velocity; Blood Pressure; Cardiovascular Diseases; Carotid Intima-Media Thickness; Cognitive Aging; Female; Humans; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Singapore; Vascular Stiffness

Vascular Risk Factors and Cognition in Parkinson's Disease. - Pilotto, Andrea; Turrone, Rosanna; Liepelt-Scarfone, Inga; Bianchi, Marta; Poli, Loris; Borroni, Barbara; Alberici, Antonella; Premi, Enrico; Formenti, Anna; Bigni, Barbara; Cosseddu, Maura; Cottini, Elisabetta; et al. (J Alzheimers Dis, 2016)
Vascular risk factors have been associated with cognitive deficits and incident dementia in the general population, but their role on cognitive dysfunction in Parkinson's disease (PD) is still unclear. The present study addresses the single and cumulative effect of vascular risk factors on cognition in PD patients, taking clinical confounders into account. Standardized neuropsychological assessment was performed in 238 consecutive PD patients. We evaluated the association of single and cumulative vascular risk factors (smoking, diabetes, hypercholesterolemia, hypertension, and heart disease), with the diagnosis of PD normal cognition (PDNC, n = 94), mild cognitive impairment (PD-MCI, n = 111), and dementia (PDD, n = 33). The association between single neuropsychological tests and vascular risk factors was evaluated with covariance analyses adjusted for age at onset, educational levels, gender, disease duration, and motor performance. Age, educational levels, disease duration, and motor function were significantly different between PDNC, PD-MCI, and PDD. Heart disease was the only vascular factor significantly more prevalent in PDD compared with PDNC in adjusted analyses. Performance of tests assessing executive and attention functions were significantly worse in patients with hypertension, heart disease, and/or diabetes (p <  0.05). Heart disease is associated with dementia in PD, suggesting a potential window of intervention. Vascular risk factors act especially on attention and executive functions in PD. Vascular risk stratification may be useful in order to identify PD patients with a greater risk of developing dementia. These findings need to be verified in longitudinal studies.
Keywords: Age of Onset; Aged; Attention; Disability Evaluation; Educational Status; Executive Function; Female; Humans; Male; Motor Activity; Neuropsychological Tests; Parkinson Disease; Prevalence; Risk Factors; Sex Factors; Time Factors; Vascular Diseases

Volumetric and shape analysis of the thalamus and striatum in amnestic mild cognitive impairment. - Leh, Sandra E; Kälin, Andrea M; Schroeder, Clemens; Park, Min Tae M; Chakravarty, M Mallar; Freund, Patrick; Gietl, Anton F; Riese, Florian; Kollias, Spyros; Hock, Christoph; Michels, Lars (J Alzheimers Dis, 2016)
Alterations in brain structures, including progressive neurodegeneration, are a hallmark in patients with Alzheimer's disease (AD). However, pathological mechanisms, such as the accumulation of amyloid and the proliferation of tau, are thought to begin years, even decades, before the initial clinical manifestations of AD. In this study, we compare the brain anatomy of amnestic mild cognitive impairment patients (aMCI, n = 16) to healthy subjects (CS, n = 22) using cortical thickness, subcortical volume, and shape analysis, which we believe to be complimentary to volumetric measures. We were able to replicate "classical" cortical thickness alterations in aMCI in the hippocampus, amygdala, putamen, insula, and inferior temporal regions. Additionally, aMCI showed significant thalamic and striatal shape differences. We observed higher global amyloid deposition in aMCI, a significant correlation between striatal displacement and global amyloid, and an inverse correlation between executive function and right-hemispheric thalamic displacement. In contrast, no volumetric differences were detected in thalamic, striatal, and hippocampal regions. Our results provide new evidence for early subcortical neuroanatomical changes in patients with aMCI, which are linked to cognitive abilities and amyloid deposition. Hence, shape analysis may aid in the identification of structural biomarkers for identifying individuals at highest risk of conversion to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Corpus Striatum; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Thalamus

What are the Most Frequently Impaired Markers of Neurodegeneration in ADNI Subjects? - Andriuta, Daniela; Moullart, Véronique; Schraen, Susanna; Devendeville, Agnes; Meyer, Marc-Etienne; Godefroy, Olivier (J Alzheimers Dis, 2016)
The aim of this study was to examine the relationship between cerebrospinal fluid (CSF) levels of biomarkers for Alzheimer's disease (AD) (Aβ1-42, t-tau, and p-tau) and 18Fluorodeoxyglucose positron emission tomography (FDG-PET) hypometabolism in subjects from the Alzheimer's Disease Neuroimaging Initiative, and specifically to determine which index of neurodegeneration was most frequently affected. The secondary objective was to determine the most frequently hypometabolic region in patients with a CSF AD signature (abnormal Aβ1-42 and abnormal p-tau). We included the 372 subjects (85 normal subjects, 212 patients with mild cognitive impairment, and 75 patients with AD) with a CSF biomarker dosage (Aβ1-42, t-tau, and p-tau) and brain FDG-PET. The relationship between FDG-PET metabolism (in five regions of interest (ROI) known to be damaged in AD) and CSF t-tau and p-tau levels was studied as a function of CSF Aβ1-42 status. FDG-PET hypometabolism and CSF t-tau and p-tau levels were correlated only in patients with an abnormal CSF Aβ1-42 level (t-tau: R2 = 0.044, p = 0.001; p-tau: R2 = 0.02, p = 0.03). In the latter patients, CSF p-tau was the most frequently (p = 0.0001) abnormal neurodegeneration marker (p-tau: 92.8%; FDG-PET: 56.5%; CSF t-tau: 59.1%). Within the five ROI of FDG PET, the angular gyrus metabolism (R2 = 0.149; p = 0.0001) was selected as the most tightly associated with CSF AD signature. The relation between CSF markers of neurodegeneration (p-tau and t-tau) and brain hypometabolism (in FDG-PET) is conditioned by presence of amyloid abnormality. This finding supports the current physiopathological model of AD. P-tau is the most frequently impaired biomarker. Using FDG PET angular gyrus hypometabolism is the most sensitive to CSF-biomarker-defined AD.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Brain; Cognitive Dysfunction; Databases, Factual; Female; Fluorodeoxyglucose F18; Humans; Male; Peptide Fragments; Phosphorylation; Positron-Emission Tomography; Radiopharmaceuticals; tau Proteins

White Matter Abnormalities Track Disease Progression in PSEN1 Autosomal Dominant Alzheimer's Disease. - Sánchez-Valle, Raquel; Monté, Gemma C; Sala-Llonch, Roser; Bosch, Beatriz; Fortea, Juan; Lladó, Albert; Antonell, Anna; Balasa, Mircea; Bargalló, Nuria; Molinuevo, José Luis (J Alzheimers Dis, 2016)
PSEN1 mutations are the most frequent cause of autosomal dominant Alzheimer's disease (ADAD), and show nearly full penetrance. There is presently increasing interest in the study of biomarkers that track disease progression in order to test therapeutic interventions in ADAD. We used white mater (WM) volumetric characteristics and diffusion tensor imaging (DTI) metrics to investigate correlations with the normalized time to expected symptoms onset (relative age ratio) and group differences in a cohort of 36 subjects from PSEN1 ADAD families: 22 mutation carriers, 10 symptomatic (SMC) and 12 asymptomatic (AMC), and 14 non-carriers (NC). Subjects underwent a 3T MRI. WM morphometric data and DTI metrics were analyzed. We found that PSEN1 MC showed significant negative correlation between fractional anisotropy (FA) and the relative age ratio in the genus and body of corpus callosum and corona radiate (p <  0.05 Family-wise error correction (FWE) at cluster level) and positive correlation with mean diffusivity (MD), axial diffusivity (AxD), and radial diffusivity (RD) in the splenium of corpus callosum. SMC presented WM volume loss, reduced FA and increased MD, AxD, and RD in the anterior and posterior corona radiate, corpus callosum (p <  0.05 FWE) compared with NC. No significant differences were observed between AMC and NC in WM volume or DTI measures. These findings suggest that the integrity of the WM deteriorates linearly in PSEN1 ADAD from the early phases of the disease; thus DTI metrics might be useful to monitor the disease progression. However, the lack of significant alterations at the preclinical stages suggests that these indexes might not be good candidates for early markers of the disease.
Keywords: Adult; Aging; Alzheimer Disease; Brain; Cohort Studies; Diffusion Tensor Imaging; Disease Progression; Family; Female; Heterozygote; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Mutation; Neuropsychological Tests; Organ Size; Presenilin-1; White Matter

White Matter and Hippocampal Volume Predict the Risk of Dementia in Patients with Cerebral Small Vessel Disease: The RUN DMC Study. - van Uden, Ingeborg W M; van der Holst, Helena M; Tuladhar, Anil M; van Norden, Anouk G W; de Laat, Karlijn F; Rutten-Jacobs, Loes C A; Norris, David G; Claassen, Jurgen A H R; van Dijk, Ewoud J; Kessels, Roy P C; de Leeuw, Frank-Erik (J Alzheimers Dis, 2016)
BACKGROUND: The relationship between cerebral small vessel disease (SVD) and dementia has been studied without considering white matter (WM) volume, the microstructural integrity of the WM surrounding the SVD, and grey matter (GM). OBJECTIVE: We prospectively investigated the relationship between these structures and the risk of dementia, and formed a prediction model to investigate which characteristics (macro- or microstructural) explained most of the variance. METHODS: The RUN DMC study is a prospective cohort study among 503 non-demented participants with an age between 50 and 85 years at baseline, with baseline assessment in 2006 and follow-up assessment in 2012. Two were lost to follow-up (yielding a 99.6% response-rate). Cox regression analysis was used, to calculate hazard ratios for dementia, of baseline MRI characteristics. Tract-Based Spatial Statistics (TBSS) analysis was used to assess the added value of microstructural integrity of the WM. RESULTS: Mean age at baseline was 65.6 years (SD 8.8) and 56.8% was male. 43 participants developed dementia (8.6%), resulting in a 5.5-year cumulative risk of 11.1% (95% CI 7.7-14.6). Low WM and hippocampal volume are significant predictors for dementia. WM, WM hyperintensities, and hippocampal volume explained most of the variance. TBSS analyses showed no additional value of diffusion parameters. CONCLUSIONS: WM and hippocampal volume were the main predictors for the development of incident dementia at 5-year follow-up in elderly with SVD. There was no additional diagnostic value of the diffusion tensor imaging parameters on top of the macrostructural characteristics.
Keywords: Aged; Cerebral Small Vessel Diseases; Cohort Studies; Dementia; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Statistics, Nonparametric; White Matter

White Matter Changes are Associated with Ventricular Expansion in Aging, Mild Cognitive Impairment, and Alzheimer's Disease. - Coutu, Jean-Philippe; Goldblatt, Alison; Rosas, H Diana; Salat, David H (J Alzheimers Dis, 2016)
White matter lesions are highly prevalent in individuals with Alzheimer's disease (AD). Although these lesions are presumed to be of vascular origin and linked to small vessel disease in older adults, little information exists about their relationship to markers of classical AD neurodegeneration. Thus, we examined the link between these white matter changes (WMC) segmented on T1-weighted MRI and imaging markers presumed to be altered due to primary AD neurodegenerative processes. Tissue microstructure of WMC was quantified using diffusion tensor imaging and the relationship of WMC properties and volume to neuroimaging markers was examined in 219 cognitively healthy older adults and individuals with mild cognitive impairment and AD using data from the Alzheimer's Disease Neuroimaging Initiative. No significant group differences in WMC properties were found. However, there were strong associations between diffusivity of WMC and ventricular volume, volume of WMC and total WM volume. In comparison, group differences in parahippocampal white matter microstructure were found for all diffusion metrics and were largely explained by hippocampal volume. Factor analysis on neuroimaging markers suggested two independent sets of covarying degenerative changes, with potentially age- and vascular-mediated tissue damage contributing to one factor and classical neurodegenerative changes associated with AD contributing to a second factor. These data demonstrate two potentially distinct classes of degenerative change in AD, with one factor strongly linked to aging, ventricular expansion, and both volume and tissue properties of white matter lesions, while the other factor related to classical patterns of cortical and hippocampal neurodegeneration in AD.
Keywords: Aged; Aging; Alzheimer Disease; Cognitive Dysfunction; Diffusion Tensor Imaging; Factor Analysis, Statistical; Female; Hippocampus; Humans; Imaging, Three-Dimensional; Male; Mental Status Schedule; Neuropsychological Tests; White Matter

δ Scores are Exportable Across Cultural and Linguistic Boundaries. - Royall, Donald R; Palmer, Raymond F; Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Nakaaki, Shutaro; Koumi, Hiroyuki; et al. (J Alzheimers Dis, 2016)
The latent variable "δ", can accurately diagnose dementia. Its generalizability across populations is unknown. We constructed a δ homolog ("dT2J") in data collected by the Texas Alzheimer's Research and Care Consortium (TARCC). From this, we calculated a composite d-score "d". We then tested d's generalizability across random subsets of TARCC participants and to a convenience sample of elderly Japanese persons with normal cognition (NC), mild cognitive impairment (MCI), and dementia (AD) (n = 176). dT2J was indicated by Instrumental Activities of Daily Living and psychometric measures. Embedded in this battery were the Mini-Mental Status Examination (MMSE) and an executive clock-drawing task (CLOX). Only MMSE and CLOX were available in both TARCC and the Japanese cohort. Therefore, a second composite variable, "T2J", was constructed solely from the factor loadings of CLOX and MMSE on d. The diagnostic accuracy of T2J was estimated in the validation sample, the remainder of the TARCC cohort, and in the Japanese sample. The areas under the receiver operating curve (AUC; ROC) for T2J were compared in each sample, and against d in TARCC. The AUCs for T2J were statistically indiscriminable within TARCC, and in Japanese persons. In Japanese persons, AUCs for T2J were 0.97 for the discrimination between AD versus NC, 0.86 for AD versus MCI, and 0.79 for NC versus MCI. The AUCs for T2J in Japanese persons were higher than any individual psychometric measure in that sample. Valid d-score composites can be abstracted from a subset of δ's indicators. Moreover, those composites are exportable across cultural and linguistic boundaries.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Cognitive Dysfunction; Cohort Studies; Culture; Executive Function; Female; Humans; Linguistics; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Psychometrics; Reproducibility of Results; ROC Curve; Texas

Phase 3 trials of solanezumab for mild-to-moderate Alzheimer's disease. - Doody, Rachelle S; Thomas, Ronald G; Farlow, Martin; Iwatsubo, Takeshi; Vellas, Bruno; Joffe, Steven; Kieburtz, Karl; Raman, Rema; Sun, Xiaoying; Aisen, Paul S; Siemers, Eric; Liu-Seifert, Hong; et al. (N Engl J Med, 2014)
BACKGROUND: Alzheimer's disease is characterized by amyloid-beta plaques, neurofibrillary tangles, gliosis, and neuronal loss. Solanezumab, a humanized monoclonal antibody, preferentially binds soluble forms of amyloid and in preclinical studies promoted its clearance from the brain. METHODS: In two phase 3, double-blind trials (EXPEDITION 1 and EXPEDITION 2), we randomly assigned 1012 and 1040 patients, respectively, with mild-to-moderate Alzheimer's disease to receive placebo or solanezumab (administered intravenously at a dose of 400 mg) every 4 weeks for 18 months. The primary outcomes were the changes from baseline to week 80 in scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11; range, 0 to 70, with higher scores indicating greater cognitive impairment) and the Alzheimer's Disease Cooperative Study-Activities of Daily Living scale (ADCS-ADL; range, 0 to 78, with lower scores indicating worse functioning). After analysis of data from EXPEDITION 1, the primary outcome for EXPEDITION 2 was revised to the change in scores on the 14-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog14; range, 0 to 90, with higher scores indicating greater impairment), in patients with mild Alzheimer's disease. RESULTS: Neither study showed significant improvement in the primary outcomes. The modeled difference between groups (solanezumab group minus placebo group) in the change from baseline was -0.8 points for the ADAS-cog11 score (95% confidence interval [CI], -2.1 to 0.5; P=0.24) and -0.4 points for the ADCS-ADL score (95% CI, -2.3 to 1.4; P=0.64) in EXPEDITION 1 and -1.3 points (95% CI, -2.5 to 0.3; P=0.06) and 1.6 points (95% CI, -0.2 to 3.3; P=0.08), respectively, in EXPEDITION 2. Between-group differences in the changes in the ADAS-cog14 score were -1.7 points in patients with mild Alzheimer's disease (95% CI, -3.5 to 0.1; P=0.06) and -1.5 in patients with moderate Alzheimer's disease (95% CI, -4.1 to 1.1; P=0.26). In the combined safety data set, the incidence of amyloid-related imaging abnormalities with edema or hemorrhage was 0.9% with solanezumab and 0.4% with placebo for edema (P=0.27) and 4.9% and 5.6%, respectively, for hemorrhage (P=0.49). CONCLUSIONS: Solanezumab, a humanized monoclonal antibody that binds amyloid, failed to improve cognition or functional ability. (Funded by Eli Lilly; EXPEDITION 1 and 2 ClinicalTrials.gov numbers, NCT00905372 and NCT00904683.).
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Cognition; Double-Blind Method; Female; Humans; Intention to Treat Analysis; Male; Neuropsychological Tests; Severity of Illness Index; tau Proteins; Treatment Failure

Plasma phospholipids identify antecedent memory impairment in older adults. - Mapstone, Mark; Cheema, Amrita K; Fiandaca, Massimo S; Zhong, Xiaogang; Mhyre, Timothy R; MacArthur, Linda H; Hall, William J; Fisher, Susan G; Peterson, Derick R; Haley, James M; Nazar, Michael D; Rich, Steven A; et al. (Nat Med, 2014)
Alzheimer's disease causes a progressive dementia that currently affects over 35 million individuals worldwide and is expected to affect 115 million by 2050 (ref. 1). There are no cures or disease-modifying therapies, and this may be due to our inability to detect the disease before it has progressed to produce evident memory loss and functional decline. Biomarkers of preclinical disease will be critical to the development of disease-modifying or even preventative therapies. Unfortunately, current biomarkers for early disease, including cerebrospinal fluid tau and amyloid-β levels, structural and functional magnetic resonance imaging and the recent use of brain amyloid imaging or inflammaging, are limited because they are either invasive, time-consuming or expensive. Blood-based biomarkers may be a more attractive option, but none can currently detect preclinical Alzheimer's disease with the required sensitivity and specificity. Herein, we describe our lipidomic approach to detecting preclinical Alzheimer's disease in a group of cognitively normal older adults. We discovered and validated a set of ten lipids from peripheral blood that predicted phenoconversion to either amnestic mild cognitive impairment or Alzheimer's disease within a 2-3 year timeframe with over 90% accuracy. This biomarker panel, reflecting cell membrane integrity, may be sensitive to early neurodegeneration of preclinical Alzheimer's disease.
Keywords: Aged; Alzheimer Disease; Asparagine; Biomarkers; Carnitine; Cohort Studies; Dipeptides; Female; Humans; Longitudinal Studies; Lysophosphatidylcholines; Malates; Male; Memory Disorders; Metabolome; Mild Cognitive Impairment; Neuropsychological Tests; Phosphatidylcholines; Phosphatidylinositols; Phospholipids; Proline; Prospective Studies; Sensitivity and Specificity; Sphingomyelins; Ursodeoxycholic Acid

Ten-year effects of the advanced cognitive training for independent and vital elderly cognitive training trial on cognition and everyday functioning in older adults. - Rebok, George W; Ball, Karlene; Guey, Lin T; Jones, Richard N; Kim, Hae-Young; King, Jonathan W; Marsiske, Michael; Morris, John N; Tennstedt, Sharon L; Unverzagt, Frederick W; Willis, Sherry L (J Am Geriatr Soc, 2014)
OBJECTIVES: To determine the effects of cognitive training on cognitive abilities and everyday function over 10 years. DESIGN: Ten-year follow-up of a randomized, controlled single-blind trial (Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE)) with three intervention groups and a no-contact control group. SETTING: Six U.S. cities. PARTICIPANTS: A volunteer sample of 2,832 persons (mean baseline age 73.6; 26% African American) living independently. INTERVENTION: Ten training sessions for memory, reasoning, or speed of processing; four sessions of booster training 11 and 35 months after initial training. MEASUREMENTS: Objectively measured cognitive abilities and self-reported and performance-based measures of everyday function. RESULTS: Participants in each intervention group reported less difficulty with instrumental activities of daily living (IADLs) (memory: effect size = 0.48, 99% confidence interval (CI) = 0.12-0.84; reasoning: effect size = 0.38, 99% CI = 0.02-0.74; speed of processing: effect size = 0.36, 99% CI = 0.01-0.72). At a mean age of 82, approximately 60% of trained participants, versus 50% of controls (P < .05), were at or above their baseline level of self-reported IADL function at 10 years. The reasoning and speed-of-processing interventions maintained their effects on their targeted cognitive abilities at 10 years (reasoning: effect size = 0.23, 99% CI = 0.09-0.38; speed of processing: effect size = 0.66, 99% CI = 0.43-0.88). Memory training effects were no longer maintained for memory performance. Booster training produced additional and durable improvement for the reasoning intervention for reasoning performance (effect size = 0.21, 99% CI = 0.01-0.41) and the speed-of-processing intervention for speed-of-processing performance (effect size = 0.62, 99% CI = 0.31-0.93). CONCLUSION: Each Advanced Cognitive Training for Independent and Vital Elderly cognitive intervention resulted in less decline in self-reported IADL compared with the control group. Reasoning and speed, but not memory, training resulted in improved targeted cognitive abilities for 10 years.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cognition Disorders; Cognitive Therapy; Female; Follow-Up Studies; Humans; Independent Living; Male; Memory Disorders; Mental Processes; Single-Blind Method; United States

Two phase 3 trials of bapineuzumab in mild-to-moderate Alzheimer's disease. - Salloway, Stephen; Sperling, Reisa; Fox, Nick C; Blennow, Kaj; Klunk, William; Raskind, Murray; Sabbagh, Marwan; Honig, Lawrence S; Porsteinsson, Anton P; Ferris, Steven; Reichert, Marcel; Ketter, Nzeera; et al. (N Engl J Med, 2014)
BACKGROUND: Bapineuzumab, a humanized anti-amyloid-beta monoclonal antibody, is in clinical development for the treatment of Alzheimer's disease. METHODS: We conducted two double-blind, randomized, placebo-controlled, phase 3 trials involving patients with mild-to-moderate Alzheimer's disease--one involving 1121 carriers of the apolipoprotein E (APOE) ε4 allele and the other involving 1331 noncarriers. Bapineuzumab or placebo, with doses varying by study, was administered by intravenous infusion every 13 weeks for 78 weeks. The primary outcome measures were scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11, with scores ranging from 0 to 70 and higher scores indicating greater impairment) and the Disability Assessment for Dementia (DAD, with scores ranging from 0 to 100 and higher scores indicating less impairment). A total of 1090 carriers and 1114 noncarriers were included in the efficacy analysis. Secondary outcome measures included findings on positron-emission tomographic amyloid imaging with the use of Pittsburgh compound B (PIB-PET) and cerebrospinal fluid phosphorylated tau (phospho-tau) concentrations. RESULTS: There were no significant between-group differences in the primary outcomes. At week 78, the between-group differences in the change from baseline in the ADAS-cog11 and DAD scores (bapineuzumab group minus placebo group) were -0.2 (P=0.80) and -1.2 (P=0.34), respectively, in the carrier study; the corresponding differences in the noncarrier study were -0.3 (P=0.64) and 2.8 (P=0.07) with the 0.5-mg-per-kilogram dose of bapineuzumab and 0.4 (P=0.62) and 0.9 (P=0.55) with the 1.0-mg-per-kilogram dose. The major safety finding was amyloid-related imaging abnormalities with edema among patients receiving bapineuzumab, which increased with bapineuzumab dose and APOE ε4 allele number and which led to discontinuation of the 2.0-mg-per-kilogram dose. Between-group differences were observed with respect to PIB-PET and cerebrospinal fluid phospho-tau concentrations in APOE ε4 allele carriers but not in noncarriers. CONCLUSIONS: Bapineuzumab did not improve clinical outcomes in patients with Alzheimer's disease, despite treatment differences in biomarkers observed in APOE ε4 carriers. (Funded by Janssen Alzheimer Immunotherapy and Pfizer; Bapineuzumab 301 and 302 ClinicalTrials.gov numbers, NCT00575055 and NCT00574132, and EudraCT number, 2009-012748-17.).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Brain; Cognition; Double-Blind Method; Edema; Female; Humans; Intention to Treat Analysis; Male; Middle Aged; Neuropsychological Tests; Phosphorylation; Positron-Emission Tomography; Severity of Illness Index; tau Proteins; Treatment Failure

Anti-amyloid β autoantibodies in cerebral amyloid angiopathy-related inflammation: implications for amyloid-modifying therapies. - Piazza, Fabrizio; Greenberg, Steven M; Savoiardo, Mario; Gardinetti, Margherita; Chiapparini, Luisa; Raicher, Irina; Nitrini, Ricardo; Sakaguchi, Hideya; Brioschi, Monica; Billo, Giuseppe; Colombo, Antonio; Lanzani, Francesca; et al. (Ann Neurol, 2013)
OBJECTIVE: Cerebral amyloid angiopathy-related inflammation (CAA-ri) is characterized by vasogenic edema and multiple cortical/subcortical microbleeds, sharing several aspects with the recently defined amyloid-related imaging abnormalities (ARIA) reported in Alzheimer's disease (AD) passive immunization therapies. Herein, we investigated the role of anti-amyloid β (Aβ) autoantibodies in the acute and remission phases of CAA-ri. METHODS: We used a novel ultrasensitive technique on patients from a retrospective multicenter case-control study, and evaluated the anti-Aβ autoantibody concentration in the cerebrospinal fluid (CSF) of 10 CAA-ri, 8 CAA, 14 multiple sclerosis, and 25 control subjects. Levels of soluble Aβ40, Aβ42, tau, P-181 tau, and APOE genotype were also investigated. RESULTS: During the acute phase of CAA-ri, anti-Aβ autoantibodies were specifically increased and directly correlated with Aβ mobilization, together with augmented tau and P-181 tau. Following clinical and radiological remission, autoantibodies progressively returned to control levels, and both soluble Aβ and axonal degeneration markers decreased in parallel. INTERPRETATION: Our data support the hypothesis that the pathogenesis of CAA-ri may be mediated by a selective autoimmune reaction against cerebrovascular Aβ, directly related to autoantibody concentration and soluble Aβ. The CSF dosage of anti-Aβ autoantibodies with the technique here described can thus be proposed as a valid alternative tool for the diagnosis of CAA-ri. Moreover, given the similarities between ARIA developing spontaneously and those observed during immunization trials, anti-Aβ autoantibodies can be considered as novel potential biomarkers in future amyloid-modifying therapies for the treatment of AD and CAA.
Keywords: Adult; Aged; Amyloid beta-Peptides; Apolipoproteins E; Autoantibodies; Brain; Case-Control Studies; Cerebral Amyloid Angiopathy; Female; Humans; Inflammation; Male; Middle Aged; Peptide Fragments; Phosphorylation; Retrospective Studies; Steroids; tau Proteins

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Cerebrospinal fluid levels of β-amyloid 1-42, but not of tau, are fully changed already 5 to 10 years before the onset of Alzheimer dementia. - Buchhave, Peder; Minthon, Lennart; Zetterberg, Henrik; Wallin, Asa K; Blennow, Kaj; Hansson, Oskar (Arch Gen Psychiatry, 2012)
CONTEXT: Early detection of prodromal Alzheimer disease (AD) is important because new disease-modifying therapies are most likely to be effective when initiated during the early stages of disease. OBJECTIVES: To assess the ability of the cerebrospinal fluid (CSF) biomarkers total tau (T-tau), phosphorylated tau (P-tau), and β-amyloid 1-42 (Aβ42) to predict future development of AD dementia within 9.2 years in patients with mild cognitive impairment (MCI) and to compare CSF biomarkers between early and late converters to AD. DESIGN: A clinical study with a median follow-up of 9.2 years (range, 4.1-11.8 years). SETTING: Memory disorder clinic. Patients A total of 137 patients with MCI who underwent lumbar puncture at baseline. MAIN OUTCOME MEASURE Conversion to AD dementia. RESULTS: During follow-up, 72 patients (53.7%) developed AD and 21 (15.7%) progressed to other forms of dementia. At baseline, CSF Aβ42 levels were reduced and T-tau and P-tau levels were elevated in patients who converted to AD during follow-up compared with nonconverters (P < .001). Baseline CSF Aβ42 levels were equally reduced in patients with MCI who converted to AD within 0 to 5 years (early converters) compared with those who converted between 5 and 10 years (late converters). However, CSF T-tau and P-tau levels were significantly higher in early converters vs late converters. A baseline Aβ42:P-tau ratio predicted the development of AD within 9.2 years with a sensitivity of 88%, specificity of 90%, positive predictive value of 91%, and negative predictive value of 86%. CONCLUSIONS: Approximately 90% of patients with MCI and pathologic CSF biomarker levels at baseline develop AD within 9 to 10 years. Levels of Aβ42 are already fully decreased at least 5 to 10 years before conversion to AD dementia, whereas T-tau and P-tau seem to be later markers. These results provide direct support in humans for the hypothesis that altered Aβ metabolism precedes tau-related pathology and neuronal degeneration.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Female; Follow-Up Studies; Humans; Male; Mild Cognitive Impairment; Peptide Fragments; Predictive Value of Tests; tau Proteins; Time Factors

Demonstrated brain insulin resistance in Alzheimer's disease patients is associated with IGF-1 resistance, IRS-1 dysregulation, and cognitive decline. - Talbot, Konrad; Wang, Hoau-Yan; Kazi, Hala; Han, Li-Ying; Bakshi, Kalindi P; Stucky, Andres; Fuino, Robert L; Kawaguchi, Krista R; Samoyedny, Andrew J; Wilson, Robert S; Arvanitakis, Zoe; Schneider, Julie A; et al. (J Clin Invest, 2012)
While a potential causal factor in Alzheimer's disease (AD), brain insulin resistance has not been demonstrated directly in that disorder. We provide such a demonstration here by showing that the hippocampal formation (HF) and, to a lesser degree, the cerebellar cortex in AD cases without diabetes exhibit markedly reduced responses to insulin signaling in the IR→IRS-1→PI3K signaling pathway with greatly reduced responses to IGF-1 in the IGF-1R→IRS-2→PI3K signaling pathway. Reduced insulin responses were maximal at the level of IRS-1 and were consistently associated with basal elevations in IRS-1 phosphorylated at serine 616 (IRS-1 pS⁶¹⁶) and IRS-1 pS⁶³⁶/⁶³⁹. In the HF, these candidate biomarkers of brain insulin resistance increased commonly and progressively from normal cases to mild cognitively impaired cases to AD cases regardless of diabetes or APOE ε4 status. Levels of IRS-1 pS⁶¹⁶ and IRS-1 pS⁶³⁶/⁶³⁹ and their activated kinases correlated positively with those of oligomeric Aβ plaques and were negatively associated with episodic and working memory, even after adjusting for Aβ plaques, neurofibrillary tangles, and APOE ε4. Brain insulin resistance thus appears to be an early and common feature of AD, a phenomenon accompanied by IGF-1 resistance and closely associated with IRS-1 dysfunction potentially triggered by Aβ oligomers and yet promoting cognitive decline independent of classic AD pathology.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Brain; Cerebellar Cortex; Cognition Disorders; Diabetes Complications; Drug Resistance; Female; Glucose; Hippocampus; Humans; Insulin; Insulin Receptor Substrate Proteins; Insulin Resistance; Insulin-Like Growth Factor I; Male; Middle Aged; Phosphorylation; Phosphoserine; Protein Processing, Post-Translational; Recombinant Proteins; Signal Transduction

Exercise Engagement as a Moderator of the Effects of APOE Genotype on Amyloid Deposition. - Head, Denise; Bugg, Julie M; Goate, Alison M; Fagan, Anne M; Mintun, Mark A; Benzinger, Tammie; Holtzman, David M; Morris, John C (Arch Neurol, 2012)
OBJECTIVE: APOE ε4 status has been associated with greater cortical amyloid deposition, whereas exercise has been associated with less in cognitively normal adults. The primary objective here was to examine whether physical exercise moderates the association between APOE genotype and amyloid deposition in cognitively normal adults. DESIGN: APOE genotyping data and answers to a questionnaire on physical exercise engagement over the last decade were obtained in conjunction with cerebrospinal fluid (CSF) samples and amyloid imaging with carbon 11-labeled Pittsburgh Compound B ([(11)C]PiB) positron emission tomography. Participants were classified as either low or high exercisers based on exercise guidelines of the American Heart Association. SETTING: Knight Alzheimer's Disease Research Center at Washington University, St Louis, Missouri. PARTICIPANTS: A total of 201 cognitively normal adults (135 of whom were women) aged 45 to 88 years were recruited from the Knight Alzheimer's Disease Research Center. Samples of CSF were collected from 165 participants. Amyloid imaging was performed for 163 participants. RESULTS: APOE ε4 carriers evidenced higher [(11)C]PiB binding (P<.001) and lower CSF Aβ42 levels (P<.001) than did noncarriers. Our previous findings of higher [(11)C]PiB binding (P=.005) and lower CSF Aβ42 levels (P=.009) in more sedentary individuals were replicated. Most importantly, we observed a novel interaction between APOE status and exercise engagement for [(11)C]PiB binding (P=.008) such that a more sedentary lifestyle was significantly associated with higher [(11)C]PiB binding for ε4 carriers (P=.013) but not for noncarriers (P=.20). All findings remained significant after controlling for age; sex; educational level; body mass index; the presence or history of hypertension, diabetes mellitus, heart problems, or depression; and the interval between assessments. CONCLUSION: Collectively, these results suggest that cognitively normal sedentary APOE ε4-positive individuals may be at augmented risk for cerebral amyloid deposition.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Aniline Compounds; Apolipoprotein E4; Brain; Cognition; Cohort Studies; Exercise; Female; Genetic Association Studies; Genotype; Humans; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Positron-Emission Tomography; Regression Analysis; Surveys and Questionnaires; Thiazoles

Neuroinflammation, hyperphosphorylated tau, diffuse amyloid plaques, and down-regulation of the cellular prion protein in air pollution exposed children and young adults. - Calderón-Garcidueñas, Lilian; Kavanaugh, Michael; Block, Michelle; D'Angiulli, Amedeo; Delgado-Chávez, Ricardo; Torres-Jardón, Ricardo; González-Maciel, Angelica; Reynoso-Robles, Rafael; Osnaya, Norma; Villarreal-Calderon, Rodolfo; Guo, Ruixin; Hua, Zhaowei; et al. (J Alzheimers Dis, 2012)
Air pollution exposures have been linked to neuroinflammation and neuropathology. Autopsy samples of the frontal cortex from control (n = 8) and pollution-exposed (n = 35) children and young adults were analyzed by RT-PCR (n = 43) and microarray analysis (n = 12) for gene expression changes in oxidative stress, DNA damage signaling, NFκB signaling, inflammation, and neurodegeneration pathways. The effect of apolipoprotein E (APOE) genotype on the presence of protein aggregates associated with Alzheimer's disease (AD) pathology was also explored. Exposed urbanites displayed differential (>2-fold) regulation of 134 genes. Forty percent exhibited tau hyperphosphorylation with pre-tangle material and 51% had amyloid-β (Aβ) diffuse plaques compared with 0% in controls. APOE4 carriers had greater hyperphosphorylated tau and diffuse Aβ plaques versus E3 carriers (Q = 7.82, p = 0.005). Upregulated gene network clusters included IL1, NFκB, TNF, IFN, and TLRs. A 15-fold frontal down-regulation of the prion-related protein (PrP(C)) was seen in highly exposed subjects. The down-regulation of the PrP(C) is critical given its important roles for neuroprotection, neurodegeneration, and mood disorder states. Elevation of indices of neuroinflammation and oxidative stress, down-regulation of the PrP(C) and AD-associated pathology are present in young megacity residents. The inducible regulation of gene expression suggests they are evolving different mechanisms in an attempt to cope with the constant state of inflammation and oxidative stress related to their environmental exposures. Together, these data support a role for air pollution in CNS damage and its impact upon the developing brain and the potential etiology of AD and mood disorders.
Keywords: Adolescent; Adult; Age Factors; Air Pollution; Child; Child, Preschool; Cohort Studies; Down-Regulation; Encephalitis; Female; Frontal Lobe; Gene Regulatory Networks; Humans; Infant; Male; Mexico; Phosphorylation; Plaque, Amyloid; Prions; tau Proteins; Young Adult

An operational approach to National Institute on Aging-Alzheimer's Association criteria for preclinical Alzheimer disease. - Jack, Clifford R; Knopman, David S; Weigand, Stephen D; Wiste, Heather J; Vemuri, Prashanthi; Lowe, Val; Kantarci, Kejal; Gunter, Jeffrey L; Senjem, Matthew L; Ivnik, Robert J; Roberts, Rosebud O; Rocca, Walter A; et al. (Ann Neurol, 2012)
OBJECTIVE: A workgroup commissioned by the Alzheimer's Association (AA) and the National Institute on Aging (NIA) recently published research criteria for preclinical Alzheimer disease (AD). We performed a preliminary assessment of these guidelines. METHODS: We employed Pittsburgh compound B positron emission tomography (PET) imaging as our biomarker of cerebral amyloidosis, and (18) fluorodeoxyglucose PET imaging and hippocampal volume as biomarkers of neurodegeneration. A group of 42 clinically diagnosed AD subjects was used to create imaging biomarker cutpoints. A group of 450 cognitively normal (CN) subjects from a population-based sample was used to develop cognitive cutpoints and to assess population frequencies of the different preclinical AD stages using different cutpoint criteria. RESULTS: The new criteria subdivide the preclinical phase of AD into stages 1 to 3. To classify our CN subjects, 2 additional categories were needed. Stage 0 denotes subjects with normal AD biomarkers and no evidence of subtle cognitive impairment. Suspected non-AD pathophysiology (SNAP) denotes subjects with normal amyloid PET imaging, but abnormal neurodegeneration biomarker studies. At fixed cutpoints corresponding to 90% sensitivity for diagnosing AD and the 10th percentile of CN cognitive scores, 43% of our sample was classified as stage 0, 16% stage 1, 12 % stage 2, 3% stage 3, and 23% SNAP. INTERPRETATION: This cross-sectional evaluation of the NIA-AA criteria for preclinical AD indicates that the 1-3 staging criteria coupled with stage 0 and SNAP categories classify 97% of CN subjects from a population-based sample, leaving only 3% unclassified. Future longitudinal validation of the criteria will be important.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Biomarkers; Brain; Cognition Disorders; Disease Progression; Female; Fluorodeoxyglucose F18; Humans; Longitudinal Studies; Male; Mental Status Schedule; National Institute on Aging (U.S.); Neuropsychological Tests; Positron-Emission Tomography; Thiazoles; United States

Predicting regional neurodegeneration from the healthy brain functional connectome. - Zhou, Juan; Gennatas, Efstathios D; Kramer, Joel H; Miller, Bruce L; Seeley, William W (Neuron, 2012)
Neurodegenerative diseases target large-scale neural networks. Four competing mechanistic hypotheses have been proposed to explain network-based disease patterning: nodal stress, transneuronal spread, trophic failure, and shared vulnerability. Here, we used task-free fMRI to derive the healthy intrinsic connectivity patterns seeded by brain regions vulnerable to any of five distinct neurodegenerative diseases. These data enabled us to investigate how intrinsic connectivity in health predicts region-by-region vulnerability to disease. For each illness, specific regions emerged as critical network "epicenters" whose normal connectivity profiles most resembled the disease-associated atrophy pattern. Graph theoretical analyses in healthy subjects revealed that regions with higher total connectional flow and, more consistently, shorter functional paths to the epicenters, showed greater disease-related vulnerability. These findings best fit a transneuronal spread model of network-based vulnerability. Molecular pathological approaches may help clarify what makes each epicenter vulnerable to its targeting disease and how toxic protein species travel between networked brain structures.
Keywords: Aged; Atrophy; Brain; Brain Mapping; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Nerve Net; Neural Pathways; Neurodegenerative Diseases; Oxygen; Reference Values

Reduction of hippocampal hyperactivity improves cognition in amnestic mild cognitive impairment. - Bakker, Arnold; Krauss, Gregory L; Albert, Marilyn S; Speck, Caroline L; Jones, Lauren R; Stark, Craig E; Yassa, Michael A; Bassett, Susan S; Shelton, Amy L; Gallagher, Michela (Neuron, 2012)
Elevated hippocampal activation is observed in conditions that confer risk for Alzheimer's disease, including amnestic mild cognitive impairment (aMCI). Studies in relevant animal models have indicated that overactivity in selective hippocampal circuits contributes to cognitive impairment. Here, we tested the effect of reducing hippocampal activation in aMCI. Under placebo treatment, hippocampal activation in the dentate gyrus/CA3 was elevated in aMCI patients compared to a healthy control group. By using a low dose of the antiepileptic levetiracetam hippocampal activation in aMCI was reduced to a level that did not differ from the control group. Compared to aMCI memory performance under placebo, performance in the scanning task was significantly improved under drug treatment. Contrary to the view that greater hippocampal activation might serve a beneficial function, these results support the view that increased hippocampal activation in aMCI is a dysfunctional condition and that targeting excess hippocampal activity has therapeutic potential.
Keywords: Aged; Aged, 80 and over; Amnesia; Brain Mapping; Case-Control Studies; Choice Behavior; Double-Blind Method; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Mild Cognitive Impairment; Neuropsychological Tests; Nootropic Agents; Oxygen; Photic Stimulation; Piracetam; Statistics as Topic

18F-THK523: a novel in vivo tau imaging ligand for Alzheimer's disease. - Fodero-Tavoletti, Michelle T; Okamura, Nobuyuki; Furumoto, Shozo; Mulligan, Rachel S; Connor, Andrea R; McLean, Catriona A; Cao, Diana; Rigopoulos, Angela; Cartwright, Glenn A; O'Keefe, Graeme; Gong, Sylvia; Adlard, Paul A; et al. (Brain, 2011)
While considerable effort has focused on developing positron emission tomography β-amyloid imaging radiotracers for the early diagnosis of Alzheimer's disease, no radiotracer is available for the non-invasive quantification of tau. In this study, we detail the characterization of (18)F-THK523 as a novel tau imaging radiotracer. In vitro binding studies demonstrated that (18)F-THK523 binds with higher affinity to a greater number of binding sites on recombinant tau (K18Δ280K) compared with β-amyloid(1-42) fibrils. Autoradiographic and histofluorescence analysis of human hippocampal serial sections with Alzheimer's disease exhibited positive THK523 binding that co-localized with immunoreactive tau pathology, but failed to highlight β-amyloid plaques. Micro-positron emission tomography analysis demonstrated significantly higher retention of (18)F-THK523 (48%; P < 0.007) in tau transgenic mice brains compared with their wild-type littermates or APP/PS1 mice. The preclinical examination of THK523 has demonstrated its high affinity and selectivity for tau pathology both in vitro and in vivo, indicating that (18)F-THK523 fulfils ligand criteria for human imaging trials.
Keywords: Alzheimer Disease; Analysis of Variance; Aniline Compounds; Animals; Autoradiography; Binding Sites; Brain; Female; Fluorodeoxyglucose F18; Humans; Immunohistochemistry; Male; Mice; Quinolines; Radiopharmaceuticals; tau Proteins

Evidence for ordering of Alzheimer disease biomarkers. - Jack, Clifford R; Vemuri, Prashanthi; Wiste, Heather J; Weigand, Stephen D; Aisen, Paul S; Trojanowski, John Q; Shaw, Leslie M; Bernstein, Matthew A; Petersen, Ronald C; Weiner, Michael W; Knopman, David S (Arch Neurol, 2011)
OBJECTIVE: To empirically assess the concept that Alzheimer disease (AD) biomarkers significantly depart from normality in a temporally ordered manner. DESIGN: Validation sample. SETTING: Multisite, referral centers. PARTICIPANTS: A total of 401 elderly participants in the Alzheimer's Disease Neuroimaging Initiative who were cognitively normal, who had mild cognitive impairment, or who had AD dementia. We compared the proportions of 3 AD biomarker values (the Aβ42 level in cerebrospinal fluid [CSF], the total tau level in CSF, and the hippocampal volume adjusted for intracranial volume [hereafter referred to as the adjusted hippocampal volume]) that were abnormal as cognitive impairment worsened. Cut points demarcating normal vs abnormal for each biomarker were established by maximizing diagnostic accuracy in independent autopsy samples. MAIN OUTCOME MEASURES: Three AD biomarkers (ie, the CSF Aβ42 level, the CSF total tau level, and the adjusted hippocampal volume). RESULTS: Within each clinical group of the entire sample (n = 401), the CSF Aβ42 level was abnormal more often than was the CSF total tau level or the adjusted hippocampal volume. Among the 298 participants with both baseline and 12-month data, the proportion of participants with an abnormal Aβ42 level did not change from baseline to 12 months in any group. The proportion of participants with an abnormal total tau level increased from baseline to 12 months in cognitively normal participants (P = .05) but not in participants with mild cognitive impairment or AD dementia. For 209 participants with an abnormal CSF Aβ42 level at baseline, the percentage with an abnormal adjusted hippocampal volume but normal CSF total tau level increased from baseline to 12 months in participants with mild cognitive impairment. No change in the percentage of MCI participants with an abnormal total tau level was seen between baseline and 12 months. CONCLUSIONS: A reduction in the CSF Aβ42 level denotes a pathophysiological process that significantly departs from normality (ie, becomes dynamic) early, whereas the CSF total tau level and the adjusted hippocampal volume are biomarkers of downstream pathophysiological processes. The CSF total tau level becomes dynamic before the adjusted hippocampal volume, but the hippocampal volume is more dynamic in the clinically symptomatic mild cognitive impairment and AD dementia phases of the disease than is the CSF total tau level.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Female; Hippocampus; Humans; Longitudinal Studies; Male; Mild Cognitive Impairment; tau Proteins

Human apoE isoforms differentially regulate brain amyloid-β peptide clearance. - Castellano, Joseph M; Kim, Jungsu; Stewart, Floy R; Jiang, Hong; DeMattos, Ronald B; Patterson, Bruce W; Fagan, Anne M; Morris, John C; Mawuenyega, Kwasi G; Cruchaga, Carlos; Goate, Alison M; Bales, Kelly R; et al. (Sci Transl Med, 2011)
The apolipoprotein E (APOE) ε4 allele is the strongest genetic risk factor for late-onset, sporadic Alzheimer's disease (AD). The APOE ε4 allele markedly increases AD risk and decreases age of onset, likely through its strong effect on the accumulation of amyloid-β (Aβ) peptide. In contrast, the APOE ε2 allele appears to decrease AD risk. Most rare, early-onset forms of familial AD are caused by autosomal dominant mutations that often lead to overproduction of Aβ(42) peptide. However, the mechanism by which APOE alleles differentially modulate Aβ accumulation in sporadic, late-onset AD is less clear. In a cohort of cognitively normal individuals, we report that reliable molecular and neuroimaging biomarkers of cerebral Aβ deposition vary in an apoE isoform-dependent manner. We hypothesized that human apoE isoforms differentially affect Aβ clearance or synthesis in vivo, resulting in an apoE isoform-dependent pattern of Aβ accumulation later in life. Performing in vivo microdialysis in a mouse model of Aβ-amyloidosis expressing human apoE isoforms (PDAPP/TRE), we find that the concentration and clearance of soluble Aβ in the brain interstitial fluid depends on the isoform of apoE expressed. This pattern parallels the extent of Aβ deposition observed in aged PDAPP/TRE mice. ApoE isoform-dependent differences in soluble Aβ metabolism are observed not only in aged but also in young PDAPP/TRE mice well before the onset of Aβ deposition in amyloid plaques in the brain. Additionally, amyloidogenic processing of amyloid precursor protein and Aβ synthesis, as assessed by in vivo stable isotopic labeling kinetics, do not vary according to apoE isoform in young PDAPP/TRE mice. Our results suggest that APOE alleles contribute to AD risk by differentially regulating clearance of Aβ from the brain, suggesting that Aβ clearance pathways may be useful therapeutic targets for AD prevention.
Keywords: Adult; Aged; Alleles; Alzheimer Disease; Amyloid beta-Peptides; Animals; Apolipoprotein E4; Biomarkers; Brain; Female; Genotype; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microdialysis; Middle Aged; Protein Isoforms

Neuronal activity regulates the regional vulnerability to amyloid-β deposition. - Bero, Adam W; Yan, Ping; Roh, Jee Hoon; Cirrito, John R; Stewart, Floy R; Raichle, Marcus E; Lee, Jin-Moo; Holtzman, David M (Nat Neurosci, 2011)
Amyloid-β (Aβ) plaque deposition in specific brain regions is a pathological hallmark of Alzheimer's disease. However, the mechanism underlying the regional vulnerability to Aβ deposition in Alzheimer's disease is unknown. Herein, we provide evidence that endogenous neuronal activity regulates the regional concentration of interstitial fluid (ISF) Aβ, which drives local Aβ aggregation. Using in vivo microdialysis, we show that ISF Aβ concentrations in several brain regions of APP transgenic mice before plaque deposition were commensurate with the degree of subsequent plaque deposition and with the concentration of lactate, a marker of neuronal activity. Furthermore, unilateral vibrissal stimulation increased ISF Aβ, and unilateral vibrissal deprivation decreased ISF Aβ and lactate, in contralateral barrel cortex. Long-term unilateral vibrissal deprivation decreased amyloid plaque formation and growth. Our results suggest a mechanism to account for the vulnerability of specific brain regions to Aβ deposition in Alzheimer's disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cerebral Cortex; Disease Models, Animal; Extracellular Fluid; Female; Lactic Acid; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microdialysis; Neurons; Plaque, Amyloid; Sensory Deprivation; Somatosensory Cortex

Stages of the pathologic process in Alzheimer disease: age categories from 1 to 100 years. - Braak, Heiko; Thal, Dietmar R; Ghebremedhin, Estifanos; Del Tredici, Kelly (J Neuropathol Exp Neurol, 2011)
Two thousand three hundred and thirty two nonselected brains from 1- to 100-year-old individuals were examined using immunocytochemistry (AT8) and Gallyas silver staining for abnormal tau; immunocytochemistry (4G8) and Campbell-Switzer staining were used for the detection ofβ-amyloid. A total of 342 cases was negative in the Gallyas stain but when restaged for AT8 only 10 were immunonegative. Fifty-eight cases had subcortical tau predominantly in the locus coeruleus, but there was no abnormal cortical tau (subcortical Stages a-c). Cortical involvement (abnormal tau in neurites) was identified first in the transentorhinal region (Stage 1a, 38 cases). Transentorhinal pyramidal cells displayed pretangle material (Stage 1b, 236 cases). Pretangles gradually became argyrophilic neurofibrillary tangles (NFTs) that progressed in parallel with NFT Stages I to VI. Pretangles restricted to subcortical sites were seen chiefly at younger ages. Of the total cases, 1,031 (44.2%) had β-amyloid plaques. The first plaques occurred in the neocortex after the onset of tauopathy in the brainstem. Plaques generally developed in the 40s in 4% of all cases, culminating in their tenth decade (75%). β-amyloid plaques and NFTs were significantly correlated (p < 0.0001). These data suggest that tauopathy associated with sporadic Alzheimer disease may begin earlier than previously thought and possibly in the lower brainstem rather than in the transentorhinal region.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Brain; Child; Child, Preschool; Cohort Studies; Disease Progression; Female; Humans; Infant; Male; Middle Aged; Neurofibrillary Tangles; Neurons; Silver Staining; Statistics, Nonparametric; tau Proteins; Young Adult

Vascular risk factors promote conversion from mild cognitive impairment to Alzheimer disease. - Li, J; Wang, Y J; Zhang, M; Xu, Z Q; Gao, C Y; Fang, C Q; Yan, J C; Zhou, H D (Neurology, 2011)
OBJECTIVE: Growing evidence suggests that vascular risk factors (VRF) contribute to cognitive decline. The aim of this study was to investigate the impact of VRF on the conversion from mild cognitive impairment (MCI) to Alzheimer disease (AD) dementia. METHODS: A total of 837 subjects with MCI were enrolled at baseline and followed up annually for 5 years. The incidence of AD dementia was investigated. A mixed random effects regression model was used to analyze the association between VRF and the progression of MCI assessed with Mini-Mental State Examination and instrumental Activities of Daily Living. Cox proportional hazard models were used to identify the association between VRF and dementia conversion, and to examine whether treatment of VRF can prevent dementia conversion. RESULTS: At the end of the follow-up, 298 subjects converted to AD dementia, while 352 remained MCI. Subjects with VRF had a faster progression in cognition and function relative to subjects without. VRF including hypertension, diabetes, cerebrovascular diseases, and hypercholesterolemia increased the risk of dementia conversion. Those subjects with MCI in whom all VRF were treated had a lower risk of dementia than those who had some VRF treated. Treatment of individual VRF including hypertension, diabetes, and hypercholesterolemia was associated with the reduced risk of AD conversion. CONCLUSION: VRF increased the risk of incident AD dementia. Treatment of VRF was associated with a reduced risk of incident AD dementia. Although our findings are observational, they suggest active intervention for VRF might reduce progression in MCI to AD dementia.
Keywords: Aged; Alzheimer Disease; Cerebrovascular Disorders; Cognition Disorders; Disease Progression; Female; Humans; Incidence; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptides; Regression Analysis; Residence Characteristics; Retrospective Studies; Risk Factors; Statistics, Nonparametric

Alzheimer's Disease Neuroimaging Initiative (ADNI): clinical characterization. - Petersen, R C; Aisen, P S; Beckett, L A; Donohue, M C; Gamst, A C; Harvey, D J; Jack, C R; Jagust, W J; Shaw, L M; Toga, A W; Trojanowski, J Q; Weiner, M W (Neurology, 2010)
BACKGROUND: Neuroimaging measures and chemical biomarkers may be important indices of clinical progression in normal aging and mild cognitive impairment (MCI) and need to be evaluated longitudinally. OBJECTIVE: To characterize cross-sectionally and longitudinally clinical measures in normal controls, subjects with MCI, and subjects with mild Alzheimer disease (AD) to enable the assessment of the utility of neuroimaging and chemical biomarker measures. METHODS: A total of 819 subjects (229 cognitively normal, 398 with MCI, and 192 with AD) were enrolled at baseline and followed for 12 months using standard cognitive and functional measures typical of clinical trials. RESULTS: The subjects with MCI were more memory impaired than the cognitively normal subjects but not as impaired as the subjects with AD. Nonmemory cognitive measures were only minimally impaired in the subjects with MCI. The subjects with MCI progressed to dementia in 12 months at a rate of 16.5% per year. Approximately 50% of the subjects with MCI were on antidementia therapies. There was minimal movement on the Alzheimer's Disease Assessment Scale-Cognitive Subscale for the normal control subjects, slight movement for the subjects with MCI of 1.1, and a modest change for the subjects with AD of 4.3. Baseline CSF measures of Abeta-42 separated the 3 groups as expected and successfully predicted the 12-month change in cognitive measures. CONCLUSION: The Alzheimer's Disease Neuroimaging Initiative has successfully recruited cohorts of cognitively normal subjects, subjects with mild cognitive impairment (MCI), and subjects with Alzheimer disease with anticipated baseline characteristics. The 12-month progression rate of MCI was as predicted, and the CSF measures heralded progression of clinical measures over 12 months.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cross-Sectional Studies; Diagnostic Imaging; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Middle Aged

APOE predicts amyloid-beta but not tau Alzheimer pathology in cognitively normal aging. - Morris, John C; Roe, Catherine M; Xiong, Chengjie; Fagan, Anne M; Goate, Alison M; Holtzman, David M; Mintun, Mark A (Ann Neurol, 2010)
OBJECTIVE: To examine interactions of apolipoprotein E (APOE) genotype with age and with in vivo measures of preclinical Alzheimer disease (AD) in cognitively normal aging. METHODS: Two hundred forty-one cognitively normal individuals, aged 45-88 years, had cerebral amyloid imaging studies with Pittsburgh Compound-B (PIB). Of the 241 individuals, 168 (70%) also had cerebrospinal fluid (CSF) assays of amyloid-beta(42) (Abeta(42)), tau, and phosphorylated tau (ptau(181)). All individuals were genotyped for APOE. RESULTS: The frequency of individuals with elevated mean cortical binding potential (MCBP) for PIB rose in an age-dependent manner from 0% at ages 45-49 years to 30.3% at 80-88 years. Reduced levels of CSF Abeta(42) appeared to begin earlier (18.2% of those aged 45-49 years) and increase with age in higher frequencies (50% at age 80-88 years) than elevations of MCBP. There was a gene dose effect for the APOE4 genotype, with greater MCBP increases and greater reductions in CSF Abeta(42) with increased numbers of APOE4 alleles. Individuals with an APOE2 allele had no increase in MCBP with age and had higher CSF Abeta(42) levels than individuals without an APOE2 allele. There was no APOE4 or APOE2 effect on CSF tau or ptau(181). INTERPRETATION: Increasing cerebral Abeta deposition with age is the pathobiological phenotype of APOE4. The biomarker sequence that detects Abeta deposition may first be lowered CSF Abeta(42), followed by elevated MCBP for PIB. A substantial proportion of cognitively normal individuals have presumptive preclinical AD.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Aniline Compounds; Apolipoprotein E2; Apolipoprotein E4; Apolipoproteins E; Brain; Female; Follow-Up Studies; Genotype; Humans; Longitudinal Studies; Male; Middle Aged; Peptide Fragments; Phosphorylation; Plaque, Amyloid; tau Proteins; Thiazoles